Renforcer l’apprentissage fondamental au Cameroun - Mirabel Yuh, Nain; Pambe, Rigobert; Fotso, Claude; Okwen, Patrick (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

L’apprentissage fondamental au Cameroun - Pambe, Rigobert; Fotso, Claude; Kelese, Mark; Mirabel Yuh, Nain; Nashipu, Sherifa; Okwen, Patrick (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Design-Based Implementation Research Report: Cycle 1. Improving collaboration through Communities of Practice to inform foundational learning policies in Cameroon - Fotso, Claude; Pambe, Rigobert; Mirabel Yuh, Nain (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Exploration de l'écosystème des données et des connaissances de l'apprentissage fondamental en Afrique subsaharienne : Analyse de la situation du Cameroun - Pambe, Rigobert; Mirabel Yuh, Nain; Awah, Noela; Kelese, Mark; Fotso, Claude; Okwen, Patrick (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Policy Brief: Strengthening Foundational Literacy and Numeracy in Cameroon - Yuh, Nain Mirabel; Pambe, Rigobert; Fotso, Claude; Okwen, Patrick (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Sound Foundational Learning Data Ecosystem: The case for increased uses and users of data in Kenya - Gachoki, Charles (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Cross-Country Analysis of Evidence Gap Maps in Malawi, Kenya, and Cameroon - Adam, Taskeen (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Unlocking the Power of Foundational Learning Data in Malawi: Strengthening Data Use and Knowledge Generation for Policy Impact - Twabi, Halima; Kadzamira, Esme; Chiwaya, Paul; Saddick, Louiss (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Unlocking the Power of Education Data: Policy Solutions to Bridge Foundational Learning Gaps in Kenya - Gachoki, Charles; Mutisya, Maurice (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Tackling three urgent questions in the African foundational learning knowledge and data ecosystem - Gachoki, Charles; Lawson, Laté; Mutisya, Maurice; Pambe, Rigobert (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

An Examination of Kenya's Foundational Learning Evidence Base - Nzomo, Christine (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Increasing Foundational Learning Data Access by Policymakers, Focus on Sub-National Level In Kenya - Gachoki, Charles; Arisa, Karen; Maurice, Mutisya (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Evidence Gap Map in the Foundational Learning Space in Sub-Saharan Africa - Lawson, Laté; Iwiire, Rashid (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

DBIR Report: Strengthening the Use of Cohort Tracking Data to Inform Foundational Learning Policies in Malawi - Twabi, Halima; Kadzamira, Esme; Saddick, Louiss; Chiwaya, Paul (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Evidence Gap Map Report: Foundational learning research in Malawi - Saddick, Louiss; Twabi, Halima; Chiwaya, Paul; Kadzamira, Esme (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Evidence Gap Map Report: Foundational Learning in Malawi - Chiwaya, Paul; Saddick, Louiss; Twabi, Halima; Kadzamira, Esme (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Evidence Gap Map Report: Foundational Learning in Kenya - Arisa, Karen; Gachoki, Charles (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

When Data Speaks: Lessons from Cameroon, Kenya, and Malawi on Unlocking Foundational Learning - Mirabel Yuh, Nain; Pambe Miong, Rigobert (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Evidence Gap Map Report: Foundational Learning in Cameroon - Pambe, Rigobert; Fotso, Claude; Kelese, Mark; Mirabel Yuh, Nain; Nashipu, Sherifa-Jamil; Okwen, Patrick (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Exploring the Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa: Guidance Notes - Lawson, Laté; Iwiire, Rashid (Unlocking data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/

Cross-Country Political Economy Analysis: The status of foundational learning data in Cameroon, Kenya, and Malawi - Moustafa, Nariman; Waziri, Nafisa; Gachoki, Charles; Kadzamira, Esme; Pambe, Rigobert (Unlocking Data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Assignment - Ministry of Basic Education (Ministry of Basic Education, Government of Cameroon, 2025)

Exploring the Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa: Guidance Note - Lawson, Laté; Iwiire, Rashid (Unlocking data, 2025)
An output of the Unlocking Data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Dataset Search - African Population and Health Research Centre (2025)

Dataset Search - CEIC (2025)

Exploring the Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa: Kenya’s Situational Analysis - Gachoki, Charles; Arisa, Karen (Unlocking Data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa Kenya’s Situational Analysis - Gachoki, Charles; Arisa, Karen (2025)

Exploring the Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa: Malawi’s Situational Analysis - Kadzamira, Esme; Saddick, Louiss; Twabi, Halima; Chiwaya, Paul (Unlocking Data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence; _related

Exploring the Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa: Cameroon's Situational Analysis - Pambe, Rigobert; Yuh, Nain Mirabel; Awah, Noella; Kelese, Mark; Okwen, Patrick (Unlocking Data, 2025)

Exploring the Foundational Learning Data and Knowledge Ecosystem in Sub-Saharan Africa: Cameroon's Situational Analysis - Pambe, Rigobert; Yuh, Nain Mirabel; Awah, Noella; Kelese, Mark; Okwen, Patrick (Unlocking Data, 2025)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

Open Access | UNESCO - UNESCO (2025)
Building peaceful, democratic and inclusive knowledge societies across the world is at the heart of UNESCO’s mandate. Universal access to information is one of the fundamental conditions to achieve global knowledge societies. This condition is not a reality in all regions of the world.

Dataset Search - World Bank (2025)

Unlocking the Power of Data in Africa’s Education Sector - Gachoki, Charles; Waziri, Nafisa (Unlocking data, 2024)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: _r:AddedByMyEducationEvidence

World Development Report 2024: The middle-income trap - World Bank (Washington, DC: World Bank, 2024)

The Unlocking Data Initiative Communications Strategy 2024 -2026 - Makunga, Jillian; Waziri, Nafisa (Unlocking data, 2024)
An output of the Unlocking data, https://unlockingdata.africa/
Keywords: Internal; _r:AddedByMyEducationEvidence

The Impact of Climate Change on Education: An evidence synthesis focused on classroom experience in hot climates - Haßler, Björn; Eso, Olamide; Villavicencio, Xuzel; Jengo, Eunice; McBurnie, Chris (Open Development & Education, 2024)
Climate change poses a significant challenge to education, particularly in low- and middle-income countries (LMICs) where extreme temperatures and deteriorating environmental conditions disrupt learning. This evidence synthesis examines how climate change affects school infrastructure, indoor environmental quality, and learning outcomes in hot climates. Rising temperatures contribute to heat stress, which impairs cognitive function, reduces student attendance, and exacerbates educational inequalities. Additionally, poor air quality, inadequate ventilation, excessive noise, and variable lighting conditions further hinder student well-being and academic performance. The study reviews adaptation strategies such as retrofitting existing school buildings, modifying roofs, installing shading devices, and using green materials to enhance climate resilience. Case studies from sub-Saharan Africa highlight the effectiveness of passive cooling techniques and improved school design in mitigating climate-related learning disruptions. Despite increasing awareness of climate adaptation in education, challenges persist in policy implementation, funding, and the availability of localised climate data. Findings underscore the urgent need for evidence-based interventions and cross-sector collaboration to improve the sustainability of school environments. By integrating climate resilience into education policies, stakeholders can support inclusive and equitable learning, ensuring that schools remain safe and conducive to learning in the face of escalating climate risks.
Keywords: Coming soon; _r:AddedByMyEducationEvidence

Impact du modèle de financement base sur la performance sur la qualité de l’éducation dans les écoles primaires du département de la Kadeï - Omgba, Jean Joël Léonce (Université de Yaoundé 1, 2024)
Cameroon’s education sector receives a great attention from the State as well as development partners. But it remains greatly affected by funding below the projections from the recent Sector Strategy (2013) and perfectible management of available resources. The report of the Sector Review (2014) highlights funding that is far from the commitments made by the public authorities, and a low budget allocated to basic education. This situation leads to an imbalance both in the distribution of educational resources and in the ability to access quality education. This study highlights the impact of performance-based financing (PBF) on certain indicators of the quality of education. Does the PBF improve certain parameters of the quality of education in the primary schools in the Kadei Division, East region of Cameroon? It is presented not only as a government policy, but also and above all as an innovative tool for the management of organizations, which relies on the purchase of performance. The improvement of the indicators of the quality of education in certain schools in the Kadei Division makes it possible to be interested in two groups of schools with identical characteristics (Pilot schools in which PBF has been implemented, and control schools where it has not been done). The data collection was done using the questionnaire, and the highlighting of the results thanks to the Propensity Score Matching which is an impact evaluation technique. For the sake of efficiency in data collection, objective-oriented sampling was associated with quota sampling, drawn from a population made up of 248 schools including 218 public schools, 17 private schools, 13 municipal schools. But also 52 nursery schools including 45 public and 7 private. The results obtained show that the PBF implemented in 2012 in the Kadei Division has a positive and significant impact of 10% on student enrolment, school dropout, program coverage, possession of textbooks, school infrastructure, on girl/boy parity, and finally on the school results of pupils. However, these same indicators in the control schools did not change during this period. This evidence reflects the influence of this management approach in schools, even if some aspects of its operationalization remain perfectible.

Kitambaa : A Convivial Future-Oriented Framework for Kinangop's Learning Hub. - Kuhn, Caroline; Warui, Mary; Kimani, Dominic (Kitambaa : A Convivial Future-Oriented Framework for Kinangop's Learning Hub., 2024)
The aim of this paper, and more generally, our project "Impact from the ground" (a multi-stage ongoing project), is to reimagine education so that it transcends the walls and harsh constraints of a "universal one size fits all" education. To achieve this, we propose a framework that will inform the design of a participatory approach to co-create a learning hub (an informal lifelong learning opportunity) with and within the community. To weave this framework, we explore the current landscape of education, looking at the challenges that youth from rural settings face to complete their studies in urban universities, and the difficulties they experience when looking for jobs after having done so. We briefly explain our research project and contextualize it in Kinangop, a small region in the Nyandarua County in Kenya, where we explored the enablers and constraints people face to engage in social innovation. We proceed to imagine an alternative education that is local and organic, with different principles and theories weaved into a, kitambaa in Swahili that serves as the ground for an education intervention that is meaningful, binding, and bonding for the community members. In so doing, we aim to center matters of knowledge production as multi-epistemic conversations, situating those at the margins of epistemic divisions at the center of productive and creative debates.
Keywords: Alternative education; Kenya; Nonformal education; Participatory design; Rural youth; Social innovation; Urban studies; Urban youth

UNICEF Cameroon Humanitarian Situation Report No. 4 (End of Year) January to December 2023 - Cameroon - UNICEF (2024)
Situation Report in English on Cameroon and 3 other countries about Contributions, Coordination, Epidemic, Flood and more; published on 20 Feb 2024 by UNICEF

Classroom practices in primary schools’ mathematics teaching supported by the Interactive Mathematics Software for Rwanda. - Uwineza, Innocente; Uworwabayeho, Alphonse; Kenya Yokoyama (Classroom practices in primary schools’ mathematics teaching supported by the Interactive Mathematics Software for Rwanda., 2024)
Over recent decades, the integration of technological resources in education increased growingly. However, studies about the assessment of information and communications technology integration in primary school mathematics activities remained few. This research intended to comparatively examine the aspects of classroom practices observed during the implementation of the Interactive Mathematics (IM) Software in primary schools in Rwanda. Designed as quasi-experimental, it involved the experimental groups from Primary-2, Primary-3, Primary-4, and Primary-5 and analyzed aspects of school statuses, the school years, and the educational cycles. Data collected using Likert-scale measurements from 63 classroom observations were analyzed using Microsoft Excel and a two-sample t-test analysis was conducted to determine if the significance of mean differences. The findings revealed no significant difference between lower and upper primary based on a p-value of 0.829368908 (p-value>.05) and between the 2019 and 2020 teaching periods (considering the same teacher) based on the p-value=0.324542 (p-value>.05). However, the findings revealed that private and public schools’ mean differences were significant based on the calculated p-value equal to 0.007144 (p-value<.01). The study made various recommendations towards using IM software to promote quality mathematics education in primary schools in Rwanda and pre-service teacher training to boost the initiation process of their technology-enhanced pedagogy knowledge to teach mathematics.
Keywords: Educational technology; Information & communication technologies; Mathematics education; Mathematics software; Primary school curriculum; Rwanda

Lower and upper primary learners' difference in performance and conceptual understanding: Support of interactive mathematics software for Rwanda. - Uwineza, Innocente; Uworwabayeho, Alphonse; Yokoyama, Kenya (Lower and upper primary learners' difference in performance and conceptual understanding: Support of interactive mathematics software for Rwanda., 2024)
The use of technology to enhance classroom practices draws attention from numerous educational systems and scientific studies. Rwanda's educational system prioritized ICT-integrated instructions in primary schools in order to enhance the provision of high-quality education from early years. Therefore, this study was undertaken at both public and private schools in Kigali City. It sought to find out the impact of Interactive Mathematics software (IM) on conceptual understanding and performance in lower and upper elementary mathematics learners. Designed as quasi-experimental, it involved 253 learners from Primary 2 and Primary 4, conveniently assigned to controls and experimental groups. A sample of learners' test works was used to collect data before and after the treatment. Learners' test scores were collected and analyzed using Excel and SPSS v.23 software. The results showed that P2 and P4 treatment groups' mean scores differed significantly from each other. The effect was more noticeable at both levels in public schools than in private ones. Based on the significance of mean difference and performance on an item, there was no discernible difference in the impact of Interactive Mathematics aided teaching on lower and upper primary mathematics performance. The study's conclusion included some recommendations for Rwanda Basic Education Board and called for additional, more thorough research on the qualitative facets of IM-supported teaching.
Keywords: Classroom environment; Computer and Computer Peripheral Equipment and Software Merchant Wholesalers; Computer and software stores; Computer software; Computer, computer peripheral and pre-packaged software merchant wholesalers; Information & communication technologies; Mathematics education; Rwanda; Software publishers (except video game publishers)

Digital Skills and the Use of Digital Platforms in the Informal Sector: A Case Study among Jua Kali Artisans in Nairobi in Kenya - Christopher Momanyi; Andrew Rasugu Riechi; Ibrahim Khatete (Digital Skills and the Use of Digital Platforms in the Informal Sector: A Case Study among Jua Kali Artisans in Nairobi in Kenya, 2024)
Context: For many businesses, one of the key indicators in their management is the adaptation of Information Technology in their operations. In Kenya, there has been a phenomenal growth in access to mobile phones, by June 2023, over 66 million mobile phones were connected to various telecommunication operators of which 58.3% were smart phones constituting 67.1% of internet connections. There are many digital technologies which can be adapted to facilitate the processing, dissemination, and access of information. The modern world has become competitive due to the uptake of Information Technology as one of the main business management skill, with the availability of smart phones and many applications that are easily available and easy to use. One of the main beneficiaries of Information Communication Technologies (ICTs) is the Jua Kali artisans who are a key player in the Kenyan economy. Entrepreneurial competencies help the growth of businesses along the dimension of innovation. Kenya intends to entrench the use of Information Technology for public service delivery, business, skills, and innovation. The Jua Kali sector cannot be ignored, it contributes more than 80% of the total employment in Kenya. Approach: This research was carried out in the Eastlands of Nairobi, Kenya. Data were collected using a questionnaire, an interview and observation schedule. The study used an interview schedule to collect data from Jua Kali artisans carrying out their artisan businesses in the Eastlands of Nairobi and a questionnaire survey to collect data from a sample of identified Nairobi residents who had engaged an artisan to work for them six months prior to the research. Findings: The research established that most Jua Kali artisans acquired their skills in the Jua Kali sector by apprenticeship (86.3%) while a small percentage (12.7%) trained in Technical Vocational Education Training (TVET) institutions while a further one percent were trained by their former employers. Most of the artisans had attained the basic formal education qualifications i.e. primary education (27.9%) and secondary education (47.6%). The Chi-square (?²) test was used to test the relationship between use of the basic social media digital platforms in business management and the formal education attained by artisans owning artisan businesses. Conclusion: At 0.05 level of significance (a) the research established that there is a significant relationship between the adaptation of digital platforms in business management and the formal education attained by the artisans.
Keywords: Apprenticeships; Business Skills; Difficulty Level; Digital Literacy; Education Work Relationship; Educational Background; Entrepreneurship; Foreign Countries; Informal Education; Kenya; Relevance (Education); Skill Development; Skilled Workers; Small Businesses; Technical Education; Unskilled Workers; Vocational Education

Lower and Upper Primary Learners' Difference in Performance and Conceptual Understanding: Support of Interactive Mathematics Software for Rwanda - Innocente Uwineza; Alphonse Uworwabayeho; Kenya Yokoyama (Lower and Upper Primary Learners' Difference in Performance and Conceptual Understanding: Support of Interactive Mathematics Software for Rwanda, 2024)
The use of technology to enhance classroom practices draws attention from numerous educational systems and scientific studies. Rwanda's educational system prioritized ICT-integrated instructions in primary schools in order to enhance the provision of high-quality education from early years. Therefore, this study was undertaken at both public and private schools in Kigali City. It sought to find out the impact of Interactive Mathematics software (IM) on conceptual understanding and performance in lower and upper elementary mathematics learners. Designed as quasi-experimental, it involved 253 learners from Primary 2 and Primary 4, conveniently assigned to controls and experimental groups. A sample of learners' test works was used to collect data before and after the treatment. Learners' test scores were collected and analyzed using Excel and SPSS v.23 software. The results showed that P2 and P4 treatment groups' mean scores differed significantly from each other. The effect was more noticeable at both levels in public schools than in private ones. Based on the significance of mean difference and performance on an item, there was no discernible difference in the impact of Interactive Mathematics aided teaching on lower and upper primary mathematics performance. The study's conclusion included some recommendations for Rwanda Basic Education Board and called for additional, more thorough research on the qualitative facets of IM-supported teaching.
Keywords: Academic Achievement; Computer Software; Concept Formation; Elementary School Mathematics; Elementary School Students; Foreign Countries; Mathematical Concepts; Mathematics Education; Mathematics Instruction; Private Schools; Public Schools; Rwanda; Technology Uses in Education

The Impact of Pre-Primary Education on Primary Student Achievement: Evidence from SACMEQ III - Kyoko Taniguchi (The Impact of Pre-Primary Education on Primary Student Achievement: Evidence from SACMEQ III, 2024)
Previous studies have paid considerable attention to the impact on a child's primary education of attending pre-primary school. Researchers have asserted that early educational intervention can compensate for the effects of poverty and inadequate learning environments on child development and school success. This study analyzes the relationship between pre-primary education and student reading and mathematics achievement in the sixth grade, focusing on disadvantaged children, in countries that participated in the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ) III project. The results show that the achievement of children who attended pre-primary education is higher than that of those who did not. The achievement of children who have many home resources for learning is better than that of children who have a few such resources. In almost all countries, disadvantaged children's achievement is increased when they attend pre-primary education. However, the contribution of pre-primary education to ameliorating social inequalities is different in the various contexts of different countries. These findings contribute to the discussion on the importance of early childhood care and education, especially in sub-Saharan Africa.
Keywords: Africa; Botswana; Cultural Differences; Disadvantaged Youth; Elementary Education; Foreign Countries; Grade 6; Kenya; Lesotho; Malawi; Mathematics Achievement; Mauritius; Mozambique; Namibia; Preschool Education; Program Effectiveness; Reading Achievement; Resources; Seychelles; Social Bias; South Africa; Swaziland; Tanzania; Uganda; Zambia; Zimbabwe

Digital Skills and the Use of Digital Platforms in the Informal Sector: A Case Study Among Jua Kali Artisans in Nairobi in Kenya. - Momanyi, Christopher; Riechi, Andrew Rasugu; Khatete, Ibrahim (Digital Skills and the Use of Digital Platforms in the Informal Sector: A Case Study Among Jua Kali Artisans in Nairobi in Kenya., 2024)
Context: For many businesses, one of the key indicators in their management is the adaptation of Information Technology in their operations. In Kenya, there has been a phenomenal growth in access to mobile phones, by June 2023, over 66 million mobile phones were connected to various telecommunication operators of which 58.3% were smart phones constituting 67.1% of internet connections. There are many digital technologies which can be adapted to facilitate the processing, dissemination, and access of information. The modern world has become competitive due to the uptake of Information Technology as one of the main business management skill, with the availability of smart phones and many applications that are easily available and easy to use. One of the main beneficiaries of Information Communication Technologies (ICTs) is the Jua Kali artisans who are a key player in the Kenyan economy. Entrepreneurial competencies help the growth of businesses along the dimension of innovation. Kenya intends to entrench the use of Information Technology for public service delivery, business, skills, and innovation. The Jua Kali sector cannot be ignored, it contributes more than 80% of the total employment in Kenya. Approach: This research was carried out in the Eastlands of Nairobi, Kenya. Data were collected using a questionnaire, an interview and observation schedule. The study used an interview schedule to collect data from Jua Kali artisans carrying out their artisan businesses in the Eastlands of Nairobi and a questionnaire survey to collect data from a sample of identified Nairobi residents who had engaged an artisan to work for them six months prior to the research. Findings: The research established that most Jua Kali artisans acquired their skills in the Jua Kali sector by apprenticeship (86.3%) while a small percentage (12.7%) trained in Technical Vocational Education Training (TVET) institutions while a further one percent were trained by their former employers. Most of the artisans had attained the basic formal education qualifications i.e. primary education (27.9%) and secondary education (47.6%). The Chi-square (χ²) test was used to test the relationship between use of the basic social media digital platforms in business management and the formal education attained by artisans owning artisan businesses. Conclusion: At 0.05 level of significance (a) the research established that there is a significant relationship between the adaptation of digital platforms in business management and the formal education attained by the artisans.
Keywords: Digital literacy; Educational innovations; Educational outcomes; Mobile learning; Teaching methods

Mapping Foundational Literacy and Numeracy Research in Sub-Saharan Africa - Acquah, Stephen; Lawson, Laté; Asare, Samuel; Essah, Pauline (Education Sub Saharan Africa (ESSA) and REAL Centre, University of Cambridge, 2024)

What matters for learning in Malawi? Evidence from the Malawi longitudinal school survey - Asim, Salman; Gera, Ravinder (World Bank, 2024)

Foundational learning: Unearthing key issues and redressal - Chandra, Reetu (International Journal of Education, 2024)
The National Education Policy 2020 in India recognizes the importance of investing in the early years which is the most important indicator of productive and efficient human capital a country must ensure. The policy thus, obligates strong investment in foundational learning with a special focus on the attainment of foundational literacy and numeracy skills among children in their early years. For this, policy lays a roadmap for academic and systemic reforms in mission mode for better planning, designing, and implementation of interventions for foundational learning. Accordingly, the NIPUN Bharat Mission was launched in 2021 with targets to be achieved in five years, i.e. by 2026-27. This paper is a narrative review of the literature with problem-solving approach to spot key issues in foundational learning in India and the remediation being followed. Review suggests issues and mitigation strategies in three areas viz, achieving access to the conducive learning environment, strengthening educational and developmental aspect of learning interventions and bringing systemic reforms as wells as developing convergence mechanism to build the robust administrative structure. Findings and strategies provided in this paper would help stakeholders identify issues beforehand and take action in, timely. This learning would also be useful to the countries having similar geographical, educational, and social constraints who want to or are in the process of designing or implementing such interventions. Keywords: foundational learning, literacy, numeracy, reading, writing, policy

Mapping Foundational Literacy and Numeracy Research in Sub-Saharan Africa - Diallo, Thierno; Lawson, Late; Asare, Samuel; Essah, Pauline (2024)

From Commitments to Action: Findings from the Foundational Learning Tracker 2024 - Hempel Foundation (UNICEF, 2024)

Mapping Foundational Literacy and Numeracy Research in Four Sub-Saharan African Countries: Lessons from country-level searches - Lawson, Laté; Acquah, S; Diallo, T; Asare, S; Essah, P (2024)

The 2024 Education Sector Performance Report - Ministry of Education (Republic of Malawi, 2024)

Life-changing foundational learning through edtech in sub-Saharan africa - Rabana, Rapelang (Childhood Education, 2024)

The County Allocation of Revenue Bill, 2024 - Republic of Kenya (2024)

Fourth Medium Term Plan 2023–2027 - Republic of Kenya (2024)

National Education Sector Strategic Plan 2023-2027 - Republic of Kenya (2024)

Beyond reading and numeracy: Examining holistic educational implications of Pakistan’s foundational learning policy - Safdar, Samina; Waqar, Yasira; Muhammad, Yaar (Journal of Social Research Development, 2024)
This paper analyses Pakistan Federal Foundational Learning Policy (FFLP) 2024 in light of holistic education. While enhancing the literacy abilities of children is a notable objective of this policy, this study examines policy in terms of its potential for the student’s education as a whole. In this paper, critical discourse analysis was employed by Mullet, focusing on language, the text structure, and the suggested measures of implementation of policy. This study shows that though FFLP 2024 ensures that gaps in foundational learning are filled, it might downplay other elements necessary for early childhood, namely socio-emotional development, creativity, and cultural competence. This policy gap may impose limitations on school’s curriculum and teaching strategies as it centers on quantifiable results & standardized tests. The findings drawn from the analysis of the policy have questioned its suitability for different regions and its effect on the teachers’ professionals’ autonomy. The study proposed that a balanced approach that incorporates basic skills and general goals is needed for inclusive student development. The study provides valuable suggestions for a broader strategy towards the foundational learning.

Building trust: A systematic review of the drivers and barriers of agricultural data sharing - Sullivan, Clare S.; Gemtou, Marilena; Anastasiou, Evangelos; Fountas, Spyros (Smart Agricultural Technology, 2024)
Smart farming practices offer decision-making support as farmers navigate economic, social, and environmental challenges. However, smart farming adoption remains low in many farming contexts due to the perceived cost and skills required, and hesitancies about sharing agricultural data. Numerous studies have reviewed the factors that influence smart farming adoption within different agricultural scenarios, but to the best our knowledge, none have specifically reviewed the motivators and obstacles of agri-data sharing within smart farming. The objective of this research was to identify and classify the most prominent drivers and barriers for sharing agridata across stakeholders, by examining the existing literature. A Systematic Literature Review was conducted using the PRISMA 2020 methodology. The query initially identified 491 papers from Scopus and Web of Science, and after screening the final number of papers for assessment was 59. Factors affecting the willingness and capability to engage in agricultural data sharing were categorised in socio-economic, systemic, technical, and legal categories. The most prominent drivers for agri-data sharing were systemic and technical, which were discussed in 58 % and 57 % of the papers, respectively. Technical factors were the most prevalent barriers, discussed in 68 % of the literature. Perceived knowledge gain leading to improved decision-making, collabo ration across the agri-value chain, improved technologies, and clarity around data sovereignty were key enablers identified for sharing data. Lack of knowledge about the purpose and benefit of sharing data, mistrust of “who will benefit from my data”, data privacy and security, and lack clarity on data ownership and rights of use were the prominent concerns. The findings from this paper will help inform on-the-ground social science research across the EU focused on feasible options for promoting the benefits of agri-data sharing.

Kenya: Education Country Brief | International Institute for Capacity Building in Africa - UNESCO (2024)
January 2024

OpenEMIS. Cloud Hosting vs. Self Hosting - UNESCO (2024)

Cameroon Humanitarian Situation Report, End of Year 2024 - UNICEF (2024)

Mapping early childhood development research outputs in sub-Saharan Africa Cross-country mapping report - Williams, E.M; Rose, P (2024)

Exploring the diverse definitions of ‘evidence’: A scoping review - Yu, Xuan; Wu, Shouyuan; Sun, Yajia; Wang, Ping; Wang, Ling; Su, Renfeng; Zhao, Junxian; Fadlallah, Racha; Boeira, Laura; Oliver, Sandy; Abraha, Yoseph G; Sewankambo, Nelson K; et al. (BMJ Evidence-Based Medicine, 2024)
Objectives To systematically collect and analyse diverse definitions of ‘evidence’ in both health and social sciences, and help users to correctly use the term ‘evidence’ and rethink what is the definition of ‘evidence’ in scientific research. Design Scoping review. Methods Definitions of evidence in the health sciences and social sciences were included. We have excluded the definition of evidence applied in the legal field, abstracts without full text, documents not published in either Chinese or English and so on. We established a multidisciplinary working group and systematically searched five electronic databases including Medline, Web of Science, EBSCO, the Chinese Social Sciences Citation Index and the Chinese Science Citation Database from their inception to 26 February 2022. We also searched websites and reviewed the reference lists of the identified studies. Six reviewers working in pairs, independently, selected studies according to the inclusion and exclusion criteria, and extracted information. Any differences were discussed in pairs, and if there was disagreement, it was resolved via discussion or with the help of a third reviewer. Reviewers extracted document characteristics, the original content for the definitions of ‘evidence’, assessed definitions as either intensional or extensional, and any citations for the given definition. Results Forty-nine documents were finally included after screening, and 68 definitions were obtained. After excluding duplicates, a total of 54 different definitions of ‘evidence’ were identified. There were 42 intensional definitions and 12 extensional definitions. The top three definiens were ‘information’, ‘fact’ and ‘research/study’. The definition of ‘evidence’ differed between health and social sciences. The term ‘research’ appeared most frequently in the definitions. Conclusions The definition of ‘evidence’ has gradually attracted the attention of many scholars and decision-makers in health and social sciences. Nevertheless, there is no widely recognised and accepted definition in scientific research. Given the wide use of the term, we need to think about whether, or under what circumstances, a standardised, clear, meaningful and widely applicable definition of ‘evidence’ might be helpful.

Scaffolding self-regulated learning in student-generated questioning using mobile phones. - Song, Donggil; Glazewski, Krista (Scaffolding self-regulated learning in student-generated questioning using mobile phones., 2023)
Focusing on the sustainability and affordability when using information technology, the mechanism of student-generated questioning (SGQ) and scaffolding for SGQ in reading comprehension tasks were explored within the self-regulated learning framework in this study. We employed a mixed methods design to examine the effects of scaffolding in an SGQ activity on (a) test scores of reading comprehension, (b) the quality of student-generated questions, and (c) participants' experience. Seventy-four 7th graders from a primary school in Kenya participated in this study. They were assigned to one of three groups: (a) SGQ with Scaffolding, (b) SGQ without Scaffolding, and (c) Direct Instruction with Teacher Questioning. As an affordable and sustainable technology solution, low-cost text message-capable mobile phones were employed to support SGQ. Data were collected from the quizzes and posttest of reading comprehension, student surveys, selected teacher/student interviews, and class observation. Statistical analyses showed that SGQ with scaffolding had a positive effect on learning outcomes and the quality of student-generated questions. The analysis of quantitative and qualitative data yielded that SGQ improves reading comprehension levels through the engaged reading with the support of metacognitive guidance.
Keywords: Administration of General Economic Programs; Cell phones; Computer literacy; Digital learning; Electronic components, navigational and communications equipment and supplies merchant wholesalers; Electronics Stores; Learning; Radio and Television Broadcasting and Wireless Communications Equipment Manufacturing; Sustainable development; Wireless Telecommunications Carriers (except Satellite)

Scaffolding Self-Regulated Learning in Student-Generated Questioning Using Mobile Phones - Song, Donggil; Glazewski, Krista (Scaffolding Self-Regulated Learning in Student-Generated Questioning Using Mobile Phones, 2023)
Focusing on the sustainability and affordability when using information technology, the mechanism of student-generated questioning (SGQ) and scaffolding for SGQ in reading comprehension tasks were explored within the self-regulated learning framework in this study. We employed a mixed methods design to examine the effects of scaffolding in an SGQ activity on (a) test scores of reading comprehension, (b) the quality of student-generated questions, and (c) participants' experience. Seventy-four 7th graders from a primary school in Kenya participated in this study. They were assigned to one of three groups: (a) SGQ with Scaffolding, (b) SGQ without Scaffolding, and (c) Direct Instruction with Teacher Questioning. As an affordable and sustainable technology solution, low-cost text message-capable mobile phones were employed to support SGQ. Data were collected from the quizzes and posttest of reading comprehension, student surveys, selected teacher/student interviews, and class observation. Statistical analyses showed that SGQ with scaffolding had a positive effect on learning outcomes and the quality of student-generated questions. The analysis of quantitative and qualitative data yielded that SGQ improves reading comprehension levels through the engaged reading with the support of metacognitive guidance.
Keywords: Control Groups; Direct Instruction; Elementary School Students; Foreign Countries; Grade 7; Handheld Devices; Independent Study; Kenya; Learning Activities; Metacognition; Outcomes of Education; Questioning Techniques; Reading Comprehension; Reading Improvement; Scaffolding (Teaching Technique); Scores; Student Experience; Student Participation; Teachers; Telecommunications

Global Education Monitoring Report 2023. Technology in Education: A Tool on Whose Terms? - UNESCO (2023)
Analysis in Arabic on World about Education, Gender, Epidemic and more; published on 27 Jul 2023 by UNESCO

Global Education Monitoring Report 2023: Technology in education: A tool on whose terms? - UNESCO (GEM Report UNESCO, 2023)

Pedagogies for critical thinking at universities in Kenya, Ghana and Botswana: the importance of a collective 'teaching culture'. - Schendel, Rebecca; McCowan, Tristan; Rolleston, Caine; Adu-Yeboah, Christine; Omingo, Mary; Tabulawa, Richard (Pedagogies for critical thinking at universities in Kenya, Ghana and Botswana: the importance of a collective 'teaching culture'., 2023)
While critical thinking is widely regarded as a key outcome of higher education, research has shown that in practice it is only developed when certain conditions are in place, relating to the pedagogical approach, the nature of the curriculum and the level of challenge, amongst other factors. This article reports on findings from a four-year mixed methods study in Botswana, Ghana and Kenya, aiming to investigate the factors underpinning the successful development of critical thinking amongst undergraduate students. A two-stage critical thinking assessment was conducted with students in 15 sites, showing that only some of the institutions were ensuring significant gains in students' critical thinking, even when endorsing learner-centred methods. The study points to the central importance of teaching orientations amongst lecturers, involving a deep shift in approaches to knowledge, and a facilitation rather than a transmission approach.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Critical thinking; Education; Educational Support Services; Ghana; Higher education; Undergraduates

Grade-3 Learners' Performance and Conceptual Understanding Development in Technology-Enhanced Teaching With Interactive Mathematics Software. - Uwineza, Innocente; Uworwabayeho, Alphonse; Kenya Yokoyama (Grade-3 Learners' Performance and Conceptual Understanding Development in Technology-Enhanced Teaching With Interactive Mathematics Software., 2023)
This study presented the effect of interactive mathematics (IM) software assisted-teaching on primary three learners' conceptual understanding and performance. The cognitive theory of multimedia learning (CTML) supported the quasi-experimental design of this study drawing on IM software features that fit a multimedia tool for effective learning. This study used a sample of 138 lower primary learners. Learners' test scores and examples of their work provided data to be analyzed. Learners' conceptual understanding was measured using the percentage of learners who performed a particular item and analyzed using sample learners' work while the overall performance was measured using the mean class scores. From the data analysis, IM-assisted teaching influenced conceptual understanding and performance based on a .05 p-value, the effect size of significance, and learning gains. The analysis of learners' workings revealed different errors in addition, subtraction, division, and multiplication, which were remarkably reduced in the post-test by IM-supported teaching. This evidenced conceptual understanding development by IMsupported teaching. The study suggested the integration of IM in the Rwandan Competence-Based curriculum and its use as an instructional tool in teaching and learning mathematics at the primary level. Besides, it was recommended that Rwanda Education Board support teachers in developing basic computer skills to effectively create and monitor a multimedia learning environment for effective learning. Furthermore, further similar research would improve the literature about interactive technologies in supporting quality mathematics delivery and outcomes.
Keywords: Citizenship; Computer and Computer Peripheral Equipment and Software Merchant Wholesalers; Computer and software stores; Computer software; Computer, computer peripheral and pre-packaged software merchant wholesalers; Mathematics; Service learning; Software publishers (except video game publishers); Volunteers

GPE endorses Commitment to Action on Foundational Learning - Global Partnership for Education (2023)

Examining Classroom Supports Systems and Learning Outcomes Among Learners with Autism Spectrum Disorders in Primary Schools. - Orao, Remi Odero; Aloka, Peter J. O. (Examining Classroom Supports Systems and Learning Outcomes Among Learners with Autism Spectrum Disorders in Primary Schools., 2023)
This study examined the relationship between classroom supports systems and learning outcomes among autistic learners in Kenya. The correlational research design was adopted. A sample size of 200 teachers was obtained from the study population using proportionate sampling technique. Classroom learning Supports Systems Questionnaire and Learning Outcomes Assessment scales were used to collect data. The reliability of the questionnaires was ensured by the Cronbach's alpha and an alpha of above 0.70 was reported for all the scales. Inferential statistics such as the Pearson Correlation Coefficient and Regression analysis were used to analyze data. The results indicate that the Regression model output, explains 35.6 percent of the variance in learning outcomes among learners with Autism spectrum disorders. The Individualized Education Program had the highest influence (Beta=.389) on learning outcomes, while use of instructional supports made the least contribution (Beta=.006) to explain the variability. The study recommends that the Kenyan Ministry of Education should post speech and language therapists to schools for learners with autism to help them improve and overcome the communication difficulties they face.
Keywords: Academic support programs; Autism spectrum disorders; Educational Support Services; Educational outcomes; Primary schools; Regression analysis

Folktales as indigenous pedagogic tools for educating school children: A mixed methods study among the Nso of Cameroon - Wiysahnyuy, Lilian F.; Valentine, Ngalim Banfegha (Frontiers in Psychology, 2023)
In many low and middle-income countries, schools are sites of cross-cultural contact and conflict due to a mismatch between the learning priorities and pedagogical practices used in children’s homes and those they encounter in school. The alien nature of school as a learning context contributes to several negative outcomes. It hampers children’s acquisition of academic skills, limits their parents’ engagement in their schooling and prevents schools from benefiting from the learning resources and pedagogical practices available in the local context. To prevent this, many low and middle-income countries are considering the feasibility of incorporating local cultural activities into the school curriculum as a means of bridging the cultural divide between schools and the communities they serve. This research aims to inform these decisions through a case study of stakeholders’ views towards the integration of a specific indigenous pedagogic tool, folktales into school settings in Cameroon, Central Africa. Qualitative data were gathered from 20 teachers and 15 parents in Kumbo, the capital of the Nso Kingdom where traditional child-rearing customs remain strong. A thematic analysis of the data revealed that most parents told their children folktales as one component in an indigenous participatory pedagogy designed to stimulates some cognitive skills and enhance moral development among children. Most teachers and parents believed that there were many potential importance of integrating folktales into schools as a traditional pedagogy for schoolteachers’ professional practice. All teachers reported that they used folktales during lessons and/or pupils’ free time. Like parents, teachers both narrated folktales and invited children to narrate them though some parents indicated that it was not necessary. This pattern of findings supports the conclusion that folktales provide invaluable pedagogic values and prospects for schools and formal education in general. Caution should be exercised in any attempt to generalize these findings because the sample and the geographical site were limited. However, this study suggests that folktales may be a readily available indigenous pedagogic tool that has both a high level of acceptability among teachers and parents and can be effective in bridging the cultural divide between schools and communities in many low and middle-income countries.
Keywords: Folktales; Indigenous pedagogy; Parents; culture; elementary school; informal learning; teachers

Navigating Secondary School: What Cushioned Adolescents in an Education Intervention in Urban Kenya - Abuya, Benta; Muhia, Nelson (Navigating Secondary School: What Cushioned Adolescents in an Education Intervention in Urban Kenya, 2023)
This paper explains sustained effects and what worked for students in the Advancing Learning Outcomes and Transformational (ALOT Change III) program. Data comes from qualitative narratives from the baseline survey of the program collected by the African Population and Health Research Center (APHRC) between December 4, 2019, and January 31, 2020, using focus group discussions (FGDs) and dialogues. The analysis followed the Miles and Huberman (1994) framework to make comparisons and contrasts. Results showed that students transferred skills such as self-confidence from primary to secondary schools, enabling the adolescents to speak up and engage. This showed an effective implementation uptake. The implication of the study points to the efficacy of community-based programs in impacting behavior of adolescents beyond primary school.
Keywords: Academic Achievement; Barriers; Bullying; Community Programs; Comparative Analysis; Digital Literacy; Elementary School Students; Enrollment; Foreign Countries; Friendship; Homework; Intervention; Kenya; Parent Attitudes; Peer Influence; Program Effectiveness; Secondary School Students; Self Esteem; Socioeconomic Status; Student Attitudes; Sustainability; Transfer of Training; Transformative Learning; Urban Areas; Well Being

Navigating Secondary School: What Cushioned Adolescents in an Education Intervention in Urban Kenya. - Abuya, Benta; Muhia, Nelson (Navigating Secondary School: What Cushioned Adolescents in an Education Intervention in Urban Kenya., 2023)
This paper explains sustained effects and what worked for students in the Advancing Learning Outcomes and Transformational (ALOT Change III) program. Data comes from qualitative narratives from the baseline survey of the program collected by the African Population and Health Research Center (APHRC) between December 4, 2019, and January 31, 2020, using focus group discussions (FGDs) and dialogues. The analysis followed the Miles and Huberman (1994) framework to make comparisons and contrasts. Results showed that students transferred skills such as self-confidence from primary to secondary schools, enabling the adolescents to speak up and engage. This showed an effective implementation uptake. The implication of the study points to the efficacy of community-based programs in impacting behavior of adolescents beyond primary school.
Keywords: Africans; Kenya; Secondary schools; Self-confidence; Teenagers; Transfer of students; Urban education

Using Consensus and Cooperative Reflective Journal Writing Instructional Strategies to Enhance Students' Achievement in Biology. - Adejimi, Saheed Ayodeji; Shivoga, William Aino; Nzabalirwa, Wenceslas (Using Consensus and Cooperative Reflective Journal Writing Instructional Strategies to Enhance Students' Achievement in Biology., 2023)
Teachers are supposed to adapt their teachinglearning process based on classroom interaction to suit the learning conditions of learners to produce a complete learning community that is intellectually and behaviourally sound. This can only be achieved in a serene, friendly, and collaborative environment. This study determined the effects of consensus and cooperative reflective journal writing instructional strategies on students' achievement in biology, with gender moderating at two levels. A pretest-posttest control group quasi-experimental design with a 3X2 factorial matrix was adopted. The treatment lasted for six weeks. The sample consisted of 305 senior secondary school II students in Ibadan metropolis, Oyo state, Nigeria. The instrument for data collection was the Students' Biology Achievement Test (SBAT). The generated data were analysed using a two-way analysis of variance (ANCOVA) and the Bonferroni post-hoc test. The results of the study revealed that consensus and cooperative reflective journal writing strategies improved students' achievement in biology. The results also revealed that gender affected students' achievement in biology. Treatment and gender did not affect students' achievement in biology. The study concluded that the strategies adopted enhance students' achievement in biology and, therefore, recommended to be adopted in biology classrooms.
Keywords: Academic achievement; Classroom environment; Educators; Elementary and Secondary Schools; Group work in education; Intellectual development; Secondary education; Students; Teacher-student relationships

Brochure, Spotlight report on basic education completion and foundational learning in Africa: Born to learn - Global Education Monitoring Report Team; Association for the Development of Education in Africa; African Union (UNESCO, 2023)

Perceptions of using interactive mathematics software among Rwandan primary school teachers. - Uwineza, Innocente; Uworwabayeho, Alphonse; Yokoyama, Kenya (Perceptions of using interactive mathematics software among Rwandan primary school teachers., 2023)
This study aimed to explore primary school teachers' perception of using Interactive Mathematics (IM) software in teaching and learning activities using qualitative interpretive phenomenology. It involved seven teachers non-randomly selected from the lower and upper primary with different gender and teaching experiences who participated in a semi-structured interview which took around 30 minutes on average for each interviewed teacher after the experimentation period. Data were collected by recording and writing in a notebook some key information using both English and Kinyarwanda languages to capture the maximum perception of teachers. Translation of Kinyarwanda answers to English and transcription followed by respecting the main interview questions. Three themes emerged: (1) the disadvantages of traditional teaching and learning of mathematics, (2) the benefits of aspects of ICT and interactive mathematics software, and (3) the challenges of using ICT and interactive mathematics software. Based on the findings, suggestions, and recommendations about the effective utilization of IM in classroom activities, as well as its integration into the curriculum, were discussed.
Keywords: Classroom activities; Genocide; Mathematics software; Primary school teachers

Perceptions of Using Interactive Mathematics Software among Rwandan Primary School Teachers - Uwineza, Innocente; Uworwabayeho, Alphonse; Yokoyama, Kenya (Perceptions of Using Interactive Mathematics Software among Rwandan Primary School Teachers, 2023)
This study aimed to explore primary school teachers' perception of using Interactive Mathematics (IM) software in teaching and learning activities using qualitative interpretive phenomenology. It involved seven teachers non-randomly selected from the lower and upper primary with different gender and teaching experiences who participated in a semi-structured interview which took around 30 minutes on average for each interviewed teacher after the experimentation period. Data were collected by recording and writing in a notebook some key information using both English and Kinyarwanda languages to capture the maximum perception of teachers. Translation of Kinyarwanda answers to English and transcription followed by respecting the main interview questions. Three themes emerged: (1) the disadvantages of traditional teaching and learning of mathematics, (2) the benefits of aspects of ICT and interactive mathematics software, and (3) the challenges of using ICT and interactive mathematics software. Based on the findings, suggestions, and recommendations about the effective utilization of IM in classroom activities, as well as its integration into the curriculum, were discussed.
Keywords: African Languages; Barriers; Class Activities; Computer Software; Educational Benefits; Elementary School Teachers; English; Foreign Countries; Gender Differences; Information Technology; Learning Processes; Mathematics Instruction; Rwanda; Teacher Attitudes; Teaching Experience; Teaching Methods; Technology Uses in Education; Translation

The Mediating Role of Text Reading Fluency in Reading Comprehension in English and Kiswahili: Evidence from Multilingual Contexts in Kenya - Wawire, Brenda Aromu; Liang, Xinya; Piper, Benjamin (The Mediating Role of Text Reading Fluency in Reading Comprehension in English and Kiswahili: Evidence from Multilingual Contexts in Kenya, 2023)
The present study examined the mediating role of text reading fluency in reading comprehension in English and Kiswahili utilizing longitudinal data from 628 first- and second-grade children from multilingual contexts in Kenya. We employed path analysis to explore the mediating role of text reading fluency on decoding and reading comprehension in English and Kiswahili. The results demonstrated that decoding and text reading fluency bridges the gap between word recognition skills and reading comprehension in English and Kiswahili. Over time, as children improve their reading skills, the direct influence of decoding on reading comprehension diminishes; hence, text reading fluency explains the unique variance in reading comprehension. The present findings highlight the importance of text reading fluency in the developmental phases of reading comprehension among multilingual children learning to read across multiple languages.
Keywords: African Languages; Decoding (Reading); Elementary School Students; English; English Language Learners; Foreign Countries; Grade 1; Grade 2; Kenya; Language Usage; Language of Instruction; Reading Comprehension; Reading Fluency; Reading Skills; Second Language Learning

Understanding and addressing the post-pandemic learning disparities - Alejo, Anna; Jenkins, Robert; Reuge, Nicolas; Yao, Haogen (International Journal of Educational Development, 2023)

Literature Search Protocol: Mapping African-Led Foundational Literacy and Numeracy Publications in English, French and Portuguese - Binesse, H; Rose, P; Silva, R (REAL Centre, University of Cambridge, 2023)

Are ALL Our Children Learning - FLANA (Usawa, 2023)

Evidence for System Transformation Brief: Foundational Learning - Global Partnership for Education (2023)

Ensuring Foundational Learning. Insights from the Global South - Hevia, F; Sabates, R (2023)

2023-2030 Education and Training Sector Strategy - Ministry of the Economy, Planning and Regional Development (Government of Cameroon, 2023)
The strategy takes on board the need for transforming education for the sake of equity, inclusion and quality of learning in connection with the country’s development needs.

Transforming Education, Training and Research for Sustainable Development in Kenya - Munavu, Raphael M (Government of Kenya, 2023)

The Broken Spider Web: Navigating the Complex Education Data Ecosystem in Cameroon - Pambe, Rigobert (2023)

Report of the Presidential Working Party on Education Reform - Republic of Kenya (2023)

Experience as the sought outcome: From foundational skills to inclusive and holistic learning - Stavrianos, Alexandros (Open Journal of Social Sciences, 2023)

Overcoming middle-income countries’ challenges in advancing the 2030 Agenda | High-Level Political Forum 2023 - United Nations (2023)

Perceptions and pedagogical considerations in professional development training for integration of an early literacy program in Kenya. - Wood, Eileen; Vica, Cristiana; Gottardo, Alexandra; Iminza, Rose; Kiforo, Enos; Wade, Anne (Perceptions and pedagogical considerations in professional development training for integration of an early literacy program in Kenya., 2022)
The present study examines experiences of mentor teachers and their teacher colleagues following three days of professional development training for early literacy instruction and a literacy software program (ABRA). Four Kenyan teacher-mentors were interviewed and 34 teachers were surveyed. Training included program specific and curriculum integration content. Thematic analysis of interviews yielded six themes, which identified perceived barriers and facilitators to adoption and integration of ABRA in the Kenyan elementary school context. Consistent with integration models, barriers involved infrastructure and access to technology, and challenges integrating the pedagogy of the software within the constraints of the existing curriculum. These challenges placed extra burdens on the 'ambassador' role, a key strategic initiative, which may require alternative support for program continuance, adoption, and fostering teachers' professional development. Ambassadors and teachers agreed on the majority of challenges identified. Recommendations were noted to address cultural norms to enhance accessibility of the software.
Keywords: Adults; Career development; Colleges, Universities, and Professional Schools; Emergent literacy; Kenya; Professional and Management Development Training; Professional education; Teachers; Vocational Rehabilitation Services

Learning Losses during COVID-19: Global Estimates of an Invisible and Unequal Crisis - Azevedo, João Pedro; Akmal, Maryam; Cloutier, Marie-Helene; Rogers, Halsey; Wong, Yi Ning (Policy Research Working Papers, 2022)
The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Bank for Reconstruction and Development/World Bank and its affiliated organizations, or those of the Executive Directors of the World Bank or the governments they represent.

The roles of childhood circumstances and schooling on adult reading skills in low- and middle-income countries. - Shafiq, M. Najeeb; Valerio, Alexandria (The roles of childhood circumstances and schooling on adult reading skills in low- and middle-income countries., 2022)
The article investigates the roles of childhood circumstances (including parental socio-economic status, parental education, parental engagement, and sibling composition) and schooling on adult reading skills in low- and middle-income countries. Using regression models and data from surveys of urban labor-force participants in Armenia, Bolivia, Colombia, Georgia, Ghana, Kenya, Ukraine, and Vietnam, the study reaches several conclusions. First, childhood circumstances predict adult reading skills in all eight countries. Second, among the childhood circumstances variables, parental education is the most frequent predictor of adult reading skills. Third, schooling is at least as important as the childhood circumstances variables in explaining adult reading skills. Finally, an extra year of schooling is associated with larger gains in adult reading skills in the relatively lower income countries.
Keywords: Adult literacy; Children; Cognitive ability; Primary education; Siblings; Social mobility; Social status

Spotlight on Basic Education Completion and Foundational Learning in Africa - UNESCO Global Education Monitoring Report Team; Association for the Development of Education in Africa; African Union (2022)
Born to learn

Can learning be measured by phone? Evidence from Kenya. - Rodriguez-Segura, Daniel; Schueler, Beth E. (Can learning be measured by phone? Evidence from Kenya., 2022)
School closures induced by COVID-19 placed heightened emphasis on alternative ways to measure learning besides in-person exams. We leverage the administration of phone-based assessments (PBAs) measuring numeracy and literacy for primary school children in Kenya, along with in-person standardized tests administered to the same students prior to school shutdowns, to assess the validity of PBAs. Compared to repeated in-person assessments, PBAs did not severely misclassify students' relative performance, but PBA scores did tend to be further from baseline in-person scores than repeated in-person assessments from each other. As such, PBAs performed well at measuring aggregate but not individual learning levels. Administrators can therefore use these tools for aggregate measurement, such as in the context of impact evaluation, but should be wary of PBAs for individual-level tracking or high-stakes decisions. Results also reveal the importance of making deliberate efforts to reach a representative sample and selecting items that provide discriminating power. Finally, in cases when collecting in-person data is possible, this study illustrates that, depending on the logistical capabilities of the data collecting agency, PBAs do not always have a cost-effectiveness advantage over in-person data collection.
Keywords: Kenya; Learning; Literacy; Numeracy; School children; School closings; Standardized tests

Breaking the Cycle: Women's Perceptions of the Causes of Violence and Crime in Informal Settlements in Nairobi, Kenya, and Their Strategies for Response and Prevention. - Winter, Samantha C.; Obara, Lena Moraa; Aguilar, Nathan Jason; Johnson, Laura (Breaking the Cycle: Women's Perceptions of the Causes of Violence and Crime in Informal Settlements in Nairobi, Kenya, and Their Strategies for Response and Prevention., 2022)
Crime and violence are serious issues in informal settlements around the world. To date, there is a dearth of evidence about the causes of and effective strategies for reducing and preventing violence and crime in informal settlements in cities in the Global South. Additionally, women's voices are often absent from research focused on violence and crime prevention and reduction in informal settlements. The purpose of this study, therefore, was (1) to identify potential causes of violence and crime in informal settlements, as perceived by women living in Mathare informal settlement in Nairobi, Kenya and (2) to highlight residents' strategies for response and prevention. Fifty-five in-depth and walk-along interviews were conducted with women living in Mathare in 2015-2016. A modified grounded theory approach was used to guide data collection and analysis. The most common contributor to violence and crime identified by women in Mathare was idle youth, but leadership and government challenges, corruption and/or inadequacy of police, community barriers, tribalism, and lack of protective infrastructure also emerged as contributing factors. Despite facing many economic, environmental, and day-to-day challenges, women in Mathare identified violence and crime as predominant issues; thus, developing effective response and prevention strategies to these issues is paramount. Women discussed many strategies and initiatives to reduce and prevent violence and crime in informal settlements, but also identified barriers to implementing them. Findings suggest there is a need for trust-building between formal and informal sectors of the community, systems of accountability, and long-term investment to foster sustainable and effective violence and crime response and prevention in these settlements.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Attitude (Psychology); Community life; Crime prevention; Data analysis software; Education; Educational Support Services; Employment; Experience; Government aid; Grounded theory; Interviewing; Judgment sampling; Kenya; Masculinity; Parenting; Qualitative research; Research methodology; Strategic planning; Thematic analysis; Unemployment; Violence prevention; Women's health

Announcing: Data-Driven Decision-Making Mapping in Education – Development Gateway: An IREX Venture – Data and digital solutions for international development. - IREX (Development Gateway: An IREX Venture, 2022)
Development Gateway: an IREX Venture (DG) and IREX, in partnership with the Hewlett Foundation, are pleased to announce a new research program supporting data-driven decision-making in education in East and West Africa. This two-year, $300,000 project to map education data and decision ecosystems in Kenya and Senegal will focus on the variety of administrative, census, and survey data collected to implement and monitor primary and secondary education. The goal is to holistically understand the barriers to more effective data collection, sharing, interoperability, and use. By understanding the barriers, we can better design support for more robust education data ecosystems that drive better learning outcomes.

Beliefs of Teachers in Urban Elementary Mathematics Classrooms: Results of a Mixed-Methods Study - Hall, Kenya; Yakimowski, Mary E. (Beliefs of Teachers in Urban Elementary Mathematics Classrooms: Results of a Mixed-Methods Study, 2022)
A mixed-methods study investigated the relationship between teachers within urban Title I elementary schools (e.g., high versus low performing) and their mathematics problem-solving beliefs in six constructs ("perseverance," "procedural," "conceptual," "importance," "effort," and "usefulness"). The 181 teachers of students in third to fifth grades in 26 schools (93% response rate) took the 36-item "Indiana Mathematics Belief Scale," and 11 were interviewed. Descriptive and inferential statistics and qualitative thematic analysis were conducted. No statistical difference between teachers in high and low-performing schools in their mathematical beliefs was found in any of the six constructs. The qualitative results did deepen the quantitative findings in offering insights into teachers' recognition of the importance of conceptual understanding in mathematics. The implications and directions for future research are discussed, including further inquiry on addressing professional development supports for teaching problem strategies in mathematics.
Keywords: Alabama; Disadvantaged Schools; Elementary School Mathematics; Elementary School Teachers; Grade 3; Grade 4; Grade 5; High Achievement; Learning Strategies; Low Achievement; Mathematics Achievement; Problem Solving; Teacher Attitudes; Teacher Surveys; Urban Schools

School Readiness Test and Intelligence in Preschool as Predictors of Middle School Success: Result of an Eight-Year Longitudinal Study. - Józsa, Krisztián; Amukune, Stephen; Zentai, Gabriella; Barrett, Karen Caplovitz (School Readiness Test and Intelligence in Preschool as Predictors of Middle School Success: Result of an Eight-Year Longitudinal Study., 2022)
Research has shown that the development of cognitive and social skills in preschool predicts school readiness in kindergarten. However, most longitudinal studies are short-term, tracking children's development only through the early elementary school years. This study aims to investigate the long-term impact of preschool predictors, intelligence, and mothers' education on grade six school performance. This study presents the results of an eight-year-long longitudinal study. The sample includes 202 Hungarian children (89 boys) from a disadvantaged region of southeastern Hungary. The independent variables were the preschool measures: DIFER (Diagnostic System for Assessing Development), a widely used, standardized school readiness test that measures cognitive and social skills; the Raven intelligence test; and socioeconomic status. The dependent variables in grade six were: National Standardized tests in math and reading (NABC, National Assessment of Basic Competencies) and school grades (GPA). Cronbach's alpha reliability of each test is above 0.76. Correlations and a series of multiple regressions were used for analysis. All three independent variables have significant predictive power for school performance in sixth grade. DIFER skills were the best predictors for reading achievement, intelligence for math achievement, and GPA was best predicted by mothers' education. The results show that developing preschool skills, mothers' education and IQ in preschool are essential to long-term learning success.
Keywords: Child Day Care Services; Elementary and Secondary Schools; Hungary; Intelligence tests; Longitudinal method; Middle school students; Middle schools; Preschools; Readiness for school

School-Entry Predictors of Lower Primary Reading and Mathematics Achievement in Kenya - Platas, Linda M.; Perry, Lindsey; Piper, Benjamin; Sitabkhan, Yasmin; Ketterlin-Geller, Leanne (School-Entry Predictors of Lower Primary Reading and Mathematics Achievement in Kenya, 2022)
Using a longitudinal data set, this paper examines to what extent school-entry (N = 553; mean age 6.32 years) early mathematics and literacy skills predict students' later achievement in a lower-middle-income country, Kenya. Controlling for socioeconomic status, intervention status, rural versus urban settings and parental literacy, the findings reveal that school-entry mathematics skills were significantly predictive of students' end of Grade 2 mathematics and reading achievement in English and Kiswahili. Likewise, school-entry English early literacy skills predicted students' end of Grade 2 mathematics and reading achievement in English and Kiswahili. This article extends earlier research on links between elements of school readiness and later achievement in high-income countries.
Keywords: African Languages; Elementary School Students; English; Foreign Countries; Grade 2; Kenya; Kindergarten; Mathematics Achievement; Mathematics Skills; Predictor Variables; Public Schools; Reading Achievement; Reading Skills; Socioeconomic Status; Student Characteristics

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, T; Lawson, L; Heady, L (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org

HOW ARE TEACHERS TRAINED FOR TEACHING COMPETENCEBASED GRADE FOUR AGRICULTURE? A CASE OF PUBLIC PRIMARY SCHOOLS IN NJORO SUB-COUNTY IN NAKURU COUNTY. - Karani, Alex O.; Miriam, Kyule N.; Nge’no, Joel (HOW ARE TEACHERS TRAINED FOR TEACHING COMPETENCEBASED GRADE FOUR AGRICULTURE? A CASE OF PUBLIC PRIMARY SCHOOLS IN NJORO SUB-COUNTY IN NAKURU COUNTY., 2022)
One of the major aims of vision 2030 is to ensure Kenya becomes a middle-income economy through industrialization. In the year 2017, Competence-Based Education (CBE) was introduced to produce school graduates with self-efficacy, self-reliance, effective communication, problem-solving, innovation, and digital literacy competencies. However, for students to acquire the competencies, quality teacher training is significant. This study sought to determine how teachers are trained for teaching CBE Grade Four Agriculture in the Njoro sub-County. A descriptive research design was used employing a cross-sectional survey method that generated quantitative data. A sample size of 96 teachers of agriculture was obtained from the 96 public primary schools in the six wards of Njoro Sub-County. Descriptive statistics were used for data analysis using Statistical Package for Social Sciences (SPSS) version 25. The findings of this study indicated that all of the grade four teachers of agriculture had attended CBE training but the majority of them (49%) attended purely theoretical sessions, 59.4% of the teachers cited the teacher-trainers were not competent. In addition, at least 16% of the teachers indicated that the training sessions were not relevant to teaching Agriculture subject. This study recommended that the Ministry of Education develop a framework for practical teacher training. Teacher trainers should be re-trained and training sessions should be aligned towards specific subjects, teacher needs, and students 'needs to increase relevance.
Keywords: Agricultural education; Descriptive statistics; Primary schools; Self-efficacy in teachers; Teacher attitudes

Conceptualizing non-cognitive attributes, entrepreneurship training, pedagogical competencies and stem education outcome: an integrated model and research proposition. - Mwasiaji, Evans; Mambo, Shadrack; Mse, Godfrey S.; Okumu, John (Conceptualizing non-cognitive attributes, entrepreneurship training, pedagogical competencies and stem education outcome: an integrated model and research proposition., 2022)
Literature on STEM education outcome in the tertiary context has pursued the construct of non-cognitive attributes distinctly from that of entrepreneurship skills and pedagogical competencies, notwithstanding the inferred indications that the three can be adapted in an integrated model to enhance positive outcomes. This study established that there is a range of approaches seeking to optimize positive learning outcomes in tertiary level institutions. This paper argues that there is need to incorporate entrepreneurship and pedagogical skills training in the curriculum for STEM educators at the tertiary level institutions. The study has therefore proposed an integrated theoretical model which can be used to generate data sets to address identified gaps.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Core competencies; Education; Educational Support Services; Entrepreneurship; Outcome assessment (Education); STEM education

When online learning and cultural values intersect: Indonesian EFL students’ voices. - Usman, Jarjani; Zainuddin, Zamzami; Zulfikar, Teuku; Lugendo, Dorine; Zulkarnaini; Yusuf, Yusri (When online learning and cultural values intersect: Indonesian EFL students’ voices., 2022)
During the COVID-19 pandemic, all lecturers had to replace their physical classroom teaching mode with online learning, albeit with challenges experienced by students and lecturers. Drawing upon Hofstede’s cultural dimensions theory, this study attempted to unearth Indonesian students’ learning culture by analysing written reflections on their learning experiences. Twenty EFL (English as a foreign language) students enrolled in the English Academic Writing courses at an Islamic university in Indonesia, wrote a reflective essay on their online learning experiences with various platforms, such as Google Classroom, Google Meet, Canvas, Moodle, and some other online learning platforms. Content analysis was used to analyse the students’ reflective writing essays. Results show that the students’ voices bring to the fore several learning issues from online learning experiences. These include: the lecturers’ dominant use of WhatsApp as an instruction tool, unclear explanations, assigning students too many assignments, and the abandonment of lecturer feedback on works submitted by students. Noteworthy, whether the students liked or disliked the online learning experience, they accepted how the lecturers treated them in the online teaching and learning process. The findings indicated that the students avoided conflicts, showed high respect to their superiors, and used indirect disagreement in the online learning contexts. The findings suggest that the ‘small culture’ of online learning in higher education is governed by a strong influence of ‘large culture’ in Indonesia.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Cultural values; Distance education; English as a foreign language; Language Schools

Anatomy of the "Free Senior High School" Policy in Ghana and Policy Prescriptions. - Adarkwah, Michael Agyemang (Anatomy of the "Free Senior High School" Policy in Ghana and Policy Prescriptions., 2022)
The paper utilized a document analysis technique and qualitative interviews to provide a comprehensive understanding of the "Free SHS" policy in Ghana, which remains illusory to many Ghanaian students. First, a preliminary study which involved analysis of prior literature (n = 12) on the policy was conducted. Interviews involving ten teachers from Ghana National Association of Teachers (GNAT), and five private school teachers were conducted to validate the findings from the preliminary study. Existing literature on other African countries such as Uganda, Kenya, Malawi, and Ethiopia was used to draw up policy lessons for decision-makers in education. The policy process cycle served as a framework to analyze the different dimensions of the policy. Similar results were observed from the two phases of the study. Implementers of the policy focused more on the program and political dimensions of policy with less emphasis on the process dimension. At the agenda setting stage, no clear problem was identified while at the policy formulation stage, there were no other alternatives to canvass from. It was observed that lack of adequate funds, limited textbooks, inadequate infrastructure, and doubts about educational quality were some of the challenges in the aftermath of policy implementation. Policy implications are also discussed in the study. It is recommended that policymakers partner with the private sector, NGOs, and international bodies, reform the school curriculum to improve learning outcomes, reduce repetition rates in school, create room for more teachers to be trained, and prepare graduates equipped to enter the labor market.
Keywords: Curriculum change; Educational change; Educational quality; Electronic textbooks; Ghana; High school seniors; Teachers

Exploring the Relationship Between Participation in an Adult-women's Soccer League and Intimate Partner Violence in Rural Kenya. - Barchi, Francis; Winter, Samantha C.; Mbogo, Daniel; Thomas, Bendettah; Ammerman, Brittany (Exploring the Relationship Between Participation in an Adult-women's Soccer League and Intimate Partner Violence in Rural Kenya., 2022)
Rates of intimate partner violence (IPV) against women in Sub-Saharan Africa are among the highest of any region in the world. Empirical studies on the effectiveness of IPV-prevention programs in Africa, though few, suggest that successful programs have emphasized community-level engagement and attitudinal change around gender roles. This study explored the relationship between adult women's participation in an all-women's soccer league and IPV in rural Kenya. Nikumbuke Project is a health- and literacy-based program for 702 women in Kwale County, Kenya, that also hosts a women's soccer league. A total of 684 Nikumbuke members completed surveys for this study, 543 of whom identified as having had a partner in the preceding 12 months and were included in this analysis. Participants in the study were, on average, in their late 30s, married with 4–6 children, a primary education or less, and no source of formal employment. Logistic regression models examined the association between a woman's participation in the soccer league and the odds that she would have experienced recent IPV, controlling for other covariates. Women who played on soccer teams had 59% lower odds of reporting physical IPV in the preceding 12 months and approximately 43% lower odds of reporting any form of IPV during the same period compared to women who did not play soccer. Support of more gender-equitable norms was associated with lower odds of all forms of recent violence. More research is needed to identify the underlying reasons for these observed effects and to determine the presence of a causal or temporal relationship between adult women's sports and IPV-risk reduction. Nonetheless, findings from this study point to a novel IPV intervention in communities that might otherwise be resistant to more overt attempts to address gender-based violence (GBV) or where social service agencies with the capacity for IPV-prevention programming may be limited.
Keywords: Chi-squared test; Confidence intervals; Data analysis software; Descriptive statistics; Educational attainment; Intimate partner violence; Kenya; Logistic regression analysis; Marital status; Multivariate analysis; Odds ratio; Research funding; Rural conditions; Soccer; Sports participation; Women

Wider Benefits of Adult Literacy Teaching: A Preliminary Exploration of the Impact of Teaching Literacy to Adults on Some Facilitators - Rogers, Alan; Gizaw, Abiy Menkir (Wider Benefits of Adult Literacy Teaching: A Preliminary Exploration of the Impact of Teaching Literacy to Adults on Some Facilitators, 2022)
This article reports on a pilot research project conducted in nine countries of Africa and Asia on some aspects of the impact that teaching literacy to adults has had on the lives of some adult literacy facilitators (ALFs). The small-scale enquiry was implemented by a team of twelve researchers in nine countries (Afghanistan, Botswana, Ethiopia, Kenya, Malawi, Nepal, Tanzania, Uganda, Zambia). All of the nineteen ALFs interviewed felt that the experience of teaching literacy to adults, even if for some of them it was brief and posed difficulties, had a positive impact on their lives, and in some cases was life-changing. Despite its limitations, the project demonstrates the importance and feasibility of such a study and encourages further surveys.
Keywords: Adult Education; Adult Educators; Adult Literacy; Afghanistan; Botswana; Ethiopia; Facilitators (Individuals); Foreign Countries; Kenya; Literacy Education; Malawi; Nepal; Program Effectiveness; Tanzania; Teacher Attitudes; Uganda; Zambia

Understanding the Effect of Educational Attainment and Unemployment on Youth Engagement in Conflicts in Machakos County, Kenya - Senga, Mike M.; Kiilu, Redempta M. (Understanding the Effect of Educational Attainment and Unemployment on Youth Engagement in Conflicts in Machakos County, Kenya, 2022)
Globally, the extensive damage caused by violent conflicts with subsequent social and economic costs have posed a real concern that needs to be urgently addressed. The provision of quality education is a force that can be utilized to curb constant conflicts within society. The purpose of the study was to establish the effect of the educational attainment and unemployment on youth engagement in conflicts in Machakos County. The study was carried out in Machakos County and targeted the youth incarcerated in two prisons located in Machakos town, Machakos County. The sample was 168 respondents consisting of both male and female youth between 18-34 years. Descriptive survey design was used. The study used Semi-Structured questionnaires to collect both qualitative and quantitative data. The data was analysed using both qualitative and quantitative techniques-assisted by use of Statistical Package for Social Sciences (SPSS) version 20. From the findings, a close link between the level of education and youth engagement in conflicts was established. The study findings indicates a statistically significant relationship between the level of education and the conflicts among the youths as illustrated by P>0.05. The study established that the youth with low levels of education were also the group that lacked employment and reported cases of conflicts and crimes. From the study, most of the youths who engaged in conflicts had low levels of education as reported by 49.4% of respondents and mostly were those who had never completed basic education, lacked basic skills required in the labour market and were found to earn less than two dollars a day. The study recommends that the government come up with affirmative action to empower such groups to engage in productive activities to enable them to earn a living.
Keywords: Basic Skills; Conflict; Crime; Educational Attainment; Foreign Countries; Institutionalized Persons; Kenya; Low Achievement; Unemployment; Violence; Young Adults

Professional Development on Digital Literacy and Transformative Teaching in a Low-Income Country: A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Professional Development on Digital Literacy and Transformative Teaching in a Low-Income Country: A Case Study of Rural Kenya, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle-income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner-centered teaching, and relevance to students' lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government's push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers' perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three-day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre- and post-surveys, participant-generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner-centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner-centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low-income countries.
Keywords: Computer Literacy; Culturally Relevant Education; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Kenya; Low Income Groups; Preschool Teachers; Secondary School Teachers; Student Centered Learning; Teacher Attitudes; Technology Uses in Education

Sustainability and Scalability of Digital tools for Learning: ABRACADABRA in Kenya - Lysenko, Larysa; Abrami, Philip C.; Wade, C. Anne (Sustainability and Scalability of Digital tools for Learning: ABRACADABRA in Kenya, 2022)
This paper explores factors to increase the likelihood that the implementation of ABRACADABRA, a technology-based approach to teaching and learning literacy, endures and expands beyond the initial research. Started as a pilot study in 12 classrooms, the implementation spread to more than 500 primary classrooms over six years in five areas of Kenya. Drawing from research about scalability and sustainability of educational interventions and value-expectancy-cost theory, an exploratory survey was designed to interview a range of actors involved in the software implementation. We used a combination of an a priori and data-driven coding approaches to analyse the narratives. We then built a model exploring the relationship between expectancy-value-cost beliefs and the factors associated with implementation and sustainability. The model explained an important portion of variance in the self-reported intent to use the software with the most significant contributions from policies, professional development, and students. These findings may be useful in the context of low- and medium-income countries where no research-proven principles exist to building sustainable and scalable educational interventions.
Keywords: Administrator Attitudes; Computer Software; Correlation; Cost Effectiveness; Educational Technology; Elementary School Students; Faculty Development; Foreign Countries; Intervention; Kenya; Literacy Education; Partnerships in Education; Pilot Projects; Program Implementation; Sustainability; Teacher Education; Teaching Methods

Academic Outcomes of Homeschooled versus Conventionally Schooled Children Pursuing the Accelerated Christian Education Curriculum in Kenya - Mwanyumba Tweni, Fredrick; Wamocha, Lydia; Buhere, Pamela (Academic Outcomes of Homeschooled versus Conventionally Schooled Children Pursuing the Accelerated Christian Education Curriculum in Kenya, 2022)
In recent times, the Kenyan education sector has experienced increased cases of students' indiscipline in schools. However, the potential of homeschooling as a possible solution to such indiscipline has not been explored. Whereas critics of homeschooling posit that homeschooled children are inferior academically, proponents of this form of learning don't think so. Therefore, this research compared the academic learning outcomes of homeschooled children and children in conventional school settings. The subjects in which scores were compared were math, English, and social studies. This research was anchored in the systems theory's input-output model developed by Ludwig Von Bertalanffy and adopted the causal-comparative research design. The target population was children pursuing the Accelerated Christian Education (ACE) curriculum. A sample of 316 children was drawn, out of whom 272 participated in the research. Data were analyzed using independent samples t-tests. Results revealed that homeschooled children achieved significantly higher math, English, and social studies scores than children in conventional schools. The research concluded that homeschooling as an alternative form of education enhances children's academic learning outcomes equally well and probably better than conventional schools. Therefore, the education sector in Kenya should consider legalizing homeschooling as an alternative form of education for some parents who want to detach their children from indiscipline cases that are majorly witnessed in conventional schools. Despite this research stating the case for legalizing Homeschooling in Kenya, a significant limitation was the reliance on the ACE curriculum and academic scores derived from one term's performance. Therefore, future studies should consider panel data that caters for comparisons across diverse curricula over time.
Keywords: Academic Achievement; Acceleration (Education); Christianity; Comparative Analysis; Conventional Instruction; English (Second Language); Foreign Countries; Home Schooling; Kenya; Mathematics Education; Outcomes of Education; Religious Schools; Social Studies

Accelerated Learning to Reach Children Furthest Behind - Ngindiru, Virginia; Mburu, James; Chepngetich, Irene (Accelerated Learning to Reach Children Furthest Behind, 2022)
Accelerated learning programs (ALP) around the world are helping disadvantaged, over-age, out-of-school children and youth catch up to their more advantaged peers. The Teaching at the Right Level (TaRL) approach applies principles of formative assessments and level-wise grouping and learning to ensure children lagging in the foundational literacy and numeracy competencies catch up within a relatively short period, usually 30-50 days. This article discusses the implementation of ALP in Kenya: the adaptations made, the evolution of the approach over time, and the impact of COVID-19 lockdowns.
Keywords: Acceleration (Education); COVID-19; Educationally Disadvantaged; Foreign Countries; Formative Evaluation; Goal Orientation; Grouping (Instructional Purposes); Kenya; Literacy; Numeracy; Pandemics; Program Implementation

Myth or Reality: Digital Literacy Programme Implementation in Primary Special Schools in Nairobi, Kenya - Omboto, Charles Magwar; Kanga, Anne; Njageh, Ann Rita K. (Myth or Reality: Digital Literacy Programme Implementation in Primary Special Schools in Nairobi, Kenya, 2022)
Information Communication Technology (ICT) enhances accessibility, efficiency, and quality of education. This study aimed to examine the status of ICT resources in teaching and learning in public primary special schools in Nairobi County, Kenya. Questionnaires, interviews, observation schedules, and manuals for document analysis were used to collect data from respondents. Research shows that most special schools have regular ICT resources provided by digital literacy programs (DLP), such as laptops and tablets. However, there is limited investment in specialized ICT resources to support the teaching and learning of children with disabilities and special educational needs. Research also shows that ICT resources are limited because most of the devices are kept by school administrators or teachers who do not know how to use them. The study concludes that limited investment in assistive and/or adaptive digital technologies and devices will harm the attainment of ICT skills as a fundamental skill by children with disabilities in special schools and special needs units. The study recommends the establishment of a technical committee on design innovation and equipment technology. This will complement DLP's efforts in providing resources for special schools to make better use of ICT for students with disabilities and special educational needs.
Keywords: Access to Computers; Educational Technology; Elementary Schools; Foreign Countries; Kenya (Nairobi); Program Effectiveness; Program Implementation; Public Schools; Special Schools; Students with Disabilities; Technological Literacy; Technology Uses in Education

Perceptions and Pedagogical Considerations in Professional Development Training for Integration of an Early Literacy Program in Kenya - Wood, Eileen; Vica, Cristiana; Gottardo, Alexandra; Iminza, Rose; Kiforo, Enos; Wade, Anne (Perceptions and Pedagogical Considerations in Professional Development Training for Integration of an Early Literacy Program in Kenya, 2022)
The present study examines experiences of mentor teachers and their teacher colleagues following three days of professional development training for early literacy instruction and a literacy software program (ABRA). Four Kenyan teacher-mentors were interviewed and 34 teachers were surveyed. Training included program specific and curriculum integration content. Thematic analysis of interviews yielded six themes, which identified perceived barriers and facilitators to adoption and integration of ABRA in the Kenyan elementary school context. Consistent with integration models, barriers involved infrastructure and access to technology, and challenges integrating the pedagogy of the software within the constraints of the existing curriculum. These challenges placed extra burdens on the 'ambassador' role, a key strategic initiative, which may require alternative support for program continuance, adoption, and fostering teachers' professional development. Ambassadors and teachers agreed on the majority of challenges identified. Recommendations were noted to address cultural norms to enhance accessibility of the software.
Keywords: Access to Computers; Barriers; Computer Software; Cultural Influences; Educational Technology; Elementary School Students; Faculty Development; Foreign Countries; Kenya; Literacy Education; Mentors; Pedagogical Content Knowledge; Reading Programs; Strategic Planning; Teacher Attitudes; Technological Literacy; Technology Integration; Web Based Instruction

Systèmes éducatifs bi/plurilingues au Rwanda et au Cameroun : enjeux pour le développement d'une littérature de jeunesse en langues locales - Ethé, Julia Ndibnu-Messina; Ntakirutimana, Évariste (Synergies Afrique des Grands Lacs, 2022)
Dans la majorité de pays africains, la place et l'essor des langues locales semblent incertains face au plurilinguisme de leurs systemes éducatifs. Le présent article analyse les contextes socioculturels et éducatifs du Rwanda et du Cameroun afin de produire, de développer et de renforcer les outils didactiques d'enseignement des langues locales au sein de leurs systemes bi-plurilingues surtout au niveau de l'éducation de base. Dans cet article, l'étude comparative des données documentaires basées sur des programmes enseignés, les disciplines des curricula, les horaires hebdomadaires des cours de langues et l'apport des politiques linguistiques et éducatives dans les écoles primaire et secondaire au Rwanda et au Cameroun, renseignent le degré d'enseignement des langues locales et la place de la littérature de jeunesse dans l'enseignement de base. Aussi, elle tente de proposer les stratégies a prendre pour leur développement durable en matiere de pratiques enseignantes.Alternate abstract:In many African countries, the place and the future of local languages seem to be uncertain confronted with the multilingualism of their educational systems. This paper is in line with the analysis of the socio-cultural and educational contexts of Rwanda and Cameroon. It aims at producing, developing and reinforcing didactic tools for teaching local languages within their bi-multilingual systems, especially at basic education level. In this article, the comparative study of documentary data based on taught programs, the curricula, weekly language classes and the contribution of language and educational policies in primary and secondary schools in Rwanda and Cameroon, inform on the level of local languages teaching and on the place of youth literature in basic education. Finally, this paper proposes some strategies and actions to be taken for the local languages sustainable development in terms of teaching practices.
Keywords: Bantu languages; Cameroon; Childrens literature; Curricula; Education; Education policy; Learning environment; Literary criticism; Literature; Multilingual systems; Multilingualism; Rwanda; Secondary schools; Sociocultural factors; Teaching; Teaching methods

Demographic and Health Survey 2022 - Government of Kenya (Government Printer, 2022)

Kenya School Readiness Assesment Tool - Government of Kenya (2022)

Foundational learning skills: Panacea for quality education - Jha, Dr Aruna; Manushi, Manya (2022)
Purpose: To understand the role of foundational learning as a means to improve quality in education. Design/methodology/approach: Secondary data sources like research papers and published reports have been used to carry out this qualitative research that is in the form of a landscape analysis. Discoveries: There is increased focus on foundational learning in India. We can learn from the experience of countries such as Kenya, Brazil, and Philippines, which have achieved significant success in the field of education, particularly foundational learning. Government, Private sector and NGOs are playing important role in improving the standards of foundational learning in India.

Mixed methods and quality of postgraduate research: A Kenyan perspective - Kwanya, Tom (Advances in knowledge acquisition, transfer, and management, 2022)
This chapter analysed the extent, nature, and suitability of use of mixed methods research by postgraduate students in Kenya as well as its influence on the quality of their research output. Data anchoring the chapter was collected through qualitative content analysis of 229 theses and dissertations of library and information science postgraduate students in Kenya retrieved from the respective institutional repositories. Of these, 193 were Master’s dissertations while 36 were doctoral theses. One hundred twenty-two (53.3%) of the theses and dissertations were developed using mixed methods research while 74 (32.3%) were based on qualitative studies. Most of the students collected both qualitative and quantitative data concurrently and merged the same during analysis and interpretation. It also emerged that the bulk of data collected by the students was qualitative; quantitative data was largely used to supplement or validate qualitative data. Using citations, it emerged that theses and dissertations developed through mixed methods research attracted more citations thereby indicating a superior quality.

The Children Act - Republic of Kenya (2022)

Questionnaires as a tool for teaching English language through learner-created knowledge - Strelluf, Christopher; Ekembe, Eric (English Teaching Forum, 2022)
The method of learner-created knowledge--where students engage with others in order to connect what they know with new knowledge to construct new meaning--ties into a broader support for learner autonomy in English language teaching (ELT) and learning. In countries like Cameroon, the social power orientation is mirrored in classroom practices, and teacher-centered pedagogies are the norm from primary to tertiary education. Developing tools to foster knowledge creation by learners in ELT contexts like those of Africa is potentially transformational. Such tools counter Sonaiya's (2005) rejection of learner autonomy in African ELT by offering alternatives for learners to take control and participate more fully in their learning through creative classroom activities. In this article, the authors present classroom-generated questionnaires as one tool for incorporating learner-created knowledge in ELT classrooms. This article describes a four-step method to suit a range of learners that are readily transferable to ELT classrooms in Africa and beyond. The article demonstrates that learner-generated, -administered, and -analyzed questionnaires offer a viable approach for ELT practitioners to increase learner autonomy in low-resource contexts and achieve highly productive outcomes.
Keywords: Cameroon; ERIC, Current Index to Journals in Education (CIJE); English (Second Language); Foreign Countries; Personal Autonomy; Questionnaires; Second Language Learning; Student Centered Learning; Teaching Methods

Are Children Really Learning? Exploring Foundational Skills in the Midst of a Learning Crisis - UNICEF (2022)

70% of 10-Year-Olds now in Learning Poverty, Unable to Read and Understand a Simple Text - World Bank (World Bank, 2022)
70% of 10-Year-Olds now in Learning Poverty, Unable to Read and Understand a Simple Text

Learning Poverty is a combined measure of schooling and learning. - World Bank (World Bank, 2022)
What is learning poverty?

Deployment of Background Knowledge and Performance in Comprehension Passage Reading among Primary School Learners in Vihiga County, Kenya. - Anyiendah, Mary Susan; Odundo, Paul A.; Kibui, Agnes W. (Deployment of Background Knowledge and Performance in Comprehension Passage Reading among Primary School Learners in Vihiga County, Kenya., 2021)
Background. Primary school learners in Vihiga County have been recording a lower mean score in English language examinations than their counterparts in neighbouring counties, with the score being lower in comprehension passage than in grammar sections. Few previous studies conducted in Kenya have investigated the issue from the instructional dimension, thereby limiting stakeholders' understanding of the issue and delaying appropriate interventions. Aim. To determine how the deployment of learners' background knowledge influences performance in reading comprehension passages. Method. Solomon Four-Group Design guided the study. Data were sourced in mid-2017 from standard six learners and English language teachers. Regression analysis generated two models, one for the experimental and control groups, each. Results. In both models, deployment of background knowledge had a significant positive effect on the performance in reading comprehension passages, which prompted rejection of the null hypothesis. However, the effect was stronger in the experimental group than in the control group. The variation was attributed to training provided to the experimental group teachers, which improved their skills in activating learners' background knowledge. Conclusions. Activating learners' background knowledge is a vital antecedent to better performance in reading comprehension passages and the English language. Although prereading vocabulary is vital for the activation of learners' background knowledge, overreliance on a single strategy to activate learners' background knowledge undermines optimal deployment of background knowledge skills in reading, albeit with implications on performance.
Keywords: English language; English teachers; Experimental groups; Kenya; Limited English-proficient students; Primary schools; Reading comprehension

Do Private Schools Improve Learning Outcomes? Evidence from Within-Household Comparisons in East Africa and South Asia. - Gruijters, Rob J.; Alcott, Benjamin; Rose, Pauline (Do Private Schools Improve Learning Outcomes? Evidence from Within-Household Comparisons in East Africa and South Asia., 2021)
A contentious debate in academic as well as policy circles relates to the growth in private schooling in the Global South. While proponents highlight the superior learning outcomes of pupils in private schools, others have argued that this is merely a reflection of the more advantaged family background of private school pupils, rather than an effect of private schooling itself. We contribute to this debate by providing estimates derived from household fixed-effect models, which control for any observed or unobserved differences between government and private school pupils at the household level. We argue that these can be interpreted as an upper bound estimate of the effect of private schooling on learning. We rely on large-scale, comparable household survey data from Kenya, Uganda, India, and Pakistan, focusing on children enrolled in grades 2–6 of primary school. Private school attendance ranges from 12 percent in Kenya to 33 percent in rural India, with substantial within-household variation. The findings show that controlling for family background almost eliminates the positive effect of private schooling in rural Pakistan and reduces it by around half in rural India, Kenya, and Uganda, to about a quarter of a standard deviation. Subgroup analyses show that the effect of private schooling is similar for children from poor and wealthier families. We argue that the benefits of private schooling are unlikely to outweigh its social costs.
Keywords: Elementary and Secondary Schools; Externalities; Private schools; School attendance; School enrollment; Socioeconomic factors

Do Private Schools Improve Learning Outcomes? Evidence from Within-Household Comparisons in East Africa and South Asia - Gruijters, Rob J.; Alcott, Benjamin; Rose, Pauline (Do Private Schools Improve Learning Outcomes? Evidence from Within-Household Comparisons in East Africa and South Asia, 2021)
A contentious debate in academic as well as policy circles relates to the growth in private schooling in the Global South. While proponents highlight the superior learning outcomes of pupils in private schools, others have argued that this is merely a reflection of the more advantaged family background of private school pupils, rather than an effect of private schooling itself. We contribute to this debate by providing estimates derived from household fixed-effect models, which control for any observed or unobserved differences between government and private school pupils at the household level. We argue that these can be interpreted as an upper bound estimate of the effect of private schooling on learning. We rely on large-scale, comparable household survey data from Kenya, Uganda, India, and Pakistan, focusing on children enrolled in grades 2-6 of primary school. Private school attendance ranges from 12 percent in Kenya to 33 percent in rural India, with substantial within-household variation. The findings show that controlling for family background almost eliminates the positive effect of private schooling in rural Pakistan and reduces it by around half in rural India, Kenya, and Uganda, to about a quarter of a standard deviation. Subgroup analyses show that the effect of private schooling is similar for children from poor and wealthier families. We argue that the benefits of private schooling are unlikely to outweigh its social costs.
Keywords: Attendance; Comparative Analysis; Cross Cultural Studies; Educational Benefits; Educational Policy; Family Characteristics; Foreign Countries; India; Kenya; National Surveys; Outcomes of Education; Pakistan; Private Schools; Public Schools; Rural Areas; Uganda

Do Private Schools Improve Learning Outcomes? Evidence from Within-Household Comparisons in East Africa and South Asia - Gruijters, Rob J.; Alcott, Benjamin; Rose, Pauline (Do Private Schools Improve Learning Outcomes? Evidence from Within-Household Comparisons in East Africa and South Asia, 2021)
A contentious debate in academic as well as policy circles relates to the growth in private schooling in the Global South. While proponents highlight the superior learning outcomes of pupils in private schools, others have argued that this is merely a reflection of the more advantaged family background of private school pupils, rather than an effect of private schooling itself. We contribute to this debate by providing estimates derived from household fixed-effect models, which control for any observed or unobserved differences between government and private school pupils at the household level. We argue that these can be interpreted as an upper bound estimate of the effect of private schooling on learning. We rely on large-scale, comparable household survey data from Kenya, Uganda, India, and Pakistan, focusing on children enrolled in grades 2-6 of primary school. Private school attendance ranges from 12 percent in Kenya to 33 percent in rural India, with substantial within-household variation. The findings show that controlling for family background almost eliminates the positive effect of private schooling in rural Pakistan and reduces it by around half in rural India, Kenya, and Uganda, to about a quarter of a standard deviation. Subgroup analyses show that the effect of private schooling is similar for children from poor and wealthier families. We argue that the benefits of private schooling are unlikely to outweigh its social costs.
Keywords: Attendance; Comparative Analysis; Cross Cultural Studies; Educational Benefits; Educational Policy; Family Characteristics; Foreign Countries; India; Kenya; National Surveys; Outcomes of Education; Pakistan; Private Schools; Public Schools; Rural Areas; Uganda

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery. - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery., 2021)
• Short-term COVID-related learning losses in sub-Saharan Africa are up to one year. • The learning loss could accumulate to 2.8 years of long-term lost learning. • Targeted instruction and structured pedagogy reforms can mitigate learning losses. • Models suggest these reforms could improve pre-COVID learning levels. • Crisis presents historic opportunity to enact reforms to address learning crisis. We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year's worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
Keywords: COVID-19 pandemic; Educational planning; Online education; Pedagogical content knowledge; School closings

Examination of the postgraduate theses on teachers’ views of values education in Turkey: A meta synthesis study - Cengizhan, Sibel (International Journal of Progressive Education, 2021)
This research study carried out to examine the postgraduate theses on teachers’ views of the values education in Turkey was designed as a meta synthesis study. Postgraduate theses were obtained from the National Thesis Center of the Council of Higher Education. During the research process, these steps were followed;(1) determining the research subject, (2) selecting the studies to be included in the study, (3) picking and presenting the data, (4) ensuring validity and reliability and (5) analyzing the data and explaining the synthesis. Content analysis was used in the analysis of the data. The qualitative findings of the 24 theses included in the study were examined singly and as a result of the examination three main themes were determined; Applications practiced to gain values education and problems encountered, The values that should be gained by the students according to the teachers and the factors effective in gaining these values, The problems that the values education can deliver solution and the behavioral changes observed in the students after the values education practices. From the findings of the research, it was concluded that the teachers mostly used the drama method to gain of values education, that there were problems experienced caused by the family in practice, and that the practices could solve the problem of injustice the most.

An Analysis of Reading Comprehension Questions in Kenyan English Textbooks - Beerwinkle, Andrea; McKeown, Debra (An Analysis of Reading Comprehension Questions in Kenyan English Textbooks, 2021)
Reading comprehension is a valued skill worldwide. In Kenya, reading comprehension is taught through English textbooks. In this study, we analyzed the reading comprehension exercises in the English textbooks for Standard 4 and Standard 5. Results indicate a strong emphasis on questions that can be answered directly from the text and questions that connect to a reader's background. A brief discussion of content is provided as well as limitations and future directions.
Keywords: Elementary Education; English (Second Language); Foreign Countries; Grade 4; Grade 5; Kenya; Questioning Techniques; Reading Comprehension; Textbook Content; Textbooks

An Analysis of Reading Comprehension Questions in Kenyan English Textbooks - Beerwinkle, Andrea; McKeown, Debra (An Analysis of Reading Comprehension Questions in Kenyan English Textbooks, 2021)
Reading comprehension is a valued skill worldwide. In Kenya, reading comprehension is taught through English textbooks. In this study, we analyzed the reading comprehension exercises in the English textbooks for Standard 4 and Standard 5. Results indicate a strong emphasis on questions that can be answered directly from the text and questions that connect to a reader's background. A brief discussion of content is provided as well as limitations and future directions.
Keywords: Elementary Education; English (Second Language); Foreign Countries; Grade 4; Grade 5; Kenya; Questioning Techniques; Reading Comprehension; Textbook Content; Textbooks

Promoting effective early grade reading: the case study of primary teachers' preparation programmes in Kenya. - Wawire, Brenda Aromu (Promoting effective early grade reading: the case study of primary teachers' preparation programmes in Kenya., 2021)
This study explores how the primary school teacher preparation curriculum prepares pre‐service teachers to teach reading in lower primary schools in Kenya. High‐quality reading teacher preparation is among the critical aspects that need to be addressed in order to curb the literacy challenges faced by early grade students living in low‐resource contexts. In this article, a case study of the Kenyan Primary Teacher Preparation programme is presented using data from the primary teacher education syllabus [PTES] and interviews of pre‐service and in‐service teachers from Western Kenya. Findings suggest that the pre‐service teaching programmes curriculum has limited content and pedagogical content knowledge (PCK) critical to equip teachers to teach emergent readers from multilingual contexts. The curriculum content needs to be revamped to include more core literacy components and early literacy PCK, practicum apprenticeship specific for the needs of early grade literacy instructors, and content on early literacy formative and summative assessment. Suggestions and recommendations are offered on how to restructure the Kenya primary teacher programmes to ensure high‐quality reading teachers' preparation.
Keywords: Educational quality; Emergent literacy; Kenya; Primary school teachers; Reading (Primary); Teacher education

Promoting Effective Early Grade Reading: The Case Study of Primary Teachers' Preparation Programmes in Kenya - Wawire, Brenda Aromu (Promoting Effective Early Grade Reading: The Case Study of Primary Teachers' Preparation Programmes in Kenya, 2021)
This study explores how the primary school teacher preparation curriculum prepares pre-service teachers to teach reading in lower primary schools in Kenya. High-quality reading teacher preparation is among the critical aspects that need to be addressed in order to curb the literacy challenges faced by early grade students living in low-resource contexts. In this article, a case study of the Kenyan Primary Teacher Preparation programme is presented using data from the primary teacher education syllabus [PTES] and interviews of pre-service and in-service teachers from Western Kenya. Findings suggest that the pre-service teaching programmes curriculum has limited content and pedagogical content knowledge (PCK) critical to equip teachers to teach emergent readers from multilingual contexts. The curriculum content needs to be revamped to include more core literacy components and early literacy PCK, practicum apprenticeship specific for the needs of early grade literacy instructors, and content on early literacy formative and summative assessment. Suggestions and recommendations are offered on how to restructure the Kenya primary teacher programmes to ensure high-quality reading teachers' preparation.
Keywords: Apprenticeships; Curriculum; Elementary School Teachers; Emergent Literacy; Foreign Countries; Formative Evaluation; Kenya; Literacy Education; Multilingualism; Pedagogical Content Knowledge; Practicums; Preservice Teacher Education; Primary Education; Student Diversity; Summative Evaluation; Teacher Competencies; Teacher Education Programs

An Analysis of the Learning Performance Gap between Urban and Rural Areas in Subsaharan Africa - Sumida, Sugata; Kawata, Keisuke (An Analysis of the Learning Performance Gap between Urban and Rural Areas in Subsaharan Africa, 2021)
The learning gap between urban and rural areas is a persistent problem in many sub-Saharan African countries. Previous studies have found that the urban-rural learning gap is attributed to the fact that student characteristics and school resources are different in urban and rural areas. Our study updates this finding by using the latest dataset and further examines the changes in the attributed sources over time. Using 15 educational systems in sub-Saharan Africa, we examined 4 potential sources of the gap: student, family, teacher, and school characteristics. Our results reveal that the urban-rural learning gap in recent years is attributed mostly to differences in school and family characteristics. We also found that the attribution remains the same over time from 2004 to 2011 and that the attribution to family characteristics' differences became slightly greater than the one to school characteristics' differences.
Keywords: Achievement Gap; Botswana; Elementary School Students; Family Characteristics; Foreign Countries; Grade 6; Institutional Characteristics; Kenya; Lesotho; Malawi; Mauritius; Mozambique; Namibia; Performance Factors; Reading Achievement; Rural Urban Differences; Seychelles; South Africa; Student Characteristics; Swaziland; Tanzania; Teacher Characteristics; Uganda; Zambia; Zimbabwe

How can reading by age 10 fix the learning crisis? - Save the Children (Save the Children International, 2021)
Every child requires basic foundational literacy skills to open up life choices and opportunities

How can reading by age 10 fix the learning crisis? - Warren, Hollie (How can reading by age 10 fix the learning crisis?, 2021)

Learning equity requires more than equality: Learning goals and achievement gaps between the rich and the poor in five developing countries⋆. - Akmal, Maryam; Pritchett, Lant (Learning equity requires more than equality: Learning goals and achievement gaps between the rich and the poor in five developing countries⋆., 2021)
• The paper quantifies the extent to which achieving within country equality would bring countries closer to global equitygoals. • Equalizing grade attainment between rich and poor children leads to only modest progress. • Equalizing learning profiles results in larger gains that vary across countries. • Even with equality of schooling and learning, children are still far from mastering basic reading and math by 12−13. • Reaching equity goals will require more than closing rich-poor gaps, but progress in learning for all. Whereas the MDG was a simple schooling goal the Sustainable Development Goals (SDGs) have a number of targets for learning. Target 4.1 specifies not just that all children complete primary and secondary school but that this schooling leads to "relevant and effective learning outcomes" and Indicator 4.1.1 tracks progress goal using the proportion of children reaching "minimum proficiency" at early (grade 2/3), intermediate (primary complete) and late (end if lower secondary) stages of basic education with the aim that "all youth...achieve literacy and numeracy" (Target 4.6). We use the Annual Status of Education Report (ASER) data from India and Pakistan, and Uwezo data from Kenya, Tanzania, and Uganda that assess all children in a given age range, whether in school or not, on simple measures of learning in math, reading (local language), and English, to quantify how much achieving within country equality between the richest 20 percent and the poorest 40 percent in (a) grade attainment and (b) learning achievement by grade would contribute to an SDG-like global equity goal of universal numeracy and literacy for all children by age 12−13. We have three empirical findings. First, except in Kenya equalizing grade attainment between children from rich and poor households would lead to only modest progress in achieving universal numeracy, closing only between 8% (India) and 25 % (Pakistan) of the existing gap to universal literacy. Second, equalizing the learning profiles, that is, closing the gap in learning for children in the same grade between those from the poorest 40 percent of households and the richest 20 percent, would close between 16 % (Pakistan and Uganda) and 34 % (India) of the gap to universal numeracy, and between 13 % (Uganda) and 44 % (India) of the gap to universal literacy. Third, even with complete equality in grade attainment and learning achievement with children from the richest 20 percent children from poorer households still be far from the equity goal of universal numeracy and literacy, as even children from the richest 20 percent of households are far from universal mastery of basic reading and math by ages 12−13. In the currently low performing countries achieving universal literacy and numeracy to reach even a minimal proficiency of global equity goal will require more than just closing the rich-poor learning gap, it will take progress in learning for all.
Keywords: Achievement gap; Achievement motivation in children; Basic education; Global method of teaching; Literacy; Numeracy; Sustainable Development Goals (United Nations)

On context and second language acquisition: The rural urban dichotomy in Cameroon - Mbibeh, Louis (Advances in Language and Literary Studies, 2021)
The complexity of the linguistic environment in Cameroon raises the question of context and its role in the acquisition of another language. This paper draws a dichotomy between learners in such contexts considered rural and those regarded as urban or cosmopolitan. Using the irregular verb as a yardstick, an evaluation of the acquisition of irregular verb patterns by 80 final year primary school learners from 2 contexts in the Northwest Region of Cameroon was done. Oral and written tests were administered to check learners' acquisition of verb inflectional categories, verb tenses and general written and oral productions. The findings reveal similar trends in the acquisition of inflectional categories and verb tenses by learners in both contexts and divergent trends in general oral and written productions. For instance, learners in both contexts had similar challenges using the Vs, Ved and Ven inflections with a very low average frequency of 26% and with a high frequency of 67.2 % for the Ving and Vo inflections. Though learners in the urban centres had higher degrees of efficiency in oral productions, their counterparts in the rural areas had more challenges in verbal as against written productions. The paper concludes that second language acquisition is not a consequence of a unilateral context but a result of a plethora of other factors both within and without the learning environment with evident pedagogic implications for stakeholders in the second language acquisition industry.
Keywords: Acculturation; African Languages; Cameroon; Context Effect; Elementary School Students; English (Second Language); Foreign Countries; French; Interlanguage; Language Tests; Morphemes; Oral Language; Rural Urban Differences; Second Language Instruction; Second Language Learning; Teaching Methods; Verbs; Written Language

Assessing the Quality of Mathematics in Cameroon Primary School Textbooks and Its Implications to Learning - Atanga, Napthalin A. (North American Chapter of the International Group for the Psychology of Mathematics Education, 2021)
Mathematics textbooks for upper primary classes in the English Subsystem of Education in Cameroon were examined to determine the quality of mathematics in them and possible teacher knowledge fostered. The quality of mathematics in these textbooks is classified as medium and the dominant teacher knowledge fostered is common content knowledge. This is because the textbooks are full of accurate standard algorithms and mathematical definitions, yet lack the use of multiple strategies and representations. They also contain high proportion of mathematical explanations that are either partially accurate or accurate but incomplete. Textbooks with medium mathematical quality have high potentials of causing learners and teachers to be mathematically malnourished. [For the complete proceedings, see ED630060.]
Keywords: Cameroon; Educational Quality; Elementary School Mathematics; Foreign Countries; Grade 5; Grade 6; Mathematics Education; Textbook Content; Textbooks

Effects of Instructional Materials Used at the Community Learning Resource Centers on Adult Learners' Participation in Community Development Activities in Nyamira North Sub-County Kenya - Bella, Benjamin Obonyo; Koome, Peter; Kamuru, Susan (Effects of Instructional Materials Used at the Community Learning Resource Centers on Adult Learners' Participation in Community Development Activities in Nyamira North Sub-County Kenya, 2021)
This research sought to investigate the effects of instructional materials used at community resource centers on adult literacy learners in community development activities with a specific focus on Nyamira North Sub-County, Kenya. The study was guided by the constructivism theory of learning. It employed the descriptive survey design where a sample of 254 learners was drawn from a population of 492 adult learners in the study area using the stratified random sampling method. Questionnaires were administered to elicit information from the respondents. The collected data were analyzed using descriptive statistical methods. From the findings, there was a clear indication that textbooks and sewing machines were more available and adequately utilized. Other resources like computers, projectors, ovens, banana ripening chambers, and videos were least available and inadequate. Results further showed that most of the adult learners were involved in small-scale farming as their main economic activity with most of their products was selling them to the market in raw form. Some learners were also involved in natural resource management activities with the majority of them planting trees, water resources management, bridges, and path construction. The study recommended that to diversify the livelihoods of the communities in the study area, the Directorate of Adult Education should provide diverse instructional materials such as ICT facilities and equipment that which will impart value addition skills to the learners.
Keywords: Adult Education; Adult Literacy; Agricultural Occupations; Community Programs; Computers; Educational Resources; Equipment; Foreign Countries; Instructional Materials; Job Skills; Kenya; Natural Resources; Skill Development; Textbooks; Video Technology

Shouting in the Kenyan Space: Can Spaceteam ESL Improve L2 Learners' Oral Reading Fluency in English? - Cardoso, Walcir; Waddington, David; Sénécal, Anne-Marie; Kiforo, Enos; Anyango, Linah; Karanja, Dickson K. (Shouting in the Kenyan Space: Can Spaceteam ESL Improve L2 Learners' Oral Reading Fluency in English?, 2021)
This study examined the effects of Spaceteam ESL, a digital shouting game, on the development of oral reading fluency (ORF) among 71 English as a second language (ESL) students in three primary and secondary schools in Mombasa, Kenya. Following a mixed-methods approach for data collection and analysis, we pre-tested and post-tested the participants on their ability to read aloud efficiently (speed) and accurately (accuracy) in three tasks: (1) phrases extracted from the game; (2) phrases not related to the game; and (3) a short anecdote. Paired-samples t-tests results revealed that, as hypothesized, participants who played Spaceteam ESL improved their ORF on measures of speed on all tasks, possibly because of the fast-paced nature of the game. However, no significant differences were observed in terms of accuracy due to a ceiling effect: the participants had already mastered the intricacies of the letter-to-sound rules of English orthography. Overall, these findings corroborate our hypothesis that some of the affordances of Spaceteam ESL (e.g., focus on speed reading, multiple and varied opportunities for practice) could contribute to the development of some aspects of oral reading fluency.
Keywords: Accuracy; Computer Games; Educational Games; Elementary School Students; English (Second Language); Foreign Countries; Handheld Devices; Instructional Effectiveness; Kenya; Oral Reading; Reading Fluency; Second Language Instruction; Secondary School Students; Speed Reading; Student Attitudes; Telecommunications

Examining Emergency Remote Teaching Using the Community of Inquiry Framework: Lecturer Experiences in a Kenyan University - Chiroma, Jane Adhiambo; Meda, Lawrence; Waghid, Zayd (Examining Emergency Remote Teaching Using the Community of Inquiry Framework: Lecturer Experiences in a Kenyan University, 2021)
The COVID-19 global pandemic has forced many universities worldwide to switch from face-to-face classes to Emergency Remote Teaching (ERT) to allow students to continue learning. Using the Community of Inquiry framework, this study aimed to examine a group of lecturers' experiences of ERT at a university in Kenya. The study was conducted using a qualitative case study design within an interpretive paradigm. Ten lecturers were purposively selected to participate in semi-structured interviews. The findings suggest that these lecturers had established teaching presence, social presence, and cognitive presence to enhance students' learning experiences during the time they engaged in ERT. The Community of Inquiry was found to be a useful framework by the researchers for lecturers to use in order to rethink, organize, and guide ERT at the university, which was the site of the study. This study has practical implications for course designers, researchers, and students at universities and other educational institutions concerning curriculum re-design using a CoI as a framework.
Keywords: COVID-19; College Faculty; Communities of Practice; Curriculum Design; Distance Education; Educational Change; Foreign Countries; Guidelines; Integrated Learning Systems; Kenya; Learning Experience; Pandemics; Teacher Attitudes; Teacher Student Relationship; Teaching Methods; Technological Literacy

Information and Communication Technology Reading Interventions: A Scoping Review - Dean, Jessica; Pascoe, Michelle; le Roux, Jane (Information and Communication Technology Reading Interventions: A Scoping Review, 2021)
Background: Information and communication technology (ICT) reading interventions can help children with reading difficulties, especially those in resource-constrained environments who otherwise might not have support. Objectives: (1) Provide an overview of ICT reading interventions used globally with primary school children. (2) Provide further information on the subset of studies conducted in majority world countries, describing the interventions used, their impact on reading and challenges faced. Method: A scoping review was used with a search strategy that yielded a total of 49 studies for inclusion in the main review (Objective 1), and a subset of five studies undertaken in the majority world (Objective 2). Results: Most published studies (93.88%, 46 studies) demonstrated positive outcomes of ICT reading interventions on learners' reading. Well-researched programmes with demonstrated effectiveness included GraphoGame, ABRACADABRA, Reading RACES and Chassymo. Only five studies (10.2%) were conducted in the majority world, but all reported in this subset described positive literacy gains through ABRACADABRA and GraphoGame. Conclusion: There is a growing evidence base of ICT reading interventions that could be helpful in addressing the reading crisis in South Africa. Programmes such as ABRACADABRA and GraphoGame demonstrate effectiveness in a variety of contexts and may have a role to play in addressing the reading challenges faced by children in South Africa. Contribution: The review highlighted evidence supporting the use of ICT reading interventions. Evidence of such approaches in South Africa (and other majority world countries) remains limited and requires further evaluation of both existing and innovative, locally developed interventions.
Keywords: Computer Uses in Education; Developing Nations; Educational Research; Elementary School Students; Foreign Countries; India; Intervention; Kenya; Program Effectiveness; Reading Difficulties; Reading Programs; South Africa; Tanzania; Zambia

POST-INDEPENDENCE BASIC EDUCATION IN KENYA: AN HISTORICAL ANALYSIS OF CURRICULUM REFORMS. - Inyega, Justus O.; Arshad-Ayaz, Adeela; Naseem, M. Ayaz; Mahaya, Evans W.; Elsayed, Dalia (POST-INDEPENDENCE BASIC EDUCATION IN KENYA: AN HISTORICAL ANALYSIS OF CURRICULUM REFORMS., 2021)
This article presents a critical review of the education system and curriculum reforms in basic education in Kenya from independence in 1963 to date. It presents a philosophical and pragmatic basis for content review and the curriculum reform process. Data collection involved a critical review of relevant literature; including several curriculum reform documents. Based on the literature review and documentary analysis, there is overwhelming evidence that radical changes have resulted in the Kenyan education system from several curriculum reviews and major reforms in response to the changing needs of the Kenyan society. The new curriculum currently under implementation is the Competency-Based Curriculum (CBC). Over the years, there have been minimal changes in the content, scope, and sequence of the basic education curriculum. This article presents salient changes in the Kenyan education system and presents recommendations that may have significant implications for future curriculum reforms that can potentially improve learning outcomes.
Keywords: Basic education; Curriculum; Curriculum change; Educational change; Historical analysis; Kenya

Post-Independence Basic Education in Kenya: An Historical Analysis of Curriculum Reforms - Inyega, Justus O.; Arshad-Ayaz, Adeela; Naseem, M. Ayaz; Mahaya, Evans W.; Elsayed, Dalia (Post-Independence Basic Education in Kenya: An Historical Analysis of Curriculum Reforms, 2021)
This article presents a critical review of the education system and curriculum reforms in basic education in Kenya from independence in 1963 to date. It presents a philosophical and pragmatic basis for content review and the curriculum reform process. Data collection involved a critical review of relevant literature; including several curriculum reform documents. Based on the literature review and documentary analysis, there is overwhelming evidence that radical changes have resulted in the Kenyan education system from several curriculum reviews and major reforms in response to the changing needs of the Kenyan society. The new curriculum currently under implementation is the Competency-Based Curriculum (CBC). Over the years, there have been minimal changes in the content, scope, and sequence of the basic education curriculum. This article presents salient changes in the Kenyan education system and presents recommendations that may have significant implications for future curriculum reforms that can potentially improve learning outcomes.
Keywords: Competency Based Education; Curriculum Development; Curriculum Implementation; Educational Change; Educational History; Elementary Secondary Education; Foreign Countries; Foreign Policy; Formative Evaluation; Higher Education; Kenya; Outcomes of Education; Preschool Education; Self Determination; Social Change; Special Needs Students; Student Evaluation; Summative Evaluation

Stakeholder Capacity Building in Monitoring and Evaluation and Performance of Literacy and Numeracy Educational Programme in Public Primary Schools in Nairobi County, Kenya - Karimi, Stella Silas; Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (Stakeholder Capacity Building in Monitoring and Evaluation and Performance of Literacy and Numeracy Educational Programme in Public Primary Schools in Nairobi County, Kenya, 2021)
To create a radical change within the educational system in public primary schools in Kenya, there is need to invest more on stakeholder capacity building specifically on monitoring and evaluation educational programme. The purpose of this article is to establish the extent to which stakeholder capacity building for monitoring and evaluation influence performance of literacy and numeracy educational programme. Despite numerous initiatives by key stakeholders to better performance of pupils little has been achieved. A descriptive survey research design and correlation design was adapted. Data collected from the respondents by use of questionnaires and interview guide from target population of 2052 and a sample size of 335. Data was analyzed using SPSS version 25 and results presented in tables and figures. Pearson moment correlation coefficient (r) were computed. The coefficient determination of R[subscript 2] is 0.456 this is an indicator that R[subscript 2] was the coefficient of determination of this model and it depicted that data collection explained 46%. The remaining 54% was explained by other factors. The overall F statistics 233.446 with p-0.00b<0 0.05 implying there is statistically significant relationship between stakeholder capacity building and performance of literacy and numeracy educational programme. The research suggests that stakeholder capacity building is part of the Participatory Monitoring and Evaluation process, so it must be observed at all stages to ensure educational programme are implemented to the latter by bringing on board all the key stakeholders in education and particularly in literacy and numeracy skills aspects.
Keywords: Administrator Attitudes; Capacity Building; Correlation; Counties; Elementary School Students; Foreign Countries; Kenya (Nairobi); Literacy Education; Models; Numeracy; Program Effectiveness; Program Evaluation; Seminars; Stakeholders; Teacher Attitudes; Teaching Methods; Workshops

Mobile Learning during School Disruptions in Sub-Saharan Africa - Kizilcec, René F.; Chen, Maximillian; Jasinska, Kaja K.; Madaio, Michael; Ogan, Amy (Mobile Learning during School Disruptions in Sub-Saharan Africa, 2021)
School closures due to teacher strikes or political unrest in low-resource contexts can adversely affect children's educational outcomes and career opportunities. Phone-based educational technologies could help bridge these gaps in formal schooling, but it is unclear whether or how children and their families will use such systems during periods of disruption. We investigate two mobile learning technologies deployed in sub-Saharan Africa: a text-message-based application with lessons and quizzes adhering to the national curriculum in Kenya (N = 1.3 million), and a voice-based platform for supporting early literacy in Côte d'Ivoire (N = 236). We examine the usage and beliefs surrounding unexpected school closures in each context via system log data and interviews with families about their motivations and methods for learning during the disruption. We find that mobile learning is used as a supplement for formal and informal schooling during disruptions with equivalent or higher intensity, as parents feel responsible to ensure continuity in schooling.
Keywords: Access to Education; Children; Cote d'Ivoire; Developing Nations; Educational Technology; Electronic Learning; Elementary Secondary Education; Emergency Programs; Emergent Literacy; Family Involvement; Foreign Countries; Handheld Devices; Informal Education; Kenya; Learning Analytics; School Closing; Supplementary Education; Teacher Strikes; Technology Integration; Telecommunications; Violence

When Boys Read Better than Girls: The Correlation between Gender Disparities in Schooling Participation and Reading Performance in Sub-Saharan Africa - Kyei, Pearl (When Boys Read Better than Girls: The Correlation between Gender Disparities in Schooling Participation and Reading Performance in Sub-Saharan Africa, 2021)
Sub-Saharan African countries have made remarkable strides in closing the gender gap in primary enrolment and more girls than ever are attending school. With the existing gender differentials in youth literacy rates, an important question is whether they are learning as well as their male classmates. This article explored factors that contribute to gender gaps in reading for sixth-grade pupils from 61 396 pupils from 15 countries in the third evaluation of the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ III). Within-class sex differences in test score performance are estimated using ordinary least squares regression models. This is done by analysing the factors associated with female learning that inhibit school attendance and class participation. The results show a female disadvantage in reading in a little under half of the countries studied, which differs from the consistently observed female reading advantage in other parts of the world. Factors that prevent girls from fully attending and participating in school such as domestic responsibilities and hostile school environments explain part of the female disadvantage in reading, indicating that households and schools need to ensure that girls can attend and participate fully in their classes without distractions or fear.
Keywords: Achievement Gap; Attendance; Botswana; Educational Environment; Elementary School Students; Foreign Countries; Gender Differences; Grade 6; Kenya; Lesotho; Literacy; Malawi; Mauritius; Mozambique; Namibia; Psychological Patterns; Reading Achievement; Reading Skills; Sex Role; Seychelles; South Africa; Student Participation; Swaziland; Tanzania; Uganda; Zambia; Zimbabwe

Educators' Intentions for Learning in Virtual School Garden Exchanges: A Comparison with the Aims of Education for Sustainable Development - Lochner, Johanna (Educators' Intentions for Learning in Virtual School Garden Exchanges: A Comparison with the Aims of Education for Sustainable Development, 2021)
It is widely recognized that education plays a key role in addressing current global challenges. Education for Sustainable Development (ESD) combines local actions with global thinking. In Virtual School Garden Exchanges (VSGEs) primary and secondary students from the Global South and North interact and communicate digitally about their school gardens. This study focuses on educators' expectations regarding learning outcomes of VSGEs and possible parallels with ESD and Virtual Exchanges (VEs) in general. A qualitative content analysis of 23 semi-structured interviews with educators engaged in 18 VSGEs was conducted. Even though the VSGEs took different individual approaches, the analysis revealed many commonalities in the respondents' intentions: amongst other things, educators were aiming to promote knowledge about gardening and food, horticultural and cooperation competencies, and values such as solidarity. Nevertheless, some educators feared that VSGEs might also have some negative effects. The results show parallels with the aims of ESD and VEs.
Keywords: Argentina; Competence; Computer Mediated Communication; Cooperation; Developed Nations; Developing Nations; Educational Objectives; Elementary School Teachers; Environmental Education; Food; Foreign Countries; Gardening; Germany; Greece; India; Intention; International Educational Exchange; Kenya; Mexico; Peru; Secondary School Teachers; Sustainable Development; Teacher Attitudes; Uganda; United Kingdom (England); United States; Values; Virtual Classrooms

Mathematics Teaching and Professional Learning in Sub-Sahara Africa. Research in Mathematics Education - Luneta, Kakoma (Research in Mathematics Education, 2021)
This book represents a crop of wide-ranging research conducted by renown scholars in sub-Sahara Africa revolving around mathematics teaching and professional development programs for mathematics teachers. The research-based proposals and actual how-to-conduct professional development initiatives that enhance effective mathematics instruction are rooted in teacher input and informed by learners errors and misconceptions. The book provides a comprehensive snapshot on mathematics teaching, learning and effective professional development programmes for mathematics teachers in sub-Sahara Africa. It is the only research output that advances and disseminates issues of mathematics education and research in the region with input from South Africa, Kenya, Rwanda, Uganda, Malawi, Namibia, Lesotho, Ethiopia and Zimbabwe.
Keywords: Academically Gifted; Algebra; Attention; Certification; Coaching (Performance); Communities of Practice; Cultural Influences; Culturally Relevant Education; Educational Change; Educational Improvement; Educational Technology; Elementary School Mathematics; Ethiopia; Faculty Development; Foreign Countries; Grade 12; Kenya; Lesotho; Malawi; Manipulative Materials; Mathematics Education; Mathematics Teachers; Mentors; Models; Namibia; Number Concepts; Preservice Teachers; Problem Based Learning; Problem Solving; Rural Areas; Rwanda; Science Instruction; Secondary School Mathematics; South Africa; Story Telling; Teacher Collaboration; Teacher Educators; Teacher Qualifications; Teaching Methods; Technology Uses in Education; Uganda; Visualization; Zimbabwe

Mathematics Teaching and Professional Learning in Sub-Sahara Africa. Research in Mathematics Education - Luneta, Kakoma (Research in Mathematics Education, 2021)
This book represents a crop of wide-ranging research conducted by renown scholars in sub-Sahara Africa revolving around mathematics teaching and professional development programs for mathematics teachers. The research-based proposals and actual how-to-conduct professional development initiatives that enhance effective mathematics instruction are rooted in teacher input and informed by learners errors and misconceptions. The book provides a comprehensive snapshot on mathematics teaching, learning and effective professional development programmes for mathematics teachers in sub-Sahara Africa. It is the only research output that advances and disseminates issues of mathematics education and research in the region with input from South Africa, Kenya, Rwanda, Uganda, Malawi, Namibia, Lesotho, Ethiopia and Zimbabwe.
Keywords: Academically Gifted; Algebra; Attention; Certification; Coaching (Performance); Communities of Practice; Cultural Influences; Culturally Relevant Education; Educational Change; Educational Improvement; Educational Technology; Elementary School Mathematics; Ethiopia; Faculty Development; Foreign Countries; Grade 12; Kenya; Lesotho; Malawi; Manipulative Materials; Mathematics Education; Mathematics Teachers; Mentors; Models; Namibia; Number Concepts; Preservice Teachers; Problem Based Learning; Problem Solving; Rural Areas; Rwanda; Science Instruction; Secondary School Mathematics; South Africa; Story Telling; Teacher Collaboration; Teacher Educators; Teacher Qualifications; Teaching Methods; Technology Uses in Education; Uganda; Visualization; Zimbabwe

Deaf Cosmopolitanism: Calibrating as a Moral Process - Moriarty, Erin; Kusters, Annelies (Deaf Cosmopolitanism: Calibrating as a Moral Process, 2021)
Cosmopolitanism theory was mostly developed separately from the study of multilingualism: while language is central to cosmopolitanism as a practice, only a few scholars focusing on cosmopolitanism have taken a language-centred approach. We further theorise the relationship between cosmopolitanism and translingual practice with our focus on "morality" in relation to the use of the semiotic repertoire. The use of resources of the semiotic repertoire in translingual practice is infused with morality in that resources (such as languages, individual signs, mouthing, fingerspelling alphabets) are value laden and have particular associations or meanings in a given context. We explore and define deaf cosmopolitanism by offering examples from three international settings: deaf tourism in Bali, a sign language conference in Brazil, and a Bible translation centre in Kenya. Deaf people engaging in international mobilities align in communication by what they call 'calibrating'. In this process, mobile deaf people quickly adopt new semiotic resources by engaging in rapid, immersive and informal (sign) language learning, acquiring (bits of) new sign languages, mouthing, written words, and fingerspelling alphabets, and including them in their practice of calibrating. Our analysis centres language ideologies about these practices, demonstrating moral ideas about what strategies and semiotic resources are most appropriate in specific contexts and/or with/by whom.
Keywords: Alphabets; Biblical Literature; Brazil; Conferences (Gatherings); Correlation; Cross Cultural Studies; Deafness; Finger Spelling; Foreign Countries; Global Approach; Indonesia; Informal Education; Kenya; Moral Values; Second Language Learning; Semiotics; Sign Language; Tourism; Translation; Written Language

Determinants of Attendance in Alternative Primary Schools in Mathare Slum, Nairobi, Kenya. - Njihia, Mukirae; Nkonge, Winniejoy G.; Nderitu, John K. (Determinants of Attendance in Alternative Primary Schools in Mathare Slum, Nairobi, Kenya., 2021)
This study sought to establish the influence of home-based and school-based factors on pupils' school attendance in Alternative Primary Schools in Mathare Constituency, Nairobi. The study employed the correlational design. The Study population was 18,000 pupils, 58 head teachers and 604 teachers. The sample size comprised of 12 head teachers (20%), 60 teachers (10%) and 317 pupils (1.8%). The study established that there was a strong positive and statistically significant correlation between home background characteristics and pupils' school attendance in Alternative Primary Schools (r = .935, p = .012) at alpha 0.05 level of statistical significance. Further, a strong negative and statistically significant (r = -.662, p = .033) correlation at alpha 0.05 level of confidence exists between family size and pupils' school attendance in Alternative Primary Schools.
Keywords: Kenya; Primary education; Primary schools; School attendance; Teacher attitudes

Effects of Performance Ranking on Students' Voice and Agency in the Mathematics Classroom - Njiru, Samson Murithi; Karuku, Simon (Effects of Performance Ranking on Students' Voice and Agency in the Mathematics Classroom, 2021)
The modalities of performance ranking in high stakes testing to a greater extent affect Mathematics teaching and learning. While performance ranking has the potential of being a critical catalyst in the process of making Mathematics classrooms a place of positive competition, it fails to balance the most crucial aspects in Mathematics discourses-the voice and agency of teachers and students. The proactive engagement of all students and teachers equitably with the process of Mathematics teaching and learning is a necessary condition for ensuring excellent students Mathematics learning outcomes. The purpose of the study was to investigate the effects of performance ranking on voice and agency in Mathematics teaching and learning in secondary schools in Embu, Kenya. The study employed a qualitative research approach. Six teachers and eight students were randomly sampled for interviews, while three teachers and eighteen students were engaged in focus group discussions. The data analyzed demonstrated that top ranked students become powerful independent learners who are capable of critiquing work presented to them by their teachers while low ranked students are guided as to whom to seek help from by the performance ranking data. This paper recommends that performance ranking should be used as a tool to give students voice and agency by ranking students on the basis of marks scored on continuous assessment tests, students' entry mark and value addition.
Keywords: Competition; Foreign Countries; Kenya; Learner Engagement; Mathematics Achievement; Mathematics Education; Personal Autonomy; Private Schools; Public Schools; Secondary School Students; Student Attitudes

Evaluating Teachers' Learning, Perceptions, and Cultural Differences Following Professional Development for Early Literacy Software - Uribe-Banda, Constanza; Wood, Eileen; Gottardo, Alexandra; Wade, Anne; Iminza, Rose; WaGiokõ, Maina (Evaluating Teachers' Learning, Perceptions, and Cultural Differences Following Professional Development for Early Literacy Software, 2021)
The present study examined the impact of professional development training on Canadian and Kenyan teachers' confidence, comfort, and perceptions of their abilities to teach early literacy skills in the primary or elementary grades. Data were collected prior to and following training on how to integrate early literacy software as part of ongoing in-class instruction. Domain and technology constructs consistent with Mishra and Koehler's (2006) technology integration model were assessed, as were perceptions related to delivery pacing. Overall, outcomes reflected more similarities than differences across the two groups of teachers. Limitations in foundational knowledge regarding concepts specific to early literacy were evident in both groups, despite higher levels of perceived confidence in Kenyan teachers compared to Canadian teachers in some content areas. Perceived comfort using technology and teaching with technology were highly correlated, with no differences observed across teacher groups. Pacing was perceived to be faster for Kenyan teachers compared to Canadian teachers. Implications for professional development in this domain are discussed.
Keywords: Canada; Computer Software; Cultural Differences; Educational Technology; Elementary School Teachers; Emergent Literacy; Faculty Development; Foreign Countries; Kenya; Teacher Attitudes; Teacher Evaluation

The role of vocabulary and decoding language skills in reading comprehension: a cross-linguistic perspective. - Wawire, Brenda Aromu; Zuilkowski, Stephanie Simmons (The role of vocabulary and decoding language skills in reading comprehension: a cross-linguistic perspective., 2021)
The present study explored the role of vocabulary and decoding skills in predicting reading comprehension, utilizing data from 322 first- grade children from four elementary schools in Kenya. The children were administered a comprehensive battery of tests to assess pseudo-word reading skills, oral reading fluency, reading comprehension, and receptive vocabulary in English and Kiswahili. The results showed that receptive vocabulary and pseudo-word reading in English played a significant role in English reading comprehension. Kiswahili decoding explained a statistically significant unique variance of Kiswahili reading comprehension. An examination of the cross-linguistic variability showed that pseudo-word decoding in English and Kiswahili explained unique variance in reading comprehension cross-linguistically, while receptive vocabulary did not explain additional variance in reading comprehension across languages. These results add to the important evidence of receptive language skills and decoding skills in reading comprehension among multilingual children from low-middle income countries.
Keywords: Bilingual education; Bilingualism; Comprehension; Linguistic input; Second language acquisition

The Role of Vocabulary and Decoding Language Skills in Reading Comprehension: A Cross-Linguistic Perspective - Wawire, Brenda Aromu; Zuilkowski, Stephanie Simmons (The Role of Vocabulary and Decoding Language Skills in Reading Comprehension: A Cross-Linguistic Perspective, 2021)
The present study explored the role of vocabulary and decoding skills in predicting reading comprehension, utilizing data from 322 first- grade children from four elementary schools in Kenya. The children were administered a comprehensive battery of tests to assess pseudo-word reading skills, oral reading fluency, reading comprehension, and receptive vocabulary in English and Kiswahili. The results showed that receptive vocabulary and pseudo-word reading in English played a significant role in English reading comprehension. Kiswahili decoding explained a statistically significant unique variance of Kiswahili reading comprehension. An examination of the cross-linguistic variability showed that pseudo-word decoding in English and Kiswahili explained unique variance in reading comprehension cross-linguistically, while receptive vocabulary did not explain additional variance in reading comprehension across languages. These results add to the important evidence of receptive language skills and decoding skills in reading comprehension among multilingual children from low-middle income countries.
Keywords: African Languages; Decoding (Reading); Developing Nations; Elementary School Students; English (Second Language); Foreign Countries; Grade 1; Intelligence Tests; Kenya; Language Skills; Multilingualism; Native Language; Peabody Picture Vocabulary Test; Predictor Variables; Public Schools; Reading Comprehension; Reading Fluency; Receptive Language; Rural Schools; Second Language Learning; Transfer of Training; Vocabulary Development; Young Children

The evolution of gender gaps in numeracy and literacy between childhood and young adulthood - Borgonovi, Francesca; Choi, Alvaro; Paccagnella, Marco (Economics of Education Review, 2021)
Numeracy and literacy are important foundation skills which command significant wage premia in modern labour markets. The existence of gender diﬀerences in these skills is therefore of potential concern, and has spurred a large amount of research, especially with respect to numeracy skills. Still, little is known about the moment in which such gaps emerge, how they evolve, and if this evolution diﬀers across countries. We use data from large scale international assessments to follow representative samples of birth-cohorts over time, and analyse how gender gaps in numeracy and literacy evolve from age 10 to age 27. We ﬁnd that the advantage of boys in numeracy is small at age 10, but grows considerably between age 15 and 27. The gender gap in literacy follows a very diﬀerent pattern: it is small at age 10, large and in favour of girls at age 15, and negligible by age 27.

Mapping Education Data in Sub-Saharan Africa - Lawson, Laté; Heady, Lucy (2021)

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)

The Early Childhood Education Act, 2021 - Republic of Kenya (2021)

Placing Blame or a Call to Action? An Analysis of Uwezo in the Kenyan Press - Monk, Jeremy (Placing Blame or a Call to Action? An Analysis of Uwezo in the Kenyan Press, 2020)
Citizen-led assessments were developed in the mid-2000s to gather evidence on children's learning outcomes following the rapid increase in primary student enrolment in the developing world. Integral to their philosophy is social accountability and community engagement. While most large-scale assessments focus on test-based accountability to promote policy shifts, citizen-led assessments, utilizing the information-accountability causal chain, theorize that information of low learning outcomes, disseminated widely, will engage stakeholders in activities and debates, ultimately leading to improvements in education quality and service delivery. This paper examines Uwezo, the oldest citizen-led assessment in East Africa, and its portrayal in the Kenyan print media. I explore whether discourse concerning Uwezo exposes education quality issues while promoting citizen engagement and how Uwezo's social accountability philosophy is used in public discourse through the lens of political evolutionary mechanisms. I find that Uwezo's findings were prominently discussed beginning in 2013, but that shock value of low learning levels has since decreased. Moreover, public discourse has highlighted cross-national and provincial/county comparisons in achievement levels while focusing on blaming teachers and the education system's culture. Although Uwezo has succeeded in disseminating its findings widely in Kenya, there is minimal engagement in public discourse with its social accountability and community engagement philosophy and discourse does not promote citizen action on a national level. As Uwezo has become a respected education policy player in East Africa, and globally, it must find ways to engage communities to act upon its findings to directly improve education quality.
Keywords: Academic Achievement; Access to Education; Accountability; Achievement Tests; African Culture; African Languages; Citizen Participation; Community Involvement; Discourse Analysis; Educational Improvement; Educational Philosophy; Educational Policy; Educational Quality; Elementary Secondary Education; English (Second Language); Evaluation Methods; Foreign Countries; Information Dissemination; Kenya; News Reporting; Newspapers; Numeracy; Outcomes of Education; Second Language Learning; Social Responsibility; Web Sites

From the Minds of Adolescents: What Has Worked for Them in an Education Intervention in the Slums of Nairobi. - Abuya, Benta A.; Muhia, Nelson (From the Minds of Adolescents: What Has Worked for Them in an Education Intervention in the Slums of Nairobi., 2020)
This paper highlights findings from the, 'Advancing learning outcomes for transformational change (A LOT-Change), whose goal was to increase efforts towards securing the future of children living in urban informal settlements. The intervention was implemented in Korogocho and Site 2 respectively. This paper looks at the narratives from girls, boys and their parents and seeks to answer the question, "From the minds of adolescents: What has worked for them in an education intervention in the slums of Nairobi. Qualitative data comes from the qualitative component of the endline evaluation study that was collected in July and August 2018, by the African Population and Health Research Center (APHRC). Findings from this study done by APHRC show that: scores in numeracy skills and literacy skills improved, improved selfconfidence, which enabled girls to model the way in their schools and communities. Aspirations for school and higher education improved as girls and boys wanted to go beyond primary school. Communication improved across the board girls and boys, together with their parents. Girls and boys gained the confidence to speak up due to the knowledge gained out of the motivational talks within the leadership component. Overall, this paper reinforces the importance of young people having a voice to speak up on programs that affect their lives.
Keywords: Africans; Elementary and Secondary Schools; Nairobi (Kenya); Secondary education; Slums; Squatter settlements; Teenagers; Transformative learning

Effects of Teacher Mentoring on the Classroom Practices of Lower Grade Primary School Teachers in Kwale County, Kenya - Muraya, Daniel Ngaru; Wairimu, Esther Nyaguthii (Effects of Teacher Mentoring on the Classroom Practices of Lower Grade Primary School Teachers in Kwale County, Kenya, 2020)
Teacher classroom practices have been identified as the key contributing factor to the low learning outcomes of primary school grades in Kenya. Teacher mentoring has the potential to improve classroom practices and this study sought to determine its effects on the classroom practices of primary school teachers in Kwale County, Kenya. Using One Group Repeated Measures Quasi-Experimental Design, one cohort of 40 teachers in 22 public primary schools was mentored for 20 months, from May 2016 to October 2018. A classroom observation tool was used in data collection during this period. The tool achieved a Cronbach's Alpha reliability coefficient of 0.84, 0.81 and 0.79 in 2016, 2017 and 2018 respectively. Data was analysed using Repeated Measures ANOVA and teacher mentoring had a statistically significant effect on mean classroom practice score at F=6.282, df=2, p=0.003. Significant mean differences were located between 2016 and 2017 in favour of 2017, and between 2016 and 2018 in favour of 2018. There was no significant mean difference between 2017 and 2018. In conclusion, teacher mentoring is effective in improving teacher classroom practices and should be integrated into the formal school programme in Kenya.
Keywords: Children; Classroom Techniques; Elementary School Teachers; Experienced Teachers; Foreign Countries; Grade 1; Grade 2; Grade 3; Instructional Improvement; Kenya; Learner Engagement; Mentors; Professional Development; Public Schools; Rural Schools; Teacher Collaboration; Teacher Effectiveness

Effects of collective promotion on the attainment of goals of basic education in english-speaking primary schools in Cameroon - Lyonga, Ngemunang Agnes Ngale; Fosso, Vivian Nzjofou (Journal of Science Education, 2020)
This study aims at investigating the effects of collective promotion on the attainment of literacy, numeracy, and essential life skills by primary school pupils and also to find out if the policy of collective promotion meets its objective of minimization of wastage in basic education. The study used written tests for pupils in the final class (Level II, class 6) to collect data in some selected English-speaking primary schools in Meme Division of Cameroon. Descriptive statistics and a one way ANOVA were used for analyzing data. The results revealed that the policy of collective promotion negatively affects the attainment of literacy, numeracy, and essential life skills of pupils in Kumba, Meme Division. Teachers who assisted in the study through personal communication with the researcher argued that collective promotion in basic education does not achieve its objective of minimizing wastage of educational resources; neither does it positively improve the literacy, numeracy, and essential life skills of pupils. This study recommends that the policy of collective promotion can be revisited and that focus be placed not only on minimizing wastage of resources but also on investing on quality education system so as to equip the would-be leaders of tomorrow with skills, knowledge, and attitudes which will make them functional and responsible citizens in their society.

SOCIAL MEDIA: AN IMPEDIMENT OR INSPIRATION TO IMPLEMENTATION OF DIGITAL LITERACY PROGRAMME IN KISII COUNTY, KENYA. - ABUYA, Teresa K.; MOCHAMA, Omosa E.; MAKWORO, Edwin O. (SOCIAL MEDIA: AN IMPEDIMENT OR INSPIRATION TO IMPLEMENTATION OF DIGITAL LITERACY PROGRAMME IN KISII COUNTY, KENYA., 2020)
Information Communication Technology (ICT) has revolutionized the way different sectors in developed and developing countries operate. They have pervaded modern societies as tools for transforming education systems, supporting economic development through the creation of new products and services, providing access to information and expertise to support improvements in agriculture, health and education, and connecting communities, teachers and students. Education sector in many countries have embraced ICT in research, teaching and learning. This has given rise to innovative learning pathways suited for different learners' situations. In initial adoption of ICT, 1higher education institutions were the first beneficiaries but in recent times, lower learning institutions like primary schools have also embraced the same. In Kenya, ICT Integration in Primary Education is one of the key flagship programmes borne out of government of Kenya's vision to make sure every pupil is prepared for today's digital world and to realize this, Digital Literacy Programme (DLP) was introduced for lower Primary schools in Kenya, particularly Class One Pupils. This study looks at the perceived ease of use and usefulness of social media by teachers of primary schools in Kisii County of Kenya and implementation success level of the Digital Learning Programme (DLP) by these teachers. Assessed was the teachers' view of technological complexity of social networking (SN) media. Survey research design was applied in the study. Random, proportionate and purposive sampling methods were used to select 250 primary schools and 276 teachers. Teachers of lower primary school segment of the Kenyan education system were surveyed using self-administered questionnaires on the frequency and ease of use of technology for Social Networking media such as Facebook, WhatsApp and Twitter and asked about their intensity of use. The results obtained showed that WhatsApp and Facebook use have a significantly increased impact on teachers' collaboration and engagement. Further, that perceived ease of use is a predictor of perceived usefulness and both of these have impact on social media use of teacher for educational purposes. Teachers accessed internet easily with the use of mobile smart phones which allows them to converse and interact with each other, to create, edit and share new forms of textual, visual and audio content. Those who use it frequently have made great attempts to implement Digital Learning Programme with ease whereby teachers use Teacher Digital Device (TDD) and learners use Learning Digital Device (LDD). This paper concludes that social media can be used as an educational tool to help teachers to collaborate and engage and recommends that the ministry of education embrace the uses of social media for teaching and learning.
Keywords: Computer literacy; Information & communication technologies; Kenya; Primary school teachers; Social media; Social media in education; Technological complexity; X Corp.

Effects of the COVID-19 pandemic on life scientists - Korbel, Jan O.; Stegle, Oliver (Genome Biology, 2020)

Teacher Quality and Mathematics Performance in Primary Schools in Kenya. - Barasa, Laura (Teacher Quality and Mathematics Performance in Primary Schools in Kenya., 2020)
This study examines the relationship between teacher quality and student achievement in Mathematics among Grade 4 pupils located in 91 urban primary schools and 181 rural primary schools in Kenya. We hypothesise that teacher quality indicators including teacher characteristics, teacher qualification comprising initial teacher education and teacher professional development and teacher classroom practices are significantly associated with student achievement. Our analysis is based on data from the 2012 World Bank and African Economic Research Consortium Service Delivery Indicators. We test our hypotheses by means of a multilevel regression. We find that teacher quality indicators have significant effects on Mathematics achievement in Kenya. Different effects between urban and rural primary schools are observed. The findings of this study underscore the need for policy makers to focus on improving teacher quality by strengthening initial teacher preparation and in-service programmes.
Keywords: Kenya; Mathematics teachers; Primary schools; Psychology of teachers; Rural families; Teacher development; Teacher effectiveness

Evaluating Subscore Uses across Multiple Levels: A Case of Reading and Listening Subscores for Young EFL Learners - Choi, Ikkyu; Papageorgiou, Spiros (Evaluating Subscore Uses across Multiple Levels: A Case of Reading and Listening Subscores for Young EFL Learners, 2020)
Stakeholders of language tests are often interested in subscores. However, reporting a subscore is not always justified; a subscore should provide reliable and distinct information to be worth reporting. When a subscore is used for decisions across multiple levels (e.g., individual test takers and schools), it needs to be justified for its reliability and distinctiveness at every relevant level. In this study, we examined whether reporting seven Reading and Listening subscores of the "TOEFL Primary"® test, a standardized English proficiency test for young English as a foreign language learners, could be justified for reporting at individual and school levels. We analyzed data collected in pilot administrations, in which 4776 students from 51 schools participated. We employed the classical test theory (CTT) based approaches of Haberman (2008) and Haberman, Sinharay, and Puhan (2009) for the individual and school-level investigations, respectively. We also supplemented the CTT-based approaches with a factor analytic approach for the individual level analysis and a multilevel modeling approach for the school-level analysis. The results differed across the two levels: we found little support for reporting the subscores at the individual level, but strong evidence supporting the added-value of the school-level subscores when the sample size for each school exceeds 50.
Keywords: Correlation; Decision Making; Elementary School Students; English (Second Language); Factor Analysis; Foreign Countries; Institutional Characteristics; Item Response Theory; Kenya; Language Proficiency; Language Tests; Listening Comprehension Tests; Profiles; Psychometrics; Reading Tests; Scores; Second Language Instruction; Second Language Learning; Test Reliability; Test of English as a Foreign Language

Evaluating Subscore Uses across Multiple Levels: A Case of Reading and Listening Subscores for Young EFL Learners - Choi, Ikkyu; Papageorgiou, Spiros (Evaluating Subscore Uses across Multiple Levels: A Case of Reading and Listening Subscores for Young EFL Learners, 2020)
Stakeholders of language tests are often interested in subscores. However, reporting a subscore is not always justified; a subscore should provide reliable and distinct information to be worth reporting. When a subscore is used for decisions across multiple levels (e.g., individual test takers and schools), it needs to be justified for its reliability and distinctiveness at every relevant level. In this study, we examined whether reporting seven Reading and Listening subscores of the "TOEFL Primary"® test, a standardized English proficiency test for young English as a foreign language learners, could be justified for reporting at individual and school levels. We analyzed data collected in pilot administrations, in which 4776 students from 51 schools participated. We employed the classical test theory (CTT) based approaches of Haberman (2008) and Haberman, Sinharay, and Puhan (2009) for the individual and school-level investigations, respectively. We also supplemented the CTT-based approaches with a factor analytic approach for the individual level analysis and a multilevel modeling approach for the school-level analysis. The results differed across the two levels: we found little support for reporting the subscores at the individual level, but strong evidence supporting the added-value of the school-level subscores when the sample size for each school exceeds 50.
Keywords: Correlation; Decision Making; Elementary School Students; English (Second Language); Factor Analysis; Foreign Countries; Institutional Characteristics; Item Response Theory; Kenya; Language Proficiency; Language Tests; Listening Comprehension Tests; Profiles; Psychometrics; Reading Tests; Scores; Second Language Instruction; Second Language Learning; Test Reliability; Test of English as a Foreign Language

Are Refugee Children Learning? Early Grade Literacy in a Refugee Camp in Kenya - Piper, Benjamin; Dryden-Peterson, Sarah; Chopra, Vidur; Reddick, Celia; Oyanga, Arbogast (Are Refugee Children Learning? Early Grade Literacy in a Refugee Camp in Kenya, 2020)
Currently, more than 25 million people across the globe live as refugees, having been driven from their countries of origin by crises and conflicts. Although the right to education is articulated in global agreements, national education systems in the host countries are primarily responsible for refugee children's instruction. In one of the first studies of its kind, we assessed all the schools providing lower primary education to refugee children in Kakuma refugee camp in Kenya, one of the largest and oldest refugee camps in the world at the time of data collection. The outcomes for these students were concerningly low, even lower than for those of disadvantaged children in the host community, Turkana County. Literacy outcomes differed among the refugee children, depending on their country of origin, the language of instruction used at the school in Kenya, the languages spoken at home, and the children's self-professed expectation of a return to their country of origin. Our findings point to the urgent need to invest heavily in improving learning among refugee children, rather than focusing solely on their access to education.
Keywords: African Languages; Citizenship; Disadvantaged Youth; Emergency Programs; Emergent Literacy; English (Second Language); Expectation; Foreign Countries; Kenya; Language of Instruction; Outcomes of Education; Predictor Variables; Primary Education; Reading Skills; Reading Tests; Refugees; Young Children

Unlocking Data to Tell the Story of Education in Africa: Webinar Summary and Synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wacharia, Wairimu; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]

Prediction Skills, Reading Comprehension and Learning Achievement in Vihiga County Kenya. Addressing Constraints and Prospects - Anyiendah, Mary Susan; Odundo, Paul Amolloh; Kibuyi, Agnes (Prediction Skills, Reading Comprehension and Learning Achievement in Vihiga County Kenya. Addressing Constraints and Prospects, 2020)
Prediction skill may be used in reading comprehension passages as encapsulated in interactive approach instruction. Prediction skills assist learners to decode the meaning of comprehension passages by constructing guesses about the contents of texts to be read in comprehension passages. Learners in Vihiga County register low achievement in English language examinations than peers in neighbouring counties over the years. The performance is much weaker in comprehension passages than grammar sections. Although there are low grades, the nexus between use of prediction skills and learners' achievement in reading comprehension passages has not been assessed. This study applied the Solomon Four Non-Equivalent Group Design to obtain primary data from 279 primary school learners and 8 teachers in 2017. Multiple linear regression used generated two models, one for the experimental group (Model 1) and one for the control group (Model 2). Findings indicate that the influence of prediction skills on learner achievement in reading comprehension passages was significant in experimental, but insignificant in the control groups. However, influence was stronger in the experimental than in the control groups, suggesting that training English language teachers on correct application of prediction skills improves learner achievement in reading comprehension passages. The study recommends need to: sensitise teachers on textbook usage, while supplementing with improvised materials; guide learners through titles; as well as update teacher training curriculum by integrating inter alia, emerging instructional methods embracing Information and Communication Technology and entrenching innovation in resource mobilization and use.
Keywords: Decoding (Reading); Elementary School Students; English (Second Language); Foreign Countries; Instructional Effectiveness; Kenya; Prediction; Public Schools; Reader Text Relationship; Reading Comprehension; Reading Instruction; Reading Skills; Second Language Learning; Textbook Content; Visualization

Teacher Quality and Mathematics Performance in Primary Schools in Kenya - Barasa, Laura (Teacher Quality and Mathematics Performance in Primary Schools in Kenya, 2020)
This study examines the relationship between teacher quality and student achievement in Mathematics among Grade 4 pupils located in 91 urban primary schools and 181 rural primary schools in Kenya. We hypothesise that teacher quality indicators including teacher characteristics, teacher qualification comprising initial teacher education and teacher professional development and teacher classroom practices are significantly associated with student achievement. Our analysis is based on data from the 2012 World Bank and African Economic Research Consortium Service Delivery Indicators. We test our hypotheses by means of a multilevel regression. We find that teacher quality indicators have significant effects on Mathematics achievement in Kenya. Different effects between urban and rural primary schools are observed. The findings of this study underscore the need for policy makers to focus on improving teacher quality by strengthening initial teacher preparation and in-service programmes.
Keywords: Classroom Techniques; Correlation; Elementary School Students; Elementary School Teachers; Faculty Development; Foreign Countries; Grade 4; Kenya; Mathematics Achievement; Preservice Teacher Education; Rural Schools; Rural Urban Differences; Teacher Characteristics; Teacher Competencies; Teacher Effectiveness; Teacher Qualifications; Teaching Methods; Urban Schools

e-Learning Challenges Faced by Universities in Kenya: A Literature Review - Kibuku, Rachael Njeri; Ochieng, Daniel Orwa; Wausi, Agnes Nduku (e-Learning Challenges Faced by Universities in Kenya: A Literature Review, 2020)
Some institutions of higher education in Kenya have adopted e-Learning with the aim of coping with the increased demand for university education and to widen access to university training and education. Though there are advantages that accrue from adopting e-Learning; its implementation and provision has not been smooth sailing. It has had to contend with certain national, organisational, technical and social challenges that undermine its successful implementation. This paper therefore aims to present a literature review of the challenges faced in the implementation and provision of e-Learning in universities in Kenya. The scoping review method was used to identify and analyze the literature of the e-Learning challenges. Some of the challenges revealed include: lack of adequate e-Learning policies, inadequate Information and Communication Technology (ICT) infrastructure, the ever evolving technologies, lack of technical and pedagogical competencies and training for e-tutors and e-learners, lack of an e-Learning theory to underpin the e-Learning practice, budgetary constraints and sustainability issues, negative perceptions towards e-Learning, quality issues, domination of e-Learning aims by technology and market forces and lack of collaboration among the e-Learning participants. These challenges need to be addressed to minimise their impact on implementation and delivery of e-Learning initiatives in institutions of higher education in Kenya. This analysis of the e-Learning challenges forms the basis for the ongoing research that seeks to explore and establish possible strategies to address some of these challenges.
Keywords: Access to Computers; Barriers; Delivery Systems; Developing Nations; Distance Education; Educational Policy; Educational Quality; Electronic Learning; Financial Support; Foreign Countries; Internet; Kenya; Negative Attitudes; Technological Literacy; Technology Integration; Tutors; Universities

Enhancing young children's language acquisition through parent–child book-sharing: A randomized trial in rural Kenya. - Knauer, Heather A.; Jakiela, Pamela; Ozier, Owen; Aboud, Frances; Fernald, Lia C.H. (Enhancing young children's language acquisition through parent–child book-sharing: A randomized trial in rural Kenya., 2020)
• Homes in rural Kenya lack storybooks that could support children's early literacy. • We conducted a cluster-randomized trial of combinations of books and training. • Dialogic reading training (DRT) can improve the quality of parent–child reading. • Books and DRT yield vocabulary gains for children with illiterate caregivers. • More intensive intervention variants did not markedly increase impacts. Worldwide, 250 million children under five (43%) are not meeting their developmental potential because they lack adequate nutrition and cognitive stimulation in early childhood. Several parent support programs have shown significant benefits for children's development, but the programs are often expensive and resource intensive. The objective of this study was to test several variants of a potentially scalable, cost-effective intervention to increase cognitive stimulation by parents and improve emergent literacy skills in children. The intervention was a modified dialogic reading training program that used culturally and linguistically appropriate books adapted for a low-literacy population. We used a cluster randomized controlled trial with four intervention arms and one control arm in a sample of caregivers (n ?=?357) and their 24- to 83-month-old children (n ?=?510) in rural Kenya. The first treatment group received storybooks, while the other treatment arms received storybooks paired with varying quantities of modified dialogic reading training for parents. Main effects of each arm of the trial were examined, and tests of heterogeneity were conducted to examine differential effects among children of illiterate vs. literate caregivers. Parent training paired with the provision of culturally appropriate children's books increased reading frequency and improved the quality of caregiver-child reading interactions among preschool-aged children. Treatments involving training improved storybook-specific expressive vocabulary. The children of illiterate caregivers benefited at least as much as the children of literate caregivers. For some outcomes, effects were comparable; for other outcomes, there were differentially larger effects for children of illiterate caregivers.
Keywords: Children's language; Cluster randomized controlled trials; Kenya; Language acquisition; Mother-child relationship; Parenting; Parenting education; Poor children; Working parents

Integration of Information Communication Technology in Teaching: The Underpinning Factors among Kenya's Primary School Teachers - Mutisya, Sammy Muteti (Integration of Information Communication Technology in Teaching: The Underpinning Factors among Kenya's Primary School Teachers, 2020)
This study was carried out with 86 primary school teachers in Kenya's Narok County and explored factors affecting integration of ICT in teaching and learning. Multiple regression was used for data analysis. The results revealed that 32.5% of the variance was explained by the independent and extraneous variables (R[superscript 2] = 0.325, P = 0.001) and was statistically significant. Attitude was found to be a significant predictor of teachers' behavioural intention to use ICT in teaching and learning ([beta] = 0.259, p < 0.05) while performance expectancy ([beta] = 0.148, p > 0.05), effort expectancy ([beta] = -0.185, p > 0.05), social influence ([beta] = 0.029, p > 0.05), facilitating condition ([beta] = 0.194, p > 0.05), self-efficacy ([beta] = 0.195, p > 0.05) and anxiety ([beta] = 0.074, p > 0.05) were not significant predictors. The study recommends training of teachers on subject-specific ICT technologies, that laptops and computers be availed for use by teachers and pupils, that School Heads be trained on how to monitor and support integration of ICT by teachers and that governments provide schools with requisite ICT infrastructure.
Keywords: Access to Computers; Elementary School Teachers; Foreign Countries; Government Role; Handheld Devices; Information Technology; Intention; Kenya; Negative Attitudes; Pedagogical Content Knowledge; Predictor Variables; Principals; Teacher Education; Technological Literacy; Technology Integration

Preparedness for Online Learning in the Context of COVID-19 in Selected Sub-Saharan African Countries - Pete, Judith; Soko, Jeketule Jacob (Preparedness for Online Learning in the Context of COVID-19 in Selected Sub-Saharan African Countries, 2020)
This study sought to evaluate the instructor and learner preparedness for online learning in Sub-Saharan Africa. Specifically, the study explored the devices lecturers and learners use for teaching and learning, their level of digital proficiency, access to internet connection and finally, their level of satisfaction of connectivity cost, speed and stability. The study followed quantitative design and used structured questionnaire which were distinct for lecturers and students but with similar variables. It targeted three Sub-Saharan countries: Kenya, Ghana and Sought Africa. A total of 2,341 respondents participated in the research comprising of 855 lecturers and learners from Ghana, 842 from Kenya and 644 from South Africa. We found out that generally the respondents in the three countries use mostly laptops and smart phone devices compared to desktop computers except for Kenya where there was high record of desktop computers. Additionally, the use of tablet device was the least among the three countries. Lecturers and learners in these universities possessed intermediate digital proficiency which meant respondents were able to use a range of applications effectively. The study established that there was extremely low level of satisfaction with the internet connection, cost and reliability. The study recommended that institutions should maximize the use of mobile technology to teach and enhance online learning since majority of the learners possess smart phones and laptop devices. Universities should shift the focus from centralized Information Communication Technology investment in the campus to off campus empowering the learner and instructor than relying on campus Information Communication Technology hence to subsidize on internet bundles. Universities should lobby for subsidized internet bundles from internet providers and policy makers should reduce tax levies for internet service providers to offer affordable and reliable internet connection to learners and instructor off campus. In collaboration with universities, United Nations Educational, Scientific and Cultural Organization should prioritize capacity building for lecturers and other users to enhance skills and knowledge of online education.
Keywords: Access to Computers; COVID-19; Capacity Building; College Faculty; College Students; Computer Use; Costs; Distance Education; Electronic Learning; Emergency Programs; Foreign Countries; Ghana; Handheld Devices; Internet; Kenya; Laptop Computers; Learning Readiness; Pandemics; Reliability; Satisfaction; South Africa; Technological Literacy; Telecommunications; Universities

Enabling Untrained Teachers to Be Engineering Facilitators: A Design-Based Research Study of Teacher Professional Development in Fragile Contexts - Radhakrishnan, Dhinesh Balaji (ProQuest LLC, 2020)
Estimates of "Street Youth" (SY) (those who live/work on the streets) show 150 million around the world, with approximately 50,000 in Kenya alone as of 2018. Challenges these youth face remain a significant barrier to national governments achieving Sustainable Development Goal 4 (Quality Education) targets, as formal schools limit access or fail to provide meaningful and supported learning experiences for SY. However, informal learning spaces that empower youth to solve problems themselves may provide them with the knowledge and skills they are denied by formal schools. SY rescue, rehabilitation, and reintegration centers all around the world emphasize and place education at the center of their operations. Recommendations for educational services for SY include providing flexible, alternative education and skills training for youth unable or unwilling to return to school. However, the lack of skilled professionals working with the SY population is one of the most critical challenges. To meet the learning needs of vast numbers of SY, teachers already connected to this population must be trained in teaching more empowering, skill-based courses such as engineering, which are typically complex. Such innovative, problem-centered curricula demand skilled teachers who are prepared to facilitate a more student-centered classroom. However, sub-Saharan Africa faces a shortage of 17 million formally qualified teachers, even for its formal public schools. Therefore, connecting with the teachers in the context and training them in engineering teaching is crucial. Researchers have long argued the need for teacher professional development to be continuous and long-term. Through this dissertation, I present a Design-Based Research (DBR) study of untrained Teacher Professional Development (TPD) in collaboration with three aspiring engineering teachers at an alternative school for SY in western Kenya. I draw on the theoretical framework of Situated Learning and Communities of Practice (CoP) to discuss the outcomes of a three-phase professional development program. Each phase was designed using the recommendation from McKenney et al. (2006) to include three iterative micro-cycles of analysis, design, and evaluation leading to a meso-cycle. In total, three meso-cycles were completed to arrive at DBR's final phase of reflection and generation of design principles. In the first phase, teachers in this study adopted reflective practice strategies to increase their awareness of the practice. Analysis from the study showed that the teachers individually and collectively showed resilience to challenging and complex experiences by establishing a strong foundation for the community of practice. In the second phase, teachers engaged in action research to improve both teaching and learning outcomes. Results demonstrated increased active participation of the teachers in their teaching practice, and developed new understandings of engineering teaching. However, the first two studies also showed the challenges limiting the teachers from constructing an engineering teacher identity and unresolved questions about the sustainability of the TPD. Therefore, in the last phase, the teachers adopted mentoring new teachers as a strategy to develop their identities and sustain the engineering TPD. The findings from the three phases resulted in generation of design outcomes that include a situated understanding of the theory in this fragile context and design principles that are transferable in comparable settings. Implications of this work suggest a sustainable teacher professional development model for untrained engineering teachers in fragile contexts and present relevant design principles for the CoP.. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Communities of Practice; Empowerment; Engineering Education; Faculty Development; Foreign Countries; Homeless People; Informal Education; Kenya; Nontraditional Education; Out of School Youth; Skill Development; Teacher Attitudes; Teacher Shortage; Youth

Resisting Epistemic Blackout: Illustrating Afrocentric Methodology in a Kenyan Classroom - Wandera, David B. (Resisting Epistemic Blackout: Illustrating Afrocentric Methodology in a Kenyan Classroom, 2020)
This article is based on the assumption that indigenous communities have a capacity to generate knowledge, and this capacity is largely underutilized or peripheralized in mainstream research. In this empirical qualitative study, the author makes a case for employing local non-Western analytic tools, in addition to Western analytic tools, to develop a fuller understanding of literacy practices in non-Western spaces. Through an interepistemic synergy approach, the author employed indexicality and interactional sociolinguistics on the one hand and Afrocentric methodology on the other hand in analyzing data produced in a grades 5 and 9 literacy collaboration in Nairobi, Kenya. This study illustrates deeper understandings of data on language use that scholars of language and literacy might derive through taking up an interepistemic synergy approach. Such understandings include tracking how multilingual speakers in postcolonial spaces modulate power imbalance and navigate layers of cross linguistic coevocation informed by contested ideologies and worldviews. The analysis also spotlights how local fingerprints of multilingualism and multiethnicity endure in written text in spite of language surveillance in a Standard Kenyan English-dominated classroom space. Taken together, these understandings cast a unique local aspect on language and literacy practices that goes beyond an emic-etic approach. Most crucially, this article is an illustrative resource for scholars and other stakeholders to address the existing epistemic imbalance that manifests through overrepresentation of Western(ized) analytic tools in constituting the metalanguage for analyzing data on language and literacy.
Keywords: Afrocentrism; Bilingual Students; Data Analysis; Epistemology; Foreign Countries; Grade 5; Grade 9; Ideology; Indigenous Knowledge; Indigenous Populations; Kenya (Nairobi); Language Research; Language Usage; Metalinguistics; Multilingualism; Research Methodology; Sociolinguistics; World Views

Are Low-Cost Private Schools Worth the Investment?: Evidence on Literacy and Mathematics Gains in Nairobi Primary Schools - Zuilkowski, Stephanie Simmons; Piper, Benjamin; Ong'ele, Salome (Are Low-Cost Private Schools Worth the Investment?: Evidence on Literacy and Mathematics Gains in Nairobi Primary Schools, 2020)
Background/Context: Low-cost private schools (LCPSs) represent a large and growing share of schools in many low- and middle-income countries, including Kenya. In some Nairobi neighborhoods, more than half of children attend LCPSs, despite policies providing free access to public education. Parents generally choose LCPSs because they believe they are higher quality, although there is little conclusive evidence supporting this belief. Objective: In this study, we aim to add to the evidence available on the comparison between LCPSs and public schools by using student gains over time as our outcome, thus controlling for the initial level of achievement and instead examining improvement. Participants: The randomly selected longitudinal sample was composed of 326 children attending 47 LCPSs and government schools in several of Nairobi's geographic zones. These children's literacy and numeracy outcomes were tracked over two academic years to determine their learning gains over time. Research Design: We used residual gain scores--as opposed to cross-sectional measures--in English and Kiswahili literacy and mathematics, to compare the outcomes of students attending LCPSs and public primary schools across the first and second grades. We discuss how these schools impacted achievement over time. Findings/Results: We found that these LCPSs did not produce significantly higher student growth than public schools under the status quo condition. However, among schools participating in an instructional improvement intervention supported by the United States Agency for International Development, LCPSs increased performance more than public schools in English, Kiswahili, and mathematics, with the largest differences in English. Conclusions/Recommendations: These findings offer a cautionary note to the rapid expansion of LCPSs in low-resource settings. The fees paid to LCPSs by low-income households are often burdensome for families and, in some contexts, may not be worth the trade-offs that families make to afford them. On the other hand, the findings also suggest that low-cost private school teachers may respond more effectively than public school teachers to project-based support.
Keywords: Academic Achievement; Achievement Gains; African Languages; Elementary School Students; English Instruction; Fees; Foreign Countries; Grade 1; Grade 2; Intervention; Kenya (Nairobi); Literacy; Mathematics Instruction; Native Language Instruction; Numeracy; Private Schools; Public Schools; School Choice; School Effectiveness; Teacher Behavior

Are Low-Cost Private Schools Worth the Investment?: Evidence on Literacy and Mathematics Gains in Nairobi Primary Schools. - Zuilkowski, Stephanie Simmons; Piper, Benjamin; Ong'ele, Salome (Are Low-Cost Private Schools Worth the Investment?: Evidence on Literacy and Mathematics Gains in Nairobi Primary Schools., 2020)
Background/Context: Low-cost private schools (LCPSs) represent a large and growing share of schools in many low- and middle-income countries, including Kenya. In some Nairobi neighborhoods, more than half of children attend LCPSs, despite policies providing free access to public education. Parents generally choose LCPSs because they believe they are higher quality, although there is little conclusive evidence supporting this belief. Objective: In this study, we aim to add to the evidence available on the comparison between LCPSs and public schools by using student gains over time as our outcome, thus controlling for the initial level of achievement and instead examining improvement. Participants: The randomly selected longitudinal sample was composed of 326 children attending 47 LCPSs and government schools in several of Nairobi's geographic zones. These children's literacy and numeracy outcomes were tracked over two academic years to determine their learning gains over time. Research Design: We used residual gain scores--as opposed to cross-sectional measures--in English and Kiswahili literacy and mathematics, to compare the outcomes of students attending LCPSs and public primary schools across the first and second grades. We discuss how these schools impacted achievement over time. Findings/Results: We found that these LCPSs did not produce significantly higher student growth than public schools under the status quo condition. However, among schools participating in an instructional improvement intervention supported by the United States Agency for International Development, LCPSs increased performance more than public schools in English, Kiswahili, and mathematics, with the largest differences in English. Conclusions/Recommendations: These findings offer a cautionary note to the rapid expansion of LCPSs in lowresource settings. The fees paid to LCPSs by low-income households are often burdensome for families and, in some contexts, may not be worth the trade-offs that families make to afford them. On the other hand, the findings also suggest that low-cost private school teachers may respond more effectively than public school teachers to project-based support.
Keywords: Academic achievement; Educational outcomes; Educational quality; Elementary and Secondary Schools; Learning; Mathematical literacy; Nairobi (Kenya); Primary schools; Private schools

Evidence-based policy making: What is it? How do we get it? - Banks, Gary (World Scientific Reference on Asia-Pacific Trade Policies, 2020)

Mapping education data in sub-Saharan Africa - ESSA; EdTech Hub; eBASE; CERT; ZiziAfrique (2020)

Demographic and Health Survey - Government of Kenya (2020)

National Educational Sector Investment Plan (2020-2030). Ministry of Education - Ministry of Education (Republic of Malawi, 2020)

NDS 30: National Development Strategy 2020-2030: For Structural Transformation and Inclusive Development - Ministry of the Economy, Planning and Regional Development (Government of Cameroon, 2020)

Elementary schools working as professional learning communities: Effects on student learning - Moulakdi, André; Bouchamma, Yamina (International Education Studies, 2020)
The professional learning community (PLC) is considered to be an effective school improvement strategy centered on student achievement. The goal of this study was to introduce the PLC approach in a few public elementary schools in Cameroon to evaluate the causal impact of this organizational model on student learning. A quasi-experimental approach was used involving an experimental group and a control group. Student pre- and post-tests were administered in two core subjects (French and mathematics) at both the beginning and the end of the first year of operation as a PLC. Our findings show a significant improvement in the students' results between the pre- and post-test. The PLC was qualified as being in its initiation stage of development, when members focus on their students' outcomes and collectively engage in solving the latter's learning-related difficulties.
Keywords: Academic Achievement; Communities of Practice; ERIC, Current Index to Journals in Education (CIJE); Educational Improvement; Elementary Education; Elementary School Students; Elementary School Teachers; Faculty Development; French; Mathematics Achievement; Pretests Posttests; Quantitative research; Quasi-experimental design; Second Language Instruction

What works to improve early grade literacy in Latin America and the Caribbean? A systematic review and meta‐analysis - Stone, Rebecca; De Hoop, Thomas; Coombes, Andrea; Nakamura, Pooja (Campbell Systematic Reviews, 2020)

Preschool attendance, schooling, and cognitive skills in East Africa. - Bietenbeck, Jan; Ericsson, Sanna; Wamalwa, Fredrick M. (Preschool attendance, schooling, and cognitive skills in East Africa., 2019)
We study the effects of preschool attendance on children's schooling and cognitive skills in Kenya and Tanzania. We use a within-household estimator and data from nationally representative surveys of school-age children's literacy and numeracy skills, which include retrospective information on preschool attendance. In both countries, school entry rules are not strictly enforced, and children who attend preschool often start primary school late. At ages 7–9, these children have thus attended fewer school grades than their same-aged peers without pre-primary education. However, they catch up over time: at ages 13–16, children who went to preschool have attended about the same number of school grades and score about 0.10 standard deviations higher on standardized tests in both countries. They are also 3 (5) percentage points more likely to achieve basic literacy and numeracy in Kenya (Tanzania).
Keywords: East Africa; Elementary and Secondary Schools; Elementary schools; Kenya; Preschool children; Primary schools; Standard deviations; Standardized tests; Tanzania

Examining Options for Reading Comprehension Assessment in International Contexts - Zuilkowski, Stephanie Simmons; Piper, Benjamin; Kwayumba, Dunston; Dubeck, Margaret (Examining Options for Reading Comprehension Assessment in International Contexts, 2019)
Background: Governments in low-income countries and donors have invested the equivalent of hundreds of millions of dollars in enhancing reading outcomes. Although reliable measures exist to assess emergent literacy skills in international contexts, there is little consensus on the assessment of reading comprehension. Methods: Using data from 5,389 Kenyan children attending low-cost private schools, we compared the reading comprehension measure from the Early Grade Reading Assessment to two alternatives. We examined relationships among children's outcome scores and the degree to which children's scores on the three measures drew on the same skills. Results: Scores on the three assessments were strongly correlated, and the assessments appeared to draw on the same abilities. The patterns observed in the exploratory factor analyses held for subgroups, including fluent and nonfluent readers and across testing languages. Conclusion: The alternatives did not provide more information on reading comprehension, and we therefore recommend continued use of the Early Grade Reading Assessment standard measure.
Keywords: Children; Developing Nations; Foreign Countries; Kenya; Private Schools; Reading Comprehension; Reading Skills; Reading Tests; Scores

Examining options for reading comprehension assessment in international contexts. - Zuilkowski, Stephanie Simmons; Piper, Benjamin; Kwayumba, Dunston; Dubeck, Margaret (Peggy) (Examining options for reading comprehension assessment in international contexts., 2019)
Background: Governments in low‐income countries and donors have invested the equivalent of hundreds of millions of dollars in enhancing reading outcomes. Although reliable measures exist to assess emergent literacy skills in international contexts, there is little consensus on the assessment of reading comprehension. Methods: Using data from 5,389 Kenyan children attending low‐cost private schools, we compared the reading comprehension measure from the Early Grade Reading Assessment to two alternatives. We examined relationships among children's outcome scores and the degree to which children's scores on the three measures drew on the same skills. Results: Scores on the three assessments were strongly correlated, and the assessments appeared to draw on the same abilities. The patterns observed in the exploratory factor analyses held for subgroups, including fluent and nonfluent readers and across testing languages. Conclusion: The alternatives did not provide more information on reading comprehension, and we therefore recommend continued use of the Early Grade Reading Assessment standard measure. Highlights: What is already known about this topicLarge‐scale reading interventions in developing countries have focused on foundational skills, such as decoding.Reliable assessments of foundational skills are available and have been used at scale in these contexts.However, the debate continues regarding how reading comprehension should be assessed, in populations with low skill levels and in contexts where tools must be straightforward and inexpensive to implement. What this paper addsWe compare the standard reading comprehension measure used on the Early Grade Reading Assessment to two others.The first alternative is similar in structure but gives students more time to read the associated passage.The second alternative uses sentences rather than a passage to assess comprehension. Implications for theory, policy or practiceAll three measures are strongly correlated, and exploratory factor analyses suggested that they are measuring the same ability.Therefore, as the standard Early Grade Reading Assessment measure is less expensive to implement on a large scale, we see no reason to prefer one of the alternatives.However, the standard measure is not perfect, and future research should explore other options for reliably measuring assessment, particularly at very low literacy levels.
Keywords: Developing countries; Educational outcomes; Emergent literacy; Reading comprehension ability testing; Word recognition

Her sentence is correct, isn't it?": Regulative discourse in English medium classrooms. - Kiramba, Lydiah Kananu; Smith, Patrick Henry (Her sentence is correct, isn't it?": Regulative discourse in English medium classrooms., 2019)
Research on discourse in African classrooms has shown the predominance of teacher centered instructional practices. Teacher centered discourse patterns have been blamed for student passivity and disengagement in knowledge production. In this article, we investigate teachers' use of the invariant tag isn't it in Kenyan primary classrooms during ELA and math lessons. Using Bernstein's pedagogical device theory, we submit that the tag plays a regulative function in classroom discourse. Based on our findings, we argue for greater attention to teachers' language choices and discuss implications for classroom discourse practice and research. • The invariant tag isn't it is a common linguistic feature in World Englishes, including Kenyan English. • Teachers across Kenya are familiar with use of isn't it in and outside the context of schooling. • We examined use of isn't it in discourse in English medium classrooms. • Teachers' use of the invariant tag isn't it regulated classroom discourse and limited dialogue
Keywords: Africa; Classroom activities; Multilingual education; Primary education; Primary schools; School children; Teachers; Teaching

Justifications and Impacts of Low-Fee Private Schools in Kenya and Uganda: Understanding Policy Evolutionary Mechanisms through Public Discourse of Bridge International Academies. - Monk, Jeremy (Justifications and Impacts of Low-Fee Private Schools in Kenya and Uganda: Understanding Policy Evolutionary Mechanisms through Public Discourse of Bridge International Academies., 2019)
Low-fee private schools (LFPS) have grown considerably in the developing world as public free primary education has been unable to cater to the poorest children. Bridge International Academies (BIA), one of the largest chains of LFPS, has positioned itself as a solution to issues of access and quality of primary education. Using newspaper articles from Kenya and Uganda, this paper examines public discourse of BIA through the lens of cultural political economy, or how public discourse can influence variation, selection and retention regarding LFPS. After exploring scholarship to understand the justifications and impacts of LFPS, this paper finds that justifications are present in public discourse while impacts are not. Therefore, public discourse has given voice and promoted the need for improvements, with LFPS as an option, but that discourse (and scholarship) has yet to emphasize LFPS as a real solution, due to inconclusive evidence and ongoing battles with governments.
Keywords: Discourse; Educational quality; Elementary and Secondary Schools; Grantmaking Foundations; Kenya; Poor children; Primary education; Private schools; Scholarship applications; Scholarships; Uganda

The legacy of colonial language policies and their impact on student learning: Evidence from an experimental program in Cameroon. - Laitin, David D.; Ramachandran, Rajesh; Walter, Stephen L. (Economic Development & Cultural Change, 2019)
The relative educational returns on colonial versus indigenous language instruction in sub-Saharan countries have yet to be decisively estimated. To address this unanswered question, this paper provides an impact assessment of an experiment in Cameroon in which the first 3 years of schooling were conducted in a local language instead of in English. Test results in examinations in both English and math reveal that treated students exhibit gains of 1.1–1.4 of a standard deviation in grades 1 and 3 compared with the control students. It also increases the probability of being present in grades 3 and 5 by 22 and 14 percentage points, respectively. However, by the end of fifth grade, 2 years after reverting to the English stream, treated students still exhibit gains of 0.40–0.60 of a standard deviation, although the absolute scores for both groups are low enough to suggest limited learning is taking place. [ABSTRACT FROM AUTHOR]
Keywords: EDUCATION; EDUCATIONAL outcomes; EXPERIMENTAL design; EXPERIMENTAL programs; LANGUAGE policy; LITERACY

Every child learns UNICEF Education Strategy 2019-2030 - UNICEF (2019)
UNICEF education strategy 2019–2030

Informal Learning and Literacy among Maasai Women: Education, Emancipation and Empowerment. Routledge Research in International and Comparative Education - Takayanagi, Taeko (Routledge Research in International and Comparative Education, 2019)
Informal Learning and Literacy among Maasai Women" highlights the importance and role of informal education in the emancipation and development of Maasai village women in Kenya. At present, knowledge and research on the impact of informal learning and literacy on community development is limited, and there is a gap between policy level discussions and women's lived experiences. Using a postcolonial feminist framework, this book sets out to examine linkages between informal learning and literacy, human development and gender inequality. Despite improvements in recent years, access to traditional education remains restricted for many women in rural communities across Kenya. Takayangi's book is the first to introduce how Maasai village women utilise informal learning and literacy for collective empowerment as well as to sustain their own well-being and that of their families. It presents the perspectives of both local women and institutions and argues that women's learning is most effective when located within their own socio-cultural and political discourses, and when their voices are listened to and heard. This ethnographic research study is a valuable resource that will contribute to the knowledge of literacy from both theoretical and practical perspectives. It is an essential read for those studying or researching information education, development studies and gender, or education, as well as for teachers, community leaders and aid workers.
Keywords: Access to Education; African Culture; Cultural Background; Empowerment; Ethnography; Females; Feminism; Foreign Countries; Indigenous Populations; Informal Education; Kenya; Literacy; Literacy Education; Sex Fairness; Womens Education

Literacy Acquisition in Multilingual Educational Contexts: Evidence from Coastal Kenya - Jasinska, Kaja K.; Wolf, Sharon; Jukes, Matthew C. H.; Dubeck, Margaret M. (Literacy Acquisition in Multilingual Educational Contexts: Evidence from Coastal Kenya, 2019)
Literacy is a powerful tool against poverty, leading to further education and vocational success. In sub-Saharan Africa, schoolchildren commonly learn in two languages--African and European. Multiple early literacy skills (including phonological awareness and receptive language) support literacy acquisition, but this has yet to be empirically tested in sub-Saharan Africa, where learning contexts are highly multilingual, and children are often learning to read in a language they do not speak at home. We use longitudinal data from 1,100 school children spanning three groups of native languages [Mijikenda languages (Digo, Duruma, Chonyi, and Giriama), Kiswahili, Kikamba] in coastal Kenya (language of instruction: Kiswahili and English). We find that baseline phonological awareness and receptive language are differentially important in predicting literacy skills in English and in Kiswahili, and these relations are moderated by the degree of shared cross-linguistic features between home and school languages. Importantly, the relative importance of these factors changes over development. Implications for language development and literacy acquisition in linguistically diverse contexts are discussed.
Keywords: African Languages; Child Development; Contrastive Linguistics; Educational Environment; Elementary School Students; English (Second Language); Family Environment; Foreign Countries; Kenya; Language Acquisition; Language Usage; Language of Instruction; Literacy; Longitudinal Studies; Multilingualism; Native Language; Phonological Awareness; Prediction; Receptive Language; Second Language Learning

Multilingual Assessment of Early Child Development: Analyses from Repeated Observations of Children in Kenya - Knauer, Heather A.; Kariger, Patricia; Jakiela, Pamela; Ozier, Owen; Fernald, Lia C. H. (Multilingual Assessment of Early Child Development: Analyses from Repeated Observations of Children in Kenya, 2019)
In many low- and middle-income countries, young children learn a mother tongue or indigenous language at home before entering the formal education system where they will need to understand and speak a country's official language(s). Thus, assessments of children before school age, conducted in a nation's official language, may not fully reflect a child's development, underscoring the importance of test translation and adaptation. To examine differences in vocabulary development by language of assessment, we adapted and validated instruments to measure developmental outcomes, including expressive and receptive vocabulary. We assessed 505 2-to-6-year-old children in rural communities in Western Kenya with comparable vocabulary tests in three languages: Luo (the local language or mother tongue), Swahili, and English (official languages) at two time points, 5-6 weeks apart, between September 2015 and October 2016. Younger children responded to the expressive vocabulary measure exclusively in Luo (44%-59% of 2-to-4-year-olds) much more frequently than did older children (20%-21% of 5-to-6-year-olds). Baseline receptive vocabulary scores in Luo (ß = 0.26, SE = 0.05, p < 0.001) and Swahili (ß = 0.10, SE = 0.05, p = 0.032) were strongly associated with receptive vocabulary in English at follow-up, even after controlling for English vocabulary at baseline. Parental Luo literacy at baseline (ß = 0.11, SE = 0.05, p = 0.045) was associated with child English vocabulary at follow-up, while parental English literacy at baseline was not. Our findings suggest that multilingual testing is essential to understanding the developmental environment and cognitive growth of multilingual children.
Keywords: African Languages; Age Differences; Child Development; Cognitive Development; Correlation; Culture Fair Tests; Elementary School Students; English (Second Language); Expressive Language; Foreign Countries; Kenya; Language Acquisition; Language Tests; Literacy; Multilingualism; Native Language; Parent Child Relationship; Preschool Children; Receptive Language; Rural Areas; Second Language Learning; Test Validity; Translation; Vocabulary Development

The evidence ecosystem in South Africa: Growing resilience and institutionalisation of evidence use - Stewart, Ruth; Dayal, Harsha; Langer, Laurenz; Van Rooyen, Carina (Palgrave Communications, 2019)
The evidence-informed approach to policy-making and implementation is, at its core, about better decisions for a better future. It is focused on the effective use of scarce resources, on avoiding harm and maximising good. It is grounded in principles of equity and equality, of accountability and transparency. Given these characteristics, for those of us who work in this ﬁeld, there is arguably a moral, economic, social and political case for paying closer attention to evidence-informed decision-making ecosystems in the South. Evidencebased policy and implementation, or evidence-informed decision-making in line with the most recent thinking, is often framed from two inter-related but limited perspectives: ﬁrst, it is viewed as an approach that has originated from ‘developed’ Northern countries, and second, it is conceptualised as a technical intervention. However, there has been a shift in how the approach is conceived, moving away from assumptions that it is an intervention implemented from outside, from the North, for the beneﬁt of the South. As part of this shift, certain initiatives in Africa have gained greater momentum. It is in acknowledging that there are different ways to think (epistemic diversity) about Southern evidence-informed decisionmaking, that this work has arisen. It seizes on the opportunity to view evidence-informed decision-making in a new light, exploring the evidence ecosystems in the South as systems strongly inﬂuenced by, but not deﬁned by, Northern stimuli, including, but not limited to, technical interventions. This work set out to describe the evidence ecosystem in South Africa. In doing so, it ﬁnds that the ecosystem is increasingly resilient despite some limitations. It has strong structural foundations, includes many diverse organisations, is supported by not inconsiderable investment, is enabled by growing and signiﬁcant capacity, contains iterations and innovations, and last but not least, incorporates complexity that gives the ecosystem resilience. The work demonstrates, through its focus on South Africa’s evidence ecosystem, that the global movement has much to learn from the South.

Reconciling heterogeneous results on the returns to skills in Africa. - Otchia, Christian S.; Yamada, Shoko (Reconciling heterogeneous results on the returns to skills in Africa., 2019)
Recent evidence indicates substantial heterogeneity in the returns to skills across countries, but only a few studies have explained the varying patterns in the return to skills. Using the 2013 STEP data for Ghana and Kenya, we estimate the causal effect of cognitive and noncognitive skills on a large set of labour market outcomes by controlling for important predetermined variables. We find that cognitive skill remains an important predictor of labour market outcomes but its effect is largely mediated by the year of schooling. We document that the labour market effects of noncognitive skills are smaller than reading proficiency, but with large variation across labour market outcomes. Interestingly, we show that schooling does not mediate the effect of noncognitive skills, meaning most of these skills are acquired outside the classroom. A decomposition analysis shows that local labour market characteristics, such as formal jobs and skilled labour demand, explains the lion share of the heterogeneity whereas the job-skill matching quality plays a significant role in the unexplained part.
Keywords: Administration of Education Programs; Africa; All Other Miscellaneous Schools and Instruction; Creative ability; Education; Educational Support Services; Heterogeneity; Labor market

Data-based decision-making for school improvement: Research insights and gaps - Schildkamp, Kim (Educational Research, 2019)
Background: Data-based decision-making in education often focuses on the use of summative assessment data in order to bring about improvements in student achievement. However, many other sources of evidence are available across a wide range of indicators. There is potential for school leaders, teachers and students to use these diverse sources more fully to support their work on a range of school improvement goals. Purpose and sources of evidence: To explore data-based decisionmaking for school improvement, this theoretical paper discusses recent research and literature from diﬀerent areas of data use in education. These areas include the use of formative assessment data, educational research study ﬁndings and ‘big data’. In particular, the discussion focuses on how school leaders and teachers can use diﬀerent sources of data to improve the quality of education. Main argument: Based on the literature reviewed, an iterative model of data use for school improvement is described, consisting of deﬁning goals for data use, collecting diﬀerent types of data or evidence (e.g. formal data, informal data, research evidence and ‘big data’), sense-making, taking improvement actions and evaluation. Drawing on the literature, research insights are discussed for each of these components, as well as identiﬁcation of the research gaps that still exist. It is noted that the process of data use does not happen in isolation: data use is inﬂuenced by system, organisation and team/individual level factors. Conclusions: When it comes to using data to improve the quality of teaching and learning, it is evident that some of the most important enablers and barriers include data literacy and leadership. However, what is less well understood is how we can promote the enablers and remove the barriers to unlock, more fully, the potential of data use. Only then can data use lead to sustainable school improvement.

P116 Factors Associated with Nutrition Knowledge Among Primary School Pupils in Laikipia County, Kenya. - Kigaru, Dorcus; Ochola, Sophie; Weru, Grace (P116 Factors Associated with Nutrition Knowledge Among Primary School Pupils in Laikipia County, Kenya., 2019)
Nutrition knowledge plays an important role in public health. It is one of the factors that affects the nutrition habits of individuals, families and communities. It provides a good foundation for making proper decisions regarding food choice and nutrition practices. To determine the demographic and socioeconomic factors associated with nutrition knowledge among primary school pupils in Laikipia County. A cross sectional study involving a total of 326 pupils aged 12-14 years recruited into the study from three rural primary schools in Laikipia County. Demographic characteristics, socioeconomic characteristics, nutrition knowledge scores. The nutrition knowledge was assessed using 20-item questionnaire. Chi-square tests, Pearson correlation coefficient and logistic regression were used to determine association between variables. The mean age of the pupils was 12.24 ± 1.39. The pupils were in classes 4, 5, and 6. The mean nutrition knowledge score was 10.96 ± 3.76. The nutrition knowledge was categorized into three levels: low (≤ 40%), moderate (41-49%) and high (≥70%). A Pearson correlation test showed that the age of the pupils was not significantly associated with the mean nutrition knowledge score (P =.051). Ownership of a television set was significantly associated with the level of nutrition knowledge among pupils at a significance level of.05 (P =.016). The main source of lighting was significantly associated with their level of nutrition knowledge (P =.008). The class of study was significantly associated with the nutrition knowledge level (P =.000) at a significance level of 0.01. Class 7 pupils were more likely to have higher nutrition knowledge as compared to class 5 and 6 pupils (OR = 8.34). Class 5 pupils were less likely to have high nutrition knowledge as compared to their class 6 and 7 counterparts (OR = 2.76). Ownership of television and source of lighting were significantly associated with the nutrition knowledge of the pupils. The television is an effective tool for delivering health messages to pupils in this age group.
Keywords: Conferences & conventions; Convention and Trade Show Organizers; Florida; Health literacy; Health occupations students; Kenya; Nutrition; School children; Socioeconomic factors

Navigating Authoritative Discourses in a Multilingual Classroom: Conversations with Policy and Practice - Kiramba, Lydiah Kananu; Harris, Violet J. (Navigating Authoritative Discourses in a Multilingual Classroom: Conversations with Policy and Practice, 2019)
Bakhtinian concepts of persuasive and authoritative discourse, this study reports on science and English language arts instructional practices in a multilingual, rural, fourth-grade classroom in Kenya. Situated in English as a medium of instruction (EMI) and through the use of case study, the study explores classroom discourse data to illustrate how teachers use instructional practices to reproduce, contest, or navigate prevailing institutional monolingual policies when mediating students' access to literacy and content. By analyzing classroom discourse, the authors argue that restrictive language policies that aspire for fixity disconnect multilingual learners from their daily realities. In contrast, they call for a (re)construction of multilingual pedagogy that capitalizes on the strengths of learners, teachers, and linguistic communities by embracing students' languages and language varieties in language learning and literacy development. In particular, implications are drawn for the use of EMI for emerging bilingual and multilingual learners. The authors identify the need to prepare teachers for a multilingual reality through legitimizing multilingual pedagogies such as translanguaging.
Keywords: Academic Language; Bilingualism; English (Second Language); English Instruction; Foreign Countries; Grade 4; Kenya; Language Arts; Language of Instruction; Literacy; Multilingualism; Science Instruction; Second Language Learning; Teaching Methods

Component Skills of Reading and Their Structural Relations: Evidence from Three Sub-Saharan African Languages with Transparent Orthographies - Kim, Young-Suk Grace; Piper, Benjamin (Component Skills of Reading and Their Structural Relations: Evidence from Three Sub-Saharan African Languages with Transparent Orthographies, 2019)
Background: We examined the component skills of reading comprehension (i.e., letter sound knowledge, syllable reading fluency, decoding fluency, text or oral reading fluency and listening comprehension) and their structural relations using data from three sub-Saharan African languages with transparent orthographies in a multilingual context. Methods: Data from Kiswahili (N = 946), Kikamba (N = 444) and Lubukusu (N = 499) reading assessments at the end of Grade 2 in Kenya were analysed using path analyses. Results: The magnitudes of the relations were similar across the three languages with some differences amongst the languages. Total effects (regression weights), accounting for direct "and" indirect effects, varied across the component skills: text reading fluency (0.73 to 0.77), decoding fluency (0.49 to 0.82), letter sound knowledge (0.44 to 0.45), syllable reading fluency (-0.12 to 0.16) and listening comprehension (0.08 to 0.23). Conclusions: The results indicate similar reading mechanisms across the three sub-Saharan languages.
Keywords: African Languages; Correlation; Decoding (Reading); Elementary School Students; Foreign Countries; Grade 2; Kenya; Listening Comprehension; Multilingualism; Oral Reading; Path Analysis; Phoneme Grapheme Correspondence; Reading Comprehension; Reading Fluency; Reading Tests; Syllables

Promoting young Kenyans' growth in literacy with educational technology: A tale of two years of implementation. - Lysenko, Larysa; Abrami, Philip C.; Wade, C. Anne; Marsh, Jonathon P.; WaGioko, Maina; Kiforo, Enos (Promoting young Kenyans' growth in literacy with educational technology: A tale of two years of implementation., 2019)
• ABRA and READS instruction is better than regular instruction on reading. • ABRA and READS effects on reading transfer to other subject areas. • ABRA and READS are effective when implemented in authentic Kenyan classroom context. This two-phase study was designed as a quasi-experiment to learn about the impacts of the interactive early literacy software and the library of digital books and stories on primary students' reading abilities and reading instruction in Kenyan schools. For more than a term 1899 students from 48 classes learnt to read with the software. A standardized test detected significantly higher reading gains for the experimental students' than for the control group. Experimental students also outperformed control students on the end-of-year exams. The system of training and support coupled with the software implementation yielded some positive albeit modest shifts in reading instruction. Building the capacity of schools and teachers will enable students to benefit from the inputs of the software after the research ceases.
Keywords: Educational technology; Primary education

Bilingualizing linguistically homogeneous classrooms in Kenya: implications on policy, second language learning, and literacy. - Mose, Peter Nyakundi (Bilingualizing linguistically homogeneous classrooms in Kenya: implications on policy, second language learning, and literacy., 2019)
Bilingualism characterizes people in linguistically heterogeneous settlements like Nairobi among other urban centres in Kenya. But the country is also predominantly rural (where you find people of a common language settled in one geographical rural region) in which mother tongues are primary means of communication. Children in lower primary in rural areas should be taught in their mother tongues. The purpose of this study was to find out the use of mother tongues and official languages in elementary linguistically homogeneous classrooms in Kenya and the possible effect of this use. Data were obtained through classroom observations and interviews with classroom teachers and head teachers. The findings indicate that instead of using mother tongues to teach, teachers use Kiswahili (a national and co-official language) and English (an official language) in various ways to teach content subjects; mathematics, science, social/religious studies, hence making the classrooms bilingual. The article presents evidence and discusses how this use of language affects learning and what it implies on language in education policy, on second language learning, and on early literacy development. Negative effects of the practice include poor learning outcomes and poor teacher morale. The study recommends corrective steps to avert learning and literacy development losses.
Keywords: Administration of Education Programs; Bilingualism; Education policy; Elementary education; Kenya; Native language; Other local, municipal and regional public administration; Other provincial and territorial public administration; Outcome-based education; School children; Second language acquisition

The Impact of an Educational Media Intervention to Support Children's Early Learning in Rwanda. - Borzekowski, Dina L. G.; Lando, Agnes Lucy; Olsen, Sara H.; Giffen, Lauren (The Impact of an Educational Media Intervention to Support Children's Early Learning in Rwanda., 2019)
Children in developing countries often lack sufficient support for early learning skills prior to beginning school. This research evaluates an educational media intervention using an animated cartoon program, Akili and Me. The program was originally created in Tanzania to teach early learning skills. This program was adapted in content and language use in this study in Rwanda. The two-week intervention involved primary school students (mean age = 7.1 years) who were randomized into two groups (intervention and comparison group). The intervention group viewed one Akili and Me episode a day for five days. This viewing was repeated the following week. Similarly, the comparison watched the same amount of television but the content consisted of local popular programs. Baseline and follow-up assessments evaluated 10 areas of early learning, using an adaptation of the International Development and Early Learning Assessment (IDELA), and also children's media receptivity. At follow-up, children in the intervention program, Akili and Me, had significantly higher scores for counting, number recognition, shape knowledge, letter identification, color identification, body part recognition, health knowledge, and vocabulary. The analyses provide promising evidence that locally produced educational media interventions can impact early learning skills, even among children living in resource-poor communities.
Keywords: Colleges, Universities, and Professional Schools; Early childhood education; Educational technology; Professional and Management Development Training; Professional education; Quality of life; Social media

Cross-language transfer of reading skills: an empirical investigation of bidirectionality and the influence of instructional environments. - Kim, Young-Suk Grace; Piper, Benjamin (Cross-language transfer of reading skills: an empirical investigation of bidirectionality and the influence of instructional environments., 2019)
The linguistic interdependence hypothesis (Cummins, 1979, 2000) states that children's second-language (L2) proficiency is, to some extent, a function of their first-language (L1) competence. Previous studies have examined this hypothesis with focus on a unidirectional relation from L1 to L2. In the present study, we examined bidirectional influences of literacy skills in multilingual contexts, and whether the nature of relations varied as a function of literacy instruction environment. To do so, we used longitudinal data from a randomized controlled trial of a literacy intervention for children in Grades 1 and 2, learning to read in Kiswahili and English, two official languages in Kenya. Children in the treatment condition received explicit and systematic instruction on literacy (e.g., phonological awareness, phoneme–grapheme correspondences) in Kiswahili and English, whereas children in the control condition did not. Overall results supported bidirectionality of relations, such that children's literacy skills in the two languages were reciprocally related over time. However, directionality of relations differed as a function of language and literacy instruction condition, such that the relation from English to Kiswahili was found across intervention conditions, but the relation from Kiswahili to English was found only among children who had received explicit instruction in Kiswahili reading. These results are discussed in light of theory and practice for language and literacy acquisition in multilingual contexts.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Interdependence theory; Kenya; Language transfer (Language learning); Transference (Psychology)

Cross-Language Transfer of Reading Skills: An Empirical Investigation of Bidirectionality and the Influence of Instructional Environments - Kim, Young-Suk Grace; Piper, Benjamin (Cross-Language Transfer of Reading Skills: An Empirical Investigation of Bidirectionality and the Influence of Instructional Environments, 2019)
The linguistic interdependence hypothesis (Cummins, 1979, 2000) states that children's second-language (L2) proficiency is, to some extent, a function of their first-language (L1) competence. Previous studies have examined this hypothesis with focus on a unidirectional relation from L1 to L2. In the present study, we examined "bidirectional" influences of literacy skills in multilingual contexts, and whether the nature of relations varied as a function of literacy instruction environment. To do so, we used longitudinal data from a randomized controlled trial of a literacy intervention for children in Grades 1 and 2, learning to read in Kiswahili and English, two official languages in Kenya. Children in the treatment condition received explicit and systematic instruction on literacy (e.g., phonological awareness, phoneme-grapheme correspondences) in Kiswahili and English, whereas children in the control condition did not. Overall results supported bidirectionality of relations, such that children's literacy skills in the two languages were reciprocally related over time. However, directionality of relations differed as a function of language and literacy instruction condition, such that the relation from English to Kiswahili was found across intervention conditions, but the relation from Kiswahili to English was found only among children who had received explicit instruction in Kiswahili reading. These results are discussed in light of theory and practice for language and literacy acquisition in multilingual contexts.
Keywords: African Languages; Correlation; Elementary School Students; English (Second Language); Foreign Countries; Grade 1; Grade 2; Intervention; Kenya; Language Proficiency; Literacy Education; Longitudinal Studies; Multilingualism; Native Language; Official Languages; Phoneme Grapheme Correspondence; Phonological Awareness; Reading Instruction; Reading Skills; Second Language Instruction; Second Language Learning; Teaching Methods; Transfer of Training

Cross-Language Transfer of Reading Skills: An Empirical Investigation of Bidirectionality and the Influence of Instructional Environments - Kim, Young-Suk Grace; Piper, Benjamin (Cross-Language Transfer of Reading Skills: An Empirical Investigation of Bidirectionality and the Influence of Instructional Environments, 2019)
The linguistic interdependence hypothesis (Cummins, 1979, 2000) states that children's second-language (L2) proficiency is, to some extent, a function of their first-language (L1) competence. Previous studies have examined this hypothesis with focus on a unidirectional relation from L1 to L2. In the present study, we examined "bidirectional" influences of literacy skills in multilingual contexts, and whether the nature of relations varied as a function of literacy instruction environment. To do so, we used longitudinal data from a randomized controlled trial of a literacy intervention for children in Grades 1 and 2, learning to read in Kiswahili and English, two official languages in Kenya. Children in the treatment condition received explicit and systematic instruction on literacy (e.g., phonological awareness, phoneme-grapheme correspondences) in Kiswahili and English, whereas children in the control condition did not. Overall results supported bidirectionality of relations, such that children's literacy skills in the two languages were reciprocally related over time. However, directionality of relations differed as a function of language and literacy instruction condition, such that the relation from English to Kiswahili was found across intervention conditions, but the relation from Kiswahili to English was found only among children who had received explicit instruction in Kiswahili reading. These results are discussed in light of theory and practice for language and literacy acquisition in multilingual contexts.
Keywords: African Languages; Correlation; Elementary School Students; English (Second Language); Foreign Countries; Grade 1; Grade 2; Intervention; Kenya; Language Proficiency; Literacy Education; Longitudinal Studies; Multilingualism; Native Language; Official Languages; Phoneme Grapheme Correspondence; Phonological Awareness; Reading Instruction; Reading Skills; Second Language Instruction; Second Language Learning; Teaching Methods; Transfer of Training

Resetting Targets: Examining Large Effect Sizes and Disappointing Benchmark Progress. Occasional Paper. RTI Press Publication OP-0060-1904 - Stern, Jonathan M. B.; Piper, Benjamin; RTI International (RTI International, 2019)
This paper uses recent evidence from international early grade reading programs to provide guidance about how best to create appropriate targets and more effectively identify improved program outcomes. Recent results show that World Bank and US Agency for International Development-funded large-scale international education interventions in low- and middle-income countries tend to produce larger impacts than do interventions in the United States, as measured by effect sizes. However, these effect sizes rarely translate into large gains in mean oral reading fluency scores and are associated with only small increases in the proportion of students meeting country-level reading benchmarks. The limited impact of these low- and middle-income countries' reading programs on the proportion of students meeting reading benchmarks is in large part caused by right-skewed distributions of student reading scores. In other words, modest impacts on the proportion of students meeting benchmarks are caused by low mean scores and large proportions of nonreaders at baseline. It is essential to take these factors into consideration when setting program targets for reading fluency and comprehension. We recommend that program designers in lower-performing countries use baseline assessment data to develop benchmarks based on multiple performance categories that allow for more ambitious targets focused on reducing nonreaders and increasing beginning readers, with more modest targets aimed at improving oral reading fluency scores and increasing the percentage of proficient readers.
Keywords: Benchmarking; Data; Developing Nations; Early Childhood Education; Effect Size; Elementary School Students; Evaluation Methods; Foreign Countries; Jordan; Kenya; Malawi; Nepal; Oral Reading; Program Design; Reading Comprehension; Reading Fluency; Reading Programs; Reading Tests; Rwanda; Scores; Uganda

Designing multimodal texts in a girls' afterschool journalism club in rural Kenya. - Kendrick, Maureen; Early, Margaret; Chemjor, Walter (Designing multimodal texts in a girls' afterschool journalism club in rural Kenya., 2019)
Characteristic of the twenty-first century are new literacy practices that require users and producers to be fluent with the affordances of multiple modes across print and digital media. In under-resourced contexts such as East Africa, these complex new multimodal practices have not been well documented. In this paper, we explore the context of an afterschool journalism club in rural Kenya as an informal learning space for 32 adolescent girls to realize multimodal text design following our donation of a laptop, digital camera and voice recorder. Using ethnographic methods that positioned the girls as researchers of their own practices, we collaboratively documented the girls' changing social practices as they produced and designed videos in the context of their community and journalism club. As we proceeded through our analysis, we drew inspiration from Luke and Freebody's Four Resources Model for reading print texts and Serafini's reconceptualization of the Four Resources required for reading visual and multimodal texts, taking up their call to critique and reformulate the model within the rapidly changing context of twenty-first century literacy practices. Our study identifies the emergent and dynamic nested social practices of: (1) explorer, (2) participant-user, (3) performer, and (4) activist as integral to the design of videos.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Digital media; Education; Educational Support Services; Internet Publishing and Broadcasting and Web Search Portals; Journalism; Nonformal education; Teenage girls

Foreign aid, education and lifelong learning in Africa - Asongu, Simplice A; Tchamyou, Vanessa S (Journal of the Knowledge Economy, 2019)
This study investigates the effect of foreign aid on education and lifelong learning in 53 African countries for the period 1996–2010. Three main issues are assessed, notably: (i) the effect of aid on education; (ii) the incremental impact of aid on education and (iii) the effect of aid on lifelong learning. Lifelong learning is measured as the combined knowledge acquired during the primary, secondary and tertiary levels of education. Foreign aid dynamics include total aid, aid from multilateral donors (MD) and aid from the Development Assistance Committee (DAC) countries. The empirical evidence is based on an endogeneity-robust generalized method of moments. The following findings are established. First, the aid variables have positive effects on primary school enrolment and lifelong learning, with the exception of aid from MD which positively affects only lifelong learning. Second, the positive effect on primary school enrolment consistently has a higher magnitude compared to the corresponding impact on lifelong learning. Third, the effects of aid dynamics on secondary and tertiary school enrolments are not significant. We also contribute to the literature by proposing an indicator of lifelong learning for developing countries.
Keywords: Africa; Business And Economics; Development; Education; F35; Foreign aid; Generalized method of moments; I20; I28; Lifelong learning; O55; P16

Status of School Feeding Programme Policy Initiatives in Primary Schools in Machakos County, Kenya - Kiilu, Redempta M.; Mugambi, Lucy (Status of School Feeding Programme Policy Initiatives in Primary Schools in Machakos County, Kenya, 2019)
Although education stakeholders agreed on achieving Education for All by 2015, high wastage rates in developing countries has remained a major concern. In Kenya, data shows that more than one million primary age children are still out school. In many countries, school feeding programmes has been used as one of the interventions to promote retention and improving learning outcomes in primary schools. The paper therefore investigated the status of school feeding policy initiatives in primary schools in Kenya. The objectives of the study were to examine the status of school feeding initiatives; to establish the sources of funding for feeding initiatives and assess the influence of feeding initiatives on school attendance in Machakos County. The study targeted 30 schools in Kalama and Kola zones. Simple random sampling was used to obtain a sample of 28 teachers and 55 class eight pupils while nine head teachers were selected purposively, making a total of 92 respondents. The study used descriptive survey design using questionnaires for data collection. Data was analyzed by use of descriptive statistics aided by Statistical Package for Social Sciences. Findings were presented in frequency tables and graphs. From the findings, majority of schools have implemented the primary school feeding programs as attested by 53% of the teachers, 88% of the head teachers and 61% of the pupils. However, 70% of funding for the school feeding programme come from the community and this has rendered the initiative less effective as most of the parents in the targeted schools have limited resources. The paper recommends for a more state participation to sustain the primary school feeding programme initiative in Machakos County
Keywords: Academic Persistence; Administrator Attitudes; Attendance; Breakfast Programs; Correlation; Elementary School Students; Elementary School Teachers; Financial Support; Food; Foreign Countries; Kenya; Lunch Programs; Out of School Youth; Program Evaluation; School Holding Power; Student Attitudes; Teacher Attitudes; Wastes

Indigenous knowledge practices for sustainable lifelong education in pastoralist communities of Kenya. - Ng'asike, John Teria (Indigenous knowledge practices for sustainable lifelong education in pastoralist communities of Kenya., 2019)
Despite setting high hopes on education, very few pastoral nomad children in Kenya transition from primary education to secondary education. This article argues that the national Kenyan compulsory formal curriculum fails to accommodate the needs of pastoralist communities. Literacy rates are particularly low among the Turkana people, pastoralist nomads who live in the Northwest of Kenya. Low literacy has resulted in an acute shortage of local teachers, a state of affairs which exacerbates the situation. Nomadic communities like the Turkana people rarely attract national discussions on education curriculum even as their children continue to perform poorly on national examinations. The author of this article demonstrates the importance of integrating Indigenous knowledge and mother-tongue instruction in the curriculum for pastoralist schools. Based on his own research in Turkana County, he identifies two main problems besides the shortage of teachers, namely the inappropriateness of the materials used for instruction, which do not reflect the pastoralist children's local Indigenous culture and everyday environment; and the failure to use Turkana mother tongue in early childhood education, which would support children's literacy development, and thus serve to improve literacy rates in the community as a whole. The author presents a family literacy project he was involved in which has made a promising start in addressing these two issues. Stories were collected from parents and elders and made into storybooks, thereby creating tailor-made, meaningful instruction materials. The author expresses his hope that this article will stimulate critical discussions in Kenya which will respect the participation of pastoralist nomadic communities in making decisions about education policy.
Keywords: Administration of Education Programs; Adult education; Children of nomads; Continuing education; Education policy; Elementary and Secondary Schools; Higher education; Other local, municipal and regional public administration; Other provincial and territorial public administration; Professional and Management Development Training; Secondary education

Indigenous Knowledge Practices for Sustainable Lifelong Education in Pastoralist Communities of Kenya - Ng'asike, John Teria (Indigenous Knowledge Practices for Sustainable Lifelong Education in Pastoralist Communities of Kenya, 2019)
Despite setting high hopes on education, very few pastoral nomad children in Kenya transition from primary education to secondary education. This article argues that the national Kenyan compulsory formal curriculum fails to accommodate the needs of pastoralist communities. Literacy rates are particularly low among the Turkana people, pastoralist nomads who live in the Northwest of Kenya. Low literacy has resulted in an acute shortage of local teachers, a state of affairs which exacerbates the situation. Nomadic communities like the Turkana people rarely attract national discussions on education curriculum even as their children continue to perform poorly on national examinations. The author of this article demonstrates the importance of integrating Indigenous knowledge and mother-tongue instruction in the curriculum for pastoralist schools. Based on his own research in Turkana County, he identifies two main problems besides the shortage of teachers, namely the inappropriateness of the materials used for instruction, which do not reflect the pastoralist children's local Indigenous culture and everyday environment; and the failure to use Turkana mother tongue in early childhood education, which would support children's literacy development, and thus serve to improve literacy rates in the community as a whole. The author presents a family literacy project he was involved in which has made a promising start in addressing these two issues. Stories were collected from parents and elders and made into storybooks, thereby creating tailor-made, meaningful instruction materials. The author expresses his hope that this article will stimulate critical discussions in Kenya which will respect the participation of pastoralist nomadic communities in making decisions about education policy.
Keywords: Achievement Tests; African Culture; African Languages; Culturally Relevant Education; Early Childhood Education; Educational Attainment; Educational Policy; Elementary School Students; Ethnic Groups; Foreign Countries; Indigenous Knowledge; Instructional Materials; Kenya; Language of Instruction; Leadership; Literacy; Literacy Education; Low Achievement; Material Development; Migrants; National Curriculum; Native Language; Native Language Instruction; Parent Attitudes; Participative Decision Making; Secondary Education; Teacher Shortage

Handbook of Research on Innovative Digital Practices to Engage Learners - Bull, Prince Hycy; Keengwe, Jar (IGI Global, 2019)
Digital integration is the driving force of teaching and learning at all levels of education. As more non-traditional students seek credentialing, certification, and degrees, institutions continue to push the boundaries of innovative practices to meet the needs of diverse students. Programs and faculty have moved from merely using technology and learning management systems to unique and innovative ways to engage learners. The "Handbook of Research on Innovative Digital Practices to Engage Learners" is a scholarly publication that offers theoretical frameworks, delivery models, current guidelines, and digital design techniques for integrating technological advancements in education contexts to enforce student engagement and positive student outcomes. Featuring a wide range of topics such as gamification, wearable technologies, and distance education, this book is ideal for teachers, curriculum developers, instructional designers, principals, deans, administrators, researchers, academicians, education professionals, and students. The following chapters are contained in this book: (1) Gaming to Learn: Bringing Escape Rooms to the Classroom (Kerry A. Bartlett and Janice L. Anderson); (2) Engaging Learners with Digital Literacy Practices (Jessica Mantei, Kylie Lipscombe, Lyn Cronin, and Lisa Kervin); (3) Breakout of a Traditional Classroom Reality with Game-Based Learning Pedagogy (Kerri Brown Parker and Peter A. Hessling); (4) Constructing Meaning and Engaging Learners through Digital Tools and Practices within the Middle Level Science Classroom (Christine Anne Royce and Susan German); (5) Solving the Creativity Crisis: The Critical Need for Professional Development in Maker-Centered Teaching (Denise M. Bressler); (6) Room to IMPROVE: Designing Virtual Professional Learning Environments (Sydney Brown, Jennifer Putnam, and Holly Mabry); (7) Examining the Links Between Affect Toward 3D Printing Technology and Interest in STEM Careers among Female Elementary Students (Nagla Ali, Shaljan Areepattamannil, Ieda Santos, and Myint Khine); (8) Using SMART Table Technology for the Interactive Elementary Classroom (James N. Oigara); (9) Saudi Arabia's Female Middle School Mathematics Teachers' Readiness and Attitudes Towards STEM Digital Technology Integration in Classrooms (Rabab Mohammed Mousa and Gilbert Kalonde); (10) Lessons Learned: Teaching Latinx Teacher Candidates through Digital Literacy and Community Service Learning (Kathy Bussert-Webb and Karin A. Lewis); (11) Engaging Learners: A Digital Best Practice (Anita Chadha); (12) Multimedia Learning: Simulated vs. Real-World Digital Logic Circuit Curriculum (Jared Wuerzburger and Oscar G. Henriquez); (13) Inclusive Education in Science Education: Are Science Teachers Using Inclusive Technologies in Science Classrooms? (Gilbert Kalonde); (14) E-Portfolios and Learning Management Systems: A New Blend for Learning in Teacher Education (Angelia Reid-Griffin); (15) Learning From Failure: Using Collaborative Technology to Make the Feedback Loop Work (Natalie Edwards Bishop and Hannah Allford); (16) MusicWorks: Supporting Students' Musical Career Paths through Technology-Enhanced Authentic Learning (Carol Johnson, Kenneth B. McAlpine, and Bradley Merrick); (17) Computational Participation as a Portal to Collaborative STEM (Ramya Sivaraj); (18) Role of IT Culture in Learners' Acceptance of E-Learning (James Wairimu, Susan Githua, and Kenneth Kungu); (19) Teaching and Learning 21st Century Skills for Life (Joseph Ezale Cobbinah); and (20) Integrating Formal and Informal Learning Opportunities of Technology in Higher Education (Emine Sendurur, Hatice Gökçe Bilgiç, and Polat Sendurur). A section about the contributors and an index are also included.
Keywords: Assistive Technology; Best Practices; Career Exploration; Computer Peripherals; Computer Simulation; Cooperative Learning; Creative Thinking; Distance Education; Educational Change; Educational Games; Educational Technology; Electronic Learning; Electronic Publishing; Elementary School Students; Foreign Countries; Geography Instruction; Graduate Study; Inclusion; Informal Education; Information Technology; Integrated Learning Systems; Kenya; Learner Engagement; Mathematics Teachers; Middle School Students; Middle School Teachers; Multimedia Instruction; Music Education; Pedagogical Content Knowledge; Portfolios (Background Materials); Printed Materials; Publications; Readiness; STEM Education; Saudi Arabia; Science Careers; Science Education; Science Teachers; Secondary School Science; Story Telling; Technological Advancement; Technological Literacy; Technology Integration; Women Faculty

Influence of Teachers Preparedness on Performance of Pupils in Mathematics in Lower Primary Schools in Aberdares Region of Kenya - Kariuki, Loise Wangechi; Njoka, Johannes Njagi; Mbugua, Zachariah Kariuki (Influence of Teachers Preparedness on Performance of Pupils in Mathematics in Lower Primary Schools in Aberdares Region of Kenya, 2019)
Performance in Mathematics among pupils in lower primary schools in Kenya is a problem that continues to be a concern to parents, teachers and stakeholders in education. Teacher related factors and in particular teacher preparedness has been cited as a major contributing factor to poor teaching methods which fundamentally translates to pupils' poor performance. The purpose of the study was to evaluate the influence of teacher preparedness on pupils' performance in Mathematics in lower primary schools in the Aberdares region of Kenya. The objectives of the study were to; evaluate the influence of teachers' preparation of lesson plans on pupils' performance in Mathematics in lower primary schools and assess the influence of teachers' preparation of schemes of work on pupils' performance in Mathematics in lower primary schools from the Aberdares region in Kenya. The following hypothesis were tested; Ho1: There is no statistically significant relationship between teachers' preparation of lesson plans and performance in Mathematics among pupils in lower primary schools, Ho2: There is no statistically significant relationship between teachers' preparation of schemes of work and pupils' performance in Mathematics in lower primary schools. The study adopted the descriptive survey research design. The study was guided by the Social Constructivism Theory (SCT) advanced by Vygotsky (1978). The target population for the study consisted of all the 385 teachers and 1320 pupils in the public primary schools in Aberdares region of Kenya. A sample of schools was selected using Gay's 10-20% sampling principle which yielded a sample size of 77 teachers and 264 pupils. Data for the study was collected using questionnaires administered to the respondents. The t-test statistic was computed to test the hypothesis which stated that there was no statistically significant relationship between teachers' preparation of lessons and pupils' performance in Mathematics. The t-test yielded a p-value = 0.027 which was less than the a-value of 0.05 hence the hypothesis was rejected. It was concluded that there were differences in pupils' performance in Mathematics depending on teacher preparation of lesson. Regarding the preparation of schemes of work, the computed t- test statistic yielded a p-value = 0.039 which was less than the p-value of 0.05. Therefore the null hypothesis was accepted. It was concluded that the pupils Mathematics mean scores were relatively the same regardless of whether the teacher prepared schemes of work or not. It is recommended that there is need for teachers to institutionalize as a best practice the preparation of professional documents before commencement of teaching.
Keywords: Correlation; Elementary School Mathematics; Elementary School Students; Elementary School Teachers; Foreign Countries; Kenya; Lesson Plans; Mathematics Achievement; Mathematics Instruction; Mathematics Teachers; Teacher Education; Teacher Influence; Teacher Student Relationship

Component Skills of Reading and Their Structural Relations: Evidence from Three Sub-Saharan African Languages with Transparent Orthographies - Kim, Young-Suk Grace; Piper, Benjamin (Component Skills of Reading and Their Structural Relations: Evidence from Three Sub-Saharan African Languages with Transparent Orthographies, 2019)
Background: We examined the component skills of reading comprehension (i.e., letter sound knowledge, syllable reading fluency, decoding fluency, text or oral reading fluency and listening comprehension) and their structural relations using data from three sub-Saharan African languages with transparent orthographies in a multilingual context. Methods: Data from Kiswahili (N = 946), Kikamba (N = 444) and Lubukusu (N = 499) reading assessments at the end of Grade 2 in Kenya were analysed using path analyses. Results: The magnitudes of the relations were similar across the three languages with some differences amongst the languages. Total effects (regression weights), accounting for direct and indirect effects, varied across the component skills: text reading fluency (0.73 to 0.77), decoding fluency (0.49 to 0.82), letter sound knowledge (0.44 to 0.45), syllable reading fluency (-0.12 to 0.16) and listening comprehension (0.08 to 0.23). Conclusions: The results indicate similar reading mechanisms across the three sub-Saharan languages. [This article was published in the "Journal of Research in Reading" (EJ1213011).]
Keywords: African Languages; Correlation; Decoding (Reading); Elementary School Students; Foreign Countries; Grade 2; Kenya; Listening Comprehension; Multilingualism; Oral Reading; Path Analysis; Phoneme Grapheme Correspondence; Reading Comprehension; Reading Fluency; Reading Tests; Syllables

Cross-Language Transfer of Reading Skills: An Empirical Investigation of Bidirectionality and the Influence of Instructional Environments - Kim, Young-Suk Grace; Piper, Benjamin (Cross-Language Transfer of Reading Skills: An Empirical Investigation of Bidirectionality and the Influence of Instructional Environments, 2019)
The linguistic interdependence hypothesis (Cummins, 1979, 2000) states that children's second-language (L2) proficiency is, to some extent, a function of their first-language (L1) competence. Previous studies have examined this hypothesis with focus on a unidirectional relation from L1 to L2. In the present study, we examined "bidirectional" influences of literacy skills in multilingual contexts, and whether the nature of relations varied as a function of literacy instruction environment. To do so, we used longitudinal data from a randomized controlled trial of a literacy intervention for children in Grades 1 and 2, learning to read in Kiswahili and English, two official languages in Kenya. Children in the treatment condition received explicit and systematic instruction on literacy (e.g., phonological awareness, phoneme-grapheme correspondences) in Kiswahili and English, whereas children in the control condition did not. Overall results supported bidirectionality of relations, such that children's literacy skills in the two languages were reciprocally related over time. However, directionality of relations differed as a function of language and literacy instruction condition, such that the relation from English to Kiswahili was found across intervention conditions, but the relation from Kiswahili to English was found only among children who had received explicit instruction in Kiswahili reading. These results are discussed in light of theory and practice for language and literacy acquisition in multilingual contexts. [This article was published in "Reading and Writing" (EJ1210814).]
Keywords: African Languages; Comparative Analysis; Correlation; Elementary School Students; English (Second Language); Foreign Countries; Grade 1; Grade 2; Intervention; Kenya; Language Proficiency; Linguistic Theory; Literacy Education; Longitudinal Studies; Multilingualism; Native Language; Official Languages; Phoneme Grapheme Correspondence; Phonological Awareness; Reading Skills; Second Language Learning; Teaching Methods; Transfer of Training

Heteroglossic Practices in a Multilingual Science Classroom - Kiramba, Lydiah Kananu (Heteroglossic Practices in a Multilingual Science Classroom, 2019)
This paper uses sociocultural theories of language learning to investigate how teachers and students navigate between monolingual institutional policies and the multilingual realities encountered in a rural Kenyan fourth-grade classroom. The paper addresses not only how learners' communicative repertoires are deployed to make meaning in a foreign-language instruction context but also the sociocultural significance of these communicative practices. Results illustrate how the science teacher used heteroglossic practices to mediate students' access to literacy, hence, supporting the content learning and language development of students. Both the science teacher and the students preferred a more flexible use of language to make sense of their multilingual realities as opposed to monolingual view of literacy imposed on them by the language policy. I argue for the potential of heteroglossic practices in multilingual classrooms to ease the cognitive load of English language learners in the process of learning in an additional language. The findings highlight the need for legitimizing fluid language practices in multilingual classrooms in the process of acquiring an additional language and preparing teachers for a multilingual reality.
Keywords: Access to Education; African Languages; Classroom Communication; Cultural Background; Dialects; Elementary School Students; Elementary School Teachers; English (Second Language); Foreign Countries; Grade 4; Kenya; Language Usage; Literacy Education; Multilingualism; Native Language; Rural Schools; Science Instruction; Science Teachers; Second Language Instruction; Second Language Learning; Sociocultural Patterns; Teacher Student Relationship; Teaching Methods

Kenyan Curriculum Reforms and Mother Tongue Education: Issues, Challenges and Implementation Strategies. - Mandillah, Lucy (Kenyan Curriculum Reforms and Mother Tongue Education: Issues, Challenges and Implementation Strategies., 2019)
The implementation of mother tongue education (MTE) remains a challenge across Africa and Kenya in particular. This continues despite the fact that the maintenance and development of language and literacy skills in one's mother tongue (MT) plays a critical role in facilitating second language (L2) learning, developing additive bilingualism and continuous cognitive development. Consequently, Kenya has had several education commissions in both colonial and post-colonial periods, which, together with the Constitution of Kenya have had a bearing on the language policy. However, the language policy has not been supported by a careful implementation strategy for MTE. Presently, Kenya is undergoing curriculum reforms from the ongoing 8-4-4 system, where learners study for eight years of basic (primary) education, four years of secondary education and four years of university education to a new system of 2-6-3-3-3. The 2-6-3-3-3 system comprises two years of pre-primary, six years of primary (three years lower and three years upper primary), six years of secondary (three years junior and three years senior) and three years of university education. While English has been given preponderant attention in the new curriculum, the role of MT has also been re-emphasised because it has not received as much attention as it deserves in the past. It is against this background and the ongoing debates on MTE that this paper attempts to examine the challenges that are likely to impede the implementation of MTE in the 2-6-3-3-3 curriculum reforms as outlined in the education policy. The paper further suggests some implementation strategies to avert the challenges. The study was conducted in Bungoma County in Kenya. Purposive sampling was used to identify key respondents from 10 schools which were used to pilot the new curriculum. The respondents included Grade 3 teachers, head teachers and quality assurance officers (QASOs). Focus group discussions (FGDs), unstructured interviews and document analysis were used to elicit data. The findings revealed that the implementation of MTE policy is likely to flop if it is not supported by careful implementation strategies that take care of teacher training, the production of teaching/learning materials and attempts to change the attitudes of parents towards indigenous languages. The paper advocates for implementation strategies such as greater resource allocation, teacher training on L1 methodologies, a change in attitude with regard to MTE, political will and clearer policy objectives to achieve the aims of an effective MTE system in Kenya.
Keywords: Curriculum change; Language acquisition; Native language

Kenyan Curriculum Reforms and Mother Tongue Education: Issues, Challenges and Implementation Strategies - Mandillah, Lucy (Kenyan Curriculum Reforms and Mother Tongue Education: Issues, Challenges and Implementation Strategies, 2019)
The implementation of mother tongue education (MTE) remains a challenge across Africa and Kenya in particular. This continues despite the fact that the maintenance and development of language and literacy skills in one's mother tongue (MT) plays a critical role in facilitating second language (L2) learning, developing additive bilingualism and continuous cognitive development. Consequently, Kenya has had several education commissions in both colonial and post-colonial periods, which, together with the Constitution of Kenya have had a bearing on the language policy. However, the language policy has not been supported by a careful implementation strategy for MTE. Presently, Kenya is undergoing curriculum reforms from the ongoing 8-4-4 system, where learners study for eight years of basic (primary) education, four years of secondary education and four years of university education to a new system of 2-6-3-3-3. The 2-6-3-3-3 system comprises two years of pre-primary, six years of primary (three years lower and three years upper primary), six years of secondary (three years junior and three years senior) and three years of university education. While English has been given preponderant attention in the new curriculum, the role of MT has also been re-emphasised because it has not received as much attention as it deserves in the past. It is against this background and the ongoing debates on MTE that this paper attempts to examine the challenges that are likely to impede the implementation of MTE in the 2-6-3-3-3 curriculum reforms as outlined in the education policy. The paper further suggests some implementation strategies to avert the challenges. The study was conducted in Bungoma County in Kenya. Purposive sampling was used to identify key respondents from 10 schools which were used to pilot the new curriculum. The respondents included Grade 3 teachers, head teachers and quality assurance officers (QASOs). Focus group discussions (FGDs), unstructured interviews and document analysis were used to elicit data. The findings revealed that the implementation of MTE policy is likely to flop if it is not supported by careful implementation strategies that take care of teacher training, the production of teaching/learning materials and attempts to change the attitudes of parents towards indigenous languages. The paper advocates for implementation strategies such as greater resource allocation, teacher training on L1 methodologies, a change in attitude with regard to MTE, political will and clearer policy objectives to achieve the aims of an effective MTE system in Kenya.
Keywords: African Languages; Attitude Change; Competency Based Education; Curriculum Implementation; Educational Policy; Elementary School Teachers; Foreign Countries; Instructional Materials; Kenya; Language of Instruction; Native Language Instruction; Parent Attitudes; Principals; Teacher Education; Teacher Shortage

Justifications and Impacts of Low-Fee Private Schools in Kenya and Uganda: Understanding Policy Evolutionary Mechanisms through Public Discourse of Bridge International Academies - Monk, Jeremy (Justifications and Impacts of Low-Fee Private Schools in Kenya and Uganda: Understanding Policy Evolutionary Mechanisms through Public Discourse of Bridge International Academies, 2019)
Low-fee private schools (LFPS) have grown considerably in the developing world as public free primary education has been unable to cater to the poorest children. Bridge International Academies (BIA), one of the largest chains of LFPS, has positioned itself as a solution to issues of access and quality of primary education. Using newspaper articles from Kenya and Uganda, this paper examines public discourse of BIA through the lens of cultural political economy, or how public discourse can influence variation, selection and retention regarding LFPS. After exploring scholarship to understand the justifications and impacts of LFPS, this paper finds that justifications are present in public discourse while impacts are not. Therefore, public discourse has given voice and promoted the need for improvements, with LFPS as an option, but that discourse (and scholarship) has yet to emphasize LFPS as a real solution, due to inconclusive evidence and ongoing battles with governments.
Keywords: Access to Education; Cross Cultural Studies; Cultural Influences; Discourse Analysis; Educational Policy; Educational Quality; Elementary Education; Foreign Countries; Government School Relationship; Kenya; News Reporting; Political Attitudes; Poverty; Private Schools; Slums; Uganda; Unions; Urban Areas

'Bilingualizing' Linguistically Homogeneous Classrooms in Kenya: Implications on Policy, Second Language Learning, and Literacy - Mose, Peter Nyakundi ('Bilingualizing' Linguistically Homogeneous Classrooms in Kenya: Implications on Policy, Second Language Learning, and Literacy, 2019)
Bilingualism characterizes people in linguistically heterogeneous settlements like Nairobi among other urban centres in Kenya. But the country is also predominantly rural (where you find people of a common language settled in one geographical rural region) in which mother tongues are primary means of communication. Children in lower primary in rural areas should be taught in their mother tongues. The purpose of this study was to find out the use of mother tongues and official languages in elementary linguistically homogeneous classrooms in Kenya and the possible effect of this use. Data were obtained through classroom observations and interviews with classroom teachers and head teachers. The findings indicate that instead of using mother tongues to teach, teachers use Kiswahili (a national and co-official language) and English (an official language) in various ways to teach content subjects; mathematics, science, social/religious studies, hence making the classrooms bilingual. The article presents evidence and discusses how this use of language affects learning and what it implies on language in education policy, on second language learning, and on early literacy development. Negative effects of the practice include poor learning outcomes and poor teacher morale. The study recommends corrective steps to avert learning and literacy development losses.
Keywords: African Languages; Bilingualism; Classroom Communication; Educational Policy; Elementary School Students; Emergent Literacy; English (Second Language); Foreign Countries; Grouping (Instructional Purposes); Kenya; Language of Instruction; Literacy; Native Language; Observation; Official Languages; Outcomes of Education; Rural Areas; Second Language Learning; Teacher Attitudes; Teacher Morale; Teaching Methods

Assessing Learning: How Can Classroom-Based Teachers Assess Students' Competencies in Numeracy? - Ngware, Moses W.; Hungi, Njora; Mutisya, Maurice (Assessing Learning: How Can Classroom-Based Teachers Assess Students' Competencies in Numeracy?, 2019)
This paper examines a procedure measuring student competencies in numeracy using school-based assessments, and demonstrates how the procedure informs the school system on quality improvement. The sample consisted of 7648 students, attending three different types of urban schools including government, formal private and low cost private in poor informal settlements in Kenya. The numeracy tool measures six curriculum outcome areas. Each outcome area is defined by 2-11 measured items based on the emphasis given to an area in the curriculum. Within each of the outcome areas, items are also hypothesised to measure categories of the cognitive domain of learning. Using the Rasch, we examine the item difficulties, person location and differential item functioning. The paper provides important implications to provision of evidence to inform teaching in poor urban informal settlements in Kenya and this can also be replicated in other sub-Saharan African countries.
Keywords: Assessment Literacy; Benchmarking; Classroom Techniques; Competency Based Education; Difficulty Level; Educational Improvement; Elementary School Students; Foreign Countries; Grade 3; Item Response Theory; Kenya (Nairobi); Mathematics Skills; Mathematics Teachers; National Curriculum; Numeracy; Poverty Areas; Private Schools; Public Schools; Student Evaluation; Test Items; Urban Schools

Access, poverty and learning achievement for primary school leavers in Kenya: analysis of evidence from 47 counties. - Oketch, Moses (Access, poverty and learning achievement for primary school leavers in Kenya: analysis of evidence from 47 counties., 2019)
To what extent, if at all, did the introduction of free primary education in Kenya in 2003 have positive equity effects, in terms of both access and achievement. Access is based on the number of candidates sitting the Kenya Certificate of Primary Education (KCPE) examination and the KCPE score is used to measure achievement levels. The study uses data that reflects Kenya's 47 devolved governance counties. A quantitative measure of poverty in all 47 counties was then entered as an independent variable of regression analysis, and a negative association with KCPE performance noted (high poverty levels associated with low KCPE scores). Also noted was a contrast between counties showing high enrolment impact and improved KCPE scores, and those showing high enrolment impact and lower KCPE scores. Counties in the former group are located almost entirely in arid and semi-arid areas, those in the latter group in the coastal region.
Keywords: Coastal development; Kenya; Kenyan economy; Poverty; Primary education; Regression analysis; Social history

Access, Poverty and Learning Achievement for Primary School Leavers in Kenya: Analysis of Evidence from 47 Counties - Oketch, Moses (Access, Poverty and Learning Achievement for Primary School Leavers in Kenya: Analysis of Evidence from 47 Counties, 2019)
To what extent, if at all, did the introduction of free primary education in Kenya in 2003 have positive equity effects, in terms of both access and achievement. Access is based on the number of candidates sitting the Kenya Certificate of Primary Education (KCPE) examination and the KCPE score is used to measure achievement levels. The study uses data that reflects Kenya's 47 devolved governance counties. A quantitative measure of poverty in all 47 counties was then entered as an independent variable of regression analysis, and a negative association with KCPE performance noted (high poverty levels associated with low KCPE scores). Also noted was a contrast between counties showing high enrolment impact and improved KCPE scores, and those showing high enrolment impact and lower KCPE scores. Counties in the former group are located almost entirely in arid and semi-arid areas, those in the latter group in the coastal region.
Keywords: Academic Achievement; Access to Education; Counties; Elementary Education; Elementary School Students; Enrollment; Equal Education; Foreign Countries; Kenya; Poverty; Public Education; Scores

Meeting the Data Challenge in Education. A Knowledge and Innovation Exchange (KIX) Discussion Paper - Crouch, Luis (2019)

Mentorship Policy for Early Learning and Basic Education - Republic of Kenya (2019)

Sessional Paper No. 1 of 2019 on a Policy Framework for Reforming Education and Training for Sustainable Development in Kenya - Republic of Kenya (2019)

The Basic Education Curriculum Framework - Republic of Kenya (2019)

The National Curriculum Policy, 2018 - Republic of Kenya (2019)

More than 855,000 children remain out of school in North-West and South-West Cameroon - UNICEF (2019)

How Kenyan Parents Maximize Their Children's Full Potential - Swigert-Gacheru, Margaretta (How Kenyan Parents Maximize Their Children's Full Potential, 2018)
Kenyan parents want their children to have an education that will maximize their full potential, and they are prepared to make tremendous sacrifices to ensure their children get that education. However, the best schools cost far more than most families can afford, and even the most humble local schools require parents to pay for school fees, school uniforms, and books. Many a young Kenyan has dropped out of school for lack of funds. Parents are among the primary teachers of their gifted children, whether the child has access to formal schooling or not. This paper provides suggestions on ways that parents can model for their gifted children, including reading a book they picked up at the library; playing a musical instrument, singing, or joining a theater group; and continuing their own informal education. By nurturing their own talents and sharing what they have learned, parents can bring new insights to their children on a daily basis to help them reach their full potential.
Keywords: Academically Gifted; Foreign Countries; Informal Education; Kenya; Learning Activities; Modeling (Psychology); Parent Child Relationship; Parent Participation; Parents as Teachers

Including all voices in international data-sharing governance - Kaye, Jane; Terry, Sharon F.; Juengst, Eric; Coy, Sarah; Harris, Jennifer R.; Chalmers, Don; Dove, Edward S.; Budin-Ljøsne, Isabelle; Adebamowo, Clement; Ogbe, Emilomo; Bezuidenhout, Louise; Morrison, Michael; et al. (Human Genomics, 2018)
Governments, funding bodies, institutions, and publishers have developed a number of strategies to encourage researchers to facilitate access to datasets. The rationale behind this approach is that this will bring a number of benefits and enable advances in healthcare and medicine by allowing the maximum returns from the investment in research, as well as reducing waste and promoting transparency. As this approach gains momentum, these data-sharing practices have implications for many kinds of research as they become standard practice across the world. The governance frameworks that have been developed to support biomedical research are not well equipped to deal with the complexities of international data sharing. This system is nationally based and is dependent upon expert committees for oversight and compliance, which has often led to piece-meal decision-making. This system tends to perpetuate inequalities by obscuring the contributions and the important role of different data providers along the data stream, whether they be low- or middle-income country researchers, patients, research participants, groups, or communities. As research and data-sharing activities are largely publicly funded, there is a strong moral argument for including the people who provide the data in decision-making and to develop governance systems for their continued participation. We recommend that governance of science becomes more transparent, representative, and responsive to the voices of many constituencies by conducting public consultations about data-sharing addressing issues of access and use; including all data providers in decision-making about the use and sharing of data along the whole of the data stream; and using digital technologies to encourage accessibility, transparency, and accountability. We anticipate that this approach could enhance the legitimacy of the research process, generate insights that may otherwise be overlooked or ignored, and help to bring valuable perspectives into the decision-making around international data sharing.

Is international migration always good for left behind households members? Evidence from children education in Cameroon. - Kuépié, Mathias (International Migration, 2018)
This study contributes to the debate about the net gain of international migration on development by analyzing the effect of migration on school attendance of children of left‐behind households in Cameroon. A quick literature review shows that migration can impact children's education through two main channels: the "budget constraint" channel and the "family disruption" channel. Based on this literature review, we develop a theoretical framework to highlight the underlying mechanisms. In order to empirically assess the two channels, we use a survey designed for this purpose. Results highlight a detrimental effect of migration on boys' school attendance, whereas girls are not affected. This negative effect is mainly explained by parental and recent migrations. Thus our empirical results provide evidence on the fact that, in the Cameroonian context, international migration does not always positively influence development, at least as far as children's education is concerned. [ABSTRACT FROM AUTHOR]
Keywords: CAMEROON; EDUCATION; EDUCATION of boys; EDUCATION of girls; EMIGRATION & immigration; SCHOOL attendance

Preschool attendance and children's reading ability: A case of Narok County Kenya. - Mwoma, Teresa (Preschool attendance and children's reading ability: A case of Narok County Kenya., 2018)
This article reports findings of a study conducted in public primary schools in Narok County Kenya. A sample size comprising 74 children in Grade 3 (37 who did not attend preschool and 37 who attended preschool), 18 head teachers, 66 lower primary school teacher's and five education officers were selected for the study. Learners' reading ability was tested using the Kenya Early Grade Reading Assessment Tests for English and Kiswahili adapted from Department for International Development end line survey of 2014. Interviews of head teachers, teachers, and education officers were conducted. Findings revealed that children who attended preschool performed better in English sub-tasks than those who did not attend preschool. However, those who did not attend preschool performed better in Kiswahili than their counter parts. Teachers revealed that they create extra time to support children who did not attend preschool, which explains why such children performed better in Kiswahili.
Keywords: Child Day Care Services; Preschool education; Reading ability testing

Adolescent girls’ primary school mobility and educational outcomes in urban Kenya. - Maluccio, John A.; Hussein, Mohamed; Abuya, Benta; Muluve, Eva; Muthengi, Eunice; Austrian, Karen (Adolescent girls’ primary school mobility and educational outcomes in urban Kenya., 2018)
Highlights • There has been substantial growth in private schools in developing countries, accompanied by increasing choice and mobility. • A number of factors determine school mobility, and consequences for educational outcomes of such mobility are ambiguous. • We find that transferring during lower primary leads to a poorer resourced school, but transferring during upper primary a higher resourced school. • Transfers during lower primary are associated with falling behind, while those in upper primary with getting ahead and improved basic test scores. Abstract With hundreds of primary schools to choose from, young adolescent girls in Nairobi’s urban informal settlements commonly transfer schools. We qualitatively investigate the causes and quantitatively investigate the consequences of such mobility. Key reasons for transferring schools include difficulty in paying fees and anticipated net benefits from a different school. Transferring during lower primary leads to a poorer resourced school, while transferring during upper primary a higher resourced school. Correspondingly, transfers during lower primary are associated with falling behind, while in upper primary with getting ahead, as well as with improved basic reading and math test scores.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Education of girls; Educational Support Services; Educational outcomes; Kenya; Primary education; Teenage girls

Changing literacy instruction in Kenyan classrooms: Assessing pathways of influence to improved early literacy outcomes in the HALI intervention. - Wolf, Sharon; Turner, Elizabeth L.; Jukes, Matthew C.H.; Dubeck, Margaret M. (Changing literacy instruction in Kenyan classrooms: Assessing pathways of influence to improved early literacy outcomes in the HALI intervention., 2018)
Abstract This study uses data from the Health and Literacy Intervention (HALI) program evaluation, an in-service teacher training program focused on early grade literacy instruction for class one teachers. We assess how changes in classroom instructional processes impacted by the HALI teacher training were associated with improved early literacy outcomes for children. We find that experimentally induced increases in exposure to print—measured both through changes to time spent reading in class and through print displayed in the classroom—were associated with improvements in students’ reading fluency and reading comprehension. Implications for global education efforts to improve learning outcomes are discussed.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Emergent literacy; Kenya; Literacy education; Reading; Teaching methods

Out of many, one: challenges in teaching multilingual Kenyan primary students in English. - Hsieh, Ching-Ni; Ionescu, Marcel; Ho, Tsung-Han (Out of many, one: challenges in teaching multilingual Kenyan primary students in English., 2018)
Using a large-scale, standardised English language proficiency test (TOEFL® PrimaryTM), this study examined Kenyan primary school students’ English reading and listening proficiency and explored challenges primary school teachers face in using English as the medium of instruction (EMI) to teach their multilingual students. The test was taken by 4768 students in Standards 3-7 from 51 primary schools across the country in Kenya. Seventeen primary school teachers, representing six major geographical regions, participated in semi-structured interviews to explore their teaching challenges. Results show that, regardless of standard/grade level, the majority of the participating students were beginner-level English language users, which suggests that they may not have the language skills needed to understand classroom instruction and learn the subject matter content effectively in English. Interview findings indicate that, as they implement the EMI policy, teachers encounter five major challenges: (1) mother tongue interference, (2) students’ attitudes toward English, (3) lack of usefulness of English language in the community, (4) resource constraints and (5) diverse student backgrounds. The results have pedagogical implications for EMI implementation in similar multilingual contexts.
Keywords: English as a foreign language; English language education; Language Schools; Language ability; Language policy; Multilingualism

Out of many, one: challenges in teaching multilingual Kenyan primary students in English. - Hsieh, Ching-Ni; Ionescu, Marcel; Ho, Tsung-Han (Out of many, one: challenges in teaching multilingual Kenyan primary students in English., 2018)
Using a large-scale, standardised English language proficiency test (TOEFL® PrimaryTM), this study examined Kenyan primary school students’ English reading and listening proficiency and explored challenges primary school teachers face in using English as the medium of instruction (EMI) to teach their multilingual students. The test was taken by 4768 students in Standards 3-7 from 51 primary schools across the country in Kenya. Seventeen primary school teachers, representing six major geographical regions, participated in semi-structured interviews to explore their teaching challenges. Results show that, regardless of standard/grade level, the majority of the participating students were beginner-level English language users, which suggests that they may not have the language skills needed to understand classroom instruction and learn the subject matter content effectively in English. Interview findings indicate that, as they implement the EMI policy, teachers encounter five major challenges: (1) mother tongue interference, (2) students’ attitudes toward English, (3) lack of usefulness of English language in the community, (4) resource constraints and (5) diverse student backgrounds. The results have pedagogical implications for EMI implementation in similar multilingual contexts.
Keywords: English as a foreign language; English language education; Language Schools; Language ability; Language policy; Multilingualism

SCALABILITY OF LEARNERS' SUCCESS RATES IN E-LEARNING:A SURVEY STUDY OF THE LEARNERS' PERSPECTIVES. - Maritim, Ezra K.; Getuno, Daniel Makini (SCALABILITY OF LEARNERS' SUCCESS RATES IN E-LEARNING:A SURVEY STUDY OF THE LEARNERS' PERSPECTIVES., 2018)
Globally, ODL institutions experience mismatch between scalability of numbers and scalability ofsuccess rates. This study explored the scalability of success rates in open, distance e-learning asperceived by the learners within the Chain of Response Model. The primary aim of the study was tolook at online learners' success rate by focusing on two institutional factors drawn from the Model,namely: the learner's study modules related challenges and support services. The results of an onlinesurvey of 180 undergraduate and postgraduate online learners of Egerton University, Kenya,showed: (a) the response rate of 16%; (b) a mixture of hardware, software and personal factorswere identified as pre-requisites for e-learning success: (c) a number of mathematically-basedmodules were identified as risks to success in online studies; and (d) while the learners saw thelearner support services as important they were less satisfied with their provision. The present studypoints to two broad areas that require further studies. First, qualitative look into specific challengesthat learners face with respect to learner support service provisions, modules interactivity, andthose identified as difficult to follow and thus posing risks to the learners' success. Second,investigation into tutor-learner contacts with the view of identifying whether such contacts arereactive or proactive.
Keywords: Academic achievement; Administration of Education Programs; Adults; All Other Miscellaneous Schools and Instruction; Distance education; Education; Educational Support Services; Egerton University; Higher education; Kenya; Mobile learning

Early Mathematics Counts: Promising Instructional Strategies from Low- and Middle-Income Countries. Occasional Paper. RTI Press Publication OP-0055-1807 - Sitabkhan, Yasmin; Platas, Linda M.; RTI International (RTI International, 2018)
This paper examines common instructional strategies in early grade mathematics interventions through a review of studies in classrooms in low- and middle-income countries. Twenty-four studies met the criteria for inclusion, and analyses reveal four sets of instructional strategies for which there is evidence from multiple contexts. Of the 24 studies, 16 involved the use of multiple representations, 10 involved the use of developmental progressions, 6 included supporting student use of explanation and justification, and 5 included integration of informal mathematics. Based on the review, we provide conclusions and recommendations for future research and policy.
Keywords: Bangladesh; Colombia; Developmentally Appropriate Practices; Early Childhood Education; Elementary School Mathematics; Elementary School Students; Ethiopia; Foreign Countries; Guatemala; India; Informal Education; Jordan; Kenya; Kosovo; Liberia; Low Income Groups; Malawi; Manipulative Materials; Mathematical Logic; Mathematics Instruction; Mozambique; Paraguay; Peru; Preschool Children; Rwanda; Socioeconomic Influences; South Africa; Teaching Methods; Turkey; Zambia

The effects of preschool participation on mathematics achievement of Grade 6 pupils in Uganda. - Hungi, Njora; Ngware, Moses (The effects of preschool participation on mathematics achievement of Grade 6 pupils in Uganda., 2018)
The objective of this article is to investigate the effects of preschool participation on learning achievement and to estimate the optimal duration of preschool participation needed for pupils to perform their best in mathematics at the Grade 6 level in Uganda. The sample consisted of 2649 Grade 6 pupils, attending 82 schools across two rural districts of Iganga and Mayuge in Uganda. Understanding the relationship between duration of preschool participation and pupils’ future learning achievement is important to policies on preschool education in Uganda. Results from multilevel analyses show that preschool participation has positive impact on mathematics achievement of Grade 6 pupils. Results further showed that the positive impact of preschool on achievement seemed to level out after 2 years of preschool participation—meaning that 2 years was the optimal duration of preschool participation that was most helpful in boosting achievement. The implications of the finding to preschool education policy and practices are discussed.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Mathematics education (Early childhood); Sixth grade (Education); Uganda

The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-year Account of Research in Kenya, Malawi and South Africa. - Essien, Anthony A. (The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-year Account of Research in Kenya, Malawi and South Africa., 2018)
The purpose of this study was to provide a systematic review of research that has been carried out between 2006 and 2016 on the role of language in early grade (Grades 1-4) mathematics teaching and learning in three countries—Kenya, Malawi and South Africa. These countries were selected because they have similar characteristics: teaching and learning occur in a multilingual context; their language in education policies are similar; transition from mother tongue to English happens during the early grades; and most of the learners learn mathematics in English—a language which for most is not their first/home language. Research outputs between 2006 and 2016 from the three countries were sourced from peer-reviewed mathematics and general education journals, monitoring and evaluation reports, and book chapters. Findings from the study revealed that there is a lack of longitudinal studies that investigate the impact of language on the teaching and learning of mathematics and that there are few studies on how teachers are and should be trained to teach mathematics in the early grades. The study also found that the implementation of the language in education policies in the three different focus countries is fraught with difficulties owing to a number of factors, amongst them the fact that the indigenous languages are not yet fully developed as academic languages. Finally, existing literature highlights the importance of the use of code switching and the provision of materials in the home language(s) of early graders. Recommendations regarding policy/curriculum, teacher education and pedagogic practices are made.

Effects of Language of Instruction on Learning of Literacy Skills among Pre-Primary School Children from Low-Income Urban Communities in Kenya - Hungi, Njora; Njagi, Joan; Wekulo, Patricia; Ngware, Moses (Effects of Language of Instruction on Learning of Literacy Skills among Pre-Primary School Children from Low-Income Urban Communities in Kenya, 2018)
This study investigates the relationship between the language of instruction and learning of literacy skills among pre-primary school children in a multilingual environment. The sample consists of 1867 learners from low-income urban households, attending 147 low-cost private pre-primary schools located in low-income areas of Nairobi, Kenya. About one-half (48.4%) of the learners were taught basic aspects of literacy such as letter naming, letters sounds and rhymes using Kiswahili (a local lingua franca) while the other half (51.6%) were taught these aspects using English. The learners involved in this study come from different ethnic backgrounds and hence Kiswahili and English are not their first languages. This study poses the question: In a multilingual environment, is there an advantage in learning literacy skills using a second language (in this case Kiswahili) over a third language (English)? Relationship between literacy scores and language of instruction is examined using descriptive techniques. This relationship is further examined using multivariate techniques controlling for learner sex, classroom resources, class size, teacher pre-service training, and teacher years of experience, among other variables. Results show that learners taught literacy skills using Kiswahili significantly outperformed their counterparts taught using English (at p < 0.05 level) even after adjusting for the effects of other factors in the analyses. The implications of the finding to education policy and practices are discussed.
Keywords: African Languages; Alphabets; Bilingual Education; English (Second Language); Foreign Countries; Instructional Effectiveness; Kenya (Nairobi); Language of Instruction; Literacy Education; Low Income Students; Multilingualism; Multivariate Analysis; Outcomes of Education; Phonology; Preschool Children; Private Schools; Reading Instruction; Rhyme; Scores; Second Language Instruction; Urban Areas

Effects of Language of Instruction on Learning of Literacy Skills Among Pre-primary School Children from Low-income Urban Communities in Kenya. - Njora Hungi; Njagi, Joan; Wekulo, Patricia; Ngware, Moses (Effects of Language of Instruction on Learning of Literacy Skills Among Pre-primary School Children from Low-income Urban Communities in Kenya., 2018)
This study investigates the relationship between the language of instruction and learning of literacy skills among pre-primary school children in a multilingual environment. The sample consists of 1867 learners from lowincome urban households, attending 147 low-cost private pre-primary schools located in low-income areas of Nairobi, Kenya. About one-half (48.4%) of the learners were taught basic aspects of literacy such as letter naming, letters sounds and rhymes using Kiswahili (a local lingua franca) while the other half (51.6%) were taught these aspects using English. The learners involved in this study come from different ethnic backgrounds and hence Kiswahili and English are not their first languages. This study poses the question: In a multilingual environment, is there an advantage in learning literacy skills using a second language (in this case Kiswahili) over a third language (English)? Relationship between literacy scores and language of instruction is examined using descriptive techniques. This relationship is further examined using multivariate techniques controlling for learner sex, classroom resources, class size, teacher preservice training, and teacher years of experience, among other variables. Results show that learners taught literacy skills using Kiswahili significantly outperformed their counterparts taught using English (at p < 0.05 level) even after adjusting for the effects of other factors in the analyses. The implications of the finding to education policy and practices are discussed.
Keywords: Kenya; Language ability; Language of instruction; Multilingual education; Preschool children; Second language acquisition

The Impact of Free Primary Education Inputs on Educational Outcomes in Kenya (2003 to 2013): The Rate of Enrolment and Retention at Primary School Level as a Factor - Owuor, Dorothy Akinyi; Ayiro ss, Laban; Too, Jackson (The Impact of Free Primary Education Inputs on Educational Outcomes in Kenya (2003 to 2013): The Rate of Enrolment and Retention at Primary School Level as a Factor, 2018)
Free Primary Education Initiative has been running for more than a decade and its purpose has been to help Kenya achieve equity, parity, quality and higher retention rate in primary schools. This study investigated the impact of FPE inputs on educational outcomes in Kenya. The objective of the study was to determine the rates of enrolment and retention at Primary school level. Random sampling was used for data collection at school level; purposive sampling for teachers namely Head teachers, Deputy Head teachers and senior teachers. Out of a population frame of 641 schools and 7776 teachers from the ten Sub-Counties in Nakuru County, the sample comprised of 384 teachers from 128 primary Schools. Data was collected using questionnaires for teachers and Interview Schedules for the Quality Assurance and Standards Officers and Education officers. The study used both Descriptive and Inferential Statistics for analysis. The findings, therefore confirm an increased rate of enrolment and retention rate. The findings are intended to influence the Government to enhance provision of quality education. This study was also intended to make the government re-asses its education policy and budget allocation so that they target educational inputs that would have the greatest influence on learning outcomes.
Keywords: After School Programs; Budgets; Class Size; Dropout Rate; Educational Facilities; Educational Policy; Educational Quality; Elementary School Students; Enrollment Rate; Foreign Countries; Input Output Analysis; Kenya; Outcomes of Education; Resource Allocation; School Holding Power; Sex Fairness; Student Participation; Teacher Student Ratio; Teacher Student Relationship; Tutoring

Examining the secondary effects of mother-tongue literacy instruction in Kenya: Impacts on student learning in English, Kiswahili, and mathematics. - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Oyanga, Arbogast (Examining the secondary effects of mother-tongue literacy instruction in Kenya: Impacts on student learning in English, Kiswahili, and mathematics., 2018)
Limited rigorous evidence is available from sub-Saharan Africa regarding whether children who learn to read in their mother tongue will have higher learning outcomes in other subjects. A randomised controlled trial of mother-tongue literacy instruction, the Primary Math and Reading (PRIMR) Initiative, was implemented in Kenya from 2013 to 2014. We compared the impacts of the PRIMR mother-tongue treatment group in two languages with those of another group that did not use mother tongue, but utilised the same instructional components. Results showed that assignment to the mother-tongue group had no additional benefits for English or Kiswahili learning outcomes beyond the non-mother-tongue group, and that the mother-tongue group had somewhat lower mathematics outcomes. Classroom observational analysis showed that assignment to the mother-tongue group had only small impacts on the usage of mother tongue in other subjects. Advocates for mother-tongue programmes must consider such results alongside local implementation resistance in programme design.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Kenya; Learning; Native language; Native language & education; Native language instruction; School children

Interrupting Ideologies of Cultural Deficiency: Illustrating Curricular Benefits of Plurilingualism in a Kenyan Classroom. - Wandera, David B.; Farr, Marcia (Interrupting Ideologies of Cultural Deficiency: Illustrating Curricular Benefits of Plurilingualism in a Kenyan Classroom., 2018)
In this paper, we exemplify the resourcefulness of using non-sanctioned ways of speaking in classroom communication within a cross-age literacy collaboration between elementary-level grade 5 and high-school level grade 9 students in Nairobi, Kenya. Our goal is two-fold: to contribute to scholarship that affirms this resourcefulness, and to respond to the need for more studies within western scholarship that are based on non-western linguistic and cultural contexts. Through spotlighting some dynamics of multilayered non-western linguistic practices, this study enriches available evidence for pedagogical planning in our contemporary pluralistic world. We employ discourse analysis grounded in an interactional sociolinguistics approach (Gumperz, 2003) to examine students' use of standard Kenyan English, Sheng, and Swahili. Overall, we argue for inclusivity at two levels: first, culturally inclusive teaching through tapping into active learner participation among other benefits of plurilingualism, and second, at the level of research through challenging western research traditions to achieve comprehensive up-to-date understandings of contemporary language use by broadening contexts of inquiry.
Keywords: Multilingualism; Teaching

Electricity supply, and access to water and improved sanitation as determinants of gender-based inequality in educational attainment in Africa - Njoh, Ambe J.; Ananga, Erick O.; Ngyah-Etchutambe, Ijang B.; Deba, Lucy E.; Asah, Fotoh Jacob; Ayuk-Etang, Elizabeth N. M.; Akiwumi, Fenda A. (Social Indicators Research, 2018)
The central hypothesis of this study is that gender-based inequality in education in Africa depends to a significant degree on electricity supply, and access to water and improved sanitation. Gender-based educational inequality is operationalized in terms of the proportion of females to males within any given group of educated people. Three groups, people with basic literacy skills, people with primary education, and people with a secondary education, are considered. Logarithmically-transformed multiple regression analyses, with R values ranging from .26 to .55, confirmed the central hypothesis in all but one instance. The instance concerns the hypothesized positive link between access to improved sanitation and females with a secondary education. An analysis of the data revealed this relationship as negative. This paradoxical revelation is explained as follows. Recent positive trends in African economies have occasioned improvements in sanitation that are unmatched by a corresponding increase in female secondary education. The confirmed positive link between access to basic services and female education is easy to explain. The availability of basic services facilitates execution of domestic chores hence, free up time for girls and women to pursue educational opportunities. The article's significance resides in its empirical validation of the following widely-held but hardly interrogated view. The progress of women in Africa is significantly retarded by the fact that they are overburdened by domestic chores. [ABSTRACT FROM AUTHOR]
Keywords: AFRICA; EDUCATIONAL equalization; ELECTRIC power; Electricity; Gender parity in education; Gender-based educational inequalities; POWER resources; SANITATION; WATER supply; Water/sanitation in Africa

The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-Year Account of Research in Kenya, Malawi and South Africa - Essien, Anthony A. (The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-Year Account of Research in Kenya, Malawi and South Africa, 2018)
The purpose of this study was to provide a systematic review of research that has been carried out between 2006 and 2016 on the role of language in early grade (Grades 1-4) mathematics teaching and learning in three countries--Kenya, Malawi and South Africa. These countries were selected because they have similar characteristics: teaching and learning occur in a multilingual context; their language in education policies are similar; transition from mother tongue to English happens during the early grades; and most of the learners learn mathematics in English--a language which for most is not their first/home language. Research outputs between 2006 and 2016 from the three countries were sourced from peer-reviewed mathematics and general education journals, monitoring and evaluation reports, and book chapters. Findings from the study revealed that there is a lack of longitudinal studies that investigate the impact of language on the teaching and learning of mathematics and that there are few studies on how teachers are and should be trained to teach mathematics in the early grades. The study also found that the implementation of the language in education policies in the three different focus countries is fraught with difficulties owing to a number of factors, amongst them the fact that the indigenous languages are not yet fully developed as academic languages. Finally, existing literature highlights the importance of the use of code switching and the provision of materials in the home language(s) of early graders. Recommendations regarding policy/curriculum, teacher education and pedagogic practices are made.
Keywords: African Languages; Code Switching (Language); Cross Cultural Studies; Educational Policy; Educational Research; Elementary School Students; English (Second Language); Foreign Countries; Instructional Materials; Kenya; Language Role; Language of Instruction; Longitudinal Studies; Malawi; Mathematics Instruction; Multilingualism; Native Language; Periodicals; Research Reports; Second Language Learning; South Africa; Teacher Education; Teaching Methods

The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-Year Account of Research in Kenya, Malawi and South Africa - Essien, Anthony A. (The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-Year Account of Research in Kenya, Malawi and South Africa, 2018)
The purpose of this study was to provide a systematic review of research that has been carried out between 2006 and 2016 on the role of language in early grade (Grades 1-4) mathematics teaching and learning in three countries--Kenya, Malawi and South Africa. These countries were selected because they have similar characteristics: teaching and learning occur in a multilingual context; their language in education policies are similar; transition from mother tongue to English happens during the early grades; and most of the learners learn mathematics in English--a language which for most is not their first/home language. Research outputs between 2006 and 2016 from the three countries were sourced from peer-reviewed mathematics and general education journals, monitoring and evaluation reports, and book chapters. Findings from the study revealed that there is a lack of longitudinal studies that investigate the impact of language on the teaching and learning of mathematics and that there are few studies on how teachers are and should be trained to teach mathematics in the early grades. The study also found that the implementation of the language in education policies in the three different focus countries is fraught with difficulties owing to a number of factors, amongst them the fact that the indigenous languages are not yet fully developed as academic languages. Finally, existing literature highlights the importance of the use of code switching and the provision of materials in the home language(s) of early graders. Recommendations regarding policy/curriculum, teacher education and pedagogic practices are made.
Keywords: African Languages; Code Switching (Language); Cross Cultural Studies; Educational Policy; Educational Research; Elementary School Students; English (Second Language); Foreign Countries; Instructional Materials; Kenya; Language Role; Language of Instruction; Longitudinal Studies; Malawi; Mathematics Instruction; Multilingualism; Native Language; Periodicals; Research Reports; Second Language Learning; South Africa; Teacher Education; Teaching Methods

Persistence and Fadeout of Preschool Participation Effects on Early Reading Skills in Low- and Middle-Income Countries - Gove, Amber; Dombrowski, Eileen; Pressley, Jennifer; King, Simon; Weatherholt, Tara (Persistence and Fadeout of Preschool Participation Effects on Early Reading Skills in Low- and Middle-Income Countries, 2018)
The adoption of the Sustainable Development Goals (SDGs) in September 2015 marked a new milestone for early childhood education, care, and development. For the first time in the framework of global goals, preschool education was described as integral to children's school readiness. Yet with few exceptions, much of the research on the impact of preschool has stemmed from high-income countries. Even fewer studies have examined preschool participation and later learning across multiple countries. This article helps fill this gap by connecting preschool participation to early primary reading outcomes, as measured by the Early Grade Reading Assessment. Drawing on a unique data set using student-level learning assessments from 16 countries, we use preprimary participation to explain primary school reading skills, including letter knowledge and oral reading fluency. We also model the influence of key demographic variables on these outcomes, including home language and classroom language of instruction (LOI). For a subset of six countries with exceptionally rich data, we examine national-level policy and practice to better understand what might explain the persistence or fadeout of the effect of preschool. Policy makers and practitioners alike will find these results useful in making cases for improving preschool experiences for children in low- and middle-income countries in the next decade of SDG-related efforts.
Keywords: Child Care; Early Childhood Education; Economic Factors; Educational Policy; Ethiopia; Foreign Countries; Ghana; Indonesia; Iraq; Jordan; Kenya; Language Usage; Language of Instruction; Malawi; Mali; Nicaragua; Nigeria; Philippines; Preschool Education; Primary Education; Reading Achievement; Reading Skills; Regression (Statistics); Rwanda; School Readiness; Senegal; Socioeconomic Influences; Statistical Analysis; Student Participation; Sustainable Development; Tanzania; Uganda; Zambia

Out of Many, One: Challenges in Teaching Multilingual Kenyan Primary Students in English - Hsieh, Ching-Ni; Ionescu, Marcel; Ho, Tsung-Han (Out of Many, One: Challenges in Teaching Multilingual Kenyan Primary Students in English, 2018)
Using a large-scale, standardised English language proficiency test (TOEFL® "Primary"™), this study examined Kenyan primary school students' English reading and listening proficiency and explored challenges primary school teachers face in using English as the medium of instruction (EMI) to teach their multilingual students. The test was taken by 4768 students in Standards 3-7 from 51 primary schools across the country in Kenya. Seventeen primary school teachers, representing six major geographical regions, participated in semi-structured interviews to explore their teaching challenges. Results show that, regardless of standard/grade level, the majority of the participating students were beginner-level English language users, which suggests that they may not have the language skills needed to understand classroom instruction and learn the subject matter content effectively in English. Interview findings indicate that, as they implement the EMI policy, teachers encounter five major challenges: (1) mother tongue interference, (2) students' attitudes toward English, (3) lack of usefulness of English language in the community, (4) resource constraints and (5) diverse student backgrounds. The results have pedagogical implications for EMI implementation in similar multilingual contexts.
Keywords: Barriers; Educational Resources; Elementary School Students; English (Second Language); Foreign Countries; Instructional Effectiveness; Interference (Language); Kenya; Language Attitudes; Language Proficiency; Language Tests; Language of Instruction; Listening Comprehension Tests; Multilingualism; Native Language; Reading Tests; Semi Structured Interviews; Sociolinguistics; Student Diversity; Teacher Attitudes

Language Ideologies and Epistemic Exclusion - Kiramba, Lydiah Kananu (Language Ideologies and Epistemic Exclusion, 2018)
Research in educational linguistics is now challenging the efficacy of monolingual approaches that often dominate educational practices in multilingual settings. In most African nations where multilingualism is the norm, there remains a persistent reluctance by educational stakeholders (principals, teachers, parents, and students) to embrace multilingualism in education or to reposition local languages as resources in classrooms. This article draws on qualitative data from a multilingual, rural, fourth-grade classroom in Kenya to interrogate the articulated ideologies and their effects on communicative practices as voiced by the participants and by observing actual classroom practices. Bourdieu's notions of habitus, legitimate language, and symbolic power serve as analytic lenses for enhancing our understanding of the power of language ideologies. From the data, 'monoglossia' emerged as the key operating ideology, with time-on-task pedagogical practice helping to consolidate these monoglossic practices. The most visible effect of this ideology was silencing student engagement in the classroom. I argue that an awareness of these articulated ideologies and their observable effects on students' learning and language-use behaviors is important for challenging the subordination of home languages and the epistemic exclusion of the children who speak marginalized languages. Ideological awareness may open spaces for alternative and inclusive educational approaches.
Keywords: African Languages; Case Studies; Classroom Communication; Classroom Techniques; Cultural Capital; Discourse Analysis; Elementary School Students; Elementary School Teachers; English (Second Language); Ethnography; Foreign Countries; Grade 4; Interviews; Kenya; Language Attitudes; Language Usage; Language of Instruction; Learner Engagement; Monolingualism; Multilingualism; Native Language; Observation; Power Structure; School Policy; Second Language Learning; Social Capital; Teacher Attitudes; Teaching Methods; Time on Task

Scalability of Learners' Success Rates in E-Learning: A Survey Study of the Learners' Perspectives - Maritim, Ezra K.; Getuno, Daniel Makini (Scalability of Learners' Success Rates in E-Learning: A Survey Study of the Learners' Perspectives, 2018)
Globally, ODL institutions experience mismatch between scalability of numbers and scalability of success rates. This study explored the scalability of success rates in open, distance e-learning as perceived by the learners within the "Chain of Response Model." The primary aim of the study was to look at online learners' success rate by focusing on two institutional factors drawn from the Model, namely: the learner's study modules related challenges and support services. The results of an online survey of 180 undergraduate and postgraduate online learners of Egerton University, Kenya, showed: (a) the response rate of 16%; (b) a mixture of hardware, software and personal factors were identified as pre-requisites for e-learning success: (c) a number of mathematically-based modules were identified as risks to success in online studies; and (d) while the learners saw the learner support services as important they were less satisfied with their provision. The present study points to two broad areas that require further studies. First, qualitative look into specific challenges that learners face with respect to learner support service provisions, modules interactivity, and those identified as difficult to follow and thus posing risks to the learners' success. Second, investigation into tutor-learner contacts with the view of identifying whether such contacts are reactive or proactive.
Keywords: Barriers; College Students; Distance Education; Educational Technology; Electronic Learning; Foreign Countries; Kenya; Online Courses; Program Effectiveness; Student Attitudes; Success

Scalability of Learners' Success Rates in E-Learning: A Survey Study of the Learners' Perspectives - Maritim, Ezra K.; Getuno, Daniel Makini (Scalability of Learners' Success Rates in E-Learning: A Survey Study of the Learners' Perspectives, 2018)
Globally, ODL institutions experience mismatch between scalability of numbers and scalability of success rates. This study explored the scalability of success rates in open, distance e-learning as perceived by the learners within the "Chain of Response Model." The primary aim of the study was to look at online learners' success rate by focusing on two institutional factors drawn from the Model, namely: the learner's study modules related challenges and support services. The results of an online survey of 180 undergraduate and postgraduate online learners of Egerton University, Kenya, showed: (a) the response rate of 16%; (b) a mixture of hardware, software and personal factors were identified as pre-requisites for e-learning success: (c) a number of mathematically-based modules were identified as risks to success in online studies; and (d) while the learners saw the learner support services as important they were less satisfied with their provision. The present study points to two broad areas that require further studies. First, qualitative look into specific challenges that learners face with respect to learner support service provisions, modules interactivity, and those identified as difficult to follow and thus posing risks to the learners' success. Second, investigation into tutor-learner contacts with the view of identifying whether such contacts are reactive or proactive.
Keywords: Barriers; College Students; Distance Education; Educational Technology; Electronic Learning; Foreign Countries; Kenya; Online Courses; Program Effectiveness; Student Attitudes; Success

Preschool Attendance and Children's Reading Ability: A Case of Narok County Kenya - Mwoma, Teresa (Preschool Attendance and Children's Reading Ability: A Case of Narok County Kenya, 2018)
This article reports findings of a study conducted in public primary schools in Narok County Kenya. A sample size comprising 74 children in Grade 3 (37 who did not attend preschool and 37 who attended preschool), 18 head teachers, 66 lower primary school teacher's and five education officers were selected for the study. Learners' reading ability was tested using the Kenya Early Grade Reading Assessment Tests for English and Kiswahili adapted from Department for International Development end line survey of 2014. Interviews of head teachers, teachers, and education officers were conducted. Findings revealed that children who attended preschool performed better in English sub-tasks than those who did not attend preschool. However, those who did not attend preschool performed better in Kiswahili than their counter parts. Teachers revealed that they create extra time to support children who did not attend preschool, which explains why such children performed better in Kiswahili.
Keywords: African Languages; Attendance; Elementary School Students; Elementary School Teachers; English (Second Language); Foreign Countries; Grade 3; Kenya; Preschool Education; Principals; Reading Ability

Mathematics gender gaps in Kenya: Are resource differentials between boys and girls to blame? - Ng'ang'a, Alice; Mureithi, Leopold P.; Wambugu, Anthony (Mathematics gender gaps in Kenya: Are resource differentials between boys and girls to blame?, 2018)
The Blinder-Oaxaca approach has been used to decompose the gender gap in mathematics test scores in private and public primary schools in Kenya. That is, the mathematics production functions are estimated separately for boys and girls, the difference between the boys' and girls' average scores is estimated and then decomposed into three components. That is, gap due to differences in resources between boys and girls, gap resulting from difference in utilization of educational resources and the gap due to unobservable factors. The results show that boys outperform girls in mathematics in both school types. In both private and public primary schools, boys take better advantage of the resources compared to the girls hence girls' scores can be improved by better utilization of the resources. In addition, the boys' scores in public primary schools can be improved by increasing the educational resources for boys. This indicates that resource based policies aimed at improving the girls' mathematics scores may not necessarily close the gender test score gap. Further, such policies may reverse the gender gap and disadvantage the boys. There should be focus on factors that improve utilization of resources by girls in order to improve their scores.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Gender differences (Psychology); Kenya; Mathematics education; Mathematics students; Primary schools

Mathematics Gender Gaps in Kenya: Are Resource Differentials between Boys and Girls to Blame? - Ng'ang'a, Alice; Mureithi, Leopold P.; Wambugu, Anthony (Mathematics Gender Gaps in Kenya: Are Resource Differentials between Boys and Girls to Blame?, 2018)
The Blinder-Oaxaca approach has been used to decompose the gender gap in mathematics test scores in private and public primary schools in Kenya. That is, the mathematics production functions are estimated separately for boys and girls, the difference between the boys' and girls' average scores is estimated and then decomposed into three components. That is, gap due to differences in resources between boys and girls, gap resulting from difference in utilization of educational resources and the gap due to unobservable factors. The results show that boys outperform girls in mathematics in both school types. In both private and public primary schools, boys take better advantage of the resources compared to the girls hence girls' scores can be improved by better utilization of the resources. In addition, the boys' scores in public primary schools can be improved by increasing the educational resources for boys. This indicates that resource based policies aimed at improving the girls' mathematics scores may not necessarily close the gender test score gap. Further, such policies may reverse the gender gap and disadvantage the boys. There should be focus on factors that improve utilization of resources by girls in order to improve their scores.
Keywords: Achievement Gap; Educational Resources; Elementary School Students; Foreign Countries; Gender Differences; Kenya; Mathematics Achievement; Mathematics Tests; Private Schools; Public Schools; Scores

Student Perceptions of the Effectiveness of Formative Assessment in an Online Learning Environment. - Ogange, Betty Obura; Agak, John O.; Okelo, Kevin Odhiambo; Kiprotich, Peter (Student Perceptions of the Effectiveness of Formative Assessment in an Online Learning Environment., 2018)
Assessment is an integral part of the teaching-learning process in both conventional and distance education contexts. Literature suggests that with the increase in the use of Information and Communications Technology in the delivery of learning, a number of institutions are resorting to formative assessment practices that are mediated by technology to not only provide flexible and more efficient means of assessment but also attain improved learning outcomes. This paper investigated student perceptions of the effectiveness of different types of formative assessment used in online learning environments. A 31-item questionnaire was used to gather data on student perceptions. On the level of difficulty, students generally perceived the various types of formative assessment as having no significant differences. Results further indicated that students received more prompt feedback from peer assessment and computer-marked assessment, compared to teacher-marked assessment. The findings of this study will support practitioners in eLearning to use formative assessment and feedback mechanisms more effectively to influence student engagement as well as learning outcomes.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Distance education; Formative tests; Psychology of students

Challenges of Adopting Open Educational Resources (OER) in Kenyan Secondary Schools: The Case of Open Resources for English Language Teaching (ORELT) - Orwenjo, Daniel Ochieng; Erastus, Fridah Kanana (Challenges of Adopting Open Educational Resources (OER) in Kenyan Secondary Schools: The Case of Open Resources for English Language Teaching (ORELT), 2018)
Kenya, like many African countries, has faced enormous challenges in the production of and access to quality relevant teaching and learning materials and resources in primary and secondary school classrooms. This has been occasioned by a plethora of factors which include, but are not limited to, lack of finances, tradition, competence, and the experience to develop such resources. Such a situation has persisted despite the existence and availability of many Open Educational Resources (OERs) that have been developed by education stakeholders at enormous cost. Such freely available resources could potentially improve the quality of existing resources or help to develop new courses. Yet, their uptake and reuse in secondary and primary schools in Kenya continues to be very low. This paper reports the findings of a study in which Open Resources for English Language Teaching (ORELT) developed by the Commonwealth of Learning (COL), Canada, were piloted in a sample of fifty (50) Kenyan secondary schools. The study applied the Model 1--Distance and Dependence (Zhao et al. 2002) model to investigate the challenges that instructors face in adopting and using ORELT materials. The study reported that poor infrastructure, negative attitudes, lack of ICT competencies, and other skill gaps among teachers, as well as lack of administrative support, are some of the challenges experienced in the adoption and use of OERs in Kenyan schools. The findings of the present study will provide useful insights to developers of OERs and Kenyan education stakeholders in devising strategies to optimise utilisation of OERs in the Kenyan school system.
Keywords: Barriers; Educational Technology; English (Second Language); Foreign Countries; Instructional Materials; Interviews; Kenya; Negative Attitudes; Resource Units; Second Language Instruction; Secondary Schools; Shared Resources and Services; Teacher Attitudes; Teacher Competencies; Technological Literacy; Technology Uses in Education

Mathematics from the Beginning: Evaluating the Tayari Preprimary Program's Impact on Early Mathematics Skills - Piper, Benjamin; Sitabkhan, Yasmin; Nderu, Evangeline (Mathematics from the Beginning: Evaluating the Tayari Preprimary Program's Impact on Early Mathematics Skills, 2018)
Given the dearth of research on early numeracy interventions in low- and middle-income countries, this paper presents the instructional methodology and impact results of the Tayari program. Tayari is a preprimary intervention in Kenya (2014-2019) that prepares children aged four and five for entry into primary school by providing materials for students, training for teachers, and continuous in-classroom support. The Tayari methodology was built on the Kenyan government's preprimary syllabus to produce instruction that was developmentally sequenced, linked to out-of-school experiences, and supportive of children's number sense. Tayari was evaluated using a randomized controlled trial (RCT) and collection of longitudinal data from 2,957 children in treatment and control schools at three time points. Pupil assessment items were drawn from a growing body of research on preprimary numeracy in developing contexts, plus instruments and techniques from the Measuring Early Learning and Quality Outcomes (MELQO) program (UNESCO, UNICEF, Brookings Institution, & World Bank Group, 2017). The impact evaluation of the longitudinal RCT results showed statistically significant effects in the numeracy tasks of producing sets, identifying numbers, and naming shapes, while revealing no initial effects in the areas of oral and mental addition. We present recommendations for Tayari's improvement in terms of mathematics instruction, as well as preprimary policy implications for Kenya and similar contexts.
Keywords: Developing Nations; Early Childhood Education; Foreign Countries; Kenya; Mathematics Education; Mathematics Instruction; Mathematics Skills; Number Concepts; Numeracy; Outcomes of Education; Predictor Variables; Preschool Children; Preschool Education; Program Evaluation; School Readiness; Sequential Approach; Teaching Methods

Cross-Language Transfer of Phonological Awareness and Letter Knowledge: Causal Evidence and Nature of Transfer - Wawire, Brenda A.; Kim, Young-Suk G. (Cross-Language Transfer of Phonological Awareness and Letter Knowledge: Causal Evidence and Nature of Transfer, 2018)
Using a randomized control trial, this study examined the causal evidence of cross-language transfer of phonological awareness and letter knowledge (names and sounds) using data from multilingual 1st-grade children (N = 322) in Kenya. Children in the treatment condition received an 8-week instruction on phonological awareness and letter knowledge in Kiswahili. The comparison group received business-as-usual classroom instruction. Children in the treatment condition showed greater improvement in phonological awareness and letter-sound knowledge in Kiswahili "and" English (positive transfer; effect sizes from 0.37 to 0.95), whereas a negative effect was found in letter-name knowledge (interference; effect size, g = 0.27). No effects were found in reading, nor did the results vary by moderators (e.g., Kiswahili vocabulary). Path analyses revealed divergent patterns of results for different outcomes. Results provide causal evidence for cross-language transfer of phonological awareness and letter knowledge and offer important theoretical and practical implications. [This article was published in "Scientific Studies of Reading" (EJ1188478).]
Keywords: African Languages; Alphabets; Attribution Theory; Elementary School Students; English (Second Language); Foreign Countries; Grade 1; Intelligence Tests; Kenya; Multilingualism; Peabody Picture Vocabulary Test; Phoneme Grapheme Correspondence; Phonological Awareness; Pretests Posttests; Reading Skills; Second Language Learning; Teaching Methods; Transfer of Training; Verbal Ability; Vocabulary

Cross-Language Transfer of Phonological Awareness and Letter Knowledge: Causal Evidence and Nature of Transfer - Wawire, Brenda A.; Kim, Young-Suk G. (Cross-Language Transfer of Phonological Awareness and Letter Knowledge: Causal Evidence and Nature of Transfer, 2018)
Using a randomized control trial, this study examined the causal evidence of cross-language transfer of phonological awareness and letter knowledge (names and sounds) using data from multilingual 1st-grade children (N = 322) in Kenya. Children in the treatment condition received an 8-week instruction on phonological awareness and letter knowledge in Kiswahili. The comparison group received business-as-usual classroom instruction. Children in the treatment condition showed greater improvement in phonological awareness and letter-sound knowledge in Kiswahili and English (positive transfer; effect sizes from 0.37 to 0.95), whereas a negative effect was found in letter-name knowledge (interference; effect size, g = 0.27). No effects were found in reading, nor did the results vary by moderators (e.g., Kiswahili vocabulary). Path analyses revealed divergent patterns of results for different outcomes. Results provide causal evidence for cross-language transfer of phonological awareness and letter knowledge and offer important theoretical and practical implications.
Keywords: African Languages; Alphabets; Attribution Theory; Elementary School Students; English (Second Language); Foreign Countries; Grade 1; Intelligence Tests; Kenya; Multilingualism; Peabody Picture Vocabulary Test; Phoneme Grapheme Correspondence; Phonological Awareness; Pretests Posttests; Reading Skills; Second Language Learning; Teaching Methods; Transfer of Training; Verbal Ability; Vocabulary

Viewing Science Learning Through an Ecosystem Lens: A Story in Two Parts - Falk, John H; Dierking, Lynn D (Navigating the Changing Landscape of Formal and Informal Science Learning Opportunities, 2018)
ResearchGate is a network dedicated to science and research. Connect, collaborate and discover scientific publications, jobs and conferences. All for free.

Competency Based Education and Training Policy Framework - Republic of Kenya (2018)

National Pre-Primary Education Policy Standard Guidelines - Republic of Kenya (2018)

Sector Policy and Implementation Guidelines for Learners and Trainees with Disabilities - Republic of Kenya (2018)

The Datafication of Learning: Data Technologies as Reflection Issue in the System of Education - Thoutenhoofd, Ernst D. (Studies in Philosophy and Education, 2018)
Like other parts of the social system, education is becoming an informationdriven venture: data technologies pervade all levels of the system. This dataﬁcation of education seems to take place alongside a general turn to learning that Gert Biesta has called learniﬁcation: a progressively singular focus on the manipulable features of individual learning in education. Given rapidly rising levels of dataﬁcation, it seems timely to take up Luhmann and Schorr’s contention that education entails a technology deﬁcit and discuss dataﬁcation as reﬂection issue in the system of education. Against their argument that human learning is not amenable to a technology, I develop the counter-argument that data technologies are replacing human learning outright with data at the level of organisation. Data thus present a concretely digital form of what Raf Vanderstraeten has called education as an ersatz order. In a data-driven form of organising education, human dimensions of learning become secondary to a systemic dimension: making learning visible as data and so susceptible to databased manipulation. The text treats school-wide positive behaviour support interventions as an evidence-based exemplar of this trend towards dataﬁcation in the system of education.

RWSS 2018: Promoting Inclusion Through Social Protection - United Nations Department of Economic and Social Affairs (2018)

Assessing the Impact of Early Learning Programs in Africa. - Gove, Amber; Brunette, Tracy; Bulat, Jennae; Carrol, Bidemi; Henny, Catherine; Macon, Wykia; Nderu, Evangeline; Sitabkhan, Yasmin (Assessing the Impact of Early Learning Programs in Africa., 2017)
We present results from early learning programs in six African countries: Ethiopia, Kenya, Liberia, Malawi, Tanzania, and Uganda. In partnership with ministries of education, RTI International has worked within government systems to support the design and deployment of locally contextualized materials, training, and assessment tools, with the goal of improving outcomes for early learners in primary schools, and in Kenya and Tanzania preprimary as well. Here we report on the experience and evidence of impact from specific programs in each country, including summary assessment results when available. In several countries with completed impact evaluations, there are significant and important learning gains of between 0.2 and 2.57 SD in effect size; in one case the percentage of students reaching grade-level reading proficiency increased from 12% to 47%. In the context of increased urgency surrounding what UNESCO has called a 'global learning crisis,' these experiences provide useful lessons for policymakers and practitioners alike.
Keywords: All other schools and instruction; Early Learning Skills Analysis; Early childhood education; Exam Preparation and Tutoring; Kenya; Literacy programs; Primary schools; Reading

Investigating the effects of community-based interventions on mathematics achievement of girls from low-income households in Kenya. - Hungi, Njora; Ngware, Moses; Lamb, Stephen (Investigating the effects of community-based interventions on mathematics achievement of girls from low-income households in Kenya., 2017)
This paper uses difference-in-difference and multivariate analyses procedures to examine the effects of two community-based intervention packages on mathematics achievement of primary school girls from low-income urban households in Kenya. The data involved in this study were collected between 2013 and 2015 from 748 12–19 years old primary school girls residing in two major Nairobi slums of Viwandani and Korogocho. These data were part of a larger intervention study that sought to improve schooling outcomes among girls from disadvantaged home backgrounds by providing them with after-school homework support, life skill mentoring and parental counselling. Results reveal intervention effects of between 23 and 26 mathematics score points on a Rasch scale with a mean of 400 a standard deviation of 100. These effects translate to at least one school term of learning for girls in the comparison group. Effect size for one of the intervention packages was small (0.24), while that of the second package was moderate (0.40).
Keywords: Achievement gains (Education); Achievement gap; Mathematics education; School children; Teaching aids

Participation in cross-national learning assessments and impact on capacity development: Programmes, practice, structures and teacher competency. Case study of Kenya, Tanzania and South Africa. - Mulongo, Godfrey; Amod, Zaytoon (Participation in cross-national learning assessments and impact on capacity development: Programmes, practice, structures and teacher competency. Case study of Kenya, Tanzania and South Africa., 2017)
This research is one of the few attempts to employ the conceptual framework of "technology transfer" to analyze the extent that participation in cross-national learning assessments has had on capacity development, particularly in the development of official public structures, by equipping educationists and influencing teachers’ competency in Kenya, Tanzania and South Africa. The researchers conducted semi-structured interviews with key informants drawn from the Ministries of Basic Education, national examinations councils, civil society organizations and curriculum development institutions in the three countries. The in-depth interviews were complemented by relevant literature on this topic. The study established improved technical capacities in the public education sector in South Africa and Kenya to design and conduct independent large-scale learning assessments. This important research demonstrates a certain level of commitment by African countries to establish official structures necessary to design/implement and sustain a culture of monitoring learning outcomes through public funded large-scale learning assessments. The research potentially contributes to the body of knowledge as far as ‘summative’ evaluation and analysis of the theory of change underpinning the participation in cross-national learning assessments espoused under the Education for All (EFA) Framework of Action
Keywords: Capacity building; Curriculum planning; Learning; Public education; Teacher competencies

Participation in cross-national learning assessments and impact on capacity development: Programmes, practice, structures and teacher competency. Case study of Kenya, Tanzania and South Africa. - Mulongo, Godfrey; Amod, Zaytoon (Participation in cross-national learning assessments and impact on capacity development: Programmes, practice, structures and teacher competency. Case study of Kenya, Tanzania and South Africa., 2017)
This research is one of the few attempts to employ the conceptual framework of "technology transfer" to analyze the extent that participation in cross-national learning assessments has had on capacity development, particularly in the development of official public structures, by equipping educationists and influencing teachers’ competency in Kenya, Tanzania and South Africa. The researchers conducted semi-structured interviews with key informants drawn from the Ministries of Basic Education, national examinations councils, civil society organizations and curriculum development institutions in the three countries. The in-depth interviews were complemented by relevant literature on this topic. The study established improved technical capacities in the public education sector in South Africa and Kenya to design and conduct independent large-scale learning assessments. This important research demonstrates a certain level of commitment by African countries to establish official structures necessary to design/implement and sustain a culture of monitoring learning outcomes through public funded large-scale learning assessments. The research potentially contributes to the body of knowledge as far as ‘summative’ evaluation and analysis of the theory of change underpinning the participation in cross-national learning assessments espoused under the Education for All (EFA) Framework of Action
Keywords: Capacity building; Curriculum planning; Learning; Public education; Teacher competencies

'We also wanted to learn': Narratives of change from adults literate in African languages - Trudell, Joel; Cheffy, Ian (International Review of Education, 2017)
This article discusses the impact of literacy programmes on those who learned to read and write in their own African languages. It draws on adult learners' reflections on the significance of literacy and numeracy in their everyday lives as evidenced in interviews conducted in 2014 and 2015 in rural sites in five African countries: Ethiopia, Kenya, Cameroon, Burkina Faso and Ghana. The research approach was influenced by the Most Significant Change (MSC) method of monitoring and evaluation, which collects and examines narratives that reveal beneficiaries' perceptions of change related to a given programme. This study emulates this approach in that it seeks to learn about perceived changes attributed to literacy acquisition from the perspectives of the beneficiaries, without imposing pre-established indicators. In the rural adult learners' view, literacy enabled lifelong learning outcomes that rivalled the results of primary schooling. Literacy programme graduates demonstrated extensive ongoing learning after they learned to read, write and calculate, consequently acquiring new literacy practices and new understandings of themselves. Even though many of those interviewed had been unable to attend school, they viewed the practices of reading and writing that they developed outside of school as equivalent to the practices of adults who had been educated in primary school.
Keywords: Adult Literacy; Adults; African Languages; Attitude Measures; Burkina Faso; Cameroon; Change; Ethiopia; Foreign Countries; Ghana; Interviews; Kenya; Lifelong Learning; Literacy Education; Native Language Instruction; Numeracy; Outcomes of Education; Personal Narratives; Program Effectiveness; Rural Areas; Student Attitudes

'We also wanted to learn': Narratives of change from adults literate in African languages. - Trudell, Joel; Cheffy, Ian ('We also wanted to learn': Narratives of change from adults literate in African languages., 2017)
This article discusses the impact of literacy programmes on those who learned to read and write in their own African languages. It draws on adult learners' reflections on the significance of literacy and numeracy in their everyday lives as evidenced in interviews conducted in 2014 and 2015 in rural sites in five African countries: Ethiopia, Kenya, Cameroon, Burkina Faso and Ghana. The research approach was influenced by the Most Significant Change (MSC) method of monitoring and evaluation, which collects and examines narratives that reveal beneficiaries' perceptions of change related to a given programme. This study emulates this approach in that it seeks to learn about perceived changes attributed to literacy acquisition from the perspectives of the beneficiaries, without imposing pre-established indicators. In the rural adult learners' view, literacy enabled lifelong learning outcomes that rivalled the results of primary schooling. Literacy programme graduates demonstrated extensive ongoing learning after they learned to read, write and calculate, consequently acquiring new literacy practices and new understandings of themselves. Even though many of those interviewed had been unable to attend school, they viewed the practices of reading and writing that they developed outside of school as equivalent to the practices of adults who had been educated in primary school.
Keywords: Adult literacy programs; African languages; All other schools and instruction; Narratives; Outcome assessment (Education); Primary schools

'We Also Wanted to Learn': Narratives of Change from Adults Literate in African Languages - Trudell, Joel; Cheffy, Ian ('We Also Wanted to Learn': Narratives of Change from Adults Literate in African Languages, 2017)
This article discusses the impact of literacy programmes on those who learned to read and write in their own African languages. It draws on adult learners' reflections on the significance of literacy and numeracy in their everyday lives as evidenced in interviews conducted in 2014 and 2015 in rural sites in five African countries: Ethiopia, Kenya, Cameroon, Burkina Faso and Ghana. The research approach was influenced by the Most Significant Change (MSC) method of monitoring and evaluation, which collects and examines narratives that reveal beneficiaries' perceptions of change related to a given programme. This study emulates this approach in that it seeks to learn about perceived changes attributed to literacy acquisition from the perspectives of the beneficiaries, without imposing pre-established indicators. In the rural adult learners' view, literacy enabled lifelong learning outcomes that rivalled the results of primary schooling. Literacy programme graduates demonstrated extensive ongoing learning after they learned to read, write and calculate, consequently acquiring new literacy practices and new understandings of themselves. Even though many of those interviewed had been unable to attend school, they viewed the practices of reading and writing that they developed outside of school as equivalent to the practices of adults who had been educated in primary school.
Keywords: Adult Literacy; Adults; African Languages; Attitude Measures; Burkina Faso; Cameroon; Change; Ethiopia; Foreign Countries; Ghana; Interviews; Kenya; Lifelong Learning; Literacy Education; Native Language Instruction; Numeracy; Outcomes of Education; Personal Narratives; Program Effectiveness; Rural Areas; Student Attitudes

'We Also Wanted to Learn': Narratives of Change from Adults Literate in African Languages - Trudell, Joel; Cheffy, Ian ('We Also Wanted to Learn': Narratives of Change from Adults Literate in African Languages, 2017)
This article discusses the impact of literacy programmes on those who learned to read and write in their own African languages. It draws on adult learners' reflections on the significance of literacy and numeracy in their everyday lives as evidenced in interviews conducted in 2014 and 2015 in rural sites in five African countries: Ethiopia, Kenya, Cameroon, Burkina Faso and Ghana. The research approach was influenced by the Most Significant Change (MSC) method of monitoring and evaluation, which collects and examines narratives that reveal beneficiaries' perceptions of change related to a given programme. This study emulates this approach in that it seeks to learn about perceived changes attributed to literacy acquisition from the perspectives of the beneficiaries, without imposing pre-established indicators. In the rural adult learners' view, literacy enabled lifelong learning outcomes that rivalled the results of primary schooling. Literacy programme graduates demonstrated extensive ongoing learning after they learned to read, write and calculate, consequently acquiring new literacy practices and new understandings of themselves. Even though many of those interviewed had been unable to attend school, they viewed the practices of reading and writing that they developed outside of school as equivalent to the practices of adults who had been educated in primary school.
Keywords: Adult Literacy; Adults; African Languages; Attitude Measures; Burkina Faso; Cameroon; Change; Ethiopia; Foreign Countries; Ghana; Interviews; Kenya; Lifelong Learning; Literacy Education; Native Language Instruction; Numeracy; Outcomes of Education; Personal Narratives; Program Effectiveness; Rural Areas; Student Attitudes

'So What's the Difference?' Talking About Race With Refugee Children in the English Language Learner Classroom. - Roy, Laura ('So What's the Difference?' Talking About Race With Refugee Children in the English Language Learner Classroom., 2017)
This study examines how an English language learner ( ELL) educator negotiated conversations about the intersectional nature of race in an elementary ELL classroom using a critical literacy framework. Few studies examine the ways in which teachers of young children negotiate conversations about the complexities of race with their students. Even fewer address the way in which African refugee children can explore the contested nature of racial labeling as a part of language instruction in the classroom. The students in this study experienced a history of persecution and displacement in Somalia in the 1990s. Their experiences in Somalia, relocation to refugee camps in Kenya, and finally relocation to the United States exposed their families to the very real impact of static and stereotypical notions of race. Through the lens of critical literacy, classroom interactions and activities are analyzed through one cycle of literacy events in an ELL classroom. Findings show that ELL educators can explore the contested nature of racial identities in ways that support and enhance language instruction. Findings also highlight the complexities of immigrant and refugee identity positions, even among members of the same group.
Keywords: Critical literacy; Elementary education; English teachers; Limited English-proficient students; Race identity

'So What's the Difference?' Talking about Race with Refugee Children in the English Language Learner Classroom - Roy, Laura ('So What's the Difference?' Talking about Race with Refugee Children in the English Language Learner Classroom, 2017)
This study examines how an English language learner (ELL) educator negotiated conversations about the intersectional nature of race in an elementary ELL classroom using a critical literacy framework. Few studies examine the ways in which teachers of young children negotiate conversations about the complexities of race with their students. Even fewer address the way in which African refugee children can explore the contested nature of racial labeling as a part of language instruction in the classroom. The students in this study experienced a history of persecution and displacement in Somalia in the 1990s. Their experiences in Somalia, relocation to refugee camps in Kenya, and finally relocation to the United States exposed their families to the very real impact of static and stereotypical notions of race. Through the lens of critical literacy, classroom interactions and activities are analyzed through one cycle of literacy events in an ELL classroom. Findings show that ELL educators can explore the contested nature of racial identities in ways that support and enhance language instruction. Findings also highlight the complexities of immigrant and refugee identity positions, even among members of the same group.
Keywords: Africa; Critical Literacy; Elementary School Students; Elementary School Teachers; English (Second Language); Foreign Countries; Interaction; Kenya; Language Teachers; Literacy Education; Minority Group Students; Race; Racial Bias; Racial Identification; Refugees; Second Language Instruction; Somalia; Stereotypes; United States

Early Language Learning: Complexity and Mixed Methods - Enever, Janet; Lindgren, Eva (Multilingual Matters, 2017)
This is the first collection of research studies to explore the potential for mixed methods to shed light on foreign or second language learning by young learners in instructed contexts. It brings together recent studies undertaken in Cameroon, China, Croatia, Ethiopia, France, Germany, Italy, Kenya, Mexico, Slovenia, Spain, Sweden, Tanzania and the UK. Themes include English as an additional language, English as a second or foreign language, French as a modern foreign language, medium of instruction controversies and content and language integrated learning (CLIL). The volume reviews the choice of research methodologies for early language learning research in schools with a particular focus on mixed methods and proposes that in the multidisciplinary context of early language learning this paradigm allows for a more comprehensive understanding of the evidence than other approaches might provide. The collection will be of interest to in-service and trainee teachers of young language learners, graduate students in the field of TESOL and early language learning, teacher educators, researchers and policymakers. Contents of this book include: (1) Introduction: Mixed Methods in Early Language Learning Research--Examining Complexity (Eva Lindgren and Janet Enever). Part 1: Overviews of Research Findings: (2) Early Language Learning in Complex Linguistic Settings: Insights from Africa (Agatha J. van Ginkel); (3) Considering the Complexities of Teaching Intercultural Understanding in Foreign Languages (Patricia Driscoll); and (4) Literacy Development in Children with English as an Additional Language (EAL) (Victoria A. Murphy). Part 2: Empirical Studies Using Mixed Methods: (5) Verbal Working Memory and Foreign Language Learning in English Primary Schools: Implications for Teaching and Learning (Alison Porter); (6) Piecing Together the Jigsaw: Understanding Motivations of English Learners in Chinese Primary School through a Questionnaire and Elicited Metaphor Analysis (Jiang Changsheng, Zhang Jie, Liang Xiaohua, Yuan Yuan and Xie Qun); (7) Codeswitching Your Way to Language Learning? Receptive Codeswitching with Digital Storybooks in Early Language Learning (Judith Buendgens-Kosten, Ilonca Hardy and Daniela Elsner); (8) Individual Differences and English L2 Learning in Two Primary Classrooms in France (Heather Hilton); and (9) Content and Language Integrated Learning (CLIL): A Panacea for Young English Language Learners? (Karmen Pižorn). Part 3: Longitudinal Perspectives using Mixed Methods: (10) The Dynamics of Motivation Development among Young Learners of English in China (Yuko Goto Butler); (11) Young Italian 'Learners' Foreign Language Development: A Longitudinal Perspective (Lucilla Lopriore); (12) Employing Mixed Methods for the Construction of Thick Descriptions of Early Language Learning (Eva Lindgren and Janet Enever); and (13) Developmental Aspects of Early EFL Learning (Jelena Mihaljevic Djigunovic). Part 4: Evaluating Early Language Learning Programmes: (14) Child EFL Interaction: Age, Instructional Setting and Development (María del Pilar García Mayo and Ainara Imaz Agirre); (15) Evaluating the Educational Outcomes of an Early Foreign Language Programme: The Design of an Impact Study for the Primary English Programme in Mexico (Peter Sayer, Ruth Ban and Magdalena López de Anda); (16) The Development of a Curriculum-Based C-Test for Young EFL Learners (Raphaela Porsch and Eva Wilden); and (17) Mixed Methods in Early Language Learning Research (Janet Enever and Eva Lindgren). An Index is included.
Keywords: Cameroon; China; Code Switching (Language); Croatia; Cultural Awareness; Difficulty Level; English (Second Language); Ethiopia; Foreign Countries; France; French; Germany; Individual Differences; Interdisciplinary Approach; Italy; Kenya; Language Research; Language Tests; Language of Instruction; Learning Motivation; Literacy Education; Longitudinal Studies; Mexico; Mixed Methods Research; Outcomes of Education; Program Evaluation; Research Methodology; Second Language Learning; Short Term Memory; Slovenia; Spain; Sweden; Tanzania; Test Construction; United Kingdom; Verbal Learning

Dynamics of Low-Fee Private Schools in Kenya: Governmental Legitimation, School-Community Dependence, and Resource Uncertainty. - EDWARDS JR., D. BRENT; KLEES, STEVEN J.; WILDISH, JANET L. (Dynamics of Low-Fee Private Schools in Kenya: Governmental Legitimation, School-Community Dependence, and Resource Uncertainty., 2017)
Background/Context: The UN Sustainable Development Goals include a renewed commitment to inclusive and equitable education for all and will maintain pressure on governments in lowincome countries to ensure this provision. A range of prominent researchers and institutional actors continue to explore and to promote low-fee private schools (LFPSs) as a viable option for achieving universal access to basic education. The emphasis on LFPSs can be seen as part of the push for education policies that attempt to improve educational access and quality not through the strengthening of public education but through the establishment of public-private partnerships. Focus of Study: In this paper we explore the Kenyan government's engagement with LFPSs, document and assess the impact of this support on the behavior of LFPS and clarify key actor perspectives and responses within this context. Research Design: Through a qualitative case study of two LFPSs in a large urban informal settlement near Nairobi, we focus on the dynamic interaction and delicate equilibrium within which government officials, LFPS representatives, parents, and students not only interact with but influence each other. Data for the study were gathered over the course of 8 weeks during May and June of 2010 in the urban slum called Mathare Village in Nairobi through document review, 35 interviews, and school visits. Conclusions: The findings suggest that LFPSs do not function in practice as in theory, and crucially, that there are inherent trade-offs, tensions, and unexpected dynamics in operation that have serious consequences for such issues as quality and equity, even when supported by formal government policy designed to address these aspects. The study reinforces the importance of national governments and international bodies increasing the resources devoted to improving access to, and the quality of, public education.
Keywords: All Other Miscellaneous Schools and Instruction; Community-school relationships; Educational quality; Educational resources; Elementary and Secondary Schools; Government aid to education; Kenya; Private school costs; School principals; Schools

Dynamics of Low-Fee Private Schools in Kenya: Governmental Legitimation, School-Community Dependence, and Resource Uncertainty. - EDWARDS JR., D. BRENT; KLEES, STEVEN J.; WILDISH, JANET L. (Dynamics of Low-Fee Private Schools in Kenya: Governmental Legitimation, School-Community Dependence, and Resource Uncertainty., 2017)
Background/Context: The UN Sustainable Development Goals include a renewed commitment to inclusive and equitable education for all and will maintain pressure on governments in lowincome countries to ensure this provision. A range of prominent researchers and institutional actors continue to explore and to promote low-fee private schools (LFPSs) as a viable option for achieving universal access to basic education. The emphasis on LFPSs can be seen as part of the push for education policies that attempt to improve educational access and quality not through the strengthening of public education but through the establishment of public-private partnerships. Focus of Study: In this paper we explore the Kenyan government's engagement with LFPSs, document and assess the impact of this support on the behavior of LFPS and clarify key actor perspectives and responses within this context. Research Design: Through a qualitative case study of two LFPSs in a large urban informal settlement near Nairobi, we focus on the dynamic interaction and delicate equilibrium within which government officials, LFPS representatives, parents, and students not only interact with but influence each other. Data for the study were gathered over the course of 8 weeks during May and June of 2010 in the urban slum called Mathare Village in Nairobi through document review, 35 interviews, and school visits. Conclusions: The findings suggest that LFPSs do not function in practice as in theory, and crucially, that there are inherent trade-offs, tensions, and unexpected dynamics in operation that have serious consequences for such issues as quality and equity, even when supported by formal government policy designed to address these aspects. The study reinforces the importance of national governments and international bodies increasing the resources devoted to improving access to, and the quality of, public education.
Keywords: All Other Miscellaneous Schools and Instruction; Community-school relationships; Educational quality; Educational resources; Elementary and Secondary Schools; Government aid to education; Kenya; Private school costs; School principals; Schools

Improving Literacy Instruction in Kenya Through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial. - Jukes, Matthew C. H.; Turner, Elizabeth L.; Dubeck, Margaret M.; Halliday, Katherine E.; Inyega, Hellen N.; Wolf, Sharon; Zuilkowski, Stephanie Simmons; Brooker, Simon J. (Improving Literacy Instruction in Kenya Through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial., 2017)
We evaluated a program to improve literacy instruction on the Kenyan coast using training workshops, semiscripted lesson plans, and weekly text-message support for teachers to understand its impact on students' literacy outcomes and on the classroom practices leading to those outcomes. The evaluation ran from the beginning of Grade 1 to the end of Grade 2 in 51 government primary schools chosen at random, with 50 schools acting as controls. The intervention had an impact on classroom practices with effect sizes from 0.57 to 1.15. There was more instruction with written text and more focus on letters and sounds. There was a positive impact on three of four primary measures of children's literacy after two years, with effect sizes up to 0.64, and school dropout reduced from 5.3% to 2.1%. This approach to literacy instruction is sustainable, and affordable and a similar approach has subsequently been adopted nationally in Kenya.
Keywords: Classrooms; Cluster analysis (Statistics); School dropouts; Teacher development; Text messages; Wireless Telecommunications Carriers (except Satellite)

Effects of livestock herd migration on child schooling in Marsabit District, Kenya. - Mburu, Samuel (Effects of livestock herd migration on child schooling in Marsabit District, Kenya., 2017)
To throw light on the challenge of providing education to pastoral households in the context of social and economic change, this study investigates the effects of herd migration on child schooling in Northern Kenya. Specifically, the analysis uses both household panel data and community-level focus-group data to identify the barriers to schooling, which include an insufficient number of schools, nomadism and communal conflicts. The results also reveal that herd migration has a significantly negative effect on school attendance -- about a 26% probability of failure to attend among the children of livestock migrating households. The child's age and mother's literacy have a positive impact on child school attendance, but with girls more likely to attend than boys, probably because of higher opportunity costs. That is, attending school takes boys away from activities like herding, which have greater economic value than the nonmonetisable household duties performed by girls.
Keywords: Animal migration; Children; Households; Live animal merchant wholesalers; Livestock; Livestock Merchant Wholesalers; Nomads; Opportunity costs; Primary education; Private Households; School attendance

Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs. - Piper, Benjamin (Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs., 2017)
The article presents a review of the consequences of conflict-related trauma for children in Sub-Saharan Africa. It tested a classroom-focused intervention that infused reading instruction with social-emotional learning principles and supported teachers in the adoption and use of these principles. It suggests that infusion of social-emotional learning principles can improve academic outcomes.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education methodology; Educational Support Services; Elementary education; Experimental methods in education; Performance; School children

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system. - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system., 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya's education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
Keywords: Academic achievement; Educational technology planning; Kenya; Primary education

Learning barriers among Grade 6 pupils attending rural schools in Uganda: implications to policy and practice. - Hungi, Njora; Ngware, Moses; Mahuro, Gerald; Muhia, Nelson (Learning barriers among Grade 6 pupils attending rural schools in Uganda: implications to policy and practice., 2017)
The paper uses multilevel analysis procedures to examine individual- and group-level learning barriers that have the greatest impact on pupil achievement in Uganda. The data for this study were collected in 2014 among 2711 Grade 6 pupils attending 82 schools in two rural districts of Iganga and Mayuge in Uganda. Data used in this paper are part of a larger study which sought to examine the schooling patterns, as well as the quality of education received by children living in rural settlements in Uganda. Among the learning barriers with the greatest impact on pupil achievement at the individual-level were lack of parental involvement, lack of pre-primary school attendance, grade repetition, and lack of basic learning resources such as writing materials. At the school-level, the barriers with the most impact on pupil achievement were lack of teacher lesson preparedness, lack of teacher-classroom support by subject advisors, distance between school and teachers' place of residence, lack of basic classroom resources, and whether or not the teacher kept pupil learning progress records. Implications of the findings for policy and practice are outlined.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Rural schools; Sixth grade (Education); Uganda

Children's reading ability in early primary schooling: Challenges for a Kenyan rural community. - Mwoma, Teresa (Children's reading ability in early primary schooling: Challenges for a Kenyan rural community., 2017)
School outcomes and good performance in different subjects depends on children's ability to read. Thus teaching children on how to read during early grades is critical in promoting learning to read. More advanced skills acquired in later grades depend on early grade learning, so children who do not acquire these reading skills in their early grades struggle to acquire more advanced skills usually absorbed through reading. This article report findings of a study conducted in rural public primary schools in Narok County, Kenya, focusing on the ability of children to read. The study sought to establish the factors influencing children's reading ability and whether there are differences in reading between boys and girls in grade three. A sample comprising 188 grade three children (94 girls and 94 boys) participated in the study, together with 18 head teachers, 66 teachers and 5 education officers from the 18 participating schools. A mixed methods research approach involving concurrent quantitative and qualitative data collection techniques was utilised. Early grade reading assessment tests for English and Kiswahili were utilised to collect quantitative data on children's reading ability. Key informant interviews with head teachers and education officers, and group interviews with teachers were conducted to collect qualitative data. Findings revealed that boys had slightly better mean scores in reading for the two subjects than girls. Availability of reading materials both at home and in school, together with getting supportive parents and teachers, were found to be critical in promoting children's reading.
Keywords: Reading ability testing; Reading interests of children

Cross-Cultural School-Based Encounters as Global Health Education - Bruselius-Jensen, Maria; Renwick, Kerry; Aagaard-Hansen, Jens (Cross-Cultural School-Based Encounters as Global Health Education, 2017)
Objective: Drawing on the concepts of the cosmopolitan person and democratic health education, this article explores the merits of primary school-based, cross-cultural dialogues for global health education. Design: A qualitative study of the learning outcomes of the Move/Eat/Learn (MEL) project. MEL facilitates cultural meetings, primarily Skype-based, between students from Kenya and Denmark, with the aim of promoting reflection on differences and similarities in everyday living conditions and their impact on health practices. Setting: Three Danish and one Kenyan primary schools. Methods: Qualitative analysis of 18 focus group discussions with 72 Danish and 36 Kenyan students. Results: Cross-cultural dialogues promoted students' engagement and reflections on their own and peers' health condition, access to education, food cultures, gender and family structures. Conclusion: Findings indicate the merits of cross-cultural dialogues as a means of educating students to become global health agents with a cosmopolitan outlook.
Keywords: Access to Education; Computer Mediated Communication; Cultural Awareness; Cultural Pluralism; Denmark; Educational Technology; Elementary Education; Elementary School Students; Family Structure; Focus Groups; Food; Foreign Countries; Gender Differences; Health Education; Holistic Approach; Intercultural Communication; Interviews; Kenya; Qualitative Research; Social Influences; Technology Uses in Education

Feminist Articulations, Social Literacies, and Ubiquitous Mobile Technology Use in Kenya - Sanya, Brenda N.; Odero, Phantus W. (Feminist Articulations, Social Literacies, and Ubiquitous Mobile Technology Use in Kenya, 2017)
This article examines the changes occurring in learning and literacy in the age of ubiquitous mobile phone use. Focusing on rural Kenyan women's use of mobile phone technologies in civic education programs, mobile banking, and to contact family members, the article explores how these women's use of mobile phones, based on their everyday needs, has facilitated the development of a literacy. The women learned to read on their phones to receive money, civic education information, and to communicate with their family members. In this process, these women, who self-identified and are also nationally classified as illiterate, developed a relevant social literacy through active use of text-based mobile phone applications.
Keywords: Activism; Banking; Citizenship Education; Females; Feminism; Foreign Countries; Handheld Devices; Illiteracy; Kenya; Learning; Literacy; Rural Population; Telecommunications; Womens Education

Designing for Scale: Reflections on Rolling Out Reading Improvement in Kenya and Liberia. - Gove, Amber; Korda Poole, Medina; Piper, Benjamin (Designing for Scale: Reflections on Rolling Out Reading Improvement in Kenya and Liberia., 2017)
Since 2008, the Ministries of Education in Liberia and Kenya have undertaken transitions from small-scale pilot programs to improve reading outcomes among primary learners to the large-scale implementation of reading interventions. The effects of the pilots on learning outcomes were significant, but questions remained regarding whether such large gains could be sustained at scale. In this article, the authors dissect the Liberian and Kenyan experiences with implementing large-scale reading programs, documenting the critical components and conditions of the program designs that affected the likelihood of successfully transitioning from pilot to scale. They also review the design, deployment, and effectiveness of each pilot program and the scale, design, duration, enabling conditions, and initial effectiveness results of the scaled programs in each country. The implications of these results for the design of both pilot and large-scale reading programs are discussed in light of the experiences of both the Liberian and Kenyan programs.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; All other schools and instruction; Education; Educational Support Services; Exam Preparation and Tutoring; Kenya; Liberia; Literacy programs; Reading promotion; Television pilot programs

The Extent to Which Parental Involvement Influences Transition of Pupils from Lower to Upper Primary in Manga District Schools - Abaya, Charles Mang'era; Nyaboga, Evans Nyagaka; Osero, Peterson Ondieki; Geta, Thomas Omao (The Extent to Which Parental Involvement Influences Transition of Pupils from Lower to Upper Primary in Manga District Schools, 2017)
The purpose of this study was to find out the extent to which parental involvement influences transition of pupils from lower to upper primary in Manga district schools in Nyamira County, Kenya. The objective of the study was to find out whether parental involvement activities influenced transition of pupils from lower to upper primary. Survey design was used for the study. The study population comprised of 19880 pupils, 590 teachers, 57 School Management Committee members, 57 and Head teachers. All the six Quality Assurance Officers were interviewed. The research instruments were the questionnaires which were filled by pupils and teachers, interview schedule for head teachers, SMC members and Education Officers. Piloting, involving two schools in the district was carried out and used test re-test technique to ascertain its reliability. The researcher visited all sampled schools and educational offices to collect data. Sampled teachers and pupils were given questionnaires to fill and head teachers and officers were interviewed by the researcher. Data was analyzed using statistical methods for analyzing and quantifying data. Statistical values in tables were used to compare the calculated value with tabulated value. It was observed that there was a strong correlation between parental involvement in school activities and performance of their children which in turn influenced their transition from one level to another. The study recommended that parents should involve themselves in school activities as it motivates their performance and enabled them to transit from one learning level to another.
Keywords: Correlation; Elementary School Students; Elementary School Teachers; Foreign Countries; Kenya; Learning Activities; Parent Participation; Parent Student Relationship; Parents; Principals; School Activities; School Districts; Transitional Programs

The Extent to Which Parental Involvement Influences Transition of Pupils from Lower to Upper Primary in Manga District Schools - Abaya, Charles Mang'era; Nyaboga, Evans Nyagaka; Osero, Peterson Ondieki; Geta, Thomas Omao (The Extent to Which Parental Involvement Influences Transition of Pupils from Lower to Upper Primary in Manga District Schools, 2017)
The purpose of this study was to find out the extent to which parental involvement influences transition of pupils from lower to upper primary in Manga district schools in Nyamira County, Kenya. The objective of the study was to find out whether parental involvement activities influenced transition of pupils from lower to upper primary. Survey design was used for the study. The study population comprised of 19880 pupils, 590 teachers, 57 School Management Committee members, 57 and Head teachers. All the six Quality Assurance Officers were interviewed. The research instruments were the questionnaires which were filled by pupils and teachers, interview schedule for head teachers, SMC members and Education Officers. Piloting, involving two schools in the district was carried out and used test re-test technique to ascertain its reliability. The researcher visited all sampled schools and educational offices to collect data. Sampled teachers and pupils were given questionnaires to fill and head teachers and officers were interviewed by the researcher. Data was analyzed using statistical methods for analyzing and quantifying data. Statistical values in tables were used to compare the calculated value with tabulated value. It was observed that there was a strong correlation between parental involvement in school activities and performance of their children which in turn influenced their transition from one level to another. The study recommended that parents should involve themselves in school activities as it motivates their performance and enabled them to transit from one learning level to another.
Keywords: Correlation; Elementary School Students; Elementary School Teachers; Foreign Countries; Kenya; Learning Activities; Parent Participation; Parent Student Relationship; Parents; Principals; School Activities; School Districts; Transitional Programs

The Role of Parental Leadership in Academic Performance: A Case of Pupils in the Free Primary Education Program in Kenya - Bellon, Emmanuel O.; Ngware, Moses Waithanji; Admassu, Kassahun (The Role of Parental Leadership in Academic Performance: A Case of Pupils in the Free Primary Education Program in Kenya, 2017)
The study examines the combined effects of key elements in parental leadership on academic performance. In the wake of inadequate learning resources, parental leadership becomes an indispensable learning input for children's academic performance. The discourse utilized data collected from 2005 to 2010 in a longitudinal study involving 1,549 children who sat for the national standardized examination in Kenya. Our findings showed that monitoring and aspirations are essential elements of parental leadership and have direct and positive effect on children's learning achievement. The effects were stronger among children from urban informal settlements compared with those from urban formal settlements. The effect of parental aspiration on children's performance was mediated through parental support and monitoring in informal settlements. The study provides evidence on the extent to which parental leadership enhances academic performance. This is useful to parents, teachers, and policy makers in their efforts to secure effective mechanisms for improving learning outcomes.
Keywords: Academic Achievement; Correlation; Elementary School Students; Factor Analysis; Foreign Countries; Kenya; Leadership; Longitudinal Studies; Multivariate Analysis; Outcomes of Education; Statistical Analysis; Structural Equation Models; Surveys

Global Inventory of Regional and National Qualifications Frameworks 2017. Volume II: National and Regional Cases - Cedefop - European Centre for the Development of Vocational Training; European Training Foundation (ETF) (Italy); United Nations Educational, Scientific; UNESCO Institute for Lifelong Learning (UIL) (Germany) (UNESCO Institute for Lifelong Learning, 2017)
A national qualifications framework (NQF) is an instrument used to classify a country's qualifications at different levels. Each level is defined by a set of learning outcomes expected at that level. NQFs can be useful tools in education and training reforms and are vital reference points for lifelong learning and comparing qualifications across borders. The "Global Inventory of Regional and National Qualifications frameworks 2017, Volume II: National and regional cases" gives an update on the national and regional qualification frameworks of 99 countries around the world. For each country, the NQF has been analysed based on the policy objectives, the levels and use of learning outcomes, stakeholder involvement and institutional arrangements, the recognition of non-formal and informal learning as well as whether references are made to existing regional frameworks. In addition, this volume also outlines existing regional frameworks in Southeast Asia, the Caribbean, Europe, the Gulf region, the Pacific, Southern Africa and the Commonwealth States. This third edition (the first two editions appeared in 2013 and 2015) of the "Global Inventory of Regional and National Qualifications Frameworks" is published at a time when the attention being paid to qualifications frameworks is rising, as evidenced by the UN's Education 2030 Framework for Action and Sustainable Development Goal (SDG) 4, which calls on countries to promote inclusive and equitable education and lifelong learning opportunities for all. Outcomes-based qualifications frameworks can contribute directly to achieving this goal. The "Global Inventory of Regional and National Qualifications Frameworks 2017, Volume II" is the result of collaborative work developed by the European Centre for the Development of Vocational Training (Cedefop), the European Training Foundation (ETF), UNESCO and the UNESCO Institute for Lifelong Learning (UIL). [The thematic chapters, and national and regional cases were drafted by: Jens Bjørnåvold, Slava Pevec Grm, Ernesto Villalba and George Kostakis, Anastasia Pouliou and Andreea Rusu (Cedefop); Michael Graham and Arjen Dej and all members of the qualifications team (ETF); Borhene Chakroun and Katerina Ananiadou (UNESCO); and Madhu Singh (UIL). For Volume I: Thematic Chapters, see ED604734.]
Keywords: Afghanistan; Africa; Albania; Angola; Armenia; Asia; Australia; Austria; Azerbaijan; Bangladesh; Belarus; Belgium; Bhutan; Bosnia and Herzegovina; Botswana; Bulgaria; Cambodia; Chile; China; Congo; Croatia; Cyprus; Czech Republic; Denmark; Educational Policy; Egypt; Estonia; Ethiopia; Europe; Finland; Foreign Countries; France; Gambia; Georgia Republic; Germany; Ghana; Global Approach; Greece; Hong Kong; Hungary; Iceland; India; Indonesia; Informal Education; Ireland; Italy; Jordan; Kazakhstan; Kenya; Kosovo; Kyrgyzstan; Latvia; Lebanon; Lesotho; Liechtenstein; Lithuania; Luxembourg; Macedonia; Madagascar; Malawi; Malaysia; Maldives; Malta; Mauritius; Mexico; Moldova; Montenegro; Morocco; Mozambique; Namibia; National Programs; Nepal; Netherlands; New Zealand; Nonformal Education; Norway; Outcomes of Education; Pakistan; Palestine; Philippines; Poland; Portugal; Qualifications; Regional Programs; Romania; Russia; Rwanda; Saudi Arabia; Serbia; Seychelles; Slovakia; Slovenia; South Africa; South Korea; Spain; Sri Lanka; Stakeholders; Swaziland; Sweden; Switzerland

Dynamics of Low-Fee Private Schools in Kenya: Governmental Legitimation, School-Community Dependence, and Resource Uncertainty - Edwards, Brent; Klees, Steven J.; Wildish, Janet L. (Dynamics of Low-Fee Private Schools in Kenya: Governmental Legitimation, School-Community Dependence, and Resource Uncertainty, 2017)
Background/Context: The UN Sustainable Development Goals include a renewed commitment to inclusive and equitable education for all and will maintain pressure on governments in low-income countries to ensure this provision. A range of prominent researchers and institutional actors continue to explore and to promote low-fee private schools (LFPSs) as a viable option for achieving universal access to basic education. The emphasis on LFPSs can be seen as part of the push for education policies that attempt to improve educational access and quality not through the strengthening of public education but through the establishment of public-private partnerships. Focus of Study: In this paper we explore the Kenyan government's engagement with LFPSs, document and assess the impact of this support on the behavior of LFPS and clarify key actor perspectives and responses within this context. Research Design: Through a qualitative case study of two LFPSs in a large urban informal settlement near Nairobi, we focus on the dynamic interaction and delicate equilibrium within which government officials, LFPS representatives, parents, and students not only interact with but influence each other. Data for the study were gathered over the course of 8 weeks during May and June of 2010 in the urban slum called Mathare Village in Nairobi through document review, 35 interviews, and school visits. Conclusions: The findings suggest that LFPSs do not function in practice as in theory, and crucially, that there are inherent trade-offs, tensions, and unexpected dynamics in operation that have serious consequences for such issues as quality and equity, even when supported by formal government policy designed to address these aspects. The study reinforces the importance of national governments and international bodies increasing the resources devoted to improving access to, and the quality of, public education.
Keywords: Access to Education; Agency Cooperation; Barriers; Case Studies; Costs; Developing Nations; Equal Education; Fees; Foreign Countries; Government Role; Interaction; Kenya (Nairobi); Parent Role; Private Schools; Qualitative Research; Slum Schools; Urban Schools

What We Are Learning about Early Education in Sub-Saharan Africa - Gove, Amber (What We Are Learning about Early Education in Sub-Saharan Africa, 2017)
This commentary discusses the three articles in this (2017) issue. The articles expand the published research base on the effectiveness of early education in the sub-Saharan Africa countries of Zambia, Kenya, and the Democratic Republic of Congo (DRC). Each of the three articles employs rigorous methods to better understand the impact of classroom-based programs, in either preprimary or primary schools, designed to improve participants' outcomes in reading, mathematics, and socio-emotional development. Articles such as these that describe the characteristics, scope, and limitations of research findings are valuable to the global educational community, especially to those who design and/or implement improved programs or practices. This commentary examines: What methods work, under what conditions, and why? Which methods best answer the questions of what works, under what conditions, and why? and What will it take to get more studies like these completed and into the hands of practitioners and policymakers? [This commentary discusses Jukes et al., 2017 (EJ1147933), McCoy et al., 2017 (EJ1147934), and Aber et al., 2017 (EJ1147937).]
Keywords: Africa; Congo Republic; Early Childhood Education; Elementary Education; Foreign Countries; Instructional Effectiveness; Instructional Improvement; Kenya; Outcomes of Education; Teaching Methods; Young Children; Zambia

Assessing the Impact of Early Learning Programs in Africa - Gove, Amber; Brunette, Tracy; Bulat, Jennae; Carrol, Bidemi; Henny, Catherine; Macon, Wykia; Nderu, Evangeline; Sitabkhan, Yasmin (Assessing the Impact of Early Learning Programs in Africa, 2017)
We present results from early learning programs in six African countries: Ethiopia, Kenya, Liberia, Malawi, Tanzania, and Uganda. In partnership with ministries of education, RTI International has worked within government systems to support the design and deployment of locally contextualized materials, training, and assessment tools, with the goal of improving outcomes for early learners in primary schools, and in Kenya and Tanzania preprimary as well. Here we report on the experience and evidence of impact from specific programs in each country, including summary assessment results when available. In several countries with completed impact evaluations, there are significant and important learning gains of between 0.2 and 2.57 SD in effect size; in one case the percentage of students reaching grade-level reading proficiency increased from 12% to 47%. In the context of increased urgency surrounding what UNESCO has called a "global learning crisis," these experiences provide useful lessons for policymakers and practitioners alike.
Keywords: Achievement Gains; Africa; Effect Size; Elementary Education; Emergent Literacy; Ethiopia; Foreign Countries; Kenya; Liberia; Malawi; Partnerships in Education; Program Effectiveness; Program Evaluation; Reading Achievement; Reading Improvement; Tanzania; Uganda

Investigating the Effects of Community-Based Interventions on Mathematics Achievement of Girls from Low-Income Households in Kenya - Hungi, Njora; Ngware, Moses (Investigating the Effects of Community-Based Interventions on Mathematics Achievement of Girls from Low-Income Households in Kenya, 2017)
This paper uses difference-in-difference and multivariate analyses procedures to examine the effects of two community-based intervention packages on mathematics achievement of primary school girls from low-income urban households in Kenya. The data involved in this study were collected between 2013 and 2015 from 748 12-19 years old primary school girls residing in two major Nairobi slums of Viwandani and Korogocho. These data were part of a larger intervention study that sought to improve schooling outcomes among girls from disadvantaged home backgrounds by providing them with after-school homework support, life skill mentoring and parental counselling. Results reveal intervention effects of between 23 and 26 mathematics score points on a Rasch scale with a mean of 400 a standard deviation of 100. These effects translate to at least one school term of learning for girls in the comparison group. Effect size for one of the intervention packages was small (0.24), while that of the second package was moderate (0.40).
Keywords: After School Programs; Community Programs; Counseling; Daily Living Skills; Disadvantaged Youth; Elementary School Students; Foreign Countries; Homework; Intervention; Kenya (Nairobi); Low Income Groups; Mathematics Achievement; Mathematics Tests; Mentors; Multivariate Analysis; Parents; Program Effectiveness; Quasiexperimental Design; Scores; Slums; Surveys; Urban Areas

Uhusiano Design for learning. - Johnstone, Christopher; Nikoi, Acacia; Kahihu, Ndungu (Uhusiano Design for learning., 2017)
Kenya’s post-colonial education system, like many in Sub-Saharan Africa, has endured many challenges. High enrollment in primary schools is often coupled with low completion rates in secondary and postsecondary education. In this article we examine some of the processes that may lead to the disempowerment and disenfranchisement of youth in Kenyan schools, and report on a new approach that we call “Uhusiano Design for Learning”. Uhusiano Design focuses on three aspects of learner-centered pedagogy: multiple teachers (which creates an egalitarian sense of togetherness among participants), hands-on learning, and confidence. Longitudinal data from a non-formal education implementation of Uhusiano Design indicates that the strategies and approaches may support traditionally marginalized learners in and out of Kenya’s formal education system.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Curriculum planning; Education & society; Education policy; Educational Support Services; Elementary and Secondary Schools; Kenya; Literacy; Other local, municipal and regional public administration; Other provincial and territorial public administration; Primary education; School enrollment; Secondary education

Improving Literacy Instruction in Kenya through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial - Jukes, Matthew C. H.; Turner, Elizabeth L.; Dubeck, Margaret M.; Halliday, Katherine E.; Inyega, Hellen N.; Wolf, Sharon; Zuilkowski, Stephanie Simmons; Brooker, Simon J. (Improving Literacy Instruction in Kenya through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial, 2017)
We evaluated a program to improve literacy instruction on the Kenyan coast using training workshops, semiscripted lesson plans, and weekly text-message support for teachers to understand its impact on students' literacy outcomes and on the classroom practices leading to those outcomes. The evaluation ran from the beginning of Grade 1 to the end of Grade 2 in 51 government primary schools chosen at random, with 50 schools acting as controls. The intervention had an impact on classroom practices with effect sizes from 0.57 to 1.15. There was more instruction with written text and more focus on letters and sounds. There was a positive impact on three of four primary measures of children's literacy after two years, with effect sizes up to 0.64, and school dropout reduced from 5.3% to 2.1%. This approach to literacy instruction is sustainable, and affordable and a similar approach has subsequently been adopted nationally in Kenya.
Keywords: Classroom Observation Techniques; Dropout Rate; Effect Size; Elementary School Students; Elementary School Teachers; Faculty Development; Foreign Countries; Grade 1; Grade 2; Handheld Devices; Intelligence Tests; Intervention; Interviews; Kenya; Literacy Education; Maximum Likelihood Statistics; Pretests Posttests; Program Effectiveness; Questionnaires; Randomized Controlled Trials; Raven Progressive Matrices; Rural Schools; Statistical Analysis; Teacher Improvement; Teaching Methods; Telecommunications

Hierarchical Linear Modelling of Sixth-Grade Students' Socio-Economic Status and School Factors on Mathematics Achievement: Case Studies of Kenya and Zimbabwe - Kanyongo, Gibbs Y.; Ayieko, Rachel (Hierarchical Linear Modelling of Sixth-Grade Students' Socio-Economic Status and School Factors on Mathematics Achievement: Case Studies of Kenya and Zimbabwe, 2017)
This study investigated the relationship between socio-economic status, school-level variables and mathematics achievement of sixth graders in Kenya and Zimbabwe. The study is based on secondary data collected by the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ III). SACMEQ employed cluster-sampling procedures to collect data from 4412 students in 193 schools in Kenya, and 3021 students in 155 schools in Zimbabwe. A multilevel model (Hierarchical linear model) was used to analyse variation in student achievement in mathematics between and within schools. Owing to the nested nature of the data, the study utilised the Wiley and Harnischfeger model as a general framework for choosing variables and conceptualising multiple components of education. The findings in both countries showed that socio-economic status and school resources were significant predictors of mathematics achievement. The variable "class size" in Kenya was positively related to mathematics achievement, but in Zimbabwe a negative and significant relationship existed between "class size" and "achievement." In Kenya "school type" was positively associated with mathematic achievement, but in Zimbabwe no such association existed. Additionally, 25-30% of the variance in student achievement in mathematics in both countries is explained by differences between schools. These findings suggest a disparity in mathematics achievement between schools in both countries based on class size and school type. Stakeholders can use these findings to make policies that help establish parity across the schools.
Keywords: Case Studies; Class Size; Comparative Education; Data Collection; Elementary School Students; Foreign Countries; Grade 6; Hierarchical Linear Modeling; Institutional Characteristics; Kenya; Mathematics Achievement; Mathematics Tests; Scores; Socioeconomic Status; Standardized Tests; Zimbabwe

Translanguaging in the Writing of Emergent Multilinguals - Kiramba, Lydiah Kananu (Translanguaging in the Writing of Emergent Multilinguals, 2017)
This article discusses the findings of an empirical study that investigated the writing practices in a multilingual, rural, fourth-grade classroom in Kenya. The study was undergirded by Bakhtin's heteroglossia. Analysis of texts indicated that these emergent multilinguals used multiple semiotic resources to maximize the chances of meeting the communicative goals through translanguaging. However, the translanguaging process in writing was a tension-filled process in terms of language separation and correctness. The emergent multilingual writer went through tensions in the process of finding a balance between authorial intentions and the authoritarian single voicedness required by the school and the national curriculum. The author suggests that translanguaging in writing disrupts unequal voices and language hierarchies by transgressing standard ideologies in academic writing. It is recommended that educators consider multilingual resources as legitimate cognitive tools and resources for communication in school contexts to allow authentic voices and inclusive instruction.
Keywords: Academic Discourse; African Languages; Code Switching (Language); Discourse Analysis; Elementary School Students; English (Second Language); Essays; Ethnography; Foreign Countries; Grade 4; Kenya; Language Research; Language Usage; Language of Instruction; Multilingualism; National Curriculum; Native Language; Official Languages; Rural Schools; Second Language Learning; Semiotics; Writing (Composition); Writing Evaluation; Writing Processes

Translanguaging in the Writing of Emergent Multilinguals - Kiramba, Lydiah Kananu (Translanguaging in the Writing of Emergent Multilinguals, 2017)
This article discusses the findings of an empirical study that investigated the writing practices in a multilingual, rural, fourth-grade classroom in Kenya. The study was undergirded by Bakhtin's heteroglossia. Analysis of texts indicated that these emergent multilinguals used multiple semiotic resources to maximize the chances of meeting the communicative goals through translanguaging. However, the translanguaging process in writing was a tension-filled process in terms of language separation and correctness. The emergent multilingual writer went through tensions in the process of finding a balance between authorial intentions and the authoritarian single voicedness required by the school and the national curriculum. The author suggests that translanguaging in writing disrupts unequal voices and language hierarchies by transgressing standard ideologies in academic writing. It is recommended that educators consider multilingual resources as legitimate cognitive tools and resources for communication in school contexts to allow authentic voices and inclusive instruction.
Keywords: Academic Discourse; African Languages; Code Switching (Language); Discourse Analysis; Elementary School Students; English (Second Language); Essays; Ethnography; Foreign Countries; Grade 4; Kenya; Language Research; Language Usage; Language of Instruction; Multilingualism; National Curriculum; Native Language; Official Languages; Rural Schools; Second Language Learning; Semiotics; Writing (Composition); Writing Evaluation; Writing Processes

Influence of Examinations Oriented Approaches on Quality Education in Primary Schools in Kenya - Mackatiani, Caleb Imbova (Influence of Examinations Oriented Approaches on Quality Education in Primary Schools in Kenya, 2017)
This paper provides a critical appraisal of the influence of examinations oriented approaches on quality education in primary schools in Kenya. The purpose of the study was to determine effects of examination oriented teaching approaches on learning achievement among primary school pupils in Kakamega County, Kenya. It explored the assumptions underlying pedagogical approaches as well as the negative influences of exam-oriented approaches in Kenyan schools. Examination oriented approaches don't address acquisition of practical skills, values, and attitudes in learners. The approaches merely concentrate on passing of national examinations by pupils. Globally, primary education is recognized as the pillar of any country that is expected to have the stable economy. Due to the role played by education in economic development and promotion of peace development, the United Nations (UN) general assembly in 1948 endorsed education as a fundamental human right. The purpose of the study is to interrogate the influence of examinations oriented approaches on quality education in primary schools. The paper examined the advances of United Nations Educational Scientific and Cultural Organization (UNESCO) in defining and actualizing quality education. The paper further assessed the role played by examinations in determining teaching approaches in schools. Instructional approaches play the crucial role in learning achievement of pupils. Appropriate approaches enhance achievement of competencies during the learning process. However, inappropriate methods affect knowledge retention negatively and lead to rote learning.The study was guided by transactional analysis theory as advanced Eric Berne in 1950. Transactional analysis is a method that facilitates communication between learners and teachers in a classroom environment. The theory illustrates how people have developed and how they treat themselves. It further outlines how people relate and communicate among themselves. This is actualized in the provision of suggestions and interventions which enable people to change and adjust to the environment. Flanders (1970), notes that teachers as initiators of communication adopt teaching methods based on their cognitive orientation. Through the pedagogy selected, the teacher communicates to learners in the classroom. Pupils are stimulated in order to achieve learning objectives. Flanders further developed a system of interaction analysis on the transaction that goes on in the classroom. The analysis came up with teacher-centered and learner-centered approaches. This study adopted by transactional analysis theory in order to analyze the influence exam oriented model of education on the use of convectional approaches by teachers in Kenyan primary schools. The qualitative property to be acquired is quality oriented model in primary school education. Inputs which lead to quality education in primary schools are the independent variables of this study. The outputs which culminate into outcomes of quality education are realized in quality indicators. The study had to examine the challenges of educational quality that arise due to pressure from examinations excellence. The study further examined how enrolment in primary schools influences examinations oriented approaches. Particular attention was given to the crises in inputs and processes that affect the output of quality primary education. These crises are reflected in class size, teacher establishment and physical resources that influence quality education. The study, therefore, focused on teaching approaches practiced by teachers in primary schools. The study adopted mixed methods of study. Both quantitative and qualitative approaches to research were used. Descriptive survey design was therefore adopted. It targeted a population of 536000 in Kakamega County, Kenya. The target population comprised of head teachers, teachers, and pupils. Purposive and simple random sampling was adopted to obtain the desired sample size. Using the descriptive survey design, data was collected using three sets of questionnaires. The reliability was estimated through use of Cranach's Alpha Coefficient using Statistical Package for Social Sciences (SPSS) version 19.0. Findings of the study revealed that examinations oriented approach negatively affect pupils' learning achievement. It is therefore anticipated that this study is significant as findings of the study may help in the formulation of education policies and legal framework which are geared towards curbing inequalities leading to the qualitative approach to primary school education. The policy implementers would also understand and appreciate education policies within which they are supposed to operate in providing effective leadership and management practices in the implementation of quality-based education at primary level. The study is also significant to the field of comparative and International education as it provides data on what the Kenyan government is doing in addressing equality and inequality in education leading to the development of quality based approach to primary school education. The study suggests moderate pressure to excel in school, as exam oriented approach can stifle a student's imagination, creativity and ultimate success the learning process. Inefficiency has infiltrated primary schools due to exam oriented system. It is there recommended that the government should come up with clear policy to redress inefficiency in primary schools to entrench quality education.
Keywords: Academic Achievement; Administrator Attitudes; Comparative Education; Counties; Creativity; Economic Development; Educational Policy; Educational Quality; Elementary School Students; Elementary School Teachers; Equal Education; Foreign Countries; Imagination; Instructional Leadership; Interaction Process Analysis; International Education; Intervention; Kenya; Leadership Effectiveness; Learning Processes; Learning Theories; Mixed Methods Research; Models; Observation; Outcomes of Education; Questionnaires; Role of Education; Student Attitudes; Surveys; Teacher Attitudes; Teacher Student Relationship; Teaching Methods; Test Preparation

Effects of Livestock Herd Migration on Child Schooling in Marsabit District, Kenya - Mburu, Samuel (Effects of Livestock Herd Migration on Child Schooling in Marsabit District, Kenya, 2017)
To throw light on the challenge of providing education to pastoral households in the context of social and economic change, this study investigates the effects of herd migration on child schooling in Northern Kenya. Specifically, the analysis uses both household panel data and community-level focus-group data to identify the barriers to schooling, which include an insufficient number of schools, nomadism and communal conflicts. The results also reveal that herd migration has a significantly negative effect on school attendance--about a 26% probability of failure to attend among the children of livestock migrating households. The child's age and mother's literacy have a positive impact on child school attendance, but with girls more likely to attend than boys, probably because of higher opportunity costs. That is, attending school takes boys away from activities like herding, which have greater economic value than the nonmonetisable household duties performed by girls.
Keywords: Access to Education; Age Differences; Agricultural Occupations; Animals; Attendance Patterns; Barriers; Elementary School Students; Focus Groups; Foreign Countries; Gender Differences; Kenya; Migrant Children; Mothers; Parent Influence; Probability; Reading Skills; Statistical Analysis

Children's Reading Ability in Early Primary Schooling: Challenges for a Kenyan Rural Community - Mwoma, Teresa (Children's Reading Ability in Early Primary Schooling: Challenges for a Kenyan Rural Community, 2017)
School outcomes and good performance in different subjects depends on children's ability to read. Thus teaching children on how to read during early grades is critical in promoting learning to read. More advanced skills acquired in later grades depend on early grade learning, so children who do not acquire these reading skills in their early grades struggle to acquire more advanced skills usually absorbed through reading. This article reports findings of a study conducted in rural public primary schools in Narok County, Kenya, focusing on the ability of children to read. The study sought to establish the factors influencing children's reading ability and whether there are differences in reading between boys and girls in grade three. A sample comprising 188 grade three children (94 girls and 94 boys) participated in the study, together with 18 head teachers, 66 teachers and 5 education officers from the 18 participating schools. A mixed methods research approach involving concurrent quantitative and qualitative data collection techniques was utilised. Early grade reading assessment tests for English and Kiswahili were utilised to collect quantitative data on children's reading ability. Key informant interviews with head teachers and education officers, and group interviews with teachers were conducted to collect qualitative data. Findings revealed that boys had slightly better mean scores in reading for the two subjects than girls. Availability of reading materials both at home and in school, together with getting supportive parents and teachers, were found to be critical in promoting children's reading.
Keywords: African Languages; Barriers; Elementary School Students; English (Second Language); Foreign Countries; Gender Differences; Grade 3; Interviews; Kenya; Language Tests; Mixed Methods Research; Qualitative Research; Reading Ability; Reading Comprehension; Reading Fluency; Reading Materials; Reading Tests; Regression (Statistics); Rural Areas; Scores; Second Language Learning; Teacher Attitudes

Towards Improvement of Student Learning Outcomes: An Assessment of the Professional Development Needs of Lecturers at Kenyan Universities - NaliakaMukhale, Phoebe; Hong, Zhu (Towards Improvement of Student Learning Outcomes: An Assessment of the Professional Development Needs of Lecturers at Kenyan Universities, 2017)
The aim of this study was to explore the professional development needs of lecturers at Kenyan universities. Specifically, the study investigated the challenges that lecturers and their learners face while in class. It also explored the professional development needs of the lecturers, preferred modes of delivery of the professional development programs and changes that lecturers need to effect in their practice of teaching in order to improve student learning outcomes. The study was guided by two theories: Andragogy and Situated Cognition. The sample size comprised 15 lecturers from one public university in Kenya. Data was collected using the semi-structured interviews. Data was transcribed and analyzed using thematic coding including, four areas of professional development needs: pedagogy, subject matter, technology and research. The study found that in order to enhance student learning outcomes, lecturers need to adopt a more student-centered approach, embrace seminar way of teaching, use practical approaches, be ICT compliant and create and teach courses which offer learners significant learning experiences. The lecturers prefer both face-to-face and online as modes of delivery for professional development programs.
Keywords: Andragogy; Blended Learning; Coding; Cognitive Processes; College Faculty; Educational Needs; Faculty Development; Foreign Countries; Information Technology; Kenya; Knowledge Base for Teaching; Knowledge Level; Needs Assessment; Preferences; Qualitative Research; Semi Structured Interviews; Seminars; Student Centered Learning; Teacher Education; Teacher Researchers; Teaching Methods

Towards Improvement of Student Learning Outcomes: An Assessment of the Professional Development Needs of Lecturers at Kenyan Universities - NaliakaMukhale, Phoebe; Hong, Zhu (Towards Improvement of Student Learning Outcomes: An Assessment of the Professional Development Needs of Lecturers at Kenyan Universities, 2017)
The aim of this study was to explore the professional development needs of lecturers at Kenyan universities. Specifically, the study investigated the challenges that lecturers and their learners face while in class. It also explored the professional development needs of the lecturers, preferred modes of delivery of the professional development programs and changes that lecturers need to effect in their practice of teaching in order to improve student learning outcomes. The study was guided by two theories: Andragogy and Situated Cognition. The sample size comprised 15 lecturers from one public university in Kenya. Data was collected using the semi-structured interviews. Data was transcribed and analyzed using thematic coding including, four areas of professional development needs: pedagogy, subject matter, technology and research. The study found that in order to enhance student learning outcomes, lecturers need to adopt a more student-centered approach, embrace seminar way of teaching, use practical approaches, be ICT compliant and create and teach courses which offer learners significant learning experiences. The lecturers prefer both face-to-face and online as modes of delivery for professional development programs.
Keywords: Andragogy; Blended Learning; Coding; Cognitive Processes; College Faculty; Educational Needs; Faculty Development; Foreign Countries; Information Technology; Kenya; Knowledge Base for Teaching; Knowledge Level; Needs Assessment; Preferences; Qualitative Research; Semi Structured Interviews; Seminars; Student Centered Learning; Teacher Education; Teacher Researchers; Teaching Methods

Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs - Piper, Benjamin (Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs, 2017)
Education researchers working in sub-Saharan Africa have recently and rapidly expanded the availability of evidence related to the impact of educational interventions on learning outcomes, particularly in preprimary and lower primary education (Ganimian & Murnane, 2016; McEwan, 2015; Popova, Evans, & Arancibia, 2016). Awareness that literacy and numeracy skills are essential for children to succeed throughout their educational career, and of the tragically poor learning outcomes for many children in sub-Saharan Africa (Gove & Cvelich, 2011; Pritchett, 2013), has spurred an increase in educational interventions in the region that focus on improving learning outcomes in the initial stages of formal education. One challenge in conducting and learning from research conducted in low- and middle-income countries (LMICs) is the difficulty in measuring learning outcomes in different contexts. The field has seen a slow trend toward developing and using universalized measures. The three articles in this (2017) issue provide an opportunity to reflect on whether this trend is beneficial. This commentary offers a comparison of the three articles, including the different measures of student learning, languages, curriculum documents, and improvements in learning outcomes for children in Zambia, Kenya, and the Democratic Republic of the Congo (DRC) respectively. [This commentary discusses Jukes et al., 2017 (EJ1147933), McCoy et al., 2017 (EJ1147934), and Aber et al., 2017 (EJ1147937).]
Keywords: Africa; Congo Republic; Developing Nations; Early Childhood Education; Educational Research; Elementary Education; Foreign Countries; Instructional Improvement; Intervention; Kenya; Literacy Education; Numeracy; Outcomes of Education; Program Effectiveness; Research Design; Teaching Methods; Zambia

Implementing Large-Scale Instructional Technology in Kenya: Changing Instructional Practice and Developing Accountability in a National Education System - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (Implementing Large-Scale Instructional Technology in Kenya: Changing Instructional Practice and Developing Accountability in a National Education System, 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya's education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
Keywords: Accountability; Educational Practices; Educational Quality; Educational Technology; Foreign Countries; Handheld Devices; Intervention; Interviews; Kenya; Literacy; National Surveys; Observation; Outcomes of Education; Questionnaires; Statistical Analysis; Statistical Significance; Technology Uses in Education; Telecommunications

Building State Capability: Evidence, Analysis, Action - Andrews, Matt; Pritchett, Lant; Woolcock, Michael (2017)

National Pre-primary Education Policy, 2017 - Republic of Kenya (2017)

The Kenya Integrated Early Childhood Development Policy Framework - Republic of Kenya (2017)

Sustainable Development Goal 4 (SDG4) | #LeadingSDG4 | Education2030 - UNESCO (2017)
Leading SDG4: Education2030 for Inclusive and Quality Education

Assessing the effectiveness of foreign aid in the education sector in africa: The case of primary education - Yogo, Thierry Urbain (African Development Review, 2017)
Since 2000, Official Development Assistance has played a crucial role in efforts related to the achievement of MDGs. This is especially the case in sub-Saharan Africa (SSA) which is the world's largest recipient of foreign aid. This paper assesses the effectiveness of aid and its efficient use in achieving universal primary education in sub-Saharan Africa. The impact of aid is assessed for a sample of 35 SSA countries over the decade 2000–10. The results suggest that higher aid to education significantly increases primary completion rate. This result is robust to the use of various methods of estimation, the inclusion of instrument to account for the endogeneity of aid and the set of control variables included in regressions. Our findings suggest that education aid can be used as a policy instrument to achieve the fourth Sustainable Development Goal (SDG) which is to ensure inclusive and quality education for all and promote lifelong learning.

Tusome: A Decade of Success in Kenyan Literacy Education - RTI International (2016)
See how Kenya's Tusome project, in collaboration with USAID, made remarkable strides in enhancing early literacy outcomes for millions of students.​​

Parental participation improves student academic achievement: A case of Iganga and Mayuge districts in Uganda. - Mahuro, G.M.; Hungi, N.; Lamb, Stephen (Parental participation improves student academic achievement: A case of Iganga and Mayuge districts in Uganda., 2016)
Educational research has linked parental participation in childrens schooling with a wide range of childrens academic outcomes. Parental involvement involves time and resource commitment towards childrens academic performance. This paper extracts data from a cross-sectional survey involving 2,669 grade six students attending public and private primary schools serving households located in IgangaMayuge health and demographic surveillance system in rural Eastern Uganda. The paper adopts two of the six types of parental involvement detailed in the Epstein parental involvement framework. This paper hypothesises that parental participation through parenting and communication types of involvement will give children an advantage towards academic achievement. Using a regression model and controlling for individual, school and household covariates, the results indicate that a unit increase in parental participation through parenting and communication types of involvement significantly increases students numeracy scores by 6 and 15 percentage points, respectively. Similarly, a unit increase in parental participation through parenting and communication types of involvement significantly increases students literacy scores, by 6 and 12 percentage points, respectively. This implies that parental participation plays a pivotal role in motivating children to improve their academic grades. For students to reap maximum benefits in an education system, the learning should not be solely left to the studentteacher relationship but should be extended to include active parental involvement among other education stakeholders.
Keywords: Academic achievement; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Cross-sectional method; Education research; Educational Support Services; Parent participation in primary education; Task performance; Uganda

Moderated effects of risky behavior on academic performance among adolescent girls living in urban slums of Kenya. - Ngware, Moses W.; Mahuro, Gerald M.; Hungi, Njora; Abuya, Benta; Nyariro, Milka P.; Mutisya, Maurice; Hui, Sammy King Fai (Moderated effects of risky behavior on academic performance among adolescent girls living in urban slums of Kenya., 2016)
This paper examines effects of life-skills, mentoring, and counseling education intervention implemented among primary school attending girls aged between 10 and 19 years, living in Nairobi slums. We hypothesized that interaction between the intervention and aspiration, self-confidence and interest in schooling, mediates the impact of risky behavior on academic performance. This quasi-experimental study had two treatment arms of 538 girls and one comparison with 272 girls. The first treatment arm received life skills mentoring, after school support with homework, and parental counseling; the second treatment arm received a package similar to the first arm excluding parental counseling; while the comparison arm received nothing during the implementation period, but they got a secondary school fees subsidy at the end of the intervention. The analysis shows that the intervention had statistically significant effects on some aspects of risky behavior and the mediators. Results from a structural equation model show existence of strong moderated mediation effects of risky behavior on academic performance. The importance of the findings is in demonstrating how inner-character attributes could enhance learning outcomes, especially among adolescent girls in low-resourced environments.
Keywords: Academic achievement; Educational counseling; Life skills; Psychology of teenage girls; Risk-taking behavior; Slums

Rethinking Women's Learning and Empowerment in Kenya: Maasai Village Women Take Initiative - Takayanagi, Taeko (Rethinking Women's Learning and Empowerment in Kenya: Maasai Village Women Take Initiative, 2016)
This study investigates the activities of a village-based literacy centre in Kenya and explores the benefits of community development activities on women's well-being in Africa. Through the analysis of the stories of two Maasai women who had experienced adult literacy learning, the author discovered that: (1) the literacy instructor had inadequate in-service teacher training support from the government; (2) these women were using a space generated by collaborative informal learning through the literacy centre to improve their families' and community's well-being; and (3) these women gained empowerment through community development activities organised by the literacy centre. The author concludes that grassroots literacy and informal learning have been effective in improving the quality of life for the village women, and should be encouraged and supported by external agencies.
Keywords: Adult Literacy; Community Development; Cooperative Learning; Empowerment; Ethnic Groups; Females; Foreign Countries; Informal Education; Inservice Teacher Education; Kenya; Literacy Education; Personal Narratives; Quality of Life; Rural Areas; Well Being; Womens Education

Implementing Mother Tongue Instruction in the Real World: Results from a Medium-Scale Randomized Controlled Trial in Kenya - Piper, Benjamin; Zuilkowski, Stephanie S.; Ong'ele, Salome (Implementing Mother Tongue Instruction in the Real World: Results from a Medium-Scale Randomized Controlled Trial in Kenya, 2016)
Research in sub-Saharan Africa investigating the effect of mother tongue (MT) literacy instruction at medium scale is limited. A randomized controlled trial of MT literacy instruction was implemented in 2013 and 2014 as part of the Primary Math and Reading (PRIMR) Initiative in Kenya. We compare the effect of two treatment groups--the base PRIMR program teaching literacy in English and Kiswahili and the PRIMR-MT program, which taught literacy in English, Kiswahili, and mother tongue--in two different language environments. Implementation of the MT program faced challenges because many educators were not speakers of the languages, some communities resisted mother tongue instruction, and some areas were more language heterogeneous. Effect sizes on MT literacy averaged between 0.3 and 0.6 standard deviations. The base PRIMR program also increased MT learning outcomes in some measures but had smaller effects than the PRIMR-MT program in oral reading fluency and comprehension.
Keywords: African Languages; Effect Size; English (Second Language); Foreign Countries; Kenya; Language of Instruction; Literacy Education; Mathematics Instruction; Native Language; Native Language Instruction; Oral Reading; Primary Education; Program Implementation; Randomized Controlled Trials; Reading Comprehension; Reading Fluency; Reading Instruction; Resistance (Psychology)

Implementing Mother Tongue Instruction in the Real World: Results from a Medium-Scale Randomized Controlled Trial in Kenya - Piper, Benjamin; Zuilkowski, Stephanie S.; Ong'ele, Salome (Implementing Mother Tongue Instruction in the Real World: Results from a Medium-Scale Randomized Controlled Trial in Kenya, 2016)
Research in sub-Saharan Africa investigating the effect of mother tongue (MT) literacy instruction at medium scale is limited. A randomized controlled trial of MT literacy instruction was implemented in 2013 and 2014 as part of the Primary Math and Reading (PRIMR) Initiative in Kenya. We compare the effect of two treatment groups--the base PRIMR program teaching literacy in English and Kiswahili and the PRIMR-MT program, which taught literacy in English, Kiswahili, and mother tongue--in two different language environments. Implementation of the MT program faced challenges because many educators were not speakers of the languages, some communities resisted mother tongue instruction, and some areas were more language heterogeneous. Effect sizes on MT literacy averaged between 0.3 and 0.6 standard deviations. The base PRIMR program also increased MT learning outcomes in some measures but had smaller effects than the PRIMR-MT program in oral reading fluency and comprehension.
Keywords: African Languages; Effect Size; English (Second Language); Foreign Countries; Kenya; Language of Instruction; Literacy Education; Mathematics Instruction; Native Language; Native Language Instruction; Oral Reading; Primary Education; Program Implementation; Randomized Controlled Trials; Reading Comprehension; Reading Fluency; Reading Instruction; Resistance (Psychology)

Know Well before Supporting: Lessons of a Comprehensive Diagnosis of Two Low-Cost Private Schools in Slums of Nairobi, Kenya - Soto, Sebastián; Cordero, Juan Luis (Online Submission, 2016)
The purpose of the present report is to show a comprehensive diagnosis of the situation of two low-cost private schools (Destiny and Saint Martin's schools) located in two slums (Mathare and Kibera) of Nairobi, capital city of Kenya, that Educafrica's team found before starting a collaboration programme through field volunteers work. A wide variety of instruments were used in order to collect data that captures all the complexities of schools that deals with contexts of deep scarcity of basic resources as well as challenging working conditions. Data collected and systematized was fundamental to have a proper understanding of the current ongoing educational situation in these schools, in order to articulate the best interventional framework that will help to improve the schools' performance. Several lessons are drawn after analysing the schools' normal operation regarding teachers' methodological and pedagogical practices. Challenges for achieving a desired teaching system are also highlighted, which would also frame the action course of Educafrica for the next years. [This report was produced by Eduafrica Foundation.]
Keywords: Academic Achievement; Access to Education; Barriers; Costs; Elementary Education; Foreign Countries; Kenya (Nairobi); Peer Relationship; Preschool Education; Private Schools; Slum Schools; Student Participation; Teacher Attitudes; Teacher Education; Teacher Role; Time Management

EVALUATING LEARNERS'S ABILITY TO USE TECHNOLOGY IN DISTANCE EDUCATION: THE CASE OF EXTERNAL DEGREE PROGRAMME OF THE UNIVERSITY OF NAIROBI. - OMITO, Ouma (EVALUATING LEARNERS'S ABILITY TO USE TECHNOLOGY IN DISTANCE EDUCATION: THE CASE OF EXTERNAL DEGREE PROGRAMME OF THE UNIVERSITY OF NAIROBI., 2016)
The study was aimed at investigating the students' ability to use technology for distance education with specific reference to the University of Nairobi's External Degree Program. To achieve this, one specific objective was formulated: To find out the student teacher's readiness to accept and utilize technology for learning purposes in relation to their work experience. The study design used was cross- sectional survey with a well -constructed questionnaire. The study population was 500 External Degree Students of the University of Nairobi who were final year students in the Bachelor of Education (Arts) by distance mode. The study sample of 217 was reached at by the use of a sample table provided by Krejcie and Morgan, (1970). Simple random sampling technique was used to identify the 217 respondents. A total of 110 questionnaires were filled and returned by respondents who were mainly primary school teachers in Kenya. A non-probability sampling technique (purposive) was used to select the cohort under study, that is, the final semester students in the External Degree Program of the University of Nairobi. The results from the pilot study were used to prove content validity as instrument reliability was determined from the internal consistency of responses from the questionnaires after the pilot study. The findings from the study revealed that majority of teachers 19 (50%) who had a work experience between 6 to 11 years were able to gather information from the internet for learning purposes. It was also learnt that as the number of years of work experience increased (21 years and above), the ability to gather information from the internet decreased drastically. When respondents were asked of their ability to troubleshoot computers, all categories of work experience showed low ability. All percentages were less than 50% with the work experience brackets of 21 and above years which recorded 22.2%, emerged as the highest percentage. Finally, when respondents were asked about their feelings towards using computers for their additional research and education, the work experience brackets of 21 and above years overwhelmingly, 6 (67.7%), enjoyed working with computers. It was, therefore, concluded that any institution aiming at introducing e-learning in their institution should assess students' technology literacy levels and prepare them in advance before the launch of e-learning.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Distance education; Educational technology; Mobile learning; Students; Teachers

Evaluating Learners's Ability to Use Technology in Distance Education: The Case of External Degree Programme of the University of Nairobi - Omito, Ouma (Evaluating Learners's Ability to Use Technology in Distance Education: The Case of External Degree Programme of the University of Nairobi, 2016)
The study was aimed at investigating the students' ability to use technology for distance education with specific reference to the University of Nairobi's External Degree Program. To achieve this, one specific objective was formulated: To find out the student teacher's readiness to accept and utilize technology for learning purposes in relation to their work experience. The study design used was cross-sectional survey with a well-constructed questionnaire. The study population was 500 External Degree Students of the University of Nairobi who were final year students in the Bachelor of Education (Arts) by distance mode. The study sample of 217 was reached at by the use of a sample table provided by Krejcie and Morgan, (1970). Simple random sampling technique was used to identify the 217 respondents. A total of 110 questionnaires were filled and returned by respondents who were mainly primary school teachers in Kenya. A non-probability sampling technique (purposive) was used to select the cohort under study, that is, the final semester students in the External Degree Program of the University of Nairobi. The results from the pilot study were used to prove content validity as instrument reliability was determined from the internal consistency of responses from the questionnaires after the pilot study. The findings from the study revealed that majority of teachers 19 (50%) who had a work experience between 6 to 11 years were able to gather information from the internet for learning purposes. It was also learnt that as the number of years of work experience increased (21 years and above), the ability to gather information from the internet decreased drastically. When respondents were asked of their ability to troubleshoot computers, all categories of work experience showed low ability. All percentages were less than 50% with the work experience brackets of 21 and above years which recorded 22.2%, emerged as the highest percentage. Finally, when respondents were asked about their feelings towards using computers for their additional research and education, the work experience brackets of 21 and above years overwhelmingly, 6 (67.7%), enjoyed working with computers. It was, therefore, concluded that any institution aiming at introducing e-learning in their institution should assess students' technology literacy levels and prepare them in advance before the launch of e-learning.
Keywords: Case Studies; Computer Attitudes; Distance Education; Educational Technology; Elementary School Teachers; Foreign Countries; Internet; Kenya (Nairobi); Questionnaires; Student Surveys; Teacher Education Programs; Teaching Experience; Technology Integration; Technology Uses in Education; Undergraduate Students

Factors Hindering the Deployment of Female Teachers to Headship Positions in Public Primary Schools in Nambale Sub-County, Kenya - Mukolwe, Joseph O.; Okwara, Michael; Ajowi, O. Jack (Factors Hindering the Deployment of Female Teachers to Headship Positions in Public Primary Schools in Nambale Sub-County, Kenya, 2016)
Worldwide, women representation in management and leadership positions is marginal. Despite immense academic advancement by women, few of them do advance to management positions. In Kenya, women make up a critical portion of human resource base. However, they are grossly underrepresented at leadership positions. This situation is reflected in school leadership positions as well, including headship of schools. Unless the gender gaps in management and leadership positions are addressed, the talent of high skilled women would be underutilized and there might be a reproduction of gender inequality across generations. The purpose of this study was to examine the factors hindering the deployment of female teachers to headship positions in public primary schools. The main objective of this study was to establish the extent to which the two-thirds gender policy was being applied in deployment of female teachers to headship positions. This study was conducted in Nambale Sub-county. Descriptive survey design was used in this study. Out of a study population of 519 respondents comprising 45 head teachers, 45 deputy head teachers, 427 teachers drawn from 45 public primary schools in Nambale Sub-County, the District Education Officer (DEO) and District Quality Assurance and Standard Officer (DQASO), stratified sampling technique was employed to select 35 head teachers, 35 deputy head teachers and 196 teachers. Saturated sampling was used to select the DEO and the DQASO. Therefore, a sample size of 268 respondents, representing 52% of the study population was used in this study. Questionnaires, interview schedule guide and document analysis guide were used as instruments of data collection. Quantitative data were analyzed using frequency counts and percentages. Findings from the study revealed that the Ministry of Education provided for equal opportunities in terms of deployment but the two-thirds gender policy was not applied in deployment of teachers to school headship. Based on these findings, the study proposed that the Teachers Service Commission should come up with clear and precise deployment policies expressed in writing so that their compliance can easily be checked and the Ministry of Education should design a mechanism for implementing the two-thirds gender policy in deployment of teachers to headship positions.
Keywords: Administrator Surveys; Barriers; Elementary Schools; Equal Opportunities (Jobs); Females; Foreign Countries; Gender Bias; Interviews; Kenya; Policy; Principals; Questionnaires; Teacher Surveys; Women Administrators; Women Faculty

Do “better” teachers and classroom resources improve student achievement? A causal comparative approach in Kenya, South Africa, and Swaziland. - Zakharov, Andrey; Tsheko, Gaelebale; Carnoy, Martin (Do “better” teachers and classroom resources improve student achievement? A causal comparative approach in Kenya, South Africa, and Swaziland., 2016)
We use the 2007 SACMEQ data to make traditional “upwardly biased” estimates of teacher and classroom resource correlates of 6th grade student achievement in Swaziland, Kenya, and South Africa using an OLS model, and a “less biased causal” approach using a student fixed effects model. Our fixed effects model exploits the fact that most students in all three countries have different teachers for reading and mathematics. Each student is therefore subject to the “treatment” of different teacher characteristics and classroom resources, yielding a relatively unbiased but rather “stringent” estimate of teacher and classroom effects. Our results suggest that: (a) several important identifiable teacher characteristics and classroom resources affect student achievement in each country; that (b) those characteristics and resources may differ from one national context to another, between male and female students, and across socioeconomic groups of students; and that (c) the “upwardly biased” results generally differ from the “less biased causal” results. We discuss and attempt to explain these differences.
Keywords: Academic achievement; Administration of Education Programs; Africa; All Other Miscellaneous Schools and Instruction; Classroom environment; Education; Educational Support Services; Effective teaching; Higher education; Least squares; Mathematical ability

Do “better” teachers and classroom resources improve student achievement? A causal comparative approach in Kenya, South Africa, and Swaziland. - Zakharov, Andrey; Tsheko, Gaelebale; Carnoy, Martin (Do “better” teachers and classroom resources improve student achievement? A causal comparative approach in Kenya, South Africa, and Swaziland., 2016)
We use the 2007 SACMEQ data to make traditional “upwardly biased” estimates of teacher and classroom resource correlates of 6th grade student achievement in Swaziland, Kenya, and South Africa using an OLS model, and a “less biased causal” approach using a student fixed effects model. Our fixed effects model exploits the fact that most students in all three countries have different teachers for reading and mathematics. Each student is therefore subject to the “treatment” of different teacher characteristics and classroom resources, yielding a relatively unbiased but rather “stringent” estimate of teacher and classroom effects. Our results suggest that: (a) several important identifiable teacher characteristics and classroom resources affect student achievement in each country; that (b) those characteristics and resources may differ from one national context to another, between male and female students, and across socioeconomic groups of students; and that (c) the “upwardly biased” results generally differ from the “less biased causal” results. We discuss and attempt to explain these differences.
Keywords: Academic achievement; Administration of Education Programs; Africa; All Other Miscellaneous Schools and Instruction; Classroom environment; Education; Educational Support Services; Effective teaching; Higher education; Least squares; Mathematical ability

“I failed, no matter how hard I tried”: A mixed-methods study of the role of achievement in primary school dropout in rural Kenya. - Zuilkowski, Stephanie Simmons; Jukes, Matthew C.H.; Dubeck, Margaret M. (“I failed, no matter how hard I tried”: A mixed-methods study of the role of achievement in primary school dropout in rural Kenya., 2016)
Initial access to school is nearly universal in Kenya, but many children who enroll drop out before completing primary school. In this mixed-methods study, we use quantitative data from a randomized control trial involving 2666 upper primary-grade students, as well as qualitative data from interviews with 41 schoolchildren, dropouts, and parents, to examine dropout. Poorer baseline performance on literacy and numeracy assessments predicted a higher risk of dropout. Interviews revealed that children are the primary decision-makers rather than parents. Together, these findings suggest that school quality interventions may be an effective means of reducing primary school dropout in this region.
Keywords: Academic achievement; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Children; Education; Educational Support Services; Educational quality; Kenya; Primary education; Primary schools; School dropouts

Language choice and education quality in Eastern and Southern Africa: a review. - Trudell, Barbara (Language choice and education quality in Eastern and Southern Africa: a review., 2016)
In 2014, UNICEF commissioned a review of language policy and education quality in the 21 countries of UNICEF’s Eastern and Southern Africa Region. This paper examines findings from the review, related to the role of English and local languages in current education practice in the region. National language policies and implementation practices are examined, as is the mismatch between the two. The evident widespread use of English as the language of instruction in primary classrooms of Eastern and Southern Africa, even where the pupils do not speak English, generates two central questions: (1) Is English really the villain in this context? And (2) Why do teachers and pupils in these classrooms have to choose one language or another as medium of instruction?
Keywords: Classroom activities; Educational quality; Elementary and Secondary Schools; English language acquisition; Language policy; Primary education; School children; Secondary education; South Africa; UNICEF

Using Educational Technology to Develop Early Literacy Skills in Sub-Saharan Africa - Abrami, Philip C.; Wade, C. Anne; Lysenko, Larysa; Marsh, Jonathon; Gioko, Anthony (Using Educational Technology to Develop Early Literacy Skills in Sub-Saharan Africa, 2016)
The research explores the impact of interactive, multimedia literacy software (ABRA) on the reading skills of early elementary students in Kenya. Twelve grade two English teachers and their students from six schools were randomly divided in half: an experimental group (N = 180) where ABRA was part of their English Language instruction and a control group (N = 174) where regular instruction was used. After the pre-test student data were collected, a three-day initial training and planning session were held for the experimental teachers on how to use ABRA to teach literacy. Every week each experimental class was bussed to a computer lab with full access to ABRA for one 90-min lesson. Teacher support included the alignment of ABRA lesson plans with the Kenyan English Language norms, weekly web conferences with the trainer, as well as technical and pedagogical help from staff at the lab site. After the 13-week intervention, significant and substantial gains in reading comprehension were found for ABRA students as measured by GRADE, a standardized test of literacy. In addition, ABRA students outperformed their peers in control classes on the core end-of-year subject exams including English, Mathematics, Science and Social Studies.
Keywords: Achievement Gains; Computer Centers; Computer Software; Control Groups; Early Reading; Educational Technology; Elementary School Students; Elementary School Teachers; English (Second Language); Experimental Groups; Foreign Countries; Grade 2; Kenya; Language Teachers; Lesson Plans; Literacy; Literacy Education; Multimedia Materials; Outcomes of Education; Pretests Posttests; Reading Comprehension; Second Language Instruction; Second Language Learning; Standardized Tests; Teaching Methods

Using Educational Technology to Develop Early Literacy Skills in Sub-Saharan Africa - Abrami, Philip C.; Wade, C. Anne; Lysenko, Larysa; Marsh, Jonathon; Gioko, Anthony (Using Educational Technology to Develop Early Literacy Skills in Sub-Saharan Africa, 2016)
The research explores the impact of interactive, multimedia literacy software (ABRA) on the reading skills of early elementary students in Kenya. Twelve grade two English teachers and their students from six schools were randomly divided in half: an experimental group (N = 180) where ABRA was part of their English Language instruction and a control group (N = 174) where regular instruction was used. After the pre-test student data were collected, a three-day initial training and planning session were held for the experimental teachers on how to use ABRA to teach literacy. Every week each experimental class was bussed to a computer lab with full access to ABRA for one 90-min lesson. Teacher support included the alignment of ABRA lesson plans with the Kenyan English Language norms, weekly web conferences with the trainer, as well as technical and pedagogical help from staff at the lab site. After the 13-week intervention, significant and substantial gains in reading comprehension were found for ABRA students as measured by GRADE, a standardized test of literacy. In addition, ABRA students outperformed their peers in control classes on the core end-of-year subject exams including English, Mathematics, Science and Social Studies.
Keywords: Achievement Gains; Computer Centers; Computer Software; Control Groups; Early Reading; Educational Technology; Elementary School Students; Elementary School Teachers; English (Second Language); Experimental Groups; Foreign Countries; Grade 2; Kenya; Language Teachers; Lesson Plans; Literacy; Literacy Education; Multimedia Materials; Outcomes of Education; Pretests Posttests; Reading Comprehension; Second Language Instruction; Second Language Learning; Standardized Tests; Teaching Methods

Using educational technology to develop early literacy skills in Sub-Saharan Africa. - Abrami, Philip; Wade, C.; Lysenko, Larysa; Marsh, Jonathon; Gioko, Anthony (Using educational technology to develop early literacy skills in Sub-Saharan Africa., 2016)
The research explores the impact of interactive, multimedia literacy software (ABRA) on the reading skills of early elementary students in Kenya. Twelve grade two English teachers and their students from six schools were randomly divided in half: an experimental group ( N = 180) where ABRA was part of their English Language instruction and a control group ( N = 174) where regular instruction was used. After the pre-test student data were collected, a three-day initial training and planning session were held for the experimental teachers on how to use ABRA to teach literacy. Every week each experimental class was bussed to a computer lab with full access to ABRA for one 90-min lesson. Teacher support included the alignment of ABRA lesson plans with the Kenyan English Language norms, weekly web conferences with the trainer, as well as technical and pedagogical help from staff at the lab site. After the 13-week intervention, significant and substantial gains in reading comprehension were found for ABRA students as measured by GRADE, a standardized test of literacy. In addition, ABRA students outperformed their peers in control classes on the core end-of-year subject exams including English, Mathematics, Science and Social Studies.
Keywords: Computers in education; Educational innovations; Educational technology; Literacy; Sub-Saharan Africa

Does community involvement affect teacher effort? Assessing learning impacts of Free Primary Education in Kenya. - Atuhurra, Julius F. (Does community involvement affect teacher effort? Assessing learning impacts of Free Primary Education in Kenya., 2016)
While the impressive school participation impacts of Universal Primary Education policies in Sub-Saharan Africa are widely recognized, attempts to measure learning gains from schooling remain minimal. Utilizing a unique international test score dataset, we measure and explain grade six reading and math learning outcomes in Kenya. By comparing competences between public and private schools before and after the introduction of free primary education, we find large achievement declines and inequalities based on gender and socioeconomic status. The declines are associated with low teacher efforts and community disengagement. Policy studies on community involvement in schools will likely lead to improved learning.
Keywords: Administration of Education Programs; Community involvement; Education policy; Kenya; Other local, municipal and regional public administration; Other provincial and territorial public administration; Primary education; Primary schools; School children; Teacher effectiveness

Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya. - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen (Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya., 2016)
Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions -- e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.
Keywords: Administration of Education Programs; Cost effectiveness; Education policy; Global studies; Information & communication technologies; Other local, municipal and regional public administration; Other provincial and territorial public administration; Primary schools; School children

Inspiring Readers. - Faulkner, Jessica (Inspiring Readers., 2016)
The article offers information on the programme Inspiring Readers for schools in Africa by the library development charity Book Aid International. It mentions that the aim of the programme was to bring book libraries into the classrooms of primary schools, reaching around a quarter of a million children. It states that the new programme begins in 2016 in Kenya and Cameroon, to improve the reading opportunities for a quarter of a million children.
Keywords: Africa; Book Aid International (Organization); Children; Commercial and Institutional Building Construction; Libraries; Libraries and Archives; Library editions; Primary schools

A Comparative Study of the Influence of Head Teachers Management Styles on Pupils Performance in KCPE in Public and Private Primary Schools in Nakuru Municipality, Kenya - Shibo, Margaret Nekesa (A Comparative Study of the Influence of Head Teachers Management Styles on Pupils Performance in KCPE in Public and Private Primary Schools in Nakuru Municipality, Kenya, 2016)
The purpose of this study was to compare the influence of management styles of head teacher's on pupils' performance in private and public primary schools in Nakuru municipality at Kenya Certificate of Primary Education level. The population comprised of teachers and head teachers in public primary schools. The study adopted the ex post facto survey research design and used a sample size of 70 primary schools in which 70 Head teachers and 70 teachers were interviewed. The respondents were selected using simple random sampling technique. Data for the study was collected by use of questionnaires and interview schedules. The study collected both qualitative and quantitative data. Data collected was analyzed through descriptive and inferential statistics with the aid of the Statistical Package for Social Sciences version 17. The results were presented by descriptive statistics. The study findings revealed that most public primary schools were using democratic and participatory leadership styles as opposed to private primary schools, which were mainly using autocratic leadership style; private primary schools were performing better than Public primary schools in Kenya Certificate of Primary Education (KCPE) in Nakuru municipality; most teachers in both private and public primary schools were not comfortable with the prevailing/current leadership styles and administration standards, and negatively related this with student performance. The findings further revealed a positive Spearman rank correlation between school mean mark and team working spirit r(62) = 0.078) p>0.05; and a positive Spearman rank correlation between school mean mark and adequate reading materials r(62) = 0.094) p>0.05. Although the two correlations were not significant. Following these findings, the study recommends that the Ministry of Education, school governing bodies, and concerned stakeholders should consider mobilizing and allocating resources geared towards mitigating the impediments to the effectiveness of primary school leadership styles.
Keywords: Academic Achievement; Administrator Attitudes; Comparative Analysis; Computer Software; Correlation; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Kenya; Leadership Effectiveness; Leadership Styles; Municipalities; Private Schools; Public Schools; Qualitative Research; Questionnaires; Resource Allocation; School Administration; Standards; Statistical Analysis; Surveys

How Freelance Journalists Can Help Shape Journalism Education. - Solomon, Eileen Fredman (How Freelance Journalists Can Help Shape Journalism Education., 2016)
Despite shrinking newsrooms, we have more journalism choices, in part because of freelance journalists. Freelancing creates workers who are particularly adaptive and creative; skills educators want to instill in students. I interviewed and surveyed more than 50 freelance journalists in several countries, including Turkey, Egypt, Colombia, Israel, Canada, Kenya, France, Germany, and the United States. While the basic skills of good journalism do not change, it is valuable to recognize and evaluate changing models. Independent and entrepreneurial freelancers have ideas that can help prepare journalism students to embrace the global realities of unpredictable and constant challenges.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Freelance journalism; Journalism education; Media journalism; Technological innovations in journalism; Video recording

Transitioning to a more sustainable society: unpacking the role of the learning–action nexus. - Moyer, Joanne M.; Sinclair, A. John; Quinn, Lisa (Transitioning to a more sustainable society: unpacking the role of the learning–action nexus., 2016)
In recent years, action on sustainability has been highly influential around the globe and many now recognize the importance of individual and social learning for inspiring action and achieving sustainability outcomes. Transformative learning theory has been criticized, however, for insufficient development of the link between learning and action. The purpose of this paper is to deepen our understanding of the learning–action cycle among adult learners in the sustainability context. We consider this through insights from two studies in Kenya and Canada, utilizing a qualitative approach. Both studies employed semi-structured interviews as their primary data collection instrument and used other tools such as focus groups and journal writing. Three broad nodes of social action—individual, interpersonal and collective—are identified and defined based on the data collected. Results show that while all three types of action were evident in the outcomes of participants, individual social action was the most common and collective social action was the least. Barriers to applying learning in action are also derived from the data, including situational, personal, interpersonal, sociocultural and environmental obstacles. Factors that assist in overcoming such barriers include community support networks and skills training.
Keywords: Acquisition of data; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Canada; Education; Educational Support Services; Educational quality standards; Higher education; Kenya; Social learning; Transformative learning

Transitioning to a more sustainable society: unpacking the role of the learning–action nexus. - Moyer, Joanne M.; Sinclair, A. John; Quinn, Lisa (Transitioning to a more sustainable society: unpacking the role of the learning–action nexus., 2016)
In recent years, action on sustainability has been highly influential around the globe and many now recognize the importance of individual and social learning for inspiring action and achieving sustainability outcomes. Transformative learning theory has been criticized, however, for insufficient development of the link between learning and action. The purpose of this paper is to deepen our understanding of the learning–action cycle among adult learners in the sustainability context. We consider this through insights from two studies in Kenya and Canada, utilizing a qualitative approach. Both studies employed semi-structured interviews as their primary data collection instrument and used other tools such as focus groups and journal writing. Three broad nodes of social action—individual, interpersonal and collective—are identified and defined based on the data collected. Results show that while all three types of action were evident in the outcomes of participants, individual social action was the most common and collective social action was the least. Barriers to applying learning in action are also derived from the data, including situational, personal, interpersonal, sociocultural and environmental obstacles. Factors that assist in overcoming such barriers include community support networks and skills training.
Keywords: Acquisition of data; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Canada; Education; Educational Support Services; Educational quality standards; Higher education; Kenya; Social learning; Transformative learning

Oral reading fluency and comprehension in Kenya: reading acquisition in a multilingual environment. - Piper, Benjamin; Schroeder, Leila; Trudell, Barbara (Oral reading fluency and comprehension in Kenya: reading acquisition in a multilingual environment., 2016)
Reading research has shown that variable relationships exist between measures of oral reading fluency and reading comprehension, depending on whether the language of the text is the reader's first language or an additional language. This paper explores this phenomenon, using reading assessment data for 2,000 Kenyan children in two or three languages: English, Kiswahili and one of two mother tongues, Dholuo or Gikuyu. The assessment data allowed us to compare reading and comprehension rates across languages. The data indicated that many children could read English words more easily than words in Kiswahili or their mother tongue; nevertheless, their reading comprehension was significantly lower in English than in Kiswahili, Dholuo or Gikuyu. The paper concludes that emphasising English reading fluency is an inefficient route to gaining reading comprehension skills because pupils are actually attaining minimal oral reading fluency in English and only modest comprehension skills in their own languages. The evidence also demonstrates that Kenya's national language policy of mother tongue as a medium of instruction in the early primary grades is consistently ignored in practice.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Children; Education; Educational Support Services; Elementary education; Fluency (Language learning); Kenya; Multilingual education; Reading (Elementary); Reading ability testing; Reading comprehension

Does Private Schooling Narrow Wealth Inequalities in Learning Outcomes? Evidence from East Africa - Alcott, Benjamin; Rose, Pauline (Does Private Schooling Narrow Wealth Inequalities in Learning Outcomes? Evidence from East Africa, 2016)
In many low- and lower-middle-income countries, private schools are often considered to offer better quality of education than government schools. Yet, there is a lack of evidence to date on their role in reducing inequalities: namely, the extent to which private schooling improves learning among the most disadvantaged children. Our paper uses household survey data from Kenya, Tanzania, and Uganda to identify whether any observed impact of private schooling on core literacy and numeracy skills differs according to children's household wealth. We demonstrate wealth gaps in access to private schooling, and use inferential models to account for observable differences between those who do and do not enrol in private schools. In Kenya and Uganda, we find that private schooling appears to improve the chances of children learning relative to their peers in government schools, but the chances of the poorest children learning in private schools remains low and is at best equivalent to the richest learning in government schools. In Tanzania, private schooling does not seem to improve poorer children's learning, whereas it does for richer children. These findings raise a caution about the extent to which private provision can help narrow learning inequalities.
Keywords: Africa; Children; Comparative Analysis; Cross Cultural Studies; Disadvantaged Youth; Economically Disadvantaged; Educational Policy; Elementary Education; Equal Education; Evidence; Foreign Countries; Global Education; Income; Kenya; Least Squares Statistics; Low Income; Middle Class; Multivariate Analysis; Outcomes of Education; Private Schools; Regression (Statistics); Surveys; Tanzania; Uganda

The Relationship between Kenyan Sign Language and English Literacy - Aura, Lillie Josephine; Venville, Grady; Marais, Ida (The Relationship between Kenyan Sign Language and English Literacy, 2016)
This paper presents results of an investigation into the relationship between Kenyan Sign Language (KSL) and English literacy skills. It is derived from research undertaken towards an MEd degree awarded by The University of Western Australia in 2011. The study employed a correlational survey strategy. Sixty upper primary deaf students from four residential schools for the hearing impaired participated in the tests that evaluated their KSL proficiency and English literacy skills. KSL skills were tested using an adapted American Sign Language Proficiency Assessment tool while the English literacy skills were evaluated using a combination of five selected sub-tests of the "Test of Reading Comprehension-Fourth Edition" ("TORC 4") and the "Test of Written Language-Fourth Edition" ("TOWL 4"). Additional data were collected from participants' audiograms and a questionnaire completed by parents. Data were analysed using the "Statistical Package for the Social Sciences" (SPSS) computer software package. A significant positive correlation was found between participants' proficiency in KSL and their English literacy scores. The results suggested KSL has a role to play in English literacy acquisition.
Keywords: Correlation; Deafness; Elementary School Students; English (Second Language); Foreign Countries; Kenya; Language Proficiency; Language Skills; Language Tests; Questionnaires; Scores; Sign Language; Special Schools; Statistical Analysis

MEASURING LEARNING OUTCOMES IN KENYA: CONTEXT AND PERSPECTIVES. - Ayiro, Laban P. (MEASURING LEARNING OUTCOMES IN KENYA: CONTEXT AND PERSPECTIVES., 2016)
The education system in Kenya is continually challenged to adapt and improve, in part because its mission has become far more ambitious than it once was due to the massive investment in education by successive governments over the last two decades. Today, most Kenyans expect schools to prepare all students to succeed in postsecondary education and to prosper in a complex, fast-changing global economy. To identify the most important measures for education and other issues and provide quality data on them to the country, there is a need for the ministry of education to establish a National Education Indicators framework. This criterion is hoped to enable policy makers and the public better assess the position and progress of the country across the education sector. The key task in developing education indicators will be to identify a clear and parsimonious set of measures and data that will be easy for non-specialists to understand but which will also do justice to the complexities of the ailing education system. These indicators will amplify the existing situation and will be drawn from a large, and sometimes conflicting, body of information about students, teachers and schools. The purpose of this study is to propose and urge the government to develop a national framework of indicators that will inform stakeholders on the performance of the education system, both at school and national level.
Keywords: Academic achievement research; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Education policy; Education research; Educational Support Services; Kenya; Other local, municipal and regional public administration; Other provincial and territorial public administration; Readiness for school research

Disadvantaged Girls in Kenyan Schools - di Marco, Alexia; Education Development Trust (United Kingdom) (Education Development Trust, 2016)
This research is related to Education Development Trust's Department for International Development-funded Girls' Education Challenge (GEC) programme in Kenya. Complementing the monitoring and evaluation data gathered for the programme, this research was funded by Education Development Trust to enrich and develop a deeper understanding of girls' experiences at school in Kenya. It explores aspects of school and schooling that affect the participation and learning of marginalised girls in the Arid and Semi-Arid Lands (ASALs) of Turkana and the slums of Nairobi. The report offers a detailed, qualitative analysis of the practices and experience of education of 128 girls across 16 primary schools in these two regions. It examines: (1) Why marginalised girls in ASALs and slums participate and learn better in some schools compared to others; (2) Why there might be a higher proportion of girls enrolled in some of these schools; and (3) How reform can be supported in other Kenyan schools to increase enrolment, achievement and the completion of basic education for girls. The study involved visiting a total of 16 schools (eight in Turkana and eight in the Nairobi slums) for two days each in term two of the 2014 school year. Over the course of the research the team met with 128 girls, 53 2 teachers, 14 heads and two deputies, observed 53 lessons and carried out 48 'out-of-class' observations. Findings are presented in two chapters. The first gives the findings from each data source and the second presents a cross-case thematic analysis. The key points are described in this report. This report suggests that schools should consider how they collect fees, build positive relationships between female pupils and teachers, and encourage active and professional leadership in order to build better learning environments in which girls are more likely to complete schooling and do well. Schools also need to continue to address quality issues and maximise learning time during the school day, and ensure that girls are not inadvertently excluded from additional learning opportunities offered outside the school day.
Keywords: Academic Achievement; Access to Education; Disadvantaged Youth; Disproportionate Representation; Economically Disadvantaged; Educational Change; Educational Environment; Elementary School Students; Enrollment; Fees; Females; Foreign Countries; Kenya; Low Income Students; Slums; Teacher Attendance; Teacher Student Relationship

A Cross-National Study of Implicit Theories of a Creative Person - Hopp, Manuel; Händel, Marion; Stoeger, Heidrun; Vialle, Wilma; Ziegler, Albert (A Cross-National Study of Implicit Theories of a Creative Person, 2016)
Implicit theories can influence learning behavior, the approaches individuals take to learning and performance situations, and the learning goals individuals set, as well as, indirectly, their accomplishments, intelligence, and creativity. For this cross-cultural study, Kenyan and German students were asked to draw a creative person and rate it on a number of attributes. The data indicated considerable differences among the implicit theories according to students' gender and nationality. Kenyan girls, in particular, frequently ascribed a gender to their prototypical creative person that differed from their own, whereas the gender of the prototypical creative people drawn by German students was more equally spread. The data offer evidence that implicit theories of a creative person are multifaceted. Kenyan students value diligence as an important attribute of a creative person. In addition, social variables were seen as important, followed by talents in languages and mathematics. By contrast, German students valued imagination and talent in artistic areas, followed by diligence and social components. Their lowest rated attributes for creativity were talents in the domains of languages, mathematics and technical areas. Future studies should further examine the influence of implicit theories on the learning behavior of gifted students.
Keywords: Art; Creativity; Cross Cultural Studies; Cultural Differences; Elementary School Students; Foreign Countries; Freehand Drawing; Gender Differences; Germany; Gifted; Imagination; Intelligence; Kenya; Language Skills; Learning Theories; Likert Scales; Mathematics Skills; Multivariate Analysis; Personality Traits; Questionnaires; Secondary School Students; Social Influences; Statistical Analysis; Stereotypes; Student Attitudes; Talent

The Relationship between Subsidized Free Day Secondary Education and Retention in Secondary Schools in Kenya - James, Asena Muganda; Simiyu, Aggrey Mukasa; Riechi, Andrew (The Relationship between Subsidized Free Day Secondary Education and Retention in Secondary Schools in Kenya, 2016)
A workforce that can adapt to the fast changing global dynamics is critical for sustainable growth and development. Secondary level segment in the education cycle of a Kenyan plays a key role in the development of this workforce and is important since it de-links one from elementary (primary) learning, provides a chance for one to complete the cycle of basic education and anchors as a springboard to either tertiary or higher learning. The study focused on the relationship between subsidized free day secondary education (SFDSE) and learners' retention in secondary schools. The specific objectives were to determine retention rates of students in secondary schools before and after the introduction of SFDSE by the government since the year 2008 and the adequacy of SFDSE funds in enhancing retention of learners in secondary schools in Bungoma County. The target population of the study comprised of all the 3,993 stakeholders in the education sector including the Educational Officers, Principals, B.O.G chairpersons, P.T.A chairpersons and Parents from each Sub County in Bungoma County in Kenya. Cross-sectional survey research and proportional stratified sampling were adopted to obtain a sample size of 340 respondents purposively for the study. Questionnaires and interview schedules were used to collect data from the respondents. Qualitative data collected was analyzed using content analysis while quantitative data using descriptive statistics. The results indicated SFDSE had increased enrollment and transition rates and reduced dropout rates of the learners at secondary level education level. The study recommended that due to the importance of SFDSE which had enhanced retention, the amount allocated per child should be increased and the government should also remove the extra burdens from the parents by removing extra charges. The information was useful to education planners, stakeholders and well wishers.
Keywords: Access to Education; Basic Skills; Case Studies; Content Analysis; Department Heads; Dropout Rate; Educational Finance; Enrollment; Foreign Countries; Graduation Rate; Interviews; Kenya; Parents; Principals; Questionnaires; Sample Size; Sampling; School Holding Power; Secondary Education; Stakeholders; Statistical Distributions; Statistics; Surveys; Transitional Programs

Multilevel Design of School Effectiveness Studies in Sub-Saharan Africa - Kelcey, Ben; Shen, Zuchao (Multilevel Design of School Effectiveness Studies in Sub-Saharan Africa, 2016)
School-based improvement programs represent a core strategy in improving education because they can leverage pre-existing social and organizational structures to promote coordinated and comprehensive change across multiple facets of schooling. School-based programs are generally designed to be implemented by intact schools/districts, frequently making it infeasible or atheoretical to assign students within the same school to different conditions while ensuring study validity. Rather, studies frequently assign intact schools/districts to treatment conditions to accommodate the multilevel structure of schooling and the theory of action underlying many school-based programs. In planning such studies, effective and efficient design requires plausible values of the variance partition coefficients and the variance explained by covariates during the design stage. Using representative samples of each country, we develop empirical estimates of design parameters within and across 15 countries that are intended to inform and facilitate the efficient design of multisite cluster-randomized studies of school improvement in sub-Saharan Africa.
Keywords: Africa; Botswana; Design; Educational Improvement; Educational Quality; Foreign Countries; Grade 6; Improvement Programs; Kenya; Lesotho; Malawi; Mathematics Achievement; Mathematics Instruction; Mauritius; Mozambique; Multivariate Analysis; Namibia; Outcomes of Education; Program Implementation; Randomized Controlled Trials; Reading Achievement; Reading Instruction; School Effectiveness; Seychelles; South Africa; Standardized Tests; Statistical Analysis; Student Surveys; Swaziland; Tanzania; Uganda; Zambia; Zimbabwe

Curriculum Implementation: Strategies for Improved Learning Outcomes in Primary Schools in Kenya - Kisirkoi, Florence Kanorio; Mse, Godfrey (Curriculum Implementation: Strategies for Improved Learning Outcomes in Primary Schools in Kenya, 2016)
Education in Kenya requires rethinking as the country faces the demands of educational and socio-economic transformation of the 21st century. One of the general objectives of primary education in Kenya states that primary education should provide the learner opportunities to acquire literacy, numeracy, creativity and communication skills. There is evidence from research reports that the objective has not been fully met. A number of learners go through the primary school course without acquiring the basic literacy skills which negates the focus of the country to develop a knowledge based economy. The purpose of this study was to find out the extent to which teachers used teaching learning resources and learner centred strategies in primary school classrooms. The methodology adopted was survey research design. A total of 490 primary school teachers from five counties were purposively sampled and a total of 402 teachers participated; out of the total, 70 were observed teaching and 332 filled in a questionnaire. Out of 35 TAC tutors selected, 27 participated. A total of 80% of the teachers observed teaching used teacher centred teaching learning approaches with little learner involvement. The majority, 61.4% of those who filled in the questionnaire, indicated that they used teacher centred teaching learning approaches. Only 1 (3.7%) was "good" in use of resources for teaching learning in class, the rest were poor or did not use resources. It was found that teaching and learning approaches employed in the classroom by most teachers was teacher centred and encouraged rote learning hence lacking in active student involvement in the learning process. It was recommended that there should be sustained school based teacher professional development activities specifically addressing pedagogy for improved curriculum implementation and ultimately improved learning outcomes.
Keywords: Curriculum Development; Curriculum Implementation; Educational Improvement; Educational Strategies; Elementary School Teachers; Foreign Countries; Kenya; Observation; Outcomes of Education; Questionnaires; Teacher Behavior; Teacher Student Relationship; Teaching Methods; Tutors

Being Untaught: How NGO Field Workers Empower Parents of Children with Disabilities in Dadaab - Krupar, Allyson (Being Untaught: How NGO Field Workers Empower Parents of Children with Disabilities in Dadaab, 2016)
Roughly 350,000 refugees, over 90% of them Somali, lived in five sprawling camps in Dadaab, Kenya in 2015. In the Dadaab refugee camps, families had unique experiences of disability, education, women's roles, and involvement with International Non-Governmental Organization (INGO) programming. INGOs provided a variety of basic services including education such as the program analyzed here for parents of children with disabilities. Many children with disabilities in the refugee camps faced social stigma and lacked access to education. This research draws on practices and literature in family literacy and parental involvement programming to explore how one NGO training sought to empower women learners to send their children with disabilities to school in Kambioos, the smallest and newest refugee camp in Dadaab. Using ethnographic methods, one training program involving parents and children was video-taped. The video was used as a cue to interview field workers about how the training empowered parents, particularly mothers. The study found that empowerment of women through training for parents of children with disabilities centered on parents' interaction with formal schools and engagement in their communities.
Keywords: Afro Asiatic Languages; Disabilities; Elementary School Students; Empowerment; Ethnography; Family Literacy; Feminism; Field Instruction; Field Studies; Foreign Countries; International Organizations; Interviews; Kenya; Nongovernmental Organizations; Notetaking; Parent Participation; Parent School Relationship; Parents; Refugees; Special Needs Students; Training; Video Technology

Being Untaught: How NGO Field Workers Empower Parents of Children with Disabilities in Dadaab - Krupar, Allyson (Being Untaught: How NGO Field Workers Empower Parents of Children with Disabilities in Dadaab, 2016)
Roughly 350,000 refugees, over 90% of them Somali, lived in five sprawling camps in Dadaab, Kenya in 2015. In the Dadaab refugee camps, families had unique experiences of disability, education, women's roles, and involvement with International Non-Governmental Organization (INGO) programming. INGOs provided a variety of basic services including education such as the program analyzed here for parents of children with disabilities. Many children with disabilities in the refugee camps faced social stigma and lacked access to education. This research draws on practices and literature in family literacy and parental involvement programming to explore how one NGO training sought to empower women learners to send their children with disabilities to school in Kambioos, the smallest and newest refugee camp in Dadaab. Using ethnographic methods, one training program involving parents and children was video-taped. The video was used as a cue to interview field workers about how the training empowered parents, particularly mothers. The study found that empowerment of women through training for parents of children with disabilities centered on parents' interaction with formal schools and engagement in their communities.
Keywords: Afro Asiatic Languages; Disabilities; Elementary School Students; Empowerment; Ethnography; Family Literacy; Feminism; Field Instruction; Field Studies; Foreign Countries; International Organizations; Interviews; Kenya; Nongovernmental Organizations; Notetaking; Parent Participation; Parent School Relationship; Parents; Refugees; Special Needs Students; Training; Video Technology

A Survey of Approaches Used in Teaching Reading in Early Childhood Classes in Dagoretti and Westlands Divisions, Nairobi County, Kenya - Marima, Esther Wairimu (A Survey of Approaches Used in Teaching Reading in Early Childhood Classes in Dagoretti and Westlands Divisions, Nairobi County, Kenya, 2016)
Reading proficiency has been identified as one of the most reliable indicators of whether a learner will attain the competence needed to achieve academic success and contribute actively to society. Research findings in Kenyan primary and secondary schools reveal inadequate reading skills among the students. There are different approaches in teaching of reading in early learning. The study sought to establish teachers' orientation in reading instructions in early childhood settings and adopted the descriptive research design using the survey method and observation technique. A sample of 10 primary schools from Dagoretti and 10 from Westlands Divisions in Nairobi County were studied. The study concludes that although most teachers indicated that they were confident, they also indicated that they were not well equipped with the relevant teaching methods. Majority of pre-unit teachers used phonics and others whole-word methods. Lack of reading materials and guidelines was the most cited challenge faced by early learning teachers. The study recommends clear policy guidelines on how to teach reading and compulsory in-service training for teachers on how to teach reading and create awareness on use of phonics and whole word approaches in teaching of reading.
Keywords: Best Practices; Classroom Observation Techniques; Early Childhood Education; Educational Practices; Educational Strategies; Elementary School Curriculum; Foreign Countries; Kenya; Preferences; Reading Instruction; Teacher Surveys; Teaching Methods

Transitioning to a More Sustainable Society: Unpacking the Role of the Learning-Action Nexus - Moyer, Joanne M.; Sinclair, A. John; Quinn, Lisa (Transitioning to a More Sustainable Society: Unpacking the Role of the Learning-Action Nexus, 2016)
In recent years, action on sustainability has been highly influential around the globe and many now recognize the importance of individual and social learning for inspiring action and achieving sustainability outcomes. Transformative learning theory has been criticized, however, for insufficient development of the link between learning and action. The purpose of this paper is to deepen our understanding of the learning-action cycle among adult learners in the sustainability context. We consider this through insights from two studies in Kenya and Canada, utilizing a qualitative approach. Both studies employed semi-structured interviews as their primary data collection instrument and used other tools such as focus groups and journal writing. Three broad nodes of social action--individual, interpersonal and collective--are identified and defined based on the data collected. Results show that while all three types of action were evident in the outcomes of participants, individual social action was the most common and collective social action was the least. Barriers to applying learning in action are also derived from the data, including situational, personal, interpersonal, sociocultural and environmental obstacles. Factors that assist in overcoming such barriers include community support networks and skills training.
Keywords: Active Learning; Adult Learning; Barriers; Canada; Case Studies; Cooperation; Focus Groups; Foreign Countries; Journal Writing; Kenya; Learning Processes; Qualitative Research; Religion; Semi Structured Interviews; Social Action; Sustainability; Transformative Learning

Moderated Effects of Risky Behavior on Academic Performance among Adolescent Girls Living in Urban Slums of Kenya - Ngware, Moses W.; Mahuro, Gerald M.; Hungi, Njora; Abuya, Benta; Nyariro, Milka P.; Mutisya, Maurice (Moderated Effects of Risky Behavior on Academic Performance among Adolescent Girls Living in Urban Slums of Kenya, 2016)
This paper examines effects of life-skills, mentoring, and counseling education intervention implemented among primary school attending girls aged between 10 and 19 years, living in Nairobi slums. We hypothesized that interaction between the intervention and aspiration, self-confidence and interest in schooling, mediates the impact of risky behavior on academic performance. This quasi-experimental study had two treatment arms of 538 girls and one comparison with 272 girls. The first treatment arm received life skills mentoring, after school support with homework, and parental counseling; the second treatment arm received a package similar to the first arm excluding parental counseling; while the comparison arm received nothing during the implementation period, but they got a secondary school fees subsidy at the end of the intervention. The analysis shows that the intervention had statistically significant effects on some aspects of risky behavior and the mediators. Results from a structural equation model show existence of strong moderated mediation effects of risky behavior on academic performance. The importance of the findings is in demonstrating how inner-character attributes could enhance learning outcomes, especially among adolescent girls in low-resourced environments.
Keywords: Academic Achievement; Adolescents; After School Programs; Aspiration; At Risk Students; Behavior Change; Community Leaders; Comparative Analysis; Counseling; Daily Living Skills; Females; Financial Support; Foreign Countries; Homework; Interaction; Intervention; Kenya (Nairobi); Likert Scales; Low Income Groups; Mentors; Parents; Preadolescents; Program Effectiveness; Questionnaires; Self Esteem; Slums; Structural Equation Models; Surveys; Tests

Home-Learning Practices in Kenya: Views of Parents and Education Officers - Nyatuka, Benard Omenge (Home-Learning Practices in Kenya: Views of Parents and Education Officers, 2016)
In order for children to acquire meaningful education, families are advised to participate in learning activities at home. Such activities range from monitoring homework, problem-solving to reading with children during leisure time. But home-learning was claimed to receive little attention from key stakeholders among primary schools in Kenya's Kakamega County. This study therefore, was meant to explore the home-learning practices in the sampled schools. A review of the literature relevant to home-learning as well as interviews were conducted. The interview participants, who were purposively selected, included twelve parents, thirteen Parent Teacher Association (PTA) chairpersons and ten District Quality Assurance and Standards Officers (DQASOs). Guided by interview schedules, semi-structured individual interviews were conducted. The findings were presented in a narrative format backed by verbatim quotations. The findings revealed gaps with respect to the home-learning practices in the county. On this basis, efforts could be combined towards strengthening home-learning so as to improve both children's academic achievement as well as behaviour.
Keywords: Administrator Attitudes; Family Environment; Family Involvement; Foreign Countries; Homework; Interviews; Kenya; Parent Associations; Parent Attitudes; Parent Role; Parent Teacher Cooperation; Parents as Teachers; Problem Solving; Qualitative Research; Reading; Teacher Associations; Teamwork

Home-Learning Practices in Kenya: Views of Parents and Education Officers - Nyatuka, Benard Omenge (Home-Learning Practices in Kenya: Views of Parents and Education Officers, 2016)
In order for children to acquire meaningful education, families are advised to participate in learning activities at home. Such activities range from monitoring homework, problem-solving to reading with children during leisure time. But home-learning was claimed to receive little attention from key stakeholders among primary schools in Kenya's Kakamega County. This study therefore, was meant to explore the home-learning practices in the sampled schools. A review of the literature relevant to home-learning as well as interviews were conducted. The interview participants, who were purposively selected, included twelve parents, thirteen Parent Teacher Association (PTA) chairpersons and ten District Quality Assurance and Standards Officers (DQASOs). Guided by interview schedules, semi-structured individual interviews were conducted. The findings were presented in a narrative format backed by verbatim quotations. The findings revealed gaps with respect to the home-learning practices in the county. On this basis, efforts could be combined towards strengthening home-learning so as to improve both children's academic achievement as well as behaviour.
Keywords: Administrator Attitudes; Family Environment; Family Involvement; Foreign Countries; Homework; Interviews; Kenya; Parent Associations; Parent Attitudes; Parent Role; Parent Teacher Cooperation; Parents as Teachers; Problem Solving; Qualitative Research; Reading; Teacher Associations; Teamwork

The Writing Skill in the Contemporary Society: The Kenyan Perspective - Okari, Florence Mokeira (The Writing Skill in the Contemporary Society: The Kenyan Perspective, 2016)
This paper is an overview of the writing skill in the lower levels of learning in the contemporary society. The following areas of writing are highlighted: the writing programme and its goals, the basic methodology for writing tasks, broad groups of writing skills, the teaching of the writing skills in pre-primary and primary schools where controlled and guided composition writing are seen as the main types of composition and lastly the punctuation, testing and marking of written tasks.
Keywords: Elementary School Students; Foreign Countries; Grading; Kenya; Preschool Education; Punctuation; Teaching Methods; Writing Instruction; Writing Skills; Writing Tests

The Writing Skill in the Contemporary Society: The Kenyan Perspective - Okari, Florence Mokeira (The Writing Skill in the Contemporary Society: The Kenyan Perspective, 2016)
This paper is an overview of the writing skill in the lower levels of learning in the contemporary society. The following areas of writing are highlighted: the writing programme and its goals, the basic methodology for writing tasks, broad groups of writing skills, the teaching of the writing skills in pre-primary and primary schools where controlled and guided composition writing are seen as the main types of composition and lastly the punctuation, testing and marking of written tasks.
Keywords: Elementary School Students; Foreign Countries; Grading; Kenya; Preschool Education; Punctuation; Teaching Methods; Writing Instruction; Writing Skills; Writing Tests

Multilingual Literacy Skill Development in Kenya: Results from Medium Scale Randomized Controlled Trials - Piper, Benjamin; Society for Research on Educational Effectiveness (SREE) (Society for Research on Educational Effectiveness, 2016)
If children do not learn how to read in the first few years of primary school, they at greater risk of dropping out. It is therefore crucial to identify and test interventions that have the potential of making a large impact, can be implemented quickly, and are affordable to be taken to scale by the Kenyan government. This paper presents the findings of three randomized controlled trials designed to improve student literacy outcomes in Kenya. Two of the studies have multiple data points, two assessments measure outcomes in two languages, and the other in four languages. Random selection and assignment methods were utilized to assign clusters of schools to treatment and control conditions in Kenya. The treatment groups varied, but in several of them, the interventions implemented a targeted literacy and numeracy instructional program with student books, teachers' guides, ongoing teacher professional development and instructional supervision. The longitudinal results suggest that literacy acquisition in Kenya follows an unexpected path, and that additional research is required to understand what intervention points are available to more rapidly improve outcomes.
Keywords: African Languages; Elementary School Students; English; Foreign Countries; Intervention; Kenya; Literacy; Longitudinal Studies; Multilingualism; Outcomes of Education; Program Effectiveness; Randomized Controlled Trials; Reading Achievement; Reading Comprehension; Reading Fluency; Skill Development; Slum Schools; Transfer of Training

The role of timing in assessing oral reading fluency and comprehension in Kenya. - Piper, Benjamin; Zuilkowski, Stephanie Simmons (The role of timing in assessing oral reading fluency and comprehension in Kenya., 2016)
Despite rapid growth in literacy-related programmes and evaluation in sub-Saharan Africa, little critical attention has been paid to the relevance of assumptions that underlie existing assessment methods. This study focuses on the issue of timing in the assessment of oral reading fluency, a critical component of successful reading (Chard, Vaughn, & Tyler, 2002; National Institute of Child Health and Human Development (NICHD), 2000; Pikulski & Chard, 2005). Within the context of the Primary Math and Reading Initiative, a randomized controlled trial of several instructional interventions in Kenya, timed and untimed Early Grade Reading Assessment (EGRA) oral reading fluency and reading comprehension tasks were administered to 4385 students in 95 government and 125 informal schools. Using the data from the EGRA – whose administration has expanded within sub-Saharan Africa recently – we found that students did not perform significantly better on the assessments when they had more time. This pattern largely held when we examined the effects disaggregated over student ability level. This suggests that timed assessments, which are faster to administer and logistically easier, are appropriate for use in Kenya.
Keywords: Administration of Public Health Programs; Children; Educational tests & measurements; Kenya; National Institute of Child Health & Human Development (U.S.); Oral reading; Primary education; Reading comprehension; School children

The Role of Timing in Assessing Oral Reading Fluency and Comprehension in Kenya - Piper, Benjamin; Zuilkowski, Stephanie Simmons (The Role of Timing in Assessing Oral Reading Fluency and Comprehension in Kenya, 2016)
Despite rapid growth in literacy-related programmes and evaluation in sub-Saharan Africa, little critical attention has been paid to the relevance of assumptions that underlie existing assessment methods. This study focuses on the issue of timing in the assessment of oral reading fluency, a critical component of successful reading (Chard, Vaughn, & Tyler, 2002; National Institute of Child Health and Human Development (NICHD), 2000; Pikulski & Chard, 2005). Within the context of the Primary Math and Reading Initiative, a randomized controlled trial of several instructional interventions in Kenya, timed and untimed Early Grade Reading Assessment (EGRA) oral reading fluency and reading comprehension tasks were administered to 4385 students in 95 government and 125 informal schools. Using the data from the EGRA--whose administration has expanded within sub-Saharan Africa recently--we found that students did not perform significantly better on the assessments when they had more time. This pattern largely held when we examined the effects disaggregated over student ability level. This suggests that timed assessments, which are faster to administer and logistically easier, are appropriate for use in Kenya.
Keywords: African Languages; Elementary School Students; English (Second Language); Foreign Countries; Institutional Characteristics; Intervention; Kenya; Language Tests; Literacy Education; Mathematics; Oral Reading; Reading Comprehension; Reading Fluency; Reading Tests; Role; Second Language Learning; Teaching Methods; Timed Tests

Using an Assessment of Early Mathematical Knowledge and Skills to Inform Policy and Practice: Examples from the Early Grade Mathematics Assessment - Platas, Linda M.; Ketterlin-Geller, Leanne R.; Sitabkhan, Yasmin (Using an Assessment of Early Mathematical Knowledge and Skills to Inform Policy and Practice: Examples from the Early Grade Mathematics Assessment, 2016)
This paper describes the development and intended uses of the Early Grades Mathematics Assessment (EGMA), which measures essential early mathematical knowledge and skills that are foundational to more sophisticated mathematical abilities, predictive of later achievement, and teachable. Administering the EGMA can provide policy makers, practitioners, and researchers with information about whether existing educational policies, curricular reforms or programs, and instructional interventions are supporting students in reaching important goals in mathematics. We highlight the utility of the EGMA results in three abbreviated illustrations of implementation studies in low-income countries. Recommendations for policy makers, practitioners, and researchers are provided.
Keywords: Achievement Tests; Comparative Analysis; Computation; Curriculum Based Assessment; Curriculum Development; Educational Policy; Educational Practices; Elementary Secondary Education; Foreign Countries; Ghana; International Assessment; International Education; Intervention; Kenya; Mathematical Aptitude; Mathematical Concepts; Mathematics; Mathematics Achievement; Mathematics Instruction; Mathematics Skills; Mathematics Tests; Numbers; Program Evaluation; Program for International Student Assessment; Science Achievement; Science Tests; Secondary School Students; Teaching Methods; Trends in International Mathematics and Science Study

School Based Factors Affecting Learning of Kenyan Sign Language in Primary Schools for Hearing Impaired in Embu and Isiolo Counties, Kenya - Rwaimba, Samuel Muthomi (School Based Factors Affecting Learning of Kenyan Sign Language in Primary Schools for Hearing Impaired in Embu and Isiolo Counties, Kenya, 2016)
This was a descriptive survey study design which sought to establish the school based factors that affect the learning of Kenyan Sign Language in primary schools for learners with hearing impairment in Embu and Isiolo counties in Kenya. The target population was all teachers teaching in primary schools for learners with hearing impairment in the two counties. From the selected schools, the study purposively and randomly sampled 2 head teachers and 8 teachers respectively. Interview guides were used to obtain data from the head teachers, questionnaires from teachers while observation schedules were used to obtain data on the general nature of the school environment. Quantitative data collected were analyzed using descriptive statistics and tabulated in frequency tables, bar charts and pie charts while qualitative data were analyzed and presented in narrative form. The study findings revealed that all the sampled respondents had training in special needs education but only 25% had training in KSL as a subject. Basing on the findings the researcher recommends that the TSC should post only teachers trained in KSL to teach KSL among learners with HI and that the universities should introduce KSL as a teaching subject alongside other subjects like Mathematics, English and Kiswahili.
Keywords: Deafness; Elementary School Students; Elementary School Teachers; Foreign Countries; Hearing Impairments; Interviews; Kenya; Naturalistic Observation; Observation; Principals; Qualitative Research; Questionnaires; Sign Language; Special Education; Statistical Analysis; Teacher Competencies

Learning Profiles: The Learning Crisis Is Not (Mostly) about Enrollment - Sandefur, Justin; Pritchett, Lant; Beatty, Amanda; Society for Research on Educational Effectiveness (SREE) (Society for Research on Educational Effectiveness, 2016)
The differential patterns of grade progression have direct implications for the calculation of learning profiles. Researchers measure learning in primary school using survey data on reading and math skills of a nationally representative, population-based sample of children in India, Pakistan, Kenya, Tanzania, and Uganda. Research demonstrates that learning levels among primary and secondary students in much of the developing world are extremely low and lag far behind the rich world, constituting what is referred to as a "learning crisis". Beyond demonstrating the learning crisis, this study seeks to estimate how much children learn--measured by reading and mathematics tests--as they progress through primary school. The main methodological challenge is that while the ASER and Uwezo surveys test children at all relevant ages and grade levels, they do not track the same children over time. Researchers are left to infer a longitudinal learning trajectory from cross-sectional data. Results from conducting some simple regressions of scores on grade level to determine how learning changes as children progress through school suggests similar or more rapid learning in East Africa than South Asia. However, the authors hypothesize that this finding may be biased by non-random dropout and grade repetition. This paper explores this hypothesis and discusses strategies for creating learning profiles with cross-sectional data. Tables are appended.
Keywords: Achievement Gap; Cognitive Style; Comparative Education; Data Analysis; Developing Nations; Dropouts; Foreign Countries; Grade Repetition; Hypothesis Testing; India; Kenya; Mathematics Skills; Mathematics Tests; Pakistan; Primary Education; Profiles; Progress Monitoring; Reading Skills; Reading Tests; Regression (Statistics); Scores; Student Evaluation; Student Surveys; Tanzania; Uganda

Imagination, Waldorf, and Critical Literacies: Possibilities for Transformative Education in Mainstream Schools - Shank, Monica (Imagination, Waldorf, and Critical Literacies: Possibilities for Transformative Education in Mainstream Schools, 2016)
In the face of transmission-oriented national curricula, this study explores possibilities for claiming space for imagination, as 'the most powerful and energetic of learning tools' (Egan 1986), in early childhood education in mainstream Kenyan schools. Drawing from Egan's work on imagination and Cummins' Nested Pedagogical Orientations framework, this study interrogates the indispensable role of imagination in transformative education, as well as its utility in the 'transmission' of the government curriculum. This study draws insights from an initiative integrating imaginative, Waldorf-inspired pedagogies into mainstream pre-primary and early primary classrooms to explore how imagination-based pedagogies, including storytelling, creative play, poems and verses, drawing and painting, can support the development of critical literacies in young children.
Keywords: Creativity; Critical Literacy; Early Childhood Education; Elementary School Students; Foreign Countries; Freehand Drawing; Imagination; Kenya; National Curriculum; Painting (Visual Arts); Partnerships in Education; Play; Poetry; Role; Story Telling; Teaching Methods; Transformative Learning

An Investigation into Implementation of ICT in Primary Schools, in Kenya, in the Light of Free Laptops at Primary One: A Case Study of Teachers Implementing ICT into Their Teaching Practice - Tonui, Betty; Kerich, E.; Koross, R. (An Investigation into Implementation of ICT in Primary Schools, in Kenya, in the Light of Free Laptops at Primary One: A Case Study of Teachers Implementing ICT into Their Teaching Practice, 2016)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley region of Kenya. It examines views in pertinent literature as well as teachers' perceptions of the benefits of integrating ICT into teaching-learning, the success factors and obstacles encountered in their endeavours to do this. Conclusions are drawn and suggestions made to address the challenges and improve on the use of ICT for teaching-learning in teaching institutions.
Keywords: Access to Computers; Barriers; Case Studies; Computer Literacy; Computer Uses in Education; Educational Technology; Elementary Schools; Foreign Countries; Kenya; Laptop Computers; Questionnaires; School Districts; Teacher Attitudes

Shaping the literacy agenda from a lifelong learning perspective - Hanemann,, Ulrike (https://unesdoc.unesco.org/ark:/48223/pf0000247779, 2016)

National Education Policy - Ministry of Education (Government of Malawi, 2016)

State of Postgraduate Research Training in Kenya - Mukhwana, Eusebius; Oure, Silas; Too, J; Some, D (2016)

Pervasiveness of data driven decision making in Kenyan Public Secondary schools - Ndirangu, Peter (International Journal of Science, Technology, Engineering and Management Research, 2016)
The major goal of every learning institution is deliver good quality education to its students just like every other organization aims to offer better quality products to it’s customers to gain a competitive advantage. Secondary schools are critical

Association between mothers' education and grade six children numeracy and literacy in Kenya. - Abuya, Benta A.; Mutisya, Maurice; Ngware, Moses (Association between mothers' education and grade six children numeracy and literacy in Kenya., 2015)
The objective of the paper is to re-examine the mother–child education achievement hypothesis, by re-examining the effect of mother's education, on math and literacy test scores of children in Kenya. Data come from the classroom Education Research Programme at the African Population and Health Research Centre which was collected between January and March 2012. Since pupils are nested within schools, we fitted a two-level random intercept model. Our findings show that mothers' and fathers' education has a positive and significant independent association with literacy and numeracy achievement. After interacting mothers' and fathers' education and controlling for school and pupil characteristics, we observed two significant findings: (1) mother's education remains statistically significant but is negatively associated with the pupil's score in both literacy and numeracy; and (2) the interaction of both parents' education is significant and positively associated with pupil scores in literacy and numeracy. This study underscores the importance of the complementarity between mothers' and fathers' education in order for children to acquire and learn literacy and numeracy in schools. In as much as mothers' education is important in the children's literacy and numeracy, the importance of fathers in children's literacy and numeracy cannot be ignored.
Keywords: Academic achievement; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Education of mothers; Educational Support Services; Kenya; Numeracy; Sixth grade (Education)

Integrating 'Ubunifu,' Informal Science, and Community Innovations in Science Classrooms in East Africa - Semali, Ladislaus M.; Hristova, Adelina; Owiny, Sylvia A. (Integrating 'Ubunifu,' Informal Science, and Community Innovations in Science Classrooms in East Africa, 2015)
This study examines the relationship between informal science and indigenous innovations in local communities in which students matured. The discussion considers methods for bridging the gap that exists between parents' understanding of informal science ("Ubunifu") and what students learn in secondary schools in Kenya, Tanzania, and Uganda. In an effort to reconcile the difference between students' lived experiences and Science, Technology, Engineering, and Mathematics (STEM) taught in classrooms, this study presents an experiential iSPACES instructional model as an example of curriculum integration in science classrooms. The culmination is presentation of lessons learned from history, including Africa's unique contributions to science, theory, and indigenous innovations, in the hope that these lessons can spur the development of new instructional practices, standards, curriculum materials, professional and community development, and dialogue among nations.
Keywords: African Culture; Community Development; Educational Innovation; Educational Practices; Experiential Learning; Foreign Countries; Indigenous Knowledge; Informal Education; Integrated Curriculum; Kenya; Models; Professional Development; STEM Education; Science Curriculum; Science Education; Tanzania; Uganda

The Singing Teacher's Role in Educating Children's Abilities, Sensibilities and Sensitivities. - Akuno, Emily Achieng' (The Singing Teacher's Role in Educating Children's Abilities, Sensibilities and Sensitivities., 2015)
In the Republic of Kenya, song is widely used to enhance the whole curriculum in lower primary classes. Song is used especially to aid recall and therefore teachers adapt tunes that children already know, inserting relevant words from the subject at hand. Despite this widespread practice, this form of singing in schools is not recognised by the same teachers as music training in the classroom, and so little, if any, effort is put into the actual music production. Teachers do not attend to the sound of the music, as the intention is to capture facts about various things, including the soil, the weather, numbers etc. and present them in a way that the young learners will quickly remember. This paper interrogates the process that 6–8-year-old children underwent as they moved from using song to learn facts (singing to learn), to developing multiple musical abilities and capacities (learning to sing), through participation in the Music for Literacy Development (MLD)1 project in selected schools in the Nyanza region of Kenya.
Keywords: Children; Effective teaching; Kenya; Music education; Music students; Musical ability in children; Primary education; Voice teachers

The Singing Teacher's Role in Educating Children's Abilities, Sensibilities and Sensitivities. - Akuno, Emily Achieng' (The Singing Teacher's Role in Educating Children's Abilities, Sensibilities and Sensitivities., 2015)
In the Republic of Kenya, song is widely used to enhance the whole curriculum in lower primary classes. Song is used especially to aid recall and therefore teachers adapt tunes that children already know, inserting relevant words from the subject at hand. Despite this widespread practice, this form of singing in schools is not recognised by the same teachers as music training in the classroom, and so little, if any, effort is put into the actual music production. Teachers do not attend to the sound of the music, as the intention is to capture facts about various things, including the soil, the weather, numbers etc. and present them in a way that the young learners will quickly remember. This paper interrogates the process that 6–8-year-old children underwent as they moved from using song to learn facts (singing to learn), to developing multiple musical abilities and capacities (learning to sing), through participation in the Music for Literacy Development (MLD)1 project in selected schools in the Nyanza region of Kenya.
Keywords: Children; Effective teaching; Kenya; Music education; Music students; Musical ability in children; Primary education; Voice teachers

The Singing Teacher's Role in Educating Children's Abilities, Sensibilities and Sensitivities - Akuno, Emily Achieng' (The Singing Teacher's Role in Educating Children's Abilities, Sensibilities and Sensitivities, 2015)
In the Republic of Kenya, song is widely used to enhance the whole curriculum in lower primary classes. Song is used especially to aid recall and therefore teachers adapt tunes that children already know, inserting relevant words from the subject at hand. Despite this widespread practice, this form of singing in schools is not recognised by the same teachers as music training in the classroom, and so little, if any, effort is put into the actual music production. Teachers do not attend to the sound of the music, as the intention is to capture facts about various things, including the soil, the weather, numbers etc. and present them in a way that the young learners will quickly remember. This paper interrogates the process that 6-8-year-old children underwent as they moved from using song to learn facts (singing to learn), to developing multiple musical abilities and capacities (learning to sing), through participation in the Music for Literacy Development (MLD) project in selected schools in the Nyanza region of Kenya.
Keywords: Cognitive Processes; Elementary School Students; Elementary School Teachers; Foreign Countries; Interdisciplinary Approach; Kenya; Literacy Education; Memory; Music Education; Singing; Teaching Methods

Music Education in Africa. - MURPHY, REGINA; FAUTLEY, MARTIN (Music Education in Africa., 2015)
Coming from Botswana, South Africa, Zimbabwe, Ghana and Kenya, the papers in this Special Issue on Music Education in Africa cannot portray a definitive story of music education in all 54 sovereign states in the Continent, but as a first step towards understanding what matters in this region of the world, the range of topics in this issue provides us with a focal point for dialogue.
Keywords: Action research in education; Administration of Education Programs; Africa; Education policy; Music education; Music literacy; Music teachers; Musical ability; Other local, municipal and regional public administration; Other provincial and territorial public administration; Primary education

The Effects of ABRACADABRA on Reading Outcomes: A Meta-Analysis of Applied Field Research - Abrami, Philip; Borohkovski, Eugene; Lysenko, Larysa (The Effects of ABRACADABRA on Reading Outcomes: A Meta-Analysis of Applied Field Research, 2015)
This meta-analysis summarizes research on the effects of a comprehensive, interactive web-based software (AXXX) on the development of reading competencies among kindergarteners and elementary students. Findings from seven randomized control trials and quasi-experimental studies undertaken in a variety of contexts across Canada, Australia and Kenya were reviewed and analyzed. Comparing the experimental groups that used AXXX to the control groups exposed to regular literacy instruction, the studies produced sixty-five independent effect sizes in six outcome categories, as defined by the National Reading Panel (NRP, 2000). The average effects were: (1) Phonics: g+ = 0.150, (k = 17, N = 914), p < 0.05; (2) Phonemic Awareness: g+ = 0.323, (k = 19, N = 1550), p < 0.001; (3) Reading Fluency: g+ = 0.082, (k = 5, N = 1522), p > 0.05 (ns); (4) Reading Comprehension: g+ = 0.087, (k = 5, N = 923), p > 0.05 (ns); •Listening Comprehension: g+ = 0.430, (k = 5, N = 846), p < 0.001; and (5) Vocabulary Knowledge: g+ = 0.031, (k = 14, N = 964), p > 0.05 (ns). The random effects model non-independent weighted overall average effect was g+ = 0.191 (k = 65). All but one of the average effect size distributions were homogeneous, suggesting that the observed effects are generally representative of the impact that AXXX may have on novice readers. The paper concludes with a discussion of AXXX classroom uses including implementation fidelity and offers the implications of the findings for future research and development.
Keywords: Achievement Tests; Australia; Canada; Comparative Analysis; Computer Assisted Instruction; Computer Software; Control Groups; Dynamic Indicators of Basic Early Literacy Skills (DIBELS); Effect Size; Elementary School Students; Emergent Literacy; Experimental Groups; Foreign Countries; Hong Kong; Kenya; Kindergarten; Listening Comprehension; Literature Reviews; Measures (Individuals); Meta Analysis; Phonemic Awareness; Phonics; Quasiexperimental Design; Randomized Controlled Trials; Reading Comprehension; Reading Fluency; Reading Instruction; Reading Tests; Technology Uses in Education; Vocabulary Skills; Wide Range Achievement Test; Woodcock Johnson Tests of Achievement; Young Children

The Effects of Abracadabra On Reading Outcomes: A Meta-analysis of Applied Field Research. - ABRAMI, PHILIP; BOROKHOVSKI, EUGENE; LYSENKO, LARYSA (The Effects of Abracadabra On Reading Outcomes: A Meta-analysis of Applied Field Research., 2015)
This meta-analysis summarizes research on the effects of a comprehensive, interactive web-based software ABRACADABRA (A Balanced Reading Approach for Canadians Designed to Achieve Best Results for All) on the development of reading competencies among kindergarteners and elementary students. Findings from nine randomized control trials and quasi-experimental studies undertaken in a variety of contexts across Canada, Australia and Kenya were reviewed and analyzed. Comparing the experimental groups that used ABRACADABRA to the control groups exposed to regular literacy instruction, the studies produced sixty-five independent effect sizes in six outcome categories, as defined by the National Reading Panel (NRP, 2000). The average Fixed Effect Model effect sizes were: • Phonics: g+ = 0.189, (k = 19, N= 1238),p < 01; • Phonemic Awareness: g+ = 0.324, (k = 20, N = 1753), p < .001; • Reading Fluency: g+ = 0.056, (k = 6,N= 1725), p > .05 (ns); • Reading Comprehension: g+ = 0.065, (k = 6,N = 1045), p > .05 (ns); • Listening Comprehension: g+ = 0.381, (k = 6, N = 968), p < .001; • Vocabulary Knowledge: g+ = 0.138, (k = 15, N= 1167),p<.05. The non-independent weighted overall average effects were g+ = 0.179 and g+ = 0.170 for the Random Effects and Fixed Effect Models, respectively (k = 73, p < .01). All but two of the average effect size distributions were homogeneous, suggesting that the observed effects are generally representative of the impact that ABRACADABRA may have on novice readers. The paper concludes with a discussion of ABRACADABRA classroom uses including implementation fidelity and offers the implications of the findings for future research and development.
Keywords: Interactive learning; Kindergarten children; Meta-analysis; Reading comprehension; Reading software; School children; Vocabulary education in elementary schools

Experiences of parents with the Reading to Learn approach: a randomised control trial initiative to improve literacy and numeracy in Kenya and Uganda. - Abuya, Benta A.; Oketch, Moses; Ngware, Moses W.; Mutisya, Maurice; K. Musyoka, Peter (Experiences of parents with the Reading to Learn approach: a randomised control trial initiative to improve literacy and numeracy in Kenya and Uganda., 2015)
Parental involvement in their children's schooling is in recognition that establishing the context in which a child attends school is important. Reading to Learn (RtL)was implemented in two districts of Kwale and Kinango in Kenya and of Amolatar and Dokolo in Uganda. This paper looks at parental involvement and their experiences with RtL. Data are obtained from survey responses at baseline and focus group discussions with parents at endline. Findings indicate that parents are key actors in literacy and numeracy of their children. The study underscores the role of parents and context in literacy activities and policy implementation.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Children; Education; Education policy; Educational Support Services; Forums; Kenya; Literacy; Numeracy; Other local, municipal and regional public administration; Other provincial and territorial public administration; Parent participation in education; Uganda

Impact of an educational intervention on breast cancer knowledge in western Kenya. - Kisuya, J.; Wachira, J.; Busakhala, N.; Naanyu, V.; Chite, A. F.; Omenge, O.; Otieno, G.; Keter, A.; Mwangi, A.; Inui, T. (Impact of an educational intervention on breast cancer knowledge in western Kenya., 2015)
Our objective was to assess the effectiveness of educational sessions that accompanied breast cancer screening events in three communities in western Kenya between October and November 2013. Five hundred and thirty-two women were recruited to complete a test of breast cancer-relevant knowledge and randomly allocated to 'pre-test' or 'post-test' groups that immediately preceded or followed participation in the educational sessions. The education was organized as a presentation by health professionals and focused mainly on causes of breast cancer, early and late cancer presentation signs, high-risk groups, screening methods to find early-stage breast cancer, self-breast exam procedures and treatment options for this disease. Participants were invited to ask questions and practice finding nodules in silicone breast models. The median age was 35 years (interquartile range: 28-45), and 86% had not undergone breast cancer screening previously. Many individual items in our test of knowledge showed statistically significant shifts to better-informed responses. When all items in the assessment questionnaire were scored as a 'test', on average there was a 2.80 point (95% CI: 2.38, 3.22) significant improvement in knowledge about breast cancer after the educational session. Our study provides evidence for the effectiveness of an educational strategy carefully tailored for women in these communities in Kenya.
Keywords: Adult education; Adults; Breast tumors; Confidence intervals; Data analysis software; Descriptive statistics; Early detection of cancer; Educational outcomes; Fisher exact test; Health education; Health literacy; Kenya; Marketing Research and Public Opinion Polling; Questionnaires; Research funding; Statistical correlation; Statistical sampling

Cameroon National Textbook Policy for a Quality Education - Ministry of Basic Education; Ministry of Secondary Education (World Bank Workshop on School Textbooks, 2015)

The Role of Classroom Resources and National Educational Context in Student Learning Gains: Comparing Botswana, Kenya, and South Africa - Carnoy, Martin; Ngware, Moses; Oketch, Moses (The Role of Classroom Resources and National Educational Context in Student Learning Gains: Comparing Botswana, Kenya, and South Africa, 2015)
We take an innovative approach to estimating student mathematics learning in the sixth grade of three African countries. The study reinforces the notion that beyond the quality of the teaching process in classrooms, national contextual factors are important in understanding the contribution that schooling makes to student performance. Our approach enhances more typical cross-sectional production function estimates in three ways: (1) to respond to critiques that production function estimates usually do not include classroom processes, we measure both teacher characteristics and teaching process variables and include them in the model; (2) to more clearly identify student learning with schooling processes, we estimate the gain in learning associated with a student's exposure to teaching characteristics and processes during the sixth-grade academic year in each country; and (3) to begin to address the issue of possible "national institutional factors" influencing student achievement, we use a comparative approach to approximate and initiate discussion of "country fixed effects.
Keywords: Academic Achievement; Achievement Gains; Achievement Tests; Botswana; Case Studies; Comparative Education; Correlation; Educational Quality; Educational Resources; Elementary School Students; Equations (Mathematics); Foreign Countries; Grade 6; Instructional Innovation; Kenya; Learning Processes; Low Income; Mathematics Achievement; Mathematics Instruction; Mathematics Teachers; Models; Outcomes of Education; Pretests Posttests; Questionnaires; Resource Allocation; Socioeconomic Background; South Africa; Statistical Analysis; Statistical Significance; Teacher Characteristics; Teacher Effectiveness; Teaching Methods

Porter's five competitive forces framework and other factors that influence the choice of response strategies adopted by public universities in Kenya. - Mathooko, Francis M.; Ogutu, Martin (Porter's five competitive forces framework and other factors that influence the choice of response strategies adopted by public universities in Kenya., 2015)
Purpose -- The purpose of this paper is to establish the extent to which Porter's five competitive forces (PFCF) framework, among other factors drive the choice of response strategies adopted by public universities in Kenya. Design/methodology/approach -- The study design was descriptive and utilized a cross-sectional survey of all the public universities in Kenya by administering a structured questionnaire to the top management team. Additional primary data were collected through observations and interviews. Secondary data were also collected in order to corroborate the data collected from the primary sources. Findings -- PFCF framework influenced the choice of response strategies adopted by the public universities "to a great extent", the most influence being the threat from new entrants. The influence of the choice of response strategies by PFCF framework was independent of the age and category of the universities. Pressure from stakeholders, changes in government policies and regulations, reforms in higher education, unethical response strategies by some universities and university location also influenced the choice of response strategies. Research limitations/implications -- The study collected data from the top management team only; however, other stakeholders could have given additional information not reported here. Further, the research only considered public universities and not all higher education institutions (HEIs) in Kenya, and was cross-sectional, hence generalization and application of the results over a long time, respectively, may be limited. Practical implications -- The value of this study lies in HEIs achieving a competitive advantage and shaping strategic policy direction in the face of changing environment and global commodification of higher education. Originality/value -- Current public universities in Kenya have adopted a business-like approach in their operations in view of changing environment and have adopted coping strategies. Therefore, understanding the factors that influence the choice of response strategies is important for improvement of quality, efficiency and effectiveness as well as in policy formulation and serve as a guide to strategic management.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Colleges, Universities, and Professional Schools; Education; Education policy; Educational Support Services; Educational quality; Kenya; Other local, municipal and regional public administration; Other provincial and territorial public administration; Public universities & colleges; School management teams; Universities & colleges

Porter's five competitive forces framework and other factors that influence the choice of response strategies adopted by public universities in Kenya. - Mathooko, Francis M.; Ogutu, Martin (Porter's five competitive forces framework and other factors that influence the choice of response strategies adopted by public universities in Kenya., 2015)
Purpose -- The purpose of this paper is to establish the extent to which Porter's five competitive forces (PFCF) framework, among other factors drive the choice of response strategies adopted by public universities in Kenya. Design/methodology/approach -- The study design was descriptive and utilized a cross-sectional survey of all the public universities in Kenya by administering a structured questionnaire to the top management team. Additional primary data were collected through observations and interviews. Secondary data were also collected in order to corroborate the data collected from the primary sources. Findings -- PFCF framework influenced the choice of response strategies adopted by the public universities "to a great extent", the most influence being the threat from new entrants. The influence of the choice of response strategies by PFCF framework was independent of the age and category of the universities. Pressure from stakeholders, changes in government policies and regulations, reforms in higher education, unethical response strategies by some universities and university location also influenced the choice of response strategies. Research limitations/implications -- The study collected data from the top management team only; however, other stakeholders could have given additional information not reported here. Further, the research only considered public universities and not all higher education institutions (HEIs) in Kenya, and was cross-sectional, hence generalization and application of the results over a long time, respectively, may be limited. Practical implications -- The value of this study lies in HEIs achieving a competitive advantage and shaping strategic policy direction in the face of changing environment and global commodification of higher education. Originality/value -- Current public universities in Kenya have adopted a business-like approach in their operations in view of changing environment and have adopted coping strategies. Therefore, understanding the factors that influence the choice of response strategies is important for improvement of quality, efficiency and effectiveness as well as in policy formulation and serve as a guide to strategic management.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Colleges, Universities, and Professional Schools; Education; Education policy; Educational Support Services; Educational quality; Kenya; Other local, municipal and regional public administration; Other provincial and territorial public administration; Public universities & colleges; School management teams; Universities & colleges

Quality of Teaching Mathematics and Learning Achievement Gains: Evidence from Primary Schools in Kenya - Ngware, Moses W.; Ciera, James; Musyoka, Peter K.; Oketch, Moses (Quality of Teaching Mathematics and Learning Achievement Gains: Evidence from Primary Schools in Kenya, 2015)
This paper examines the contribution of quality mathematics teaching to student achievement gains. Quality of mathematics teaching is assessed through teacher demonstration of the five strands of mathematical proficiency, the level of cognitive task demands, and teacher mathematical knowledge. Data is based on 1907 grade 6 students who sat for the same test twice over an interval of about 10 months. The students were drawn from a random selection of 72 low- and high-performing primary schools. Multi-level regression shows the effects of quality mathematics teaching at both individual and school levels, while controlling for other variables that influence achievement. Results show that students in low-performing schools gained more by 6% when mathematics instruction involved high-level cognitive task demands, with two thirds of all the lessons observed demonstrating the strands of mathematics proficiency during instruction. The implication to education is that quality of mathematics instruction is more critical in improving learning gains among low-performing students.
Keywords: Achievement Gains; Educational Quality; Elementary School Mathematics; Foreign Countries; Grade 6; Instructional Effectiveness; Kenya; Low Achievement; Mathematics Achievement; Mathematics Instruction; Mathematics Skills; Pedagogical Content Knowledge; Regression (Statistics)

Quality of Teaching Mathematics and Learning Achievement Gains: Evidence from Primary Schools in Kenya - Ngware, Moses W.; Ciera, James; Musyoka, Peter K.; Oketch, Moses (Quality of Teaching Mathematics and Learning Achievement Gains: Evidence from Primary Schools in Kenya, 2015)
This paper examines the contribution of quality mathematics teaching to student achievement gains. Quality of mathematics teaching is assessed through teacher demonstration of the five strands of mathematical proficiency, the level of cognitive task demands, and teacher mathematical knowledge. Data is based on 1907 grade 6 students who sat for the same test twice over an interval of about 10 months. The students were drawn from a random selection of 72 low- and high-performing primary schools. Multi-level regression shows the effects of quality mathematics teaching at both individual and school levels, while controlling for other variables that influence achievement. Results show that students in low-performing schools gained more by 6% when mathematics instruction involved high-level cognitive task demands, with two thirds of all the lessons observed demonstrating the strands of mathematics proficiency during instruction. The implication to education is that quality of mathematics instruction is more critical in improving learning gains among low-performing students.
Keywords: Achievement Gains; Educational Quality; Elementary School Mathematics; Foreign Countries; Grade 6; Instructional Effectiveness; Kenya; Low Achievement; Mathematics Achievement; Mathematics Instruction; Mathematics Skills; Pedagogical Content Knowledge; Regression (Statistics)

Quality of teaching mathematics and learning achievement gains: evidence from primary schools in Kenya. - Ngware, Moses; Ciera, James; Musyoka, Peter; Oketch, Moses (Quality of teaching mathematics and learning achievement gains: evidence from primary schools in Kenya., 2015)
This paper examines the contribution of quality mathematics teaching to student achievement gains. Quality of mathematics teaching is assessed through teacher demonstration of the five strands of mathematical proficiency, the level of cognitive task demands, and teacher mathematical knowledge. Data is based on 1907 grade 6 students who sat for the same test twice over an interval of about 10 months. The students were drawn from a random selection of 72 low- and high-performing primary schools. Multi-level regression shows the effects of quality mathematics teaching at both individual and school levels, while controlling for other variables that influence achievement. Results show that students in low-performing schools gained more by 6 % when mathematics instruction involved high-level cognitive task demands, with two thirds of all the lessons observed demonstrating the strands of mathematics proficiency during instruction. The implication to education is that quality of mathematics instruction is more critical in improving learning gains among low-performing students.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Cognitive styles in children; Education; Educational Support Services; Educational quality; Effective teaching; Elementary and Secondary Schools; Kenya; Mathematics education (Primary); Mathematics teachers; Primary education; Schools

An Overview of Educational Technology in Sub-Saharan Africa. - Blatnick-Gagne, Katy; Caverly, Gregg; Kreider, Rebecca (An Overview of Educational Technology in Sub-Saharan Africa., 2015)
As part of the second largest continent, many African countries have seen their economy improve in the past decade. Access and use of technology, especially in the field of education, have also seen upticks. The changes that are being influenced by educational technology can be seen in the shifts that are occurring in K-12, higher education, and corporations. The region of Sub-Saharan Africa that one resides defines how much technology is accessible and how reliable that technology will be. With the increased availability of cellular and satellite technology, some of the more rural areas are starting to have increased exposure to technology and are weaving it into the culture.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Corporations; Education; Educational Support Services; Educational technology; Higher education; Sub-Saharan Africa; Technology

Assessing reading fluency in Kenya: Oral or silent assessment? - Piper, Benjamin; Zuilkowski, Stephanie (Assessing reading fluency in Kenya: Oral or silent assessment?, 2015)
In recent years, the Education for All movement has focused more intensely on the quality of education, rather than simply provision. Many recent and current education quality interventions focus on literacy, which is the core skill required for further academic success. Despite this focus on the quality of literacy instruction in developing countries, little rigorous research has been conducted on critical issues of assessment. This analysis, which uses data from the Primary Math and Reading Initiative (PRIMR) in Kenya, aims to begin filling this gap by addressing a key assessment issue - should literacy assessments in Kenya be administered orally or silently? The authors compared second-grade students' scores on oral and silent reading tasks of the Early Grade Reading Assessment (EGRA) in Kiswahili and English, and found no statistically significant differences in either language. They did, however, find oral reading rates to be more strongly related to reading comprehension scores. Oral assessment has another benefit for programme evaluators - it allows for the collection of data on student errors, and therefore the calculation of words read correctly per minute, as opposed to simply words read per minute. The authors therefore recommend that, in Kenya and in similar contexts, student reading fluency be assessed via oral rather than silent assessment.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Education for All (Project); Educational Support Services; Educational quality; Fluency (Language learning); Kenya; Primary education; Reading ability testing; Second grade (Education)

Assessing Reading Fluency in Kenya: Oral or Silent Assessment? - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Assessing Reading Fluency in Kenya: Oral or Silent Assessment?, 2015)
In recent years, the Education for All movement has focused more intensely on the quality of education, rather than simply provision. Many recent and current education quality interventions focus on literacy, which is the core skill required for further academic success. Despite this focus on the quality of literacy instruction in developing countries, little rigorous research has been conducted on critical issues of assessment. This analysis, which uses data from the Primary Math and Reading Initiative (PRIMR) in Kenya, aims to begin filling this gap by addressing a key assessment issue--should literacy assessments in Kenya be administered orally or silently? The authors compared second-grade students' scores on oral and silent reading tasks of the Early Grade Reading Assessment (EGRA) in Kiswahili and English, and found no statistically significant differences in either language. They did, however, find oral reading rates to be more strongly related to reading comprehension scores. Oral assessment has another benefit for programme evaluators--it allows for the collection of data on student errors, and therefore the calculation of words read correctly per minute, as opposed to simply words read per minute. The authors therefore recommend that, in Kenya and in similar contexts, student reading fluency be assessed via oral rather than silent assessment.
Keywords: African Languages; Best Practices; Comparative Analysis; Comparative Testing; Early Reading; English (Second Language); English Curriculum; Error Analysis (Language); Evaluation Methods; Evaluation Research; Foreign Countries; Grade 2; Kenya; Literacy; Oral Reading; Reading Comprehension; Reading Fluency; Reading Tests; Scores; Silent Reading; Statistical Significance; Test Reliability; Test Validity

Assessing Reading Fluency in Kenya: Oral or Silent Assessment? - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Assessing Reading Fluency in Kenya: Oral or Silent Assessment?, 2015)
In recent years, the Education for All movement has focused more intensely on the quality of education, rather than simply provision. Many recent and current education quality interventions focus on literacy, which is the core skill required for further academic success. Despite this focus on the quality of literacy instruction in developing countries, little rigorous research has been conducted on critical issues of assessment. This analysis, which uses data from the Primary Math and Reading Initiative (PRIMR) in Kenya, aims to begin filling this gap by addressing a key assessment issue--should literacy assessments in Kenya be administered orally or silently? The authors compared second-grade students' scores on oral and silent reading tasks of the Early Grade Reading Assessment (EGRA) in Kiswahili and English, and found no statistically significant differences in either language. They did, however, find oral reading rates to be more strongly related to reading comprehension scores. Oral assessment has another benefit for programme evaluators--it allows for the collection of data on student errors, and therefore the calculation of words read correctly per minute, as opposed to simply words read per minute. The authors therefore recommend that, in Kenya and in similar contexts, student reading fluency be assessed via oral rather than silent assessment.
Keywords: African Languages; Best Practices; Comparative Analysis; Comparative Testing; Early Reading; English (Second Language); English Curriculum; Error Analysis (Language); Evaluation Methods; Evaluation Research; Foreign Countries; Grade 2; Kenya; Literacy; Oral Reading; Reading Comprehension; Reading Fluency; Reading Tests; Scores; Silent Reading; Statistical Significance; Test Reliability; Test Validity

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools. - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teacher coaching in Kenya: Examining instructional support in public and nonformal schools., 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Colleges, Universities, and Professional Schools; Education; Educational Support Services; Educational coaching; Educational outcomes; Kenya; Professional and Management Development Training; Professional education; Services for teachers; Teacher education

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya. - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya., 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
Keywords: Administration of Education Programs; Adults; All Other Miscellaneous Schools and Instruction; Best practices; Education; Educational Support Services; Educational innovations; Educational intervention; Elementary education; Kenya; Literacy; Teacher development; Teaching methods

A CALL TO LEARNING FOCUS IN EAST AFRICA: UWEZO'S MEASUREMENT OF LEARNING IN KENYA, TANZANIA AND UGANDA. - Mugo, John Kabutha; Ruto, Sara Jerop; Nakabugo, Mary Goretti; Mgalla, Zaida (Africa Education Review, 2015)
From the late 1990s, education in East Africa started to be appraised on the basis of enrolment. The universalisation of primary education that started in Uganda in 1997 – and peaked in Tanzania in 2002, as well as in Kenya in 2003 – was politicised as the epitome of education reform. Yet, alternative voices called for consideration of improving quality and looking beyond numbers. Uwezo, an East African initiative, aims at contributing to the focus on learning outcomes for children aged 6 to 16 years in Kenya, Tanzania and Uganda and operates on a theory of change that envisions large-scale learning assessment Mugo et al A call to learning focus in East Africa: Uwezo's measurement of learning as critical for strengthening the quality voice. Evidence is viewed as public utility in which citizens participate as both actors and consumers, and build bottom-up pressure to improve education quality. This article situates Uwezo's assessment in context of education reform in East Africa and presents succinct discussion of the evidence on learning competences generated between 2009 and 2012. The article concludes that learning outcomes are low and demands extensive efforts and multiple solutions – from both within and outside of the schooling systems – in changing the way schools work towards improved outcomes.
Keywords: Citizens; East Africa; Educational quality; Learning; Primary education

PRO-POOR PRIMR: IMPROVING EARLY LITERACY SKILLS FOR CHILDREN FROM LOW-INCOME FAMILIES IN KENYA. - Piper, Benjamin; Jepkemei, Evelyn; Kibukho, Kennedy (PRO-POOR PRIMR: IMPROVING EARLY LITERACY SKILLS FOR CHILDREN FROM LOW-INCOME FAMILIES IN KENYA., 2015)
Children from low-income families are at risk of learning outcome difficulties, particularly in literacy. Various studies link poor literacy results with performance later in primary and secondary school, and suggest that poverty, literacy skills and weak instructional methods combine to drastically limit the educational opportunities for many poor children. The Primary Math and Reading (PRIMR) Initiative was designed to support the learning gains of Class 1 and 2 pupils in seven counties across Kenya. PRIMR uses a randomised controlled trial design to establish the effect of its intervention and employs basic literacy measures to estimate causal effects. This study shows that PRIMR has been effective for children from low-income families and that early literacy interventions can mitigate socio-economic effects. The findings suggest that efforts to improve literacy outcomes for the poor should begin early in primary school. Strategies for ensuring that instruction is equitable across socio-economic status are advocated.
Keywords: Educational outcomes; Kenya; Learning; Parameter estimation; Poverty; Social status

Association between Mothers' Education and Grade Six Children Numeracy and Literacy in Kenya - Abuya, Benta A.; Mutisya, Maurice; Ngware, Moses (Association between Mothers' Education and Grade Six Children Numeracy and Literacy in Kenya, 2015)
The objective of the paper is to re-examine the mother-child education achievement hypothesis, by re-examining the effect of mother's education, on math and literacy test scores of children in Kenya. Data come from the classroom Education Research Programme at the African Population and Health Research Centre which was collected between January and March 2012. Since pupils are nested within schools, we fitted a two-level random intercept model. Our findings show that mothers' and fathers' education has a positive and significant independent association with literacy and numeracy achievement. After interacting mothers' and fathers' education and controlling for school and pupil characteristics, we observed two significant findings: (1) mother's education remains statistically significant but is negatively associated with the pupil's score in both literacy and numeracy; and (2) the interaction of both parents' education is significant and positively associated with pupil scores in literacy and numeracy. This study underscores the importance of the complementarity between mothers' and fathers' education in order for children to acquire and learn literacy and numeracy in schools. In as much as mothers' education is important in the children's literacy and numeracy, the importance of fathers in children's literacy and numeracy cannot be ignored.
Keywords: Educational Attainment; Elementary School Students; Fathers; Foreign Countries; Hypothesis Testing; Interviews; Kenya; Listening Skills; Literacy; Mathematics Achievement; Mathematics Tests; Models; Mothers; Numeracy; Parent Background; Parent Influence; Reading Achievement; Reading Tests; Regression (Statistics); Scores; Statistical Significance; Surveys; Urban Areas; Writing Tests

The Southern and Eastern Africa Consortium for Monitoring Educational Quality. Assessment GEMs No. 8 - Australian Council for Educational Research (Australian Council for Educational Research, 2015)
The Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ) carries out large-scale cross-national research studies in member countries in the Southern and Eastern Africa region. It aims to assess the conditions of schooling and performance levels of learners and teachers in the areas of literacy and numeracy. SACMEQ has completed three cross-national educational research projects so far at five- to six-year intervals (SACMEQ I, 1995-1999, SACMEQ II, 1998-2004 and SACMEQ III, 2005-2010). It is currently implementing the fourth project.
Keywords: Academic Achievement; Africa; Botswana; Cognitive Tests; Comparative Analysis; Educational Assessment; Educational Policy; Educational Quality; Educational Research; Elementary School Students; Elementary School Teachers; Foreign Countries; Grade 6; Kenya; Lesotho; Malawi; Mathematics Tests; Mauritius; Mozambique; Namibia; Principals; Questionnaires; Reading Tests; Researchers; Seychelles; South Africa; Student Surveys; Swaziland; Tanzania; Teacher Surveys; Uganda; Zambia; Zimbabwe

Problematizing early grade reading: Should the post-2015 agenda treasure what is measured? - Bartlett, Lesley; Dowd, Amy Jo; Jonason, Christine (Problematizing early grade reading: Should the post-2015 agenda treasure what is measured?, 2015)
Learning has emerged as a central theme within post-2015 debates. Central to these efforts have been a focus on literacy, and specifically early grade reading. This article identifies significant challenges raised by the current framing of emergent literacy in international educational development circles. Specifically, we examine how the Early Grade Reading Assessment, or EGRA, one very influential oral reading assessment tool based largely on an American reading assessment called DIBELs, has shaped the educational quality debate in the past decade and what important elements might be missing from this dominant view of reading. To do so, the article first considers the historical development of EGRA. We discuss concerns with the model of reading embedded in EGRA. We then examine the evidence, to date, of the impact of EGRA-informed interventions in places like Liberia, Malawi, and Kenya. The article concludes with implications for the future of literacy and international educational development, especially in light of discussions within the Learning Metrics Task Force to make early grade reading a central indicator of educational quality in the post-2015 agenda.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Educational quality; Kenya; Liberia; Malawi; Primary education; Reading (Primary); Reading ability testing

The Congruence between Teaching and Learning! Exploration of the Relationship between Preschool Teaching or Instructional Methods and Mathematics Performance in Lower Primary Schools in Kenya - Bonface, Kamau; Thinguri, Ruth W.; Koech, Peter K.; Ngaruiya, B. N. (The Congruence between Teaching and Learning! Exploration of the Relationship between Preschool Teaching or Instructional Methods and Mathematics Performance in Lower Primary Schools in Kenya, 2015)
The obstacles and difficulties hindering good performance in mathematics by Lower Primary school children seem to originate from inconsistence of instructional methods applied by teachers at the level. These methods don't agree with the ones initially applied by the children's teachers at preschool level. The effect of that could result in denying children a precious start to their future mathematics performance. There is a persistent indication that a discontinuity exists between pre-school learning methods and those in the lower primary schools. Teaching methods of the lower primary should be amended to make allowance for the stages of children's development and provide opportunities to encourage children to improve in their ability to understand and apply mathematical concepts. The purpose of this study was to explore the impact of the pre-school mathematics programme on mathematics performance in the Lower Primary Schools of the Makuyu Zone, Murang'a South District. The objectives of this study were: - to investigate continuity of teaching methods from pre-school to lower primary school; and to compare the relationship between performance in mathematics of children who had had pre-school education with those who had not. This study used a descriptive survey design to achieve the set objectives. Purposive (deliberately) sampling was used to select a sample population of 60 pupils; a lottery (random choice) method of sampling was applied to get 30 teachers, whereas 10 head teachers were chosen through appointment (deliberate) sampling. Open-ended questionnaires to collect data from the selected teachers and head teachers were applied; and for the children's responses, an interview schedule was employed. Observational checklists were also used where archival records were to apply. To test the construct validity and reliability of the research instruments, the researchers used 'split-half'. The researchers pilot-tested the research instruments with a small representative group from the population. The data collected was analysed, using frequency counts and percentages and presentations were done in tables, bar graphs, pie charts and histograms as necessary to present a better picture of the findings. This study recommends frequent mathematics methodology seminars, workshops/in-service training for lower primary mathematics' teachers which will guarantee effective methodological knowledge for teachers to teach mathematics effectively. Children's learning at play should be very much emphasized. To avoid discontinuity this study recommends that in the lower primary male and female teachers should alternate to make the learners get used to male teachers. More male teachers should also get to teach in the preschool level.
Keywords: Barriers; Check Lists; Elementary School Students; Foreign Countries; Gender Differences; Interviews; Kenya; Lesson Plans; Mathematics Achievement; Observation; Preschool Children; Preschool Education; Preschool Teachers; Primary Education; Principals; Progress Monitoring; Questionnaires; Student Attitudes; Surveys; Teacher Competencies; Teacher Education; Teaching Methods

Parental Involvement in Homework and Primary School Academic Performance in Kenya - Echaune, Manasi; Ndiku, Judah M.; Sang, Anthony (Parental Involvement in Homework and Primary School Academic Performance in Kenya, 2015)
The factors associated with students' academic performance may have been addressed but the impact of parental involvement continues to be a significant issue. Some schools in Kenya post poor results amid claims that parents are not supportive. This study examined the effect of parental involvement in homework on academic performance in public primary schools in Teso North Sub County, Busia-Kenya. The objectives were; to establish the types of homework assistance children get from parents, to ascertain the extent of parental involvement in homework and to examine the association between parental involvement in homework and school academic performance. All teachers, head teachers, pupils and parents in public primary schools were targeted. Thirty schools were sampled randomly from where 532 respondents (30 head teachers, 30 parents, 192 teachers and 280 pupils) were then sampled. Parents and head teachers were purposively sampled while teachers and pupils were proportionately sampled. A descriptive survey design was employed and data collected using questionnaires, semi-structured interviews schedules and document analysis. Quantitative data was analyzed using means, percentages and frequencies and qualitative data was reported directly. T-tests, Pearson moment correlation coefficient, and OLS regression coefficients were used to test hypotheses. The results indicate female parents were more willing to assist children in homework. Parents provided limited assistance in areas such as reading, writing and solving difficult sums. Parental involvement in homework positively correlated with school academic performance. The positive effect of parental involvement in homework disappeared when other variables were controlled for. It was concluded that since educational gains of parental involvement are noted and confirmed the significance of parents in educational processes. It was recommended that parents who don't assist children in homework should be sensitized to do so.
Keywords: Academic Achievement; Administrator Surveys; Elementary School Students; Foreign Countries; Helping Relationship; Homework; Kenya; Parent Participation; Parent Surveys; Public Schools; Questionnaires; Regression (Statistics); Semi Structured Interviews; Student Surveys; Teacher Surveys

E-Learn 2015: World Conference on E-Learning. Proceedings (Kona, Hawaii, October 19-22, 2015) - Ho, Curtis; Lin, Grace; Association for the Advancement of Computing in Education (Subregional Seminar for Eastern and Southern African Countries, 2015)
The Association for the Advancement of Computing in Education (AACE) is an international, non-profit educational organization. The Association's purpose is to advance the knowledge, theory, and quality of teaching and learning at all levels with information technology. "E-Learn 2015: World Conference on E-Learning" took place in Kona, Hawaii, October 19-22, 2015. This year's E-Learn conference again covered many different topics from the ever-present MOOCs to learner analytics to more rare topics such as personal innovativeness and semantic text theme generation. There are over 300 papers covering these topics in the proceedings. The following are the award papers presented at the conference: (1) Implementation of the Inverted Classroom Model for Theoretical Computer Science (Karsten Morisse); (2) Students' Conceptual Understanding of Leadership in a Global World: Learning via a Web-based Simulation of Political and Economic Development (Seungoh Paek and Daniel L. Hoffman); (3) Ready to Practice? Learning Skills Using Digital Simulated Patients (Nataly Martini, Ashwini Datt, Anuj Bhargava, and Craig Webster); (4) Mobile Learning for Students with and without Disabilities in K-12 Educational Setting (Jingrong Xie and James Basham); and (5) Using ADDIE to Design Online Courses via Hybrid Faculty Development (Michelle Read, Gwendolyn Morel, and Danyelle Hennington). [For the E-Learn 2014 proceedings, see ED602926.]
Keywords: Academically Gifted; Africa; Australia; Brazil; Computer Science; Computer Simulation; Concept Formation; Distance Education; Economic Development; Educational Games; Educational Technology; Electronic Learning; Elementary Secondary Education; Faculty Development; Finland; Foreign Countries; Handheld Devices; Higher Education; Instructional Design; Kenya; Large Group Instruction; Leadership; Online Courses; Patients; Pedagogical Content Knowledge; Political Issues; Preservice Teacher Education; Russia; Singapore; South Africa; South Korea; Students with Disabilities; Sweden; Taiwan; Technological Literacy; Technology Uses in Education; Telecommunications; Thailand; Training; United States; Video Games; Web Based Instruction

Advancing Higher Education with Mobile Learning Technologies: Cases, Trends, and Inquiry-Based Methods - Keengwe, Jar; Maxfield, Marian B. (IGI Global, 2015)
Rapid advancements in technology are creating new opportunities for educators to enhance their classroom techniques with digital learning resources. Once used solely outside of the classroom, smartphones, tablets, and e-readers are becoming common in many school settings. "Advancing Higher Education with Mobile Learning Technologies: Cases, Trends, and Inquiry-Based Methods" examines the implementation and success of mobile digital learning tools. With the inclusion of data on specific learning environments enhanced by ubiquitous educational technologies, this publication emphasizes the benefits of exploration and discovery in and out of the classroom. This book is an essential reference source for academicians, professionals, education researchers, school administrators, faculty, technology staff, and upper-level students interested in understanding the future of higher education. Following a foreword by Susan M. Powers, a preface by Jared Keengwe and Marian Maxfield, and an acknowledgment section by Jared Keengwe, chapters include: (1) Mobile Social Media as a Catalyst for Collaborative Curriculum Redesign (Thomas Cochrane, Matthew Guinibert, Clinton Simeti, Ross Brannigan, and Abhishek Kala); (2) Developing Faculty to Effectively Use Mobile Learning Technologies in Collegiate Classes: A Guide for Department Chairs (Richard E. Newman, Michael T. Miller, and Kenda S. Grover); (3) A Case Study of Developing Suitable Mobile Learning Technology for a Distance Learning Masters Programme (Tracey Dodman, Terese Bird, and David Hopkins); (4) Mobile Learning: Trends, Issues, and Challenges in Teaching and Learning (Chien Yu, Sang Joon Lee, and Carlos Ewing); (5) Teacher Development, Support, and Training with Mobile Technologies (Nance S. Wilson, Vassiliki I. Zygouris-Coe, and Victoria M. Cardullo); (6) Using Mobile Technology for Student Teaching Observations of Special Education Candidates (Josh Harrower, and Cathi Draper Rodríguez); (7) Mobile Technology in Higher Education: Patterns of Replication and Transferability (Meghan Morris Deyoe, Dianna L. Newman, and Jessica M. Lamendola); (8) Improving the Work Integrated Learning Experience through Mobile Technologies (Chris Dann, and Tony Richardson); (9) Opportunities and Challenges of Mobile Technologies in Higher Education Pedagogy in Africa: A Case Study (Frederick Kang'ethe Iraki); (10) Promoting Strategic Reading Using the iBooks Author Application (Natalia Auer); (11) Using Mobile Technologies to Co-Construct TPACK in Teacher Education (Cornelis de Groot, Jay Fogleman, and Diane Kern); (12) Reconceptualizing Learning Designs in Higher Education: Using Mobile Devices to Engage Students in Authentic Tasks (Nathaniel Ostashewski, Sonia Dickinson-Delaporte, and Romana Martin); (13) Framing Mobile Learning: Investigating the Framework for the Rationale Analysis of Mobile Education (Kim A. Hosler); (14) Integrating Mobile Technologies in Multicultural Multilingual Multimedia Projects (Melda N. Yildiz, and Kristine Scharaldi); and (15) Web 2.0 Technology Use by Students in Higher Education: A Case of Kenyan Universities (Rhoda K. Gitonga, and Catherine G. Murungi). A section about the contributors and an index are included.
Keywords: Africa; Case Studies; College Faculty; Curriculum Development; Distance Education; Educational Technology; Faculty Development; Foreign Countries; Handheld Devices; Higher Education; Instructional Design; Kenya; Learner Engagement; Masters Programs; Multicultural Education; Multimedia Instruction; Observation; Reading; Social Media; Special Education; Student Teaching; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; Web 2.0 Technologies

Congruence Between the Intended, Implemented, and Attained ICT Curricula in Sub-Saharan Africa. - Mereku, Damian Kofi; Mereku, Cosmas Worlanyo Kofi (Congruence Between the Intended, Implemented, and Attained ICT Curricula in Sub-Saharan Africa., 2015)
The PanAfrican Research Agenda on the Pedagogical Integration of information and communication technology (ICT; PanAf) research project was initiated in 2006 to support initiatives in African countries to integrate ICT into teaching and learning through the frequent collection and analysis of data on ICT usage. The article examines the congruence between the intended and implemented ICT curricula in six African countries (Cameroon, Côte d’Ivoire, Ghana, Kenya, Senegal, and South Africa) that participated in the study. Data obtained from the PanAf observatory (atwww.observatoiretic.org) on these countries’ use of ICT in education revealed that the national curricula documents (intended curricula) and teachers’ classroom practices (implemented curricula) both emphasize ICT as the subject of learning rather than as a means of learning.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; All Other Telecommunications; Communication Equipment Repair and Maintenance; Education; Educational Support Services; Information technology; Mathematical ability; Mathematical analysis; Mathematical programming; Other telecommunications; Telecommunication; Telecommunications Resellers

A Call to Learning Focus in East Africa: Uwezo's Measurement of Learning in Kenya, Tanzania and Uganda - Mugo, John Kabutha; Ruto, Sara Jerop; Nakabugo, Mary Goretti; Mgalla, Zaida (A Call to Learning Focus in East Africa: Uwezo's Measurement of Learning in Kenya, Tanzania and Uganda, 2015)
From the late 1990s, education in East Africa started to be appraised on the basis of enrolment. The universalisation of primary education that started in Uganda in 1997--and peaked in Tanzania in 2002, as well as in Kenya in 2003--was politicised as the epitome of education reform. Yet, alternative voices called for consideration of improving quality and looking beyond numbers. Uwezo, an East African initiative, aims at contributing to the focus on learning outcomes for children aged 6 to 16 years in Kenya, Tanzania and Uganda and operates on a theory of change that envisions large-scale learning assessment Mugo et al A call to learning focus in East Africa: Uwezo's measurement of learning as critical for strengthening the quality voice. Evidence is viewed as public utility in which citizens participate as both actors and consumers, and build bottom-up pressure to improve education quality. This article situates Uwezo's assessment in context of education reform in East Africa and presents succinct discussion of the evidence on learning competences generated between 2009 and 2012. The article concludes that learning outcomes are low and demands extensive efforts and multiple solutions--from both within and outside of the schooling systems--in changing the way schools work towards improved outcomes.
Keywords: Academic Achievement; Difficulty Level; Educational Assessment; Educational Change; Educational Development; Educational Indicators; Educational Quality; Foreign Countries; Grades (Scholastic); Institutional Characteristics; Kenya; Mothers; Outcomes of Education; Parent Background; Reading Achievement; Socioeconomic Status; Tanzania; Trend Analysis; Uganda

Difficulties Encountered by Students in the Learning and Usage of Mathematical Terminology: A Critical Literature Review - Mulwa, Ednah Chebet (Difficulties Encountered by Students in the Learning and Usage of Mathematical Terminology: A Critical Literature Review, 2015)
This study sought to review literature pertinent to difficulties encountered by students in the learning and usage of mathematical terminology. The need to carry out this study arose from the concern by the Kenya National Examinations Council, and the general public, over the poor annual results in mathematics. Therefore, the objective of this study was to investigate the extent to which the meanings of some mathematical terms are understood and/or confused by students for whom English is a second language. The basis of this study was the constructivist theory by J. Bruner and the cognitive flexibility theory of R. Spiro, P. Heltovitch and R. Coulson which advocates for teaching learners to construct the meanings of mathematical terms. This study's objectives were achieved through the use of document analysis. Data analysis involved document review. The findings of this study showed that students have difficulties in using mathematical terms and their related concepts. Possible ways of teaching these terms so as to generate more meaning to the learners were also suggested. It is hoped that this will assist mathematics teachers, curriculum planners and textbook authors to counter the poor performance in the subject in Kenya.
Keywords: Arithmetic; Change Strategies; Content Analysis; Elementary School Students; English (Second Language); Foreign Countries; Fractions; Geometric Concepts; Kenya; Language Role; Literature Reviews; Mathematical Aptitude; Mathematical Concepts; Mathematics Curriculum; Misconceptions; Number Concepts; Textbook Content; Textbook Evaluation; Vocabulary

Relative Contribution of Different Levels of Parental Involvement to Primary School Readiness in Preschool Pupils in Nairobi County - Mungai, David N. (Relative Contribution of Different Levels of Parental Involvement to Primary School Readiness in Preschool Pupils in Nairobi County, 2015)
Recent developments have led to a lot of emphasis being placed on early childhood education. Massive growth has also occurred in this segment of the education sector. Emphasis continues to be placed not just on growth but also on quality of the educational experiences that children are exposed to. In Kenya reports continue to emerge of pupils in primary school who lack numeracy and literacy competencies expected at their level. This inevitably shines the spotlight on the quality of educational experiences at the preschool level, which lays the foundation for all future learning and later success in school. One of the parameters of quality is parental involvement. In Kenya this parameter happens to be amongst the least understood. This paper sought to shed some light on the contribution of this aspect of quality to primary school readiness in preschool pupils in Nairobi. Parental involvement at six levels of involvement was measured for a sample of 150 parents of preschool pupils, while primary school readiness was assessed for a sample of 156 pupils. The results indicate that four of the six levels of parental involvement have a positive correlation to primary school readiness, while two are negatively correlated. The researcher recommends that schools and educators explore ways of creating and enhancing parental involvement so as to tap into the associated and recognized benefits of such cooperation.
Keywords: Cooperation; Correlation; Decision Making; Early Childhood Education; Elementary Education; Family Involvement; Foreign Countries; Kenya; Multiple Regression Analysis; Parent Participation; Parent Role; Preschool Children; Preschool Education; Rating Scales; School Readiness; Statistical Analysis; Surveys

Relative Contribution of Different Levels of Parental Involvement to Primary School Readiness in Preschool Pupils in Nairobi County - Mungai, David N. (Relative Contribution of Different Levels of Parental Involvement to Primary School Readiness in Preschool Pupils in Nairobi County, 2015)
Recent developments have led to a lot of emphasis being placed on early childhood education. Massive growth has also occurred in this segment of the education sector. Emphasis continues to be placed not just on growth but also on quality of the educational experiences that children are exposed to. In Kenya reports continue to emerge of pupils in primary school who lack numeracy and literacy competencies expected at their level. This inevitably shines the spotlight on the quality of educational experiences at the preschool level, which lays the foundation for all future learning and later success in school. One of the parameters of quality is parental involvement. In Kenya this parameter happens to be amongst the least understood. This paper sought to shed some light on the contribution of this aspect of quality to primary school readiness in preschool pupils in Nairobi. Parental involvement at six levels of involvement was measured for a sample of 150 parents of preschool pupils, while primary school readiness was assessed for a sample of 156 pupils. The results indicate that four of the six levels of parental involvement have a positive correlation to primary school readiness, while two are negatively correlated. The researcher recommends that schools and educators explore ways of creating and enhancing parental involvement so as to tap into the associated and recognized benefits of such cooperation.
Keywords: Cooperation; Correlation; Decision Making; Early Childhood Education; Elementary Education; Family Involvement; Foreign Countries; Kenya; Multiple Regression Analysis; Parent Participation; Parent Role; Preschool Children; Preschool Education; Rating Scales; School Readiness; Statistical Analysis; Surveys

Randomized Impact Evaluation of Education Interventions: Experiences and Lessons from a Reading to Learn Intervention in East Africa - Ngware, Moses Waithanji; Abuya, Benta; Oketch, Moses; Admassu, Kassahun; Mutisya, Maurice; Musyoka, Peter (Randomized Impact Evaluation of Education Interventions: Experiences and Lessons from a Reading to Learn Intervention in East Africa, 2015)
This paper presents the experiences and lessons learnt during the design and implementation of the randomized impact evaluation (IE) of a reading to learn (RtL) intervention in early primary grades. The study was to assess the impact of RtL on literacy and numeracy among pupils in low-performing districts in East Africa. The intervention was designed in a way that in each country one district implemented an intervention package that included teacher training, and teaching and learning materials; while the other district implemented this same package with an additional parental involvement component. Baseline data were collected in mid-2009 in Grades 1 and 2, and in 2010 for the incoming Grade 1. The endline data were collected in mid-2011. A total of 119 treatments and 110 control schools participated in the study. The randomized design provided an opportunity to attribute causality and also qualitatively establish pathways through which the intervention impacted on learning. The paper provides lessons learnt and demonstrates how the challenges faced during the evaluation were addressed. Additionally, the paper shows how IE was utilized to provide robust evidence of what works thus enabling policy-makers to make decisions on sustainability and scale-up of education interventions.
Keywords: Cost Effectiveness; Elementary School Students; Foreign Countries; Grade 1; Grade 2; Grade 3; Instructional Effectiveness; Intervention; Kenya; Literacy; Numeracy; Outcome Measures; Reading Instruction; Statistical Analysis; Uganda

Assessing the Influence of the PTTC Principal's Competency in ICT on the Teachers' Integration of ICT in Teaching Science in PTTCs in Nyanza Region, Kenya - Omwenga, Ezekiel; Nyabero, Charles; Okioma, Lazarous (Assessing the Influence of the PTTC Principal's Competency in ICT on the Teachers' Integration of ICT in Teaching Science in PTTCs in Nyanza Region, Kenya, 2015)
The study was conducted to assess the influence of Primary Teacher Training College (PTTC) principal's competency in ICT on the teacher's integration of ICT in teaching science in PTTC's in Nyanza region in Kenya. The one research question and one research hypothesis guided the study. The population comprised of 21 principals and 159 tutors. Data from the college principals and tutors was collected by use of interview schedule and a questionnaire. Cronbach alpha reliability computation was done to determine the overall reliability of the instrument. Cronbach alpha coefficient of 0.90 and higher was considered as reliable. The mean, standard deviation and Pearson correlation coefficient was used to analyze the data collected and the hypothesis tested at 0.01 alpha level. The results from the data indicated that the Principal who is competent in Information Communication Technology (ICT) favored the tutor's ICT integration in teaching science. Results of the hypothesis testing further revealed that there was a significant liner relationship between the principal's competency in ICT and teacher's integration of ICT in the teaching of science in PTTC's. Based on the findings of the study it was recommended that the Kenya government should make it a priority to develop a policy to guide leaders in ICT integration, in teaching science, and Teacher's Service Commission, Kenya Institute of Curriculum Development, Kenya Education Staff Institute and Ministry of Education and Science Technology should develop packages in ICT integration in teaching science for in servicing Principals prior to appointment.
Keywords: Administrator Qualifications; Administrator Surveys; Competence; Correlation; Elementary School Science; Foreign Countries; Influences; Interviews; Kenya; Leadership Role; Principals; Questionnaires; Schools of Education; Teacher Educators; Teacher Surveys; Technological Literacy; Technology Integration; Technology Uses in Education

Assessing the Influence of the PTTC Principal's Competency in ICT on the Teachers' Integration of ICT in Teaching Science in PTTCs in Nyanza Region, Kenya - Omwenga, Ezekiel; Nyabero, Charles; Okioma, Lazarous (Assessing the Influence of the PTTC Principal's Competency in ICT on the Teachers' Integration of ICT in Teaching Science in PTTCs in Nyanza Region, Kenya, 2015)
The study was conducted to assess the influence of Primary Teacher Training College (PTTC) principal's competency in ICT on the teacher's integration of ICT in teaching science in PTTC's in Nyanza region in Kenya. The one research question and one research hypothesis guided the study. The population comprised of 21 principals and 159 tutors. Data from the college principals and tutors was collected by use of interview schedule and a questionnaire. Cronbach alpha reliability computation was done to determine the overall reliability of the instrument. Cronbach alpha coefficient of 0.90 and higher was considered as reliable. The mean, standard deviation and Pearson correlation coefficient was used to analyze the data collected and the hypothesis tested at 0.01 alpha level. The results from the data indicated that the Principal who is competent in Information Communication Technology (ICT) favored the tutor's ICT integration in teaching science. Results of the hypothesis testing further revealed that there was a significant liner relationship between the principal's competency in ICT and teacher's integration of ICT in the teaching of science in PTTC's. Based on the findings of the study it was recommended that the Kenya government should make it a priority to develop a policy to guide leaders in ICT integration, in teaching science, and Teacher's Service Commission, Kenya Institute of Curriculum Development, Kenya Education Staff Institute and Ministry of Education and Science Technology should develop packages in ICT integration in teaching science for in servicing Principals prior to appointment.
Keywords: Administrator Qualifications; Administrator Surveys; Competence; Correlation; Elementary School Science; Foreign Countries; Influences; Interviews; Kenya; Leadership Role; Principals; Questionnaires; Schools of Education; Teacher Educators; Teacher Surveys; Technological Literacy; Technology Integration; Technology Uses in Education

Reading Skill Transfer across Languages: Outcomes from Longitudinal Bilingual Randomized Control Trials in Kenya and Haiti - Piper, Benjamin; Bulat, Jennae; Johnston, Andrew; Society for Research on Educational Effectiveness (SREE) (Society for Research on Educational Effectiveness, 2015)
If children do not learn how to read in the first few years of primary school, they will struggle to complete the cycle, and are at greater risk of dropping out. It is therefore crucial to identify and test interventions that have the potential of making a large impact, can be implemented quickly, and are affordable to be taken to scale. This is the goal of the PRIMR Initiative in Kenya and the ToTAL program in Haiti--to test various options for improving learning outcomes and instruction in primary schools, using a randomized controlled design. Due to high student-teacher ratios, limited teacher training, and lack of sufficient text materials, reading outcomes for students attending Kenyan and Haitian primary schools are generally poor. There is international focus on improving literacy, including through bilateral donors such as USAID and DFID, in Kenya and Haiti. However, there is limited knowledge about how reading skills are acquired in multilingual environments such as in Sub-Saharan Africa or the Caribbean. This paper presents the findings of a longitudinal tracer study evaluating student literacy outcomes in Kenya over two years, three data collection points, and across two languages. Random selection and assignment methods were utilized to assign clusters of schools to a treatment and a control condition. The treatment group implemented a targeted literacy and numeracy instructional program. This paper also presents the findings of a two-year randomized control trial in Haiti evaluating the efficacy of a literacy curriculum for Haitian Creole and French. Both interventions included student books, teachers' guides, and ongoing teacher professional development and supervision. Analysis shows that PRIMR had a positive impact on the literacy outcomes of interest, including but not limited to letter sound identification fluency, oral reading fluency, the percentage of pupils who read at the MOE's benchmark, and reading comprehension, although not on all combinations of language, grade, and school type. The longitudinal analysis is able to determine how the language skills interact over time and across languages, and suggests that in some skills, pupils are transferring literacy skills from English to Kiswahili. This is unexpected based on the Western literature, which generally suggests language transfer in the other direction. Analysis similarly shows that ToTAL has a positive impact on key foundational skills of initial sound identification and letter sound identification, although not on all combinations of language and grade. Patterns suggest that instruction in the mother tongue of Haitian Creole led to gains in French on skills that were not explicitly taught. This research shows that teachers can be sensitive to in-service teacher professional development (ITPD) if that ITPD is closely linked to the books and lesson plans used in schools, and if teachers are observed and supported frequently.
Keywords: African Languages; Bilingual Education; Comparative Analysis; Control Groups; Creoles; Curriculum Design; Elementary School Students; Elementary School Teachers; Elementary Schools; English (Second Language); Experimental Groups; Faculty Development; Foreign Countries; French; Haiti; Intervention; Kenya; Multilingualism; Oral Reading; Phonological Awareness; Randomized Controlled Trials; Reading Achievement; Reading Comprehension; Reading Fluency; Reading Instruction; Reading Skills; Supervision; Teacher Education; Teacher Student Ratio; Teaching Guides; Textbooks

Pro-Poor PRIMR: Improving Early Literacy Skills for Children from Low-Income Families in Kenya - Piper, Benjamin; Jepkemei, Evelyn; Kibukho, Kennedy (Pro-Poor PRIMR: Improving Early Literacy Skills for Children from Low-Income Families in Kenya, 2015)
Children from low-income families are at risk of learning outcome difficulties, particularly in literacy. Various studies link poor literacy results with performance later in primary and secondary school, and suggest that poverty, literacy skills and weak instructional methods combine to drastically limit the educational opportunities for many poor children. The Primary Math and Reading (PRIMR) Initiative was designed to support the learning gains of Class 1 and 2 pupils in seven counties across Kenya. PRIMR uses a randomised controlled trial design to establish the effect of its intervention and employs basic literacy measures to estimate causal effects. This study shows that PRIMR has been effective for children from low-income families and that early literacy interventions can mitigate socio-economic effects. The findings suggest that efforts to improve literacy outcomes for the poor should begin early in primary school. Strategies for ensuring that instruction is equitable across socio-economic status are advocated.
Keywords: Achievement Gains; Causal Models; Control Groups; Early Intervention; Early Reading; Educational Improvement; Effect Size; Emergent Literacy; Experimental Groups; Foreign Countries; Grade 1; Grade 2; Kenya; Low Income Students; Oral Reading; Poverty; Randomized Controlled Trials; Reading Comprehension; Reading Fluency; Reading Tests; Regression (Statistics); School Effectiveness; Skill Development; Socioeconomic Status

Relative Contributions of Caregivers' Level of Education, Role Definition and Average Household Income to Caregiver Involvement in Children's Emergent Reading - Wambiri, Gladwell N.; Ndani, Mary N. (Relative Contributions of Caregivers' Level of Education, Role Definition and Average Household Income to Caregiver Involvement in Children's Emergent Reading, 2015)
Recent studies have consistently reported low reading achievement levels among primary school children in Kenya. Reading is a very critical component of children's development. Many aspects of learning at school revolve around this skill. Being the media via which other subjects are taught and learnt, reading is very significant and could contribute to failure in school. Reading is not only a school agenda. Children also acquire early reading skills through specific experiences at home that require support of other adults besides teachers. Parent involvement in children's early reading development has been found to play a very critical role in the child's later reading success. Parents who take an active role in children's reading foster children's lifelong passion for reading, which in turn leads to improved children's performance in learning at school. However, the majority of the parents do not perceive themselves as crucial partners in children's emergent reading development. This paper is based on a study that compared the relative contributions of the parents' level of education, parents' role definition and the average household income, to parents' involvement in children's emergent reading development. The authors argue that although these three factors positively correlate with parents' involvement in children's reading development, parents' perceptions about their role in children's reading development is the most important predictor of their involvement in terms of direct and indirect behaviours and strategies with children around print. Interventions to improve reading achievement levels need to address parent involvement in children's reading. Such interventions should place priority in helping parents to correctly define their role in this important aspect of children's development.
Keywords: Correlation; Early Childhood Education; Educational Attainment; Elementary School Students; Emergent Literacy; Family Income; Foreign Countries; Kenya; Low Achievement; Parent Attitudes; Parent Background; Parent Participation; Parent Role; Predictor Variables; Questionnaires; Reading Achievement; Reading Instruction; Reading Skills; Teaching Methods; Young Children

National Plan of Action for Children in Kenya - Republic of Kenya (2015)

The Basic Education Regulations - Republic of Kenya (2015)

‘No One Should Destroy the Forest': Using photo-based vignette interviews to understand Kenyan teachers' views of the environment. - Quigley, Cassie F.; Miller, Zachary D.; Dogbey, James; Che, S. Megan; Hallo, Jeffrey (‘No One Should Destroy the Forest': Using photo-based vignette interviews to understand Kenyan teachers' views of the environment., 2014)
In the midst of the current environmental crisis, scientists, academics, authors, and politicians worldwide are urging citizens to create sustainable communities. However, there is little capability to build a sustainable society without an informed, active, and engaged populous. This requires more than just environmentally knowledgeable citizens. It requires a society that understands the principles of the environment and can also exemplify them in daily life. In order to create a more environmentally literate world, there has been a push for environmental education integrated into schools. This qualitative study sought to examine Kenyan teachers’ perspectives on the human–nature interaction by conducting vignette focus-group interviews. It is a subject not widely explored but vital for conservation not only in this area, but also other areas that seek to have an ecological informed populous. The vignettes were created using photographs and explanations of the photographs that the participants collected and emailed to the authors. For the focus-group vignette interviews, there were a total of 55 participants (30 females and 25 males). After InVivo analysis, we had 6 codes (resentment, pride, perils, blame, pragmatism, and self-interested) within 3 major themes. This study has implications for informing science education to combat these traditions of subjecting students to a science curriculum that demotes Kenyan cultural heritage and lifestyle. By incorporating local knowledge such as the ideas discussed in this paper into Kenyan science education, Kenyans can reach one of most challenging objectives of education, which is to produce children who are fundamentally aware of their environment.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Children; Education; Educational Support Services; Environmental education; Kenya; Photography in education; Science education; Teacher attitudes; Vignettes (Teaching technique)

Assessing early grade reading: the value and limits of ‘words per minute’. - Graham, Barbara Elaine; van Ginkel, Agatha J. (Assessing early grade reading: the value and limits of ‘words per minute’., 2014)
Primary school enrolment in low-income countries has increased in recent years. The quality of education is, however, still a cause for concern. Better measurement of early reading progress has been suggested as a means of improving education quality. Benchmarks based on the number of ‘words per minute’ (WPM) students are able to read correctly have been proposed as a basis for assessment and comparison, even where languages and orthographies differ. This paper explores the extent to which WPM benchmarks, based mainly on research with native English speakers, are appropriate for cross-language comparisons. A quantitative study of early grade reading in two European (English and Dutch) and two African languages (Sabaot and Pokomo) analysed WPM and comprehension scores of over 300 children in three countries. Results indicate that similar comprehension scores were associated with diverse WPM rates. This suggests that WPM is not a reliable comparative measure of reading development since linguistic and orthographic features can differ considerably and are likely to influence the reading acquisition process. We argue that a good understanding of the languages of literacy (L1 and/or other) and their effects on reading acquisition are essential to the quest for quality education.
Keywords: Bilingualism; Foreign language education; Language & education; Language Schools; Linguistic minorities; Multilingualism; Reading

Assessing early grade reading: the value and limits of ‘words per minute’. - Graham, Barbara Elaine; van Ginkel, Agatha J. (Assessing early grade reading: the value and limits of ‘words per minute’., 2014)
Primary school enrolment in low-income countries has increased in recent years. The quality of education is, however, still a cause for concern. Better measurement of early reading progress has been suggested as a means of improving education quality. Benchmarks based on the number of ‘words per minute’ (WPM) students are able to read correctly have been proposed as a basis for assessment and comparison, even where languages and orthographies differ. This paper explores the extent to which WPM benchmarks, based mainly on research with native English speakers, are appropriate for cross-language comparisons. A quantitative study of early grade reading in two European (English and Dutch) and two African languages (Sabaot and Pokomo) analysed WPM and comprehension scores of over 300 children in three countries. Results indicate that similar comprehension scores were associated with diverse WPM rates. This suggests that WPM is not a reliable comparative measure of reading development since linguistic and orthographic features can differ considerably and are likely to influence the reading acquisition process. We argue that a good understanding of the languages of literacy (L1 and/or other) and their effects on reading acquisition are essential to the quest for quality education.
Keywords: Bilingualism; Foreign language education; Language & education; Language Schools; Linguistic minorities; Multilingualism; Reading

Examining the impact of age on literacy achievement among grade 6 primary school pupils in Kenya. - Hungi, Njora; Ngware, Moses; Abuya, Benta (Examining the impact of age on literacy achievement among grade 6 primary school pupils in Kenya., 2014)
The main objective of this paper is to investigate the optimal age category at which primary school pupils from low income families perform their best in literacy at grade 6 level. Age is a potential learning barrier because of its link to cognitive development as well as its influence on interactions between pupils within classrooms. The sample consisted of 7041 grade 6 pupils, spread in 226 schools across six major urban slums in Kenya. Using descriptive statistics, we examine the distribution of grade 6 pupils’ age. We then examine incidences of over-age pupils and incidences of grade repetition across various subgroups of pupils disaggregated by factors such as sex, wealth background, grade repetition, school type and geographical location. Finally, using multilevel techniques, we estimate the pupil age category that has greatest positive impact on literacy achievement at grade 6 after controlling selected pupil and school factors. Irrespective of pupil sex, grade repetition, wealth background, school type or geographical location the results indicate that grade 6 pupils perform their best in literacy when they are in the age category ranging from 10 years 6 months to 11 years 5 months. The results also indicate that, in general, younger pupils were likely to achieve better than older pupil in literacy regardless of the background under consideration. Implications of the findings for policy and practice as well as further research are outlined.
Keywords: Elementary education; Influence of age on ability; Kenya; Literacy; Reading level of students; School children; Sixth grade (Education); Urban schools

Social relations as predictors of achievement in math in Kenyan primary schools. - Kodzi, Ivy A.; Oketch, Moses; Ngware, Moses W.; Mutisya, Maurice; Nderu, Evangeline N. (Social relations as predictors of achievement in math in Kenyan primary schools., 2014)
In sub-Saharan Africa, where there is limited financial and human capital, it is important to examine how social relationships may serve to promote or undermine human capital formation. However, little is known about the contributions of social relations to human capital development, especially in terms of academic achievement in Africa. This study examined how variations in key aspects of social relations among teachers; between teachers and students; between principals, teachers, parents and students affect achievement in mathematics among sixth graders in 70 schools in six districts in Kenya. We modeled mathematics achievement as a function of measures of social perception and support while adjusting for school-, classroom- and student level background characteristics. We found that net of teacher subject knowledge and background characteristics, teachers who display commitment to teaching by always correcting homework and keeping students engaged during math lessons had their students performing better. Teacher absenteeism and lack of interest in teaching were negatively associated with performance in math. Lack of parental involvement in the classroom also had negative effects on grades. At the school level, the level of engagement of the principal, measured by supervision of teachers and good interpersonal interactions with parents had positive effects on math achievement. Schools where parents provided material and financial support had better grades, while student delinquency and absenteeism negatively affected grades.
Keywords: Administration of Education Programs; Adults; All Other Miscellaneous Schools and Instruction; Education & society; Educational Support Services; Elementary education; Human capital; Kenya; Mathematics education (Elementary); Prediction of scholastic success; School children; Teacher-student relationships

An Integrated Who-Done-It Mystery for 7th Graders. - Roberts, Charlene; Rose, Tim; Corrigan, Daniel (An Integrated Who-Done-It Mystery for 7th Graders., 2014)
The article discusses the Great Explorer Mystery (G.E.M.) project of the International School of Kenya (ISK) for grade 7 students which aimed for students to work as a team in main subject areas such as Physical Education (PE), Math, and Science based on set standards to solve the mystery of the explorer. Topics discussed include the planning process of 7th grade teachers, the use of a planning wheel which was the central planning tool and the student scheduler, and the plot of the mystery.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Educational standards; Group work in education; International schools; Kenya; Physical education; Sports and Recreation Instruction; Team learning approach in education

Number, age composition and school achievements of siblings in two African capital cities. - Kuepie, Mathias; Tenikue, Michel; Nouetagni, Samuel; Misangumukini, Nicaise (Oxford Development Studies, 2014)
This paper uses biographical data from Dakar and Yaoundé, two large African cities, to study the link between number of siblings and school attainment. The data describe all fertility events experienced by parents and the number of siblings of each child over time. The average family size effect is estimated first. The family size effect at different ages is then estimated. The results show that, in Dakar, both the overall and age-specific effect of family size on education are negative and statistically significant. In Yaoundé, the overall effect is not significant, but negative effects at some schooling ages (between 14 and 17) are observed in this study. Finally, the negative impact of family size on school achievement seems to be driven more by elder siblings than by younger ones. [ABSTRACT FROM AUTHOR]
Keywords: ACADEMIC achievement; AFRICA; EDUCATION; EDUCATIONAL background; SCHOOL size; SIBLINGS

IMPROVING EARLY-GRADE LITERACY IN EAST AFRICA: EXPERIMENTAL EVIDENCE FROM KENYA AND UGANDA. - Lucas, Adrienne M.; McEwan, Patrick J.; Ngware, Moses; Oketch, Moses (IMPROVING EARLY-GRADE LITERACY IN EAST AFRICA: EXPERIMENTAL EVIDENCE FROM KENYA AND UGANDA., 2014)
Primary school enrollments have increased rapidly in sub-Saharan Africa, spurring concerns about low levels of learning. We analyze field experiments in Kenya and Uganda that assessed whether the Reading to Learn intervention, implemented by the Aga Khan Foundation in both countries, improved early-grade literacy as measured by common assessments. We find that Ugandan literacy (in Lango) increased by 0.2 standard deviations. We find a smaller effect (0.08) on a Swahili literacy test in Kenya. We find no evidence that differential effects are explained by baseline differences across countries in student test scores, classroom attributes, or implementation fidelity. A plausible explanation that cannot be directly tested is differential effective exposure to the literacy treatment in the tested languages. Students in Kenya were tested in Swahili, which is not necessarily the main language of instruction in primary schools, despite official policy.
Keywords: Academic achievement; East Africa; Learning; Literacy; Primary education; Primary schools; School enrollment

The complexity of literacy in Kenya: narrative analysis of Maasai women’s experiences. - Taeko, Takayanagi (The complexity of literacy in Kenya: narrative analysis of Maasai women’s experiences., 2014)
This paper aims to challenge limited notions of literacy and argues for the recognition of Maasai women’s self-determined learning in order to bring about human development in Kenya. It also seeks to construct a complex picture of literacy, drawing on postcolonial feminist theory as a framework to ensure that the woman’s voice is heard. Through the analysis of narratives from three Maasai women, the author discovered that: (1) these ‘illiterate’ women have their own literacy through which they read the world (their community); (2) these women use this self-determined literacy to raise critical awareness on community issues; and (3) these women have become ‘organic intellectuals’ in that they have the capacity to synthesise information and skills in order to solve community issues by themselves. This paper concludes that a literacy programme should be more centred on the women from the village and must acknowledge their traditions and culture.
Keywords: Adult education; Adult literacy; Adults; Feminist theory; Maasai women; Narrative inquiry (Research method); Postcolonialism; Reading (Adult education); Women's education

The complexity of literacy in Kenya: narrative analysis of Maasai women’s experiences. - Taeko, Takayanagi (The complexity of literacy in Kenya: narrative analysis of Maasai women’s experiences., 2014)
This paper aims to challenge limited notions of literacy and argues for the recognition of Maasai women’s self-determined learning in order to bring about human development in Kenya. It also seeks to construct a complex picture of literacy, drawing on postcolonial feminist theory as a framework to ensure that the woman’s voice is heard. Through the analysis of narratives from three Maasai women, the author discovered that: (1) these ‘illiterate’ women have their own literacy through which they read the world (their community); (2) these women use this self-determined literacy to raise critical awareness on community issues; and (3) these women have become ‘organic intellectuals’ in that they have the capacity to synthesise information and skills in order to solve community issues by themselves. This paper concludes that a literacy programme should be more centred on the women from the village and must acknowledge their traditions and culture.
Keywords: Adult education; Adult literacy; Adults; Feminist theory; Maasai women; Narrative inquiry (Research method); Postcolonialism; Reading (Adult education); Women's education

Replicating impact of a primary school HIV prevention programme: primary school action for better health, Kenya. - Maticka-Tyndale, E.; Mungwete, R.; Jayeoba, O. (Replicating impact of a primary school HIV prevention programme: primary school action for better health, Kenya., 2014)
School-based programmes to combat the spread of HIV have been demonstrated to be effective over the short-term when delivered on a small scale. The question addressed here is whether results obtained with small-scale delivery are replicable in large-scale roll-out. Primary School Action for Better Health (PSABH), a programme to train teachers to deliver HIV-prevention education in upper primary-school grades in Kenya demonstrated positive impact when tested in Nyanza Province. This article reports pre-, 10-month post- and 22-month post-training results as PSABH was delivered in five additional regions of the country. A total of 26 461 students from 110 primary schools in urban and rural, middle- and low-income settings participated in this repeated cross-sectional study. Students ranged in age from 11 to 16 years, were predominantly Christian (10% Muslim), and the majority were from five different ethnic groups. Results demonstrated positive gains in knowledge, selfefficacy related to changes in sexual behaviours and condom use, acceptance of HIV+ students, endorsement of HIV-testing and behaviours to post-pone sexual debut or decrease sexual activity. These results are as strong as or stronger than those demonstrated in the original impact evaluation conducted in Nyanza Province. They support the roll-out of the programme across Kenyan primary schools.
Keywords: AIDS education; Adolescent health; Children; Children's health; Cross-sectional method; Data analysis software; Descriptive statistics; Elementary and Secondary Schools; Elementary schools; HIV prevention; Health literacy; Health promotion; Kenya; Logistic regression analysis; Primary education; Questionnaires; Research funding; Research methodology; Student health; Teacher education; Teenagers

Shift … centre : cross-cultural spaces for dance training and choreographic enquiry. - Adair, Christy (Shift … centre : cross-cultural spaces for dance training and choreographic enquiry., 2014)
Contemporary dance in East Africa, specifically Kenya, is a newly emerging art form informed by the political drive of a small number of choreographers. In this article, I discuss Kenyan choreographer Opiyo Okach’s contribution to dance training as exemplified through theShift…centre Series 10which was performed at The Place, London, October, 2009. The research for this writing draws on observations of dance rehearsals, workshops and performances and interviews conducted during a number of visits to Nairobi, Dar es Salaam and Kampala from 2007 to 2010.Shift … centrecombines improvisation, responses to site-specific locations, collaborations between artists, and offers an opportunity for dance training for the performers. Okach’s choreography is informed by his desire to de-centre the performing space and to challenge mainstream dance practice. This case study offers an example of a choreographer who creates both in his homeland and Europe and has been instrumental in the development of contemporary dance in Kenya and internationally.
Keywords: Administration of Education Programs; African dance; All Other Miscellaneous Schools and Instruction; Choreographers; Choreography; Dance collaboration; Dance training & conditioning; Education; Educational Support Services; Independent Artists, Writers, and Performers; Independent actors, comedians and performers; Modern dance; Okach, Opiyo; Site-specific performance art

Improving reading outcomes in Kenya: First-year effects of the PRIMR Initiative. - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Mugenda, Abel (Improving reading outcomes in Kenya: First-year effects of the PRIMR Initiative., 2014)
Highlights: [ • ] The PRIMR Initiative aimed to improve primary literacy instruction in Kenya. [ • ] PRIMR led to significant improvements in English and Kiswahili oral reading fluency and reading comprehension. [ • ] Uptake was better among nonformal school teachers than formal school teachers. [•] Classroom observation and instructional support was an essential element to improving instruction.
Keywords: Academic support programs; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; English language education; Kenya; Literacy; Literacy education; Oral reading; Study & teaching of reading comprehension; Swahili language

END 2014: International Conference on Education and New Developments. Conference Proceedings (Madrid, Spain, June 28-30, 2014) - Carmo, Mafalda; World Institute for Advanced Research and Science (WIARS) (Portugal) (Subregional Seminar for Eastern and Southern African Countries, 2014)
We welcome you to the International Conference on Education and New Developments 2014, taking place in Madrid, Spain, from 28 to 30 of June, 2014. Education, as an important right in our contemporary world, began since we exist. Knowledge and skills were passed by adults to the young, and cultures began to extend their experiences through various forms. Schools and academies were formed since the most ancient civilizations. Although between innumerous difficulties, these experiences were capable to teach us how to develop better formative effects and to turn education a generalized and global right. Formal education and other educational practices are used by all of us in the constitution of the human being, in the way one thinks, feels and acts. One of the most important contributions resides in what and how we learn through the improvement of educational processes, both in formal and informal settings. This international conference seeks to provide explore the processes, actions, challenges and outcomes of learning, teaching and human development. Our goal is to offer a worldwide connection between teachers, students, researchers and lecturers, from a wide range of academic fields, interested in exploring and giving their contribution in educational issues We take pride in having been able to connect and bring together academics, scholars, practitioners and others interested in a field that is fertile in new perspectives, ideas and knowledge. We counted on an extensive variety of contributors and presenters, which can supplement our view of the human essence and behavior, showing the impact of their different personal, academic and cultural experiences. This is, certainly, one of the reasons we have many nationalities and cultures represented, inspiring multi-disciplinary collaborative links, fomenting intellectual encounter and development. END 2014 received over more 292 submissions, from 40 different countries, reviewed by a double-blind process. Submissions were prepared to take form of Oral Presentations, Posters, Virtual Presentations and Workshops. It were accepted for presentation in the conference, 83 submissions (28% acceptance rate). The conference also includes a keynote presentation from the distinguished Professor Hanna David, Tel Aviv University (Emerita), Israel, to whom we express our most gratitude. This volume is composed by the proceedings of the International Conference on Education and New Developments (END 2014), organized by the World Institute for Advanced Research and Science (W.I.A.R.S.) and co-sponsored by the respected partners we reference in the dedicated page. This conference addressed different categories inside the Education area and papers are expected to fit broadly into one of the named themes and sub-themes. To develop the conference program we have chosen four main broad-ranging categories, which also covers different interest areas: (1) In TEACHERS AND STUDENTS: Teachers and Staff training and education; Educational quality and standards; Curriculum and Pedagogy; Vocational education and Counseling; Ubiquitous and lifelong learning; Training programs and professional guidance; Teaching and learning relationship; Student affairs (learning, experiences and diversity; Extracurricular activities; Assessment and measurements in Education. (2) In PROJECTS AND TRENDS: Pedagogic innovations; Challenges and transformations in Education; Technology in teaching and learning; Distance Education and eLearning; Global and sustainable developments for Education; New learning and teaching models; Multicultural and (inter)cultural communications; Inclusive and Special Education; Rural and indigenous Education; Educational projects. (3) In TEACHING AND LEARNING: Educational foundations; Research and development methodologies; Early childhood and Primary Education; Secondary Education; Higher Education; Science and technology Education; Literacy, languages and Linguistics (TESL/TEFL); Health Education; Religious Education; Sports Education. (4) In ORGANIZATIONAL ISSUES: Educational policy and leadership; Human Resources development; Educational environment; Business, Administration, and Management in Education; Economics in Education; Institutional accreditations and rankings; International Education and Exchange programs; Equity, social justice and social change; Ethics and values; Organizational learning and change. The proceedings contain the results of the research and developments conducted by authors who focused on what they are passionate about: to promote growth in research methods intimately related to teaching, learning and applications in Education nowadays. It includes an extensive variety of contributors and presenters, who will extend our view in exploring and giving their contribution in educational issues, by sharing with us their different personal, academic and cultural experiences. (Individual papers contain references.)
Keywords: Academic Standards; Accreditation (Institutions); Athletics; Australia; Business Administration Education; Colombia; Conferences (Gatherings); Counseling; Curriculum Development; Denmark; Distance Education; Early Childhood Education; Economics Education; Educational Assessment; Educational Change; Educational Development; Educational Environment; Educational History; Educational Innovation; Educational Policy; Educational Principles; Educational Quality; Educational Research; Educational Trends; Electronic Learning; Elementary Secondary Education; English (Second Language); Equal Education; Ethical Instruction; Ethics; Extracurricular Activities; Faculty Development; Foreign Countries; Greece; Health Education; Higher Education; Human Resources; Inclusion; Indigenous Populations; Interdisciplinary Approach; International Educational Exchange; Israel; Kenya; Languages; Lifelong Learning; Linguistics; Literacy; Mexico; Multicultural Education; Organizational Change; Physical Education; Poland; Religious Education; Research Methodology; Research and Development; Rural Education; STEM Education; Second Language Instruction; Second Language Learning; Social Change; Social Justice; South Korea; Spain (Madrid); Special Education; Staff Development; Student Evaluation; Student Personnel Services; Sustainable Development; Taiwan; Teacher Student Relationship; Teaching Methods; Teaching Models; Technology Uses in Education; Trend Analysis; United Kingdom; Values; Vocational Education

Does teaching style explain differences in learner achievement in low and high performing schools in Kenya? - Ngware, Moses W.; Oketch, Moses; Mutisya, Maurice (Does teaching style explain differences in learner achievement in low and high performing schools in Kenya?, 2014)
Highlights: [•] Recitation style and teaching aids account for inter school differences in academic performance. [•] Visual teaching aids such as illustrative charts are important to learning when used effectively. [•] High performing schools had larger class sizes than low performing schools. [•] Large class sizes did not lead to low test scores. [•] Teacher in-servicing is necessary to rejuvenate teacher's pedagogical knowledge.
Keywords: Academic achievement; Administration of Education Programs; Adults; All Other Miscellaneous Schools and Instruction; Class size; Disadvantaged schools; Education; Educational Support Services; Elementary and Secondary Schools; Elementary education; Kenya; School children; Schools; Teacher training; Teaching aids; Teaching methods; Visual aids

Assessing Early Grade Reading: The Value and Limits of 'Words per Minute' - Graham, Barbara Elaine; van Ginkel, Agatha J. (Assessing Early Grade Reading: The Value and Limits of 'Words per Minute', 2014)
Primary school enrolment in low-income countries has increased in recent years. The quality of education is, however, still a cause for concern. Better measurement of early reading progress has been suggested as a means of improving education quality. Benchmarks based on the number of 'words per minute' (WPM) students are able to read correctly have been proposed as a basis for assessment and comparison, even where languages and orthographies differ. This paper explores the extent to which WPM benchmarks, based mainly on research with native English speakers, are appropriate for cross-language comparisons. A quantitative study of early grade reading in two European (English and Dutch) and two African languages (Sabaot and Pokomo) analysed WPM and comprehension scores of over 300 children in three countries. Results indicate that similar comprehension scores were associated with diverse WPM rates. This suggests that WPM is not a reliable comparative measure of reading development since linguistic and orthographic features can differ considerably and are likely to influence the reading acquisition process. We argue that a good understanding of the languages of literacy (L1 and/or other) and their effects on reading acquisition are essential to the quest for quality education.
Keywords: African Languages; Benchmarking; Contrastive Linguistics; Correlation; Educational Quality; Elementary School Students; English; Foreign Countries; Indo European Languages; Kenya; Language Attitudes; Language Minorities; Literacy; Native Language; Netherlands; Reading Comprehension; Reading Rate; Reading Tests; Scores; Statistical Analysis; United Kingdom (England)

Assessing Early Grade Reading: The Value and Limits of 'Words per Minute' - Graham, Barbara Elaine; van Ginkel, Agatha J. (Assessing Early Grade Reading: The Value and Limits of 'Words per Minute', 2014)
Primary school enrolment in low-income countries has increased in recent years. The quality of education is, however, still a cause for concern. Better measurement of early reading progress has been suggested as a means of improving education quality. Benchmarks based on the number of 'words per minute' (WPM) students are able to read correctly have been proposed as a basis for assessment and comparison, even where languages and orthographies differ. This paper explores the extent to which WPM benchmarks, based mainly on research with native English speakers, are appropriate for cross-language comparisons. A quantitative study of early grade reading in two European (English and Dutch) and two African languages (Sabaot and Pokomo) analysed WPM and comprehension scores of over 300 children in three countries. Results indicate that similar comprehension scores were associated with diverse WPM rates. This suggests that WPM is not a reliable comparative measure of reading development since linguistic and orthographic features can differ considerably and are likely to influence the reading acquisition process. We argue that a good understanding of the languages of literacy (L1 and/or other) and their effects on reading acquisition are essential to the quest for quality education.
Keywords: African Languages; Benchmarking; Contrastive Linguistics; Correlation; Educational Quality; Elementary School Students; English; Foreign Countries; Indo European Languages; Kenya; Language Attitudes; Language Minorities; Literacy; Native Language; Netherlands; Reading Comprehension; Reading Rate; Reading Tests; Scores; Statistical Analysis; United Kingdom (England)

The ‘ideal’ vs. the ‘reality’: medium of instruction policy and implementation in different class levels in a western Kenyan school. - Jones, Jennifer M. (The ‘ideal’ vs. the ‘reality’: medium of instruction policy and implementation in different class levels in a western Kenyan school., 2014)
This paper investigates the perceptions of teachers from one Sabaot dominated primary school in western Kenya regarding the medium of instruction (MoI) policy in different class levels. While their ‘ideal’ MoI policy bears some resemblance to the official policy which advocates mother tongue (MT) as medium in lower primary and English in upper primary, it also has significant differences because of the teachers' desire to move learners as quickly as possible from MT to Kiswahili and English. The ‘reality’ that learners do not have the proficiency required to comprehend instruction in English, however, means that code-switching between languages is a dominant feature of classroom discourse. Ethnographic data were collected over a seven-month period through lesson observation, semi-structured and focus group interviews, and document analysis. This paper particularly draws on data from Science and Mathematics lessons to provide a lens for observing teachers' actual practice. Implications from the study reveal that policy-makers should make it a priority to address policy goals related, for example, to personnel, methodology and materials, so that teachers can give the learners' first language the attention it deserves. In addition, policy-makers would do well to consider extending the time allocated to this language.
Keywords: English language; Kenya; Language & education; Language planning; Language policy

The 'Ideal' vs. the 'Reality': Medium of Instruction Policy and Implementation in Different Class Levels in a Western Kenyan School - Jones, Jennifer M. (The 'Ideal' vs. the 'Reality': Medium of Instruction Policy and Implementation in Different Class Levels in a Western Kenyan School, 2014)
This paper investigates the perceptions of teachers from one Sabaot dominated primary school in western Kenya regarding the medium of instruction (MoI) policy in different class levels. While their "ideal" MoI policy bears some resemblance to the official policy which advocates mother tongue (MT) as medium in lower primary and English in upper primary, it also has significant differences because of the teachers' desire to move learners as quickly as possible from MT to Kiswahili and English. The "reality" that learners do not have the proficiency required to comprehend instruction in English, however, means that code-switching between languages is a dominant feature of classroom discourse. Ethnographic data were collected over a seven-month period through lesson observation, semi-structured and focus group interviews, and document analysis. This paper particularly draws on data from Science and Mathematics lessons to provide a lens for observing teachers' actual practice. Implications from the study reveal that policy-makers should make it a priority to address policy goals related, for example, to personnel, methodology and materials, so that teachers can give the learners' first language the attention it deserves. In addition, policy-makers would do well to consider extending the time allocated to this language.
Keywords: African Languages; Classroom Communication; Educational Policy; Elementary School Students; Elementary School Teachers; English (Second Language); Ethnography; Focus Groups; Foreign Countries; Instructional Materials; Kenya; Language Attitudes; Language Proficiency; Language Usage; Language of Instruction; Mathematics Instruction; Native Language; Observation; Science Instruction; Second Language Learning; Semi Structured Interviews; Teacher Attitudes; Teacher Characteristics; Teaching Methods

Dialogic Instruction and Learning: The Case of One Kiswahili Classroom in Kenya - Lisanza, Esther Mukewa (Dialogic Instruction and Learning: The Case of One Kiswahili Classroom in Kenya, 2014)
This paper reports on an ethnographic case study which was carried out in a Kenyan first-grade classroom. The classroom had 89 students with their 2 teachers who taught at different times. The classroom was very crowded and had a high paucity of literacy materials. The study was guided by sociocultural and dialogic frameworks which maintain that social and dialogic interactions have important roles to play in a child's literacy and language development. Thus, the social life of the observed classroom was central to the children's literacy and language learning. Although there were a shortage of literacy materials and space limitations in this classroom, the Kiswahili teacher's mediating role and children's agency in this classroom were paramount. Through the teacher's dialogic instruction and mediation, the children's voices were recognised and acknowledged. There were dynamic classroom interactions and dialogues which involved different practices such as storytelling, peer-guided reading, play, and classroom talk. The study concluded that meaningful instruction and dialogue are important for meaningful language learning to occur. Also, oral and written language develop simultaneously in a classroom setting. Finally, classroom contexts play a major role in language learning.
Keywords: African Languages; Case Studies; Classroom Environment; Elementary School Students; Elementary School Teachers; Ethnography; Foreign Countries; Interaction; Interpersonal Communication; Kenya; Peer Teaching; Play; Reading Materials; Story Telling; Student Participation; Teacher Role; Teaching Methods

Improving Early-Grade Literacy in East Africa: Experimental Evidence from Kenya and Uganda - Lucas, Adrienne M.; McEwan, Patrick J.; Ngware, Moses; Oketch, Moses (Improving Early-Grade Literacy in East Africa: Experimental Evidence from Kenya and Uganda, 2014)
Primary school enrollments have increased rapidly in sub-Saharan Africa, spurring concerns about low levels of learning. We analyze field experiments in Kenya and Uganda that assessed whether the Reading to Learn intervention, implemented by the Aga Khan Foundation in both countries, improved early-grade literacy as measured by common assessments. We find that Ugandan literacy (in Lango) increased by 0.2 standard deviations. We find a smaller effect (0.08) on a Swahili literacy test in Kenya. We find no evidence that differential effects are explained by baseline differences across countries in student test scores, classroom attributes, or implementation fidelity. A plausible explanation that cannot be directly tested is differential effective exposure to the literacy treatment in the tested languages. Students in Kenya were tested in Swahili, which is not necessarily the main language of instruction in primary schools, despite official policy.
Keywords: African Languages; Educational Policy; Elementary School Students; Enrollment Trends; Foreign Countries; Intervention; Kenya; Language Tests; Language of Instruction; Literacy Education; Outcomes of Education; Scores; Second Language Learning; Uganda

Mother Tongue Education in Primary Teacher Education in Kenya: A Language Management Critique of the Quota System - Mwaniki, Munene (Mother Tongue Education in Primary Teacher Education in Kenya: A Language Management Critique of the Quota System, 2014)
Mother tongue education (MTE) has been a subject of rigorous debate for more than half a century, in both industrialised and developing societies. Despite disparate views on MTE, there is an uneasy consensus on its importance in educational systems, especially in the foundational years. Using the Language Management Framework, the article provides a critical appraisal of MTE discourses in relation to primary teacher education and the quota system of student teacher selection and teacher deployment in Kenya. The article argues that from a language management perspective, these two mechanisms are critical in sustaining and promoting MTE in Kenya, and possibly elsewhere.
Keywords: African Languages; Discourse Analysis; Elementary School Teachers; Foreign Countries; Guidelines; Kenya; Language Planning; Language of Instruction; Native Language Instruction; Student Teachers; Teacher Education; Teacher Selection

When to Randomize: Lessons From Independent Impact Evaluation of Reading to Learn (RtL) Programme to Improve Literacy and Numeracy in Kenya and Uganda. - Oketch, Moses; Ngware, Moses; Mutisya, Maurice; Kassahun, Admassu; Abuya, Benta; Musyoka, Peter (When to Randomize: Lessons From Independent Impact Evaluation of Reading to Learn (RtL) Programme to Improve Literacy and Numeracy in Kenya and Uganda., 2014)
In East Africa, there is great effort directed toward ensuring that there is learning and value for money invested in universal education policies initiated over the past decade. Kenya and Uganda are two countries that typify this effort. The effort includes the work of research organisations such as Uwezo, which assess learning levels; RTI, which assesses language and early grade reading; and the work of African Population and Health Research Center (APHRC), which looks at schooling patterns of different households. All these studies paint a disappointing picture both for the universal access Education for All policy and the large sums of money that have been devoted to achieve it. The verdict is that too many pupils in schools are not learning and too many poor ones are excluded from universal public access. Uwezo reports that 70% of pupils in Grade 3 cannot do Grade 2 work, and 9% of those completing Primary 8 in Kenya cannot do Grade 2 work. Answers are not easy to find, so borrowing what has worked elsewhere has been attempted. This article presents one effort toward finding what can work to improve learning for pupils in early grades. It is based on the idea of “Reading to Learn” implemented elsewhere and attempted in East Africa by Aga Khan Foundation and independently evaluated by APHRC using randomization methods. Lessons presented highlight the role and complexities of randomization in addressing the educational challenges in East Africa.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; All other schools and instruction; East Africa; Education; Education policy; Educational Support Services; Exam Preparation and Tutoring; Literacy programs; Other local, municipal and regional public administration; Other provincial and territorial public administration; Randomization (Statistics); Research; Right to education

When to Randomize: Lessons from Independent Impact Evaluation of Reading to Learn (RtL) Programme to Improve Literacy and Numeracy in Kenya and Uganda - Oketch, Moses; Ngware, Moses; Mutisya, Maurice; Kassahun, Admassu; Abuya, Benta; Musyoka, Peter (When to Randomize: Lessons from Independent Impact Evaluation of Reading to Learn (RtL) Programme to Improve Literacy and Numeracy in Kenya and Uganda, 2014)
In East Africa, there is great effort directed toward ensuring that there is learning and value for money invested in universal education policies initiated over the past decade. Kenya and Uganda are two countries that typify this effort. The effort includes the work of research organisations such as Uwezo, which assess learning levels; RTI, which assesses language and early grade reading; and the work of African Population and Health Research Center (APHRC), which looks at schooling patterns of different households. All these studies paint a disappointing picture both for the universal access Education for All policy and the large sums of money that have been devoted to achieve it. The verdict is that too many pupils in schools are not learning and too many poor ones are excluded from universal public access. Uwezo reports that 70% of pupils in Grade 3 cannot do Grade 2 work, and 9% of those completing Primary 8 in Kenya cannot do Grade 2 work. Answers are not easy to find, so borrowing what has worked elsewhere has been attempted. This article presents one effort toward finding what can work to improve learning for pupils in early grades. It is based on the idea of "Reading to Learn" implemented elsewhere and attempted in East Africa by Aga Khan Foundation and independently evaluated by APHRC using randomization methods. Lessons presented highlight the role and complexities of randomization in addressing the educational challenges in East Africa.
Keywords: Classroom Observation Techniques; Elementary School Students; Foreign Countries; Grade 1; Grade 2; Grade 3; Improvement; Kenya; Literacy Education; Models; Numeracy; Outcome Measures; Parent Participation; Primary Education; Program Evaluation; Reading Programs; Sampling; Scaffolding (Teaching Technique); Scores; Statistical Analysis; Uganda

JiFUNzeni: A Blended Learning Approach for Sustainable Teachers' Professional Development - Onguko, Brown Bully (JiFUNzeni: A Blended Learning Approach for Sustainable Teachers' Professional Development, 2014)
JiFUNzeni blended learning approach is a sustainable approach to provision of professional development (PD) for those in challenging educational contexts. JiFUNzeni approach emphasizes training regional experts to create blended learning content, working with appropriate technology while building content repositories. JiFUNzeni approach was field-tested though a design-based research intervention conducted in rural western Kenya. The field test included design, development and implementation of a blended learning course for teachers' professional development utilizing appropriate technologies including tablets powered by solar energy, open educational resources and open source software. One year after the intervention, follow-up interviews were conducted with eight of the ten teachers and two professional development tutors (PDTs) who participated in the research. The findings from the follow-up interviews shared in this paper revealed that: teachers still used cooperative learning and activity-based learning strategies in their teaching. The PDTs on the other hand designed, developed and implemented one other jiFUNzeni blended learning course for twelve teachers in one school in Korogocho slum in Nairobi city. Implementation by PDTs of jiFUNzeni approach confirmed that they had learned through a sustainable way of delivering professional development in challenging educational contexts. The PDTs utilized the instructional design approaches learned through their participation in the research in designing blended learning content, while they also innovated new ways of developing self-study content as an important creative addition to what they had previously learned. Two teenage children participated in digital content development by advising the PDTs on some appropriate ways of applying technology thus, attesting to the fact that digital natives are important reciprocal supporters to digital immigrants and vice versa.
Keywords: Blended Learning; Computer Software; Computers; Cooperative Learning; Course Content; Design; Disadvantaged Environment; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Interviews; Kenya; Learning Activities; Multimedia Materials; Open Source Technology; Program Development; Qualitative Research; Rural Areas; Self Evaluation (Individuals); Sustainability; Teacher Attitudes; Teaching Methods; Training

ICT, Literacy and Teacher Change: The Effectiveness of ICT Options in Kenya - Piper, Benjamin; Society for Research on Educational Effectiveness (SREE) (Society for Research on Educational Effectiveness, 2014)
There is a dearth of literature that use research design for causal inference that estimate the effect of information and communications technology (ICT) programs on literacy outcomes in early primary, particularly in Sub-Saharan Africa. There are several programs that have used ICT at a large scale, including Los Angeles, Peru, Nicaragua, Rwanda and an ongoing program in Turkey. Seldom have the studies directly estimated the effect of the ICT program on learning, as the measures used have typically been a middle level of the causal chain (Strigel & Pouezevara, 2012). Mobile phones are increasingly available in the market, and several authors argue that mobile learning is an increasingly ideal way to increase outcomes at scale (UNESCO, 2012; GSMA, 2012; McKinsey & Co., 2012; Vosloo, 2012). There are concerns that using mobiles for learning would differentiate by gender (Murthy, 2011). Fewer studies have estimated the impact of e-readers on learning, though some recent studies in Kenya and Ghana are promising (Worldreader, 2012). Analyses of the impact of large scale tablet and laptop initiatives is somewhat discouraging. The World Bank blog of ICT Specialist Michael Trucano recently presented an analysis of several countries programs, including the USA, Uruguay, Thailand, Peru, Kenya, Rwanda, Turkey, India, Argentina and Portugal (Trucano, 2013). Few of these studies consider cost when estimating impact, and the impacts identified remain small or not yet determined. In all of the studies researched, in fact, there was no attempt to compare the cost and effectiveness of different ICT interventions within one study. The Kenya Primary Math and Reading Initiative (PRIMR) aims to improve literacy learning by aligning learning materials and teacher practices with current research, providing ongoing instructional support and observation, and supplying instructional materials and English and Kiswahili books for students. PRIMR is a partnership between USAID/Kenya and the Ministry of Education, with implementation by RTI International. Embedded in PRIMR is a study of the effectiveness and cost-effectiveness of ICT in Kenya, located in Kisumu county. What little evidence exists suggests that ICT programs are not often ineffective. However, in a context where printed material is quite expensive, e-readers may dramatically expand access to print. Similarly, the lack of integration of ICT into the formal system is often decried by the Kenyan Ministry of Education. The ICT program is under careful examination in order to determine the lessons learned for Kenya's own ICT program, with an emphasis on rapidly expanding access to ICT for primary school. Tables and figures are appended.
Keywords: African Languages; Alignment (Education); Cost Effectiveness; Elementary School Mathematics; Elementary School Students; Elementary School Teachers; English; English (Second Language); Foreign Countries; Handheld Devices; Information Technology; Instructional Effectiveness; Instructional Materials; Intervention; Kenya; Mathematics Instruction; Oral Reading; Phonological Awareness; Reading Fluency; Reading Instruction; Technology Integration; Telecommunications

Whatever the law says: language policy implementation and early-grade literacy achievement in Kenya. - Trudell, Barbara; Piper, Benjamin (Whatever the law says: language policy implementation and early-grade literacy achievement in Kenya., 2014)
Language policy is generally seen as a national-level decision regarding which languages the state will support, and in which public domains. However, the reality is that language policy plays out at regional and local levels as well. In fact, it could be argued that the most important instantiations of language policy are those which directly determine local-language behaviors in institutions such as schools, government and civil society. Using data drawn from Kenya, this article examines the formulation and implementation of language policy as it plays out in the primary classroom environment. The relationships between language policy implementation at the classroom level and students' early literacy outcomes are explored, giving insight into how the degree of adherence to language policy in the classroom intersects with student achievement. The article presents findings using language use as a predictor, school and student-level economic status as control variables and student achievement as the outcomes. The country-level differences in language policy implementation between Kenya and Uganda, and the impact of those differences on student achievement in the two countries, are also examined. The article has implications for the establishment of a learning environment in the multi-language primary classroom, and demonstrates the extent to which choices about language policy implementation can present a serious challenge to effective education.
Keywords: Academic achievement; Civil society; Classroom environment; Kenya; Language policy

Whatever the law says: language policy implementation and early-grade literacy achievement in Kenya. - Trudell, Barbara; Piper, Benjamin (Whatever the law says: language policy implementation and early-grade literacy achievement in Kenya., 2014)
Language policy is generally seen as a national-level decision regarding which languages the state will support, and in which public domains. However, the reality is that language policy plays out at regional and local levels as well. In fact, it could be argued that the most important instantiations of language policy are those which directly determine local-language behaviors in institutions such as schools, government and civil society. Using data drawn from Kenya, this article examines the formulation and implementation of language policy as it plays out in the primary classroom environment. The relationships between language policy implementation at the classroom level and students' early literacy outcomes are explored, giving insight into how the degree of adherence to language policy in the classroom intersects with student achievement. The article presents findings using language use as a predictor, school and student-level economic status as control variables and student achievement as the outcomes. The country-level differences in language policy implementation between Kenya and Uganda, and the impact of those differences on student achievement in the two countries, are also examined. The article has implications for the establishment of a learning environment in the multi-language primary classroom, and demonstrates the extent to which choices about language policy implementation can present a serious challenge to effective education.
Keywords: Academic achievement; Civil society; Classroom environment; Kenya; Language policy

Whatever the Law Says: Language Policy Implementation and Early-Grade Literacy Achievement in Kenya - Trudell, Barbara; Piper, Benjamin (Whatever the Law Says: Language Policy Implementation and Early-Grade Literacy Achievement in Kenya, 2014)
Language policy is generally seen as a national-level decision regarding which languages the state will support, and in which public domains. However, the reality is that language policy plays out at regional and local levels as well. In fact, it could be argued that the most important instantiations of language policy are those which directly determine local-language behaviors in institutions such as schools, government and civil society. Using data drawn from Kenya, this article examines the formulation and implementation of language policy as it plays out in the primary classroom environment. The relationships between language policy implementation at the classroom level and students' early literacy outcomes are explored, giving insight into how the degree of adherence to language policy in the classroom intersects with student achievement. The article presents findings using language use as a predictor, school and student-level economic status as control variables and student achievement as the outcomes. The country-level differences in language policy implementation between Kenya and Uganda, and the impact of those differences on student achievement in the two countries, are also examined. The article has implications for the establishment of a learning environment in the multi-language primary classroom, and demonstrates the extent to which choices about language policy implementation can present a serious challenge to effective education.
Keywords: Academic Achievement; African Languages; Case Studies; Conflict; Correlation; Cross Cultural Studies; Educational Policy; Elementary School Students; English (Second Language); Foreign Countries; Kenya; Language Planning; Language of Instruction; Literacy Education; Multilingualism; Native Language; Predictor Variables; Reading Tests; Second Language Learning; Socioeconomic Influences; Teaching Methods; Uganda

Improving Reading Outcomes in Kenya: First-Year Effects of the PRIMR Initiative - Zuilkowski, Stephanie Simmons; Piper, Benjamin; Society for Research on Educational Effectiveness (SREE) (Society for Research on Educational Effectiveness, 2014)
If children do not learn how to read in the first few years of primary school, they will struggle to complete the cycle and are at greater risk of dropping out. It is therefore crucial to identify and test interventions that have the potential of making a large impact, can be implemented quickly, and are affordable to be taken to scale by the Kenyan government. This is the goal of the PRIMR Initiative--to test various options for improving learning outcomes and instruction in Kenyan schools, using a randomized controlled design. The design is essential to this contribution, as many pilot programs in the sector do not test the impacts of quality-improvement methods at a medium scale and with enough rigor to identify a causal impact. In this paper, the authors focus on early-grade literacy outcomes--reading fluency and comprehension--after one year of implementation for pupils in grades 1 and 2. Study findings indicated that the first year of PRIMR had a positive impact on the three outcomes of interest--oral reading fluency, the percentage of pupils who read at the MOE's benchmark, and reading comprehension--although not on all combinations of language, grade, and school type. Also, the meaningful first-year impacts of PRIMR on student achievement have implications for teacher professional development in Kenya. One table and one figure are appended.
Keywords: Benchmarking; Foreign Countries; Grade 1; Grade 2; Intervention; Kenya; Kenya (Nairobi); Oral Reading; Outcomes of Education; Program Effectiveness; Program Implementation; Randomized Controlled Trials; Reading Achievement; Reading Comprehension; Reading Fluency; Reading Improvement; Reading Instruction

Demographic and Health Survey 2014 - Government of Kenya (Government Printer, 2014)

The County Early Childhood Education Bill, 2014 - Republic of Kenya (2014)

Global report on early childhood care and education: the right to a strong foundation - UNESCO Digital Library - UNESCO; UNICEF (2014)

Influence of mothers' education on children's maths achievement in Kenya. - Abuya, Benta A.; Oketch, Moses; Mutisya, Maurice; Ngware, Moses; Ciera, James (Influence of mothers' education on children's maths achievement in Kenya., 2013)
Research shows that fathers' level of education predicts achievement of both boys and girls, with significantly greater effect for boys. Similarly, mothers' level of education predicts the achievement of girls but not boys. This study tests the mother–child education achievement hypothesis, by examining the effect of mothers' education on the maths test score of children, using data from 71 schools across 6 districts in Kenya. The findings of a multilevel random intercept model, based on a sample of 1907 learners reveal surprisingly negative effect of mothers' education on pupil's achievement, with an interaction effect of mother's and father's education being positive.
Keywords: Academic achievement & society; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Children; Education; Educational Support Services; Educational attainment; Influence; Kenya; Mother-child relationship

Grassroots Inquiry: Reconsidering the Location of Innovation. - Ghiso, María Paula; Campano, Gerald; Simon, Rob (Grassroots Inquiry: Reconsidering the Location of Innovation., 2013)
The article discusses a grassroots approach to innovation in literacy education, in which change comes from teachers themselves. Examples of innovations such as the involvement of Ngũgĩ wa Thiong'o in Kenya in the 1960s to introduce African literature into the nation's schools, the weekly meetings of the Philadelphia Teachers Learning Cooperative (PTLC) to analyze student data, and the efforts of Gerald and María Paula in building a social-justice-oriented community center, are examined.
Keywords: Administration of Education Programs; African literature; All Other Miscellaneous Schools and Instruction; Child and Youth Services; Community centers; Education; Educational Support Services; Educational innovations; Literacy education; Ngugi wa Thiong'o, 1938-; Other Individual and Family Services; Pennsylvania; Philadelphia (Pa.); Services for the Elderly and Persons with Disabilities

Motivation for Reading and Upper Primary School Students’ Academic Achievement in Reading in Kenya. - Mucherah, Winnie; Herendeen, Abbey (Motivation for Reading and Upper Primary School Students’ Academic Achievement in Reading in Kenya., 2013)
This study examined primary school students' reading motivation and performance on the standardized exam. Participants included 901 seventh and eighth grade students from Kenya. There were 468 females and 433 males. Contrary to previous studies, results showed reading challenge and aesthetics, but not efficacy, predicted reading achievement, indicating reading motivation may not influence achievement similarly across cultures. Gender differences were found in reading achievement but not motivation, an indication of a complex relationship between reading motivation and achievement. Students who read mostly for compliance and recognition did poorly in reading. Eighth graders did better in both reading motivation and achievement.
Keywords: Kenya; Reading (Primary); Reading interests; Reading level of students; Reading motivation; School children

Examinations as an instrument for strengthening pedagogy: lessons from three decades of experience in Kenya. - Wasanga, Paul; Somerset, Anthony (Examinations as an instrument for strengthening pedagogy: lessons from three decades of experience in Kenya., 2013)
This paper starts with an analysis of the twin purposes of an examination reform programme originally launched in Kenya during the 1970s: first, to broaden the spectrum of cognitive skills being tested; and second, to set up a feedback system based on the performance profiles, providing schools and teachers with guidance as to how pedagogy and learning might be strengthened. Then, in a change of time perspective, the paper looks back over 30 years of implementation experience, examining the reasons why some components of the original programme have proved more sustainable than others. A final section discusses three key issues which have emerged in recent years, and considers their implications for policy.
Keywords: Administration of Education Programs; Africa; All Other Miscellaneous Schools and Instruction; Education; Education policy; Educational Support Services; Educational change; Educational quality; Educational tests & measurements; Government policy; Kenya; Other local, municipal and regional public administration; Other provincial and territorial public administration; Psychological feedback

Basic Education from Early Childhood: Impacts of Free Primary Education and Subsidized Secondary Education on Public ECDE Centers in Nyahururu District, Kenya - Mwangi, Peter Murage; Serem, T. D. K. (Basic Education from Early Childhood: Impacts of Free Primary Education and Subsidized Secondary Education on Public ECDE Centers in Nyahururu District, Kenya, 2013)
Kenya must invest more in education to realize her vision 2030. The government commitment to Education for All's goal has been expressed through provision of basic education in pre-primary, primary and secondary school levels. To this end, the government introduced two kitties; Free Primary Education in 2003 and Subsidized Secondary Education in 2008 (where the government paid tuition fees for the students in secondary schools), but left parents to finance Early Childhood Development and Education. Since public centers were not well equipped, only the poor parents enrolled their children. The study was carried out in Nyahururu District in 2010, to assess the impacts of the two government kitties on public Early Childhood Development and Education centers in Kenya. To evaluate the impact of the kitties on the public Early Childhood Development and Education centers, private centers were also studied together. The study revealed that while the kitties led to rising enrolment in primary, secondary school and private Early Childhood Development and Education centers, enrolment declined in public centers. The two have lowered the quality of education in public Early Childhood Development and Education centers since parents were unwilling to raise finances enough to employ and motivate teachers, buy teaching/learning resources, school facilities and school feeding program. High enrolment after Free Primary Education also took up classrooms meant for Early Childhood Development and Education in public centers.
Keywords: Access to Education; Basic Skills; Budgets; Early Childhood Education; Educational Finance; Elementary Secondary Education; Enrollment; Financial Support; Foreign Countries; Kenya; Questionnaires

They own this: Mother tongue instruction for indigenous Kuku Children in Southern Sudan. - Laguarda, Ana Isabel; Woodward, Walter Pierce (They own this: Mother tongue instruction for indigenous Kuku Children in Southern Sudan., 2013)
This article details a pilot program of mother tongue instruction in five primary schools for classes one through three, in Kajokeji County, Central Equatoria State, South Sudan. The program was launched by teachers and volunteers with the support of the Jesuit Refugee Service, an international non-governmental organization. The research examines how mother tongue education impacted teaching and learning during one academic term. The article discusses the reasons for mother tongue education in Kajokeji, the implementation methods, the results of the pilot effort, and implications for educational personnel working with indigenous populations in Kajokeji, in South Sudan, and across the World.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Descriptive statistics; Education; Educational Support Services; Educational tests & measurements; Indigenous peoples; Language acquisition; Pilot projects; School environment; Sudan; Teachers; Uganda

Qur'anic school sermons as a site for sacred and second language socialisation - Moore, Leslie C (Journal of Multilingual and Multicultural Development, 2013)
Research on Islamic education in Africa has focused on the core curriculum of elementary Qur'anic school -- that is, the memorisation, recitation, reading, and writing of the Qur'an without explanation of the literal meaning of the sacred text. Taking a language socialisation perspective, I examine the Qur'anic school sermon as practiced by Fulbe in northern Cameroon. I situate the practice by providing an overview of the Qur'anic school tradition in this community and of the sociolinguistic context in which Fulbe children are being schooled. I then present discourse analysis of a sermon, showing how the activity provides children with instruction in proper Muslim conduct and feeling, as well as Qur'anic Arabic text that is glossed in Fulfulde and connected to their daily lives. I conclude by discussing Qur'anic school sermons as routine activities in which children learn to engage with the Qur'an and other Arabic texts as language that they can comprehend and use in ways that are socially and culturally appropriate in their community. Adapted from the source document
Keywords: 5610:sociolinguistics; Arabic (03750); Cameroon (10230); Children (11850); Education (20900); Religious Language (72790); Religious Literature (72800); Second Languages (76200); Socialization (80000); Sociolinguistics (80200); article; sociolinguistics

Critical Perspectives on Free Primary Education in Kenya: Towards an Anti-Colonial Pedagogy. - Milu, Esther (Critical Perspectives on Free Primary Education in Kenya: Towards an Anti-Colonial Pedagogy., 2013)
This paper is a reading of the Free Primary Education (FPE) policy in Kenya through the lenses of critical theory/pedagogy. The study critiques the National Alliance Rainbow Coalition (NARC) government for adoption of the Freirian banking model to design and implement the policy. The paper argues that such a model has ended up marginalizing the voices of other FPE stakeholders and sustaining educational inequalities in the country. The paper also examines how neoliberal policies like Structural Adjustment Programs (SAPS) have influenced and shaped the FPE policy, and other educational reforms in the country. Such policies are read as colonial projects functioning to produce particular meanings and serving the interests of the dominant stakeholders—top government leaders and transnational capital markets. The paper concludes by theorizing an anticolonial pedagogy that aims at transforming FPE to an educational program that works to serve the interests of the local populace. The anticolonial pedagogy theorized also proposes strategies that different government and education stakeholders can employ in order to resist and counter the colonial, neo-colonial and neo-liberal structures and ideologies that continue to be perpetuated in the country.
Keywords: Capital market; Critical theory; Educational equalization; Government policy; Kenya; National Alliance Rainbow Coalition (Political party : Kenya); Neoliberalism; Primary education

Critical Perspectives on Free Primary Education in Kenya: Towards an Anti-Colonial Pedagogy - Milu, Esther (Critical Perspectives on Free Primary Education in Kenya: Towards an Anti-Colonial Pedagogy, 2013)
This paper is a reading of the "Free Primary Education" (FPE) policy in Kenya through the lenses of critical theory/pedagogy. The study critiques the National Alliance Rainbow Coalition (NARC) government for adoption of the Freirian banking model to design and implement the policy. The paper argues that such a model has ended up marginalizing the voices of other FPE stakeholders and sustaining educational inequalities in the country. The paper also examines how neoliberal policies like Structural Adjustment Programs (SAPS) have influenced and shaped the FPE policy, and other educational reforms in the country. Such policies are read as colonial projects functioning to produce particular meanings and serving the interests of the dominant stakeholders--top government leaders and transnational capital markets. The paper concludes by theorizing an anticolonial pedagogy that aims at transforming FPE to an educational program that works to serve the interests of the local populace. The anticolonial pedagogy theorized also proposes strategies that different government and education stakeholders can employ in order to resist and counter the colonial, neo-colonial and neo-liberal structures and ideologies that continue to be perpetuated in the country.
Keywords: Access to Education; Africa; At Risk Persons; Critical Theory; Educational Change; Educational Finance; Educational Policy; Elementary Education; Equal Education; Foreign Countries; Foreign Policy; Government Role; Kenya; Neoliberalism; Politics of Education; Poverty; Social Bias; Stakeholders

Weaknesses in the Search for the Evidence for the Effectiveness of Applying Psychological Learning Theory to Teaching: The Case of Plant Nutrition. - Okunya, Luke Odiemo (Weaknesses in the Search for the Evidence for the Effectiveness of Applying Psychological Learning Theory to Teaching: The Case of Plant Nutrition., 2013)
It was observed by Thomas Shuell (1996; 2005) that there is a large body of knowledge in psychological learning theory to inform teaching practice. However, there is little evidence to support the need for its application to teaching. He said this was mainly due to the fact the available resources are arbitrarily and selectively applied. In their application there is rarely any systematic linkage between the various sub-aspects of the theory-informed teaching sequence and the accrued learning gains to enable the characterisation the actual effectiveness of the applied learning theory. This review paper sought to establish the validity of the reasons provided as being a hindrance to the development of a reliable evidence base for the effectiveness of psychological learning at informing teaching in the area of plant nutrition. The findings showed that Shuell's observations have strong validity. The implications for these findings to the search for evidence for effectiveness of theory-informed teaching are presented.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Educational psychology; Learning theories in education; Plant nutrition; Psychology of teaching; Validity of statistics

Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count? - Akyeampong, Kwame; Lussier, Kattie; Pryor, John; Westbrook, Jo (Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count?, 2013)
Abstract: Teacher education has an important role in ensuring quality of learning especially for the poorest children. The article draws on a study of teacher preparation for the early primary grades in six African countries – Ghana, Kenya, Mali, Senegal, Tanzania and Uganda – in reading and mathematics. Initial teacher education had the strongest impact on newly qualified teachers but also induced misplaced confidence leading to standardised teacher-led approaches that failed to engage learners. Learning to read was divorced from meaning while mathematical activities were not linked to learning concepts. We suggest that teacher education is reconstructed as a study of classroom practice that places children''s learning at its centre.
Keywords: Africa; Classrooms; Educational quality; Learning; Reading; Teacher education; Teaching

Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count? - Akyeampong, Kwame; Lussier, Kattie; Pryor, John; Westbrook, Jo (Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count?, 2013)
Abstract: Teacher education has an important role in ensuring quality of learning especially for the poorest children. The article draws on a study of teacher preparation for the early primary grades in six African countries – Ghana, Kenya, Mali, Senegal, Tanzania and Uganda – in reading and mathematics. Initial teacher education had the strongest impact on newly qualified teachers but also induced misplaced confidence leading to standardised teacher-led approaches that failed to engage learners. Learning to read was divorced from meaning while mathematical activities were not linked to learning concepts. We suggest that teacher education is reconstructed as a study of classroom practice that places children''s learning at its centre.
Keywords: Africa; Classrooms; Educational quality; Learning; Reading; Teacher education; Teaching

Creating cycles of writing and reading in a resource-poor school community in Kenya: Could one literacy event lead to ongoing literacy practices? - Graham, Barbara (Creating cycles of writing and reading in a resource-poor school community in Kenya: Could one literacy event lead to ongoing literacy practices?, 2013)
Abstract: Strong correlations between high levels of poverty and low education outcomes have prompted interventions aimed at raising literacy levels in communities characterised by poverty within Kenya, as in other countries. However, interventions aimed at improving literacy only in the languages of instruction (LOI) may not be the best option for students who speak mother tongues (MT) different from the school''s LOI. The Capability Approach framework is used to examine the potential of parent-produced MT materials to be low-cost entry points into early-grade literacy for one resource-poor Kenyan school. It demonstrates that factors related to poverty strongly impact that potential.
Keywords: All Other Miscellaneous Schools and Instruction; Educational intervention; Educational outcomes; Elementary and Secondary Schools; Kenya; Literacy; Reading; Schools; Students; Writing

Creating Cycles of Writing and Reading in a Resource-Poor School Community in Kenya: Could One Literacy Event Lead to Ongoing Literacy Practices? - Graham, Barbara (Creating Cycles of Writing and Reading in a Resource-Poor School Community in Kenya: Could One Literacy Event Lead to Ongoing Literacy Practices?, 2013)
Strong correlations between high levels of poverty and low education outcomes have prompted interventions aimed at raising literacy levels in communities characterised by poverty within Kenya, as in other countries. However, interventions aimed at improving literacy only in the languages of instruction (LOI) may not be the best option for students who speak mother tongues (MT) different from the school's LOI. The Capability Approach framework is used to examine the potential of parent-produced MT materials to be low-cost entry points into early-grade literacy for one resource-poor Kenyan school. It demonstrates that factors related to poverty strongly impact that potential.
Keywords: African Languages; Correlation; Economically Disadvantaged; Educational Attainment; Foreign Countries; Guidelines; Intervention; Kenya; Language of Instruction; Literacy; Native Language; Outcomes of Education; Poverty; Second Language Learning

Classroom-Up Policy Change: Early Reading and Math Assessments at Work - Gove, Amber; Habib, Samir; Piper, Benjamin; Ralaingita, Wendi (Classroom-Up Policy Change: Early Reading and Math Assessments at Work, 2013)
This article reviews the development of the Early Grade Reading and Mathematics Assessments (EGRA and EGMA), which are locally tailored, timely assessments designed to directly inform policy and instruction for learning improvement, particularly for countries on the lower end of the income spectrum. The history of the design and implementation of the tools, as well as case studies of their use in Egypt and Kenya, are a useful counterbalance to the experience of the more traditional international large-scale assessments (ILSAs) documented in this special issue--in particular for understanding the needs of countries struggling to transform "education for all" into "learning for all".
Keywords: Case Studies; Educational Assessment; Educational Improvement; Egypt; Elementary School Students; Equal Education; Foreign Countries; International Programs; Kenya; Mathematics Instruction; Mathematics Tests; Measurement; Primary Education; Reading Instruction; Reading Tests; Test Construction; Test Use; Testing

Motivation for Reading and Upper Primary School Students' Academic Achievement in Reading in Kenya - Mucherah, Winnie; Herendeen, Abbey (Reading Psychology, 2013)
This study examined primary school students' reading motivation and performance on the standardized exam. Participants included 901 seventh and eighth grade students from Kenya. There were 468 females and 433 males. Contrary to previous studies, results showed reading challenge and aesthetics, but not efficacy, predicted reading achievement, indicating reading motivation may not influence achievement similarly across cultures. Gender differences were found in reading achievement but not motivation, an indication of a complex relationship between reading motivation and achievement. Students who read mostly for compliance and recognition did poorly in reading. Eighth graders did better in both reading motivation and achievement.
Keywords: Age Differences; Competition; Compliance (Psychology); Elementary School Students; Foreign Countries; Gender Differences; Grade 7; Grade 8; Grades (Scholastic); Kenya; Questionnaires; Reading Achievement; Reading Motivation; Recognition (Achievement); Recreational Reading; Standardized Tests

Freeing the Hand of the Lord: Securing Constructivist Pedagogy through Professional Development in Kenyan Rural Schools - Ngundi, James (ProQuest LLC, 2013)
This study explores the use of constructivist pedagogy promoting learner-centered teaching in Kenya's rural primary schools. It explores both the school-based as well as bureaucratic hurdles to the success of constructivist pedagogy. Teacher ideologies, issues of diverse cultures and traditional beliefs, the rural context characterized by underresourced, understaffed and over-crowded schools, as well as teacher professional development are some of the lenses through which the practice of learner-centered teaching is investigated. This qualitative research uses the case-study method, focusing on the instructional practices of rural primary school teachers and data from multiple sites collected through classroom observations, interviews, teachers' journals, a focus group and situated recall, based on video clips of teachers' classroom instruction. Teachers' views on the state and conditions of their work, the official curriculum, adequacy of instructional time, and the value of extant professional development programs are examined against views espoused by Ministry officials. The study suggests that despite the promise of learner-centered teaching, and policy reforms in Kenya promoting constructivist pedagogy, the future of constructivist pedagogies is yet to be secured. It enumerates the threats to learner-centered teaching that left unresolved may lead to an inaccurate conclusion that constructivist teaching is not possible or suitable for schools outside Western traditions. The study suggests a need to re-think current conceptualizations of poverty and its assumed role in educational investment choices among rural communities. It suggests a paradigm shift in how policymakers and education officials engage with rural schools, particularly in communities where schooling has been slow to take off. To secure constructivist pedagogy, the study recommends re-thinking professional development to make it targeted, cyclical, school-based, and more responsive to expressed teacher needs rather than one that is generic, spotty, punitive, and leads to marginalization and isolation of teachers. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Barriers; Case Studies; Constructivism (Learning); Educational Policy; Educational Practices; Focus Groups; Foreign Countries; Interviews; Journal Writing; Kenya; Misconceptions; Observation; Poverty; Primary Education; Professional Development; Qualitative Research; Rural Education; Rural Schools; Student Centered Curriculum; Teacher Attitudes; Teaching Methods

Examinations as an Instrument for Strengthening Pedagogy: Lessons from Three Decades of Experience in Kenya - Wasanga, Paul; Somerset, Anthony (Examinations as an Instrument for Strengthening Pedagogy: Lessons from Three Decades of Experience in Kenya, 2013)
This paper starts with an analysis of the twin purposes of an examination reform programme originally launched in Kenya during the 1970s: first, to broaden the spectrum of cognitive skills being tested; and second, to set up a feedback system based on the performance profiles, providing schools and teachers with guidance as to how pedagogy and learning might be strengthened. Then, in a change of time perspective, the paper looks back over 30 years of implementation experience, examining the reasons why some components of the original programme have proved more sustainable than others. A final section discusses three key issues which have emerged in recent years, and considers their implications for policy.
Keywords: Change; Educational Change; Educational History; Educational Quality; Elementary Education; English; Exit Examinations; Feedback (Response); Foreign Countries; Kenya; Knowledge Level; Newsletters; Private Schools; Test Bias; Test Construction; Test Format; Thinking Skills; Writing Tests

Investing in preschool programs - Duncan, Greg J.; Magnuson, Katherine (The Journal of Economic Perspectives: A Journal of the American Economic Association, 2013)

Education and Training Sector Strategy Paper (2013-2020) - Ministry of the Economy, Planning and Regional Development (Government of Cameroon, 2013)

Investigating the Quality of Postgraduate Research in African Universities Today: A Qualitative Analysis of External Examination Reports - Mulinge, Munyae; Arasa, Josephine (International Journal of Arts and Commerce, 2013)
Keywords: ⛔ No DOI found

Official bilingualism and field narratives: Does school practice echo policy discourse? - Nana, Genevoix (International Journal of Bilingual Education and Bilingualism, 2013)
This research builds on several layers of meaning representing views from education officials, head teachers, teachers and pupils to investigate the discourse and implementation of official bilingualism policy in primary schools in Cameroon. While at the macro-level, the celebration of the "National Bilingualism Day" in schools has tended to suggest that the country's option for bilingualism is a success, at the micro-level, views from the participants researched indicate that the implementation of official bilingualism policy is still far from a reality. The exploration of participants' views at various levels showed how they grounded their accounts within the context of everyday practice and highlighted issues related to official bilingualism inefficiency, although statistics at a national level rather point to an apparent success of the policy in schools. While some adults seemed to operate double standards regarding their perception of policy application, the pupils' views were more straightforward, based on the evidence of classroom daily teaching and learning interaction. (Contains 9 figures and 19 notes.)
Keywords: Administrator Attitudes; Bilingualism; Cameroon; Discourse Analysis; ERIC, Current Index to Journals in Education (CIJE); Educational Policy; Elementary Education; English (Second Language); Evidence; Foreign Countries; French; Interviews; Language of Instruction; Second Language Learning; Student Attitudes; Teacher Attitudes

"This is no French school": Language and education traditions in primary schooling in Cameroon - A comparative perspective - Nana, Genevoix (Research in Comparative and International Education, 2013)
This study draws on the concepts of instrumental and expressive orders to analyse school practice in two Anglophone and two Francophone primary schools in Cameroon, and how micro processes of language socialisation in the schools studied instantiated Anglophone and Francophone education traditions and related to macro processes of systems of education. Using a multimodal method of data collection, including participant observation, focus group and individual interviews, the study adopts a vertical case study approach which corresponds to Bernstein's down-top data collection and analysis approach of research in schools, and draws its comparative stance from the contextualisation of studied cases as a microcosm of global education practice. The study considers the pupils, their classroom, their school, the language that they are socialised into, and the culture that it mediates as units of analysis, and participant observation as a research method into the social life of pupils and their school that seeks to gain an insight into the intricacy of studied phenomenon from the comparative perspective of the dialectic of the local and the global.
Keywords: Administrative Organization; African Languages; Bilingual Education; Cameroon; Case Studies; Case study; ERIC, Current Index to Journals in Education (CIJE); Educational Administration; Educational Practices; Elementary Education; Elementary School Students; English (Second Language); Focus Groups; Focus groups; Foreign Countries; Foreign Policy; Foundations of Education; French; Interviews; Language Role; Language Usage; Language of Instruction; Participant Observation; Participant observation; Qualitative research; Second Language Learning; Socialization

The Basic Education Act, 2013 - Republic of Kenya (2013)

Teaching in linguistically diverse classrooms: difficulties in the implementation of the language-in-education policy in multilingual Kenyan primary school classrooms. - Nyaga, Susan; Anthonissen, Christine (Teaching in linguistically diverse classrooms: difficulties in the implementation of the language-in-education policy in multilingual Kenyan primary school classrooms., 2012)
Kenya’s language-in-education policy supports mother-tongue education as the ideal approach to developing language and literacy skills of young learners. The policy has been informed by findings of various past national education commissions as well as international declarations such as the UNESCO declaration on the use of Vernacular Languages in Education of 1953, the World Declaration on Education for All of 1990 and the Dakar framework of 2000. The country’s Constitution of 2010 re-affirms this policy. However, available reports indicate that little progress has been made in implementing the use of Kenyan mother tongues in education. This paper reports on impressions gained in the process of collecting and analysing data for a doctoral study still in progress. Preliminary findings indicate that in most urban and peri-urban schools, where the learner population is highly multilingual, the policy has been implemented in such a way that in effect either the notion of ‘mother tongue’ seems to have been redefined or the term is used in an unconventional way. Even in rural areas where, comparatively, there is minimal diversity, practical aspects of the use of mother tongue in education seem not to be in accordance with policy provisions. Learning materials and assessment systems are not suitably structured to enable mother-tongue education to take place. The paper (1) gives an impression of the status quo regarding use of language in multilingual primary school classrooms in Kenya, (2) considers the different interpretations given to the term ‘mother tongue’ in current classroom practices and (3) provides pointers to the gap between de jure and de facto policy, which may eventually be helpful in improving the implementation of the current language-in-education policy, in such a way that it will strengthen mother-tongue literacy and facilitate eventual transfer to English as medium of instruction.
Keywords: Education for All (Project); Kenya; Language policy; Multilingual education; Native language instruction; UNESCO

Parental aspirations for their children's educational attainment and the realisation of universal primary education (UPE) in Kenya: Evidence from slum and non-slum residences - Oketch, Moses; Mutisya, Maurice; Sagwe, Jackline (Parental aspirations for their children's educational attainment and the realisation of universal primary education (UPE) in Kenya: Evidence from slum and non-slum residences, 2012)
Abstract: There is a sound research base attesting to the importance of parental involvement and to the many potential benefits it can offer for children''s education. This study sought to examine differences in parental aspirations (as a mechanism of parental involvement in their children''s education) for their children''s educational attainment between slum and non-slum residing parents in Kenya. The study used cross-sectional household data for a sample of 4065 parents, collected in 2007 by the African Population and Health Research Centre (APHRC) in Nairobi. A multinomial logistic model was used for the analysis to explore the factors determining parental aspirations. The results indicate the following: (i) that parents who live in the slums have lower aspirations for their children''s educational attainment when compared to those who live in non-slum areas; (ii) that parents in the slums have aspirations for higher levels of educational attainment for their children than their own levels of education. We conclude that parents in urban Kenya have a strong belief in the education of their children irrespective of their slum or non-slum residence but aspirations are higher in non-slums than in slums.
Keywords: Cross-sectional method; Educational attainment; Kenya; Mathematical models; Parent participation in primary education; Primary education; Slums

Parental aspirations for their children's educational attainment and the realisation of universal primary education (UPE) in Kenya: Evidence from slum and non-slum residences - Oketch, Moses; Mutisya, Maurice; Sagwe, Jackline (Parental aspirations for their children's educational attainment and the realisation of universal primary education (UPE) in Kenya: Evidence from slum and non-slum residences, 2012)
Abstract: There is a sound research base attesting to the importance of parental involvement and to the many potential benefits it can offer for children''s education. This study sought to examine differences in parental aspirations (as a mechanism of parental involvement in their children''s education) for their children''s educational attainment between slum and non-slum residing parents in Kenya. The study used cross-sectional household data for a sample of 4065 parents, collected in 2007 by the African Population and Health Research Centre (APHRC) in Nairobi. A multinomial logistic model was used for the analysis to explore the factors determining parental aspirations. The results indicate the following: (i) that parents who live in the slums have lower aspirations for their children''s educational attainment when compared to those who live in non-slum areas; (ii) that parents in the slums have aspirations for higher levels of educational attainment for their children than their own levels of education. We conclude that parents in urban Kenya have a strong belief in the education of their children irrespective of their slum or non-slum residence but aspirations are higher in non-slums than in slums.
Keywords: Cross-sectional method; Educational attainment; Kenya; Mathematical models; Parent participation in primary education; Primary education; Slums

Kenyan Student Club Takes Reading Further. - Muthiga, Margaret (Kenyan Student Club Takes Reading Further., 2012)
The article offers information on the Reading Club of the Kilimo Primary School in Kenya, which visited the Haven of Hope children's home on the Orphans Day on June 1, 2012. It states that the Reading Club has helped the children to improve their academic performance and reading skills. It mentions that the teachers of the school focus on stimulating the ordinary people to unusual effort towards reading.
Keywords: Academic achievement; Book clubs (Discussion groups); Civic and Social Organizations; Kenya; Primary schools; Reading associations

ICTs as placed resources in a rural Kenyan secondary school journalism club. - Kendrick, Maureen; Chemjor, Walter; Early, Margaret (ICTs as placed resources in a rural Kenyan secondary school journalism club., 2012)
In this study, we draw on three interrelated concepts, i.e. placed resources, multiliteracies and the carnivalesque, to understand how information and communication technology (ICT) resources are taken up within the context of a print-based journalism club. Our research participants attend an under-resourced girls’ residential secondary school in rural Kenya. We used ethnographic methods to document how the 32 club members (aged 14–18 years) used digital cameras, voice recorders and laptops with connectivity to research, conduct interviews, photograph and create texts. Key findings include shifts in identity performance, journalistic competence, and hierarchical distinctions and societal power; growing writer activism and audiences; and the emergence of imagined identities and transformative social futures. Our research challenges current skills-based approaches to introducing new literacies and highlights how the introduction of new ICT resources, when situated within collaborative practices (both research and pedagogical), can result in enhanced literacy learning and text production. These changes have not been without tensions and dilemmas, including the extent to which such practices could only occur outside the formalized classroom with its traditional practices, structures and emphasis on exam results. In addition, some of these tensions raise new questions about the role of ICTs as pedagogical tools and the tendency to ‘romanticize’ their potential.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Australia; Education; Educational Support Services; Electronic services; Elementary and Secondary Schools; Information & communication technologies; Information technology; Kenya; School journalism; Secondary education

‘I use my mother tongue at home and with friends – not in school!’ Multilingualism and identity in rural Kenya. - Spernes, Kari (‘I use my mother tongue at home and with friends – not in school!’ Multilingualism and identity in rural Kenya., 2012)
The present paper investigates students’ experiences of being multilingual. Qualitative data have been collected during observation, focus groups, interviews and text writing in a public primary school in rural Kenya. The informants are students in standards one, three and eight whose mother tongue is the indigenous language called Nandi, which all these students use at home and with friends. The school languages are Swahili and English, and the use of Nandi is forbidden in school except in mother-tongue lessons in standards one to three. The aim of the study is to explore the students’ experiences of being multilingual, and to analyse how the prohibition against the use of the mother tongue in school may influence their identity. The data are interpreted in the light of research and theory concerned with the influence of the colonisation of education in Africa and the effect of languages on identity. Results indicated that the students are proud of their vernacular language and culture, but also see the importance of being multilingual in a global world. The students agree with the prohibition against the use of their mother tongue in school, and understand that English and Swahili are important for education. The conclusion constitutes a critical contribution to add to earlier research about multilingualism and education in Africa.
Keywords: Group identity; Imperialism; Kenya; Multilingualism; Native language; Students & society

Of gateways and gatekeepers: Language, education and mobility in francophone Africa - Trudell, Barbara (Of gateways and gatekeepers: Language, education and mobility in francophone Africa, 2012)
Abstract: Over the past 15 years, a range of alternative education programs have been launched in Burkina Faso. The programs have been developed primarily by international or national NGOs, within a supportive policy space provided by the national government. They aim to respond to the widely recognized inadequacy of the French-language écoles classiques to provide a meaningful primary education experience for most Burkinabè children. One of the values which these programs all espouse is support for the lived realities of Burkinabè communities, particularly the communities that are least well served by the traditional school system. This value is reflected in, among other things, the use of the learner''s mother tongue as a gateway to effective learning. However the influence of the French-dominated educational system is evident in the curriculum choices made in these programs; clearly, success in that system is a crucial step in navigating one''s way past the social and economic gatekeepers of success in Burkina Faso. Thus language is seen as both gateway and gatekeeper, depending on its role in facilitating academic success or inhibiting social mobility. This paradoxical allegiance to both local realities and the colonially established education system has led to the development of bilingual education models which are at variance with the models promoted by theorists in the North. This paper examines several of these programs in the context of larger issues of mobility, literacy, language and culture in francophone Africa.
Keywords: Alternative education; Burkina Faso; Educational programs; Foreign language education; French-speaking Africa; Gatekeepers; Gateways (Computer networks); Internet Publishing and Broadcasting and Web Search Portals; Language Schools; Social mobility

Evaluation of Library Utilization by Students Enrolled in External Degree Programme in University of Nairobi, Kenya - Gor, Peter Ochieng (Evaluation of Library Utilization by Students Enrolled in External Degree Programme in University of Nairobi, Kenya, 2012)
With the increasing popularity of distance education, focus has turned to the role of libraries in distance learning process. It is widely agreed that like their campus-based counterparts, distance education learners need adequate library services if they are to gain quality education. This study sought to examine library utilization by students enrolled in the external degree programme of the University of Nairobi. The unit of analysis consisted of students from the school continuing education and distance studies enrolled in Bachelor of Education Arts (B. Ed Arts) Bachelor of Education (B.ED-Science) and Bachelor of Commerce (B. com) which is basically offered through distance learning. The sample population comprised of 278 students out of 1000 that formed the target population of students and all the 14 librarians spread across the university branch libraries. Self-administered questionnaires and structured interview schedule were used as the main tools of data collection. The finding of the study indicated that effective utilization of library service is influenced by a number of factors. These include enhanced usage of the library facility like making good use of book loan service, frequent access to the library facility, adequate support from the library staff and proper induction by librarians. As a result of the research finding, some conclusions were drawn. The majority of the students were not satisfied with most of the library services offered by the central library. This was attributed to factors such as restrictive library hours, distance, lack of services at the regional centers and inadequate reading materials. The study also revealed that the University of Nairobi was still at the infancy stage of establishing internet-based service thus a hindrance to effective utilization of the library service. The library staff-recruitment and training in distance education was still wanting. Finally this study had the following recommendations: Firstly there is need to promote access to library services to distance learning student population by strengthening computer based and information service delivery, instituting library user instruction to instill effective information literacy skills and ensuring reliable, rapid access to institutional networks and the internet. There is also the need to come up with special collection targeting the distance learning community. Effective learning in the University is a collaborate effort between curriculum planners, implementers, administrators and thus in order to provide library support services to distance learners, there is need for policy guidelines to identify types and availability of the library services as well as funding service providers and targeted users.
Keywords: Academic Libraries; Access to Information; Distance Education; External Degree Programs; Foreign Countries; Internet; Kenya (Nairobi); Librarians; Library Services; Questionnaires; Structured Interviews; Undergraduate Students; Use Studies; User Satisfaction (Information)

What explains gender gaps in maths achievement in primary schools in Kenya? - Ngware, Moses W.; Ciera, James; Abuya, Benta A.; Oketch, Moses; Mutisya, Maurice (What explains gender gaps in maths achievement in primary schools in Kenya?, 2012)
This paper aims to improve the understanding of classroom-based gender differences that may lead to differential opportunities to learn provided to girls and boys in low and high performing primary schools in Kenya. The paper uses an opportunity to learn framework and tests the hypothesis that teaching practices and classroom interactions explain gender gaps in maths achievement in Kenya. The data used is obtained from a cross sectional study involving video recordings of 70 lessons in mathematics, students’ scores in a maths test and interviews with subject teachers in Kenyan primary schools randomly selected from six districts. Results show that gender gaps in maths achievement are more evidenced in the area of measurement. The gaps are more pronounced among low achievers in favour of boys. The most revealing finding is that entry achievement level is the main source of gender gaps in maths learning outcomes, implying that girls start at lower levels than boys and this gap is not closed by school. The policy implication to education is that boys have better chances of transition to secondary school and tertiary levels than girls, and consequently, there are broader gender disparities than can be closed by pro-gender education policies.
Keywords: Academic achievement; Cross-sectional method; Gender differences (Psychology) in children; Kenya; Mathematics education (Primary); Outcome assessment (Education); Primary schools

Patterns of teaching style and active teaching: do they differ across subjects in low and high performing primary schools in Kenya? - Ngware, Moses W.; Mutisya, Maurice; Oketch, Moses (Patterns of teaching style and active teaching: do they differ across subjects in low and high performing primary schools in Kenya?, 2012)
This paper focuses on the patterns of teaching styles and active teaching across subjects and between low and high performing schools in an attempt to examine what accounts for differences in performance between schools which are within the same locality. It uses data collected in 72 primary schools spread across six districts in Kenya. Video recordings of 213 lessons in maths (72), science (71) and English (70), and interviews with subject teachers in primary schools, were used to generate evidence on patterns of teaching styles and active teaching. Results show that teaching practice across subjects is inclined towards the command and task styles that do not promote critical thinking among learners. The dominant teaching activity was individual seat work in maths lessons; recitation in English lessons; and whole class chorus in science lessons. Overall, active teaching accounted for 62% of the lesson time. The one way ANOVA results show insignificant variation between subjects and school category on active teaching, and therefore this may not be the source of differential performance between low and high performing schools.
Keywords: All Other Miscellaneous Schools and Instruction; Critical thinking; Direct instruction; Elementary and Secondary Schools; Kenya; Primary schools; Schools; Teaching methods

The effect of active teaching and subject content coverage on students’ achievement: evidence from primary schools in Kenya. - Oketch, Moses; Mutisya, Maurice; Sagwe, Jackline; Musyoka, Peter; Ngware, Moses W. (The effect of active teaching and subject content coverage on students’ achievement: evidence from primary schools in Kenya., 2012)
There is a growing public concern in Kenya over the persistent gap between those schools that are consistently ranked at the top and those ranked at the bottom of the annual Kenya Certificate of Primary Education (KCPE) examination league tables. This has raised the issue of inequality in educational opportunity. Our primary concern in this paper is to understand some of the classroom–school factors that may explain the persistent differences in achievement between the top and bottom schools. We focus on time-on-task (the length of exposure to any particular teaching and learning task) and curriculum content, and ask whether this explains the difference in performance. We test the following hypotheses: differences exist on teachers’ time-on-task between low and high performing schools; greater teacher time-on-task has a positive effect on student gain score; and greater content coverage has a positive effect on student achievement. For the student achievement gains, we use item response theory test scores of 1889 Grade 6 pupils from 70 schools in Kenya. Data on time-on-task were generated from 70 maths lessons observed in these schools, while content coverage was developed from students’ maths note books for the entire period they were in Grade 6. The study was conducted by a team of researchers at the African Population and Health Research Center (APHRC) with funding from Google.org. Using two level hierarchical modelling, we control for pupil, teacher and school factors. Results show that exposure to content is positively correlated with pupil gain scores (gain score is the difference in score between test at time t1 and test at time t2 of the same pupil taught by the same teacher). Maths teachers in both bottom and top performing schools spend the same proportion of time-on-task. However, we do not find that time-on-task is related to achievement in this sample.
Keywords: Academic achievement; All Other Miscellaneous Schools and Instruction; Direct instruction; Elementary and Secondary Schools; Kenya; Learning ability; Mathematics teachers; Primary schools; Schools

Early Primary Literacy Instruction in Kenya. - DUBECK, MARGARET M.; JUKES, MATTHEW C. H.; OKELLO, GEORGE (Early Primary Literacy Instruction in Kenya., 2012)
We report on a study that used observations, conversations, and formal interviews to explore literacy instruction in 24 lower-primary classrooms in coastal Kenya. Specifically, we report the ways literacy instruction is delivered and how that delivery aligns with practices understood to promote reading acquisition. We find (1) prioritization of developing oral language skills over teaching the relationships between sounds and symbols, (2) enablers to literacy instruction that are the result of teachers' efforts, and (3) constraints to successful literacy instruction as perceived by the teachers. We identify challenges and opportunities to improve literacy instruction in English and Swahili.
Keywords: All other schools and instruction; English language; Exam Preparation and Tutoring; Kenya; Literacy programs; Oral communication; Primary education; Swahili language

Early Primary Literacy Instruction in Kenya - Dubeck, Margaret M.; Jukes, Matthew C. H.; Okello, George (Early Primary Literacy Instruction in Kenya, 2012)
We report on a study that used observations, conversations, and formal interviews to explore literacy instruction in 24 lower-primary classrooms in coastal Kenya. Specifically, we report the ways literacy instruction is delivered and how that delivery aligns with practices understood to promote reading acquisition. We find (1) prioritization of developing oral language skills over teaching the relationships between sounds and symbols, (2) enablers to literacy instruction that are the result of teachers' efforts, and (3) constraints to successful literacy instruction as perceived by the teachers. We identify challenges and opportunities to improve literacy instruction in English and Swahili. (Contains 2 footnotes.)
Keywords: Alignment (Education); Delivery Systems; Discourse Analysis; Educational Practices; Elementary Education; Emergent Literacy; Foreign Countries; Interviews; Kenya; Language Skills; Literacy; Observation; Oral Language; Performance Factors; Reading Achievement; Reading Instruction; Teacher Behavior; Teaching Methods

Little by Little: Global Citizenship through Local Action Inspired by Wangari Maathai - Christie, Erica M.; Montgomery, Sarah E.; Staudt, Jessica (Little by Little: Global Citizenship through Local Action Inspired by Wangari Maathai, 2012)
Dr. Wangari Maathai--"environmentalist, human rights advocate, global peace worker, and community builder"--passed away in 2011. The first African woman to receive the Nobel Peace Prize, Dr. Maathai left a legacy even greater than the 47 million trees that her organization, the Greenbelt Movement, has planted across Kenya since 1977. As the Nobel Prize committee lauded in 2004, "She has taken a holistic approach to sustainable development that embraces democracy, human rights and women's rights in particular. She thinks globally and acts locally." Like Dr. Maathai, Iowa teacher Jessica Staudt seeks to encourage global thinking and local action in her fourth-grade classroom. To honor and share Dr. Maathai's legacy, Jessica developed a service-learning project that integrates critical literacy and social studies themes to promote an active, global vision of citizenship. Service learning, an educational strategy that purposefully connects academic curriculum with community service and student reflection, is an apt vehicle to encourage global thinking and empower students to take action. Dr. Maathai serves as a fitting and unique role model for a service-learning project, providing a compelling example of global citizenship at work. (Contains 5 online resources and 8 notes.)
Keywords: Advocacy; Art Activities; Art Expression; Blacks; Citizenship; Citizenship Education; Civil Rights; Community Services; Critical Literacy; Democracy; Elementary School Students; Females; Foreign Countries; Global Approach; Global Education; Grade 4; Holistic Approach; Iowa; Kenya; Popular Culture; Reflection; Role Models; School Community Programs; School Community Relationship; School Vandalism; Service Learning; Social Studies; Sustainable Development; Vandalism; Visual Arts

Teacher Education in Sub-Saharan Africa: Closer Perspectives - Griffin, Rosarii (Symposium Books, 2012)
In the drive to achieve universal primary education as one of the Millennium Development Goals, there is an increasing recognition of the urgency of focusing on teacher education to both meet the demand for more than one million qualified teachers required to achieve this goal within sub-Saharan Africa, as well as to combat the sometimes poor quality educational experience reported in the school. Currently, approximately only one third of teachers are qualified to teach. This dearth in qualified teachers also means that secondary and tertiary education need to be improved upon to provide an educated cohort of graduates. This in turn will ensure that the quality of teacher trained and retained within the profession is of a sufficiently high standard to ensure sustainable progress. This volume focuses on the various aspects of teacher education which need to be addressed in order for the wider Millennium Goals to be achieved, but more importantly, so that each African child living within sub-Saharan Africa will have the right to a quality education: ensuring they too experience their right and entitlement as children to reach their full potential--often taken for granted in Western countries--giving African children the necessary tools to build a better future for themselves. Of particular interest to the education researcher and policy maker, this volume's contributors look at the various issues and challenges around the teacher profession, particularly in relation to resources and practices within sub-Saharan Africa. The contributors examine the issue of building research capacity for educational research within teacher education Colleges and explore the concept of education for sustainable development with the view to improving the development of quality teacher education within the global South. In this volume, research reports are presented highlighting the various challenges within the structure and provision of teacher education within certain national contexts, including assessment and curricula issues, which need to be addressed. This volume goes from the global to the local and examines teacher educator teaching, learning and reflective practice issues within different contexts, as well as exploring alternative pre-service experiences for western teachers who wish to work within the sub-Saharan context as well as some teacher educator exchange programmes between the South and North. Case countries explored include Lesotho, South Africa, Mozambique, Uganda, Kenya, Tanzania and Madagascar, to mention but a few. Of particular value to the education researcher and policy maker, this book provides a timely resource focusing on an area of neglect, highlighting the central role of the teacher and teacher education towards sustainable development within the sub-Saharan African context. This book is divided into three parts. First, International and National Discourses on Teacher Education, contains the following: (1) Education as a Humanitarian Response as Applied to Teachers and Their Training in Sub-Saharan Africa (Colin Brock); (2) Teacher Education in Sub-Saharan Africa: Issues and Challenges around Teacher Resources and Practices (Bob Moon & Freda Wolfenden); (3) Contradictions in Teacher Education and Teacher Professionalism in Sub-Saharan Africa: The Case of South Africa (Clive Harber); (4) What Hope for the Dakar Goals? The Lower Levels of Education in Lesotho and Uganda since 2000 (James Urwick & Rosarii Griffin with Veronica Opendi & Matemoho Khatleli); (5) A Critical Overview of Education for Sustainable Development with Particular Focus upon the Development of Quality Teacher Education in Sub-Saharan Africa (David Stephens); and (6) Building Capacity for Educational Research in Sub-Saharan Africa: Opportunities, Constraints and Lessons in the Context of Mozambique, Tanzania and Uganda (Peadar Cremin, Mary Goretti Nakabugo & Eimear Barrett). Second, Case Country Research Reports on Aspects of Teacher Education in Sub-Saharan Africa, contains the following: (7) Towards a Holistic Understanding of Special Educational Needs (Jacqui O'Riordan, James Urwick, Stella Long & Maria Campbell); (8) The Teaching and Learning of Mathematics in Ugandan Secondary Schools: Poised for Change? (Paul Conway, Elizabeth Oldham, James Urwick, Sarah Kisa, Justine Otaala & Anne Mugwera); (10) Implementing the Thematic Curriculum in Uganda: Implications for Teacher Education (Marty Holland, Louise Long & Laura Regan); and (11) How Much Is Enough? Investigating Mathematical Knowledge for Primary Teaching in Lesotho (Dolores Corcoran & Anne Dolan). Third, Teacher Education at the Chalkface: Closer Perspectives, contains the following: (12) Teacher Educators and Teaching, Learning and Reflective Practice among the Turkana Nomads of Kenya (Thomas G. Grenham); (13) An Account of the Alternative Education Experience Africa Programme in Transition: Irish Pre-Service Teachers' Experience in Zambia and the Gambia (Fiona Baily & Deirdre O'Rourke); and (14) Teacher Educator Exchange Partnership in Uganda and Ireland: Closer Perspectives on Teacher Education in Sub-Saharan Africa (Patricia Kieran, Carmel Hinchion, Doris Kaije, Ruth Kyambadde & Paddy Bradley).
Keywords: Academic Achievement; Capacity Building; Case Studies; Developing Nations; Educational Development; Educational Needs; Educational Policy; Educational Quality; Educational Research; Elementary Education; Exchange Programs; Foreign Countries; Gambia; Holistic Approach; International Education; International Organizations; Ireland; Kenya; Lesotho; Madagascar; Mathematics Education; Migrants; Mozambique; Nontraditional Education; Partnerships in Education; Pedagogical Content Knowledge; Preservice Teacher Education; Reflective Teaching; Research Needs; Research Reports; Role of Education; Secondary School Mathematics; South Africa; Special Education; Sustainable Development; Tanzania; Teacher Education Curriculum; Teacher Education Programs; Teacher Educators; Teacher Effectiveness; Teacher Qualifications; Thematic Approach; Uganda; Zambia

Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics - Kiboss, Joel Kipkemboi (Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics, 2012)
Achievement in mathematics is an issue of great concern not only to students and parents but also to employers and researchers in Kenya. This is because the Kenya National Examination Council (KNEC) has continuously reported dismal results in this area, and especially in geometry. Also, KNEC indicates that it presents difficulties to both the teachers and learners during instructional sessions. In an extension of research demonstrating causal effects of electronic learning environments on special education learners' achievement and perceptions of mathematics instruction, the present study experimentally examined the effectiveness of a special electronic learning program (SELP) to improve hearing-impaired learners' achievement of basic geometry and their perception of the Geometry learning environment. Sixty-six hearing-impaired learners from four special education schools situated in Rift Valley province were sampled purposively on the basis of the school's accessibility to participate in the study. The study employed the Solomon-Four Group Design research method. The specific dependent measures were the learners' achievement in geometry and their perception of the classroom learning environment. Measurement of achievement and perception were conducted using two instruments: (i) the Geometry Achievement Test (GAT), and (ii) the Special Learners Classroom Environment Questionnaire (SLCEQ). GAT's reliability was computed using K-R20 formula yielding a reliability of 0.78. On the other hand, SLCEQ reliability was determined using Cronbach alpha yielding a reliability coefficient of 0.82. The study established that SELP was modestly effective in improving the achievement of hearing-impaired learners on geometry and their perception of the classroom environment. The study concludes that teachers can arrest the special learners' problem of poor performance in geometry through the use of electronic learning programs. (Contains 7 tables and 11 figures.)
Keywords: Achievement Tests; Assistive Technology; Attitude Measures; Classroom Environment; Computer Assisted Instruction; Computer Interfaces; Control Groups; Courseware; Developing Nations; Electronic Learning; Elementary School Students; Experimental Groups; Foreign Countries; Geometry; Hearing Impairments; High Stakes Tests; Instructional Design; Instructional Effectiveness; Kenya; Mathematics Achievement; Mathematics Instruction; Mathematics Tests; Multimedia Instruction; National Competency Tests; Predictor Variables; Pretests Posttests; Programming; Quasiexperimental Design; Questionnaires; Reliability; Sign Language; Special Education; Special Needs Students; Student Attitudes

What Explains Gender Gaps in Maths Achievement in Primary Schools in Kenya? - Ngware, Moses W.; Ciera, James; Abuya, Benta A.; Oketch, Moses; Mutisya, Maurice (What Explains Gender Gaps in Maths Achievement in Primary Schools in Kenya?, 2012)
This paper aims to improve the understanding of classroom-based gender differences that may lead to differential opportunities to learn provided to girls and boys in low and high performing primary schools in Kenya. The paper uses an opportunity to learn framework and tests the hypothesis that teaching practices and classroom interactions explain gender gaps in maths achievement in Kenya. The data used is obtained from a cross sectional study involving video recordings of 70 lessons in mathematics, students' scores in a maths test and interviews with subject teachers in Kenyan primary schools randomly selected from six districts. Results show that gender gaps in maths achievement are more evidenced in the area of measurement. The gaps are more pronounced among low achievers in favour of boys. The most revealing finding is that entry achievement level is the main source of gender gaps in maths learning outcomes, implying that girls start at lower levels than boys and this gap is not closed by school. The policy implication to education is that boys have better chances of transition to secondary school and tertiary levels than girls, and consequently, there are broader gender disparities than can be closed by pro-gender education policies. (Contains 7 tables.)
Keywords: Achievement Gap; Classroom Environment; Educational Policy; Elementary School Mathematics; Elementary School Students; Females; Foreign Countries; Gender Differences; Interaction; Kenya; Low Achievement; Males; Mathematics Achievement; Mathematics Tests; Scores

Patterns of Teaching Style and Active Teaching: Do They Differ across Subjects in Low and High Performing Primary Schools in Kenya? - Ngware, Moses W.; Mutisya, Maurice; Oketch, Moses (Patterns of Teaching Style and Active Teaching: Do They Differ across Subjects in Low and High Performing Primary Schools in Kenya?, 2012)
This paper focuses on the patterns of teaching styles and active teaching across subjects and between low and high performing schools in an attempt to examine what accounts for differences in performance between schools which are within the same locality. It uses data collected in 72 primary schools spread across six districts in Kenya. Video recordings of 213 lessons in maths (72), science (71) and English (70), and interviews with subject teachers in primary schools, were used to generate evidence on patterns of teaching styles and active teaching. Results show that teaching practice across subjects is inclined towards the command and task styles that do not promote critical thinking among learners. The dominant teaching activity was individual seat work in maths lessons; recitation in English lessons; and whole class chorus in science lessons. Overall, active teaching accounted for 62% of the lesson time. The one way ANOVA results show insignificant variation between subjects and school category on active teaching, and therefore this may not be the source of differential performance between low and high performing schools. (Contains 12 tables and 2 figures.)
Keywords: Academic Achievement; Achievement Gap; Active Learning; Comparative Analysis; Critical Thinking; Elementary School Teachers; Elementary Schools; English (Second Language); Foreign Countries; Interviews; Kenya; Mathematics Instruction; Rote Learning; Science Instruction; Second Language Instruction; Statistical Analysis; Teacher Attitudes; Teacher Characteristics; Teaching Methods; Teaching Styles; Video Technology

Teaching in Linguistically Diverse Classrooms: Difficulties in the Implementation of the Language-in-Education Policy in Multilingual Kenyan Primary School Classrooms - Nyaga, Susan; Anthonissen, Christine (Teaching in Linguistically Diverse Classrooms: Difficulties in the Implementation of the Language-in-Education Policy in Multilingual Kenyan Primary School Classrooms, 2012)
Kenya's language-in-education policy supports mother-tongue education as the ideal approach to developing language and literacy skills of young learners. The policy has been informed by findings of various past national education commissions as well as international declarations such as the UNESCO declaration on the use of Vernacular Languages in Education of 1953, the World Declaration on Education for All of 1990 and the Dakar framework of 2000. The country's Constitution of 2010 re-affirms this policy. However, available reports indicate that little progress has been made in implementing the use of Kenyan mother tongues in education. This paper reports on impressions gained in the process of collecting and analysing data for a doctoral study still in progress. Preliminary findings indicate that in most urban and peri-urban schools, where the learner population is highly multilingual, the policy has been implemented in such a way that in effect either the notion of "mother tongue" seems to have been redefined or the term is used in an unconventional way. Even in rural areas where, comparatively, there is minimal diversity, practical aspects of the use of mother tongue in education seem not to be in accordance with policy provisions. Learning materials and assessment systems are not suitably structured to enable mother-tongue education to take place. The paper (1) gives an impression of the status quo regarding use of language in multilingual primary school classrooms in Kenya, (2) considers the different interpretations given to the term "mother tongue" in current classroom practices and (3) provides pointers to the gap between "de jure" and "de facto" policy, which may eventually be helpful in improving the implementation of the current language-in-education policy, in such a way that it will strengthen mother-tongue literacy and facilitate eventual transfer to English as medium of instruction. (Contains 4 notes and 5 excerpts.)
Keywords: African Languages; Doctoral Dissertations; Educational Policy; Elementary School Students; English (Second Language); Foreign Countries; Instructional Materials; Kenya; Language Acquisition; Language Usage; Language of Instruction; Literacy; Multilingualism; Rural Areas; Second Language Learning; Student Evaluation; Urban Schools

The Effect of Active Teaching and Subject Content Coverage on Students' Achievement: Evidence from Primary Schools in Kenya - Oketch, Moses; Mutisya, Maurice; Sagwe, Jackline; Musyoka, Peter; Ngware, Moses W. (The Effect of Active Teaching and Subject Content Coverage on Students' Achievement: Evidence from Primary Schools in Kenya, 2012)
There is a growing public concern in Kenya over the persistent gap between those schools that are consistently ranked at the top and those ranked at the bottom of the annual Kenya Certificate of Primary Education (KCPE) examination league tables. This has raised the issue of inequality in educational opportunity. Our primary concern in this paper is to understand some of the classroom-school factors that may explain the persistent differences in achievement between the top and bottom schools. We focus on time-on-task (the length of exposure to any particular teaching and learning task) and curriculum content, and ask whether this explains the difference in performance. We test the following hypotheses: differences exist on teachers' time-on-task between low and high performing schools; greater teacher time-on-task has a positive effect on student gain score; and greater content coverage has a positive effect on student achievement. For the student achievement gains, we use item response theory test scores of 1889 Grade 6 pupils from 70 schools in Kenya. Data on time-on-task were generated from 70 maths lessons observed in these schools, while content coverage was developed from students' maths note books for the entire period they were in Grade 6. The study was conducted by a team of researchers at the African Population and Health Research Center (APHRC) with funding from Google.org. Using two level hierarchical modelling, we control for pupil, teacher and school factors. Results show that exposure to content is positively correlated with pupil gain scores (gain score is the difference in score between test at time t1 and test at time t2 of the same pupil taught by the same teacher). Maths teachers in both bottom and top performing schools spend the same proportion of time-on-task. However, we do not find that time-on-task is related to achievement in this sample. (Contains 1 note and 5 tables.)
Keywords: Academic Achievement; Achievement Gains; Correlation; Course Content; Educational Opportunities; Elementary School Curriculum; Elementary School Students; Foreign Countries; Grade 6; Hypothesis Testing; Item Response Theory; Kenya; Mathematics Achievement; Mathematics Instruction; Mathematics Teachers; Scores; Time on Task

Rethinking Teacher Preparation and Professional Development in Africa: An Analysis of the Curriculum of Teacher Education in the Teaching of Early Reading and Mathematics - Pryor, John; Akyeampong, Kwame; Westbrook, Jo; Lussier, Kattie (Rethinking Teacher Preparation and Professional Development in Africa: An Analysis of the Curriculum of Teacher Education in the Teaching of Early Reading and Mathematics, 2012)
This paper reports research on the initial teacher training and continuing professional development of teachers in six African countries (Ghana, Kenya, Mali, Senegal, Tanzania and Uganda). The focus of the research was on the teaching of early reading and mathematics. The curriculum of both these areas was analysed in terms of (i) implementation by providers such as Colleges of Education, and (ii) impact in schools. The study found that there were many and deep gaps in the curriculum taught and consequently in teacher knowledge and skills in these two crucial subject areas. The paper sets out a series of recommendations for addressing this problem including an overall alternative approach to teacher education that emerges from the research findings as a whole. (Contains 1 note, 11 tables, and 10 figures.)
Keywords: Africa; Curriculum Evaluation; Early Reading; Elementary School Mathematics; Emergent Literacy; Faculty Development; Foreign Countries; Ghana; Kenya; Knowledge Base for Teaching; Mali; Preservice Teacher Education; Program Implementation; Schools of Education; Senegal; Tanzania; Uganda

'I Use My Mother Tongue at Home and with Friends--Not in School!' Multilingualism and Identity in Rural Kenya - Spernes, Kari ('I Use My Mother Tongue at Home and with Friends--Not in School!' Multilingualism and Identity in Rural Kenya, 2012)
The present paper investigates students' experiences of being multilingual. Qualitative data have been collected during observation, focus groups, interviews and text writing in a public primary school in rural Kenya. The informants are students in standards one, three and eight whose mother tongue is the indigenous language called Nandi, which all these students use at home and with friends. The school languages are Swahili and English, and the use of Nandi is forbidden in school except in mother-tongue lessons in standards one to three. The aim of the study is to explore the students' experiences of being multilingual, and to analyse how the prohibition against the use of the mother tongue in school may influence their identity. The data are interpreted in the light of research and theory concerned with the influence of the colonisation of education in Africa and the effect of languages on identity. Results indicated that the students are proud of their vernacular language and culture, but also see the importance of being multilingual in a global world. The students agree with the prohibition against the use of their mother tongue in school, and understand that English and Swahili are important for education. The conclusion constitutes a critical contribution to add to earlier research about multilingualism and education in Africa. (Contains 4 notes.)
Keywords: African Languages; Educational Environment; Elementary School Students; English (Second Language); Family Environment; Focus Groups; Foreign Countries; Foreign Policy; Friendship; Interviews; Kenya; Language Usage; Language of Instruction; Multilingualism; Native Language; Second Language Learning; Self Concept

The Debate on Learning Assessments in Developing Countries - Wagner, Daniel A.; Lockheed, Marlaine; Mullis, Ina; Martin, Michael O.; Kanjee, Anil; Gove, Amber; Dowd, Amy Jo (The Debate on Learning Assessments in Developing Countries, 2012)
Over the past decade, international and national education agencies have begun to emphasize the improvement of the quality (rather than quantity) of education in developing countries. This trend has been paralleled by a significant increase in the use of educational assessments as a way to measure gains and losses in quality of learning. As interest in assessment has grown, low-income countries have begun to adopt and adapt international and other assessments for a variety of uses, including the comparability of national quality with other countries, improved ways of measuring reading achievement, and further attempts to reach marginalized populations within a country. The present group of papers provides multiple perspectives on the debate currently underway about the best approaches to create and use learning assessments in low-income countries. (Contains 7 figures and 9 notes.)
Keywords: Developing Nations; Educational Assessment; Educational Improvement; Educational Policy; Egypt; Elementary Education; Foreign Countries; Gambia; International Programs; Kenya; Liberia; Measurement; Progress in International Reading Literacy Study; Reading Tests; South Africa; Testing Programs; Uruguay; Vietnam

The Dialectics of African Education and Western Discourses: Counter-Hegemonic Perspectives. Black Studies and Critical Thinking. Volume 21 - Wright, Handel Kashope; Abdi, Ali A. (Peter Lang New York, 2012)
The Dialectics of African Education and Western Discourses" addresses how continental Africans who have worked or are currently working in the Canadian academy address their dual legacy of African and Euro-American knowledge paradigms. Reflecting a range of approaches to hegemonic Euro-American paradigms that can be summarized as "appropriation, ambivalence and alternatives," the authors bring African indigenous knowledge and praxes into play in addressing issues in various sub-fields of education from philosophy and gnosis to teacher education and classroom practice, memory work and storying to higher education policy and development studies, language and mathematics pedagogy to giftedness and special education. By simultaneously engaging Western and African worldviews, theory, policy and practice, the twelve essays provide an intervention in and contribution to critical approaches to education as a comprehensive global field and as an aspect of African studies. Contents include: (1) Introducing the Dialectics of African Education and Western Discourses: Appropriation, Ambivalence, and Alternatives (Handel K. Wright and Ali A. Abdi); (2) Eurocentric Discourses and African Philosophies and Epistemologies of Education: Counter-Hegemonic Analyses and Responses (Ali A. Abdi); (3) Ubuntu, African Epistemology and Development: Contributions, Contradictions, Tensions, and Possibilities (Dalene Swanson); (4) Inkumbulo as Remembering, Communing, and Praxis: Retelling the Stories of Transformation and Learning (Nombuso Dlamini); (5) Integrating African Indigenous Knowledge in Kenya's Formal Education System: The Potential for Sustainable Development (Jenipher A. Owuor); (6) Reframing African Higher Education (Michael Kariwo); (7) Re-Culturing Teacher Education in Africa (Musembi Nungu); (8) Reframing and Indigenizing Science Education in Africa (Samson M. Nashon); (9) African Ways of Knowing: Rethinking Pedagogy in Africa (Constantine Ngara); (10) Linguistic Independence and African Education and Development (Edward Shizha); (11) Cultural Games and Mathematics Education in Ghana: A Theoretical Analysis (Michael Nabie); and (12) Is This an African I See Before Me? Black/African Identity and the Politics of (Western, Academic) Knowledge (Handel Kashope Wright).
Keywords: Africa; African Studies; Canada; Change; Education; Educational Philosophy; Educational Policy; Epistemology; Foreign Countries; Ghana; Gifted; Higher Education; Identification; Indigenous Knowledge; Kenya; Learning; Mathematics Education; Memory; Philosophy; Politics; Praxis; Science Education; Special Education; Story Telling; Sustainable Development; Teacher Education

Situational Analysis on the Policies, Practices and Barriers to Inclusive Education in Primary Education Sector in Cameroon. - Tchombe, T.M.S. (2012)

INVESTIGATIONS OF STUDENTS' MOTIVATION TOWARDS LEARNING SECONDARY SCHOOL PHYSICS THROUGH MASTERY LEARNING APPROACH. - Changeiywo, Johnson; Wambugu, P.; Wachanga, S. (INVESTIGATIONS OF STUDENTS' MOTIVATION TOWARDS LEARNING SECONDARY SCHOOL PHYSICS THROUGH MASTERY LEARNING APPROACH., 2011)
Teaching method is a major factor that affects students' motivation to learn physics. This study investigated the effects of using mastery learning approach (MLA) on secondary school students' motivation to learn physics. Solomon four non-equivalent control group design under the quasi-experimental research method was used in which a random sample of 4 co-educational secondary schools was obtained in Kieni East Division of Nyeri District in Kenya. The 4 schools were randomly put into 4 groups. Each school provided 1 Form Two class for the study; hence, a total of 161 students were involved. The students were taught the same physics content. In the experimental groups, MLA teaching method was used while the regular teaching method was used in the control groups. The researchers trained the teachers in the experimental groups on the technique of MLA before the treatment. Two groups were pre-tested prior to the implementation of the MLA treatment. At the end of treatment period, all the 4 groups were post-tested using a validated Students' Motivation Questionnaire, whose reliability coefficient was 0.76. Data were analysed using the t test, analysis of variance and analysis of covariance. The results of the study show that students exposed to MLA have significantly higher motivation than those taught through regular methods. Gender has no significant influence on their motivation to learn physics. The researchers conclude that MLA is an effective teaching method in motivating students; hence, physics teachers should incorporate it in teaching.
Keywords: Academic motivation; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Elementary and Secondary Schools; Kenya; Mastery learning; Physics education; Secondary education

Household-level social capital in Cameroon and children’s schooling: a gender analysis - Tabi Atemnkeng, Johannes (Africa Development, 2011)
This article examines household-level social capital as a determinant of children's schooling using a cross-sectional data of the 2001 Cameroon Household Survey. Reduced form demand equations of schooling for the entire sample, male and female children are estimated separately. Results indicate that parent's education and income strongly influence parental decisions towards a child's schooling. However, social capital, especially in the female dimension, is more important as both male and female children are equally given the opportunity to attend school and there is no gender bias in children's schooling outcome when parents participate in groups or associations. We recommend the building of social capital by creating associations and encouraging females to be actively involved in such associative groups.

Perceptions of Wildlife Parks by Youth Who Live Near Them: A Study in Samburu, Kenya. - Bruyere, Brett L.; Beh, Adam W.; Foster, George (Perceptions of Wildlife Parks by Youth Who Live Near Them: A Study in Samburu, Kenya., 2011)
This study investigated the perceptions of 99 youth from two Samburu, Kenya primary schools about the benefits and impacts of nearby wildlife-based protected areas. Participants responded in writing to two questions which the researchers coded to identify key themes. Building on prior work with youth in the Maasai region of Kenya and adults in Samburu, the study revealed that most youth perceived parks as providing economic benefits related to tourism, showed limited understanding of the conservation benefits, and believed that protected areas create opportunities for undesirable behavior (e.g., poaching, crime) and impacts (e.g., pollution). The authors call for enhanced instruction in science and ecology in schools, and improved outreach to youth by protected area staff.
Keywords: Animal ecology; Habitats; Kenya; Primary schools; School children

Homing In: Mothers at the Heart of Health and Literacy in Coastal Kenya. (Homing In: Mothers at the Heart of Health and Literacy in Coastal Kenya., 2011)
This study includes a critical inquiry into literacy education that takes into account constraints to literacy such as health; an engagement with mothers as the primary caregivers and literacy models for their children; and guidelines for developing literacy interventions that move beyond entrenched modes of thought to promote additive approaches to forming literacy. In this mixed methods study, quantitative reading data from 800-second graders in 40 schools from the U.S.-funded Early Grade Reading Assessment (EGRA) in coastal Kenya were analyzed, then qualitative data were collected and analyzed from mothers in three EGRA treatment schools. Results reinforced the close relationship between adult literacy and child literacy, and particularly the need to work with mothers when aiming to improve child literacy. Home and school literacies need to be connected so that reading can become an indigenous process. Health improvements as part of the environmental layers identified in the home were linked to literacy becoming an indigenous process as well.
Keywords: Health of school children; Mother-child relationship

Worldreader Expands into Kenya. - Albanese, Andrew (Worldreader Expands into Kenya., 2011)
The article reports on the plan of Worldreader, a nonprofit organization aimed at creating reading culture in developing countries through the use of electronic-books (e-books) and electronic-readers (e-readers), to expand its efforts in Kilgoris, Kenya starting May 2011. The organization, which was launched in 2009 by David Risher, Colin McElwee and Mike Sundermeyer, will provide Kindles and e-books to the Intimigon Nursery and Primary School. Information on the achievements and financial status of Worldreader is also given.
Keywords: All other schools and instruction; Electronic books; Exam Preparation and Tutoring; Kenya; Kindle (Electronic book reader); Literacy programs; Nonprofit organizations; Other Social Advocacy Organizations; Reading promotion

From Assessment to Learning: The Teaching of English Beyond Examinations. - Vikiru, Lilian I. (From Assessment to Learning: The Teaching of English Beyond Examinations., 2011)
The backwash of testing on teaching can be positive or negative. This article is based on the findings of a study carried out in Kenya on strengthening the development of literacy in English among primary school children, which established that the learners performed poorly on skills that were not directly tested in the conventional examinations. Interventions used in improving teaching, learning, and assessment to target communicative competence are discussed in the article. Reprinted by permission of the publisher.
Keywords: Communicative competence; English language; English language education; English language education in elementary schools; Evaluation; Foreign language education; Kenya; Learning; Testing

Pupils' environmental awareness and knowledge: A springboard for action in primary schools in Kenya's Rift valley. - Mutisya, Sammy M.; Barker, Miles (Pupils' environmental awareness and knowledge: A springboard for action in primary schools in Kenya's Rift valley., 2011)
This study was carried out with 276 standard eight pupils in eleven primary schools in the rural town of Narok in Kenya's Rift Valley. It evaluated their awareness of key environmental issues in their local area and their knowledge about the causes, effects and solutions pertaining to these environmental issues. A descriptive research design was used and data was collected using the Pupils' Environmental Education Questionnaire (PEEQ). The study found that most pupils were aware of the key environmental issues in their local area and they also understood the causes of some of these environmental issues. The study further found that pupils had ideas about solutions to some of the environmental issues. This data was used as a springboard for exploring ways by which environmental education (EE) in primary schools might capitalise on pupil knowledge, and hence progress towards environmental action taking; and how this might occur through primary school pupils being nurtured into the role of informed decision-makers and action-takers. The study also recommends that EE should be taught both theoretically in class and practically in the environment, providing solutions to local environmental issues. Further, it suggests that primary school teachers' in-service training should include interactive teaching pedagogies to enhancing active teaching and learning of EE. It recommends that Ministry of Education should develop and implement an EE policy which empowers schools (teachers and pupils) and surrounding communities to collaborate in taking action to conserve their immediate environments.
Keywords: Environmental literacy; Great Rift Valley; Kenya; Primary schools; School children

Understanding students' out-of-school mathematics and science practice. - Masingila, Joanna O.; Muthwii, Samson M.; Kimani, Patrick M. (Understanding students' out-of-school mathematics and science practice., 2011)
This study examined standard 6 and 8 (Standards 6 and 8 are the sixth and eighth years, respectively, of primary level schooling in Kenya.) students’ perceptions of how they use mathematics and science outside the classroom in an attempt to learn more about students’ everyday mathematics and science practice. The knowledge of students’ everyday mathematics and science practice may assist teachers in helping students be more powerful mathematically and scientifically both in doing mathematics and science in school and out of school. Thirty-six students at an urban school and a rural school in Kenya were interviewed before and after keeping a log for a week where they recorded their everyday mathematics and science usage. Through the interviews and log sheets, we found that the mathematics that these students perceived they used outside the classroom could be classified as 1 of the 6 activities that Bishop (Educ Stud Math 19:179–191, 1988) has called the 6 fundamental mathematical activities and was also connected to their perception of whether they learned mathematics outside school. Five categories of students’ perceptions of their out-of-school science usage emerged from the data, and we found that 4 of our codes coincided with 2 activities identified by Lederman & Lederman (Sci Child 43(2):53, 2005) as part of the nature of science and 2 of Bishop’s categories. We found that the science these students perceived that they used was connected to their views of what science is.
Keywords: Kenya; Mathematical literacy; Mathematics; Mathematics education (Elementary); Primary education; School children; Science; Science education (Elementary); Scientific literacy; Sensory perception

Relevance and Rigor in International Business Teaching: Using the CSA-FSA Matrix. - Collinson, SimonC.; Rugman, AlanM. (Relevance and Rigor in International Business Teaching: Using the CSA-FSA Matrix., 2011)
We advance three propositions in this paper. First, teaching international business (IB) at any level needs to be theoretically driven, using mainstream frameworks to organize thinking. Second, these frameworks need to be made relevant to the experiences of the students; for example, by using them in case studies. Third, these parameters of rigor and relevance need to be seamlessly integrated. We then demonstrate these principles using Rugman's CSA-FSA matrix, describing both the theoretical and practical value of the framework.
Keywords: Active learning; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Business and Secretarial Schools; Business education; Colleges, Universities, and Professional Schools; Education; Educational Support Services; International Trade Financing; International trade; Matrices (Mathematics); Teaching

Making Space for Expressive and Creative Writing in African Primary Schools: A Two-Site Action Research Study in Kenya and South Africa - Gains, Paula; Graham, Barbara (Making Space for Expressive and Creative Writing in African Primary Schools: A Two-Site Action Research Study in Kenya and South Africa, 2011)
Similar concerns about the development of children's creative writing abilities in Kenya and South Africa prompted two Mother Tongue (MT) education practitioners in Summer Institute of Linguistics (SIL) and Molteno Institute for Language and Literacy of Linguistics (MILL) to undertake parallel intervention studies to increase teachers' competence in writing pedagogy and improve the quantity and quality of learners' writing. Most early literacy teachers have had no experience themselves of expressive writing, so it is not surprising that this activity rarely, if ever, features in public school early literacy classrooms. The hypothesis which formed the basis for this action research study was that educators, exposed to extensive and expressive writing themselves, will be more skilled in the generation of such activities with learners. This paper reports on the workshop processes in the two sites, identifying similarities and differences in the experience. Whilst the hypothesis, though tested, remains unproven, this paper presents findings that are of relevance to further study in the area of writing pedagogy research and also to teachers and teacher educators involved in writing in the primary school.
Keywords: Action Research; African Languages; Comparative Education; Creative Writing; Elementary School Students; Elementary School Teachers; Expressive Language; Foreign Countries; Instructional Effectiveness; Intervention; Kenya; Native Language; South Africa; Teacher Education; Teaching Methods; Writing Attitudes; Writing Instruction; Writing Workshops

What Does It Mean to Learn Oral and Written English Language: A Case Study of a Rural Kenyan Classroom - Lisanza, Esther Mukewa (ProQuest LLC, 2011)
This study was an ethnographic case study that investigated oral and written language learning in a first grade classroom in Kenya. The languages used in this classroom were Swahili and English only. Kamba the mother tongue of the majority of the children, was banned in the entire school. In this classroom there were 89 children with two teachers, one a teacher of English, the other a teacher of Swahili. The children's ages ranged from five to eight years. The main participants were six focal children with their parents, the two teachers, and the school administrator. Data collection took place over a two and half month period and employed classroom participant observations, audio recording, interviewing, and collection of official documents and children's writings. The study was guided by a sociocultural and dialogic framework which maintains that social interactions and cultural institutions (e.g. societies, schools, and classrooms) have important roles to play in a child's literacy and language development. Thus, the social life of this classroom was central to the children's literacy and language learning. The physical, institutional, and policy contexts of this school influenced the nature of social interaction and, thereby, of the language teaching and learning that occurred. To begin, in this classroom, there was a great shortage of literacy and educational materials and space. Moreover, the school's language policy--that is, English as the language of instruction, Swahili as language of communication, and the banning of Kamba-combined with the physical context shaped the classroom's practices to a great extent. As the teacher and the students or students interacted with each other in the classroom, they were involved in different practices or genres and this is what marked the culture of this classroom. There were both official (i.e. teacher controlled) and unofficial practices (i.e. children controlled). On one hand, during the daily English official writing, the teacher followed the mandated curriculum, making adjustments for the lack of the textbooks (i.e., having children copy excerpts on the board). The interaction structure was traditional recitation involving much repetition of the teacher's words. On the other hand, during the Swahili official writing, reading, and speaking practices, the teacher taught with the same space and text limitations but involved the children in dialogues with her and other students through storytelling, peer guided reading, classroom talk, and drawing. In the Swahili classroom through the teacher's dialogic instruction and mediation, the children's voices were recognized and acknowledged. During writing practices the children went beyond copying off the board and drew and colored. Moreover, during unofficial curriculum, the children drew and played together. They drew, wrote, played, or sang songs which focused on their community practices or experiences, identities, and imaginations. Thus, the English conventional practices did not provide insights into the children's experiences and imaginations as the drawing, storytelling, singing, recitation of poems, and play did during Swahili lessons and during unofficial times. Therefore, drawing, storytelling, singing, recitation of poems, and play should be included in the official English curriculum. In conclusion, this study manifested that language learning cannot be separated from its ideological, social, and physical contexts. These contexts shape language learning. Also, meaningful dialogues are important for meaningful language learning to occur. And, oral and written language develops simultaneously in a classroom setting. Lastly, written language development is supported by other media such as drawing, play, singing, etc. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Administrators; African Languages; Case Studies; Cultural Centers; Elementary School Students; English (Second Language); Ethnography; Foreign Countries; Freehand Drawing; Grade 1; Imagination; Interpersonal Relationship; Interviews; Kenya; Language Acquisition; Language Teachers; Language of Instruction; Literacy; Native Language Instruction; Oral Language; Play; Poetry; Rural Areas; Second Language Learning; Singing; Story Telling; Teacher Student Relationship; Written Language

Gender and increased access to schooling in Cameroon: A marginal benefit incidence analysis - Tabi Atemnkeng, Johannes; Noula, Armand (Journal of International Women's Studies, 2011)
Of great importance to policy makers is to know if females and poor households benefit more or less than the males or rich households from an expansion in access to public education. This is marginal benefit incidence of public spending which is rarely determined. In this paper, we determine the extent to which an expansion in public education is effective in reducing gender gaps in enrollments and thus, poverty in Cameroon. Government subsidies directed towards higher education are poorly targeted and the poorest income groups receive less than the richest income groups and indeed favor those who are better off. Similarly, gender disparity in access to public schools is higher at the tertiary level and lowest at primary level. Further, contrary to earlier studies which found that primary education expansion mostly benefits the poor, the present paper found that increased subsidy to primary and secondary education is captured by the middle income groups and as such cannot be good as a program that can be directed (explicitly) at fighting poverty. The difference may come from the fact that their enrollment estimates lump together private and public schools enrollments. It is difficult to think of a policy at which private operators will want to expand on their schooling projects.

From Assessment to Learning: The Teaching of English beyond Examinations - Vikiru, Lilian I. (From Assessment to Learning: The Teaching of English beyond Examinations, 2011)
The backwash of testing on teaching can be positive or negative. This article is based on the findings of a study carried out in Kenya on strengthening the development of literacy in English among primary school children, which established that the learners performed poorly on skills that were not directly tested in the conventional examinations. Interventions used in improving teaching, learning, and assessment to target communicative competence are discussed in the article. (Contains 2 tables.)
Keywords: Communicative Competence (Languages); Elementary School Students; English (Second Language); Evaluation Methods; Foreign Countries; Formative Evaluation; Infants; Intervention; Kenya; Language Skills; Literacy Education; Second Language Instruction; Test Construction; Tests

Nonproduction Benefits of Education - Lance, Lochner (Handbook of the Economics of Education, 2011)

The foundations for learning campaign: Helping hand or hurdle? - Meier, Corinne (South African Journal of Education, 2011)

Mother tongue education: necessary? Possible? Sustainable? - Graham, BarbaraElaine (Mother tongue education: necessary? Possible? Sustainable?, 2010)
Issues affecting pre-school education in a rural area of Kenya are highlighted in a study of a mother tongue education (MTE) programme in one indigenous language group, the Pokomo. Factors supporting the introduction of MTE include official support for MTE, the welcoming of non-government stakeholder involvement in education, the presence of individuals and organisations committed to MTE and the willingness of local education authorities to partner with organisations in the establishment of the programme. Issues which emerged as constraining the development of the programme included the dominant teaching styles, the dearth of educational resources in Kipfokomo, widespread poverty and societal attitudes and structures which exclude local languages from education settings. The tensions between enabling and constraining factors are explored, as, too, is the sustainability of the programme.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Child Day Care Services; Education; Education policy; Educational Support Services; Educational resources; Foreign language education; Kenya; Language Schools; Native language & education; Native language instruction; Other local, municipal and regional public administration; Other provincial and territorial public administration; Pokomo language; Preschool education; Teaching aids

Narrative inquiry in service learning contexts: Possibilities for learning about diversity in teacher education. - Mitton-Kükner, Jennifer; Nelson, Carla; Desrochers, Claire (Narrative inquiry in service learning contexts: Possibilities for learning about diversity in teacher education., 2010)
This paper explores the experiences of pre- and in-service teachers through intentionally created narrative inquiry (Connelly Clandinin, 2006) spaces within three different service-learning engagements in Canada, Kenya, and Turkey. Because the contexts where our studies were situated were culturally different from participants' backgrounds, narrative inquiry spaces shaped windows in which participants could restory their understandings of others different from themselves. We argue thinking narratively suits the purpose of learning within service learning, highlighting the potential this kind of work holds for pre- and in-service teachers' professional identities in school contexts shaped by diversity. Reprinted by permission of the publisher.
Keywords: Canada; Cross-cultural differences; Education; Experiential learning; Kenya; Narration; Narrative inquiry (Research method); Service learning; Teacher education; Turkey; Young volunteers

When 'Prof' speaks, who listens? The African elite and the use of African languages for education and development in African communities. - Trudell, Barbara (When 'Prof' speaks, who listens? The African elite and the use of African languages for education and development in African communities., 2010)
The role of African languages in formal and nonformal learning is the subject of increasing local, national and international interests. Cognitive and pedagogical reasons abound for using the language best understood by the learner. However, many nonpedagogical factors related to politics, economics, language attitudes and colonial history are also extremely influential as decisions are made regarding language of instruction. Among the various stakeholders in this issue of language choice for education, an important interest group is the African elite. Members of the elite are able to access resources, marshal arguments that promote their values and ultimately influence the formulation and implementation of policy in ways that the average local community member cannot do. This paper examines the influence of international, national and local contexts upon the perspectives of the African elite where language and education are concerned. It argues that organized, intentional action by concerned members of the African elite can have significant impact on language-and-education choices.
Keywords: Administration of Education Programs; Africa; African languages; All Other Miscellaneous Schools and Instruction; Education; Education policy; Educational Support Services; Language & education; Language & languages; Learning; Literacy; Other local, municipal and regional public administration; Other provincial and territorial public administration; Teaching

Evaluation of the Extent of Achievement of the Objectives of NEPAD Schools' ICT Project in Kenya. - Mildred, A. Ayere; Florence, Y. Odera (Evaluation of the Extent of Achievement of the Objectives of NEPAD Schools' ICT Project in Kenya., 2010)
The New Partnership for Africa Development (NEPAD) is a combination Project of the United Nations and World Bank aimed at developing an integrated socio-economic framework for Africa's renewal. Its three main areas of operation included economics, educational and social dimensions. NEPAD's aim was to have Africans develop homegrown solutions to the continents problems of poverty, illiteracy and disease. The infrastructure, especially Information and Communication Technology (ICT) were identified as a key priority action area in order to promote useful conditions for Education on Sustainable Development (ESD). To fulfill the continents ICT objective, NEPAD e-Africa Commission was tasked to develop and implement the NEPAD ICT program. This article reports the results of a study that examined the implementation of ICT application in NEPADs' Project Schools and Non-NEPAD schools in Kenya. The purpose of the study was to find out the input of ICT in NEPAD and Non-NEPAD schools. The study used a combination of descriptive survey and ex-post factor design to compare areas of ICT application. The study population consisted of 1600 form four students, 12 principals, 12 head of departments, 12 computer teachers, 7 education officers and 2 NEPAD officers. The sampling unit was the school and the actual sample included 570 form four students, 12 principals, 12 head of computer departments, 12 teachers and 2 KIE officers, Ministry of education official, and Ministry of education official and NEPAD representative. Data collection instrument was the questionnaire, interviews, and check list. Analysis of data was done using both descriptive and inferential statistic and the results that there was significance in ICT application areas. The study suggested further research on the state of other implementation of ICT in NEPAD schools.
Keywords: Administration of Education Programs; Administration of General Economic Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Information & communication technologies; Kenya; Literacy; Poverty reduction; Social status; Sustainable development

Distinction, integration and identity: Motivations for local language literacy in Senegalese communities - Trudell, Barbara; Klaas, Anthony R. (Distinction, integration and identity: Motivations for local language literacy in Senegalese communities, 2010)
Abstract: Successful adult literacy and basic education programs are notoriously difficult to achieve. One reason for this has to do with how the question, “literacy for what?” is answered for a given program. All too frequently, the answer to that question is shaped more by the goals of the literacy provider than it is by learners’ own goals and desires. Accurate assessment of people''s motivations for participating in literacy programs can uncover motivations beyond the economic or development-related outcomes so often given as reasons for becoming literate. One type of motivation which has received limited attention is that related to cultural identity and cultural expression. Such motivations do not figure strongly for many of the target populations of literacy programs; yet for the minority language speakers of sub-Saharan Africa and elsewhere, the issues of cultural and linguistic identity are significant and could easily give rise to this type of motivation. This paper addresses the question of whether cultural identity and expression, linked to the development and use of the mother tongue, are really a reliable motivation for adult literacy. Based on research done in five language communities of Senegal, the paper argues that two strong motivations exist among these communities for literacy: (1) the drive for internal social cohesion, solidarity and cultural uniqueness and (2) the drive towards citizenship, acceptance and equality in the larger national society. These two motivations, while apparently in opposition to each other, actually complement and enhance each other in the literacy programs under study.
Keywords: Adult literacy programs; African languages; All other schools and instruction; Basic education; Communities; Cultural identity; National unification; Senegal; Senegalese; Social cohesion

Variations in Reading Achievement Across 14 Southern African School Systems: Which Factors Matter? - Hungi, Njora; Thuku, Florence W. (Variations in Reading Achievement Across 14 Southern African School Systems: Which Factors Matter?, 2010)
In this study the authors employed a multilevel analysis procedure in order to examine the pupil and school levels factors that contributed to variation in reading achievement among Grade 6 primary school pupils in 14 southern African school systems (Botswana, Kenya, Lesotho, Malawi, Mauritius, Mozambique, Namibia, Seychelles, South Africa, Swaziland, Tanzania, Uganda, Zambia, and Zanzibar). The data for this study were collected in 2002 as part of a major project known as the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ) that sought to examine the quality of education offered in primary schools in these countries. The most important factors affecting variation in pupil achievement across most of these school systems were grade repetition, pupil socioeconomic background, speaking the language of instruction at home, and Pupil age. South Africa, Uganda and Namibia were among the school systems with the largest between-school variation while Seychelles and Mauritius had the largest within-school variation. Low social equity in reading achievement was evident in Mauritius, Seychelles and Tanzania. Policy implications of the findings are discussed.
Keywords: Academic achievement; Education; Education policy; Educational quality; Primary school facilities; Reading; Reading level of students; School children; Socioeconomic factors; Southern Africa

Variations in Reading Achievement across 14 Southern African School Systems: Which Factors Matter? - Hungi, Njora; Thuku, Florence W. (Variations in Reading Achievement across 14 Southern African School Systems: Which Factors Matter?, 2010)
In this study the authors employed a multilevel analysis procedure in order to examine the pupil and school levels factors that contributed to variation in reading achievement among Grade 6 primary school pupils in 14 southern African school systems (Botswana, Kenya, Lesotho, Malawi, Mauritius, Mozambique, Namibia, Seychelles, South Africa, Swaziland, Tanzania, Uganda, Zambia, and Zanzibar). The data for this study were collected in 2002 as part of a major project known as the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ) that sought to examine the quality of education offered in primary schools in these countries. The most important factors affecting variation in pupil achievement across most of these school systems were grade repetition, pupil socioeconomic background, speaking the language of instruction at home, and Pupil age. South Africa, Uganda and Namibia were among the school systems with the largest between-school variation while Seychelles and Mauritius had the largest within-school variation. Low social equity in reading achievement was evident in Mauritius, Seychelles and Tanzania. Policy implications of the findings are discussed.
Keywords: Academic Achievement; Africa; Age; Educational Quality; Elementary Education; Foreign Countries; Grade 6; Grade Repetition; Language of Instruction; Native Language Instruction; Reading Achievement; School Districts; Socioeconomic Background

“I Have Been Given the Power to Teach. The Children Understand Me Very Well”: A Preliminary Study of The Social and Academic Impact of Deaf Teacher Training in Kenya. - Johnstone, Christopher; Corce, Heidi (“I Have Been Given the Power to Teach. The Children Understand Me Very Well”: A Preliminary Study of The Social and Academic Impact of Deaf Teacher Training in Kenya., 2010)
Kenya has 41 Deaf schools that serve children from Class 1 through secondary school. These schools are all characterised by the fact that they have very few teachers who are fluent in Kenyan sign language. In order to meet the needs of schools and to provide employment opportunities for Deaf Kenyan adults, a small non-governmental organisation identified Deaf secondary school students for training. They received two years of teacher training free of charge. Most have since been awarded teaching contracts by the Kenyan Teacher Service Commission or local school boards. This article reports on results from a preliminary study of the social and academic impacts of this innovation. Results indicate that Deaf teachers are inspirational in the classroom, represent a significant resource for their school communities and are preferred by Deaf students. A follow-up study on the relative learning gains of Deaf students when taught by Deaf teachers is planned once relevant data are available.
Keywords: Adults; Deaf students; Deaf teachers; Education; Education of teachers of the deaf; Hearing impaired children; Kenya; Kenyan Sign Language; Services for the hearing impaired; Sign language; Teacher education; Teachers with disabilities

'I Have Been Given the Power to Teach. The Children Understand Me Very Well.' The Social and Academic Impact of Deaf Teacher Training in Kenya - Johnstone, Christopher; Corce, Heidi ('I Have Been Given the Power to Teach. The Children Understand Me Very Well.' The Social and Academic Impact of Deaf Teacher Training in Kenya, 2010)
Kenya has 41 Deaf schools that serve children from Class 1 through secondary school. These schools are all characterised by the fact that they have very few teachers who are fluent in Kenyan sign language. In order to meet the needs of schools and to provide employment opportunities for Deaf Kenyan adults, a small non-governmental organisation identified Deaf secondary school students for training. They received two years of teacher training free of charge. Most have since been awarded teaching contracts by the Kenyan Teacher Service Commission or local school boards. This article reports on results from a preliminary study of the social and academic impacts of this innovation. Results indicate that Deaf teachers are inspirational in the classroom, represent a significant resource for their school communities and are preferred by Deaf students. A follow-up study on the relative learning gains of Deaf students when taught by Deaf teachers is planned once relevant data are available.
Keywords: Deafness; Followup Studies; Foreign Countries; Kenya; Nontraditional Education; Program Effectiveness; Secondary School Students; Sign Language; Special Education Teachers; Special Schools; Teacher Education

The Right to Education for Children in Domestic Labour: Empirical Evidence from Kenya. - Munene, Ishmael I.; Ruto, Sara J. (The Right to Education for Children in Domestic Labour: Empirical Evidence from Kenya., 2010)
Since 1948, various UN conventions have recognised basic education as a human right. Yet this right continues to be denied to many child labourers across the world. This articles draws on the results of a study examining how children in domestic labour in Kenya access and participate in education. Three issues were explored: (1) the correlates of child domestic labourers; (2) their working conditions and contexts; and (3) the right to education. Interviews and group discussions held in one city and two rural districts elicited data from 91 child domestic labourers and 84 adults. The results indicated that child labour was both poverty-induced and adult-initiated, and that children worked in hazardous environments characterised by economic exploitation. Most did not attend school; those who did had to contend with a rigid school structure and an authoritarian class environment. Children in domestic labour often skipped school, and their participation in classes was low.
Keywords: Child labor; Children's rights; Education policy; Educational law & legislation; Elementary education; Human rights; Kenya; Literacy; Right to education; Student rights

Digital learning management systems in Africa: myths and realities. - Unwin, Tim; Kleessen, Beate; Hollow, David; Williams, JamesB.; Oloo, LeonardMware; Alwala, John; Mutimucuio, Inocente; Eduardo, Feliciana; Muianga, Xavier (Digital learning management systems in Africa: myths and realities., 2010)
This paper reports on a survey of 358 respondents across 25 African countries into their usage of learning management systems. It concludes that while there are some enthusiastic advocates of such systems, the reality is that most African educators as yet have little knowledge about, or interest in, their usage. There remain very considerable infrastructural constraints to be overcome before they can be widely adopted for open and distance learning across the continent, and there is still reluctance in many institutions to develop systems that can enable learning resources to be made available in this way. This does not mean that the potential of high-quality digital learning management systems should be ignored in Africa, but rather that much more sustained work needs to be done in human capacity development and infrastructural provision if African learners are truly to benefit from the interactive learning experiences that such systems can deliver.
Keywords: Administration of Education Programs; Africa; All Other Miscellaneous Schools and Instruction; Computers in education; Courseware; Cyberschools; Digital learning; Distance education; Internet in education; Online education; Online reading programs; Telecourses

What's it got to do with us? Everything. - Eldred, Jan (What's it got to do with us? Everything., 2010)
The author comments on the CONFINTEA VI adult education conference organized by UNESCO. Presentations were given by Director-General Of UNESCO, Irina Bokova and Princess Laurentien, UNESCO's Special Envoy on Literacy for Development. John Gates of Wales and Magdalene Motsi of Kenya stressed the importance of listening to what learners want from their learning. According to the author, the outcomes of the event are important.
Keywords: Adult education; Bokova, Irina, 1952-; Conferences & conventions; Convention and Trade Show Organizers; Gates, John; Motsi, Magdalene; UNESCO

Homing in: Mothers at the Heart of Health and Literacy in Coastal Kenya - Mount-Cors, Mary Faith (ProQuest LLC, 2010)
An economics-driven discourse about early literacy (Trudell, 2009) in sub-Saharan African settings often includes a list of reasons for poor levels of literacy that remain mired in deficit thinking or a deficiencies model in which the problem lies within the non-literate people themselves. Meanwhile, the established post-colonial educational structure is held largely blameless and unexamined. This study includes a critical inquiry into literacy education that takes into account constraints to literacy such as health; an engagement with mothers as the primary caregivers and literacy models for their children; and guidelines for developing literacy interventions that move beyond entrenched modes of thought to promote additive approaches to forming literacy. This study makes contributions to literatures at the intersection of discipline areas critical to literacy, health and development in sub-Saharan Africa and other parts of the developing world, including development theory, sociolinguistics, reading research, cultural anthropology, cultural psychology, feminist theory, social epidemiology, and research methodology. In this mixed methods study, quantitative reading data from 800 second graders in 40 schools from the U.S.-funded Early Grade Reading Assessment (EGRA) in coastal Kenya were analyzed, then qualitative data were collected and analyzed by the researcher from mothers in three EGRA treatment schools. Mothers of second grade students involved in the quantitative portion of the study in coastal Kenya talked with researchers in focus groups and provided demographic data in one-on-one interviews. Interviews were also conducted with the head teacher at each research site and with local education partners. The disjunctures found between mothers' realities and development discourses resulted in a foundational critique of the best practices and evidence-based wave of development approaches. Three simple findings from the quantitative and qualitative phases of research came together to support one another and led to theory- and model-building. EGRA reading growth was linked to commonly considered socioeconomic status variables, which were unpacked in the qualitative portion of the research. Reading items, such as letter-sound recognition, which showed growth, suggested the value of the transfer of home language literacy to school literacy learning in the context of Kiswahili and Kigiriama. The disconnection between the two showed up in the qualitative portion of the study. Mothers' responses informed these salient factors from the EGRA data by demonstrating that health is deeply embedded in the home, that health affects literacy learning at school, and that the same environmentally situated drivers affect both health and literacy. Results reinforced the close relationship between adult literacy and child literacy, and particularly the need to work with mothers when aiming to improve child literacy. Home and school literacies need to be connected so that reading can become an indigenous process. Health improvements were also linked to literacy becoming an indigenous process. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: African Languages; Best Practices; Caregivers; Criticism; Emergent Literacy; Family Environment; Feminism; Focus Groups; Foreign Countries; Grade 2; Guidelines; Health; Intervention; Interviews; Kenya; Literacy Education; Mother Attitudes; Phoneme Grapheme Correspondence; Reading Achievement; Reading Research; Reading Tests; Research Methodology; Socioeconomic Status; Sociolinguistics; Statistical Analysis; Transfer of Training

The Effect of Embossed Picture Technique on Reading Performance of Learners with Hearing Impairments: A Case of Kambui School for the Deaf - Munyendo, Sella; Wamocho, Franciscah Irangi (The Effect of Embossed Picture Technique on Reading Performance of Learners with Hearing Impairments: A Case of Kambui School for the Deaf, 2010)
The purpose of this study was to find out the effect of embossed picture technique when used in teaching reading to the pupils with hearing impairment. The study was guided by Piaget's theory of human mental development. The study adopted an experimental design. The study was carried out at Kambui School for the hearing impaired located on Githunguri-Ruiru road in Kiambu District, Githunguri Division, Ngewa zone, 3 kilometers off Kwa-Maiko centre. The school was chosen since it caters for all categories of pupils with hearing impairment from nursery to class eight. The school also admits pupils from all over the country. Pupils were assigned randomly to the experimental and control groups. Each group consisted of 9 pupils totaling 18. Data were collected from both experimental and control groups for a period of 6 weeks. Criterion reference test (CTR) was used as a pre-test and post-test for the purpose of data collection. Nonparametric tests such as the Mann-Whitney test and the Wilcoxon sum of rank test were used to test the significant difference in performance in reading of pupils with hearing impairment taught with embossed picture technique and those taught with "look and say" method. To determine if there was any significant effect of the degree of hearing loss on performance of pupils with hearing impairment in reading, and the difference in performance of pupils of different ages when taught with embossed picture technique, the Kruskal-Wallis one-way Analysis of Variance (ANOVA) which takes care of small samples were used with the different degrees of hearing loss and the different ages as factors. The results showed that there is a high statistical significant difference between pupils taught with embossed picture technique and those taught with the look and say method. The results revealed that there is no significant age effect on reading performance of pupils with hearing impairment of different ages taught with embossed picture technique. Finally, the study revealed that there is no significant performance difference in reading of pupils with hearing impairment at different degrees of hearing loss when taught with embossed picture technique.
Keywords: Control Groups; Deafness; Elementary School Students; Experimental Groups; Foreign Countries; Hearing Impairments; Instructional Effectiveness; Kenya; Nonparametric Statistics; Performance Based Assessment; Pretests Posttests; Reading Instruction; Severity (of Disability); Statistical Analysis; Statistical Significance; Tactile Adaptation; Teaching Methods

Assessing and Teaching Reading to Pupils with Reading Disabilities in Nyeri and Nairobi Districts-Kenya: The Teachers' Opinion - Runo, Mary; Kargu, Geoffrey; Mugo, John K. (Assessing and Teaching Reading to Pupils with Reading Disabilities in Nyeri and Nairobi Districts-Kenya: The Teachers' Opinion, 2010)
The study aimed at finding out whether teachers can identify the courses of reading disabilities in learners. It intended to establish whether teachers have adequate knowledge of identifying learners with reading disabilities, determine the proportion of non-readers in grade five. It also investigated the existing methods and materials teachers use in teaching and remediating reading including the difficulties teachers encounter when teaching. Finally, the study aimed at finding out whether there are any gender differences in learners with reading disabilities. This study adopted both qualitative and quantitative research approaches where mixed method designs were used for collecting and analyzing data for both teachers and learners. The study embarked on interviews for learners by use of structured questionnaires. Learners were also assessed to determine the level of reading ability. The study also used semi-structured questionnaires for teachers. A focus group interview was also held with teachers in the study. The study was conducted in Central and Nairobi provinces where Nyeri and Nairobi districts respectively were used. Purposive sampling was used to select the provinces, districts, divisions, primary schools, populations and the target groups, in this case of the teachers and learners. This was based on KCPE results analysis for 2006, the division that performed best overall in Nairobi and the poorest performing division in Nairobi from KCPE results, 2006. Nyeri District was representative of rural primary schools and therefore, the municipality and one rural division was selected. In this case, Nyeri municipality division and Othaya division. There were four schools selected from each of the four divisions, giving a total of 16 schools from both Nairobi and Nyeri. In each school, 15 pupils were purposively selected from the list of those learners scoring 250 marks and below from their end of standard 5 examinations. If the learners were more than 15 scoring 250 marks and below, the researcher used random sampling. A total of 240 learners were the sample for the study, streams were not considered in the study. All teachers who taught English to the learners in the study, in class in 2007, were in the study. All the class teachers of grade five in 2007 of not the English teacher were also included in the study. A total of 34 teachers participated in the study. There were five types of instruments namely: questionnaires for teachers, questionnaires for learners, assessment tools for reading--wood list A to E, passage 1 to 4; checklist on reading errors and learners' reading attitude survey. Statistical Package for Social Sciences (SPSS) was used to analyze quantitative data from the assessment tools, questionnaires for learners, and reading attitude survey. All the hypotheses were tested at P=0.05 Pearson product moment correlation coefficient was used to measure the strength and direction of the relationship between the different variables. Multiple regression analysis and chisquare test were also used. Teachers' questionnaire was analyzed through descriptive research. The following results were obtained based on the objectives, questions and hypotheses of the study: The teachers assessed their learners reading ability but they did not use proper methods of assessment; teachers were able to identify children who could not read at class level as non-performers but not able to identify the specific reading difficulties. Non-readers ranged from 0 to 27.1% for Nairobi and 0 to 53.6% in Nyeri; almost half of the teachers in the study did not either teach reading or they did not know the methods to use in teaching reading. The study indicated that there were more boys (103) than girls (78) who could not read. The study concluded that: teacher training syllabus on reading whether in mother tongue, Kiswahili or English be adequately developed to cater for individual learners and equip the teachers with methods for teaching reading adequately. More time be given to teaching reading, assessing reading and remediating reading disabilities both at the primary teacher education colleges and at primary schools; reading in an ongoing process and therefore it is recommended that reading be taught all through primary levels. (standard 1 to 8) and be within the developmental states of reading; reading readiness curriculum be developed for early childhood and at primary levels. Such policy should ensure smooth transition of learners' movement from home, preschool and primary schools. Finally the study recommended adequate development of teacher training syllabus on reading in mother tongue English or Kiswahili more time, reading be taught continuously from standard 1 to 8 and smooth transition for learners' movement from home, pre-school and primary schools.
Keywords: African Languages; Correlation; Elementary School Students; Elementary School Teachers; English (Second Language); Focus Groups; Foreign Countries; Gender Differences; Grades (Scholastic); Interviews; Kenya; Language Teachers; Learning Disabilities; Mixed Methods Research; Multiple Regression Analysis; Native Language; Questionnaires; Reading Difficulties; Rural Schools; Sampling; Second Language Instruction; Second Language Learning; Teacher Attitudes; Teacher Education; Teaching Methods; Word Lists

Cameroon Decree of Application 2010 Law - Government of Cameroon (2010)

Decree No. 2010/0241/PM 26 February 2010 - Government of Cameroon (2010)

DECREE No. 2010/0240/PM OF 26 FEB 2010 to lay down conditions for the exercise of some powers transferred by the State to councils relating to the creation and maintenance of unclassified rural roads and the building and management of ferries; - Ministry of the Economy, Planning and Regional Development (Government of Cameroon, 2010)

Growth and Employment Strategy Paper (GESP) 2010/2020 - Ministry of the Economy, Planning and Regional Development (Government of Cameroon, 2010)
2 CAMEROON – Growth and Employment Strategy Paper (GESP) – 2010/2020 Growth and Employment Strategy Paper (GESP) SECTOR STRATEGIES MATRICES

The Constitution of Kenya, 2010 - Republic of Kenya (2010)

The National Children's Policy of 2010 - Republic of Kenya (2010)

The National Policy Framework for Nomadic Education, 2010 - Republic of Kenya (2010)

Attitudes of Teachers and Students towards Art and Design Curriculum: Implications for Vocational Education in Kenya - Wagah, M. O.; Indoshi, F. C.; Agak, J. O. (Attitudes of Teachers and Students towards Art and Design Curriculum: Implications for Vocational Education in Kenya, 2009)
Art and Design Curriculum taught in secondary schools in Kenya is intended not only to prepare learners for a vocation in Art and Design industry but also to complement literacy, scientific and factual subjects by awakening creativity in the individual. It is part of the government policy of diversification and vocationalization of the curriculum. However, enrolment of students in this subject has gone down to as low as one (1) student in form four classes in some schools. The number of schools offering Art and Design Curriculum has also gone down drastically since the inception of the diversified and vocationalized 8. 4. 4 system of education in Kenya in 1985. The 8 - 4 - 4 system is a structure of education in Kenya with 8 years of primary education, 4 years of secondary education and a minimum of 4 years of University education. The survival of this subject in the Kenyan School Curriculum is therefore worrying to the stakeholders. The attitude of the learners towards a subject of study greatly influences the readiness of learners to take it or perform well in it. This article is based on a study carried out in secondary schools in Nyanza province of Kenya. Objectives of the study were to find out the attitude of Teachers and Students towards Art and Design Curriculum and to determine the differences in attitudes between Teachers and Students. Respondents were 113 students taking Art and Design, 131 students who had dropped Art and Design and 15 teachers of Art and Design Curriculum. The findings of the study revealed that students who had dropped Art and Design Curriculum and Teachers of Art and Design Curriculum had negative attitudes towards the curriculum. Although students taking Art and Design liked the subject their reasons for this were not fully in line with the objectives of the curriculum. Some of the students were taking the subject for merely boosting their Kenya Certificate of Secondary Examination (K. C. S. E) result. Based on these findings, it is recommended that students be given proper career guidance on Art and Design Curriculum. The subject should also be made compulsory in Forms 1 and 2 to give early opportunity to students to identify their talents. (Contains 5 tables and 3 figures.)
Keywords: Art Education; Career Guidance; Creativity; Design; Foreign Countries; Kenya; Negative Attitudes; Public Policy; Secondary School Curriculum; Secondary School Students; Student Attitudes; Talent; Teacher Attitudes; Teacher Student Relationship; Vocational Education

Reconstructing Masculinity and Power in Africa through Open Distance Learning for Sustainable Development: A Critical Analysis of Wole Soyinka's 'Climate of Fear' - Adetunji, Barihi; Adesida, Aderonke Adetunji (Reconstructing Masculinity and Power in Africa through Open Distance Learning for Sustainable Development: A Critical Analysis of Wole Soyinka's 'Climate of Fear', 2009)
The strabismus conception of masculinity and power with its manipulation as reflected in the consequences of actions endorsed and demonstrated by leaders, followers, citizens as individuals and groups at different times in the past, and present has been a major source of the seemingly quiescence and underdevelopment in Africa. Masculinity has often been associated with being athletic, breadwinner, objective, sexually aggressive, unemotional, dominating, etc.; while power is frequently construed as a tool of dominance, authority, superiority, influence, and governance. This inapt perception was borne out of Africa's nictitating and ignorance. The consequences of the misconception include abuse of power, intolerance, intimidation, militancy, humiliation, insecurity, inadequate dialogic tools and opportunities, etc. These result in the "Climate of Fear" as being experienced in the Niger-Delta of Nigeria, Kenya, and other parts of Africa. Thus, this paper examines the concepts of masculinity and power with exemplification from Africa with Wole Soyinka's "Climate of Fear." The research methodology employs a combination of critical discourse analysis and Halliday's systemic functional theory of grammar with sociolinguistics approaches for the analysis. The study posits that the root of the problems that abound in Africa is traceable to the lack of precise socio-cultural, political and philosophical ideologies by Africans. The research opines that these fundamental problems of Africa can be resolved through orientation with education for all, which is one of the challenges of the millennium development goals. Thus, the paper examines the contrivance of open distance learning and its role in the education of African citizenry. It concludes on the ground that open distance learning as a recent and welcomed information technological development in Africa, if properly channeled and adequately funded would enhance sustainable development in Africa by its elimination of some of the aforementioned obstacles. (Contains 1 table.
Keywords: Access to Education; Africa; Barriers; Critical Theory; Developing Nations; Discourse Analysis; Distance Education; Educational Change; Educational Environment; Educational Technology; Fear; Foreign Countries; Gender Issues; Ideology; Males; Masculinity; Misconceptions; Power Structure; Role of Education; Sex Role; Sex Stereotypes; Social Change; Sociocultural Patterns; Sociolinguistics; Sustainable Development

Adult Education Learners' Recruitment: Challenges and Prospects for Re-Engineered Access to Adult Education in Kenya - Mualuko, Ndiku J.; Hellen, Muthamia; Odeo, Ipara; Obaki, Samuel (Adult Education Learners' Recruitment: Challenges and Prospects for Re-Engineered Access to Adult Education in Kenya, 2009)
A research survey was designed to investigate the factor affecting participation of illiterate adults in adult education in Kenya and suggests ways to improve on the literacy levels. From the findings it was established that lack of conducive learning environments for adult learners, unavailability of enough instructional materials, negative attitude towards learning and shortage of professionally trained trainers for adult learners were some of the factors hindering many illiterate adults from participating in adult education programmes. It was recommended that the government and other agencies should take more responsibility in supporting adult education to make it more attractive to adult learners to attend the programmes by providing adequate funding and facilitating teacher training. The need for effective involvement of the learners in curriculum developed was emphasized.
Keywords: Access to Education; Adult Basic Education; Adult Learning; Adult Students; Change Strategies; Educational Research; Foreign Countries; Illiteracy; Kenya; Lifelong Learning; Outreach Programs; Performance Factors; Student Attitudes; Student Recruitment; Teacher Attitudes

Infectious Disinfection: Exploring Global Water Quality. - Mahaya, Evans; Tippins, Deborah J.; Mueller, Michael P.; Thomson, Norman (Infectious Disinfection: Exploring Global Water Quality., 2009)
Learning about the water situation in other regions of the world and the devastating effects of floods on drinking water helps students study science while learning about global water quality. This article provides science activities focused on developing cultural awareness and understanding how local water resources are integrally linked to the quality of the world's water supply. After reading and discussing a case study highlighting one water situation facing the people of Kenya, students explore water sanitation and testing methods, including solar pasteurization and the Colilert test for total coliform bacteria and Escherichia coli. These investigations are relevant to inquiry-based water quality labs for high school biology, chemistry, and environmental science. Reprinted by permission of the publisher.
Keywords: Activity programs in science education; Education; Escherichia coli; High schools; Kenya; Lesson planning; Science education (Secondary); Teaching aids; Water purification; Water quality; Water supply

Teachers' and Caregivers' Perceptions of Gender Differences in Educational Experiences of Children Affected by Parental AIDS in Western Kenya - Jepkemboi, Grace; Aldridge, Jerry (Teachers' and Caregivers' Perceptions of Gender Differences in Educational Experiences of Children Affected by Parental AIDS in Western Kenya, 2009)
The purpose of this qualitative case study was to describe the perceptions of teachers and caregivers concerning gender differences in the educational experiences of children influenced by the HIV status of their parents or orphaned by AIDS in 7 orphanage schools of Western Kenya. 12 teachers and 8 caregivers participated in the study. Data were collected over 3 months using participant observation and individual interviews. Findings indicated that no gender differences in educational experiences were noted during preschool. However, during the elementary school years and beyond, participants described gender differences in terms of math, science, languages, and school attendance. Boys were perceived to do better at math and science, while girls were believed to do better in languages. Girls were also more likely to be kept out of school to assist with or take care of family needs when a parent became ill due to AIDS.
Keywords: Acquired Immunodeficiency Syndrome (AIDS); Attendance; Caregivers; Case Studies; Educational Experience; Family Needs; Females; Foreign Countries; Gender Differences; Interviews; Kenya; Mathematics Achievement; Parent Child Relationship; Parents; Participant Observation; Science Achievement; Second Language Learning; Student Attitudes

Changing pedagogical practice in Kenyan primary schools: the impact of school-based training. - Hardman, Frank; Abd-Kadir, Jan; Agg, Catherine; Migwi, James; Ndambuku, Jacinta; Smith, Fay (Changing pedagogical practice in Kenyan primary schools: the impact of school-based training., 2009)
This study reports on an investigation into the impact of a national, school-based teacher development programme on learning and teaching in Kenyan primary schools. Building on a national baseline study (n = 102), 144 video-recorded lessons, covering the teaching of English, maths and science at Standards 3 and 6, were analysed to investigate whole-class teaching and group-based learning. Interviews were also conducted with school management committees, head teachers, teachers and pupils to elicit their views on the impact of the school-based training programme on learning and teaching. The study found that compared to the earlier baseline, teachers were more interactive with the pupils in their whole-class teaching and greater use was being made of group work. Lesson plans, teaching resources and flexible classroom layouts were also much more in evidence. However, the greatest impact on classroom practice was seen in the classrooms of those teachers who had undergone the most systematic in-service training. The wider implications of the findings for improving the quality of classroom learning in Kenyan primary classrooms are considered. Reprinted by permission of the publisher.
Keywords: Career development; Curriculum; Curriculum change; Curriculum enrichment; Curriculum planning; Elementary education; Elementary schools; In-service training of teachers; Instructional systems; Kenya; Lesson planning; Primary education; School personnel management; Teacher development; Teacher training; Teaching methods

Changing Pedagogical Practice in Kenyan Primary Schools: The Impact of School-Based Training - Hardman, Frank; Abd-Kadir, Jan; Agg, Catherine; Migwi, James; Ndambuku, Jacinta; Smith, Fay (Changing Pedagogical Practice in Kenyan Primary Schools: The Impact of School-Based Training, 2009)
This study reports on an investigation into the impact of a national, school-based teacher development programme on learning and teaching in Kenyan primary schools. Building on a national baseline study (n=102), 144 video-recorded lessons, covering the teaching of English, maths and science at Standards 3 and 6, were analysed to investigate whole-class teaching and group-based learning. Interviews were also conducted with school management committees, head teachers, teachers and pupils to elicit their views on the impact of the school-based training programme on learning and teaching. The study found that compared to the earlier baseline, teachers were more interactive with the pupils in their whole-class teaching and greater use was being made of group work. Lesson plans, teaching resources and flexible classroom layouts were also much more in evidence. However, the greatest impact on classroom practice was seen in the classrooms of those teachers who had undergone the most systematic in-service training. The wider implications of the findings for improving the quality of classroom learning in Kenyan primary classrooms are considered. (Contains 5 tables, 4 figures, and 1 note.)
Keywords: Classroom Techniques; Educational Change; Elementary School Teachers; Foreign Countries; Inservice Teacher Education; Instructional Effectiveness; Instructional Improvement; Interviews; Kenya; Material Development; Microteaching; Multitrait Multimethod Techniques; National Programs; Program Effectiveness; Program Evaluation

Languages and Education in Africa a Comparative and Transdisciplinary Analysis - Brock-Utne, Birgit; Skattum, Ingse (Symposium Books, 2009)
The theme of this book cuts across disciplines. Contributors to this volume are specialized in education and especially classroom research as well as in linguistics, most being transdisciplinary themselves. Around 65 sub-Saharan languages figure in this volume as research objects: as means of instruction, in connection with teacher training, language policy, lexical development, harmonization efforts, information technology, oral literature and deaf communities. The co-existence of these African languages with English, French and Arabic is examined as well. This wide range of languages and subjects builds on recent field work, giving new empirical evidence from 17 countries: Botswana, Ethiopia, Ghana, Kenya, Madagascar, Malawi, Mali, Mozambique, Niger, Nigeria, Senegal, South Africa, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe, as well as to transnational matters like the harmonization of African transborder languages. As the Editors--a Norwegian social scientist and a Norwegian linguist, both working in Africa---have wanted to give room for African voices, the majority of contributions to this volume come from Africa. Following a Foreword (Ayo Bamgbose), Series Editor's Preface (Michael Crossley), and Introduction (Ingse Skattum and Birgit Brock-Utne), the book is divided into four parts. Part 1, General Considerations on Language and Education, includes: Parents' and Policy Makers' Insistence on Foreign Languages as Media of Education in Africa: Restricting Access to Quality Education--For Whose Benefit? (Martha A.S. Qorro); Mother-Tongue Education in Africa for Emancipation and Development: Towards the intellectualisation of African Languages (Kwesi Kwaa Prah); Promoting Multilingual and Multicultural Education in Francophone Africa: Challenges and Perspectives (Hassana Alidou); and Assumptions and Aspirations Regarding African Languages in South African Higher Education: A Sociolinguistic Appraisal (Rajend Mesthrie.) Part 2, Language as a Means of Instruction and as a Subject in Formal Education, includes: L'Utilisation des Langues Nationales dans le Systeme Educatif Malien: Historique, Defies et Perspectives (Mamadou Lamine Traore); The Role of National Languages in Mali's Modernising Islamic Schools (Madrasa) (Tal Tamari); National Language Teaching as a Tool for Malagasy Learners' Integration into Globalisation (Irene Rabenoro); Implications of the Use of Mother Tongues versus English as Languages of Instruction for Academic Achievement in Ethiopia (Mekonnen Alemu Gebre Yohannes); Weaning Africa from Europe: Toward a Mother-Tongue Education Policy in Southern Africa (Silvester Ron Simango); The Training of Teachers of African Languages in Southern Africa with Special Reference to Botswana and Zambia (Lazarus M. Miti & Kemmonye C. Monaka); and Spare No Means: Battling with the English/Kiswahili Dlemma in Tanzanian Secondary School Classrooms (Halima Mohammed Mwinsheikhe.) Part 3, Language Standardisation and Harmonisation, includes: Language, Dialect and Region: The Handling of Language Herbert Chimhundu Variation in Shona Dictionaries (Herbert Chimhundu); Harmonisation of the Shona Varieties: Doke Revisited (Nhira Edgar Mberi); Adjectives in Shona (Nomalanga Mpofu); and From Standardisation to Harmonisation: A Survey of the Sociolinguistic and Political Conditions for the Creation of Nguni in Southern Africa (Samukele Hadebe.) Part 4, Beyond Formal Education, includes: La Communication Mediatisee par les Technologies de les Technologies de l'Information et de la Communication: La Porte d'Acces au Domaine de l'Escrit pour les Langues Africaines? (Kristin Vold Lexander); Comment les Langues se Melangent-elles a l'Ecrit? Pratiques Actuelles de deux Agriculteurs Passes par une Ecole Bilingue (Franco-Bambara) au Mali (Aissatou Mbodj-Pouye & Cecile Van Den Avenne); Towards an Enriched Beginning Reading Programme in Yoruba (Foluso O. Okebukola); and What is South African Sign Language? What is the South African Deaf Community? (Philemon Akach, Eline Demey, Emily Matabane, Mieke Van Herreweghe and Myriam Vermeerbergen.) Contributor information is included.
Keywords: Africa; African Languages; Beginning Reading; Bilingual Education; Bilingualism; Botswana; Comparative Analysis; Computer Mediated Communication; Deafness; Educational Policy; Educational Quality; Ethiopia; Foreign Countries; Ghana; Global Approach; Interdisciplinary Approach; Islam; Kenya; Language Planning; Language Role; Language Teachers; Language of Instruction; Madagascar; Malawi; Mali; Mozambique; Multicultural Education; Multilingualism; Niger; Nigeria; Official Languages; Second Language Learning; Second Languages; Senegal; Sign Language; Sociolinguistics; South Africa; Swaziland; Tanzania; Teacher Education; Uganda; Zambia; Zimbabwe

Foreign direct investment as an engine for economic growth and human development: A review of the arguments and empirical evidence - Liesbeth, Colen; Maertens, Miet; Swinnen, Johan (Human Rights and International Legal Discourse, 2009)

The Alternative Provision of Basic Education and Training Policy, 2009 - Republic of Kenya (2009)

The National Special Needs Education Policy Framework - Republic of Kenya (2009)

Differentiated quality assurance for the African Virtual University's teacher education qualification in mathematics and science. - Hattingh, A. (Differentiated quality assurance for the African Virtual University's teacher education qualification in mathematics and science., 2008)
For the African Virtual University and its consortium of African universities the implementation of quality promoting initiatives are not without challenges and scepticisms. To be discussed in this article is the case of a teacher education qualification in ten different African countries. Seven countries were sampled and visited in 2006 with the aim of understanding quality assurance cultures and practices used for promoting quality. Findings showed that quality assurance processes manifest at various levels of readiness and maturity. The uneven quality assurance landscape led me to propose a ten-tiered differentiated Quality Assurance Framework. In analogy to Vygotsky's theory of the 'zone of feasible development' I suggest the presence of do-able next steps where an institution can set their own priorities and timelines for reform towards quality. Self-paced planning I contend, will not be branded as technobureaucratic control, but will serve a developmental purpose towards inculcation and ownership of quality milestones.
Keywords: Administration of Education Programs; African Virtual University (Nairobi, Kenya); All Other Miscellaneous Schools and Instruction; Curriculum; Education; Educational Support Services; Emotion regulation; Kenya; Nairobi (Kenya); Quality assurance; Skepticism

Music and Physical Play: What Can We Learn From Early Childhood Teachers in Kenya? - Freshwater, Amy; Sherwood, Elizabeth; Mbugua, Esther (Music and Physical Play: What Can We Learn From Early Childhood Teachers in Kenya?, 2008)
Vignettes that capture Kenyan early childhood teaching practices highlight how Kenyan teachers use multiple musical and physical strategies to promote meaningful learning. These vignettes illustrate how teachers teach language development through music, use music to teach social skills and support emotional development, foster logico-mathematical skills through music, encourage physical development through music, and use music to teach personal safety, autonomy, and mastery.
Keywords: Dance in education; Developmentally appropriate education; Early childhood education; Education; Education research; Kenya; Language arts (Early childhood); Music education; Music in education; Play; Preschools

The role of cognitive skills in economic development - Hanushek, Eric A.; Woessmann, Ludger (Journal of Economic Literature, 2008)
The role of improved schooling, a central part of most development strategies, has become controversial because expansion of school attainment has not guaranteed improved economic conditions. This paper reviews the role of cognitive skills in promoting economic well-being, with a particular focus on the role of school quality and quantity. It concludes that there is strong evidence that the cognitive skills of the population—rather than mere school attainment—are powerfully related to individual earnings, to the distribution of income, and to economic growth. New empirical results show the importance of both minimal and high level skills, the complementarity of skills and the quality of economic institutions, and the robustness of the relationship between skills and growth. International comparisons incorporating expanded data on cognitive skills reveal much larger skill deficits in developing countries than generally derived from just school enrollment and attainment. The magnitude of change needed makes clear that closing the economic gap with developed countries will require major structural changes in schooling institutions.
Keywords: Aggregate Productivity; Analysis of Education; Analysis of Education, Human Capital; Cross-Country Output Convergence; Human Capital; Skills; Occupational Choice; Labor Productivity; Labor Productivity, Wage Level and Structure; Measurement of Economic Growth; Aggregate Productivity; Cross-Country Output Convergence; Occupational Choice; Skills; Wage Differentials, Measurement of Economic Growth; Wage Level and Structure; Wage Differentials

Examining Aspects of Linguistic Knowledge of Anglophone Primary School Teachers of North West Province of Cameroon in Relation to Children's Literacy Achievement - Ghong, Mary Njang (Texas A&M UniversityUniversity Microfilms International (UMI); ProQuest, 2008)
Keywords: Cameroon; English language teaching; second language reading

Adopt-a-Marathoner: Making the Most of School-Business Alliances. - Silver, Ilene S. (Adopt-a-Marathoner: Making the Most of School-Business Alliances., 2008)
Adopt-a-Marathoner is the outcome of an alliance between Elmwood School, Massachusetts, and John Hancock Inc. Through the program, students meet Kenyan runners who compete in the Boston Marathon. In addition, they learn about Kenya through activities integrated in the language arts, social studies, mathematics, and technology curriculum.
Keywords: Boston Marathon; Business & education; Educational cooperation; Educational programs; Elementary school curriculum; Hopkinton (Mass.); John Hancock (Company); Massachusetts; Partnerships in education; Schools

Girls Raise Cash for Kenya. - Birdsall, Bart (Girls Raise Cash for Kenya., 2008)
The writer discusses Literacy Leads to Hope, a fund-raising initiative launched to support the American Friends of Kenya organization by Danielle Rodriguez and Megan Adams, both high school juniors at the Academy of the Holy Names in Tampa, Florida. The recent political violence in Kenya, while jeopardizing the girls' objective of raising enough money to build and set up a library in Thika, has only made them more determined.
Keywords: Adams, Megan; Education; Finance; Fundraising; International economic assistance; Kenya; Libraries; Literacy; Rodriguez, Danielle

A Future in Rubbish. - Labi, Aisha (A Future in Rubbish., 2008)
The article presents a profile of Sammy Gitau, a Kenyan who managed to overcome many obstacles and complete a two-year degree at the University of Manchester in England. Gitau began supporting his mother and 10 siblings at age 13, after his father's death. In the slums of Kenya's Mathare Valley he turned to petty crime and drugs, as there were few opportunities for legitimate work. After a personal crisis, Gitau began working with local youth to try to improve the slum area where he lived. He learned of the international development program at Manchester and with the help of a European Union official who was impressed with Gitau's efforts he received the preliminary education and support he needed to enter and complete the program, which he intends to put to use back in Kenya.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Economic development; Education; Educational Support Services; Foreign study; Gitau, Sammy; Kenya; Kenyans; Mathare Valley (Nairobi, Kenya); Social conditions of developing countries; University of Manchester

The Changing Landscape of Education in Africa: Quality, Equality and Democracy - Johnson, David (Symposium Books, 2008)
It is 40 years since Coombs (1967) first drew attention to the World Education Crisis, and specifically problems in the educational systems of countries in the developing world. Today, many of these problems remain, and are most visible in the educational systems of countries in sub-Saharan Africa. A large number of children remain out of school and for those who do enrol, less than half complete the primary education cycle. More worrying is the fact that those who do complete primary schooling leave with unacceptably low levels of knowledge and skills. The problems of access to education, and the quality of learning opportunities and learning outcomes are unevenly spread between rural and urban areas, better- and worse-off constituencies, and between boys and girls. This raises questions about the nature of the state and its commitment to equality and equity for all. The chapters in this volume argue that quality, equity and democratic accountability are inseparable objectives in the quest to strengthen and improve educational systems in the developing world. Between them they highlight the specific problems of quality, equity and democratic accountability in a number of African educational systems, and provide useful insights into ongoing work by national governments and international donor agencies to remedy these shortcomings. Contents include: Introduction (David Johnson and William Beinart); The Challenge of Learning: Improving the Quality of Basic Education in Sub-Sahara Africa (Andriaan M. Verspoor); Improving the Quality of Education in Nigeria: A Comparative Evaluation of Recent Policy Imperatives (David Johnson); Education and Democracy in The Gambia: Reflections on the Position of Development Projects in a Small African State (Michele Schweisfurth); International and Comparative Research and the Quality of Education: Learning from the Primary School Management Project in Kenya (Michael Crossley); Remaking the Nation: Changing Masculinities and Education in South Africa (Elaine Unterhalter); Redressing School Inequalities in the Eastern Cape, South Africa (Anthony Lemon); Language, Literacy and Equality: minority language communities in the Cameroon (Barbara Trudell); and Gatherers of Knowledge: Namibian Khoisan Healers and their World of Possibilities (Chris Low.)
Keywords: Access to Education; Accountability; Africa; Cameroon; Comparative Analysis; Democracy; Democratic Values; Developing Nations; Educational Change; Educational Improvement; Educational Policy; Educational Quality; Educational Research; Elementary Education; Equal Education; Foreign Countries; Gambia; Indigenous Knowledge; Kenya; Knowledge Level; Language Usage; Literacy; Masculinity; Minority Groups; Namibia; Nigeria; Social Influences; South Africa

Demographic and Health Survey 2008 - Government of Kenya (Government Printer, 2008)

Balancing basic and post-basic education in Kenya: National versus international policy agendas - King, Kenneth (Balancing basic and post-basic education in Kenya: National versus international policy agendas, 2007)
Abstract: The article traces the policy history of Kenya over more than 40 years (1963–2006) in order to tease out the tensions between the key themes of its own national agenda and the priorities of its principal development partners. The national concerns with the education-and-employment connection and with the orientation of schooling towards skills for work in the formal and informal economies can be contrasted with the aid agency priorities on quality and on education-for-poverty reduction. Equally, national preoccupations have been with the whole of the education and training system—from early childhood, to technical, to university. By contrast, external donors have frequently prioritised a particular sub-sector such as primary schooling. In the most recent period, 2002–2006, the paper identifies the emergence of common ground between the national and external agendas. Thus the international education agenda, as marked out by the UN Millennium Project, the Commission for Africa, and the World Bank''s most recent education policy paper, is not dissimilar in its priorities to the latest Kenyan education agenda, as expressed in the Kenya Education Sector Support Programme. There is also an agreement that the education sector, on its own, cannot deliver the many benefits so often associated with schooling; rather, there needs to be an enabling environment in other sectors of the economy, if the investment in education is to be most productive. The one area where there is serious divergence, between the Government of Kenya, and, at least, its principal Western donors is on the treatment of corruption. At the point of writing, the extent of corruption remains a major threat to the external funding so necessary to Kenya''s large educational ambitions. Though the article is primarily concerned to analyse the tension between the national and the international policy agendas in terms of Kenya, arguably a similar case could be developed for many other countries in Sub-Saharan Africa, and not least those which are most donor-dependent.
Keywords: Basic education; Educational planning; Kenya; Poverty

Balancing basic and post-basic education in Kenya: National versus international policy agendas - King, Kenneth (Balancing basic and post-basic education in Kenya: National versus international policy agendas, 2007)
Abstract: The article traces the policy history of Kenya over more than 40 years (1963–2006) in order to tease out the tensions between the key themes of its own national agenda and the priorities of its principal development partners. The national concerns with the education-and-employment connection and with the orientation of schooling towards skills for work in the formal and informal economies can be contrasted with the aid agency priorities on quality and on education-for-poverty reduction. Equally, national preoccupations have been with the whole of the education and training system—from early childhood, to technical, to university. By contrast, external donors have frequently prioritised a particular sub-sector such as primary schooling. In the most recent period, 2002–2006, the paper identifies the emergence of common ground between the national and external agendas. Thus the international education agenda, as marked out by the UN Millennium Project, the Commission for Africa, and the World Bank''s most recent education policy paper, is not dissimilar in its priorities to the latest Kenyan education agenda, as expressed in the Kenya Education Sector Support Programme. There is also an agreement that the education sector, on its own, cannot deliver the many benefits so often associated with schooling; rather, there needs to be an enabling environment in other sectors of the economy, if the investment in education is to be most productive. The one area where there is serious divergence, between the Government of Kenya, and, at least, its principal Western donors is on the treatment of corruption. At the point of writing, the extent of corruption remains a major threat to the external funding so necessary to Kenya''s large educational ambitions. Though the article is primarily concerned to analyse the tension between the national and the international policy agendas in terms of Kenya, arguably a similar case could be developed for many other countries in Sub-Saharan Africa, and not least those which are most donor-dependent.
Keywords: Basic education; Educational planning; Kenya; Poverty

Balancing Basic and Post-Basic Education in Kenya: National versus International Policy Agendas - King, Kenneth (Balancing Basic and Post-Basic Education in Kenya: National versus International Policy Agendas, 2007)
The article traces the policy history of Kenya over more than 40 years (1963-2006) in order to tease out the tensions between the key themes of its own national agenda and the priorities of its principal development partners. The national concerns with the education-and-employment connection and with the orientation of schooling towards skills for work in the formal and informal economies can be contrasted with the aid agency priorities on quality and on education-for-poverty reduction. Equally, national preoccupations have been with the whole of the education and training system--from early childhood, to technical, to university. By contrast, external donors have frequently prioritised a particular sub-sector such as primary schooling. In the most recent period, 2002-2006, the paper identifies the emergence of common ground between the national and external agendas. Thus the international education agenda, as marked out by the UN Millennium Project, the Commission for Africa, and the World Bank's most recent education policy paper, is not dissimilar in its priorities to the latest Kenyan education agenda, as expressed in the Kenya Education Sector Support Programme. There is also an agreement that the education sector, on its own, cannot deliver the many benefits so often associated with schooling; rather, there needs to be an enabling environment in other sectors of the economy, if the investment in education is to be most productive. The one area where there is serious divergence, between the Government of Kenya, and, at least, its principal Western donors is on the treatment of corruption. At the point of writing, the extent of corruption remains a major threat to the external funding so necessary to Kenya's large educational ambitions. Though the article is primarily concerned to analyse the tension between the national and the international policy agendas in terms of Kenya, arguably a similar case could be developed for many other countries in Sub-Saharan Africa, and not least those which are most donor-dependent.
Keywords: Developing Nations; Donors; Economic Development; Education Work Relationship; Educational History; Educational Policy; Ethics; Foreign Countries; Foreign Policy; Kenya; Outcomes of Education; Poverty; Role of Education

The Contribution of the Competency-based Approach to Education for all in Cameroon - Bipoupout, J C (Prospects, 2007)
Issue Title: Curriculum Change and Competency-based Approaches: A Worldwide Perspective Taking place in a context where national policy is concerned about Education for All (EFA), where the educational provision to satisfy political, economic and social demands for a changing world falls well below the minimal requirements, and where international organizations demand signs of more significant progress, this article presents in an analytical manner the contribution made by the competency-based approach to EFA in Cameroon. In fact, the introduction of this approach in an effort to tackle primary school repetition led to remarkable results including not only an improvement in classroom practice with teaching/learning experiences that take into account the principles of the competency-based approach within the provision of remedial teaching, but also by the significant positive contribution towards the achievement of EFA in general and a more effective and equitable school in particular. This analysis ends with a presentation of the implications of the widespread introduction of these positive effects.[PUBLICATION ABSTRACT]
Keywords: Access to Education; Cameroon; Competence; Computer Assisted Instruction; Education; Education For All; International Organizations; International organizations; Perspective Taking; Remedial Instruction; Remedy; Teaching Methods

An integrative review of teaching reading in Kenyan primary schools. - Commeyras, Michelle; Inyega, Hellen N. (An integrative review of teaching reading in Kenyan primary schools., 2007)
THIS INTEGRATIVE review on the teaching of reading in Kenyan primary schools provides a foundation for the growing movement there to improve reading education. In gathering sources for this review, we took an inclusive historical stance. Thus, we did not dismiss research reports that lacked traditional indicators of quality such as being published in peer-reviewed journals. We used multiple methods to find relevant research and associated documents, including two trips to Kenya. The review is organized by six topics: (a) language of instruction, (b) reading instruction, (c) reading materials, (d) reading culture, (e) assessment, and (f) teacher development. The review concludes with six proposals for policymakers, educational researchers, and teacher educators for the development of reading instruction based on what we learned in reviewing the literature. The first proposals are intended specifically to address the teaching of reading in Kenya, but they may be relevant to other sub-Saharan nations. The final proposal encourages others to conduct similar reviews to make possible a handbook of reading in Africa. Reprinted by permission of the publisher.
Keywords: Africa; Education policy; Educational evaluation; Kenya; Meta-analysis; Primary school teachers; Reading; Reading (Elementary); Reading research; Teaching research

Parental participation in pupils' homework in Kenya: In search of an inclusive policy. - Ogoye-Ndegwa, Charles; Mengich, William Saisi; Abidha, Ombech (Parental participation in pupils' homework in Kenya: In search of an inclusive policy., 2007)
Homework is assigned on the assumption that parents or other elder members have the capacity to assist the pupils and that home environment is conducive for the pupil to do homework. A cross-sectional survey using structured and semi-structured interviews was conducted among pupils and parents in Kengeleni division in Mombasa district to explore socio-cultural and economic factors that influence parental participation in pupils' homework and, consequently, propose recommendations for homework policy formulation. The results show that although parental willingness to be involved in pupils' homework is high, this involvement is hampered by many socio-economic factors, including illiteracy and low income. On many occasions, homework is not only incomplete, but also not done, and the pupils are consequently punished for this. In the absence of clear, written policy on homework, there is a poor fit of inclusion of homework as the unwritten part of the curriculum.
Keywords: Home environment; Homework; Kenya; Literacy; Mombasa (Kenya); Parent participation in education; Parent-child relationships; Poor people; School children

Parental participation in pupils' homework in Kenya: In search of an inclusive policy. - Ogoye-Ndegwa, Charles; Mengich, William Saisi; Abidha, Ombech (Parental participation in pupils' homework in Kenya: In search of an inclusive policy., 2007)
Homework is assigned on the assumption that parents or other elder members have the capacity to assist the pupils and that home environment is conducive for the pupil to do homework. A cross-sectional survey using structured and semi-structured interviews was conducted among pupils and parents in Kengeleni division in Mombasa district to explore socio-cultural and economic factors that influence parental participation in pupils' homework and, consequently, propose recommendations for homework policy formulation. The results show that although parental willingness to be involved in pupils' homework is high, this involvement is hampered by many socio-economic factors, including illiteracy and low income. On many occasions, homework is not only incomplete, but also not done, and the pupils are consequently punished for this. In the absence of clear, written policy on homework, there is a poor fit of inclusion of homework as the unwritten part of the curriculum.
Keywords: Home environment; Homework; Kenya; Literacy; Mombasa (Kenya); Parent participation in education; Parent-child relationships; Poor people; School children

The Discourse of Whole Class Teaching: A Comparative Study of Kenyan and Nigerian Primary English Lessons. - Abd-Kadir, Jan; Hardman, Frank (The Discourse of Whole Class Teaching: A Comparative Study of Kenyan and Nigerian Primary English Lessons., 2007)
This paper explores the discourse of whole class teaching in Kenyan and Nigerian primary school English lessons. Twenty lessons were analysed using a system of discourse analysis focusing on the teacher-led three-part exchange sequence of Initiation -- Response -- Feedback (IRF). The focus of the analysis was on the first and third part of the IRF sequence as it is here that research suggests teachers can enhance pupil learning through questions and follow-up which asks pupils to expand on their thinking, justify or clarify their opinions, or make connections to their own experiences. The findings suggest that teacher questions were mainly closed requiring recall of information and teacher follow-up, where it occurred, often consisting of a low level evaluation of a pupil response, thereby severely constraining opportunities for pupil participation in the classroom discourse and higher order thinking. The implications of the findings are considered in the light of their impact on classroom pedagogy and the professional development of Kenyan and Nigerian primary teachers.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Discourse analysis; Education research; Educational Support Services; Kenya; Language & education; Lectures & lecturing; Nigeria; Research; Teacher-student communication; Teachers

The Discourse of Whole Class Teaching: A Comparative Study of Kenyan and Nigerian Primary English Lessons - Abd-Kadir, Jan; Hardman, Frank (The Discourse of Whole Class Teaching: A Comparative Study of Kenyan and Nigerian Primary English Lessons, 2007)
This paper explores the discourse of whole class teaching in Kenyan and Nigerian primary school English lessons. Twenty lessons were analysed using a system of discourse analysis focusing on the teacher-led three-part exchange sequence of Initiation-Response-Feedback (IRF). The focus of the analysis was on the first and third part of the IRF sequence as it is here that research suggests teachers can enhance pupil learning through questions and follow-up which asks pupils to expand on their thinking, justify or clarify their opinions, or make connections to their own experiences. The findings suggest that teacher questions were mainly closed requiring recall of information and teacher follow-up, where it occurred, often consisting of a low level evaluation of a pupil response, thereby severely constraining opportunities for pupil participation in the classroom discourse and higher order thinking. The implications of the findings are considered in the light of their impact on classroom pedagogy and the professional development of Kenyan and Nigerian primary teachers.
Keywords: Classroom Communication; Comparative Analysis; Discourse Analysis; Elementary School Students; Elementary School Teachers; English (Second Language); Faculty Development; Foreign Countries; Kenya; Nigeria; Second Language Instruction; Student Participation; Teaching Methods

An Integrative Review of Teaching Reading in Kenyan Primary Schools - Commeyras, Michelle; Inyega, Hellen N. (An Integrative Review of Teaching Reading in Kenyan Primary Schools, 2007)
This integrative review on the teaching of reading in Kenyan primary schools provides a foundation for the growing movement there to improve reading education. In gathering sources for this review, we took an inclusive historical stance. Thus, we did not dismiss research reports that lacked traditional indicators of quality such as being published in peer-reviewed journals. We used multiple methods to find relevant research and associated documents, including two trips to Kenya. The review is organized by six topics: (a) language of instruction, (b) reading instruction, (c) reading materials, (d) reading culture, (e) assessment, and (f) teacher development. The review concludes with six proposals for policymakers, educational researchers, and teacher educators for the development of reading instruction based on what we learned in reviewing the literature. The first proposals are intended specifically to address the teaching of reading in Kenya, but they may be relevant to other sub-Saharan nations. The final proposal encourages others to conduct similar reviews to make possible a handbook of reading in Africa.
Keywords: Educational Research; Elementary Schools; Foreign Countries; Kenya; Language of Instruction; Professional Development; Reading Instruction; Reading Materials; Teacher Educators

Forum on Flexible Education. Reaching Nomadic Populations in Africa. Summary Report - de Souza, Alba; Commonwealth of Learning (Commonwealth of Learning, 2007)
This report describes the Forum on Flexible Education: Reaching Nomadic Populations in Africa, which was held in Garissa, Kenya, from 20-23 June 2006. The objectives of the Forum were to share experiences and best practices, create linkages and encourage collaboration in order to make education more accessible to nomadic communities. Representatives from the Kenyan MOE, COL, ComSec and UNICEF provided remarks at the Opening Session of the Forum. They stressed the need to find ways to include nomadic children in the education process and the importance of developing alternative channels for the delivery of education and training. There were two keynote addresses. The first, from Professor Gidado Tahir, Executive Secretary of the Universal Basic Education Commission in Nigeria--presented by his colleague, Dr Salihu Bakari--focused on the realities of the nomadic lifestyle and educational strategies that have been effective. The second, by Dr. Nafisa Muhammad and Professor M. I. Junaid from the Nigerian National Commission for Nomadic Education (NCNE), provided an overview of innovative interventions in nomadic education in that country over the past decade. The Forum covered issues related to the following topics: (1) Ensuring basic education for all; (2) Access to education and training for girls and women; (3) Teacher/facilitator training; (4) Skills training; and (5) Government policy. The Forum concluded with nine Recommendations for Action for improving access to education for nomadic groups. Appendices include: (1) Keynote Address: Nomadic Life and the Implication for Education Provision; (2) Forum on Flexible Education: Reaching Nomadic Populations in Africa. Background Paper; (3) List of Participants; and (4) Forum Agenda.
Keywords: Access to Education; Adjustment (to Environment); Adult Basic Education; Africa; Educational Innovation; Educational Strategies; Foreign Countries; Instructional Effectiveness; Kenya; Literacy; Migrants; Nigeria; School Community Relationship; Sex Fairness; Tanzania

Chapter 5: Policies on Free Primary and Secondary Education in East Africa--Retrospect and Prospect - Oketch, Moses; Rolleston, Caine (Chapter 5: Policies on Free Primary and Secondary Education in East Africa--Retrospect and Prospect, 2007)
This article reviews the evolution of education policies in the East African region in a historical context. The focus is on the formulation of policies for access to primary and secondary education in Kenya, Uganda, and Tanzania since their independence in the 1960s. The three countries have common characteristics and historical backgrounds. For example, few of their population had access to education at all levels in the past, and hence, each faced similar educational and literacy challenges at the time of their political independence in the 1960s. All three have over time been characterized by Consortium for Research on Education Access, Transition and Equity (CREATE) zones of exclusion (i.e., those with no access, those who are excluded after initial entry, those at risk of dropout, and those excluded from secondary education). They have similarly announced and implemented new policies for Free Primary Education (FPE) following the international and internal pressure leading to the reintroduction of multiparty politics in the late 1990s. However, the three countries have had different experiences with the implementation of both Universal Primary Education (UPE) in the 1960s and FPE in the 1990s and have differed in the philosophies underpinning their education expansion more generally. This article is organized as follows: First, the authors discuss policies and action taken by governments of the three countries in the immediate postindependence era in relation to expanding access to those who had been excluded by the colonial education policies. Second, they present the formulation of those policies again in relation to how and whom they benefited. Third, they discuss implementation strategies and processes of those policies. Fourth, they discuss their institutionalization, replicability, and financial sustainability. Fifth, they outline the implications of these policies for the poorest groups. Sixth, they provide an overview of recent policies on access to secondary education and ask whom they have benefited and how the excluded groups can be reached. The conclusion follows. (Contains 2 figures and 2 tables.)
Keywords: Access to Education; Africa; At Risk Persons; Disadvantaged Youth; Educational Change; Educational History; Educational Policy; Elementary Secondary Education; Enrollment Trends; Equal Education; Females; Foreign Countries; Gender Bias; Kenya; Policy Formation; Politics of Education; Public Education; Tanzania; Uganda

The effect of in-service education and training (INSET) programmes in mathematics and science on classroom interaction: a case study of primary and secondary schools in Kenya. - Sifuna, Daniel N.; Kaime, James G. (The effect of in-service education and training (INSET) programmes in mathematics and science on classroom interaction: a case study of primary and secondary schools in Kenya., 2007)
The purpose of this study was to assess the effectiveness of the Strengthening of Mathematics and Science in Secondary Education (SMASSE) and the School-based Teacher Development (SbTD) programmes on classroom interaction in secondary and primary schools in Kenya. It was a case study which focused on four districts, and included holding interviews with 185 teachers, observing lessons and holding focus group discussions with pupils and students. It was established that, while teachers evaluated the two INSET programmes as having been effective in exposing them to a student-centred approach, this was not reflected in their classroom practices which were largely teacher dominated. This is partly attributed to large classes, the use of English as a second language and pressure to cover the syllabuses in preparation of the national examinations. It is however, recommended that the Ministry of Education mainstream INSET programmes in its policy for teacher development in the country.
Keywords: Elementary and Secondary Schools; Foreign language education; Forums; Kenya; Language Schools; Mathematics education (Secondary); Science education (Secondary); Secondary education; Teacher development

Kenya Vision 2030 - Republic of Kenya (2007)

Discretion and Control in Education: The Teacher as Street-level Bureaucrat - Taylor, Ian (Educational Management Administration & Leadership, 2007)
This article assesses the impact of education reform and the new public management (NPM) on the discretion of school teachers. The focal point of the study is Michael Lipsky's theory of discretion which casts public service professionals and others involved in service delivery as `street-level bureaucrats' because their high degree of discretionary rule-making power enabled them to effectively make policy as well as implement it. The article considers the relationship between education reform and the NPM and focuses on the increased emphasis on skills-based teaching and changes in management and leadership in schools. The literature and survey of teachers demonstrate that discretion in the workplace has been eroded to such an extent due to a high degree of central regulation and local accountability as to question the applicability of Lipsky's model. The findings are based on the literature and a small survey undertaken by the author.

Poor African countries need regional research institute. - MacGregor, Karen (Poor African countries need regional research institute., 2006)
In his keynote speech at the 16th Conference of Commonwealth Education Ministers in South Africa, renowned African scholar Mahmood Mamdani called for the creation of regional research institutions for clusters of countries to be made a developmental focus for the Commonwealth. Noting that only African countries with a dense network of universities seemed able to pay for research universities, Mamdani argued that smaller countries, such as Uganda, Kenya, and Tanzania, should collaborate to create a regional research university.
Keywords: Africa; Conferences & conventions; Higher education; Partnerships in education; Primary education; Research institutes; Right to education; Universities & colleges

Towards the making of education policy in Kenya: Conclusions and implications. - Oduol, Truphena (Towards the making of education policy in Kenya: Conclusions and implications., 2006)
Keywords: Academic achievement; Education; Education policy; Kenya; Mathematics; Reading level of students; Schools research

Towards the Making of Education Policy in Kenya: Conclusions and Implications - Oduol, Truphena (Towards the Making of Education Policy in Kenya: Conclusions and Implications, 2006)
This paper uses the SACMEQ II data to carry out an analysis of classroom context factors that accounted for student scores in reading and mathematics as well as a review of methods used to derive policies in Kenya in order to emphasise the need for evidence-based research for the derivation of policies for the leadership and management of primary education in Kenya. The paper goes further to explain the advantages of the approach as well as some of the impediments. Some suggestions of measures needed to foster the approach are provided. It emphasises that this approach is a necessary ingredient for effectiveness and efficiency in education. (Contains 1 table.)
Keywords: Causal Models; Classroom Research; Educational Administration; Educational Policy; Educational Principles; Elementary Education; Foreign Countries; Inferences; Kenya; Mathematics Achievement; Performance Factors; Policy Formation; Reading Achievement; School Effectiveness; Theory Practice Relationship

Recognizing Neglected Strengths - Sternberg, Robert J. (Recognizing Neglected Strengths, 2006)
To identify diverse student strengths and to learn how teachers can build instruction on those strengths, the author and his colleagues have conducted multiple studies among students in Alaska, the mainland United States, Kenya, and other countries. In a series of studies in Alaska and Kenya, the researchers measured the adaptive cultural knowledge and skills of native Alaskan students and rural Kenyan students and demonstrated that instruction geared to these cultural skills improved academic achievement. In another series of studies, the researchers grouped students by their cognitive areas of strength (memory, analysis, creativity, and practical intelligence) and found that students performed better when they were taught in ways that were compatible with their strengths. The author's conclusion: When schools teach in ways that respect students' different strengths, students learn and perform better. (Contains 1 figure.)
Keywords: Academic Ability; Academic Achievement; Alaska; Alaska Natives; Comparative Education; Culturally Relevant Education; Elementary School Students; Foreign Countries; Indigenous Knowledge; Kenya; Mathematics Curriculum; Minority Groups; Secondary School Students; Teaching Methods; Thinking Skills; United States

Internationalising a learning environment instrument for evaluating transnational online university courses. - Yeo, Shelley; Taylor, Peter; Kulski, Martijntje (Internationalising a learning environment instrument for evaluating transnational online university courses., 2006)
This article describes the adaptation and validation of the Constructivist OnLine Learning Environment Survey (COLLES) for use in the transnational higher education context. As higher education becomes a more global phenomenon, ‘borderless’ education, either online or by distance education, is becoming a reality and there is a need for remote evaluation of course delivery and student learning. Curtin University of Technology is managing supported online delivery of Business Studies Degree and Diploma courses to four partner institutions of the African Virtual University, an initiative based in Nairobi, Kenya. Evaluation of students’ learning has included an online survey about the provision of resources and the quality of the learning environment in the various computer-based classrooms. Embedded in this instrument has been the adapted COLLES, providing a concomitant opportunity to test the properties and usefulness of the learning environment instrument. Problematic issues surrounding adaptation of the instrument have included the consequences of modifying the wording and establishing or confirming the meaning of the latent constructs in partially online courses and for transnational students. The process of establishing the validity and reliability of the scales is discussed.
Keywords: Academic degrees; Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Colleges, Universities, and Professional Schools; Distance education; Education; Educational Support Services; Internet in education; Nairobi (Kenya); Students; Surveys; Transnational education; Universities & colleges

National Early Childhood Development Policy Framework 2006 - Republic of Kenya (2006)

Language development and social uses of literacy: A study of literacy practices in Cameroonian minority language communities - Trudell, Barbara (International Journal of Bilingual Education and Bilingualism, 2006)
In Northwest Cameroon, the emergence of literacy in the mother tongue is providing minority language communities with new alternatives for learning and communication. To some extent, these alternatives are shaped by existing literacy practices in English, as English is the language of formal education. However, new spaces are also emerging in society for the use of literacy in the mother tongue. This paper examines the impact of mother-tongue literacy on attitudes towards, and uses of, written text in the Bafut, Kom and Nso' language communities of Northwest Cameroon. The paper is based on qualitative case study research conducted in these communities in 2002-2003. The paper concludes with a discussion of the future of mother-tongue literacy in the Bafut, Kom and Nso' language communities.
Keywords: African Languages; Cameroon; Case Studies; Case study; ERIC, Current Index to Journals in Education (CIJE); English (Second Language); English for Academic Purposes; Foreign Countries; Language Acquisition; Language Attitudes; Language Minorities; Language Usage; Literacy; Qualitative Research; Qualitative research; Second Language Learning; Sociolinguistics

Next Up for Developing Nations: Secondary Schooling. - Keller, Bess (Next Up for Developing Nations: Secondary Schooling., 2005)
The widespread move toward a free basic education for all in developing nations has raised parents' and policymakers' interest in secondary education. In general, policymakers in such countries, as well as many development strategists, believe that there is a link between secondary education and the opportunity to compete vigorously in a global economy. Some of the challenges to secondary education in developing countries are discussed.
Keywords: Africa; Basic education; Developing countries; Education; Education policy; Kenya; Primary school facilities; Secondary education

Barriers to Participation in Adult Literacy Programs in Kenya. - Muiru, John; Mukuria, Gathogo (Barriers to Participation in Adult Literacy Programs in Kenya., 2005)
To compete internationally, adapt to new technologies, and attain higher levels of efficiency and productivity, a country needs a highly literate populace. However, in Kenya literacy stands at less than 65% of the population. With such a low rate of literacy, most development is hampered. In order for Kenya to make progress in political, social, and economic development, the level of literacy has to be raised. This paper makes an important contribution in the promotion of adult literacy in Kenya and other parts of the world by identifying and discussing the pertinent barriers to participation in adult literacy programs. Barriers such as the lack of adequate resources, poverty, the HIV/AIDS pandemic, gender disparities, traditionalism, and the absence of a literacy environment are discussed. The paper also makes suggestions on how the effects of these barriers can be mitigated. Reprinted by permission of the publisher.
Keywords: Adult education; Education; Education policy; Educational technology; Functional literacy; Kenya; Literacy education; Literacy policy; Literacy programs; Social history; Socioeconomics

BEING AN ADULT LITERACY EDUCATION STUDENT IN KENYA. - Muiru, John; McLean, Gary N. (BEING AN ADULT LITERACY EDUCATION STUDENT IN KENYA., 2005)
The focus of this hermeneutic phenomenological study was the experience of being an adult literacy education student in Kenya. Ten adult literacy education students in three learning centres were interviewed. A thematic analysis of the interview transcripts uncovered sixteen common themes in three broad categories: reasons for participating; effects of literacy in the daily lives of students and challenges students encountered.
Keywords: Administration of Education Programs; Adult education; Adult education research; All Other Miscellaneous Schools and Instruction; Education & society; Educational Support Services; Evaluation; General education; Hermeneutics; Kenya; Literacy; Literacy & society; Literacy research; Older students

The discourse of classroom interaction in Kenyan primary schools. - Pontefract, Caroline; Hardman, Frank (The discourse of classroom interaction in Kenyan primary schools., 2005)
This paper addresses the role of classroom discourse in supporting children's learning in Kenyan primary schools. The discourse strategies of 27 teachers teaching English, mathematics and science across the primary phase were intensively studied using discourse analysis and semi-structured interviews. A survey questionnaire (n=359) was also used to explore teacher perceptions of classroom discourse practices. The findings revealed the dominance of teacher-led recitation in which rote and repetition dominated the classroom discourse with little attention being paid to securing pupil understanding. The wider implications of the findings for improving the quality of classroom discourse in Kenyan primary schools are considered together with the need for further research into how the wider social order is influencing discourse practices in Kenyan primary schools. Reprinted by permission of the publisher.
Keywords: Discourse; Discussion in education; Early childhood education; Education; Elementary education; Elementary schools; Kenya; Primary education; Student participation; Teacher-student relationships; Teachers; Verbal behavior

Barriers to Participation in Adult Literacy Programs in Kenya - Muiru, John; Mukuria, Gathogo (Barriers to Participation in Adult Literacy Programs in Kenya, 2005)
To compete internationally, adapt to new technologies, and attain higher levels of efficiency and productivity, a country needs a highly literate populace. However, in Kenya, literacy stands at less than 65% of the population. With such a low rate of literacy, most development is hampered. In order for Kenya to make progress in political, social, and economic development, the level of literacy has to be raised. This paper makes an important contribution in the promotion of adult literacy in Kenya and other parts of the world by identifying and discussing the pertinent barriers to participation in adult literacy programs. Barriers such as the lack of adequate resources, poverty, the HIV/AIDS pandemic, gender disparities, traditionalism, and the absence of a literacy environment are discussed. The paper also makes suggestions on how the effects of these barriers can be mitigated.
Keywords: Adult Literacy; Economic Development; Foreign Countries; Gender Differences; Kenya; Literacy Education; Poverty; Sexually Transmitted Diseases

Editorial. (Editorial., 2004)
Two recent events occurred in the academic life of one of the editors of this journal. The first was a seminar presented at the University of Sydney by the Director of the Centre for Refugee Research at the University of New South Wales. The Director focused upon the ethics of research with extremely vulnerable populations such as refugees; in particular, refugee women who frequently experience systematised sexual torture and rape. She saw her work as a form of action research whose political intent was to change the appalling situation in which the women and young girls found themselves. She travelled to camps situated as far afield as the borders of Thailand and Burma, and the Kakuma refugee camp in Kenya. The refugees with whom she worked sought to develop skills that would enable them to tell and publish their stories as a means of shattering the silences surrounding the abuse of women such as themselves.The second event was an advisory session with a young academic who was crossing boundaries in his work between medical anthropology and adult education. He quickly strayed from the path of his formal doctoral candidature to discuss his passion, which was coaching a group of women as a ''barbershop'' choir. His desire was to write about the study as an action research project that embodied his development as he unravelled not only the management problems that he encountered along the way, but those related to his inclusion as the sole male in the enterprise.Two events manifestly different in substance, but each claiming an engagement with action research. Kemmis & Brennan (2003) characterise what they have termed participatory action research as that where:people aim to improve three things: their own practices, their understanding of their practices and the social realities in which they live and work. They do their research in a spiral of cycles of self-reflection. They make an initial reconnaissance of their situation, then work out what they could do to improve things. (p. 3)Whether considering the transformation and emancipation of cruelly abused refugee women or the increased enlightenment of a musical impresario, action research as a modus operandi acted to open up the communicative space that each required in ways that were neither oppressive nor exploitative. Such is the case with this edition of the journal. Each contribution, in one way or another, serves to open up a communicative space that will allow debate and discussion about practice, whether at a systems, local or individual level. A number of the studies have been undertaken in widely differing national contexts and serve to illustrate how action research has had its impact upon practice in a number of different countries.ngel Prez Gmez outlines the contradictions and challenges of introducing comprehensive, compulsory education in Andalusia for students up to the age of 16. Following documentation of the developments, he argues that, while the intention was for a significant, planned reform, it may be better characterised as one that is, at best, an improvisation. The work of John Elliott has been acknowledged as an important influence upon the inquiry that was undertaken and the subsequent analysis of its results. Therefore, not only are the results of an action-orientated study reported here, but also there is an extensive set of guiding principles that could enable the reform to be truly actualised. Working in the Thai context, Kirin Sahasewiyon investigates the development of local curriculum in the Fang District, Chiang Mai Province. She discusses the factors that have consequences for the development of the curriculum, in the face of some initial resistance, through the action research of the teachers.Anjum Halai takes us to a consideration of the impact of action research upon classroom practices in the teaching of mathematics in Karachi, Pakistan. His study is viewed through the lens of teacher professional learning. Judy Peters challenges some cherished beliefs about the ways in which action research might be truly emancipatory in the State of South Australia with particular reference to assumptions that might be being made about the conditions under which teachers work. Thus, the communicative space that is opened up is not only with respect to a specific study, but also with regard to more broadly based teacher education practices.Partnerships and their rewards and challenges are the focus of many of the papers that are published in this edition. A collaborative piece of writing comes to us from Cincinnati in the USA, where two university academics work in collaboration with three classroom teachers (see Helen Meyer, Bennyce Hamilton, Steve Kroeger, Stephanie Stewart and Mary Brydon-Miller) to develop insight about daily classroom practice. From the United Kingdom, we read about the challenge to beginning teachers'' beliefs as they seek to straddle the world of the university and the world of the school. Adopting action research procedures has enabled the beginning teachers to extract principles that will assist them in new contexts in the future. Chris Day and Mark Hadfield''s piece looks at the corporate learning of schools in a network partnership, where self-selected primary schools in England have sought to work together, through action research, to enhance their understanding of their operational principles.New understandings emerge from Elaine Wilson''s work in which she uses activity theory as a tool to design an intervention program intended to equip beginning teachers with strategies to enhance their professional learning by extracting sound principles of practice. As an action learning project the process enlarged the communicative space available to all stakeholders: the university partner; the schools and the beginning teachers who were faced with often difficult and challenging circumstances in the context of high stakes assessment in the United Kingdom.Valerie Dagley''s article takes us more directly into the lived life of the classroom. She discusses the issue of ''making the invisible visible'' from a methodological and a substantive viewpoint. The ideas emerged from a doctoral research study into individual target setting with middle ability students in an English secondary school. The students involved had been identified by assessments as ''average'' and by their teachers as quiet, un-noticed children. It is suggested that the methods used by the researcher to elicit the students'' perceptions could also be used by teachers in order to engage these quiet students in a learning discourse, yet another communicative space.Finally, the theoretical resource, by Gaby Weiner ''tumbles us into the big ideas'' that Somekh (2003) wrote about in her review of a decade of such pieces. The article plots recent developments in feminist ideas and their relevance for critical action research. Recreating and reliving the ways in which we might consider our work is constructed for us by Weiner as she finds those things in common between feminism and action enquiry. Among other things she identifies:a critique of positivist research paradigms;a recognition of the place of values that are embedded in practice and lived experience;an understanding of historical and cultural roots;a view that such enquiry should aim to be transformative.This argument returns us to the beginning of this editorial. Whether the mission is to transform a global understanding of the oppression of women in refugee camps or the transformation of the self in new and unfamiliar circumstances it is possible to see from this edition of Educational Action Research, and of course those that preceded it, that we are in a serious and universalistic enterprise.The EditorsReferencesKemmis, S. & Brennan, R. (2003) Making and Writing the History of the Future Together: exploratory action in participatory action research, invited address to the Congreso Internacional de Educacion, Cordoba, Argentine Republic, 9-11 October.Somekh, B. (2003) Theory and Passion in Action Research, Educational Action Research, 11(2), pp. 247-264.
Keywords: Action research; Colleges, Universities, and Professional Schools; Educational anthropology; Research ethics; Universities & colleges

Educating Children in Poor Countries - Jenkner, Eva; Hillman, Arye L. (Educating Children in Poor Countries, 2004)
"Educating Children in Poor Countries" published on 23 Nov 2004 by International Monetary Fund.

Developmentally and Culturally Appropriate Practice in the Global Village: The Kenya Literacy Project. - Dunn, Maylan; Mutuku, Moses; Wolfe, Randi (Developmentally and Culturally Appropriate Practice in the Global Village: The Kenya Literacy Project., 2004)
Part of a special issue on young learners around the world. A team of American teacher educators is engaged in a cooperative venture with a rural community in Kenya to improve children's academic achievement. The first step in the cooperative venture involves the development of community resources and leaders. Participants also want to strengthen the educational infrastructure and improve educational practices in the local school. Some important lessons that the U.S. teacher educators have learned from the project are discussed.
Keywords: Academic achievement; American educational assistance; Children; Communities; Community development; Early childhood education; Education; Educators; Kenya; Reading

Language of Instruction: A Qualitative Analysis of the Perceptions of Parents, Pupils and Teachers Among the Kalenjin in Kenya. - Muthwii, Margaret Jepkirui (Language of Instruction: A Qualitative Analysis of the Perceptions of Parents, Pupils and Teachers Among the Kalenjin in Kenya., 2004)
The paper reports the results of a survey of parents (n = 12), teachers (n = 8) and pupils (n = 20) in primary schools in rural Kenya. The sample was divided equally between multilingual and monolingual schools, the former using English or Kiswahili only, right through primary school, the latter using the mother tongue (in this case, Kalenjin) Kalenjin in primary classes 1-3, and English or Kiswahili from primary class 4 on, where the children are on average 9 years old. Virtually all the respondents preferred using English or Kiswahili instead of their mother tongue as the language of instruction in primary classes 1-3. The paper discusses the findings and their implications for further research and policy-making.
Keywords: All Other Miscellaneous Schools and Instruction; Elementary and Secondary Schools; Kalenjin language; Kenya; Language & languages; Schools; Surveys

Persons with Disabilities Act - Republic of Kenya (2004)

Teaching and Learning High School Physics in Kenyan Classrooms Using Analogies. - Nashon, Samson Madera (Teaching and Learning High School Physics in Kenyan Classrooms Using Analogies., 2003)
This study provides insights into the nature of the analogies deployed by Kenyan physics teachers and generated by students in class. The analogies looked at (both teacher- and student-generated) were largely environmental (drawn from students' socio-cultural environment), anthropomorphic (life and human characteristics ascribed to analogues), and to a limited extent, scientific (analogue and target are science concepts). In some cases, anthropomorphic analogies proved problematic for students, sometimes resulting in serious misconceptions. Good analogy use is based on clear identification of mulching and non-matching features of the analogue-target structure. Several models, including the General Model for Analogy Teaching (GMAT). Teaching with Analagy (TWA) and Working with Analogies (WWA) are discussed in this paper, with a view to providing a lens through which analogies can be understood. To transform students' understanding from cultural belief systems to the science system of thinking, while respecting their socio-cultural backgrounds, can be a daunting task. Where it proves problematic for the students to 'decamp' from indigenous ways of reasoning, then collateral learning may be considered.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Analogy; Education; Educational Support Services; Kenya; Kenyans; Learning; Methodology; Physics education; Research and Development in the Social Sciences and Humanities; Social sciences; Teaching

DISPATCHES. - Harac, Lani (DISPATCHES., 2003)
Presents news briefs related to schools all over the world as of March 2003. Conducting of science and mathematics classes in English by schools in Malaysia; Cash incentives for students in Sweden for continuing their education; Benefits obtained by students from a move by the Kenyan government to provide free education to students in the country.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Elementary and Secondary Schools; Kenya; Schools; Students; Sweden

Reading for All in Africa: Building Communities Where Literacy Thrives. - Arua, Arua E.; International Reading Association, Newark (2003)
This collection of more than 40 papers was selected from more than 150 presentations at the 2nd Pan-African Conference on Reading sponsored by the Reading Association of Nigeria and the International Reading Association's International Development in Africa Committee. The collection is divided into seven sections. Under Section 1--Towards Building Literate Communities in Africa--is the following paper: "Towards a Reading Society" (Pai Obanya). Under Section 2--Promoting a Culture of Reading: General Issues--are these papers: "Destroying the Reading Culture-A Way Backwards: A Beginner's Guide to Millennial Ignorance" (Tony Marinho); "Concept of the Children's Reading Tent as Practised in Chitungwiza, Zimbabwe" (Agrena Mushonga); "Portable Libraries as Vehicles for Literacy Development: A Library Service to Pupils and Prisoners in Nigeria" (Virgina W. Dike); "Mobilising Local Resources for Reading Promotion" (Miriam Bamhare); "What Are Students in Botswana's High Schools Reading?" (Arua E. Arua and Mary Lederer); "Cultivating a Reading Culture in a High School in Swaziland" (Virginia Thontea Dlamini); "Family Basic Education in Uganda" (Simon Kisira); "Developing and Promoting Lifetime Reading Habits in Kenya: The Reading Tent Project and Njoro Reading Facility" (Margaret Makenzi); "Masifunde Sonke: Building a Nation of Readers in South Africa" (Mandla Maseko and Beulah Thumbadoo); "Reviving a Culture of Teaching and Learning through Parents and Schools Learning Clubs" (Letta Mashishi). Under Section 3--Promoting a Reading Culture: Book Development--are these papers: "Multipronged Approach to Promoting a Reading Culture: The East African Experience" (James Tumusiime); "Promoting a Reading Culture" (Pilli Dumea); "Association for Creative Teaching as an Agent for Book Development in Cameroon" (Patrick Mbunwe Samba; Mike Nwana; N.M. Tangu; Semuyeh Nyugab); "Demystifying Science for Children through Reading: The ELSSA Approach" (Sam T. Bajah); "Girls and Literacy: Gend
Keywords: Africa; Cultural Context; Elementary Secondary Education; Foreign Countries; Geographic Regions; Literacy; Reading; Reading Instruction; Reading Motivation

Voices of the Stakeholders: A Case of Power Mechanics in Kenya - Kitainge, Kisilu Mashtakh (Voices of the Stakeholders: A Case of Power Mechanics in Kenya, 2003)
The primary purpose of this study was to find out the attitudes of trainers and trainees towards the 8-4-4 power mechanics course offered in secondary schools in Kenya. The attitudes and other related aspects obtained from the trainers and trainees were used as evaluative devices for the course and hence the graduates of the course. A comparison between the 8-4-4 power mechanics graduates and non power mechanics trainees was done to establish how well they fit into the job market in the automotive industry and in further training institutions. All the automotive engineering trainers in middle level training institutions and the automotive industry, and 31 secondary school graduates of the power mechanics course were used as subjects. They were selected from institutions and industries in Nairobi, Thika and Mombasa towns. Likert types of questionnaires were used to obtain the required information for the attitude evaluation study. Data were analysed using: percentages, means, standard deviations, variances, t-test for the difference of mean, chi-square and the analysis of variance (ANOVA) statistical methods. Tests for significance were carried out at the 0.05 level of significance testing. It was found that there is no significant difference between the attitudes of the trainers and trainees towards the course and the graduates. In addition, the positive attitudes of both the trainers and the trainees were independent of the respondent's level of education. It did not matter whether the respondent was a trainee or a trainer. A significant difference was realised in the following areas: job performance, trainability, and performance in training examinations between the 8-4-4 power mechanics secondary school graduates and their non-power mechanics counterparts. The 8-4-4 power mechanics graduates were superior in all the above measured aspects. However, despite the 8-4-4 power mechanics secondary school graduates being better in comparison to others who had not taken the course, they were lacking in supervisory skills, creativity, mathematics, application of knowledge to practical situations, independence at work, innovativeness, and interpersonal skills.
Keywords: Attitude Measures; Auto Mechanics; Comparative Analysis; Course Evaluation; Education Work Relationship; Followup Studies; Foreign Countries; Graduates; Industry; Job Performance; Kenya; Labor Market; Power Technology; Program Effectiveness; Questionnaires; Secondary School Students; Stakeholders; Statistical Analysis; Student Attitudes; Supervisory Training; Teacher Attitudes; Trainers; Vocational Education; Vocational Education Teachers

Can free primary education meet the needs of the poor? Evidence from Malawi - Kadzamira, Esme; Rose, Pauline (International Journal of Educational Development, 2003)
Following elections in 1994, the Government of Malawi embarked on an ambitious programme of free primary education (FPE), resulting in a dramatic increase in enrolment. The paper argues that the policy did not sufficiently consider the ways in which direct and indirect costs of schooling continue to be prohibitive for some households, or the effects that the expansion would have on quality. The relevance of education for the majority of children who receive only a few years of primary schooling is also questioned. The paper suggests that FPE might not be contributing to the achievement of poverty alleviation goals, as intended.
Keywords: Development; Educational policy; Gender; International education; Malawi; Poverty

English in Francophone Elementary Grades in Cameroon - Kouega, Jean-Paul (Language and Education, 2003)
Since Reunification of French Cameroon and British Cameroons in 1961, the country has adopted French and English as its joint official languages and recommended the promotion of bilingualism in these two foreign languages in official domains. This paper focuses on the primary school level in the francophone sub system of education and examines the various measures that successive governments have taken. The first two measures failed to bear fruit, for various reasons including insufficient teachers and lack of teaching materials. The most recent measure still to be implemented makes the teaching of the second official language a compulsory subject in all primary school classes and a subject in both the First School Leaving Certificate and the "Certificat d'Etudes Primaires" (CEP), its French equivalent. This decision seems to have been taken hastily, as the problems of staff and materials are still not resolved. The position of the present researcher is that, as the Government is at present better prepared to provide teaching in one or other of the two official languages, it should make some French-medium and some English-medium schools available in as many localities as possible, and give parents the choice of which system they want for their children. (Contains 1 table and 5 notes.)
Keywords: Bilingualism; Cameroon; ERIC, Current Index to Journals in Education (CIJE); Elementary Education; Elementary Schools; English (Second Language); Foreign Countries; French; Instructional Materials; Language of Instruction; Official Languages; Required Courses; Second Language Instruction; Second Language Learning; Teacher Shortage

Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities - Max-Planck-Gesellschaft (2003)

College for women. - Kamotho, Kihumba (College for women., 2002)
In Kenya, Kiriri Women's University of Science and Technology has opened in a bid to improve women's access to science and technology courses. Kiriri, which is only the second women's university in East and Central Africa, will initially offer courses in mathematics and computer science and will later provide courses in physics, biology, and actuarial sciences.
Keywords: Education; Kenya; Universities & colleges; Women college students; Women's education

Putting Bread on the Table: Literacy and Livelihood in Kenya. Knowledge and Information Management. - Thompson, Ekundayo J. D.; Adult Education for Development, Nairobi (Kenya). (2002)
The effects of literacy and livelihood programs on female learners' participation in literacy were examined through case studies of groups of women who participated in four literacy and income-earning projects in Kenya. Data were collected through focus group discussions and a questionnaire. The four programs were started between 1968 and 1999 and included between 24 and 300 participants. All four programs offered different mixes of literacy components (mathematics, Kiswahili, mother tongue, reading, writing, nutrition and English) and livelihood components (handicraft, tailoring and dressmaking, business education, and handicraft marketing). The designs and delivery systems of all four groups featured close links between the uses of literacy and effective performance of livelihood activities. In all cases, the women stated that their effectiveness would have been constrained without literacy. The combination of literacy and livelihood components was credited with improving the women's income-earning effectiveness, increasing their self-esteem, changing their perceptions of the stereotypical roles of women, and helping them develop a strong sense of community. The case studies confirmed the need to reconsider the objectives of literacy in light of learners' changing needs and circumstances and documented the strong connection between linking literacy program objectives to learners' basic needs and rights and program success. (MN)
Keywords: Adult Basic Education; Adult Literacy; Case Studies; Community Development; Definitions; Delivery Systems; Developing Nations; Disadvantaged Environment; Education Work Relationship; Educational Improvement; Educational Policy; Educational Principles; Foreign Countries; Functional Literacy; Handicrafts; Illiteracy; Kenya; Learning Motivation; Literacy Education; Models; Outcomes of Education; Policy Formation; Poverty; Program Effectiveness; Self Esteem; Student Educational Objectives; Student Motivation; Womens Education

Parcours et paroles de jeunes analphabètes (Cameroun, Niger, Burkina Faso) - Barreteau, Daniel; Bayo Mana, Alioum; Fandar BaIdam, Jean-Claude; Yacouba, Tine; Yaro, Anselme (Journal des africanistes, 2002)
Keywords: Burkina Faso; CULTURAL ETHNOGRAPHY; Cameroon; Education; Literacy; Niger; Socioeconomic conditions; Young people

Education. - Thaker, Pratibha; Cowan, David (Country Profile. Kenya, 2001)
Focuses on the educational development in Kenya. Decline of the educational standards; Decrease in the number of enrollments and completions in both primary and secondary education; Disparities in the regional basic education of the country.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Kenya; Literacy

Primary education quality in francophone sub-Saharan Africa: Determinants of learning achievement and efficiency considerations - Michaelowa, Katharina (World Development, 2001)
What are the most efficient means to ensure basic learning competencies for a high number of children? This question is analyzed on the basis of the exceptionally rich data set provided by the "Program on the Analysis of Education Systems" (PASEC), standardized and comparable for the five countries Burkina Faso, Cameroon, Cote d'Ivoire, Madagascar and Senegal. A Hierarchical Linear Model (HLM) is used to assess the individual, school level, and national characteristics determining fifth-grade students' achievement in French and mathematics. Special consideration is given to institutional factors. A further question addressed is the possibility of a tradeoff between enrollment and education quality.
Keywords: Analysis of Education I21; Economic Development: Human Resources; Human Development; Income Distribution; Migration O15

Classroom Interaction in Kenyan Primary Schools. - Ackers, Jim; Hardman, Frank (Classroom Interaction in Kenyan Primary Schools., 2001)
This article reports on a study of classroom interaction in Kenyan primary schools carried out as part of a national baseline study for the Ministry of Education and Human Resource Development in 1998. The baseline was designed to provide a comprehensive picture of the quality of primary education so as to allow the Kenyan Government to prioritise expenditure on resources to improve education in the republic and to assess the impact of any interventions. Video recordings of 102 lessons in English, mathematics and science were analysed using systematic observation, discourse analysis and a time-line analysis. The findings revealed the domination of transmissional forms of teaching, thereby providing little opportunity for pupils to question or explore ideas to help regulate their own thinking. The wider implications of the findings for improving the quality of classroom interaction in Kenyan primary schools are considered together with the training needs of teachers.
Keywords: Classrooms; Kenya; Primary education

Classroom Interaction in Kenyan Primary Schools. - Ackers, Jim; Hardman, Frank (Classroom Interaction in Kenyan Primary Schools., 2001)
Reports on a study of classroom interaction in Kenyan primary schools. Analyzes video recordings of 102 lessons in English, mathematics, and science using systematic observation, discourse analysis, and a time-line analysis. Reveals the preponderance of teacher dominated lessons with little opportunity for student interaction. Considers educational needs of Kenyan teachers. (CAJ)
Keywords: Classroom Communication; Classroom Techniques; Comparative Education; Discourse Analysis; Elementary Education; Elementary Schools; Foreign Countries; Kenya; Observation; Research Methodology; Teacher Behavior; Teacher Education; Teacher Student Relationship; Teaching Styles; Videotape Recordings

Voices of Authority: Education and Linguistic Difference. Contemporary Studies in Linguistics and Education, Volume 1. - Heller, Monica; Martin-Jones, Marilyn (2001)
Chapters in this volume include the following: "Co-Constructing School Safetime: Safetalk Practices in Peruvian and South African Classrooms" (Nancy H. Hornberger, J. Keith Chick); "Codeswitching and Collusion: Classroom Interaction in Botswana Primary Schools" (Jo Arthur); "Language and Educational Inequality in Primary Classrooms in Kenya" (Grace Bunyi); "The Contradictions of Teaching Bilingually in Postcolonial Burundi: From Nyakatsi to Maisons en Etages" (Lin Ndayipfukamiye); "Turn-Taking and the Positioning of Bilingual Participants in Classroom Discourse: Insights from Primary Schools in England" (Marilyn Martin-Jones, Mukul Saxena); "Symbolic Domination and Bilingual Classroom Practices in Hong Kong" (Angel M. Y. Lin); "'Like You're Living Two Lives in One Go': Negotiating Different Social Conditions for Classroom Learning in a Further Education Context in England" (Celia Roberts, Srikant Sarangi); "Constructing Hybrid Postcolonial Subjects: Codeswitching in Jaffna Classrooms" (Suresh Canagarajah); "Language Values and Identities: Codeswitching in Secondary Classrooms in Malta" (Antoinette Camilleri Grima); "Classroom Interaction and the Bilingual Resources of Migrant Students in Switzerland" (Lorenza Mondada, Laurent Gajo); "Authority and Authenticity: Corsican Discourse on Bilingual Education" (Alexandra Jaffe); "Languages of State and Social Categorization in an Arctic Quebec Community" (Donna Patrick); "Collusion, Resistance, and Reflexivity: Indigenous Teacher Education in Brazil" (Marilda C. Cavalconti); "Telling What Is Real: Competing Views in Assessing ESL Development in Australia" (Helen Moore); "Legitimate Language in a Multilingual School" (Monica Heller); "Youth, Race, and Resistance: A Sociopolinguistic Perspective on Micropolitics in England" (Ben Rampton); "Education in Multilingualism Settings: Stakes, Conditions, and Consequences" (Monica Heller, Marilyn Martin-Jones). (KFT)
Keywords: Australia; Bilingualism; Botswana; Brazil; Burundi; Canada; Code Switching (Language); Cultural Maintenance; Educational Policy; Ethnic Groups; Foreign Countries; France; Heritage Education; Hong Kong; Immigrants; Kenya; Language Attitudes; Language Maintenance; Language Minorities; Language Planning; Languages; Malta; National Programs; Official Languages; Peru; Politics of Education; Public Policy; School Role; Second Language Instruction; Second Language Learning; Sociolinguistics; Switzerland; Uncommonly Taught Languages; United Kingdom

The Quality of Education: Some Policy Suggestions Based on a Survey of Schools--Kenya. SACMEQ Policy Research Report. - Nzomo, Juliana; Kariuki, Mary; Guantai, Lilian; United Nations Educational, Scientific (2001)
The Southern Africa Consortium for Monitoring Educational Quality (SACMEQ) is a consortium of ministries of education in southern Africa. This bound report--one of seven--presents the research results and policy suggestions that emerged from implementation of SACMEQ's initial educational policy research project. The report looks broadly at five areas of policy concern: (1) baseline data for selected inputs to primary schools; (2) how conditions of primary schooling compare with the Ministry of Education's benchmark standards; (3) whether educational inputs to primary schools have been allocated in an adequate fashion among and within education districts; (4) the level of reading achievement for Grade 6 students; and (5) which educational inputs to primary schools have had the strongest effect on the reading achievement of Grade 6 students. Data for the study were gathered from a student test of basic reading literacy and student, teacher, and principal questionnaires. This report specifically focuses on reading achievement in the nation of Kenya. Along with reading test scores, the report presents information on the characteristics of Grade 6 students and teachers; student access to materials; conditions of school rooms and buildings; and other information on the state of education in Kenya. (Contains 11 references and 33 tables.) (WFA)
Keywords: Administrator Qualifications; Educational Assessment; Educational Environment; Educational Equity (Finance); Educational Facilities; Educational Planning; Educational Quality; Elementary Education; Evaluation; Foreign Countries; Grade 6; Kenya; Reading Achievement; School Surveys; Scores; Student Characteristics; Teacher Qualifications; Tests

Notes on Literacy, 2001. - Spaeth, Carole; Summer Inst. of Linguistics, Dallas (Notes on Literacy, 2001)
These four issues include the following articles: "Cheke Holo Orthography: Local Tradition Clashes with a Linguist's Concerns" (Freddy Boswell); "Avoiding Tone Marks: A Remnant of English Education?" (Mike Cahill); "Nontraditional Education among the Iranun, a Malaysian Ethnic Minority" (Karla Smith); "Learning Well: The Socioliteracy of Some Incipient Literate Women in a Ghanaian Community" (Merieta Johnson); "Training National Partners for Leadership: Priorities for Training as Capacity Building" (Susan Malone); "Cumulative Index 1966-2001"; "Factors Affecting Community Literacy Programs: Assessment and Response" (Barbara Trudell); "Mother-Tongue Education in Schools in Tharaka Language Group of Kenya" (Leila Schroeder); "The Recent History of Education in Cambodia" (Ari Vitikainen); "Orthography Challenges in Bantu Languages" (William Gardner); "Training Nationals in Literature Production: An Experience in Northwestern Benin" (JeDene Reeder and Elizabeth L. White); "Transitional Literature among the Cotabato Manobo, Philippines" (Nida Guil-an Apang); and "Pedagogical Dictionaries: Ho-hum or Gung-ho?" (Louise Maranz). The issues also include reviews of books on such topics as training for transformation, misreading reading, reading instruction that works, evaluating literacy for development efforts, foundations of bilingual education and bilingualism, teaching adult second language learners, and using newspapers in classrooms. (Adjunct ERIC Clearinghouse for ESL Literacy Education.) (SM)
Keywords: Adult Education; Bantu Languages; Benin; Bilingual Education; Bilingualism; Cambodia; Community Education; Cultural Differences; Dictionaries; Foreign Countries; Ghana; Kenya; Leadership Training; Literacy Education; Literature; Malaysia; Minority Groups; Nontraditional Education; Philippines; Reading Instruction; Second Language Instruction; Sociolinguistics; Womens Education

The effects of primary school quality on school dropout among Kenyan girls and boys. - Lloyd, Cynthia B.; Mensch, Barbara S.; Clark, Wesley H. (The effects of primary school quality on school dropout among Kenyan girls and boys., 2000)
A study examined how primary school quality influenced school dropout rates among girls and boys in Kenya. The data were gathered through school and household visits in rural areas of three districts in the country. Results revealed that girls' retention is discouraged in schools in which boys are provided with a more supportive environment than girls in terms of advice, in which boys are free to harass girls, in which teachers take the importance of difficult subjects like math less seriously for girls, and in which boys do not acknowledge girls' experience of unequal treatment. The findings suggest that there is more to the quality of the school environment than material resources for the basic curriculum, pedagogical practices, and time to learn and that there is more to school effectiveness than the development of academic competency.
Keywords: Elementary school dropouts; Kenya; Primary education; Schools research; Sex discrimination in education

Drip Drop: Access to Water. Water in Africa. - Franz, Kristi Rennebohm; Peace Corps, Washington (Drip Drop: Access to Water. Water in Africa., 2000)
The Water in Africa Project was realized over a 2-year period by a team of Peace Corps volunteers, World Wise Schools (WWS) classroom teachers, and WWS staff members. As part of an expanded, detailed design, resources were collected from over 90 volunteers serving in African countries, photos and stories were prepared, and standards-based learning units were created for K-12 students. This unit, intended for primary students, is designed to facilitate students' understandings of access to water through reading stories from Peace Corps Volunteers who served in Kenya (East African region) and Ghana (West African region). Each student will make a book comparing access to water in the United States, Kenya, and Ghana. An overall goal is to develop students' understandings of the similarities and differences of water use by the people in Kenyan and Ghanaian communities and their own community. The unit, which contains many photos of Kenya and Ghana, can be used in reading and writing classes. Two to three weeks are needed for completion. The unit lists materials needed, outlines applicable standards, poses discussion questions, and gives student objectives. It details day-by-day procedures for the teacher, gives a reading rubric and a writing rubric for assessment, suggests follow-up/enrichment activities, and lists five print resources. (BT)
Keywords: Academic Standards; Benchmarking; Community Resources; Comparative Analysis; Curriculum Enrichment; Developing Nations; Foreign Countries; Geography; Ghana; Hydrology; Interdisciplinary Approach; Kenya; Primary Education; Social Studies; United States; Water Resources

Precious Droplets: The Value of Water. Water in Africa. - Franz, Kristi Rennebohm; Peace Corps, Washington (Precious Droplets: The Value of Water. Water in Africa., 2000)
The Water in Africa Project was realized over a 2-year period by a team of Peace Corps volunteers, World Wise Schools (WWS) classroom teachers, and WWS staff members. As part of an expanded, detailed design, resources were collected from over 90 volunteers serving in African countries, photos and stories were prepared, and standards-based learning units were created for K-12 students. This unit, intended for primary grade students, is designed to facilitate students' understandings of the value of water through reading stories from Peace Corps Volunteers who served in Kenya (East African region) and Ghana (West African region). Each student will make a book comparing the value of water in the United States, Kenya, and Ghana. An overall goal is to develop students' understandings of the similarities and differences of how the people in Kenyan and Ghanaian communities and their own community value water. The unit can be used in reading and writing classes. Two to three weeks is needed for completion. The unit lists materials needed, outlines applicable standards, poses discussion questions, and gives student objectives. It details day-by-day procedures for the teacher, discusses reading and writing assessment, suggests follow-up/enrichment activities, and lists five print resources. (BT)
Keywords: Academic Standards; Benchmarking; Comparative Analysis; Curriculum Enrichment; Developing Nations; Foreign Countries; Geography; Ghana; Hydrology; Interdisciplinary Approach; Kenya; Primary Education; Social Studies; Water; Water Resources

Splish Splash: A Daily Use of Water. Water in Africa. - Franz, Kristi Rennebohm; Peace Corps, Washington (Splish Splash: A Daily Use of Water. Water in Africa., 2000)
The Water in Africa Project was realized over a 2-year period by a team of Peace Corps volunteers, World Wise Schools (WWS) classroom teachers, and WWS staff members. As part of an expanded, detailed design, resources were collected from over 90 volunteers serving in African countries, photos and stories were prepared, and standards-based learning units were created for K-12 students. This unit, intended for primary grade students, is designed to facilitate students' understandings of daily water use through reading stories from Peace Corps Volunteers who served in Kenya (East African region) and Ghana (West African region). Each student will make a book comparing daily uses of water in America, Kenya, and Ghana. An overall goal is to develop students' understandings of the similarities and differences of water use by the people in Kenyan and Ghanaian communities and their own community. The unit can be used in reading and writing classes. Two to three weeks are needed for completion. The unit lists materials needed, outlines applicable standards, poses discussion questions, and gives student objectives. It details day-by-day procedures for the teacher, suggests a reading assessment and a writing assessment, provides follow-up/enrichment activities, and lists five print resources. (BT)
Keywords: Academic Standards; Benchmarking; Comparative Analysis; Curriculum Enrichment; Developing Nations; Foreign Countries; Geography; Ghana; Hydrology; Interdisciplinary Approach; Kenya; Primary Education; Social Studies; Water; Water Resources

The State of Adult and Continuing Education in Africa. - Indabawa, Sabo A.; Oduaran, Akpovire; Afrik, Tai; Walters, Shirley (2000)
This document contains 21 papers examining the state of adult and continuing education in Africa. The following papers are included: "Introduction: An Overview of the State of Adult and Continuing Education in Africa" (Akpovire Oduaran); "Setting the Tone of Adult and Continuing Education in Africa" (Michael A. Omolewa); "Significant Post Independence Developments in Adult and Continuing Education in Africa" (Tai Afrik); "Research and Scholarship in Adult and Continuing Education in Africa" (Akpovire Oduaran); "From Adult Education to Lifelong Learning in Southern Africa over the Last Twenty Years" (Shirley Walters, Kathy Watters); "The State of Adult and Continuing Education in Botswana" (Gbolagade Adekanmbi, Oitshepile Modise); "Creating a Knowledge Society through Distance and Open Learning in Cameroon" (Ajaga Nji); "The State of Adult Literacy in the Democratic Republic of Congo" (Ikete E. Belotsi, Muntumosi Atukimba); "Research Priorities in Adult and Continuing Education in Kenya" (Florida A. Karani); "The State of Adult and Continuing Education in Lesotho" (Lephoto H. Manthoto, Dele Braimoh, and A. Adeola); "The State of Adult and Continuing Education in Madagascar" (Violette Rabakoarivelo, Rakotozafy-Harisson, Solo Randriamahaleo); "Diversity of Adult and Nonformal Education Provisions in Namibia" (Sabo A. Indabawa); "Continuing Education Policy Provisions and Options in Nigeria" (Gidado Tahir); "The State of Adult and Continuing Education in Senegal" (Lamine Kane); "The Political and Social Contexts of Adult Education and Training in South Africa" (Zelda Groener); "The Development and Provision of Adult Education and Literacy in Zambia" (Derek C. Mulenga); "The State of Adult Literacy Education in Zimbabwe" (Stanley T. Mpofu); "Re-Defining Adult and Continuing Education in Africa" (Paul Fordham); "Inventing a Future for Adult Education in Africa" (H.S. Bhola); "International Cooperation in Adult Education: A German View of Focus on Africa" (Heribert Hinzen); and "Annotated Bibliography of 44 Selected Works of Jones Akinpelu" (Sabo A. Indabawa). (Most papers contain substantial bibliographies.) (MN)
Keywords: Access to Education; Adult Education; Adult Learning; Adult Literacy; Africa; Annotated Bibliographies; Case Studies; Change Strategies; Continuing Education; Cultural Differences; Cultural Pluralism; Definitions; Delivery Systems; Distance Education; Economic Climate; Educational Attitudes; Educational Change; Educational History; Educational Needs; Educational Policy; Educational Research; Educational Resources; Educational Trends; Foreign Countries; Futures (of Society); Germany; Illiteracy; International Cooperation; International Educational Exchange; Lifelong Learning; Literacy Education; Needs Assessment; Nonformal Education; Open Education; Policy Formation; Political Attitudes; Postsecondary Education; Research Needs; State of the Art Reviews; Training; Trend Analysis; Womens Education

Water Uses and Children's Lives in East Africa. Water in Africa. - Maher, Robert; Peace Corps, Washington (Water Uses and Children's Lives in East Africa. Water in Africa., 2000)
The Water in Africa Project was realized over a 2-year period by a team of Peace Corps volunteers, World Wise Schools (WWS) classroom teachers, and WWS staff members. As part of an expanded, detailed design, resources were collected from over 90 volunteers serving in African countries, photos and stories were prepared, and standards-based learning units were created for K-12 students. Intended for third to fifth grade students, this unit uses children's interactions with water to help them compare and contrast their lives with those of children in Kenya and Tanzania. It looks at the ways access to water helps define children's roles in the family, and how this shapes culture. The unit contains many photos of daily activities in Kenya and Tanzania. Students will write essays and create pictures to demonstrate their understanding of the concepts. The unit can be used in language arts, geography, art, or mathematics classes. Four to six 40-minute classes are suggested for completion. The unit lists materials needed, outlines applicable standards, poses discussion questions, and gives student objectives. It details day-by-day procedures for the teacher, suggests assessment and follow-up/enrichment activities, and lists nine print and on-line resources. (BT)
Keywords: Academic Standards; Africa; Benchmarking; Children; Comparative Analysis; Cultural Context; Curriculum Enrichment; Developing Nations; Elementary Education; Foreign Countries; Geography; Hydrology; Interdisciplinary Approach; Kenya; Social Studies; Tanzania; United States; Water

United Nations Millennium Declaration - United Nations (2000)

Constraints on the Acquisition Planning of Indigenous African Languages: The Case of Kiswahili in Kenya. - Musau, Paul M. (Constraints on the Acquisition Planning of Indigenous African Languages: The Case of Kiswahili in Kenya., 1999)
The paper examines the linguistic situation in Kenya and the teaching of Kiswahili in its schools. While there is widespread support for the school programme, the paper concludes that there are major problems to be overcome, particularly in the areas of attitudes, teacher training and course materials. General expressions of support for Kiswahili are of little value without effective interventions in these areas.
Keywords: Bantu languages; Comparative grammar; Grammaticality (Linguistics); Kenya; Language & languages; Linguistics; Public institutions; Swahili language; Teaching

How worldwide is the Web? - Bruce, Bertram C. (How worldwide is the Web?, 1999)
The writer discusses four important lessons learned while using the World Wide Web to locate a student's grandmother in Kenya. These lessons are that Web material has the potential to support global understanding, that the knowledge encoded in the Web results in serendipitous learning, that there is a need to critically investigate the Web's store of knowledge, and that the Web is far from worldwide. The writer describes InfoNation, an easy-to-use two-step database that allows the user to view and compare up-to-date statistical data for members of the United Nations; discusses Literacy Web Australia, a valuable resource for schools and literacy education; and provides a glossary of terms.
Keywords: Computer network resources; Education; World Wide Web

Literacy for Sustainable Development in the Age of Information. Language and Education Library 14. - Rassool, Naz (1999)
This book examines literacy for sustainable development in the age of information. It begins by discussing the relationship between literacy and hegemony, social policy, national language policy, colonial relations, and postcolonial realities. Also discussed in the introduction are views and definitions of literacy and considerations in mapping a typology of literacy. Part 1 explores the theoretical frameworks of literacy and the disparate ways literacy has featured in academic discourse. Part 2, which focuses on older literacy discourses and practices within the framework of the nation-state, contains chapters devoted to the following issues: (1) literacy as a social practice in terms of its relationship with institutions, political systems, structures, and processes within the nation-state; (2) historical links between literacy and social development; and (3) lessons from the mass literacy campaigns that featured in the drive for modernization in the 1970s. Part 3, which considers the impact of globalization on literacy concepts and definitions, addresses the following topics: (1) technological and cultural transformations; (2) changing definitions of "text" within the information society; (3) conceptualizing literacy, knowledge, and power in the information society; and (4) moving toward "communicative competence" for democratic participation in the information society. (Ten tables/figures are included. The bibliography lists 317 references.) (MN)
Keywords: Adjustment (to Environment); Adult Basic Education; Adult Literacy; Africa; Bangladesh; Citizenship Education; Communication Skills; Competence; Computer Literacy; Computer Uses in Education; Cultural Context; Definitions; Democracy; Democratic Values; Developed Nations; Developing Nations; Economic Development; Educational Environment; Educational History; Educational Needs; Educational Policy; Educational Trends; English; Ethiopia; Experiential Learning; Functional Literacy; Global Approach; India; Individual Power; Information Literacy; Information Technology; International Educational Exchange; Internet; Iran; Kenya; Literacy Education; Malaysia; Mass Instruction; Needs Assessment; Nicaragua; Nongovernmental Organizations; Outcomes of Education; Policy Formation; Political Power; Political Socialization; Power Structure; Reading Skills; Role of Education; Russia; Social Change; Social Development; South Africa; Sustainable Development; Tanzania; Technological Advancement; Theory Practice Relationship; Trend Analysis; United Kingdom; United States; Womens Education

Commission of Inquiry into the Education System of Kenya - Koech, Davy (Government Printer, 1999)

Children starved of hope and a future. - Ramsden, Sally (Children starved of hope and a future., 1998)
The Sudanese civil war that began 15 years ago has resulted in famine and a disruption of education. An information officer at Operation Lifeline Sudan headquarters in Nairobi, Kenya, has said that continued support for education in the region is vital so that people can learn basic skills and help rebuild the country. Education can also help to restore hope and security for thousands of children.
Keywords: Africa; Children & war; Education; Schools; Sudan; Sudanese Civil War, Sudan, 1983-2005

Africa Adult Education. Chronologies in Commonwealth Countries. - Draper, James A.; National Inst. of Adult Continuing Education, Leicester (England).; University of the Western Cape, Bellville (South Africa). Centre for Adult and Continuing Education.; Swedish International Development Authority (SIDA).; Adult Educators and Trainers Association of South Africa. (1998)
In this document, leading educators from 12 African Commonwealth countries trace the development of adult education in Africa and show how providers of adult education outside the formal education system (including government and nongovernment organizations, trade unions, women's groups, and religious organizations) have met the needs of their nations by providing various types of education and training, including agricultural extension and literacy, health, and political education. The following papers are included: "Introduction" (Edwin K. Townsend-Coles); "Purpose and Method of the Project" (James A. Draper); "Looking Back: Acquiring a Historical Perspective" (James A. Draper); "Botswana" (Frank Youngman); "Ghana" (Miranda Greenstreet, Kofi Siabi-Mensah); "Kenya" (David K. Kirui); "Lesotho" (Lois Anne Sebatane, Bill Moore); "Mauritius" (Prem R. Hurrynag); "Nigeria" (Michael Omolewa); "Seychelles" (Alain Daniel Lucas, Marguerite-Marie Mondon); "Sierra Leone" (Edward D. A. Turay); "South Africa" (Cathy Gush, Shirley Walters); "Tanzania" (Philemon A. K. Mushi, Yosiah D. M. Bwatwa); "Zambia" (Elizabeth Mumba); "Zimbabwe" (Clara Sipiwe Nondo, Evison James Muti); "Observations" (James A. Draper); "Introduction [to a Selected Chronology]" (James A. Draper); and "Regional Chronology" (Ekundayo J. D. Thompson). (MN)
Keywords: Adult Education; Africa; Agricultural Education; Comparative Analysis; Educational Change; Educational History; Educational Practices; Educational Trends; Extension Education; Foreign Countries; Government Role; Health Education; Literacy Education; Nonformal Education; Nongovernmental Organizations; Political Socialization; Program Development; Religious Organizations; School Community Relationship; Trend Analysis; Unions; Womens Education

Under the Sun or in the Shade? Jua Kali in African Countries. National Policy Definition in Technical and Vocational Education: Beyond the Formal Sector. A Subregional Seminar for Eastern and Southern African Countries (Nairobi, Kenya, September 15-19, 1997). International project on Technical and Vocational Education (UNEVOC). - United Nations Educational, Scientific (Subregional Seminar for Eastern and Southern African Countries, 1998)
This document is a comprehensive report a subregional seminar for eastern and southern African countries on the Jua Kali movement. (Jua Kali, "hot sun" in Swahili, refers to the informal or nonformal sector of the economy.) Section 1 explains the role of the International Project on Technical and Vocational Education (UNEVOC) in the development of technical and vocational education and training (TVET). The following opening and closing speeches are provided in Section 2: "Introductory Statement" (R. Barry Hobart); "Opening Speech" (Shem Wandiga); and "Closing Speech" (S.M. Kyungu). Section 3 is an overview of the discussion and debate, and Section 4 lists recommendations regarding development of national strategies for TVET. The following papers are presented in Section 5:"Technical and Vocational Education and Training Policy in Kenya" (Peter O. Okaka); "A Position Paper" (B. Wanjala Kerre); "TVET beyond the Formal Sector in Botswana" (K. Kabecha, M. M. Kewagamang); "Existing Set-Up in Ethiopia" (Mesfin Terefe); "Brief Description of the Jua Kali Movement in Kenya" (G.K.N. Mbugua); "Non-Government Organisations and Enterprise in Lesotho" (Mota Sekonyela); "The National Policy Definition in Malawi" (Joyce Phekani, Maston M. Mtambo); "Beyond the Formal Sector in Mauritius" (Feroze Coowar); "An Effective System for Non-Formal TVET in South Africa" (Siphamandla I. Xulu); "Essential Features of the Non-Formal Sector in Swaziland" (William S.A. Shongwe); "TVET at Mwanza Rural Housing Programme in Tanzania" (Lunogelo L. Sakafu); "A Case for Uganda" (Ben M. Manyindo); and "Training for the Informal Sector in Zambia" (Joseph S. Mukuni, Joseph P. Kalunga). Appended are the following: daily schedule, background information about the seminar, list of main seminar participants, and text of the convention on technical and vocational education adopted by the General Conference of the United Nations Educational, Scientific and Cultural Organization. (MN)
Keywords: Adult Education; Africa; Agency Role; Developing Nations; Economic Development; Educational Needs; Educational Objectives; Educational Policy; Educational Trends; Enrollment Trends; Foreign Countries; International Educational Exchange; International Organizations; Needs Assessment; Nonformal Education; Policy Formation; Position Papers; Postsecondary Education; Program Development; Public Policy; Regional Planning; Role of Education; Rural Areas; Rural Education; Vocational Education

Loi No 98/004 Du 14 Avril 1998 D'orientation De L'éducation Au Cameroun - Government of Cameroon (1998)

Feeling for all humanity. - White, Peter (Feeling for all humanity., 1997)
Part of a special section on development education in Great Britain. Some activities that are being used to introduce students to human rights issues are discussed. A lecturer at the University of Brighton is working with 12 secondary schools in a project to introduce human rights through dance work, six- and seven-year-olds in London's Tower Hamlets have undertaken a project on Kenya, and students at a primary school in Rochdale write letters on behalf of prisoners of conscience and participate in multicultural math.
Keywords: Civil rights education; College-school cooperation; Dance; England; Human rights education; International cooperation on human rights

Contextualising Teaching and Learning in Rural Primary Schools: Using Agricultural Experience. Volume 1 [and] Volume 2. Education Research. - Taylor, Peter; Mulhall, Abigail; Department for International Development, London (England). (1997)
This research project examined the potential role of agricultural experiences as a vehicle for meeting the diverse learning needs of rural primary students in developing countries. Volume 1 of the project report represents a literature review that investigated a "new role" for agriculture as a key element for developing rural students' basic skills of literacy and numeracy. Volume 2, the second phase of the project, involved case studies of four developing countries in which contextualization of learning and teaching is supported by educational policy and practice. Contextualization of learning occurs when curriculum content and the methods and materials associated with it are directly related to the experiences and environment of the learner. The literature review concludes that serious problems affect the provision and effectiveness of primary schooling in developing countries, particularly in rural areas; that the curriculum in rural primary schools in developing countries is centralized, inflexible, and geared toward an urban middle-class context; that the contextualization of teaching and learning has the potential to strengthen links among the learning environments of school, home, and community; and that agriculture may act as a unifying theme for curricula relevant to rural primary students. Implications for educational practice in the use of agriculture as a contextualizing medium for instruction are discussed relevant to language, science, mathematics, social studies, nutrition, and health instruction. Examples of the integrated approach to curriculum development, which in some cases involved contextualization of teaching and learning, are provided for the following countries: Malaysia, Uganda, Cameroon, Jordan, Papua New Guinea, Sri Lanka, Tanzania, Brazil, Kenya, India, Colombia, Ethiopia, Zambia, and Guatemala. (Contains 147 references and numerous data tables and photographs.) (LP)
Keywords: Agriculture; Curriculum Development; Developing Nations; Educational Environment; Educational Improvement; Educational Innovation; Educational Practices; Educational Research; Elementary Education; Foreign Countries; Integrated Curriculum; Learning Experience; Relevance (Education); Research Projects; Rural Education; Teaching Methods

Multilingualism and Discourse in Primary School Mathematics in Kenya. - Bunyi, Grace (Language, Culture and Curriculum, 1997)
Reviews the literature on second language medium of instruction and educational achievement in Kenya using classroom data from English, Kiswahili, and mother tongue mathematics lessons and from lessons where code switching occurred. Argues that regardless of the instructional medium, a transmissional model of teaching and learning predominates. Discusses the importance of teacher education programs based on the realities of the local situation. (33 references) (Author/CK)
Keywords: Academic Achievement; Code Switching (Language); Discourse Analysis; English (Second Language); Foreign Countries; Kenya; Language of Instruction; Learning Strategies; Mathematics Instruction; Models; Multilingualism; Second Language Instruction; Second Languages; Swahili; Teacher Education; Teaching Methods; Uncommonly Taught Languages

Governance and Civic Education. - Thompson, Ekundayo J. D.; Adult Education for Development, Nairobi (Kenya). (1997)
This book contains 13 papers on the socioeconomic development, legal, gender, philosophical, and human rights dimensions of state governance within the context of social, economic, and political processes in Sierra Leone and Kenya. The Political Literacy and Civic Education (PLACE) Project, which was sponsored by the British Overseas Development Administration through the International Community Education Association, is credited with being the book's catalyst. The following papers are included: "Foreword" (S.K. Tororei); "Antecedents of the PLACE Project"; "Conceptualising Civic Education" (S.K. Tororei); "Reflections on Community Education" (Berewa R. Jommo); "Rationale for Political Literacy and Civic Education" (Ekundayo Thompson); "Purpose, Nature, and Scope of Civic Education" (Samuel K. Tororei); "The Development Context of Civic Education" (Ekundayo J.D. Thompson, Margaret Manley); "Civil Society and the Citizen" (Akie Wilson, Joe Sam-King); "Gender, Political Literacy and Civic Education" (Agnes Pessima); "The Constitution of Sierra Leone" (Solomon E. Berewa); "Democracy and the Rights of the Individual" (David G. Thompson); "Political Tolerance--A Prerequisite for Enhanced Democracy in a Multi-Party Environment" (Ahmed Ramadan Dumbuya); "Meaning and Nature of Government" (Walter N. Davies, Peter O. Koroma); "Politics, Political Literacy & Political Participation" (Edward D.A. Turay); "Curriculum for Civic Education" (Ekundayo J.D. Thompson, Joseph Simekha). (MN)
Keywords: Adult Education; Adult Learning; Adult Programs; Citizenship Education; Civil Liberties; Community Education; Curriculum Development; Democracy; Economic Development; Educational Benefits; Educational Objectives; Educational Principles; Empowerment; Foreign Countries; Government School Relationship; Kenya; Law Related Education; Political Socialization; Role of Education; School Community Relationship; Sex Differences; Sierra Leone; Social Development

The Prince of AALAE. Corruption and Mismanagement in an African NGO. - Thompson, Ekundayo J. D.; Adult Education for Development, Nairobi (Kenya). (1997)
In this book, the former coordinator of the Technical Assistance Project of the African Association for Literacy and Adult Education (AALAE) provides an insider's account of the corruption, political management, and organizational mismanagement of the AALAE in 1991-1996. Chapter 1 introduces six myths regarding nongovernmental organizations (NGOs): NGOs have the capacity to reach the poor and vulnerable; NGOs are better placed than governments to address the needs of the poor and vulnerable; NGO work is characterized by innovation and flexibility; NGOs have greater potential than government bureaucracies in empowering people at the grassroots to achieve self-reliant development; African NGOs are people's organizations; and NGOs complement governments' development efforts. These are among the topics discussed in chapters 2-12, which systematically expose each myth, are as follows: ownership of the AALAE; organizational dysfunction; roots, causes, and essence of the AALAE's current crisis; action by donors and partners; the AALAE audit; issues uncovered; and lessons learned. Fifteen tables/figures are included. Appended are the following: questionnaire used to survey of AALAE members on the AALAE's reorganization; survey findings; chronological account of the AALAE's crisis; case study of program mismanagement; and list of executive council members. The book contains 187 references. (MN)
Keywords: Adult Basic Education; Adult Literacy; Case Studies; Educational Finance; Educational Needs; Financial Problems; Foreign Countries; Government Role; Government School Relationship; Literacy Education; Nongovernmental Organizations; Organizational Change; Organizational Climate; Organizational Development; Political Power; Politics of Education; Power Structure; Program Administration

Globalization, Adult Education & Training. Impacts & Issues. Global Perspectives on Adult Education and Training Series. - Walters, Shirley (1997)
An introduction (Maurice Amutabi et al.) begins this 25-chapter book on adult education and training (AET) in a context of globalization. Chapter titles and authors are as follows: "The Impact of Globalization on Adult Education (AE)" (Ove Korsgaard); "In Defense of Civil Society: Canadian AE in Neo-Conservative Times" (Michael Welton); "Women, Poverty, and AE in Chile" (Teresa Quiroz Martin); "The State, Civil Society, and the Economy: AE in Britain" (Keith Jackson); "Globalization from Below: The Trade Union Connections" (Judith Marshall); "Feminist Popular Education in the Light of Globalization" (Linzi Manicom, Shirley Walters); "Women on the Global Assembly Line" (Chan Lean Heng); "'Sit Down, Listen to the Women!'" (Daniel Moshenberg); "Personal, Professional, and Political Development for Women" (Pauline Murphy); "From Economic Dependency to Regional Self-Reliance" (Mildred Minty); "ETDP [Education, Training and Development Practitioner]: Passing Fad or New Identity?" (Jeanne Gamble, Shirley Walters); "The NQF [National Qualifications Framework], Reconstruction, and Development" (Rosemary Lugg); "The Politics of Memory: The Recognition of Experiential Learning" (Elana Michelson); "Workplace Training and Enskilling" (Jonathan and Ruth Winterton); "Race, Class, Gender, and Culture: A Possible Program" (Tammy Shefer, Joe Samuels, Tony Sardien); "Multicultural Education and Lifelong Learning" (Berndt Gustavsson, Ali Osman); "Aboriginal Education: A Case for Self-Determination" (Lillian Holt, Michael F. Christie, Norman Fry); "The Plight of AE in Kenya" (Maurice Amutabi); "Literacy Strategies among Unschooled Workers" (Mignonne Breier); "Dynamics and Process in the Training of Health Committees" (Mizana Matiwana); "Is Consensus Possible?" (Minnie Venter-Hildebrand, Charlene Houston); "On the Periphery: The Needs of Rural Women" (Ellen Gumede); "Lifelong Learning Reconsidered" (Berndt Gustavsson); "The Meaning of Lifelong Learning" (Staffan Larsson); and "The Worlds of the Hand and of the Mind" (Ove Korsgaard). Contributors' notes and an index are included. (YLB)
Keywords: Adult Education; Adult Literacy; Canada; Chile; Economically Disadvantaged; Employed Women; Experiential Learning; Foreign Countries; Individual Development; Inplant Programs; International Relations; Job Training; Kenya; Labor Force Development; Lifelong Learning; Literacy Education; Role of Education; Rural Women; South Africa; Teaching Methods; Womens Education

Adult Education and Development, No. 47. - German Adult Education Association, Bonn (Germany). Inst. for International Cooperation. (Adult Education and Development, 1996)
This serial issue contains a total of 26 articles grouped under five headings: "Adult Learning: A Key for the Twenty-First Century (Fifth International Conference on Adult Education (Confintea V))"; "Trends in Adult Education Policy" (Belanger); "Adult Education in Modern Times" (Geissler); "From Criticism to Constructiveness" (Torres); "An Uninvited Speaker Is Asked to Leave, But He Doesn't Go..." (Aramendy); "Small Farmers of La Cocha" (Calle); "The Botina de la Cruz Family Farm" (Corrales et al.); "Poison in the Home" (interview with Javier Souza Casadinho); "Productive Terracing in Coelemu" (Loguercio); "The Use of Green Manure by Small-Scale Farmers" (Bunch); "Women's and Men's Informal Sector Enterprises in Nairobi, Kenya" (Karugu, Otiende); "Situation of Women in the Informal Sector. The Example of Rwanda" (Burckhardt); "Informal Training and Socio-cultural Regulators in Small Enterprises in New Delhi" (Singh); "Skills in the Informal Sector in Lima, Peru" (Bakke-Seeck); "Can Community Projects Sustain Local Literacy Efforts?" (Herbert); "Literacy and Language" (Robinson-Pant); "New View of Literacy: My experience in Adult Education Practice in Nepal" (Nwangwu); "Internal Funding for Literacy" (Mbuagbaw); "Executive Summary from Adult Literacy in America" (Kirsch et al.); "International Literacy Watch. Warning against Lip-Service" (Chiba); "Training of Communication Workers in the Area of Popular Radio Broadcasting" (Gutierrez); "'La Senal': An FM Radio Initiative"; "Study Circles on HIV/AIDS for Africa. Swazi Women Gain a Public Voice." (Oliver);"Darien--The Map of Participation" (Gonzalez et al.); "Violence and Impunity - Our Daily Bread" (Palma); "Education for Minority Tribes: Hope for Success" (Das); and "Participatory Training for Promotion of Social Development" (Acharya, Verma). (SK)
Keywords: Adult Education; Adult Literacy; Continuing Education; Ecology; Educational Policy; Environmental Education; Foreign Countries; Job Skills; Literacy Education

Law No. 96-6 of 18 January 1996 to amend the Constitution of 2 June, 1972 - Government of Cameroon (1996)

Reading Literacy in Relation to Patterns of Academic Achievement. - Agak, John Odwar (1995)
A study explored how reading literacy is related to academic achievement among 14-year-old students in Kenya. The International Evaluation and Educational Assessment Association (IEA) Reading Literacy Test was used for measuring reading literacy, and the Kenya Certificate of Primary Education (KCPE) was used for measuring academic achievement. It was hypothesized that there are degrees of variation in correlation between reading literacy and each subject area a student opts for at KCPE. It was also hypothesized that there is a variation in performance on reading literacy due to influences caused by background factors (literacy interaction) and voluntary reading processes. Reading literacy was assumed to be decomposable into latent variables including: a general reading ability factor, a document reading factor, and specific passage factors. However, such a measurement model was not successful. General reasoning ability proved to be the main factor across most of the subjects at KCPE while verbal ability was connected to the subjects loaded mainly with connected texts to be comprehended. When voluntary reading was explored, a good measurement model was obtained. The measurement model for voluntary reading encompassed seven different types of voluntary reading. Significant relationships between voluntary reading and both reading literacy and academic achievement were observed. An examination of the background factors in the study indicated that they have an impact on students' performance on reading literacy and academic achievement. (Contains a table of data, two figures, and 32 references.) (Author/NKA)
Keywords: Academic Achievement; Background; Foreign Countries; Kenya; Literacy; Reading Processes; Reading Research; Secondary Education

To Wish upon a Star, a Stone, or a...Folktales from around the World and Shared Book Experiences: Multicultural Education for Young Children. - Slaughter, Judith Pollard (To Wish upon a Star, a Stone, or a...Folktales from around the World and Shared Book Experiences: Multicultural Education for Young Children., 1995)
Intended to provide a natural and positive way to introduce young children to the stories told by different ethnic groups, this paper suggests a series of language activities that adapt folktales from around the world for classroom use to enable young children to read the stories for themselves. The paper notes that these activities are particularly appropriate for children of minority groups whose feelings of self-worth can be increased as they find themselves reflected in the stories they and their classmates are reading and enjoying. These stories can also become the backbone of an emergent literacy program or can be used to enhance the curriculum in early grades. In the first section, a story from Kenya ("The Magic Stone") has been rewritten in predictable language and procedures are given to make this into a big book to be used for shared book experiences. The next section describes a collection of small group activities, using a variety of folktales from different ethnic groups (including "The Fisherman and his Wife" from Germany, and "The Magic Orange Tree" from Haiti). The final section suggests additional ideas appropriate for the theme on wishes, based on folktales that include "The Story of the Stone Lion" from Tibet. Four figures are included. An appendix contains "The Magic Stone" story. A reference section contains 26 academic references, a list of 12 folkstories about wishes, and a list of 17 predictable folkstories and modern tales. (SR)
Keywords: Class Activities; Cultural Awareness; Emergent Literacy; Foreign Countries; Literature Appreciation; Minority Group Children; Multicultural Education; Primary Education; Reader Response; Self Esteem; Tales; Young Children

Curriculum Development in Non-Formal Education. - Thompson, J. D. Ekundayo; African Association for Literacy and Adult Education, Nairobi (Kenya). (Curriculum Development in Non-Formal Education., 1995)
The two parts of this book consider two main facets of nonformal curriculum development: theory and practice. Part I on nonformal curriculum theory has four chapters. Chapter 1 addresses the origins, meaning, purpose, and scope of nonformal education. Chapter 2 examines three major themes in discussions on nonformal education: nonformal education as an instrument of positive change, as a social control mechanism, and the context. Chapter 3 explores the rationale. Chapter 4 examines the rational planning model and three models that have relevance for curriculum development in nonformal education: psychosocial, liberal education, and Bhola's core-interface. The five chapters in Part II on nonformal curriculum practice consider the case of the People's Educational Association of Sierra Leone in integrating population education into adult literacy. Chapter 5 describes nonformal education in the Sierra Leone context where it is an educational response to the problems of out-of-school youth and illiterate adults and an alternative development strategy. Chapter 6 sets forth the rationale for population education and literacy. Chapter 7 describes the process of curriculum integration. Chapter 8 is a case analysis of the population education project. Chapter 9 highlights these conclusions: contingent nature of curriculum development in nonformal education; importance of learner participation; and need for staff development. Appendixes contain a 359-item bibliography and index. (YLB)
Keywords: Adult Basic Education; Curriculum Development; Economic Development; Foreign Countries; Labor Force Development; Literacy Education; Nonformal Education; Population Education; Sierra Leone

Creating Healthier Communities: Nonformal Education Strategies. - World Education, Inc. (World Education Reports, 1995)
This issue focuses on several efforts in maternal and child health education and environmental sanitation throughout the world in which bridges between technical content and participatory education have been built successfully. The following articles are included: "Editorial" (David Kahler, Bonnie Mullinix); "Women's Health Education and Adult Literacy in Nepal" (Cristine Smith, Chij Shrestha, and John Comings); "Getting Local Players into the Act: School and Community Collaboration on Environmental Sanitation in a Chinese Municipality" (David Kahler et al.); "Assessing Empowerment in Health Education Programs: Challenges for Evaluators Based on Experiences in Cambodia" (Hitoshi Murakami, David Kahler, and Peggy Levitt); "Let's Talk Health: Promoting Participatory Health Education in Kenya" (Bonnie Mullinix, Florence Gachanja); "Taking Care and Taking Action: Using Learner Generated Stories for Cancer Education in the United States" (Loren McGrail); and "From the Field--Messages in the Marketplace: Namibian Business Women Combat HIV/AIDS" (Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome) (Armin Sethna). Contains a 27-item annotated bibliography describing related organizations, newsletters/journals, courses/workshops, and books. (MN)
Keywords: Acquired Immune Deficiency Syndrome; Adult Basic Education; Adult Literacy; Annotated Bibliographies; Cambodia; Cancer; China; Community Education; Educational Cooperation; Educational Strategies; Environmental Education; Foreign Countries; Health Education; Health Promotion; Kenya; Literacy Education; Namibia; Nepal; Nonformal Education; Participative Decision Making; Patient Education; Periodicals; Program Evaluation; Sanitation; School Community Relationship; Student Developed Materials; United States; Womens Education

Reading in Kenya: A study in contrasts. - Johns, Jerry L. (Reading in Kenya: A study in contrasts., 1994)
Presents the author's assessment of the educational system in Kenya. Difference between private and public schools in the country; Efforts of authorities in education to establish the Kenya Reading Association; Aim of promoting literacy in the country; Publishing efforts.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Education; Educational Support Services; Elementary and Secondary Schools; Kenya; Schools

Interactive Radio Instruction: Broadening the Definition. LearnTech Case Study Series No. 1. - Moulton, Jeanne; Education Development Center, Inc. (1994)
Interactive radio instruction has gained attention as a low-cost means of improving the academic achievement of primary school students. The Radio Mathematics Project in Nicaragua and subsequent programs developed by the Learning Technologies for Basic Education (LearnTech) Project illustrate the evolution such programs have undergone as technology and society have changed. The term "interactivity," was used to characterize the simulated conversation of radio broadcasts in which students responded in chorus to questions posed by the radio teacher, but the concept has expanded. Programs started after Radio Mathematics, which was initiated in 1974, have presented new and different challenges. Concepts being taught are more complex, students are expected to apply what they learn outside the classroom, and classroom teachers have a more important role. Such programs as Radio Science, which is taught in Papua New Guinea, have employed new cognitive-learning theories. A new radio program based on constructivist principles is being used in South Africa. Radio projects have pioneered interactive instruction and remain in the vanguard of the application of learning theory to education in the developing countries. (Contains 20 references.) (SLD)
Keywords: Academic Achievement; Cognitive Processes; Constructivism (Learning); Cooperation; Costa Rica; Developing Nations; Distance Education; Dominican Republic; Educational Change; Educational Radio; Educational Technology; Elementary Secondary Education; Foreign Countries; Honduras; Interaction; International Programs; Kenya; Learning Theories; Nepal; Nicaragua; Papua New Guinea; Partnerships in Education; Program Development; South Africa; Teacher Role; Technological Advancement; Telecommunications

Interactive Radio as a Component of Distance Education in Third World Countries. - Norman, Douglas (1993)
Interactive radio is a technique to promote active listening to educational radio programs targeted at students and teachers in Third World countries. The U.S. Agency for International Development (USAID) has supported interactive radio in Africa, Asia, and Latin American to provide supplementary training to students with poorly prepared teachers. An example was a language arts program in Kenya, where evaluators concluded that radio students were consistent in their statistically significant superiority over control students in listening, speaking, reading, and writing. Despite these findings, other studies concluded that interactive radio is better for teaching math, which has a limited number of correct answers, than language. USAID also has funded interactive radio projects in science, mathematics, teacher training, and high-school equivalency. Some critics of interactive radio say it is too dependent on expensive hardware and that Third World students are not well enough motivated, cannot read well enough, and cannot work well enough on their own for distance education to significantly affect educational progress in developing nations. (Contains 9 references.) (Author)
Keywords: Developing Nations; Distance Education; Educational Change; Educational Radio; Elementary Secondary Education; Foreign Countries; Higher Education; Language Arts; Mathematics Instruction; Problems; Science Instruction; Teacher Education

Kenyan women adult literacy learners: why their motivation is difficult to sustain. - Mwiria, Kilemi (Kenyan women adult literacy learners: why their motivation is difficult to sustain., 1993)
Women comprise more than seventy per cent of those enrolled in the Kenya literacy programme. The reasons for this include: the limited formal educational opportunities available to females; the demands of a changing economy which have forced women to acquire extra responsibilities outside the home; the socializing opportunity made possible by literacy class attendance; flexible work schedules; and cultural beliefs which in some Kenyan communities discourage men from enrolling in the same literacy classes as women. Women literacy learners may find it difficult to sustain their interest in literacy learning because of: their multiple responsibilities; having to operate in environments not particularly conducive to learning; having to contend with professionally unqualified teachers; their limited exposure to reading materials and other learning aids; their very limited mastery of the two languages of official communication in Kenya; as well as the fact that the literacy programme is mainly administered by men. Although changes at the wider societal level still will, to the most part, determine the extent of women's participation in the Kenyan literacy programme, much could be accomplished through involving more of them in the programme's administration and by improving the quality of literacy instruction.
Keywords: Education; Kenya; Literacy education; Women's education

Development Communication Report, 1993. - Bosch, Andrea; Agency for International Development (IDCA), Washington (Development Communication Report, 1993)
The three 1993 issues of the newsletter "Development Communication Report" focus on the use of communication technologies in developing countries to educate the people about various social issues as well as the field of development communication itself. Agricultural communication is the theme of the first issue which contains the following articles: "Development Support Communication and Agriculture: The Road Ahead" (Silvia Balit); "Mobilizing Villagers to Action: Communication for Agricultural Micro-Enterprises in Pakistan" (Frank Byrnes); "Women, Seed, Technology and Change: Communicating with Farmers in Senegal and the Gambia" (Tom Osborn); "Interactive Communication Strategies: Playing Games with Labor" (July Leesberg and Emperatriz Valencia); "Special Farmer Field Days in Kenya" (Anderson G. Mwaloma); "Sudan Rural Television (RTV): Communicating with Rural People" (M. O. Elsiddig); "Centers of Excellence: Building Agricultural Communication in India" (Royal D. Colle); and "Being a Good Communicator Doesn't Solve All of Extension's Problems" (Willem Zijp). The theme of the second issue is interactivity and learning technologies and contains the following articles: "People Based Interactive Instruction: A Workshop by Thiagi" (Sivasailam Thiagarajan); "Cutting Edge Multimedia Technologies: Promise and Pitfalls" (Janice Brodman); "Rethinking Interactivity: Lessons from Interactive Radio Instruction" (Jeanne Moulton); "Breaking the Ice: The Karate Kids Mixed Media Package" (Christopher Lowry); "Script Writing for Interactive Radio Instruction" (Esta de Fossard); "Interactivity and Soft Technologies: Peer Group Learning Systems" (Aida Pasigna); "Forum Theater in Burkina Faso: Paving the Way for Dialogue, Interactivity and Change" (Joy Morrison); and "Adult Literacy Is Important...But How Can We Use More Interactive Methods?" (Jose Carleton Corrales). Finally, multi-channel learning is the focus of the final issue which contains the following articles: "Expanding the Vision of Basic Education through Multi-Channel Learning" (Stephen Anzalone); "Multi-Channel Solutions: The Prospects of Open Secondary Education" (Paud Murphy); "Multi-Channel Learning in Focus: Project No-Drops and a Learning System for All" (Minda C. Sutaria); "Kenya's Rural Press Project: Bringing the Local Reality into Focus" (Usman Jimada); "Multi-Channel Learning in Practice: Case Studies from India, Costa Rica, South Africa and Bolivia" (Andrea Bosch); "Internetworking: Understanding E-Mail" (Mark Prado); and "Satellite TV Broadcasting: Looking to the Future of Educational Technologies" (Charles Morrow). (JLB)
Keywords: Agriculture; Developing Nations; Development Communication; Distance Education; Educational Change; Educational Innovation; Educational Technology; Foreign Countries; Information Technology; Interaction; Rural Environment

A Popular Version of Yash Tandon's Militarism and Peace Education in Africa. - Kisembo, Paul; African Association for Literacy and Adult Education, Nairobi (Kenya). (A Popular Version of Yash Tandon's Militarism and Peace Education in Africa., 1993)
This book is a briefer, simpler popular edition of "Militarism and Peace Education in Africa." It is intended to interest the African peoples in the problems of peace and allow them to discuss and debate the issues of militarism and peace for Africa and to suggest solutions. It is also intended to interest leading organizations and people working at the grassroots level in urban and rural areas in problems of militarism and peace education. The first two chapters show how, in former times, militarism was brought to Africa by the Europeans through slave trade and colonialism. Chapter 3 shows how militarism continued after independence under neocolonialism in these forms: state terrorism, militarism based on ethnic nationality/conflicts, militarism resulting from "pastoralist conflicts," militarism resulting from cultural and religious conflicts, and militarism based on ideological conflicts. Chapter 4 explores how militarism is still connected to the exploitation and oppression of Africa with the new strategy called "low intensity conflict" or "low intensity war." Chapter 5 considers developing types of peace education and proposed content of peace education. Chapter 6 proposes the content of African peace education, including African history and civilization, cultural and moral education, development education, and human rights and equality education. Contains 15 references. (YLB)
Keywords: Adult Education; Africa; Civil Liberties; Civil Rights; Colonialism; Community Education; Conflict Resolution; Developing Nations; Economic Development; Foreign Countries; Freedom; International Relations; Nationalism; Peace; Political Attitudes; Slavery; Terrorism; Violence; War; World Problems

Kenyan Women Adult Literacy Learners: Why Their Motivation Is Difficult to Sustain. - Mwiria, Kilemi (Kenyan Women Adult Literacy Learners: Why Their Motivation Is Difficult to Sustain., 1993)
Examines reasons for high representation of women and factors influencing their persistence in Kenya's literacy programs. Considers the limited formal learning opportunities available, economic demands, women's multiple social roles, inadequate learning environments, unqualified literacy teachers, and the impact of a male-centered society. Provides suggestions for sustaining women's motivation in literacy programs. (18 references) (CA)
Keywords: Access to Education; Adult Basic Education; Adult Literacy; Cultural Influences; Disadvantaged Environment; Economic Factors; Educational Needs; Females; Foreign Countries; Kenya; Literacy Education; Student Characteristics; Student Motivation; Womens Education

Cost-Effectiveness of Management Training in the Informal Sector. Discussion Paper No. 101. - Nubler, Irmgard; International Labour Office, Geneva (Switzerland). (1992)
A research project in the Ivory Coast, Kenya, and Tanzania evaluated the cost effectiveness of management training seminars for women entrepreneurs in the informal sector. Women, a large and growing part of entrepreneurs, had less access to needed resources, skills, and information than men. Reasons for failure to study the cost effectiveness and efficiency of development assistance included lack of clear concepts, methodologies, and standards. Grassroots management training seminars were conducted for businesswomen operating established informal sector businesses. In each country, 40 businesswomen were selected; some were assigned to a control group. A set of indicators was developed to measure benefits. Levels of criteria considered in evaluating outcomes were reaction, learning, behavioral, and result. Impact of the training program was assessed by applying this set of indicators and comparing pre- and postseminar values. Findings indicated that participants appreciated acquisition of management skills, had a more favorable attitude toward learning and the importance of management know-how to improve business, and acquired cognitive skills. Behavioral changes were reflected in the application of acquired skills and knowledge through business expansion by at least one-third of participants in each country. They improved or stabilized their businesses. Benefits to participants exceeded costs in all three countries. (Appendixes include 29 references, a summary of seminar content, and data tables.) (YLB)
Keywords: Adult Education; Business Administration; Business Education; Cost Effectiveness; Economic Development; Economic Opportunities; Entrepreneurship; Evaluation Methods; Females; Foreign Countries; Informal Education; Job Training; Kenya; Management Development; Program Effectiveness; Program Evaluation; Research Methodology; Self Employment; Seminars; Small Businesses; Tanzania

Concerns of Women around the World: The Responsibilities of the Adult Education Movement. - Cassara, Beverly B. (Concerns of Women around the World: The Responsibilities of the Adult Education Movement., 1991)
Around the world, women suffer oppression to various degrees. In the United States, they have a difficult time rising in corporations or having their ideas taken seriously. In some other countries, they are abused and overworked. Some women in Norway are concerned that their country's entrance into the European Community will mean an end to the humanitarian and egalitarian nature of their country. Women in the former East Germany feel they have lost more than they have gained in some cases, such as the loss of jobs, day care, and abortion rights. Women in Kenya, Guatemala, and India often suffer at the hands of men and of the government. Adult education has a role to play for all women. Women can gain knowledge and strength from mutual study, and they can use this knowledge to gain political power. They can also use adult education to foster acceptance of cultural pluralism, which will be necessary for a better world in the future. (KC)
Keywords: Adult Education; Adult Literacy; Developed Nations; Developing Nations; East Germany; Educational Trends; Foreign Countries; Guatemala; Kenya; Literacy Education; Norway; Postsecondary Education; Role of Education; Self Actualization; Sex Discrimination; Womens Education

Opportunities for Distance Education in the Commonwealth African Countries. - INTELECON Research & Consultancy Ltd., Vancouver (British Columbia). (1991)
The geo-demographic, economic, and infrastructural makeup of 12 African countries (Botswana. Gambia, Kenya, Lesotho, Malawi, Nigeria, Sierra Leone, Swaziland, Tanzania, Uganda, Zambia, and Zimbabwe) were compared to determine the potential benefits to them of a Commonwealth of Learning (COL) distance education initiative. Data were collected on six criteria regarding suitability for such initiatives: developmental need, geographic and demographic features, government priorities, infrastructure, existing experience, and human resource development. Data were incorporated into a multiattribute model that ranked countries by relevant indicators. Seven countries with a television/radio network and/or rural telecommunications infrastructure appropriate for cost-effective implementation of distance education were strong possibilities for COL: Nigeria, Kenya, Swaziland, Botswana, Zimbabwe, Zambia, and Malawi, but not Gambia, Lesotho, Sierra Leone, Tanzania, and Uganda. Countries offering the best opportunities for human resource development projects in the broadcasting sector were Gambia, Swaziland, Tanzania, and Zambia. The African regional networks were not conducive to use of distance education techniques between countries. (Appendixes, which represent the bulk of the report, include country summaries, multi-attribute comparison model, annotated list of existing correspondence and distance education programs, summary of country comparative analysis, outline maps of national and international earth stations, statistical data, and list of telecommunications and broadcast administrations with addresses.) (YLB)
Keywords: Adult Education; Adult Literacy; Africa; Botswana; Comparative Analysis; Cost Effectiveness; Developing Nations; Distance Education; Economic Development; Educational Benefits; Educational Needs; Educational Technology; Feasibility Studies; Foreign Countries; Gambia; Human Resources; International Cooperation; International Educational Exchange; Kenya; Labor Force Development; Lesotho; Malawi; Needs Assessment; Nigeria; Regional Cooperation; Sierra Leone; Swaziland; Tanzania; Telecommunications; Uganda; Zambia; Zimbabwe

Adult Education in Development. Methods and Approaches from Changing Societies. - McGivney, Veronica; Murray, Frances; National Inst. of Adult Continuing Education, Leicester (England). (1991)
The case studies described in this book provide examples of initiatives illustrating the role of adult education in development and its contribution to the process of change in developing countries. The book is organized in five sections. Case studies in Part 1, "Health Education," illustrate the links between primary health care and adult education: use of traditional knowledge to develop confidence and initiate change (Peru); training without written texts (Nicaragua); working through peer-group methods and cascade teaching (Brazil, Ghana); use of drama and puppetry to mobilize debate and confront difficult issues (Malawi, India); and linking of school, home, and community education (India). Part 2, "Literacy," contains case studies that show ways in which literacy affects personal growth and contributes to social and economic change: an integrated social literacy program (Northern Bangladesh); role of post-literacy in irrigation (Senegal); popular education and literacy in a women's laundry workshop (Chile); literacy crash course with tribal women (India); and personal experiences (Zaire, Zimbabwe). Case studies in part 3 illustrate how rural development can be achieved: a coordinated education "intervention" system (Southeast Asia); a national initiative with hill tribes (Thailand); Association for the Orientation of Cooperatives (Brazil); drama workshops (Sierra Leone); nongovernmental development organizations (Bangladesh); and the Green Belt Movement (Kenya). Case studies in part 4, "The Role of Women in Development," show how women's education projects can have important development outcomes for communities in Kenya, Tanzania, and India. Part 5, "Concluding Observations," highlights factors that international agencies must take into account in development activities. Twenty-two references are listed. (YLB)
Keywords: Adult Basic Education; Adult Education; Adult Literacy; Asia; Bangladesh; Brazil; Chile; Developing Nations; Economic Development; Foreign Countries; Ghana; Health Education; Illiteracy; India; Kenya; Literacy Education; Malawi; Nicaragua; Outcomes of Education; Peru; Role of Education; Rural Development; Senegal; Sierra Leone; Social Change; Social Development; Tanzania; Thailand; Womens Education; Zimbabwe

The African Adult Education Movement in Blossom. Report of the Secretary General to the Second General Assembly on the 1987-90 Period. - African Association for Literacy and Adult Education, Nairobi (Kenya). (1990)
Since 1987, many activities have been undertaken by the African Association for Literacy and Adult Education (AALAE). Perhaps the most important program activity has been the building of institutional capacities in the adult education movement. Important elements are organizational development, networking and solidarity, management development training, and small grants. Networks have been instituted to help members develop and implement programs. Under the Catalytic Initiatives Program, AALAE undertakes specific, concentrated action in particular subregions to strengthen adult education. The Exchange Program facilitates the sharing of experiences between adult educators and development activists. In other activities, the AALAE: (1) developed a program for Peace Education, Human and People's Rights; (2) began to build training capacities, especially through the training of trainers; (3) conducted a feasibility study to determine the need for an African Training Center for Literacy and Adult Education; (4) endeavored to ensure the generation, creation, recording, and wide dissemination of information and knowledge; (5) cultivated regional and international relations; (6) undertook research projects in volunteerism, multilevel partnerships, literacy, and environmental education; and (7) mobilized human, material, and financial resources. Ongoing, end-of-year, and terminal evaluations have been planned. Problems have been: undertaking too broad a program; too much dependence on external funding; and difficulties with decentralization. (YLB)
Keywords: Adult Education; Adult Educators; Adult Literacy; Adult Programs; Developing Nations; Educational Cooperation; Feasibility Studies; Foreign Countries; International Cooperation; International Educational Exchange; International Organizations; International Programs; International Relations; Literacy Education; Networks; Program Development; Program Evaluation; Program Implementation; Teacher Education; Volunteers

Improving the Quality of Basic Education, Volume 5. Country Papers: Brunei Darussalam, Canada, Kenya, Uganda. Conference of Commonwealth Education Ministers (11th, Barbados, October 29-November 2, 1990). - Commonwealth Secretariat, London (England). (1990)
Commonwealth Ministries of Education were asked to report on how they are undertaking the improvement of the quality of basic education in their respective countries. The papers in this volume focus on: (1) Brunei Darussalam; (2) Canada; (3) Kenya; and (4) Uganda. Charts and statistical data support each country's report. (EH)
Keywords: African Studies; Basic Skills; Brunei; Canada; Canadian Studies; Comparative Education; Cross Cultural Studies; Culture; Foreign Countries; Foreign Culture; Functional Literacy; Higher Education; International Education; Islamic Culture; Kenya; Middle Eastern Studies; Social Science Research; Uganda

Scouts Serving the Cause of Literacy. Literacy Lessons. - Moreillon, Jacques; International Bureau of Education, Geneva (Switzerland). (1990)
Scouting is an expanding worldwide youth movement, with more than 16 million members in 169 countries and territories. Its goal is to contribute to the physical, intellectual, social, and spiritual development of young people. Since participation in development is one of the cornerstones of their program, scouts cannot ignore the challenge that literacy represents for them. Properly trained and organized, scouts can undertake literacy and reading promotion programs, and they can help create an environment in which this new knowledge can be used. Scouts do not embark upon literacy activities in isolation, but rather in cooperation with the authorities and other specialized organizations. Scouts are carrying out extensive literacy programs in Indonesia, where they are involved in literacy training, study centers, vocational training, and other programs. They also have taken advanced training courses and are applying their skills to literacy training in Haiti. In India, young scouts and guides participate in literacy projects within the framework of the National Adult Education Program. They have also been involved in literacy education programs in Bangladesh, Pakistan, Senegal, Benin, Zaire, Burkina Faso, Kenya, Bolivia, and Saudi Arabia. The scouts have published a series of four pamphlets to help other scout groups gets started in literacy work. (KC)
Keywords: Adolescents; Adult Basic Education; Adult Literacy; Community Development; Cooperative Programs; Developing Nations; Economic Development; Elementary Secondary Education; Foreign Countries; Haiti; India; Indonesia; Literacy Education; Program Development; Program Implementation; Volunteers; Youth Clubs; Youth Leaders

World Declaration on Education for All and Framework for Action to Meet Basic Learning Needs; 1990 - UNESCO (1990)

The Kenya Literacy Programme: A View from Below. Report of an IIEP Research Review Workshop (Nairobi, Kenya, November 27-29, 1989). - United Nations Educational, Scientific (Subregional Seminar for Eastern and Southern African Countries, 1989)
Research conducted in Kenya had two purposes: to describe the literacy program and literacy learners and to determine the literacy skill levels of participants and to what use they are putting those skills. Researchers collected data from 5 districts in Kenya, including information about the characteristics and functioning of the literacy centers, and interviewed 388 of the 660 learners who had earned literacy certification and 64 teachers. Some of the findings of the study were the following: (1) the majority of the learners (67.5%) in the literacy programs are women; (2) enrollments in the program have been declining after enthusiastic growth resulting from a massive campaign in the 1970s; (3) facilities and equipment were found to be in relatively good shape; (4) teachers had been trained by 2-week courses or by 2-year correspondence courses; (5) learning motivation of more than 65 percent of the participants involves simply the desire to read and write; (6) large proportions of learners continue attending literacy classes after they have attained their certificates; and (7) numeracy skills are used more often than literacy skills. The study concluded that the main problem with the literacy program was that learners lacked motivation to attend, partially because of poor teaching. The findings of the study were reviewed at a workshop in Nairobi, Kenya, with 42 participants, and policy implications were formulated. (Appendixes include a list of workshop participants and the workshop program.) (KC)
Keywords: Adult Basic Education; Adult Literacy; Adult Programs; Developing Nations; Educational Needs; Educational Policy; Foreign Countries; Kenya; Literacy Education; Outcomes of Education; Participant Characteristics; Policy Formation; Program Effectiveness; Program Implementation; Public Policy; Workshops

A Note on Language of Instruction, Teaching and Cognitive Outcomes of Science Instruction in Primary Schools in Kisii and Kwale Districts, Kenya. - Eisemon, Thomas Owen (A Note on Language of Instruction, Teaching and Cognitive Outcomes of Science Instruction in Primary Schools in Kisii and Kwale Districts, Kenya., 1989)
Questions Kenyan language instructional policy, arguing exclusive use of English for science instruction confuses students and impedes learning. Offers examples the authors observed in elementary classrooms in Kisii and Kwale districts when teacher use of English synonyms rather than Kiswahili words led to confusion, misunderstanding, and ineffective teaching. (CH)
Keywords: Classroom Research; Cognitive Development; Communication (Thought Transfer); Communication Skills; Comprehension; Concept Teaching; Educational Policy; Elementary Education; English (Second Language); Foreign Countries; Kenya; Language Usage; Language of Instruction; Native Speakers; Observation; Science Instruction; Scientific Concepts; Scientific Literacy; Second Language Learning; Sociolinguistics; Swahili; Teacher Effectiveness; Teaching Methods; Vocabulary Development

Interactive Radio Instruction: Developing Instructional Methods. - Friend, Jamesine (Interactive Radio Instruction: Developing Instructional Methods., 1989)
Describes three projects funded by the U.S. Agency for International Development that used new methodologies for educational radio with elementary students: (1) the Radio Mathematics Project of Nicaragua; (2) the Radio Language Arts Project of Kenya; and (3) the Radio Science Project of Papua New Guinea. (LRW)
Keywords: Developing Nations; Educational Radio; Elementary Education; Elementary School Mathematics; Elementary School Science; Foreign Countries; Instructional Innovation; Kenya; Language Arts; National Programs; Nicaragua; Papua New Guinea; Second Language Instruction; Student Role; Teacher Role

Handbook for Designing and Writing Distance Education Materials. - Gachuhi, D.; Matiru, B.; Nairobi Univ. (Kenya). (Handbook for Designing and Writing Distance Education Materials., 1989)
Developed from a series of workshops in Kenya, this handbook offers practical guidance for those creating printed distance education materials for African students. The introduction describes the workshops and a short section explains how to use the handbook. Twelve units appear on the following topics: (1) overview of distance education; (2) distance education systems and subsystems; (3) learner characteristics; (4) writing objectives; (5) writing to be read and understood; (6) active learning; (7) developing a format for writing; (8) the role of visualization in distance education materials; (9) the editorial process; (10) practical aspects of pretesting distance education materials; (11) the printing process; and (12) a summary of course development from planning to printing. Units start with advance organizers for the unit and typically include in-text questions to think about, self-tests (answers appear at the back of the document), checklists, and writing assignments. Important points are marked for the reader. The document includes an 18-item bibliography. (CML)
Keywords: Adult Education; Africa; Distance Education; Editing; Instructional Materials; Layout (Publications); Material Development; Printing; Writing Processes

Dossier of Evaluation Instruments for Literacy Programmes. A Contribution to the International Literacy Year 1990. - Muller, Josef; Dietrich, Anja; German Foundation for International Development, Bonn (West Germany) (Dossier of Evaluation Instruments for Literacy Programmes. A Contribution to the International Literacy Year 1990., 1989)
This document contains a collection of literacy program evaluation instruments from developing countries, as well as several papers describing how to use evaluation instruments to assess various types of systems. The following titles (with author or country of origin) are contained in this collection: "Designing a System of Evaluation and Monitoring for Literacy and Post-Literacy Programmes" (by R. H. Dave); "Problem Study Questionnaire: Work-Oriented Adult Literacy Project" (Iran); "Initial Survey Instrument Scheme for the 15-25 Age Group" (India); "What Is a Management Information System (MIS)?" (by H. S. Bhola); "The Management Information System of the Tanzania Literacy Campaign" (by Z. J. Mpogolo); "Guidelines for Monitoring the Malawi National Adult Literacy Programme" (Malawi); "The Management Information System of the Zimbabwe Literacy Campaign" (Zimbabwe); "The Management Information System of the Botswana National Literacy Programme" (Botswana); "Preliminary Guidelines on Monitoring" (India); "Literacy Learner Assessment" (Malawi); "Guidelines on Learner Evaluation in the Adult Education Programme" (India); "Literacy Levels Prescribed by the National Literacy Mission" (India); "Achievement Test in Agriculture" (Iran); "Global Evaluation of a Literacy Project" (by Roger Couvert); "Indicators and Elements for Measurement of Change in Experimental Literacy Projects" (UNESCO); "Construction of Measurement Tools and Methods and Procedures for Sampling and Control for Evaluation of Experimental Literacy Projects" (UNESCO); "The Effects of Literacy in Kenya: Questionnaire for Literacy Learners and Questionnaire for Literacy Teachers" (UNESCO/Kenya); "Programme Listening Report" (Tanzania); "Literacy Listening Report" (Zambia); "Questionnaire on the Use of Radio and Television in Literacy Campaigns" (by John Maddison); and "An Alternative Approach to Evaluation" (India). (KC)
Keywords: Adult Basic Education; Adult Literacy; Adult Programs; Botswana; Developing Nations; Educational Radio; Evaluation Criteria; Evaluation Methods; India; Iran; Kenya; Literacy Education; Malawi; Management Information Systems; Outcomes of Education; Program Effectiveness; Program Evaluation; Questionnaires; Research Methodology; Tanzania; Zimbabwe

Seminar on African Perspectives and Issues on Peace Education and Action in Africa: A Report from a Seminar Held in Conjunction with the Meeting of the Adult Education Association of Zambia (Lusaka, Zambia, October 3-7, 1988). - Machila, Margaret M. C.; Wangoola, Paul; African Association for Literacy and Adult Education, Nairobi (Kenya). (Subregional Seminar for Eastern and Southern African Countries, 1988)
This report presents the proceedings of a seminar that brought together almost 30 intellectuals, artists, and development activists from eight African countries and Canada to identify the obstacles to peace in Africa and develop strategies to overcome them. One of the other purposes of the seminar was to develop elements of curriculum and instructional materials for peace education and action plans for selected target groups of adults and other special groups. The report features seminar objectives; the seminar process; an introduction of the participants; organizations and methods of work; on your mark; an introduction of the African Association for Literacy and Adult Education; an introduction to the Adult Education Association of Zambia; the official opening of the seminar; Dr. Sets'abi's vote of thanks; an overview of the basic Working Document; the concept of peace; militarism; violence; peace; liberation education and training for peace education; content of peace education; literature for peace education; media for peace education, exchange of experience; the target for peace education; Africa's troubled spots; non-interference in the internal affairs of another country; foreign military bases; final recommendations and resolutions; and an evaluation of the seminar. Two appendices also are included: (1) the opening speech by Mr. John Mwanakatwe, and (2) a list of participants. (DB)
Keywords: Adult Education; Africa; Developing Nations; Foreign Countries; International Education; International Educational Exchange; Peace; Social Change

The Presidential working party on education and manpower for the next decade and beyond, Nairobi: Government Printer - Kamunge, James (Government Printer, 1988)

Attitudes towards mathematics of grade six pupils and teachers from urban and rural communities in Kenya. - Okech, Jack Green (Attitudes towards mathematics of grade six pupils and teachers from urban and rural communities in Kenya., 1987)
Keywords: Kenya; Mathematics; Psychology; School children

Achievement Motivation in Distance Education: An Experimental Study to Measure Students' Achievement Motive as Elicited by Achievement Arousal Conditions Given in Reference to, and with Emphasis on Written Assignments. - Gitau, Ben K. (Achievement Motivation in Distance Education: An Experimental Study to Measure Students' Achievement Motive as Elicited by Achievement Arousal Conditions Given in Reference to, and with Emphasis on Written Assignments., 1987)
Discusses achievement motivation among distance education students, and describes a study of Kenyan primary school teachers enrolled in an in-service training course taught primarily through correspondence. A modified Thematic Apperception Test will be used to determine the correlation between achievement motive and performance score in written assignments. (LRW)
Keywords: Achievement Need; Correlation; Developing Nations; Distance Education; Foreign Countries; Hypothesis Testing; Inservice Teacher Education; Kenya; Literature Reviews; Performance Factors; Primary Education; Scores; Student Motivation; Thematic Apperception Test; Writing (Composition)

Designing and Writing of Distance Education Materials for Basic Education and Development Training Programmes. A Report on the 1987 Workshop Series. - Mazrui, K.; Nairobi Univ. (Kenya). Coll. of Adult and Distance Education. (1987)
A series of two 2-week workshops was conducted in East Africa in 1987 by the German Foundation for International Development to assist educators in the development of instructional materials for distance and adult education. These workshops were designed to: (1) bring together writers of distance education materials to share their experiences and learn together; (2) build a core of experienced distance education materials designers and writers who would disseminate their skills throughout the region; (3) familiarize course writers with what is involved in a distance education system; (4) equip course writers with the skills needed to design a specific correspondence course; and (5) have course writers plan, develop, and write a unit for a specific course. Topics covered in the workshops included the essential elements of distance education; the characteristics and needs of distance learners; course development for distance education; course production; assessment of learners; and testing and evaluating the course materials. More than 20 participants from Kenya, Somalia, and Tanzania met in March for 2 weeks, then returned to their institutions and completed the units outlined and designed at the workshop. They met again August for 2 weeks to present their units and have them commented on by other participants and facilitators. Five publications which constituted the basic documentation for the workshops are listed, and three appendixes provide the results of summative evaluations of the workshops, a list of participants, and a list of units produced at workshops in 1985-1987. (EW)
Keywords: Adult Education; Africa; Correspondence Study; Developing Nations; Distance Education; Foreign Countries; Illustrations; Instructional Design; Instructional Materials; Literacy Education; Material Development; Postsecondary Education; Production Techniques; Program Evaluation; Secondary Education; Skill Development; Teacher Education; Workshops

Environmental Education through Adult Education. A Manual for Adult Educators, Instructors, Teachers and Social Extension Workers. - Rugumayo, Edward B.; Ibikunle-Johnson, Victor O.; African Association for Literacy and Adult Education, Nairobi (Kenya). (Environmental Education through Adult Education. A Manual for Adult Educators, Instructors, Teachers and Social Extension Workers., 1987)
The purpose of this manual is to make available to adult educators and field extension workers in Kenya resource material that may be used in formal and nonformal training programs for the environmental education of a wide range of target groups. The document begins with a 26-item glossary, an introduction, a section on the document's use, background and context material, a philosophy and rationale section, and a section on perspectives on adult education. Thereafter come four sections that contain concepts, principles, processes, problems, issues, and ideas that are relevant to the themes of environmental health; agroforestry and rural development; population, environment, and development; and urban/industrial development. Within these four sections are bibliographies with a total of 79 references. A section on methodologies and instructional aids concludes the document. (CML)
Keywords: Adult Education; Community Education; Developing Nations; Economic Development; Environmental Education; Extension Education; Foreign Countries; Forestry; Health Education; Industrialization; Kenya; Population Education; Rural Development

Human Rights and Education. Comparative & International Education Series, Volume 3. - Tarrow, Norma Bernstein (1987)
This book discusses the relationship between human rights and education. Education is discussed both within the context of human rights, and as the ultimate sanction and guarantee of all human rights. Part 1, "Education as a Human Right," is comprised of the following chapters: (1) "Human Rights and Education: An Overview" (D. R. Ray; N. B. Tarrow); (2) "Rights of Access and Equal Opportunity: Focus on Sub-Saharan Africa" (W. M. Rideout, Jr.); (3) "The Right to Education Free from Discrimination: The Case of India and Saudi Arabia" (R. Ghosh and A. Attieh); (4) "Exceptional Abilities and Educational Rights: Concern for the Handicapped and Gifted in Britain, China and Indonesia" (R. M. Thomas); (5) "The Right to Literacy" (L. J. Limage); (6) "The Right to Education for Multicultural Development: Canada and Israel" (V. L. Masemann; Y. Iram); (7) "The Right to Education for Employment and Mobility: Norway and Yugoslavia" (V. D. Rust); (8) "The Right to Lifelong Education in Kenya and the United States with Special Reference to Adult Education" (J. Davison; K. Gezi); (9) "The Rights of Parents, Students and Teachers in Canada and the Philippines" (R. Magsino); and (10) "The Right to a Political Education" (C. L. Hahn). Part 2, "Education About Human Rights," is comprised of the following chapters: (11) "Human Rights Education in Schools" (S. M. Shafer); (12) "Education about Human Rights: Teacher Preparation" (K. Sebaly); and (13) "Human Rights and Education Viewed in a Comparative Framework: Synthesis and Conclusions" (J. Torney-Purta). Each chapter is accompanied by a list of references. The Epilogue (J. P. Humphrey) discusses the role of education as the ultimate sanction that supports the new international law of human rights. The appendices include summaries of the education provisions of United Nations, UNESCO, and regional human rights documents. An index is also included. (FMW)
Keywords: Access to Education; Adult Basic Education; Adult Education; Citizenship Education; Civil Liberties; Comparative Education; Democratic Values; Educational Discrimination; Educational Policy; Elementary Secondary Education; Equal Education; Ethnic Discrimination; Foreign Countries; International Education; Lifelong Learning; Literacy Education; Minority Groups; Multicultural Education; Parent Rights; Political Issues; Special Education; Universal Declaration of Human Rights

Literacy for Development: An African Perspective (Notes from a Sabbatical). - Bhola, H. S. (Literacy for Development: An African Perspective (Notes from a Sabbatical)., 1986)
This report contains one man's impressions of the state of adult literacy education in several countries of Africa and in India. The first country reported on is Ethiopia, where signs of a capitalist society were evident in that officially Marxist country, where literacy education was still a priority in the midst of a waning famine. Ethiopia had conducted continuous "campaigns for literacy" that had succeeded despite lack of resources. Next, the planning for a literacy broadcasting system to provide radio support to literacy in Malawi is described. In India, political corruption and official neglect make the progress of literacy education doubtful. However, literacy may come to be inevitable, though the progress is slow. A workshop in Kenya showed that literacy education was progressing slowly, serving 350,000 adults in about 1,300 centers that year (80 percent being women), but that official support from the highest government levels seemed to be waning. Finally, adult literacy programs in several areas of Tanzania are described. The report concludes that literacy is a basic need and a powerful force that will inevitably come to all peoples because it is innately desired by all. (KC)
Keywords: Adult Basic Education; Adult Literacy; Africa; Developing Nations; Economic Development; Educational Radio; Ethiopia; India; Kenya; Literacy Education; Malawi; Outcomes of Education; Personal Narratives; Program Effectiveness; Program Implementation; Tanzania

Primary School Literature and Folktales in Kenya: What Makes a Children's Story African? - Eisemon, Thomas Owen (Comparative Education Review, 1986)
Compares African children's stories with Kenyan primary school literature with regard to structure, use of characterization, forms of dramatization, and social contexts of storytelling. Argues that school texts, published mostly by multinational firms, have been adapted to only surface characteristics of African cultures. Proposes that features of oral tradition be incorporated into language-arts materials for cultural maintenance purposes. (KS)
Keywords: African Culture; Childrens Literature; Educational Objectives; Elementary Education; Ethnicity; Foreign Countries; Kenya; Oral Tradition; Reading Materials; Story Telling; Textbooks

Hands of Knowledge. 'Adult Education, Development and Peace.' Report of the World Assembly of Adult Education (Buenos Aires, Argentina, November 22-30, 1985). - Stultz, Erma; International Council for Adult Education, Toronto (Ontario). (Subregional Seminar for Eastern and Southern African Countries, 1986)
This report, written in popular education style and designed to be readable both by adult educators and by the people with whom they work, describes a week-long meeting of the World Assembly of Adult Education. Under the general themes "Where are we?""Where are we going?" and How to do it" the report provides synopses of the reports of 17 working groups on the following topics: peace and human rights, popular theater and communications, participatory research, rural adult education, adult education and prisons, adult education and indigenous peoples, workers' education, adult education and self-management, adult education and new technology, literacy and post-literacy, history of adult education, adult education and women, adult education and older adults, civic adult education, training of adult educators, adult education and primary health care, and adult education and the disabled. The report also includes comments from numerous participants from around the world, as well as officials of UNICEF, UNESCO, the International Conference on Adult Education, the presidents of Argentina and France, and other dignitaries. The report includes numerous drawings and photographs. The meeting agenda and a list of participants are included. (KC)
Keywords: Adult Basic Education; Adult Education; Adult Educators; Adult Literacy; Adult Programs; Argentina; Brazil; Canada; China; Communication Skills; Community Education; Comparative Education; Continuing Education; Correctional Education; Developing Nations; Disabilities; Educational History; Educational Improvement; Finland; Foreign Countries; France; Health Education; Inservice Teacher Education; Kenya; Labor Education; Literacy Education; Nicaragua; Older Adults; Postsecondary Education; Rural Education; Saint Vincent and the Grenadines; Self Actualization; Sweden; Tanzania; Teacher Education; Technical Education; Technological Advancement; Thailand; Theater Arts; United Kingdom (Scotland); Vocational Education; Womens Education

A Look at Kenya's Children. - Roberson, Glenda F.; Muoki, Isaac Mulatya (A Look at Kenya's Children., 1985)
Focusing on the education of young children in Kenya, this brief paper contains excerpts from a question and answer interview between two early childhood educators from the United States and Kenya. Both similarities and differences of the Kenyan and the U.S. system of education are revealed. Interview topics covered include the following: socially respected professions; educational theories and philosophy; beginning reading instruction; teacher/pupil ratios in classrooms; compulsory school attendance; trends in sex of teachers; incorporation of American educational practices into Kenyan schools and vice versa; and the future of education in Kenya. (DST)
Keywords: Comparative Education; Early Childhood Education; Educational Practices; Educational Trends; Elementary Education; Foreign Countries; Futures (of Society); Kenya; United States

The Education of Women in Kenya, 1975-1984. - Eshiwani, G. S.; Kenyatta Univ. College, Nairobi (Kenya). Bureau of Educational Research. (1985)
The extent to which the educational system reaches women in Kenya will in some measure dictate the pace of national development. Data indicate that significant progress was made in the area of education for Kenyan women during the 1975-1984 decade. This was particularly so at the primary school level where near-parity was achieved in the enrollments between boys and girls, and, to a lesser extent, in the adult literacy role for women. There are, however, regional disparities and significant differences in attrition rates and in achievement. At the secondary school level, modest progress has been made in the number of girls attending school. Three disturbing observations at this level are the high rate of drop-outs among females due to pregnancy, the limited number of secondary schools for girls, and non-participation of girls in science and technical education. On the positive side, improvement in the number of girls attending secondary school can be attributed to changed parental attitudes regarding the value of education for women that has taken place during the last decade. Eight recommendations for educational development conclude this document. (BZ)
Keywords: Access to Education; Area Studies; Attendance; Cultural Context; Developing Nations; Educational Change; Educational Development; Educationally Disadvantaged; Elementary Secondary Education; Equal Education; Females; Foreign Countries; Kenya; Literacy; Rural Areas; Social Science Research

Development Communication Report. No. 49. - Agency for International Development (Dept. of State), Washington (Development Communication Report, 1985)
Concerned primarily with interactive radio for instruction, this issue highlights radio projects in developing countries that have proven to be a successful tool for educational development. These include: (1) an experimental project designed to investigate the feasibility of using radio as a medium of instruction in the teaching of elementary school mathematics, used in Nicaragua from mid-1974 to early 1979; (2) the Radio Language Arts Project, a direct follow up to the Nicaraguan Radio Math Project for the purpose of applying and adapting the model to a different subject area in Kenya; and (3) Radio-assisted Community Basic Education (RADECO), which teaches the basic curricula of grades one through four through the exclusive use of radio to children in rural areas of the Dominican Republic. The descriptions of each of the projects (by J. Friend, P. R. Christensen and J. F. Helwig/J. Friend respectively) includes instructional design decisions, adaptation challenges, and curriculum choices. A follow up evaluation of all three radio projects is also included; this evaluation, by B. Searle, concludes that interactive radio is effective for the instruction of primary school subjects, and that both trained teachers and untrained classroom proctors can use radio lessons effectively. The newsletter also contains reviews of four books on the topic of radio and broadcasting plus two additional articles: "Radio Science: Completing the Interactive Radio Instruction Curriculum," by J. Meadowcroft, and "The Fourth R--(Interactive) Radio," by Philip Spain. (JB)
Keywords: Book Reviews; Developing Nations; Distance Education; Educational Radio; Elementary Education; Instructional Design; Language Arts; Listening Groups; Mathematics Education; Programing (Broadcast)

Issues in Planning and Implementing National Literacy Programmes. - Carron, G.; Bordia, A.; United Nations Educational, Scientific (Issues in Planning and Implementing National Literacy Programmes., 1985)
The following papers were produced by participants and resource persons on specific issues of planning, management and implementation of literacy and post-literacy strategies: "People's Participation and Mobilization: Characteristics of the Literacy Campaigns in China" (Yanwei); "Strategies for Mobilization and Participation of Volunteers in Literacy and Post-Literacy Programmes: The Case of Nicaragua" (Grigsby); "Motivating the People to Participate in Literacy and Complementary Education Work in the Socialist Republic of Vietnam" (Niun); "Organizing a Mass Literacy Campaign: The Case of Iraq" (Sulyman); "Structures and Linkages for Involvement of Political Leadership in the Ethiopian Mass-Literacy Campaign" (Mammo); "Decentralization of Educational Administration for Literacy Programmes: The Case of Kenya" (Kebathi); "Programmes with Focus on Women's Involvement: The Case of India" (Dighe); "Language and Literacy: The Planning of Literacy Activities in Multilingual States" (Ryan); "Planning and Management of Post-Literacy Programmes" (Bordia); "Decentralization of Resource Structures for Literacy and Post-Literacy: The Case of Indonesia" (Napitupulu); "Innovative Methods in the Use of Mass Media: Utilizing Television for Functional Literacy" (Rafe-Uz-Zaman); "Training of Literacy Personnel: Experience of the Unesco Regional Office for Education in Asia and the Pacific" (Chiba); "Designing a System of Evaluation and Monitoring for Literacy and Post-Literacy Programmes" (Dave); "Learner Evaluation as an Instrument for Improving Qualitative Aspects of Literacy Programmes: The Case of the United Republic of Tanzania" (Lasway); "Impact of Parents' Literacy on School Enrollments and Retention of Children: The Case of Nepal" (Kasaju, Manandhar); "Planning Literacy and Post-Literacy Programmes for the Implementation of Basic Education: The Case of Brazil" (Moreira); "Co-ordination between School Education and Literacy and Post-Literacy Programmes" (Caillods, Carron); and "Integrating Literacy and Post-Literacy Activities and Basic Services" (Ahmed). A list of workshop participants and workshop agenda are appended. (MN)
Keywords: Adult Basic Education; Adult Literacy; Asia; Brazil; China; Citizen Participation; Community Involvement; Cooperative Planning; Coordination; Developing Nations; Educational Resources; Ethiopia; Foreign Countries; India; Indonesia; Iraq; Kenya; Literacy Education; National Programs; Nepal; Nicaragua; Postsecondary Education; Program Administration; Program Development; Program Evaluation; Secondary Education; Tanzania; Vietnam; Volunteers

Learning Strategies for Post-Literacy and Continuing Education in Kenya, Nigeria, Tanzania and United Kingdom. Outcomes of an International Research Project. UIE Studies on Post-Literacy and Continuing Education 3. - Dave, R. H.; United Nations Educational, Scientific (1985)
Many countries have recently launched massive programs to promote nation-wide adult literacy, but while these efforts have been commendable, it has been observed that neo-literates who acquire literacy through such programs have great difficulty in retaining it; hence an urgent need to develop suitable programs of post-literacy and continuing education has been felt. In 1980, Unesco's Institute for Education initiated a major research project designed to respond to this need. The research was carried out within the broad framework of lifelong education, and resulted in the series of case studies of which this volume is a part. It includes the following reports: "The Development of Learning Strategies for Post-Literacy and Continuing Education in Kenya in the Perspective of Lifelong Education" (David Macharia); "Post-Literacy Activities and Continuing Education of Adults in Nigeria" (Charles O. Akinde); "Learning Strategies or Post-Literacy and Continuing education in Tanzania" (Zakayo J. Mpogolo); and "Strategies for Post-Literacy and Continuing Education at the Basic Level in the United Kingdom" (Arthur Stock). Each report includes some or all of the following components: background information on the country and its educational system; an analysis of techniques and learning strategies used; a summary and conclusion; and tables and figures. The United Kingdom (U.K.) report also includes nine specific case studies which are illustrative of post-literacy efforts in general in the U.K. (CML)
Keywords: Adult Education; Adult Literacy; Continuing Education; Educational Media; Foreign Countries; Instructional Materials; Kenya; Learning Strategies; Lifelong Learning; Literacy Education; Nigeria; Tanzania; Teaching Methods; United Kingdom

One Billion Illiterates. One Billion Reasons for Action. Report and Extracts from Papers of an International Seminar on Co-operating for Literacy (Berlin, West Germany, October 1983). - Fordham, Paul; German Foundation for International Development, Bonn (West Germany).; International Council for Adult Education, Toronto (Ontario). (Subregional Seminar for Eastern and Southern African Countries, 1985)
This document contains the report and edited papers from an international seminar emphasizing the sharing of ideas and resources to eliminate illiteracy. Chapter I of the seven-chapter report offers background information and seminar objectives. Chapter II provides a world overview, which describes the general development context of literacy. In chapter III, emphasis is on literacy in context. The role of national governments in eliminating illiteracy, the correlation between literacy and poverty, and the purpose of literacy are discussed. Chapter IV focuses on women and literacy. Chapter V discusses continuing education beyond literacy. Chapter VI suggests international cooperation in training and research and regional cooperation in training and research. Chapter VII discusses principles and problems of cooperation and provides two examples of cooperation: cooperation between international agencies and international assistance to a national literacy campaign. Appendix I contains case studies from selected countries. Literacy work is described in the Caribbean, China, Ethiopia, Burma, India, Botswana, Kenya, Mozambique, Spanish-speaking countries of Latin America, and Malawi. Appendix II is an excerpt, "The Price of Literacy," from "Literacy, Depression, and the Poor" (R. H. Green). Other appendixes include the program, list of participants, and descriptions of organizing institutions. (YLB)
Keywords: Adult Basic Education; Adult Literacy; Case Studies; Developing Nations; Economic Development; Females; Foreign Countries; Illiteracy; International Cooperation; Literacy Education; Regional Cooperation; Seminars; West Germany

Applications of Distance Education in Kenya. - Holmberg, Borge (Applications of Distance Education in Kenya., 1985)
Discusses several conditions that hamper the application of distance education in Kenya and describes three distance education programs that have been planned and executed since 1980 to illustrate what is presently being achieved. Programs include an inservice course for primary school teachers, a foundation course for adult literacy, and a paramedical training course. (MBR)
Keywords: Adult Education; Adult Literacy; Allied Health Occupations Education; Developing Nations; Distance Education; Educational Improvement; Elementary Education; Inservice Teacher Education; Kenya; Program Descriptions; Sociocultural Patterns; Teaching Methods

IFLA General Conference, 1984. Section on Adult Education. Papers. - International Federation of Library Associations, The Hague (Netherlands). (IFLA General Conference, 1984. Section on Adult Education. Papers., 1984)
Four papers on the role of libraries in adult education were presented at the 1984 IFLA general conference meeting of the Section on Adult Education. They include: (1) "The Library of the Pompeia Leisure Centre, Sao Paulo, Brazil," in which Apaty Peroni of Brazil provides background on the community, location, collection, personnel, operation, and programs of the library; (2) "The Promotion of Reading Habits and Adult Education in Kenya," in which Peter E. Kinyanjui of Kenya presents the central theme that, if adult learners are provided for, encouraged and guided in their quest for knowledge and information, they will take responsibility for their own learning and personal growth and development throughout their lives; (3) "The Basis of Library and Information Services for National Development: Promotion of Reading Habits and Adult Education" (D. O. Olembo), which examines the current status of reading habits at all levels of education in Africa, reading motives, and implementation of reading habits; and (4) "Promotion of the Reading Habit and Adult Education" (E. A. Ulzer), which describes collaboration efforts between the International Council for Adult Education (ICAE) and the African Association for Literacy and Adult Education (AALAE). (THC)
Keywords: Adult Education; Adult Literacy; Africa; Brazil; Developing Nations; Foreign Countries; Information Services; International Organizations; Library Associations; Library Cooperation; Library Role; Library Services; Reading Achievement; Reading Habits; Reading Improvement; Special Libraries; Technological Advancement

Co-operative posters in Kenya. - Venna, Yrjo; Wafhuko, John (Co-operative posters in Kenya., 1984)
Keywords: Adult education; Kenya; Literacy education; Pilot projects; Posters; Rural education

TESOL Newsletter, Vol. 18, 1984. - Teachers of English to Speakers of Other Languages. (TESOL Newsletter, 1984)
The 1984 volume of the Teachers of English to Speakers of Other Languages (TESOL) newsletter includes articles on language competence and cultural awareness in the United States; interest in English in Peru; employment trends; the case method in adult English as a second language (ESL); evaluating computer assisted instruction; the "sakura" technique; writing and editing instruction; practice teaching; ESL literacy; second language learning theory and writing instruction; part-time teaching issues; teaching English to Namibians; international issues; Japanese students; peer telephoning; ESL program self-evaluation; public school teacher education and ESL; ESL in Kenya; public domain software; the handicapped limited-English-proficient student; computer-generated materials for reading comprehension; teacher and ESL association responsibilities; using native pop music for instruction; the importance of language competence in education; teacher self-observation; Chinese English language education; surveys and second language learning; computer technology and national development; the National Association for Foreign Student Affairs; the British Council; instructional software; and bilingual education mainstreaming. Professional announcements, association notes, book and materials reviews, and notes on successful teaching techniques are also presented. (MSE)
Keywords: Adult Education; Bilingual Education; China; Computer Assisted Instruction; Computer Software; Courseware; Cultural Awareness; Developing Nations; Disabilities; Employment Practices; English (Second Language); Foreign Countries; Foreign Students; Japan; Kenya; Limited English Speaking; Literacy; Mainstreaming; Namibia; Newsletters; Part Time Faculty; Peru; Professional Associations; Second Language Instruction; Self Evaluation (Groups); Self Evaluation (Individuals); Student Teaching; Teacher Developed Materials; Teacher Education; Technological Advancement; Telephone Usage Instruction; Writing Instruction

The Relationship between Social Environment in the Home & Achievement in Science--Uganda. African Studies in Curriculum Development & Evaluation. - Abeti, S. L.; African Curriculum Organisation. (1983)
This study attempted to identify specific social environmental factors of the home that are related to science achievement at the primary school level and to determine the extent of the relationships between achievement in science and the factors identified. A sample of 200 subjects were given three instruments in a group setting, a mental ability test, an achievement test, and a student questionnaire. Findings indicate that: (1) boys achieved better in science than girls and that younger students achieved better than older students at the same class level; (2) brighter children attended school more regularly than dull students and bright boys attended school more regularly than bright girls; and (3) social environment of the home was not significantly related to achievement in science. However, sub-variables of parental unity, parental status, and family conditions were found to be significantly related to achievement in science for boys. The study also confirmed the positive correlations between achievement in science and intelligence quotients (sample = +0.50; girls = +0.55; boys = +0.46) as obtained by others in previous studies. (The student questionnaire and science achievement test used are included in appendices.) (Author/JN)
Keywords: Academic Achievement; Cognitive Ability; Elementary Education; Elementary School Science; Family Environment; Family Influence; Intelligence Quotient; Performance Factors; Science Education; Sex Differences; Social Influences; Uganda

Option on Examination Subjects and Its Effects on Teaching and Learning Process in Primary Schools in Kenya. African Studies in Curriculum Development & Evaluation No. 95. - Lumallas, Jack E. S.; Kenya Inst. of Education, Nairobi.; Nairobi Univ. (Kenya).; German Agency for Technical Co-Operation, Nairobi (Kenya).; African Curriculum Organisation. (1983)
At the end of the seventh grade, students in Kenya are required to take the Certificate of Primary Education Examination (CPE), which is used as a selection instrument to determine whether students will be allowed to continue an academic course of education at the secondary school level. While the full range of subjects in the primary school curriculum includes 15 subjects, only 5 of these are covered in the CPE. The examination covers achievement in English and mathematics, and includes a general paper dealing with three subjects: science, history, and geography. A study was made to show that the omission of other subjects from the CPE makes teachers and learners in the schools consider the omitted subjects as unimportant for teaching and learning. Teachers are inclined to give less attention to the teaching of these subjects and the learners do not take them seriously and lose interest in them. These under-emphasized or ignored subjects are important to the development of a well-rounded individual, and many students are hampered in opportunities to choose careers that do not require excellence in the subjects covered by the CPE. (JD)
Keywords: Career Choice; Curriculum Evaluation; Educational Objectives; Elementary Education; English (Second Language); Foreign Countries; Kenya; Program Content; Relevance (Education); Standardized Tests; Student Attitudes; Teacher Attitudes; Test Validity

Development Communication Report No. 42, June 1983. - Hanssen, Andrew; Agency for International Development (Dept. of State), Washington (Development Communication Report, 1983)
In addition to the lead article by Andrew Hanssen, Steven Kozlow, and Anne Olsen, this publication contains the following articles related to communications in developing nations: (1) "World Communications Year, 1983"; (2) "Field Research in Botswana Leads to More Relevant Media Production," by Chris Garforth; (3) "Kenya Explores New Ways of Producing Literacy Materials for Basic Education," by Muriithi Kinyua; (4) "Changing Health Behaviors in the Hospital Setting," by Bette Booth; (5) "Rural Development through Puppetry," by Bunker Roy; (6) "Information Resources; Places to Contact, Publications to Order," by Judy Brace; (7) "Radio Formats Offer Choices," by Esta de Fossard; (8) "Community Radio in Ecuador Meeting People's Needs," by Kurt Hein; and (9) "Housing Finance Software Package." In addition, two columns discuss current resource materials: "A Communicators Checklist" offers book reviews by Joan Dassin, Maurice Imhoof, and Michael Laflin, and Barb Minor reviews five ERIC listings in "On File at ERIC." (LMM)
Keywords: Adult Basic Education; Botswana; Community Development; Design Requirements; Developing Nations; Dominican Republic; Ecuador; Educational Radio; Educational Television; Ethiopia; Health Education; India; Instructional Materials; Kenya; Literacy Education; Material Development; Production Techniques; Puppetry; Rural Development

Interactive Radio in the Classroom: Ten Years of Proven Success. - Agency for International Development (IDCA), Washington (1983)
Research on the role of educational radio in the classroom sponsored by the Agency for International Development over a ten-year period in Nicaragua, Kenya, and the Dominican Republic is reviewed. An introductory section outlines the reasons for using radio for instructional purposes: (1) it is widespread and democratic; (2) serious radio use is still a novelty in most classrooms; (3) it can entertain and teach simultaneously; (4) it can establish a uniform standard of excellence; (5) it can use the best educational methods; (6) it is cost-effective; and (7) it is familiar technology. Four landmark programs are described, including a primary level radio mathematics project in Nicaragua, a five-year language arts project in Kenya, a Dominican Republic basic education program for out-of-school children aged 7 to 14, and a yet-to-be implemented science project. Lessons learned from past experience with instructional radio are examined, and include the potential for its use, how children learn with it, techniques and advantages of intensive use, the need to stimulate pupil participation and immediate feedback, the advantage of using distributed learning principles and devoting each lesson to a variety of topics, enhancing the role of teachers and parents, the availability of low cost instructional aids, and the reliability of equipment. (MSE)
Keywords: Basic Skills; Classroom Techniques; Costs; Developing Nations; Dominican Republic; Educational Radio; Elementary Secondary Education; Equipment Evaluation; Foreign Countries; Instructional Materials; Kenya; Language Arts; Learning Processes; Mathematics; Media Selection; Nicaragua; Parent Role; Program Descriptions; Science Instruction; Teacher Role; Technical Assistance

The Promise of Literacy. Campaigns, Programs and Projects. Report of the International Seminar on Campaigning for Literacy (Udaipur, India, January 4-11, 1982). - Bhola, H. S.; German Foundation for International Development, Bonn (West Germany).; International Council for Adult Education, Toronto (Ontario). (Subregional Seminar for Eastern and Southern African Countries, 1983)
This report on the International Seminar on Campaigning for Literacy at Udaipur, India is divided into three main parts. Part 1 describes the context and background of the seminar, its specific objectives, and the organization and procedures of the seminar. Part 2 provides an overview of the seminar proceedings. The inaugural statements are summarized to provide a framework to the deliberations. Reports follow that were presented by two sets of countries--those who had experience in conducting reputedly successful mass literacy campaigns (Somalia, Tanzania, Burma, Vietnam, Cuba) and those who had recently decided to conduct a mass literacy campaign or were planning to do so (Botswana, Ethiopia, Iraq, Kenya, Nigeria, Sierra Leone, Sudan, Zambia, Bangladesh, India, Thailand, Nicaragua). A section entitled "Conversations" reports on the concerns expressed, questions raised, and issues discussed by the participants. The section "Convergences" includes memoranda formally accepted and declarations made by the seminar participants generally. Part 3 discusses possibilities of transfer of experiences across the various countries, plans of individual nations, and possibilities of international cooperation. Appendixes provide information on the agencies that supported the seminar and on its participants and program. A short bibliography on literacy planning and implementation of literacy programs is included. (YLB)
Keywords: Adult Education; Adult Literacy; Bangladesh; Botswana; Burma; Cuba; Demonstration Programs; Developing Nations; Ethiopia; Foreign Countries; Illiteracy; India; Iraq; Kenya; Literacy Education; National Programs; Nicaragua; Nigeria; Program Descriptions; Program Development; Program Implementation; Seminars; Sierra Leone; Somalia; Sudan; Tanzania; Thailand; Vietnam; Zambia

Writing for Distance Education. Samples Booklet. - International Extension Coll., Cambridge (England). (Writing for Distance Education. Samples Booklet., 1983)
Approaches to the format, design, and layout of printed instructional materials for distance education are illustrated in 36 samples designed to accompany the manual, "Writing for Distance Education." Each sample is presented on a single page with a note pointing out its key features. Features illustrated include use of typescript layout, a comic strip story, various question and instruction formats, check lists, signs and a key, study guidance, diagrams, list formats, pictures reinforcing written messages, objectives, culturally relevant design, charts, flowcharts, tables, photographs, and illustrations. Materials used in the examples are taken from a variety of actual projects and courses--e.g., biology, French, English, German, mathematics, educational studies, introduction to the computer, and vegetable growing--in such institutions as the Mauritius College of the Air, Javeriana Open University (Colombia), Botswana Extension College, Kenya Cooperative College, Open University, Lesotho Distance Teaching Centre, and the National Extension College. (LMM)
Keywords: Design Requirements; Distance Education; Instructional Materials; Layout (Publications); Material Development; United Kingdom; England; Visual Aids

Evaluation of Mathematics Curriculum in Primary Teacher Training Institute in Somalia. African Studies in Curriculum Development & Evaluation. - Jama, Mohamed A. F.; African Curriculum Organisation. (1983)
This study sought to evaluate the mathematics curriculum of the Halane Teacher Training Institute in Somalia with a view toward: (1) determining its weaknesses and recommending measures for improvement; (2) examining its relevance to the present needs of the Somali society; (3) determining the suitability of instructional materials and other support resources; and (4) investigating the present organization of teaching practice and the time allocated to it. Thirteen of 15 mathematics teachers at the Institute were included in the study, as well as a proportional random sampling of 60 of 2617 trainees and a random sample of 40 mathematics teachers (graduates of the Institute) from four schools in Mogadisho. Questionnaires, some structured interviews, tests, and documentary resources were used to collect data. Among the numerous findings were: (1) most of the teachers at the Institute had not taught in primary schools; (2) training was basically theoretical, focused on content, with minimal attention to methodology; (3) there was a lack of relationship between the syllabi of the Institute and primary schools; and (4) time devoted to training was too limited. Appended are the instruments used (in the Somali language). (MNS)
Keywords: Educational Planning; Educational Research; Elementary Education; Elementary School Mathematics; Mathematics Curriculum; Mathematics Instruction; Preservice Teacher Education; Somalia; Teacher Education; Teacher Qualifications

New Trends in School Science Equipment. - Lowe, Norman K.; United Nations Educational, Scientific (1983)
This four-part volume examines trends, problems, and issues related to school science equipment. Part 1 focuses on laboratory work and practical activities in science and technology education, considering equipment and curriculum development, equipment development related to curricula in Brazil, uses of local resources for practical work, elementary technology materials for science curricula, project work and the needs of a technology laboratory, and the development and utilization of equipment for scientific subjects in Hungary. Part 2 examines the development and production of science and technology equipment, discussing the provision of equipment on a national scale, the Regional Centre for Education in Science and Mathematics (Penang), the National Educational Equipment Centre in Pakistan, development of school equipment production in Kenya, production of low-cost equipment in Hong Kong, and science equipment centers in Belgium. Part 3 examines various aspects of teacher training for practical work in science and technology, including the approach of the Australian Science Teacher Education Project, teacher training in Trinidad and Tobago, and the establishment of a laboratory technician training school in Afghanistan. Part 4 reports on information and communication related to school science and technology equipment, examining the need for a clearinghouse and information network. (JN)
Keywords: Curriculum Development; Elementary School Science; Elementary Secondary Education; Equipment Utilization; Foreign Countries; France; Material Development; Resource Centers; Science Curriculum; Science Education; Science Equipment; Science Instruction; Secondary School Science; Teacher Education; Technology

Investigation of Problems of Implementing Curriculum in Primary Schools in Somalia. African Studies in Curriculum Development & Evaluation. - Mohamed, Ibrahim Jeylani; African Curriculum Organisation. (1983)
The aim of this study was to investigate the implementation of modern mathematics in the primary schools of Somalia. In particular, three concerns were addressed: (1) teachers' confidence and ability in teaching mathematics; (2) students' interest in mathematics; and (3) students' examination performance in mathematics. Subjects were 30 teachers and 150 pupils in Primary One (age 8) in four schools in Mogadishu and Afgoye. Observations, teachers' notes, interviews, questionnaires (for teachers), and tests (for students) were used. The results are reported in terms of: (1) class size (only 10 percent of the classes had an enrollment of less than 50); (2) teachers' qualifications (only two-thirds had attended the in-service course in mathematics) and achievement of students and teachers (poor); (3) lesson preparation; (4) classroom evaluation; and (5) confidence and ability of teachers. Recommendations suggest that a training course needs to be carefully planned, and some basic characteristics are listed. Appended are the instruments used in the study. (MNS)
Keywords: Curriculum Development; Developing Nations; Educational Planning; Educational Research; Elementary Education; Elementary School Mathematics; Inservice Teacher Education; Mathematics Achievement; Mathematics Curriculum; Mathematics Instruction; Primary Education; Somalia; Student Attitudes; Teacher Education; Teacher Qualifications

Evaluation of the Literacy Programme, Machakos District. African Studies in Curriculum Development & Evaluation No. 91. - Nzioki, S.; Kenya Inst. of Education, Nairobi.; Nairobi Univ. (Kenya).; German Agency for Technical Co-Operation, Nairobi (Kenya). (1983)
Faced with the fact that over 50% of its citizens are illerate, and recognizing the link between illiteracy, poverty, and disease, the government of Kenya, in 1963, created an adult literacy program. The program's objectives were (1) to train literacy teachers, (2) to produce materials for teaching and learning and for continuing education after literacy was achieved, and (3) to appoint officers from the Ministry for Housing and Social Services in each district, province, and division to establish adult literacy centers and to oversee the program. From the beginning the program has encountered difficulties, and a study, conducted in the Machakos District, was undertaken to evaluate its effectiveness. The study found a high percentage of untrained teachers working in the program, a lack of funds for effective supervision and coordination, irregular attendance by learners at literacy centers, poor cooperation between the district and the divisions, an irregular supply of teaching materials, the use of improper methods in teaching adults, a high dropout rate among male learners, and, especially, a great disparity in salaries among the three categories of teachers in the program. Part-time and self-help teachers handled the bulk of the instruction, yet their wages were minimal. As a consequence teacher morale was low and instruction suffered. The findings suggest that unless the ministry takes corrective measures to alleviate these problems, it is unlikely that the goals of the literacy campaign will be realized soon. (A list of recommendations and suggestions to accelerate the implementation of an effective literacy program, based on the study findings, plus appendixes that contain instruments used in the study, are included in this report.) (RBW)
Keywords: Adult Basic Education; Adult Literacy; Basic Skills; Developing Nations; Educational Policy; Federal Government; Functional Literacy; Government Role; Government School Relationship; Illiteracy; Kenya; Literacy Education; Minimum Competencies; Politics of Education; Program Effectiveness; Salary Wage Differentials; Teacher Administrator Relationship

National Geographic Gifted Program, 1982-83. Final Evaluation Report. - Walker, Sharon; Thomas, Earl; New York City Board of Education, Brooklyn. Office of Educational Assessment. (1983)
The report presents evaluation data on a program designed to use National Geographic Society materials (periodicals, filmstrips, maps, etc.) as part of a curriculum on African cultures for gifted students (grades 5-6). Among program goals were to develop pupil skills and knowledge horizontally and vertically; to introduce anthropology, sociology, and archaeology as subjects in the elementary curriculum; and to encourage institutional involvement in the educational process. The program featured regular staff development and field trips (including a visit to Kenya). Evaluation methodology included a review of program documents and materials; analysis of weekly teacher logs; and questionnaire observations. Results indicated that the materials were judged to be of good quality; there was not quantitative evidence that the program had a positive influence on cognitive skills development; and use of consultants, experts, and area resources was built into all of the curriculum units. Recommendations were made for program improvement, including that curriculum unit tests be developed to measure student performance. Appended materials include an outline of the pilot program and sample evaluation forms. (CL)
Keywords: Anthropology; Archaeology; Community Resources; Demonstration Programs; Elementary Education; Gifted; Learning Activities; Social Studies; Sociology; Talent; U.S.; New York; Units of Study

Writing the Instructional Radio Script. - de Fossard, Esta; Academy for Educational Development, Washington (1982)
This guide was developed for script writers on the Radio Language Arts Project, which was designed to develop, implement, and test the effectiveness of an instructional radio system to teach English as a second language at the primary school level in Kenya. The project was planned to produce a radio-based, English language program with approximately 195 taped 30-minute lessons for each school year, appropriate tests, teacher orientation materials, and classroom observation and data-gathering procedures. The following specific topics are addressed: writing for instructional media; radio as an instructional medium; listening; sound effects; the classroom teacher; writing stories for children; animal characteristics; writing instructional programs for children; purpose and objectives; evaluation; modeling; reinforcement; the program format; writing the program segments; and script check list. Script format is described including segment headers, special script instructions, script punctuation, script cover sheet, and review. The script for lesson 76 from the first year broadcast is included. (LMM)
Keywords: Developing Nations; Educational Radio; Elementary Education; English (Second Language); Kenya; Material Development; Production Techniques; Program Development; Programing (Broadcast); Scripts; Second Language Instruction; Teaching Methods

Handwriting Manual for Primary Teachers in Somalia. African Studies in Curriculum Development & Evaluation No. 61. - Dirie, Mohamed Farah; Kenya Inst. of Education, Nairobi.; Nairobi Univ. (Kenya).; German Agency for Technical Co-Operation, Nairobi (Kenya). (Handwriting Manual for Primary Teachers in Somalia. African Studies in Curriculum Development & Evaluation No. 61., 1982)
Concern over the poor and illegible handwriting of the students in Somalia led to the development of this handwriting manual for primary school teachers to: (1) give teachers guidance in teaching handwriting; (2) help teachers in the methodology of teaching handwriting; (3) let teachers know the easier ways of making cheap and obtainable materials for handwriting; and (4) show teachers how to evaluate handwriting. The first chapter provides general information about learning and includes sections on learning with the five senses, activities with movement for growing and learning, learning by imitation, meaningful learning, practice in learning, influence of punishment and failure on learning, learning by doing, and how students learn handwriting. The focus of the second chapter is on manuscript writing with discussion centered on the modern way of writing capital letters, why capital letters are taught in manuscript, why capital letters are taught before lower case letters, the help of squared paper, the use of capital letters, and correct position for writing. The third chapter discusses games for the teaching of handwriting, and the final chapter presents information for teaching and evaluating handwriting, with sections on how to teach handwriting, how to plan a lesson, how to make a lesson interesting, what to use in teaching handwriting, what to do when handwriting is taught, why handwriting is evaluated, how to evaluate handwriting, how to evaluate daily practice in handwriting, how to give marks on handwriting papers, and how to construct handwriting tests. (HOD)
Keywords: Educational Games; Elementary Education; Foreign Countries; Handwriting; Instructional Materials; Lesson Plans; Manuscript Writing (Handlettering); Somalia; Teaching Guides; Test Construction; Visual Aids; Writing Evaluation; Writing Instruction; Writing Skills

Participatory Research: An Emerging Alternative Methodology in Social Science Research. Participatory Research Network Series No. 2. - Kassam, Yusuf; Mustafa, Kemal; Society for Participatory Research in Asia, New Delhi (India).; African Adult Education Association, Nairobi (Kenya). (Subregional Seminar for Eastern and Southern African Countries, 1982)
This book, consisting of a series of discussion papers and case studies, is a compilation of the papers presented at a region 1 workshop on participatory research in Africa. Included in the volume are the following discussion papers: "The Concept of Development in the Social Sciences," by Kemal Mustafa and Deborah Bryceson; "The Politics of Research Methodology in the Social Sciences," by Marjorie Mbilinyi, Ulla Vuorela, Yusuf Kassam, and Yohana Masisi; "The Methodology of the Participatory Research Approach," by Deborah Bryceson, Linzi Manicom, and Yusuf Kassam; and "Participatory Research: Redefining the Relationship Between Theory and Practice," by Deborah Bryceson and Kemal Mustafa. Several case studies are also presented, including: "Participatory Research as an Instrument for Training: The Youth Development Project in the Coast Region of Tanzania," by Marja-Liisa Swantz; "Rural Vocational Education in Tanzania: An Exploratory Research," by R. Mshana and T. Bita; "The Use of Popular Theatre for Adult Education in Botswana and its Relation to the Concept of Participatory Research," by Ziki Kraai, Bob MacKenzie, and Frank Youngman; "Demystifying Research: A Case Study of the Chiwanda Nutrition Education Project," by Y. K. C. Masisi; "Appropriate Technology for Grain Storage at Bwakira Chini Village," by E. K. Mduma; "The Jipemoyo Project," by Kemal Mustafa; and "On Literacy Content," by Ngugi wa Mirii. (MN)
Keywords: Adult Education; Africa; Case Studies; Cooperative Programs; Data Collection; Definitions; Educational Research; Educational Strategies; Nutrition Instruction; Research Design; Research Methodology; Rural Education; Social Science Research; Technological Advancement; Theater Arts; Vocational Education; Youth Programs

Investigation of the Effectiveness of Teacher-Education Curriculum in Primary School Mathematics in Tanzania Mainland. African Studies in Curriculum Development & Evaluation. No. 64. - Masota, Laurent Anatoly; Kenya Inst. of Education, Nairobi.; Nairobi Univ. (Kenya).; German Agency for Technical Co-Operation, Nairobi (Kenya).; African Curriculum Organisation. (1982)
An investigation was made of the effectiveness of the teacher education curriculum for primary school mathematics teachers in Tanzania. Subjects were a random sample of 8 teacher trainees in each of 4 selected colleges, as well as 4 school principals, 12 tutors, and 16 serving teachers. Data were gathered by means of questionnaires and observations. Results showed that colleges in Tanzania do not have a prescribed mathematics textbook. It was also indicated that topics such as probability, number bases (other than base 10), and intersection and union of sets should be dropped or taught with very little emphasis and that topics such as equations and business arithmetic should be added to the present syllabus. Results indicate that a review of the existing college mathematics syllabus is necessary. Other observations showed that mathematics teachers in primary schools used very few teaching aids, class textbooks were available, and subject matter was fairly well understood by pupils. The poor mathematics background of the teacher trainees was noted by all respondents, and block teaching practice during the first and second year of teacher training was recommended. Samples of the research instruments are appended. (JD)
Keywords: Developing Nations; Elementary Education; Elementary School Mathematics; Foreign Countries; Instructional Materials; Mathematics Education; Mathematics Teachers; Preservice Teacher Education; Program Effectiveness; Program Evaluation; Tanzania; Teacher Education Curriculum; Teacher Effectiveness

An Investigation into the Effectiveness of Teaching Mathematics in Primary One of Gambian Schools. African Studies in Curriculum Development & Evaluation No. 51. - Sallah, Malick Alieu; African Curriculum Organisation. (1982)
This research was undertaken to study the effectiveness of elementary school teachers with pupils, aged 8, entering Gambian schools. The investigator attempts to describe what teachers do, to search for associations between theoretically or empirically derived variables and learning, and to infer the power of given factors in instructional procedures which may make practical differences in sought outcomes. Following a review of relevant literature on teacher effectiveness, the methodology of the study is outlined. The sample included 16 urban, semi-urban, and rural elementary schools. Observations, lesson plan assessments, teacher questionnaires, and pupil achievement tests were employed. Data were analyzed in terms of class size, teachers' qualifications, teachers' experience levels, lesson preparation, classroom environment, classroom communication, teachers' attitudes, pupils' attainment of Primary 1 mathematics objectives, problems of teaching Primary 1 mathematics, and correlations between variables. Finally, conclusions and recommendations are given. Appendices contain the teacher questionnaire, the observation and assessment guide, and achievement test items. (MNS)
Keywords: Achievement; Attitudes; Educational Research; Elementary Education; Elementary School Mathematics; Gambia; Grade 1; Lesson Plans; Mathematics Instruction; Primary Education; Research Reports; Student Teacher Relationship; Teacher Characteristics; Teacher Effectiveness; Teaching Methods

A Teacher Training Reading Methodology Manual in Kiswahili for Lower Primary Classes in Kenya. African Studies in Curriculum Development & Evaluation. No. 62. - Wanyoike, E. N.; Kenya Inst. of Education, Nairobi.; Nairobi Univ. (Kenya).; German Agency for Technical Co-Operation, Nairobi (Kenya).; African Curriculum Organisation. (A Teacher Training Reading Methodology Manual in Kiswahili for Lower Primary Classes in Kenya. African Studies in Curriculum Development & Evaluation. No. 62., 1982)
Kiswahili was declared the national language of Kenya in 1968 and since then has also been established as the language of parliamentary debate. There are, however, inadequate instructional materials in this language, particularly at the primary level of schooling. Since there are almost 20 different languages, or dialects, in Kenya, Kiswahili must be taught as a second language to a number of children in the early grades. This teacher's manual provides a methodology for instructing children in reading, speaking, and writing Kiswahili. Chapter 1 presents an overview of the language situation in Kenya and the language learning needs of the Kenyan child, who may speak a different mother tongue and must learn not only Kiswahili but also, in later years, English. Chapter 2 discusses the basic language skills of listening, speaking, reading, and writing. Methods of teaching reading are addressed in the third chapter. Chapters 4 and 5 are devoted to reading Kiswahili as a first and as a second language. Suggestions are made in chapter 6 for supportive reading materials which may be created by the teacher, and the seventh chapter presents ways to reinforce reading skills through handwriting and creative writing exercises. Chapter 8 offers a short conclusion, and there are three one-page appendices. (JD)
Keywords: Bilingual Education; Class Activities; Creative Writing; Developing Nations; Dialects; Educational Resources; Elementary Education; Foreign Countries; Instructional Materials; Kenya; Language Proficiency; Listening Skills; Multilingualism; Reading Instruction; Reading Readiness; Second Language Instruction; Teacher Developed Materials; Teaching Methods

A Comparative Study of the Mass Literacy Campaigns of Tanzania and Kenya. - Bhola, H. S. (A Comparative Study of the Mass Literacy Campaigns of Tanzania and Kenya., 1981)
A two-pronged theory underlying literacy campaigns suggests that (1) the prevailing ideology of a society will determine the objectives of the literacy campaign as well as the language of justification used by the development elite in the promotion of adult literacy; and (2) the ideology, as expressed in the political culture of a society, will influence the technology of a literacy campaign in regard to the strategies used for the articulation of the national commitment; the mobilization of the masses; and the establishment of organizational structures, the management of incentives for the recruitment of participants and teachers, the development of curricula, and the design of systems for the delivery of instruction. This two-pronged theory can be seen at work in the literacy campaigns conducted in Tanzania and Kenya, where differing ideologies have resulted in differing methods for promoting literacy. Tanzania follows a socialist ideology, and emphasizes literacy as a tool for the participation of the masses in society in its very successful literacy campaign. Kenya, on the other hand, while following an espoused socialist philosophy, supports individual initiatives and thus uses different programs and incentives, with less success so far, in its less committed literacy campaign. Other studies of literacy campaigns also show much greater success rates in totalitarian than in free societies. Therefore, it is clear that democracies will have to better articulate their ideological positions on literacy and they will have to extend the conception of democracy to include political, social, and economic democracy if they expect to achieve success in literacy efforts. (KC)
Keywords: Adult Basic Education; Adult Literacy; Capitalism; Comparative Analysis; Cultural Context; Democratic Values; Educational Policy; Educational Theories; Kenya; Literacy Education; Political Issues; Political Power; Political Socialization; Program Effectiveness; Public Policy; Social Values; Socialism; Tanzania

Basic Education in International Perspective. - Cain, Edmund J. (Subregional Seminar for Eastern and Southern African Countries, 1981)
These papers, delivered at the 1981 World Assembly of the International Council on Education for Teaching, reflect the theme of the conference: provision of basic education for all persons, focusing particularly on policies and situations in developing nations. The 14 presentations were from nine nations: (1) "Curriculum Materials for Basic Education: United States" (Edmund J. Cain); (2) "Linking Basic Education to Community Development: United States" (Elmer J. Clark); (3) "Articulation of Basic with Secondary Education: Nigeria" (Ade Fajana); (4) "Citizenship Education: United States" (William E. Gardner); (5) "Basic Education in Science and Technology: United States" (Robert W. Howe); (6) "The Status of Basic Education: England/Wales" (David J. Johnston); (7) "The Development of Basic Education: Kenya" (Joseph A. Lijembe); (8) "Basic Education Issues and Policies: Brazil" (Nelly Aleotti Maia); (9) "Science and Basic Education: Trinidad" (Paula Mark); (10) "New Educational Priorities: Tanzania" (G. V. R. Mmari); (11) "Basic Skills Assessment: United States" (John D. Mulhern); (12) "Basic Education in Rural Areas: Bolivia" (Ignacio Paravicini Ruiz); (13) "Educating A Good Citizen: United Kingdom" (Jean Russell-Gebbett); and (14) "Primary and Secondary Education: Korea" (In-Jong You). The papers present situation reports for each country, describing the national programs and policies or local efforts to promote basic learning skills. (FG)
Keywords: Basic Skills; Citizenship Education; Curriculum Development; Developing Nations; Educational Change; Elementary Secondary Education; Equal Education; Foreign Countries; National Programs; Science Education; U.S.; District of Columbia

Basic Education for the Real World. International Perspectives on Human Resource Development. Proceedings of the ICET World Assembly, (28th, Cairo, Egypt, August 10-14, 1981). - International Council on Education for Teaching, Washington (Subregional Seminar for Eastern and Southern African Countries, 1981)
The papers is this volume were presented at the 1981 World Assembly of the International Council of Education for Teaching, attended by representatives from over 35 nations. The papers are organized in seven sections, and all relate to the theme of the assembly, basic skills development. Section I contains one paper, an address on motivating people for educational change, by W. Clement Stone. Section II presents three papers by Egyptian educators on the educational system in Egypt. The four papers in Section III discuss methods of linking education with economic goals. The fourth section is a paper by a member of the United Nations Educational, Scientific, and Cultural Organization on redirecting educational priorities toward eliminating illiteracy and providing basic education for all individuals. An international perspective on basic education is presented in Section V, with reports from the United States, Nigeria, Great Britain, Kenya, Brazil, Trinidad, Tanzania, Bolivia, and South Korea. The papers in Section VI survey the preparation of teachers in basic education in the United States, Australia, Ireland, and Malaysia. The final section has four papers on methods of relating educational research to practice, using case studies in the United States, Colombia, and Japan. (FG)
Keywords: Basic Skills; Developing Nations; Education Work Relationship; Educational Change; Educational Policy; Educationally Disadvantaged; Egypt; Equal Education; Foreign Countries; Global Approach; Illiteracy; Literacy Education; Research Utilization; Teacher Education; Teaching Methods

Dispatch Case. (Dispatch Case., 1981)
Presents news briefs on education as of July 6, 1981. Complaints of foreign students in Romania on the living conditions and the prevalence of corruption in higher education in the country; Elimination of mathematics courses from elementary and secondary schools in Kenya; Information on a protest staged by Nobel laureates concerning the internal exile imposed by Soviet authorities on computer scientist and Jewish activist Viktor Brailovsky.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Brailovsky, Viktor; Corruption; Education; Educational Support Services; Foreign students; Higher education; Kenya; Mathematics education; Romania; Soviet Union

Trends in Innovation: Basic Education in Africa. - Bartels, Francis L.; United Nations Educational, Scientific (1981)
A comparative study is reported of basic education in 10 African countries: Ethiopia, Kenya, Somalia, Sudan, Uganda, Zambia, Benin, Mali, Upper Volta, and Angola. Basic education is defined as learning experiences to which all citizens are entitled or which are required to help them develop their potential to function effectively as individuals and members of society. Data sources include findings of seminars on basic education and teacher training for basic education and other relevant documents of the UNESCO/UNICEF Cooperation Programme in Africa. The report focuses on definitions of terms; trends in international, national, and regional philosophies of basic education; African educational efforts in the schools; teacher training; and basic education efforts for the unschooled adult and rural poor. The list of 23 findings suggests that experiments in basic education have not made a major impact on the national level. Two philosophical trends were identified: one, that basic education should occur principally through the formal educational system; two, that basic education should occur through the adult community outside school and college. Concerns which influence basic education are resistance to change, sub-regional political demands, economic growth, and poverty and privation. Finally, a good primary system was perceived as the most vital target for the general health and energy of a nation. (KC)
Keywords: Adult Education; Africa; Basic Skills; Comparative Analysis; Comparative Education; Educational Needs; Educational Philosophy; Educational Practices; Educational Trends; Elementary Secondary Education; Foreign Countries; Postsecondary Education; Poverty; Quality of Life; Rural Education; Teacher Education

Using Radio's Potential to Teach Language Arts. - Cutler, Morris (1981)
The Radio Language Arts Project (RLAP) is a pilot program being developed in Kenya to provide a cost effective English-as-a-second-language program via radio to rural children. The RLAP will use an integrative language arts approach focusing on language function, meaning, and communication activities, with listening and oral language preceding reading and writing. Each 20- to 30-minute broadcast will consist of several brief segments of varied learning activities designed to teach or maintain a skill, and will allow as many as four to eight pupil responses per minute. Children in the primary grades will receive English instruction via daily broadcasts; will talk, write, and respond physically throughout the program; and will receive immediate results to stimulate learning. A teacher's guide will provide classroom teachers with information about each lesson and suggestions for their participation. After each broadcast, classroom teachers will direct additional oral and written language exercises. Evaluation of the project will include trained observers noting pupil reaction, and a measure to compare the achievement of pupils taught by RLAP with that of pupils taught by conventional methods. If successful, the RLAP will provide improved instruction of English at a lower cost to a greater number of students, and its design will allow for its transfer, intact or with alterations, to other geographical locations to meet their needs. (HTH)
Keywords: Developing Nations; Educational Radio; English (Second Language); Kenya; Language Arts; Primary Education; Program Content; Program Descriptions; Radio; Rural Education; Rural Youth; Second Language Instruction; Teaching Methods

Developing and Evaluating Supplementary Science Readers for Primary 3 Pupils in Uganda. African Studies in Curriculum Development & Evaluation. - Kiyimba, David S.; African Curriculum Organisation. (1981)
Five science reading booklets were developed to foster the development of communication, observation, and experimentation skills in Uganda elementary school students. Topics selected, resulting from interviews with teachers and students, included: 1) rain; 2) round worms; 3) caterpillars; 4) butterflies; and 5) insects in the school ground. Booklets were evaluated after an initial trial (focusing on vocabulary level, time required to read the readers, student interest, whether related activities were workable and simple, and suggested improvements). Following revisions based on the trial editions, revised readers were evaluated by observing students and teachers using the readers and analyzing questionnaires designed to assess cognitive, psychomotor, and affective impacts of the readers on students and teachers. Results indicate that the readers aroused and maintained student interest, developed scientific skills and attitudes, and enabled students to gain science knowledge through independent or group reading. In addition, it was demonstrated that well-written, inexpensive, supplementary reading materials could be produced to encourage appreciation of written materials among students of low-income parents in rural areas. The five readers and questionnaires used are included. (Author/JN)
Keywords: Curriculum Development; Elementary School Science; Foreign Countries; Formative Evaluation; Grade 3; Instructional Materials; Material Development; Primary Education; Science Curriculum; Science Education; Supplementary Reading Materials; Uganda

Presidential working party on the establishment of the second university - Mackay, C.B. (Government Printer., 1981)

Curriculum for Early Childhood Education: A Report of a Workshop Held at the Kenya Institute of Education (July 16 to August 3, 1979). Volume 1. - German Foundation for International Development, Bonn (West Germany). (Subregional Seminar for Eastern and Southern African Countries, 1980)
A workshop on "Curriculum for Early Childhood Education," held in the summer of 1979 at the Kenya Institute of Education, aimed to familiarize participants with the problems facing early childhood education in Africa. Specific workshop objectives were (1) to familiarize participants with the psychological, social, political, and economic factors influencing the young African child; (2) to enable participants to apply educational implications inferred from the first objective; and (3) to inculcate necessary skills for designing curriculum for early childhood education in Africa. This document, one of two volumes of the workshop proceedings, includes foundation papers, country profiles, working group reports, opening session addresses, and an evaluation of the workshop. Topics of foundation papers include specific African aspects of developmental tasks facing young children, sociocultural environments, traditional forms of early childhood education, teacher training, political and economic realities, and evaluation. Representatives from various countries reported on teacher training, early childhood education, and trends in curriculum development within their respective countries. Working group reports focused on developing language skills, developing scientific, computational, and manipulative skills, and catering for children with special needs. (Author/DB)
Keywords: Africa; Child Development; Computation; Curriculum Development; Developing Nations; Developmental Tasks; Early Childhood Education; Elementary School Teachers; Foreign Countries; Language Skills; Preschool Education; Preschool Teachers; Science Instruction; Socialization; Special Education; Teacher Education; Teacher Workshops

Survey of Basic Education in Eastern Africa. UNESCO/UNICEF Co-Operation Programme. - United Nations Educational, Scientific; United Nations Children's Fund, Nairobi (Kenya). Eastern Africa Regional Office. (1980)
A survey of basic education in 13 Eastern African countries (Madagascar, Burundi, Comores, Ethiopia, Mauritius, Botswana, Kenya, Lesotho, Swaziland, Tanzania, Zambia, Malawi, and Somalia) covers basic education programs and UNICEF's supporting role. Basic education is seen as a concept evolved in the region, involving formal school systems and educational programs for out-of-school children, adolescents, and adults; and having goals determined by political philosophies of different countries, with the overall aim of providing all citizens with education to prepare them for satisfying lives in their socio-cultural economic environment. Tables give statistics on basic education programs by country; indicate the importance attached to 20 basic education components; and chart unanimity on literacy, numeracy, and basic skills. Brief descriptions of Tanzania's community schools program and Somalia's nomadic education centers are presented. Important factors in the development of basic education are detailed: sharing experiences, generation of new ideas, personnel, infrastructures, and financing. UNICEF's role in supporting basic education is discussed, including regional programs, financing, relevance/effectiveness of UNICEF assistance, and problem areas. Recommendations call for future UNICEF assistance to advocacy, planning, programs and projects, preschool activities, inclusion of indigenous cultural elements in the curricula, and monitoring/evaluation activities. Appendices list objectives and characteristics of basic education, by country, and proposed themes for future regional meetings. (MH)
Keywords: Adult Education; Africa; Community Schools; Cultural Education; Developing Nations; Educational Objectives; Educational Philosophy; Elementary Secondary Education; Financial Support; Foreign Countries; General Education; International Programs; Migrant Education; National Programs; Nomads; Nonformal Education; Program Development; Program Effectiveness; Program Evaluation; Rural Education; Somalia

Literacy for and by the People: Kenya's Kamirithu Project. - wa Mirie, Ngugi (Literacy for and by the People: Kenya's Kamirithu Project., 1980)
Describes a literacy program in Kamirithu, Kenya. Discusses the needs of the community and the importance of integrating literacy projects into the process of community development. (JOW)
Keywords: Adult Basic Education; Adult Literacy; Community Education; Community Involvement; Developing Nations; Kenya; Literacy Education

Research in Adult Education: Adult Education and Development. Report on the International Seminars Held at the Nordic Folk Academy (Kungalv, Sweden, June 25-27, 1979). - International Council for Adult Education, Toronto (Ontario).; Swedish National Federation of Adult Education Associations, Stockholm. (Subregional Seminar for Eastern and Southern African Countries, 1979)
This publication contains reports, papers, and presentations from the International Seminar on Research in Adult Education and Development. The keynote address, The Role (Past, Present, and Future) of Adult Education in Development, reviews the five-year Design for Action from the 1976 International Conference on Adult Education and Development. The report of the research seminar contains these sections: key issues raised, summaries of ten papers and presentations (panels and consortium), and research needs. Titles include (1) Adult Learning--The Study Circle as Method, (2) The Role of Research in Adult Education Activities, (3) Recruitment to Adult Education--Research and Outreaching Activities, (4) Evaluation Plan for the National Adult Education Program in India, and (5) Issues in Participatory Research. The report of the second seminar contains these materials: observation, questions, and issues; strategies and recommendations; six national case studies; and reports on three international and four national development aid agencies. The case studies of adult education in practice describe literacy and health in Kenya, rural development in Honduras and Haiti, integrated child development services in India, women's participation in development in Nigeria, and Tanzania's Folk Development Colleges. (YLB)
Keywords: Adult Education; Adult Learning; Adult Literacy; Case Studies; Cooperation; Developing Nations; Development; Economic Development; Educational Development; Educational Research; International Organizations; International Programs; International Relations; Literacy Education; National Organizations; National Programs; Rural Development; Seminars; Social Change; Sweden

African Seminar on Education for International Understanding at the Primary School Level. (African Seminar on Education for International Understanding at the Primary School Level., 1979)
Presents the text of a speech given by Dr. Taaitta Towett at the opening ceremony of a seminar on the promotion of education for international understanding in primary schools in January 1979 in Kenya. (CK)
Keywords: Africa; Civil Liberties; Comparative Education; Cooperation; Elementary Education; Foreign Countries; International Education; International Programs; Kenya; Peace; Racial Bias; Speeches

Curriculum Development for Functional Literacy and Nonformal Education Programs. Workshop. - Bhola, H. S.; German Foundation for International Development, Bonn (West Germany). (Curriculum Development for Functional Literacy and Nonformal Education Programs. Workshop., 1979)
To provide an introduction to processes, issues, and problems of curriculum development in functional literacy and nonformal education, a monograph provides 11 chapters, each followed by exercises. The first chapter discusses curriculum development in relation to national development. The second chapter covers concepts of functional literacy and nonformal education, with particular reference to development objectives. A third chapter presents a model of the curriculum development process, including objectives. Assessing developmental and educational needs of communities, with emphasis on participatory strategies, is covered in a fourth chapter. In the fifth chapter, the concept of instructional systems design is introduced, with elaboration on task analysis, learner analysis, and learning environment analysis, and including an instructional system analyzer. Training of literacy teachers is described in the sixth chapter. The seventh chapter covers a variety of instructional materials for functional literacy, with emphasis on message making. In the eighth chapter, a plan for establishing learning resource centers discusses delivery systems for instruction and instructional materials. The ninth chapter provides case studies of projects in curriculum development/implementation for functional literacy in Brazil, Burma, Colombia, India, Iran, Kenya, Mali, Sudan, Tanzania, and Thailand. The tenth chapter discusses curriculum evaluation, and the eleventh covers training for curriculum development, including a workshop description and questionnaire. (MH)
Keywords: Adult Education; Case Studies; Community Development; Community Education; Community Involvement; Curriculum Development; Curriculum Evaluation; Delivery Systems; Developing Nations; Educational Environment; Educational Strategies; Foreign Countries; Functional Literacy; Inservice Teacher Education; Instructional Materials; Instructional Systems; National Programs; Needs Assessment; Nonformal Education; Resource Centers; Task Analysis; U.S.; West Germany; Workshops

A Manual for the Analysis of Costs and Outcomes in Nonformal Education. - Educational Testing Service, Princeton (A Manual for the Analysis of Costs and Outcomes in Nonformal Education., 1979)
Guidelines are presented for applying cost-effectiveness and cost-benefit analysis techniques to nonformal education (NFE) programs in developing nations. The methods are based on workshops conducted in Kenya, Tanzania, Indonesia, and Guatemala. The manual is designed for those personnel responsible for planning, administering, and evaluating NFE programs, and government or private agency officials who make investment decisions. The manual is intended as a guide, and is organized as follows: economic analysis in project selection, development, and evaluation; organizing for economic analysis; concepts in economic analysis of NFE; step-by-step procedures--including defining the project and stating objectives, listing resources, determining and adjusting resource costs, summarizing and analyzing project costs, specifying educational outcomes and skills to develop, specifying intended and unintended proect outcomes, valuing and adjusting project outcomes, relating costs and outcomes, and interpreting results of the analysis; report writing; information processing; and use of computer-based information systems. Examples and exercises are included in the manual, and explanations of statistical methods and concepts are appended. (MH)
Keywords: Administrator Guides; Cost Effectiveness; Cost Estimates; Data Analysis; Data Processing; Decision Making; Developing Nations; Economic Research; Educational Assessment; Educational Objectives; Financial Needs; Foreign Countries; Guides; Information Processing; Nonformal Education; Program Costs; Program Evaluation; Resource Allocation; Skill Development; Technical Writing; Training Objectives; U.S.; New Jersey

Literacy Research in Developing Countries. Final Report. - King, Kenneth; International Development Research Centre, Ottawa (Ontario).; German Foundation for International Development, Bonn (West Germany) (Subregional Seminar for Eastern and Southern African Countries, 1978)
The nine papers in this document represent the final report of a workshop on research on literacy in developing countries. It is noted in the introduction by Kenneth King that research in literacy tends to be performed by persons who are also literacy activists and that the problem of motivation seems to be central to most literacy research. It is suggested that adult literacy research must be connected with research on the quality and effectiveness of elementary and secondary education. The papers included are: "Development Policy Outcomes of Adult Literacy Research"; "Literacy without Schooling: Testing for Intellectual Effects"; "Primary School Leaving Examinations, Basic Intellectual Skills, and Equity: Some Evidence from Kenya"; "International Study of the Retention of Literacy and Numeracy: the Egypt Case Study"; "Research on Innovative Nonformal Education for Rural Adults: Implications for Literacy Motivation"; "New Research Approaches to Literacy Development in Tanzania"; "First Report on the National Adult Education Programme: the Scope for Evaluation"; "A Comparison of Three-Script Literacy in Liberia"; and "Literacy Research: Some Observations on its Nature and Conduct." (MKM)
Keywords: Adult Literacy; Canada; Ontario; Comparative Education; Developing Nations; Educational Research; Foreign Countries; Functional Literacy; Government Role; Job Skills; Literacy; Literacy Education; Motivation Techniques; Reading Research; Reading Skills

Basic Education: Reflections on Participatory Curriculum Development and Planning. - Sachsenmeier, Peter; German Foundation for International Development, Bonn (West Germany). (1978)
Basic education as the first stage of lifelong education is emerging as a significant alternative to traditional education, especially for rural populations in Third World countries. Basic education is a set of interrelated ideas: community orientation of education, integration of formal, nonformal, and informal learning into lifelong learning, stress on practical skills, involvement of the total population, and overcoming traditional subject orientation of curriculum. Education, an integral part of national development, is more effective when based on well-defined learning needs, and such a curriculum requires both horizontal and vertical integration within a country. Implications for curriculum planners include: concentration on basic needs (health, food, functional literacy); attitude change toward work and development; emphasis on integration of formal/nonformal education; implementation of a flexible, lifelong, lifewide curriculum encompassing needs identification, curriculum control, evaluation, levels of responsibility; new approach to teacher education, teacher role/function; alternative teaching/learning patterns; examination systems reflecting identified learning needs. Four case studies of formal and nonformal education in East Africa illustrate implications of participatory curriculum development and planning policies for educational planners, curriculum developers, and researchers. (RS)
Keywords: Adult Education; Community Education; Curriculum Development; Curriculum Evaluation; Decentralization; Developing Nations; Development; Educational Planning; Foreign Countries; Kenya; Lifelong Learning; Nonformal Education; Nontraditional Education; Participation; Primary Education; Rural Areas; Tanzania; Teacher Role; Uganda

Kikuyu Lifestyles. An Instructional Unit for Intermediate, Elementary Grades. - Roberts, Betty Jean; Illinois Univ., Urbana. African Studies Program. (Kikuyu Lifestyles. An Instructional Unit for Intermediate, Elementary Grades., 1977)
A six-week unit on the Kikuyu people of Kenya for grades 4, 5, and 6 is presented. An overview of the unit lists major concepts and skills to be developed, behavioral objectives, and materials needed for each unit. Following the overview, seven lessons are outlined. In lesson one, students analyze their attitudes toward African culture. Lesson two focuses on Kikuyu housing. Students construct diaramas displaying traditional and modern homes. Lesson three considers the importance of the extended family in African culture. Lesson four investigates the naming of children and the role of Kikuyu family members. Students write a short play depicting the role of a Kikuyu family member. Lesson five, focusing on food production, includes recipes for traditional African foods. In lesson six, students study African clothing. Activities include tie-dyeing and making dashikis. Lesson seven examines traditional educational processes which involve parents teaching children folk tales, crafts, and family tradition. The length of time necessary for presentation, general objectives, reading resources, and teaching methods are provided for each lesson. (KC)
Keywords: African Culture; Area Studies; Cultural Awareness; Educational Objectives; Elementary Education; Folk Culture; Grade 4; Grade 5; Grade 6; Instructional Materials; Kenya; Learning Activities; Resource Materials; Social Studies; Teacher Developed Materials; Teaching Guides; Units of Study

Radio for Education and Development: Case Studies, Volume I. World Bank Staff Working Paper No. 266. - Spain, Peter L.; World Bank, Washington (1977)
Six papers describe use of the radio for in-school and out-of-school formal education in this first volume of working papers on how radio can and is being used for education and development. Part one on in-school education contains: a Nicaraguan project to teach mathematics to first grade children (including curriculum, materials, teacher activities, problems, and envisioned solutions); an evaluation of the radio schools of Tarahumara, Mexico, begun by Jesuit missionaries in 1955, geared toward first-fourth grades; the "Radioprimaria" project headquartered in San Luis Potosi, Mexico, begun in 1970 for fourth-sixth graders in rural areas (format, materials, student participation, and gradual shift from rural to urban use are discussed); a planning study on potential of radio in elementary formal education in Indonesia (covering existing elementary education system and estimates of comparative performances and costs of alternatives). Part two deals with use of radio for distance learning: for inservice training of teachers in Kenya (distinguished by use of correspondence materials supplemented by radio broadcasts to reach a widely scattered adult population) and in Radio Santa Maria's primary and intermediate adult education program in the Dominican Republic (adapted from a model developed in the Canary Islands, Spain). (RS)
Keywords: Adult Education; Case Studies; Communications; Costs; Developing Nations; Dominican Republic; Educational Radio; Elementary Education; Indonesia; Inservice Teacher Education; Kenya; Mathematics; Mexico; Nicaragua; Rural Development; Rural Education; Technology

Report of the National Committee on Educational Objectives and Policies - Republic of Kenya (Government Printer, 1976)

Seminar on 'Structures of Adult Education in Developing Countries, with Special Reference to Africa'. Final Report. - African Adult Education Association, Lusaka (Zambia). (Subregional Seminar for Eastern and Southern African Countries, 1975)
The Kikuyu seminar, third in a series of international meeting on the use of comparative studies as a tool of adult education, focused on the application of the comparative approach to developing countries, particularly Africa. Essential components of the structure of adult education were divided into main sectors, which are individually discussed within the document: (1) goals of adult education; (2) content of adult education; (3) providing agencies; (4) administration and finance; (5) staff, training, and research; (6) methods and materials; and (7) external relationships. The report highlights the range of subjects within each sector, indicates some of the alternatives under discussion, and offers 17 recommendations related to the seven sectors. The seminar conclusion wa s that "only by taking a comprehensive view of the total field of adult education, regarding it as a system made up of apparently independent but nevertheless interacting components each either supporting or weakening the others, would it be possible to secure a harmonious development of the whole and thus bring about a significant and lasting development of adult education." Appendixes contain the opening speech by the Minister for Housing/Social Services, Kenya and diagrams of adult education structure in Sudan, Tanzania, and Zambia. (EA)
Keywords: Adult Education; Adult Programs; Africa; Comparative Education; Developing Nations; Educational Methods; Educational Objectives; Program Administration; Program Costs; Program Development; Resources; Seminars; Teachers

Seven Programs for Seven Countries - Otte, Max R. (Seven Programs for Seven Countries, 1975)
Programs from abroad represented at the January, 1975 Multinational Workshop on Adult Education (Washington, D. C.) included: Rural Reconstruction Movement (Philippines); Nonformal Education for Rural Women (Andhra Pradesh, India); Accion Cultural Popular (Colombia); Village Polytechnic Centers (Kenya); CONCORDE (Honduras); National Adult Education Plan (Tanzania); Functional Literacy and Family Life Planning Program (Thailand). (Author/EA)
Keywords: Adult Basic Education; Adult Education; Adult Programs; Developing Nations; Family Life Education; Human Resources; Literacy Education; National Programs; Rural Education; Technical Education; Womens Education

[Innovative Programs in Adult Education: Foreign.] - World Education, Inc.; Adult Education Association of U.S.A., Washington (Subregional Seminar for Eastern and Southern African Countries, 1975)
The six descriptive position papers were prepared after selection for the Multi-National Workshop on Basic and Functional Education for Adults. Those selected are significant innovative programs of adult education in other countries that may have direct applicability to improving program practices in various parts of the world. The six programs described are: Adult Education in Tanzania; A National Movement; The Functional Literacy and Family Life Planning Project (Thailand); Accion Cultural Popular (Colombia); Concorde--Honduras; Functional Education for Family Life Planning Project (Neuva Ecija, Philippines); and Village Polytechnics--Kenya. Each paper describes in detail the program's setting, organization and administration, program and activities, educational strategy, and future activities and projections. (BP)
Keywords: Adult Education; Adult Programs; Colombia; Educational Innovation; Foreign Countries; Honduras; Kenya; Philippines; Program Descriptions; Tanzania; Thailand

Directory of Adult Education Centres in Africa. - United Nations Educational, Scientific (Directory of Adult Education Centres in Africa., 1974)
The Bureau Regional pour L'Education en Afrique (BREDA) survey, published partly in French, assembled data on the activities of adult education institutions in Africa in order to identify and develop future regional documentation centers. This draft copy of the survey is the first step towards improving international collaboration among documentation centers serving adult education. The survey was formulated through personal staff visits, questionnaires, and studies of the documentation available in Regional Offices of Education. The centers in Cameroon (6 centers), the Congo/Zaire (3 centers), the Ivory Coast (5 centers), Dahomey (1 center), Ethiopia (1 center), Ghana (3 centers) Kenya (3 centers), Madagascar/Malawi (5 centers), Nigeria (22 centers), Sudan (3 centers), Tanzania (8 centers), Uganda (3 centers), and Zambia (6 centers) are covered in the areas of activities, financial resources and publications. The activities section describes the nature of the centers as either those with strong documentation programs, training programs, or information and research programs or as agencies concerned with general or special aspects of adult education. The scope of the adult education programs cover literacy, vocational training, social work, health, agriculture, cooperatives, regional planning and economic development, village studies, language study, and general and continuing education. (JB)
Keywords: Adult Basic Education; Adult Education; Adult Farmer Education; Adult Literacy; Adult Programs; Adult Vocational Education; Africa; Directories; Foreign Countries

Devising Strategies for the Effective Education of Adults in the Developing Countries. Proceedings of the World Confederation of Organizations of the Teaching Profession Seminar on Adult Education (8th, Nairobi, Kenya, August 6, 1973). (Subregional Seminar for Eastern and Southern African Countries, 1973)
Proceedings presented are from a specialized seminar on adult education held in conjunction with the 22nd Assembly of the World Confederation of Organizations of the Teaching Profession (WCOTP). Statements from three countries are presented relating the seminar theme, "Devising Strategies for the Effective Education of Adults in the Developing Countries," to their countries: from Kenya, Ambrose A. Adongo; from Ghana, T. A. Bediako; and from Nigeria, J. C. S. Kong-Doomahbey. A brief statement by Wade Wilson on the implications for adult education of the theme of the WCOTP, "Education for Peace," is presented, as are the report of the secretary of the Committee on Adult Education (Robert A. Luke) and the program of the meeting. (SC)
Keywords: Adult Education; Adult Educators; Adult Literacy; Adult Programs; Comparative Education; Conference Reports; Developing Nations; Educational Needs; Educational Objectives; Educational Planning; Educational Strategies; Foreign Countries; Ghana; Illiteracy; Kenya; Nigeria

Adult Education in Vocational Training: Roles and Methods - Inukai, Ichirou (Adult Education in Vocational Training: Roles and Methods, 1973)
Emphasizing the need to increase literacy among older people in rural areas in Kenya, the author points out that these people have already demonstrated their ability to learn in other skill areas and suggests approaching literacy by way of vocational skills or help in developing small businesses. (SA)
Keywords: Adult Education; Adult Literacy; Foreign Countries; Kenya; Literacy; Rural Areas; Vocational Education

Adult Education in Kenya (A Historical Perspective). Decadal Report 1960-1970. - Board of Adult Education, Nairobi (Kenya). (Adult Education in Kenya (A Historical Perspective). Decadal Report 1960-1970., 1972)
In preparation for the Third World Conference in Adult Education, the chaptrs of this report are based on Unesco's questionnaire. It is, therefore, not an exhaustive account of the period 1960-1970. The report discusses the following topics: National Education System; The Board of Adult Education; Financing; Methodology; and Personnel for Training of Adult Education. Three appendixes present Publications Pertaining to Adult Education Published during the Decade; Members of the Board, 1971; and Statistics and Figures. It is emphasized that informal, fundamental and vocational adult education in Kenya has been more pronounced than formal and literacy education. (DB)
Keywords: Adult Education; Africa; African Culture; Correspondence Study; Developing Nations; Educational Programs; Educational Resources; Kenya; National Programs; Questionnaires; Rural Education; Vocational Education

Kamusi ya Kwanza Kiswahili-Kiingereza. A First Dictionary Swahili-English. - Cahill, William F. (Kamusi ya Kwanza Kiswahili-Kiingereza. A First Dictionary Swahili-English., 1972)
This dictionary is written for students who are learning Swahili as a second language. The 1,837 words that are defined in it are words likely to be encountered by a primary school student in East Africa who is learning Swahili. Most of the English words in the definitions have been taken from among the English words taught during the first four years of the English courses currently in use in Kenya primary schools. In addition to the definitions, typical sentences are included as well as some illustrations. (AMH)
Keywords: Definitions; Elementary Secondary Education; English; Swahili; U.S.; California; Vocabulary

Radio and Television in Literacy. A Survey of the Use of the Broadcasting Media in Combating Illiteracy among Adults. - Maddison, John; United Nations Educational, Scientific (Radio and Television in Literacy. A Survey of the Use of the Broadcasting Media in Combating Illiteracy among Adults., 1971)
Information obtained in a survey of the uses of radio and television in connection with literacy work in 40 countries of the world is presented. Much of the information consists of replies to Unesco questionnaires on the subject. The countries surveyed were: Algeria, Cameroon, Central African Republic, Chad, Congo (Brazzaville), Ethiopia, Gabon, Guinea, Ivory Coast, Kenya, Madagascar, Mali, Niger, Rwanda, Senegal, Sudan, Tunisia, United Arab Republic, Upper Volta, Zambia, Cuba, Guatemala, Jamaica, Mexico, United States, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru, Burma, China (Republic of--Taiwan), India, Iran, Laos, Italy, Spain, and Yugoslavia. A profile or composite picture of practices and experience in various countries is presented. The survey showed that broadcasting is making a valuable and in some cases essential contribution to literacy campaigns. Recommendations made include the following: (1) All the various ways of using radio and television should be fully exploited in all countries that have a sizeable illiteracy problem; (2) This should be done as part of an overall plan to develop the new techniques of communication for economic and social, and especially educational, advancement; (3) Research that aids in planning and further research as well as into "methods" and "materials" is needed; and (4) Training centers and programs for broadcasting personnel are needed. (DB)
Keywords: Adult Basic Education; Adult Literacy; Audiovisual Instruction; Bibliographies; Disadvantaged; Educational Radio; Educational Television; Functional Literacy; Independent Study; Literacy Education; Mass Media; Non Western Civilization; Questionnaires; Surveys; Western Civilization

Masomo Ya Kiswahili [A Kiswahili Course]. - Michuki, David N.; Cahill, William F.; Ministry of Education, Nairobi (Kenya). (Masomo Ya Kiswahili [A Kiswahili Course]., 1970)
This series of illustrated texts in beginning Swahili is a project of the Language Section of the Curriculum Development and Research Centre of the Ministry of Education, Nairobi, Kenya. The course is designed specifically for children who begin the study of Swahili as a second language in Standard (Grade) 4. Students' texts consist of Volumes 1 (in two parts), 2, 3 and 4, accompanied by Teacher's Books 1, 2, 3, and 4. All material in the Students' Books appears in Swahili; in the Teacher's Books, the step-by-step instructions for carrying out the drills and other suggestions for classroom work are presented in English, for "those teachers of Swahili in Kenya who are still improving their own Swahili." Emphasis throughout the course is on oral practice; presentation of structures is graded for difficulty. Supplementary exercises are provided at the end of the Students' Books. Vocabulary lists are given at the end of the Teacher's Books. (AMM)
Keywords: Audiolingual Methods; Elementary Education; FLES; Illustrations; Instructional Materials; Language Instruction; Secondary Education; Swahili

Toward a theory of street level bureaucracy - Lipsky, Michael (Annual Meeting of the American Political Science Association, Commodore Hotel, New York, New York, September 2-6, 1969, 1969)

Report of a Conference of African Educators, EDC and CREDO on Social Studies (Mombasa, Kenya, August 19-30, 1968). - Center for Curriculum Renewal and Educational Development Overseas, London (England). (Report of a Conference of African Educators, EDC and CREDO on Social Studies (Mombasa, Kenya, August 19-30, 1968)., 1968)
The conference aims for primary school social studies teaching are: 1) to create an awareness and an understanding of the evolving social and physical environment as a whole, together with the rational use and conservation of these resources for development; 2) to develop a capacity to learn and to acquire basic skills together with the skills of observation, analysis, inference, and critical thinking; 3) to insure the acquisition of relevant knowledge essential for personal and value development; and, 4) to develop an appreciation of the diversity and interdependence of all members of the local international community. The main functions of the school are to promote the acceptance of change and to foster the notion of individual control over the environment. The specific aspects of change are: national integration, problems of rapid economic development, and the promotion of self-confidence and initiative. In this integrated interdisciplinary approach to learning, the teacher's role is to provide experiences which will provoke questions, to provide media, and to assist the inquiry process, centering around learning techniques rather than subject knowledge. Other methodology includes: inservice and preservice teacher education, multimedia instruction, cognitive and affective testing and evaluation, and conference followup. (SBE)
Keywords: Citizenship; Community Study; Critical Thinking; Cultural Awareness; Curriculum Design; Educational Objectives; Elementary Education; Environmental Education; Inquiry; Integrated Curriculum; Interdisciplinary Approach; International Education; Multimedia Instruction; Self Concept; Social Change; Social Development; Social Studies; Social Values; Socialization

Bilingualism in the Educational System of Kenya. - Gorman, T. P. (Bilingualism in the Educational System of Kenya., 1968)
The article discusses the history and evolution of bilingualism in education in Kenya. Apparently, the Kiunguja dialect of Swahili is used extensively, usually as a contact language between members of different language groups. But at the same time, usage of the English language has also increased and has become the primary language of Central Government, of the law, of banking and of industry and commerce. With the use of the vernacular languages and Swahili and English provided evidence on the stability of the bilingual situation in Kenya.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Bilingual education; Bilingualism; Dialects; Education; Educational Support Services; English language; History of Kenya; Kenya; Language & languages; Language contact; Native language

ADULT EDUCATION IN AFRICA. CURRENT INFORMATION SOURCES, NUMBER 12. - Syracuse Univ., NY. ERIC Clearinghouse on Adult Education. (ADULT EDUCATION IN AFRICA. CURRENT INFORMATION SOURCES, NUMBER 12., 1968)
TWENTY-THREE ABSTRACTS AND ANNOTATIONS OF RECENT (1962-67) PUBLICATIONS ON ADULT EDUCATION IN AFRICA ARE PROVIDED IN THIS BIBLIOGRAPHY. EDUCATIONAL NEEDS AND POLICIES AND SPECIFIC NATIONAL AND INSTITUTIONAL PROGRAMS IN ETHIOPIA, TANZANIA, KENYA, MALAWI, ZAMBIA, RHODESIA, AND NIGERIA ARE FEATURED, WITH COMMUNITY AND RURAL DEVELOPMENT, MANPOWER NEEDS, LITERACY WORK, LEADERSHIP TRAINING, UNIVERSITY EXTENSION, CURRICULUM AND PROGRAM PLANNING, THE EDUCATION OF TEACHERS AND EXTENSION AGENTS, AND USES OF CORRESPONDENCE STUDY AND THE BROADCAST MEDIA CONSTITUTING THE MAJOR TOPICS AND AREAS OF CONCERN. THE DOCUMENT ALSO LISTS ERIC CLEARINGHOUSE ON ADULT EDUCATION PUBLICATIONS AND NATIONAL ADVISORY BOARD MEMBERS. (LY)
Keywords: Adult Education; Africa; Annotated Bibliographies; Community Development; Correspondence Study; Developing Nations; Educational Radio; Educational Television; Extension Agents; Labor Force Development; Leadership Training; Literacy Education; National Programs; Program Development; Rural Development; Teacher Education; Universities

Continuing Literacy. - Clarke, Ronald F. (Continuing Literacy., 1968)
The aim of this conference was to stimulate joint action among organizations involved with adult education in east and central Africa, as well as publishers, journalists, librarians and book distributors; it focused on the problems of keeping people reading and improving their ability to read in any language. Opening addresses covered reading skills, problems of getting books to the people, and problems in cooperation. Participant papers discussed literacy work in the Sudan, Ethiopia, Uganda, Ghana, Kenya, and Zambia; books, bookselling, and journalism; the East African Literature Bureau Mobile Distribution Scheme; and readability and reading habits. Since links have been made with west and north Africa, as well as east and central Africa, it was decided to change the name of the association to the African Adult Education Association; the constitution is included. (PT)
Keywords: Adult Education; Adult Literacy; Africa; Bookmobiles; Conference Reports; Developing Nations; Followup Studies; Journalism; Library Services; Professional Associations; Publishing Industry; Reading Materials; Reading Skills; Regional Cooperation; Retention (Psychology); Teaching Methods

Language Usage Questionnaire, Ethiopian Schoolchildren. Draft. - Ferguson, Charles A.; Survey of Language Use and Language Teaching in Eastern Africa, Nairobi (Kenya). (Language Usage Questionnaire, Ethiopian Schoolchildren. Draft., 1968)
The questionnaire presented here was designed to be administered to a representative sample of Ethiopian children enrolled in primary and secondary schools. Responses to be elicited pertain to --(1) personal use of language in several domains of speech behavior, (2) use of language by others in situations which the respondent has had an opportunity to observe, and (3) personal history. See related document AL 001 282. (AMM)
Keywords: Diglossia; Elementary School Students; Ethiopia; Language Research; Language Role; Language Usage; Multilingualism; National Surveys; Questionnaires; Secondary School Students

FUNCTIONAL LITERACY AND INTERNATIONAL DEVELOPMENT, A STUDY OF CANADIAN CAPABILITY TO ASSIST WITH THE WORLD CAMPAIGN TO ERADICATE ILLITERACY. - KIDD, J. ROBY; Ontario Inst. for Studies in Education, Toronto. (FUNCTIONAL LITERACY AND INTERNATIONAL DEVELOPMENT, A STUDY OF CANADIAN CAPABILITY TO ASSIST WITH THE WORLD CAMPAIGN TO ERADICATE ILLITERACY., 1967)
A STUDY WAS MADE OF THE FEASIBILITY OF CANADIAN ASSISTANCE IN DEVELOPING NATIONS IN THE WORLD LITERACY CAMPAIGN. NEEDS FOR SPECIALIZED PERSONNEL, MASS MEDIA SERVICES, LITERATURE BUREAUS AND LIBRARIES, INSTRUCTIONAL MATERIALS AND SUPPLIES, AUDIOVISUAL AND OTHER EQUIPMENT, AND PROVISION FOR TEACHER EDUCATION, WOMEN'S EDUCATION, AND RESEARCH AND DEVELOPMENT WERE IDENTIFIED. RELEVANT CANADIAN PROGRAMS OF OVERSEAS AID BY BOTH GOVERNMENTAL AND NONGOVERNMENTAL BODIES (INCLUDING UNIVERSITIES) WERE DESCRIBED. IT WAS FELT THAT THE NATIONAL PROGRAM OF ACTION SHOULD INCLUDE UNIVERSAL BASIC EDUCATION IN CANADA, INFORMATION TO CANADIANS ON LITERACY AND THE WORLD LITERACY CAMPAIGN, COMPREHENSIVE PARTICIPATION, CANADIAN INITIATIVE IN PROGRAM PLANNING, ASSISTANCE PROJECTS IN DESIGNATED NATIONS, SPECIALLY TRAINED OVERSEAS PERSONNEL, AMPLE SUPPLIES AND SPECIALIZED SERVICES, AND RESTRAINT IN BUDGETING AND IN ADMINISTRATIVE ORGANIZATION. (ALSO INCLUDED ARE 64 REFERENCES, EXAMPLES OF PROGRAMS AND NEEDS IN KENYA AND INDIA, PROFESSIONAL COURSES IN ADULT EDUCATION IN CANADIAN UNIVERSITIES, AND INFORMATION SOURCES.) (LY)
Keywords: Audiovisual Aids; Canada; Consultants; Cooperative Planning; Developing Nations; Educational Needs; Feasibility Studies; Federal Government; Financial Policy; Foreign Countries; Functional Literacy; India; Instructional Materials; Kenya; Library Services; Literacy Education; Mass Media; National Programs; Private Agencies; Program Administration; Program Development; Publicize; Research Needs; Statistical Data; Teacher Education; Technical Assistance; Universities

THE TEACHING PROFESSION AND THE WORLD-WIDE LITERACY PROGRAMME, A HANDBOOK FOR LEADERS OF WCOTP AFFILIATED ORGANIZATIONS. - World Confederation of Organizations of the Teaching Profession, Morges (Switzerland). (THE TEACHING PROFESSION AND THE WORLD-WIDE LITERACY PROGRAMME, A HANDBOOK FOR LEADERS OF WCOTP AFFILIATED ORGANIZATIONS., 1967)
A LITERACY HANDBOOK PREPARED BY THE WORLD CONFEDERATION OF ORGANIZATIONS OF THE TEACHING PROFESSION INDICATES THE WAYS IN WHICH TEACHERS' ASSOCIATIONS, TRADITIONALLY CHILD-CENTERED, CAN EFFECTIVELY ENGAGE IN ADULT EDUCATION. A 1966 CASE STUDY ON THE PHILIPPINE PUBLIC SCHOOL TEACHERS' ASSOCIATION, AND WCOTP SURVEYS CONDUCTED DURING 1965 IN KENYA AND THAILAND, SUGGEST THE EXTENT TO WHICH THE PUBLIC SCHOOL SYSTEMS OF DEVELOPING NATIONS CAN AND SHOULD PARTICIPATE IN PLANNING AND COORDINATING LITERACY CAMPAIGNS AND IN PROVIDING SUITABLE FACILITIES AND INSTRUCTION. TEACHERS' ORGANIZATIONS CAN GRANT LEAVES OF ABSENCE FOR TRAINING AND SUPPORT FOLLOWUP READING DEVELOPMENT ACTIVITIES FOR NEW LITERATES. UNIVERSITIES CAN SERVE IN SUCH AREAS AS CURRICULUM AND PROGRAM PLANNING, LEADERSHIP TRAINING, BASIC AND APPLIED RESEARCH, COORDINATION AND LIAISON, AND INFORMATION DISSEMINATION. TRAINING CURRICULUMS WOULD STRESS ADULT CHARACTERISTICS AND MOTIVATION, INSTRUCTIONAL METHODS FOR WORKING EITHER WITH THE STUDENT'S MOTHER TONGUE OR WITH A GIVEN COLONIAL (EUROPEAN) LANGUAGE, AND AUDIOVISUAL TECHNIQUES. FINALLY, TEACHERS' ORGANIZATIONS SHOULD ENLIST MORE NONPROFESSIONAL VOLUNTEER LITERACY WORKERS AND WORK MORE CLOSELY WITH VOLUNTARY ORGANIZATIONS. (LY)
Keywords: Adult Basic Education; Adult Literacy; Adults; Case Studies; Developing Nations; Educational Planning; Facilities; Illiteracy; Individual Characteristics; Instructional Materials; Leadership Training; Literacy Education; National Programs; Philippines; Professional Associations; School Involvement; Teacher Education; Teacher Role; Teaching Methods; Universities; Voluntary Agencies; Volunteers

Adult Education for Developing Countries. - Prosser, Roy (Adult Education for Developing Countries., 1967)
In developing countries the need for providing opportunities for all forms of adult learning is a first priority, since all basic development must be associated with learning. At present, most emphasis is placed on subject matter--ideas, information, skills, and techniques. It is often not realized that as far as education is concerned, the way knowledge is arranged and delivered is as important as the knowledge itself. The three sections of this book cover the relationship between adult education and national development, problems of organization and administration, and methods and means experience has shown can be used to realize specific objectives and bring them to a satisfactory conclusion. (A list of readings is included.) (se)
Keywords: Administrative Organization; Adult Education; Adult Educators; Audiovisual Aids; Correspondence Study; Developing Nations; Educational Radio; Educational Television; Libraries; Literacy Education; National Programs; Professional Education; Program Content; Residential Programs; Teaching Methods

CORRESPONDENCE INSTRUCTION IN ETHIOPIA, KENYA, TANZANIA, MALAWI, ZAMBIA, AND UGANDA--EXPERIENCES, NEEDS, AND INTEREST. - EDSTROEM, LARS-OLOF; Dag Hammarskjold Foundation, Stockholm (Sweden). (CORRESPONDENCE INSTRUCTION IN ETHIOPIA, KENYA, TANZANIA, MALAWI, ZAMBIA, AND UGANDA--EXPERIENCES, NEEDS, AND INTEREST., 1966)
THIS REPORT ON THE SALIENT FEATURES AND CONCERNS OF CORRESPONDENCE INSTRUCTION IN ETHIOPIA, KENYA, TANZANIA, MALAWI, ZAMBIA, AND UGANDA--(1) DISCUSSES ADVANTAGES, DISADVANTAGES, AND REQUIREMENTS OF THE CORRESPONDENCE METHOD IN AN AFRICAN CONTEXT, (2) SURVEYS CONDITIONS AND FACILITIES (POSTAL SERVICES, ROADS, INSTRUCTIONAL RADIO AND TELEVISION, CORRESPONDENCE SCHOOLS AND COLLEGES, AND RESOURCES FOR PRODUCING INSTRUCTIONAL MATERIALS), (3) SUGGESTS NATIONAL TASKS FOR CORRESPONDENCE TEACHING, AND (4) ASSESSES INTEREST IN A PROPOSED 1967 CORRESPONDENCE INSTRUCTION SEMINAR. TEACHER TRAINING AND UPGRADING, PREPARATION OF CORRESPONDENCE EDUCATORS, MASS EDUCATION OF UNEMPLOYED PRIMARY SCHOOL DROPOUTS, INSERVICE MEDICAL TRAINING (FOR EXAMPLE, FOR THE ETHIO-SWEDISH PEDIATRIC CLINIC), IMPROVEMENT OF TEACHING METHODS BY COMBINING CORRESPONDENCE COURSES WITH CLASSROOM SETTINGS, AND INCULCATION OF STUDY SKILLS AND HABITS FOR LIFELONG LEARNING, ARE DISCUSSED AS A PART OF THE URGENT MANPOWER TRAINING NEEDS THROUGHOUT AFRICA. PROBLEMS AND ISSUES SUCH AS LANGUAGE (AS IN ETHIOPIA AND MALAWI) AND GOVERNMENTAL VERSUS PRIVATE COURSES, MAJOR ORGANIZATIONS SUCH AS THE CORRESPONDENCE COURSE UNIT (ZAMBIA MINISTRY OF EDUCATION), OUTSTANDING EFFORTS SUCH AS THE MALAWI CORRESPONDENCE COLLEGE RADIO CLASSROOM, AND RECOMMENDATIONS ON PARTICIPATION IN THE SEMINAR, ARE STRESSED. APPENDIXES ON OPERATING EXPENSES AND PROGRAM PLANNING ARE INCLUDED. (LY)
Keywords: Administration; Adult Education; Adult Programs; Africa; Community Development; Correspondence Study; Developing Nations; Educational Needs; Ethiopia; Extension Education; Financial Support; Government Role; Instructional Materials; Kenya; Library Services; Literacy Education; Malawi; Mass Media; National Programs; Program Development; Rural Areas; Surveys; Tanzania; Teacher Education; Teacher Qualifications; Teaching Methods; Uganda; Zambia

A Study of The 'New Primary Approach' in The Schools of Kenya. - Hutasoit, Marnixius; Prator, Clifford H.; Ministry of Education, Nairobi (Kenya). (A Study of The 'New Primary Approach' in The Schools of Kenya., 1965)
This two-part study is an outgrowth of the explosive expansion in English-medium instruction which has taken place in the primary schools of Kenya since 1957. "Part I: The Prator Statement," which concentrates on the linguistic, methodological, and teacher-training aspects of the overall problem, presents first a description of the linguistic background of Kenya, the rationale underlying the use of English as a medium of instruction, and the role of Swahili and the vernaculars. Also described are the present language policy, its implementation and future, and the development of the NPA ("New Primary Approach" -- referred to formerly as the "English-Medium Scheme"). The author evaluates the "New Peak Course" and the teacher training colleges. "Part II: The Hutasoit Statement" focuses attention on the administrative and financial aspects of education in Kenya and implementation of the NPA. A few of the joint recommendations appended to the report suggest that (1) English should become the universal medium of instruction in Kenya schools, (2) Swahili should be introduced in Standard (Grade) IV and be continued as a compulsory subject, (3) primary school pupils should become literate in their vernacular, and (4) for adequate instruction in Swahili, it is necessary to prepare teaching materials and to develop teacher training facilities. (AMM)
Keywords: Advisory Committees; Bilingual Education; Educational Innovation; English (Second Language); Kenya; Language; Language Programs; Language Role; Multilingualism; Official Languages; Primary Education; Second Language Learning; Surveys; Swahili; Teacher Education; Teaching Methods

Kenya Education Commission Report - Ominde, S (Government Printer, 1964)

Overcoming tribal prejudices against educating girls in Kenya. - Matheson, Alastair (Overcoming tribal prejudices against educating girls in Kenya., 1954)
Keywords: Education; Education of indigenous peoples; Kenya; Women's education

Full Library – Evidence Library – Unlocking Data

Girls’ Attitudes Towards Science in Kenya. - Chetcuti, Deborah A.; Kioko, Beriter (International Journal of Science Education)
This study investigated girls’ attitudes towards science in Kenya. It was carried out with 120 girls from four secondary schools in the Eastern province of Kenya. These were an urban single-sex (SS) and co-educational (Co-Ed) school and a rural SS and Co-Ed school. Different schools were chosen in order to explore whether there are any differences in attitudes in SS and Co-Ed schools and in schools in rural and urban areas. The methodology included the use of both questionnaires and focus group interviews. The main aim was to gain insight into the extent and depth of students’ attitudes towards science. The findings of the study showed that the majority of Kenyan girls who participated in the study have a favourable attitude towards science. Girls in SS schools were found to have a more favourable attitude than those in Co-Ed schools, while girls in rural area schools were found to find science more relevant than those in urban schools. It emerged from this study that the attitudes of Kenyan girls are influenced by their perceptions of the relevance of science, enjoyment of studying science, perceptions of the suitability of science for a career, and their perceptions of subject difficulty.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Attitude (Psychology); Education; Education of girls; Educational Support Services; Girls; Kenya; Science education (Higher); Science student attitudes

Dialogic instruction and learning: the case of one Kiswahili classroom in Kenya. - Lisanza, Esther Mukewa (Language, Culture & Curriculum)
This paper reports on an ethnographic case study which was carried out in a Kenyan first-grade classroom. The classroom had 89 students with their 2 teachers who taught at different times. The classroom was very crowded and had a high paucity of literacy materials. The study was guided by sociocultural and dialogic frameworks which maintain that social and dialogic interactions have important roles to play in a child's literacy and language development. Thus, the social life of the observed classroom was central to the children's literacy and language learning. Although there were a shortage of literacy materials and space limitations in this classroom, the Kiswahili teacher's mediating role and children's agency in this classroom were paramount. Through the teacher's dialogic instruction and mediation, the children's voices were recognised and acknowledged. There were dynamic classroom interactions and dialogues which involved different practices such as storytelling, peer-guided reading, play, and classroom talk. The study concluded that meaningful instruction and dialogue are important for meaningful language learning to occur. Also, oral and written language develop simultaneously in a classroom setting. Finally, classroom contexts play a major role in language learning.
Keywords: Administration of Education Programs; All Other Miscellaneous Schools and Instruction; Bilingualism; Classroom environment; Education; Educational Support Services; Kenya; Primary education; Swahili language; Teaching methods

About the Unlocking Data Initiative - Mutsiya, Maurice; Lawson, Laté; Waziri, Nafisa

Rapport PASEC Cameroun 2004/2005: Le défi de la scolarisation universelle de qualité - Programme d'analyse des systèmes éducatifs de la Confemen (PASEC)

Sustainable Development Goal 4 | - United Nations Department of Economic and Social Affairs